Abnormal epigenetic modification of lysosome and lipid regulating genes in Alzheimer's disease. - Ruan, Tingting; Ling, Yunxiang; Wu, Can; Niu, Yanfang; Liu, Guili; Xu, Chunshuang; Lv, Zhongyue; Yuan, Yalan; Zhou, Xinkai; Wang, Qinwen; Xu, Shujun (J Alzheimers Dis, 2025)
BackgroundAbnormal lipid metabolism has been identified as a potential pathogenic mechanism of Alzheimer's disease (AD), which might be epigenetically regulated. Lysosomes are critical organelles for lipid metabolism. However, the epigenetic modifications of lysosome and lipid regulating genes remain unclear in AD patients.ObjectiveExplore the role of abnormal epigenetic modifications, especially methylation of lysosome and lipid metabolism-related genes in AD.MethodsMethylation beadchip and MALDI-TOF mass spectrometry were used to detect genome-wide DNA methylation levels and validate key gene methylation, respectively. Clinical data were collected from all participants. Associations between clinical biochemical characteristics and altered DNA methylation in AD patients were analyzed, and a risk factor model of AD was established.Results41 differentially methylated positions (DMPs) corresponding to 33 genes were identified in AD patients, with 18 hypermethylated and 23 hypomethylated positions. Significant alterations were observed in lipid regulating genes () and lysosomal transmembrane gene (). Clinical analysis revealed that TP, ALB, IB, ADA, ALP, HCY, GLU, TC, BUN, HDL-C, LDL-C, and APOA1 levels were significantly higher in AD patients, whereas A/G and DB levels were lower. hypermethylation was further verified and found to correlate with TC, HDL-C, LDL-C, APOA1, IB, and HCY. The AUC of the AD risk model, which integrated clinical lipid markers and methylation, reached 0.9519 (< 0.0001).ConclusionsAbnormal epigenetic regulation of lysosomal gene and lipid dyshomeostasis were high-risk factors in AD. Methylation modifications of lysosome and lipid regulating genes might be key processes in AD pathogenesis.

Association of Alzheimer's disease biomarkers with low premorbid intellectual functioning in a multi-ethnic community-dwelling cohort: A cross-sectional study of HABS-HD. - Abdullah, Lubnaa; Zhou, Zhengyang; Hall, James; Petersen, Melissa; Zhang, Fan; O'Bryant, Sid (J Alzheimers Dis, 2025)
Individuals with intellectual disability (ID) may have a five-fold increased risk for developing Alzheimer's disease (AD). However, studies investigating brain aging among individuals with ID without Down syndrome (DS) are lacking. To begin addressing this gap, our study utilized word reading, a widely recognized indicator of an individual's premorbid intellectual ability (pIQ), to examine the effects of ID without DS on plasma AD biomarker outcomes. To investigate the relationship between premorbid intellectual ability (pIQ) and plasma AD biomarkers in individuals with ID without DS, while considering ethnic differences in these associations. Participants from the Health & Aging Brain Study - Health Disparities (HABS-HD) were categorized into low (z ≤ -2.00) or average (z = 0.00 ± 1.00) pIQ groups based on word reading scores. Plasma biomarkers including Aβ, Aβ, Aβ, phosphorylated tau 181 (p-Tau181), neurofilament light chain (NfL), and total tau (t-tau) were assayed using Simoa technology. Individuals with low pIQ exhibited significantly higher levels of p-Tau181 ( < 0.05), NfL ( < 0.05), and t-tau ( < 0.05) compared to those with average pIQ. Stratified analysis by ethnicity revealed differential associations, with Hispanic and non-Hispanic White (NHW) participants showing distinct biomarker profiles relative to non-Hispanic Black (NHB) individuals. The findings demonstrate that low pIQ is a reliable factor associated with plasma AD biomarker outcomes. Ethnicity appears to modulate these associations, suggesting complex interactions between factors driving AD susceptibility across diverse populations. This study highlights the importance of considering both pIQ and ethnicity in neurodegenerative processes, particularly in individuals with non-DS intellectual developmental disability.

Chronic gingivitis increases the risk of early-onset Alzheimer's disease. - Mo, Dongcan; Li, Xiaoling; He, Jing; Lin, Xiaozuo; Wang, Pingkai; Zeng, Yinan; Wu, Xiaoju; Liu, LiuYu; Chi, Li; Luo, Man (J Alzheimers Dis, 2025)
BackgroundPeriodontal disease has two types of inflammatory states: gingivitis and periodontitis. While studies suggest a link between periodontal disease and Alzheimer's disease (AD), current evidence is insufficient to establish causality. This study employed Mendelian randomization (MR) and bioinformatics to investigate causal relationships between gingivitis, periodontitis, and AD types, while identifying diagnostic biomarkers through transcriptome-based bioinformatics approaches.ObjectiveThis study aims to explore the causal relationship between periodontal disease and AD using MR combined with bioinformatics analysis, investigate potential pathogenesis, and construct/validate diagnostic biomarkers.MethodsExposures and outcomes were selected from the Open whole-genome association study. Causal relationships were assessed using inverse variance-weighted (IVW), MR-Egger, and other supplementary methods. Transcriptome sequencing datasets were downloaded from Gene Expression Omnibus datasets. Key pathways and functions were identified through Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis. Protein-protein interaction and LASSO regression were used to construct and evaluate the diagnostic signature for early-onset AD (EOAD). Gene Set Enrichment Analysis was applied to analyze gene set enrichment between high and low-risk groups.ResultsIVW showed a positive correlation (OR = 1.161, 95% CI = 1.011-1.332, p = 0.035), and MR-Egger validated this result (OR = 1.296, 95% CI = 1.020-1.645, p = 0.049). These findings suggest that chronic gingivitis may increase EOAD risk. Reverse analysis results were negative. Immune activation, angiogenesis, and blood-brain barrier damage link the two diseases. The Inter-alpha-trypsin inhibitor heavy chain H5 () gene and pathway emerged in MR and bioinformatics analyses. A gene signature composed of , , and shows potential for diagnosing EOAD.ConclusionsChronic gingivitis may be associated with an increased risk of EOAD.

DNA methylation age acceleration is associated with incident cognitive impairment in the health and retirement study. - Blostein, Freida; Bakulski, Kelly M; Fu, Mingzhou; Wang, Herong; Zawistowski, Matthew; Ware, Erin B (J Alzheimers Dis, 2025)
BackgroundDNA methylation clocks have emerged as promising biomarkers for cognitive impairment and dementia. Longitudinal studies exploring the association between DNA methylation clocks and cognitive decline have been constrained by limited sample sizes and a lack of diversity.ObjectiveOur study aimed to investigate associations between DNA methylation clocks and incident cognitive impairment using a larger and US nationally-representative sample from the Health and Retirement Study.MethodsWe measured DNA methylation age acceleration in 2016 by regressing the DNA methylation clocks, including GrimAge, against chronological age. Cognitive change over time was determined by Langa-Weir cognition status from 2016 to 2018. Multivariable logistic regression evaluated the association between DNA methylation age acceleration and cognitive change, adjusting for cell-type proportions, demographic, and health factors. We also applied inverse probability weighting to address potential selection bias from varying loss-to-follow-up rates.ResultsThe analytic sample (N = 2713) was 54% female, 8.4% Black/African American, 86% White, 7.5% Hispanic, and 68 years old at baseline. During the two years of follow-up, 12% experienced cognitive change and had higher baseline GrimAge (mean = 1.2 years) acceleration compared to those maintaining normal cognition (mean = -0.8 years). A one-year increase in GrimAge acceleration was associated with 1.05 times higher adjusted and survey-weighted odds of cognitive change during follow-up (95% CI: 1.01-1.10). This association was consistent after accounting for loss-to-follow-up (OR = 1.07, 95% CI: 1.04-1.11).ConclusionsOur study offers insights into DNA methylation age acceleration associated with cognitive change over time, suggesting avenues for improved prevention, diagnosis, and treatment.

Factors associated with a healthy diet and willingness to change dietary behavior in older adults at increased risk of dementia. - Blotenberg, Iris; Zülke, Andrea E; Luppa, Melanie; Wittmann, Felix; Fankhänel, Thomas; Weise, Solveig; Döhring, Juliane; Escales, Catharina; Kosilek, Robert P; Michel, Irina; Brettschneider, Christian; Oey, Anke; et al. (J Alzheimers Dis, 2025)
BackgroundHealthy dietary patterns have been linked to reduced risks for cardiovascular diseases and dementia, making nutrition an essential part of a comprehensive approach for dementia prevention. Knowledge about factors associated with a healthy diet in people with increased dementia risk is scarce.ObjectiveTo analyze dietary habits and associated factors in older adults with increased dementia risk in Germany.MethodsWe used baseline-data of the AgeWell.de-trial (n = 1001, %= 52.2, M= 69.0, SD = 4.9). Nutrition was assessed using a composite score, comprising 11 components covered by national recommendations for a healthy diet (range = 0-11 points). Linear regressions assessed associations of sociodemographic, social, health-related and psychological factors with consumption of a healthy diet. Further, we assessed stages of change based on the transtheoretical model of behavior change.ResultsConsumption of a healthy diet was moderate (Median = 4, IQR = 2). Female sex (b = 0.64, 95% CI: 0.41, 0.88), higher levels of motivation for healthy eating (b = 0.22, 95% CI: 0.10, 0.34) and higher self-efficacy (b = 0.33, 95% CI: 0.20, 0.46) were linked to a healthy diet. Regarding the stages of behavior change, the majority were in the maintenance stage (45.2%), followed by the contemplation (21.5%) and precontemplation (21.2%) stages.ConclusionsResults suggest room for improvement regarding a healthy diet in our sample. Lifestyle-based interventions in older adults should be tailored towards current levels of motivation and self-efficacy of participants. Including modules targeting motivation and self-efficacy might help maximize intervention effectiveness.

Iron chelation by oral deferoxamine treatment decreased brain iron and iron signaling proteins. - Thorwald, Max A; Sta Maria, Naomi S; Chakhoyan, Ararat; O'Day, Peggy A; Jacobs, Russell E; Zlokovic, Berislav; Finch, Caleb E (J Alzheimers Dis, 2025)
BACKGROUND: Deferoxamine (DFO) and other iron chelators are clinically used for cancer and stroke. They may also be useful for Alzheimer's disease (AD) to diminish iron from microbleeds. DFO may also stimulate antioxidant membrane repair which is impaired during AD. DFO and other chelators do enter the brain despite some contrary reports. OBJECTIVE: Low dose, oral DFO was given in lab chow to wildtype (WT) C57BL/6 mice to evaluate potential impact on iron levels, iron-signaling and storage proteins, and amyloid-β protein precursor (AβPP) and processing enzymes. Young WT mice do not have microbleeds or disrupted blood-brain barrier of AD mice. METHODS: Iron was measured by MRI and chemically after two weeks of dietary DFO. Cerebral cortex was examined for changes in iron metabolism, antioxidant signaling, and AβPP processing by western blot. RESULTS: DFO decreased brain iron 18% ( < 0.01) estimated by R2 MRI and decreased seven major proteins that mediate iron metabolism by at least 25%. The iron storage proteins ferritin light and heavy chain decreased by at least 30%. AβPP and secretase enzymes also decreased by 30%. CONCLUSIONS: WT mice respond to DFO with decreased AβPP, amyloid processing enzymes, and antioxidant repair. Potential DFO treatment for early-stage AD by DFO should consider the benefits of lowered AβPP and secretase enzymes.

Lipopolysaccharides from indirectly induce neuronal GSK3β-dependent synaptic defects and cause cognitive decline in a low-amyloid-β-concentration environment in Alzheimer's disease. - Gui, Shuge; Zeng, Fan; Wu, Zhou; Nonaka, Saori; Sano, Tomomi; Ni, Junjun; Nakanishi, Hiroshi; Moriyama, Masafumi; Kanematsu, Takashi (J Alzheimers Dis, 2025)
BackgroundLipopolysaccharides from s (LPS) are involved in the pathology of Alzheimer's disease (AD). However, the effect of LPS on synaptic defects remains unclear.ObjectiveIn this study, we tested our hypothesis that LPS induces synaptic defects in a low-amyloid-beta (Aβ)-concentration environment.MethodsMG6 microglia or N2a neurons was treated with LPS (0.1 μg/mL), soluble Aβ (0.1 μM) or AL (combined LPS and soluble Aβ at 0.1 μM).ResultsIn cultured MG6 microglia, increased the mRNA expression of TNF-α, IL-1β and IL-6 and the TNF-α release in parallel with increased NF-κB activation. In cultured N2a neurons, treatment with Aβ, LPS, and AL did not affect the mRNA expression of synapsin1 (SYN1) or post-synaptic density protein-95 (PSD-95). However, the treatment with conditioned medium from AL-exposed MG6 microglia (AL-MCM) significantly reduced the mRNA and protein expression of SYN1, PSD-95, and nuclear translocation of repressor element-1 silencing transcription factor (REST) but significantly increased the mRNA expression of TNF receptor type I (at 48 h) and glycogen synthase kinase (GSK)3β (at 24 h). TWS119 pretreatment (5 μM), a GSK3β specific inhibitor, significantly reversed the AL-MCM-induced reduction in the mRNA expression of SYN1 and PSD-95 and nuclear translocation of REST in cultured N2a neurons. In APP mice, the immunofluorescence intensity of SYN1 and PSD-95 in cortical neurons was positively correlated with the index of the memory test but negatively correlated with that of TNF-α-positive microglia.ConclusionsThese observations demonstrate that LPS induces neuronal GSK3β-dependent synaptic defects in a low-Aβ concentration environment via microglial activation.

Semaglutide improves cognitive function and neuroinflammation in APP/PS1 transgenic mice by activating AMPK and inhibiting TLR4/NF-κB pathway. - Zhai, Yanyu; Lu, Kaili; Yuan, Yuan; Zhang, Ziyao; Xue, Lixia; Zhao, Fei; Xu, Xiaofeng; Wang, Hongmei (J Alzheimers Dis, 2025)
BackgroundAlzheimer's disease (AD) causes cognitive function disorder and has become the preeminent cause of dementia. Glucagon-like peptide-1 (GLP-1) receptor agonists, semaglutide, have shown positive effects on promoting the cognitive function. However, research about the mechanism of semaglutide as a therapeutic intervention in AD is sparse.ObjectiveThis study was to investigate the therapeutic efficacy of semaglutide in a transgenic mouse model of AD pathology and explored the detailed mechanism by semaglutide modulated neuroinflammatory processes.MethodsMale amyloid precursor protein/presenilin 1 (APP/PS1) transgenic mice were treated with semaglutide or vehicle for 8 weeks. Morris water maze test was used to assess the therapeutic efficacy of semaglutide on recognition function. Pathology analysis was performed to detect the deposition of amyloid plaques. High-throughput sequencing analysis was applied to specify the mechanism. Microglia and astrocyte activation were assessed with immunofluorescent staining. Inflammation cytokine levels were evaluated with enzyme-linked immunosorbent assay (ELISA). Related proteins and pathway were evaluated with western blot.ResultsSemaglutide treatment attenuated Aβ accumulation and enhanced cognitive function in APP/PS1 transgenic mice. Through transcriptomic profiling, immunohistochemical staining, and ELISA, semaglutide was substantiated to inhibit the overactivation of microglia and astrocytes, as well as to curtail the secretion of inflammatory mediators. Furthermore, semaglutide robustly activated AMP-activated protein kinase (AMPK) and suppressed the toll-like receptor 4 (TLR4)/nuclear factor-kappa B (NF-κB) signaling cascade, thus reducing the Aβ deposition and dampening the inflammatory cascade.ConclusionsThe results demonstrated that semaglutide mitigated neuroinflammation and decelerated the advance of AD in APP/PS1 transgenic mice.

Acute Hyperglycemia Induced by Hyperglycemic Clamp Affects Plasma Amyloid-β in Type 2 Diabetes. - Rolandsson, Olov; Tornevi, Andreas; Steneberg, Pär; Edlund, Helena; Olsson, Tommy; Andreasson, Ulf; Zetterberg, Henrik; Blennow, Kaj (J Alzheimers Dis, 2024)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of cognitive symptoms and Alzheimer's disease (AD). Mis-metabolism with aggregation of amyloid-β peptides (Aβ) play a key role in AD pathophysiology. Therefore, human studies on Aβ metabolism and T2D are warranted. OBJECTIVE: The objective of this study was to examine whether acute hyperglycemia affects plasma Aβ1-40 and Aβ1-42 concentrations in individuals with T2D and matched controls. METHODS: Ten participants with T2D and 11 controls (median age, 69 years; range, 66-72 years) underwent hyperglycemic clamp and placebo clamp (saline infusion) in a randomized order, each lasting 4 hours. Aβ1-40, Aβ1-42, and insulin-degrading enzyme (IDE) plasma concentrations were measured in blood samples taken at 0 and 4 hours of each clamp. Linear mixed-effect regression models were used to evaluate the 4-hour changes in Aβ1-40 and Aβ1-42 concentrations, adjusting for body mass index, estimated glomerular filtration rate, and 4-hour change in insulin concentration. RESULTS: At baseline, Aβ1-40 and Aβ1-42 concentrations did not differ between the two groups. During the hyperglycemic clamp, Aβ decreased in the control group, compared to the placebo clamp (Aβ1-40: p = 0.034, Aβ1-42: p = 0.020), IDE increased (p = 0.016) during the hyperglycemic clamp, whereas no significant changes in either Aβ or IDE was noted in the T2D group. CONCLUSIONS: Clamp-induced hyperglycemia was associated with increased IDE levels and enhanced Aβ40 and Aβ42 clearance in controls, but not in individuals with T2D. We hypothesize that insulin-degrading enzyme was inhibited during hyperglycemic conditions in people with T2D.
Keywords: Aged; Amyloid beta-Peptides; Blood Glucose; Diabetes Mellitus, Type 2; Female; Glucose Clamp Technique; Humans; Hyperglycemia; Insulysin; Male; Peptide Fragments

Alzheimer's Disease Immunotherapy: Current Strategies and Future Prospects. - Aljassabi, Ali; Zieneldien, Tarek; Kim, Janice; Regmi, Deepika; Cao, Chuanhai (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is an extremely complex and heterogeneous pathology influenced by many factors contributing to its onset and progression, including aging, amyloid-beta (Aβ) plaques, tau fibril accumulation, inflammation, etc. Despite promising advances in drug development, there is no cure for AD. Although there have been substantial advancements in understanding the pathogenesis of AD, there have been over 200 unsuccessful clinical trials in the past decade. In recent years, immunotherapies have been at the forefront of these efforts. Immunotherapy alludes to the immunological field that strives to identify disease treatments via the enhancement, suppression, or induction of immune responses. Interestingly, immunotherapy in AD is a relatively new approach for non-infectious disease. At present, antibody therapy (passive immunotherapy) that targets anti-Aβ aimed to prevent the fibrillization of Aβ peptides and disrupt pre-existing fibrils is a predominant AD immunotherapy due to the continuous failure of active immunotherapy for AD. The most rational and safe strategies will be those targeting the toxic molecule without triggering an abnormal immune response, offering therapeutic advantages, thus making clinical trial design more efficient. This review offers a concise overview of immunotherapeutic strategies, including active and passive immunotherapy for AD. Our review encompasses approved methods and those presently under investigation in clinical trials, while elucidating the recent challenges, complications, successes, and potential treatments. Thus, immunotherapies targeting Aβ throughout the disease progression using a mutant oligomer-Aβ stimulated dendritic cell vaccine may offer a promising therapy in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Immunization, Passive; Immunotherapy; Inflammation

Association of Plastic Exposure with Cognitive Function Among Chinese Older Adults. - Zhu, Yongbin; Wu, Yueping; Shi, Liping; Yang, Yue; Wang, Yanrong; Pan, Degong; He, Shulan; Wang, Liqun; Li, Jiangping (J Alzheimers Dis, 2024)
BACKGROUND: The widespread exposure to plastic products and the increasing number of individuals with cognitive impairments have imposed a heavy burden on society. OBJECTIVE: This study aims to investigate the relationship between plastic product exposure in daily life and cognitive function in older Chinese individuals. METHODS: Data were obtained from the 2023 Ningxia Older Psychological Health Cohort, comprising 4045 participants aged 60 and above. Cognitive function was assessed using the Mini-Mental State Examination scale. A population-based plastic exposure questionnaire was used to calculate plastic exposure scores (PES). Binary logistic regression was employed to analyze the relationship between PES and cognitive function, while restricted cubic splines were used to examine the dose-response relationship between PES and cognitive function. Latent profile analysis (LPA) was employed to explore the potential patterns of plastic exposure, and logistic regression was used to investigate the relationship between different exposure patterns and cognitive function. A linear regression model was utilized to investigate the relationship between PES and different dimensions of cognitive function. RESULTS: Among the 4045 participants, 1915 individuals were assessed with mild cognitive impairment (MCI). After adjusting for all covariates, PES (OR = 1.04, 95% CI 1.02-1.06) was significantly associated with the risk of MCI and exhibited a dose-response relationship. LPA identified two potential categories of plastic exposure, with a higher risk of MCI observed in the group using plastic utensils. CONCLUSIONS: This study indicates a positive correlation between plastic exposure levels and MCI risk, particularly among individuals who frequently use plastic tableware.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognitive Dysfunction; Cohort Studies; East Asian People; Environmental Exposure; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Plastics; Surveys and Questionnaires

Association of Statin Use with Dementia Risk Among Older Adults in Japan: A Nested Case-Control Study Using the LIFE Study. - Ge, Sanyu; Kitamura, Tetsuhisa; Zha, Ling; Komatsu, Masayo; Komukai, Sho; Murata, Fumiko; Maeda, Megumi; Gon, Yasufumi; Kimura, Yasuyoshi; Kiyohara, Kosuke; Sobue, Tomotaka; Fukuda, Haruhisa (J Alzheimers Dis, 2024)
BACKGROUND: Previous studies have shown a possible association between statin use and a decreased risk of dementia, but the association has not been sufficiently established, especially in the super-aging society of Japan. OBJECTIVE: This study aimed to determine the association between statin use and the risk of dementia among Japanese participants aged> =65 years old. METHODS: Data from the Longevity Improvement and Fair Evidence (LIFE) Study were utilized, including medical and long-term care (LTC) claim data from 17 municipalities between April 2014 and December 2020. A nested case-control study was conducted with one case matched to five controls based on age, sex, municipality, and year of cohort entry. We used a conditional logistic regression model to calculate the odds ratios (ORs) and 95% confidence intervals (95% CIs). RESULTS: This study included 57,302 cases and 283,525 controls, with 59.7% of the participants being woman. After adjusting for potential confounders, statin use was associated with a lower risk of dementia (OR, 0.70; 95% CI: 0.68-0.73) and Alzheimer's disease (OR: 0.66; 95% CI: 0.63-0.69). Compared with non-users, the ORs of dementia were as follows: 1.42 (1.34-1.50) for 1-30 total standardized daily dose (TSDD), 0.91 (0.85-0.98) for 31-90 TSDD, 0.63 (0.58-0.69) for 91-180 TSDD, and 0.33 (0.31-0.36) for >180 TSDD in dose-analysis. CONCLUSIONS: Statin use is associated with a reduced risk of dementia and Alzheimer's disease among older Japanese adults. A low cumulative statin dose is associated with an increased risk of dementia, whereas a high cumulative statin dose is a protective factor against dementia.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Dementia; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Japan; Male; Risk Factors

Association of Vitamin D Levels with Risk of Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis of Prospective Studies. - Zhang, Xiao-Xue; Wang, He-Ran; Hu, Ya-Zhuo; Sun, Hong-Mei; Feng, Yu-Xin; Jia, Jian-Jun (J Alzheimers Dis, 2024)
BACKGROUND: Emerging evidence suggests the potential relationship between vitamin D deficiency and risk of cognitive impairment or dementia. To what extent the excess risk of dementia conferred by vitamin D deficiency is less clear. OBJECTIVE: We summarized the current evidence from several aspects and further quantified these associations. METHODS: We collected relevant prospective cohort studies by searching PubMed, Embase and Cochrane up to July 2023. The pooled relative risks (RR) were evaluated by random-effects models. Dose-response analyses were conducted by the method of two-stage generalized least squares regression. RESULTS: Of 9,267 identified literatures, 23 were eligible for inclusion in the meta-analyses, among which 9 and 4 literatures were included in the dose-response analyses for the risk of dementia and Alzheimer's disease (AD). Vitamin D deficiency exhibited a 1.42 times risk for dementia (95% confidence interval (CI) = 1.21-1.65) and a 1.57-fold excess risk for AD (95% CI = 1.15-2.14). And vitamin D deficiency was associated with 34% elevated risk with cognitive impairment (95% CI = 1.19-1.52). Additionally, vitamin D was non-linearly related to the risk of dementia (pnonlinearity = 0.0000) and AD (pnonlinearity = 0.0042). The approximate 77.5-100 nmol/L 25-hydroxyvitamin D [25(OH)D] was optimal for reducing dementia risk. And the AD risk seemed to be decreased when the 25(OH)D level >40.1 nmol/L. CONCLUSIONS: Vitamin D deficiency was a risk factor for dementia, AD, and cognitive impairment. The nonlinear relationships may further provide the optimum dose of 25(OH)D for dementia prevention.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Dementia; Humans; Prospective Studies; Risk Factors; Vitamin D; Vitamin D Deficiency

The Associations of Phosphorylated Tau 181 and Tau 231 Levels in Plasma and Cerebrospinal Fluid with Cognitive Function in Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Li, Zhirui; Fan, Zixuan; Zhang, Qian (J Alzheimers Dis, 2024)
BACKGROUND: Cerebrospinal fluid (CSF) or blood biomarkers like phosphorylated tau proteins (p-tau) are used to detect Alzheimer's disease (AD) early. Increasing studies on cognitive function and blood or CSF p-tau levels are controversial. OBJECTIVE: Our study examined the potential of p-tau as a biomarker of cognitive status in normal control (NC), mild cognitive impairment (MCI), and AD patients. METHODS: We searched PubMed, Cochrane, Embase, and Web of Science for relevant material through 12 January 2023. 5,017 participants from 20 studies-1,033 AD, 2,077 MCI, and 1,907 NC-were evaluated. Quantitative analysis provided continuous outcomes as SMDs with 95% CIs. Begg tested publication bias. RESULTS: MCI patients had lower CSF p-tau181 levels than AD patients (SMD =-0.60, 95% CI (-0.85, -0.36)) but higher than healthy controls (SMD = 0.67). AD/MCI patients had greater plasma p-tau181 levels than healthy people (SMD =-0.73, 95% CI (-1.04, -0.43)). MCI patients had significantly lower p-tau231 levels than AD patients in plasma and CSF (SMD =-0.90, 95% CI (-0.82, -0.45)). MCI patients showed greater CSF and plasma p-tau231 than healthy controls (SMD = 1.34, 95% CI (0.89, 1.79) and 0.43, (0.23, 0.64)). Plasma p-tau181/231 levels also distinguished the three categories. MCI patients had higher levels than healthy people, while AD patients had higher levels than MCI patients. CONCLUSIONS: CSF p-tau181 and p-tau231 biomarkers distinguished AD, MCI, and healthy populations. Plasma-based p-tau181 and p-tau231 biomarkers for AD and MCI need further study.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition; Cognitive Dysfunction; Humans; tau Proteins

Bisecting N-Acetylglucosamine Correlates with Phospho-Tau181 in Subjective Cognitive Decline but not in Control Cases. - Egebäck Arulf, Sofia; Ziyue Zhou, Robin; Kirsebom, Bjørn-Eivind; Jejcic, Alenka; Fladby, Tormod; Winblad, Bengt; Tjernberg, Lars; Schedin-Weiss, Sophia (J Alzheimers Dis, 2024)
BACKGROUND: The N-glycan structure bisecting N-acetylglucosamine (bisecting GlcNAc) is present on several N-glycans that are elevated in Alzheimer's disease (AD), and previous studies have shown that bisecting GlcNAc levels correlate with total tau and phospho-tau181 in cerebrospinal fluid at early stages of AD. A recent population-based study showed that bisecting GlcNAc correlates with total tau also in blood and that this correlation could predict conversion to dementia. OBJECTIVE: In this study, we have further investigated how bisecting GlcNAc relates to total tau and phospho-tau 181 in cerebrospinal fluid samples from controls and cases with early cognitive deficits, stratified by amyloid/tau status and gender. METHODS: Relative levels of bisecting GlcNAc in cerebrospinal fluid were measured by an enzyme-linked lectin assay in individuals with subjective cognitive decline, mild cognitive impairment and controls from the Norwegian Dementia Disease Initiation cohort. RESULTS: As in our previous study, the correlation between bisecting GlcNAc and total tau or phospho-tau181 was particularly strong in the subjective cognitive decline group. The correlation was observed in amyloid negative and tau negative as well as amyloid positive and tau positive individuals, both in females and in males. Interestingly, among the amyloid negative and tau negative individuals, the correlation was observed in individuals with subjective cognitive decline but not in the controls. CONCLUSIONS: Thus, bisecting GlcNAc could be a biomarker for early cognitive decline.

Blood-Based mtDNA Quantification Indicates Population-Specific Differences Associated with Alzheimer's Disease-Related Risk. - Gorham, Isabelle K; Reid, Danielle Marie; Sun, Jie; Zhou, Zhengyang; Barber, Robert C; Phillips, Nicole R (J Alzheimers Dis, 2024)
BACKGROUND: Age is known to be the biggest risk factor for Alzheimer's disease (AD), and Mexican Americans (MAs), who are one of the fastest-aging populations in the United States, are at a uniquely elevated risk. Mitochondrial stress and dysfunction are key players in the progression of AD and are also known to be impacted by lifestyle and environmental exposures/stressors. OBJECTIVE: This study aimed to identify population-specific differences in indicators of mitochondrial stress and dysfunction associated with AD risk that are detectable in the blood. METHODS: Examining blood from both non-Hispanic white (NHW) and MA participants (N = 527, MA n = 284, NHW n = 243), mitochondrial DNA (mtDNA) and nuclear DNA (nDNA) copy numbers were assessed through quantitative PCR. Data was stratified by population and sample type, and multiple linear regression analyses were performed to identify factors that may influence this phenotype of mitochondrial dysfunction. RESULTS: In the MA cohort, there was a significant relationship between cellular mtDNA:nDNA ratio and body mass index, CDR sum of boxes score, the APOEɛ2/ɛ3 genotype, and education. Further, there was a significant relationship between cell-free mtDNA copy number and both education and CDR sum score. In the NHW cohort, there was a significant relationship between cellular mtDNA:nDNA ratio and both age and CDR sum score. Age was associated with cell-free mtDNA in the NHW cohort. CONCLUSIONS: This evidence supports the existence of population-based differences in the factors that are predictive of this blood-based phenotype of mitochondrial dysfunction, which may be indicative of cognitive decline and AD risk.

Causal Association Between Sepsis and Neurodegenerative Diseases: A Bidirectional Two-Sample Mendelian Randomization Study. - Zeng, Youjie; Cao, Si; Pang, Ke; Tang, Juan; Lin, Guoxin (J Alzheimers Dis, 2024)
BACKGROUND: Previous observational studies suggested an association between sepsis and neurodegenerative diseases, but causality remains unclear. OBJECTIVE: Determining the causal association between sepsis and four neurodegenerative diseases (Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, and Lewy body dementia) through bidirectional two-sample Mendelian randomization (MR) analysis. METHODS: Genome-wide association study summary statistics for all traits were obtained from publicly available databases. Inverse variance weighted (IVW) was the primary method for evaluating causal associations. In addition, three additional MR methods (MR-Egger, weighted median, and maximum likelihood method) were employed to supplement IVW. Furthermore, various sensitivity tests were conducted to assess the reliability: 1) Cochrane's Q test for assessing heterogeneity; 2) MR-Egger intercept test and MR-PRESSO global test for evaluating horizontal pleiotropy; 3) leave-one-out sensitivity test for determining the stability. RESULTS: The results of IVW indicated that sepsis significantly increased the risk of Alzheimer's disease (OR = 1.11, 95% CI: 1.01-1.21, p = 0.025). In addition, three additional MR methods suggested parallel results. However, no causal effect of sepsis on the three other neurodegenerative diseases was identified. Subsequently, reverse MR analysis indicated that the four neurodegenerative diseases do not causally affect sepsis. Furthermore, sensitivity tests demonstrated the reliability of the MR analyses, suggesting no heterogeneity or horizontal pleiotropy. CONCLUSIONS: The present study contributes to a deeper comprehension of the intricate interplay between sepsis and neurodegenerative disorders, thereby offering potential avenues for the development of therapeutic agents that can effectively mitigate the multifarious complications associated with sepsis.
Keywords: Alzheimer Disease; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Neurodegenerative Diseases; Reproducibility of Results; Sepsis

Characterizing Gut Microbiota in Older Chinese Adults with Cognitive Impairment: A Cross-Sectional Study. - Wang, Jing; Zhang, Gong; Lai, Hao; Li, Zengbin; Shen, Mingwang; Li, Chao; Kwan, Patrick; O'Brien, Terence J; Wu, Ting; Yang, Siyu; Zhang, Xueli; Zhang, Lei (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive impairment is a clinical manifestation that occurs in the course of dementia like Alzheimer's disease. The association between cognitive impairment and gut microbiota is unclear. OBJECTIVE: We aimed to identify gut microbiota characteristics and key gut microbiota biomarkers associated with cognitive impairment in a relatively large cohort of older adults in China. METHODS: A total of 229 adults aged ≥60 years from Shenzhen, China were recruited into this cross-sectional study. Participants were divided into cognitive impairment (CI) and no cognitive impairment (NCI) groups according to the results of the Mini-Mental State Examination. Diversity analysis and network analysis were used to characterize the gut microbiota between the two groups. The linear discriminant analysis effect size method and machine learning approaches were sequentially performed to identify gut microbiota biomarkers. The relationship between biomarkers and lifestyle factors was explored using Transformation-based redundancy analysis (tb-RDA). RESULTS: A total of 74 CI participants and 131 NCI participants were included in the analysis. The CI group demonstrated lower α-diversity compared to the NCI group (Shannon: 2.798 versus 3.152, p < 0.001). The density of the gut microbiota interaction network was lower in the CI group (0.074) compared to the NCI group (0.081). Megamonas, Blautia, Pseudomonas, Stenotrophomonas, and Veillonella were key biomarkers for CI. The tb-RDA revealed that increased fruit intake and exercise contribute to a higher abundance of Megamonas, Blautia, and Veillonella. CONCLUSIONS: We identified a significantly reduced abundance of certain beneficial gut microbiota in older Chinese adults with cognitive impairment.
Keywords: Aged; Aged, 80 and over; Biomarkers; China; Cognitive Dysfunction; Cross-Sectional Studies; East Asian People; Female; Gastrointestinal Microbiome; Humans; Machine Learning; Male; Middle Aged

Creating an Unprotected Class: Addressing Legal Risks in the Era of Biologically-Defined Alzheimer's Disease. - Vaishnav, Neil; Gonzalez, Rosa; Karunungan, Krystal; Tyler, Ana; Zheng, William; Arias, Jalayne J (J Alzheimers Dis, 2024)
BACKGROUND: Documentation of preclinical biomarker tests for Alzheimer's disease (AD) in the medical record may expose patients to employment and insurance discrimination risks. There is a gap in research describing clinicians' approaches to documenting biomarker results. OBJECTIVE: To evaluate discrimination risks faced by patients undergoing biomarker testing for AD through a qualitative analysis of clinician documentation practices. METHODS: Semi-structured interviews using hypothetical patient scenarios. The qualitative analysis focused on interviewees' responses related to documentation and disclosure of results. RESULTS: We collected and analyzed 17 interviews with dementia experts; and identified three approaches to documenting biomarkers as: an association with active AD, noninformative, and an increased susceptibility for AD. Those who associated biomarkers with active disease were more likely to favor disclosure to employers and insurers, which could increase discrimination risks. CONCLUSIONS: This study demonstrates the variety of documentation and disclosure practices likely to emerge for preclinical AD biomarker tests and highlights a need for guidelines in this area.
Keywords: Alzheimer Disease; Biomarkers; Disclosure; Humans

Enhancing Rab7 Activity by Inhibiting TBC1D5 Expression Improves Mitophagy in Alzheimer's Disease Models. - Liang, Xiao; Wang, Yangyang; Li, Siyu; Fan, Jianing; Zhou, Fanlin; Li, Xiaoju; Li, Shijie; Li, Yu (J Alzheimers Dis, 2024)
BACKGROUND: Mitochondrial dysfunction exists in Alzheimer's disease (AD) brain, and damaged mitochondria need to be removed by mitophagy. Small GTPase Rab7 regulates the fusion of mitochondria and lysosome, while TBC1D5 inhibits Rab7 activation. However, it is not clear whether the regulation of Rab7 activity by TBC1D5 can improve mitophagy and inhibit AD progression. OBJECTIVE: To investigate the role of TBC1D5 in mitophagy and its regulatory mechanism for Rab7, and whether activation of mitophagy can inhibit the progression of AD. METHODS: Mitophagy was determined by western blot and immunofluorescence. The morphology and quantity of mitochondria were tracked by TEM. pCMV-Mito-AT1.03 was employed to detect the cellular ATP. Amyloid-β secreted by AD cells was detected by ELISA. Co-immunoprecipitation was used to investigate the binding partner of the target protein. Golgi-cox staining was applied to observe neuronal morphology of mice. The Morris water maze test and Y-maze were performed to assess spatial learning and memory, and the open field test was measured to evaluate motor function and anxiety-like phenotype of experimental animals. RESULTS: Mitochondrial morphology was impaired in AD models, and TBC1D5 was highly expressed. Knocking down TBC1D5 increased the expression of active Rab7, promoted the fusion of lysosome and autophagosome, thus improving mitophagy, and improved the morphology of hippocampal neurons and the impaired behavior in AD mice. CONCLUSIONS: Knocking down TBC1D5 increased Rab7 activity and promoted the fusion of autophagosome and lysosome. Our study provided insights into the mechanisms that bring new possibilities for AD therapy targeting mitophagy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; GTPase-Activating Proteins; Humans; Male; Mice; Mice, Transgenic; Mitochondria; Mitophagy; Neurons; rab GTP-Binding Proteins; rab7 GTP-Binding Proteins

Equilibrium of Dietary Patterns Between Alzheimer's Disease Patients and Healthy People: A Comprehensive Analysis Using Multiple Factor Analysis and Classification Modeling. - Ahmed, Tahera; Zhang, Ping; Kumar, Kuldeep (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a particular type of dementia that currently lacks a definitive treatment and cure. It is possible to reduce the risk of developing AD and mitigate its severity through modifications to one's lifestyle, regular diet, and alcohol-drinking habits. OBJECTIVE: The objective of this study is to examine the daily dietary patterns of individuals with AD compared to healthy controls, with a focus on nutritional balance and its impact on AD. METHODS: This study incorporated multiple-factor analysis (MFA) to evaluate dietary patterns and employed Random Forest (RF) classifier and Sparse Logistic Regression (SLR) for Variable Importance analysis to identify food items significantly associated with AD. RESULTS: MFA revealed trends in the data and a strong correlation (Lg = 0.92, RV = 0.65) between the daily consumption of processed food and meat items in AD patients. In contrast, no significant relationship was found for any daily consumed food categories within the healthy control (HC) group. Food items such as meat pie, hamburger, ham, sausages, beef, capsicum, and cabbage were identified as important variables associated with AD in RF and SLR analyses. CONCLUSIONS: The findings from MFA indicated that the diversity or equilibrium of daily diet might play a potential role in AD development. RF and SLR classifications exhibit among the processed foods, especially deli meats and food made with meat items, are associated with AD.
Keywords: Alzheimer Disease; Diet; Factor Analysis, Statistical; Humans; Vegetables

The Etiology of Rapidly Progressive Dementia: A 3-Year Retrospective Study in a Tertiary Hospital in China. - Shi, Qin; Liu, Wei-Shi; Liu, Fang; Zeng, Yi-Xuan; Chen, Shu-Fen; Chen, Ke-Liang; Yu, Jin-Tai; Huang, Yu-Yuan (J Alzheimers Dis, 2024)
BACKGROUND: Rapidly progressive dementia (RPD), characterized by a rapid cognitive decline leading to dementia, comprises a diverse range of disorders. Despite advancements in diagnosis and treatment, research on RPD primarily focuses on Western populations. OBJECTIVE: This study aims to explore the etiology and demographics of RPD in Chinese patients. METHODS: We retrospectively analyzed 323 RPD inpatients at Huashan Hospital from May 2019 to March 2023. Data on sociodemographic factors, epidemiology, clinical presentation, and etiology were collected and analyzed. RESULTS: The median onset age of RPD patients was 60.7 years. Two-thirds received a diagnosis within 6 months of symptom onset. Memory impairment was the most common initial symptom, followed by behavioral changes. Neurodegenerative diseases accounted for 47.4% of cases, with central nervous system inflammatory diseases at 30.96%. Autoimmune encephalitis was the leading cause (16.7%), followed by Alzheimer's disease (16.1%), neurosyphilis (11.8%), and Creutzfeldt-Jakob disease (9.0%). Alzheimer's disease, Creutzfeldt-Jakob disease, and frontotemporal dementia were the primary neurodegenerative causes, while autoimmune encephalitis, neurosyphilis, and vascular cognitive impairment were the main non-neurodegenerative causes. CONCLUSIONS: The etiology of RPD in Chinese patients is complex, with neurodegenerative and non-neurodegenerative diseases equally prevalent. Recognizing treatable conditions like autoimmune encephalitis and neurosyphilis requires careful consideration and differentiation.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Creutzfeldt-Jakob Syndrome; Dementia; Disease Progression; Encephalitis; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neurodegenerative Diseases; Neurosyphilis; Retrospective Studies; Tertiary Care Centers

Influence of genotype on PCSK9-lipids association in cerebrospinal fluid and serum of patients in the Alzheimer's disease continuum. - Papotti, Bianca; Palumbo, Marcella; Adorni, Maria Pia; Elviri, Lisa; Chiari, Annalisa; Tondelli, Manuela; Bedin, Roberta; Baldelli, Enrica; Lancellotti, Giulia; Lupo, Maria Giovanna; Ferri, Nicola; Bertolotti, Marco; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alterations in factors involved in cholesterol homeostasis are critical in Alzheimer's disease (AD), but the stage of occurrence, their specific association, and a possible relationship with the genotype are not clarified. OBJECTIVE: We aimed to quantify and correlate specific lipid factors in patients with different degrees of cognitive decline, namely patients with AD and patients with mild cognitive impairment due to AD (MCI-AD), carriers or non-carriers of the genotype. METHODS: We evaluated Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9), cholesterol and the oxidative metabolites 24-, 25-, 27-hydroxycholesterol (HC) in the cerebrospinal fluid (CSF) and serum of AD (n = 28) and MCI-AD (n = 27) patients. RESULTS: CSF and serum PCSK9 and lipids were similar, except for higher serum PCSK9 and triglycerides in MCI-AD compared to AD. In CSF, AD carriers showed higher PCSK9 and 24-HC (+61.3%,  = 0.027 and +32.7%,  = 0.037), compared to non-carriers. There was a negative association between CSF PCSK9 and 27-HC in AD (r = -0.444,  = 0.049) and, exclusively among AD carriers, a negative association between CSF PCSK9 and 24-HC (r = -0.786,  = 0.028). A positive correlation was observed between CSF and serum PCSK9 in AD (r = 0.520,  = 0.004), driven by carriers (r = 0.544,  = 0.038), suggesting PCSK9 exchange between brain and periphery. A positive correlation was detected between serum and CSF 27-HC (r = 0.465,  = 0.039) in AD. None of these results were found in MCI-AD patients. CONCLUSIONS: PCSK9 and 24-HC might be specific markers of ApoE4-associated lipid alterations in AD, possibly contributing to clinical progression in the AD continuum.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cholesterol; Cognitive Dysfunction; Female; Genotype; Humans; Lipids; Male; Middle Aged; Proprotein Convertase 9

An Insertion Within SIRPβ1 Shows a Dual Effect Over Alzheimer's Disease Cognitive Decline Altering the Microglial Response. - García-Alberca, José María; de Rojas, Itziar; Sanchez-Mejias, Elisabeth; Garrido-Martín, Diego; Gonzalez-Palma, Laura; Jimenez, Sebastian; Pino-Angeles, Almudena; Cruz-Gamero, Jose Manuel; Mendoza, Silvia; Alarcón-Martín, Emilio; Muñoz-Castro, Clara; Real, Luis Miguel; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Microglial dysfunction plays a causative role in Alzheimer's disease (AD) pathogenesis. Here we focus on a germline insertion/deletion variant mapping SIRPβ1, a surface receptor that triggers amyloid-β(Aβ) phagocytosis via TYROBP. OBJECTIVE: To analyze the impact of this copy-number variant in SIRPβ1 expression and how it affects AD molecular etiology. METHODS: Copy-number variant proxy rs2209313 was evaluated in GERALD and GR@ACE longitudinal series. Hippocampal specimens of genotyped AD patients were also examined. SIRPβ1 isoform-specific phagocytosis assays were performed in HEK393T cells. RESULTS: The insertion alters the SIRPβ1 protein isoform landscape compromising its ability to bind oligomeric Aβ and its affinity for TYROBP. SIRPβ1 Dup/Dup patients with mild cognitive impairment show an increased cerebrospinal fluid t-Tau/Aβ ratio (p = 0.018) and a higher risk to develop AD (OR = 1.678, p = 0.018). MRIs showed that Dup/Dup patients exhibited a worse initial response to AD. At the moment of diagnosis, all patients showed equivalent Mini-Mental State Examination scores. However, AD patients with the duplication had less hippocampal degeneration (p < 0.001) and fewer white matter hyperintensities. In contrast, longitudinal studies indicate that patients bearing the duplication allele show a slower cognitive decline (p = 0.013). Transcriptional analysis also shows that the SIRPβ1 duplication allele correlates with higher TREM2 expression and an increased microglial activation. CONCLUSIONS: The SIRPβ1 internal duplication has opposite effects over MCI-to-Dementia conversion risk and AD progression, affecting microglial response to Aβ. Given the pharmacological approaches focused on the TREM2-TYROBP axis, we believe that SIRPβ1 structural variant might be considered as a potential modulator of this causative pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Humans; Microglia; Phagocytosis; Receptors, Cell Surface

Loss of Adaptive DNA Breaks in Alzheimer's Disease Brains. - Zhang, Xiaoyu; Haeri, Mohammad; Swerdlow, Russell H; Wang, Ning (J Alzheimers Dis, 2024)
BACKGROUND: DNA breaks accumulate in Alzheimer's disease (AD) brains. While their role as true genomic lesions is recognized, DNA breaks also support cognitive function by facilitating the expression of activity-dependent immediate early genes. This process involves TOP2B, a DNA topoisomerase that catalyzes the formation of DNA double-strand breaks. OBJECTIVE: To characterize how AD impacts adaptive DNA breaks at nervous system genes. METHODS: We leveraged the ability of DNA single- and double-strand breaks to activate poly(ADP-ribose) polymerases (PARPs) that conjugate poly(ADP-ribose) (PAR) to adjacent proteins. To characterize the genomic sites harboring DNA breaks in AD brains, nuclei extracted from 3 AD and 3 non-demented autopsy brains (frontal cortex, all male donors, age 78 to 91 years of age) were analyzed through CUT&RUN in which we targeted PAR with subsequent DNA sequencing. RESULTS: Although the AD brains contained 19.9 times more PAR peaks than the non-demented brains, PAR peaks at nervous system genes were profoundly lost in AD brains, and the expression of these genes was downregulated. This result is consistent with our previous CUT&RUN targeting γH2AX, which marks DNA double-strand breaks. In addition, TOP2B expression was significantly decreased in the AD brains. CONCLUSIONS: Although AD brains contain a net increase in DNA breaks, adaptive DNA breaks at nervous system genes are lost in AD brains. This could potentially reflect diminished TOP2B expression and contribute to impaired neuron function and cognition in AD patients.

Microglial TLR4/NLRP3 Inflammasome Signaling in Alzheimer's Disease. - Li, Yunfeng; Chen, Xiongjin; Zhou, Mulan; Feng, Sifan; Peng, Xiaoping; Wang, Yan (J Alzheimers Dis, 2024)
Alzheimer's disease is a pervasive neurodegenerative disease that is estimated to represent approximately 70% of dementia cases worldwide, and the molecular complexity that has been highlighted remains poorly understood. The accumulation of extracellular amyloid-β (Aβ), intracellular neurofibrillary tangles formed by tau hyperphosphorylation, and neuroinflammation are the major pathological features of Alzheimer's disease (AD). Over the years, there has been no apparent breakthrough in drug discovery based on the Aβ and tau hypotheses. Neuroinflammation has gradually become a hot spot in AD treatment research. As the primary cells of innate immunity in the central nervous system, microglia play a key role in neuroinflammation. Toll-like receptor 4 (TLR4) and nucleotide-binding oligomerization domain-like receptor 3 (NLRP3) inflammasomes are vital molecules in neuroinflammation. In the pathological context of AD, the complex interplay between TLR4 and the NLRP3 inflammasomes in microglia influences AD pathology via neuroinflammation. In this review, the effect of the activation and inhibition of TLR4 and NLRP3 in microglia on AD pathology, as well as the cross-talk between TLR4 and the NLRP3 inflammasome, and the influence of essential molecules in the relevant signaling pathway on AD pathology, were expounded. In addition, the feasibility of these factors in representing a potential treatment option for AD has been clarified.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Inflammasomes; Microglia; Neurodegenerative Diseases; Neuroinflammatory Diseases; NLR Family, Pyrin Domain-Containing 3 Protein; Signal Transduction; Toll-Like Receptor 4

A Novel Score to Predict Individual Risk for Future Alzheimer's Disease: A Longitudinal Study of the ADNI Cohort. - Guo, Hongxiu; Sun, Shangqi; Yang, Yang; Ma, Rong; Wang, Cailin; Zheng, Siyi; Wang, Xiufeng; Li, Gang (J Alzheimers Dis, 2024)
BACKGROUND: Identifying high-risk individuals with mild cognitive impairment (MCI) who are likely to progress to Alzheimer's disease (AD) is crucial for early intervention. OBJECTIVE: This study aimed to develop and validate a novel clinical score for personalized estimation of MCI-to-AD conversion. METHODS: The data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study were analyzed. Two-thirds of the MCI patients were randomly assigned to a training cohort (n = 478), and the remaining one-third formed the validation cohort (n = 239). Multivariable logistic regression was performed to identify factors associated with MCI-to-AD progression within 4 years. A prediction score was developed based on the regression coefficients derived from the logistic model and tested in the validation cohort. RESULTS: A lipidomics-signature was obtained that showed a significant association with disease progression. The MCI conversion scoring system (ranged from 0 to 14 points), consisting of the lipidomics-signature and five other significant variables (Apolipoprotein ɛ4, Rey Auditory Verbal Learning Test immediate and delayed recall, Alzheimer's Disease Assessment Scale delayed recall test, Functional Activities Questionnaire, and cortical thickness of the AD signature), was constructed. Higher conversion scores were associated with a higher proportion of patients converting to AD. The scoring system demonstrated good discrimination and calibration in both the training cohort (AUC = 0.879, p of Hosmer-Lemeshow test = 0.597) and the validation cohort (AUC = 0.915, p of Hosmer-Lemeshow test = 0.991). The risk classification achieved excellent sensitivity (0.84) and specificity (0.75). CONCLUSIONS: The MCI-to-AD conversion score is a reliable tool for predicting the risk of disease progression in individuals with MCI.

O-GlcNAcylation and Its Roles in Neurodegenerative Diseases. - Du, Pengyang; Zhang, Xiaomin; Lian, Xia; Holscher, Christian; Xue, Guofang (J Alzheimers Dis, 2024)
As a non-classical post-translational modification, O-linked β-N-acetylglucosamine (O-GlcNAc) modification (O-GlcNAcylation) is widely found in human organ systems, particularly in our brains, and is indispensable for healthy cell biology. With the increasing age of the global population, the incidence of neurodegenerative diseases is increasing, too. The common characteristic of these disorders is the aggregation of abnormal proteins in the brain. Current research has found that O-GlcNAcylation dysregulation is involved in misfolding or aggregation of these abnormal proteins to mediate disease progression, but the specific mechanism has not been defined. This paper reviews recent studies on O-GlcNAcylation's roles in several neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, Huntington's disease, Machado-Joseph's disease, and giant axonal neuropathy, and shows that O-GlcNAcylation, as glucose metabolism sensor, mediating synaptic function, participating in oxidative stress response and signaling pathway conduction, directly or indirectly regulates characteristic pathological protein toxicity and affects disease progression. The existing results suggest that targeting O-GlcNAcylation will provide new ideas for clinical diagnosis, prevention, and treatment of neurodegenerative diseases.
Keywords: Acetylglucosamine; Alzheimer Disease; Disease Progression; Humans; N-Acetylglucosaminyltransferases; Neurodegenerative Diseases; Protein Processing, Post-Translational; Proteins

Parkinson's Disease and Other Alzheimer's Disease and Related Dementia Pathologies and the Progression of Parkinsonism in Older Adults. - Buchman, Aron S; Yu, Lei; Oveisgharan, Shahram; Zammit, Andrea R; Wang, Tianhao; Shulman, Joshua M; VanderHorst, Veronique; Nag, Sukrit; Bennett, David A (J Alzheimers Dis, 2024)
BACKGROUND: The interrelationship of parkinsonism, Parkinson's disease (PD) and other Alzheimer's disease (AD) and Alzheimer's disease and related dementias (ADRD) pathologies is unclear. OBJECTIVE: We examined the progression of parkinsonian signs in adults with and without parkinsonism, and their underlying brain pathologies. METHODS: Annual parkinsonian signs were based on a modified Unified Parkinson's Disease Rating Scale. We used linear mixed effects models to compare the progression of parkinsonian signs in 3 groups categorized based on all available clinical evaluations: Group1 (never parkinsonism or clinical PD), Group2 (ever parkinsonism, but never clinical PD), Group3 (ever clinical PD). In decedents, we examined the progression of parkinsonian signs with PD and eight other AD/ADRD pathologies. RESULTS: During average follow-up of 8 years, parkinsonian signs on average increased by 7.3% SD/year (N = 3,807). The progression of parkinsonian signs was slowest in Group1 (never parkinsonism or clinical PD), intermediate in Group2, and fastest in Group3. In decedents (n = 1,717) pathologic PD and cerebrovascular (CVD) pathologies were associated with a faster rate of progressive parkinsonian signs (all p values <0.05). However, pathologic PD was rare in adults without clinical PD (Group1, 5%; Group2, 7% versus Group3, 55%). Yet, 70% of adults in Group2 without pathologic PD showed one or more CVD pathologies. In Group2, adults with pathologic PD showed faster progression of parkinsonian signs compared with those without evidence of pathologic PD and their rate of progression was indistinguishable from adults with clinical PD. CONCLUSIONS: Parkinsonism in old age is more commonly related to cerebrovascular pathologies relative to pathologic PD and only a minority manifest prodromal PD.

Pharmacologic and Nutritional Interventions for Early Alzheimer's Disease: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials. - Zeng, Baoqi; Tang, Chunbian; Wang, Junjian; Yang, Qingqing; Ren, Qingcuo; Liu, Xiaozhi (J Alzheimers Dis, 2024)
BACKGROUND: Early intervention is essential for meaningful disease modification in Alzheimer's disease (AD). OBJECTIVE: We aimed to determine the efficacy and safety of pharmacologic and nutritional interventions for early AD. METHODS: PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov were searched from database inception until 1 September 2023. We included randomized controlled trials that evaluated the efficacy of interventions in early AD. Only interventions that demonstrated efficacy compared to placebo were included in the network meta-analysis (NMA). Then we performed frequentist fixed-effects NMA to rank the interventions. GRADE criteria were used to evaluate the level of evidence. RESULTS: Fifty-eight trials including a total of 33,864 participants and 48 interventions were eligible for inclusion. Among the 48 interventions analyzed, only 6 (12.5%) treatments- ranging from low to high certainty- showed significant improvement in cognitive decline compared to placebo. High certainty evidence indicated that donanemab (standardized mean difference [SMD] -0.239, 95% confidence interval [CI] -0.343 to -0.134) and lecanemab (SMD -0.194, 95% CI -0.279 to -0.108) moderately slowed the clinical progression in patients with amyloid pathology. Additionally, methylphenidate, donepezil, LipiDiDiet, and aducanumab with low certainty showed significant improvement in cognitive decline compared to placebo. However, there was no significant difference in serious adverse events as reported between the six interventions and placebo. CONCLUSIONS: Only 12.5% of interventions studied demonstrated efficacy in reducing cognitive impairment in early AD. Donanemab and lecanemab have the potential to moderately slow the clinical progression in patients with amyloid pathology. Further evidence is required for early intervention in AD.
Keywords: Alzheimer Disease; Humans; Network Meta-Analysis; Randomized Controlled Trials as Topic

Plasma BDNF/Irisin Ratio Associates with Cognitive Function in Older People. - Huang, Xiuxiu; Wang, Jiaxin; Zhang, Shifang; Zhao, Xiaoyan; An, Ran; Lan, Yue; Yi, Ming; Wan, Qiaoqin (J Alzheimers Dis, 2024)
BACKGROUND: Reliable blood biomarkers are crucial for early detection and treatment evaluation of cognitive impairment, including Alzheimer's disease and other dementias. OBJECTIVE: To examine whether plasma biomarkers and their combination are different between older people with mild cognitive impairment (MCI) and cognitively normal individuals, and to explore their relations with cognitive performance. METHODS: This cross-sectional study included 250 older adults, including 124 participants with MCI, and 126 cognitively normal participants. Plasma brain-derived neurotrophic factor (BDNF), irisin and clusterin were measured, and BDNF/irisin ratio was calculated. Global cognition was evaluated by the Montreal Cognitive Assessment. RESULTS: Plasma irisin levels, but not BDNF, were significantly different between MCI group and cognitively normal group. Higher irisin concentration was associated with an increased probability for MCI both before and after controlling covariates. By contrast, plasma BDNF concentration, but not irisin, was linearly correlated with cognitive performance after adjusting for covariates. Higher BDNF/irisin ratios were not only correlated with better cognitive performance, but also associated with lower risks of MCI, no matter whether we adjusted for covariates. Plasma BDNF and irisin concentrations increased with aging, whereas BDNF/irisin ratios remained stable. No significant results of clusterin were observed. CONCLUSIONS: Plasma BDNF/irisin ratio may be a reliable indicator which not only reflects the odds of the presence of MCI but also directly associates with cognitive performance.
Keywords: Aged; Aged, 80 and over; Aging; Biomarkers; Brain-Derived Neurotrophic Factor; Clusterin; Cognition; Cognitive Dysfunction; Cross-Sectional Studies; Female; Fibronectins; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests

Pre-existing dementia is associated with 2-3 folds risk for in-hospital mortality and complications after intracerebral hemorrhage stroke. - Zuo, Lijun; Hu, Yang; Dong, YanHong; Seet, Raymond Cs; Li, Zixiao; Wang, Yongjun; Zhao, Xingquan (J Alzheimers Dis, 2024)
BACKGROUND: Pre-existing dementia was related to poor functional outcome after intracerebral hemorrhage (ICH), and its commonly underlying pathologies were considered as cerebral amyloid angiopathy. But the impact of pre-existing dementia on in-hospital mortality in Chinese ICH patients has not been well characterized. OBJECTIVE: To investigate the association between pre-existing dementia and in-hospital mortality after ICH. METHODS: Data were extracted from the China Stroke Center Alliance database. Information about the existence of prior to stroke dementia was obtained from next of kin informants and registered in clinical charts. Patients' characteristics, in-hospital mortality, home discharge and complications were compared between ICH patients with and without pre-existing dementia. RESULTS: Out of the 72,318 ICH patients, we identified 328 patients with pre-existing dementia. Patients with pre-existing dementia were more likely to experience greater stroke severity as measured by the National Institute of Health Stroke Scale and Glasgow Coma Scale. In the adjusted models, the presence of pre-existing dementia was associated with an increased risk of in-hospital mortality (OR 2.31, 95% CI 1.12-4.77), more frequent in-hospital complications of pulmonary embolism (OR 5.41, 95% CI 1.16-25.14), pneumonia (OR 1.58, 95% CI 1.08-2.33), urinary tract infection (OR 2.37, 95% CI 1.21-4.64), gastrointestinal bleeding (OR 2.39, 95% CI 1.27-4.49) and lower home discharge (OR 0.59, 95% CI 0.38∼0.93). CONCLUSIONS: ICH patients with pre-existing dementia are more likely to suffer from greater stroke severity, poorer outcomes and lower home discharge. Future studies should evaluate the value of intensive risk factor control among individuals with pre-existing dementia for stroke prevention.
Keywords: Aged; Aged, 80 and over; Cerebral Hemorrhage; China; Dementia; Female; Hemorrhagic Stroke; Hospital Mortality; Humans; Male; Middle Aged; Risk Factors; Stroke

Primary cortical cell tri-culture to study effects of amyloid-β on microglia function and neuroinflammatory response. - Kim, Hyehyun; Le, Bryan; Goshi, Noah; Zhu, Kan; Grodzki, Ana Cristina; Lein, Pamela J; Zhao, Min; Seker, Erkin (J Alzheimers Dis, 2024)
BACKGROUND: Microglia play a critical role in neurodegenerative disorders, such as Alzheimer's disease, where alterations in microglial function may result in pathogenic amyloid-β (Aβ) accumulation, chronic neuroinflammation, and deleterious effects on neuronal function. However, studying these complex factors in vivo, where numerous confounding processes exist, is challenging, and until recently, in vitro models have not allowed sustained culture of critical cell types in the same culture. OBJECTIVE: We employed a rat primary tri-culture (neurons, astrocytes, and microglia) model and compared it to co-culture (neurons and astrocytes) and mono-culture (microglia) to study microglial function (i.e., motility and Aβ clearance) and proteomic response to exogenous Aβ. METHODS: The cultures were exposed to fluorescently-labeled Aβ (FITC-Aβ) particles for varying durations. Epifluorescence microscopy images were analyzed to quantify the number of FITC-Aβ particles and assess cytomorphological features. Cytokine profiles from conditioned media were obtained. Live-cell imaging was employed to extract microglia motility parameters. RESULTS: FITC-Aβ particles were more effectively cleared in the tri-culture compared to the co-culture. This was attributed to microglia engulfing FITC-Aβ particles, as confirmed via epifluorescence and confocal microscopy. FITC-Aβ treatment significantly increased microglia size, but had no significant effect on neuronal surface coverage or astrocyte size. Upon FITC-Aβ treatment, there was a significant increase in proinflammatory cytokines in tri-culture, but not in co-culture. Aβ treatment altered microglia motility evident as a swarming-like motion. CONCLUSIONS: The results suggest that neuron-astrocyte-microglia interactions influence microglia function and highlight the utility of the tri-culture model for studies of neuroinflammation, neurodegeneration, and cell-cell communication.
Keywords: Amyloid beta-Peptides; Animals; Astrocytes; Cells, Cultured; Cerebral Cortex; Coculture Techniques; Cytokines; Microglia; Neuroinflammatory Diseases; Neurons; Rats; Rats, Sprague-Dawley

Recent Advances in Drug Delivery Systems Targeting Insulin Signalling for the Treatment of Alzheimer's Disease. - Sachdeva, Punya; Narayanan, Kannan Badri; Sinha, Jitendra Kumar; Gupta, Saurabh; Ghosh, Shampa; Singh, Krishna Kumar; Bhaskar, Rakesh; Almutary, Abdulmajeed G; Zothantluanga, James H; Kotta, Kranthi Kumar; Nelson, Vinod Kumar; Paiva-Santos, Ana Cláudia; et al. (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is a complex neurodegenerative disorder characterized by the accumulation of neurofibrillary tangles and amyloid-β plaques. Recent research has unveiled the pivotal role of insulin signaling dysfunction in the pathogenesis of AD. Insulin, once thought to be unrelated to brain function, has emerged as a crucial factor in neuronal survival, synaptic plasticity, and cognitive processes. Insulin and the downstream insulin signaling molecules are found mainly in the hippocampus and cortex. Some molecules responsible for dysfunction in insulin signaling are GSK-3β, Akt, PI3K, and IRS. Irregularities in insulin signaling or insulin resistance may arise from changes in the phosphorylation levels of key molecules, which can be influenced by both stimulation and inactivity. This, in turn, is believed to be a crucial factor contributing to the development of AD, which is characterized by oxidative stress, neuroinflammation, and other pathological hallmarks. Furthermore, this route is known to be indirectly influenced by Nrf2, NF-κB, and the caspases. This mini-review delves into the intricate relationship between insulin signaling and AD, exploring how disruptions in this pathway contribute to disease progression. Moreover, we examine recent advances in drug delivery systems designed to target insulin signaling for AD treatment. From oral insulin delivery to innovative nanoparticle approaches and intranasal administration, these strategies hold promise in mitigating the impact of insulin resistance on AD. This review consolidates current knowledge to shed light on the potential of these interventions as targeted therapeutic options for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Drug Delivery Systems; Glycogen Synthase Kinase 3 beta; Humans; Insulin; Insulin Resistance

Senescence Targeting Methods Impact Alzheimer's Disease Features in 3xTg Mice. - Ng, Pei Y; Zhang, Cheng; Li, Hu; Baker, Darren J (J Alzheimers Dis, 2024)
BACKGROUND: Cellular senescence has been associated with neurodegenerative disease and clearance of senescent cells using genetic or pharmaceutical strategies (senolytics) has demonstrated beneficial effects in mouse models investigating individual disease etiologies of Alzheimer's disease (AD). However, it has remained unclear if senescent cell clearance in a mouse model exhibiting both plaque and tau pathologies modifies the disease state (3xTg). OBJECTIVE: To investigate the effects of senescent cell clearance in the 3xTg mouse model. METHODS: 3xTg mice were treated with senolytics (ABT263 (navitoclax; NAVI), a combination of dasatinib and quercetin (D+Q)), or subjected to transgene-mediated removal of p16-expressing cells (via INK-ATTAC). RESULTS: Senolytic treatments consistently reduced microgliosis and ameliorated both amyloid and tau pathology in 3xTg mice. Using RNA sequencing, we found evidence that synaptic dysfunction and neuroinflammation were attenuated with treatment. These beneficial effects were not observed with short-term senolytic treatment in mice with more advanced disease. CONCLUSIONS: Overall, our results further corroborate the beneficial effects senescent cell clearance could have on AD and highlight the importance of early intervention for the treatment of this debilitating disease.
Keywords: Alzheimer Disease; Animals; Cellular Senescence; Disease Models, Animal; Mice; Mice, Transgenic; Neurodegenerative Diseases; Senotherapeutics; tau Proteins

Serial Cerebrospinal Fluid Sampling Reveals Trajectories of Potential Synaptic Biomarkers in Early Stages of Alzheimer's Disease. - Duits, Flora H; Nilsson, Johanna; Zetterberg, Henrik; Blennow, Kaj; van der Flier, Wiesje M; Teunissen, Charlotte E; Brinkmalm, Ann (J Alzheimers Dis, 2024)
BACKGROUND: Synaptic dysfunction is closely associated with cognitive function in Alzheimer's disease (AD), and is present already in an early stage of the disease. OBJECTIVE: Using serial cerebrospinal fluid (CSF) sampling, we aimed to investigate slopes of CSF synaptic proteins, and their relation with cognition along the AD continuum. METHODS: We included subjects with subjective cognitive decline (SCD) or mild cognitive impairment (MCI) (n = 50 amyloid-β+ [A +], n = 50 A-) and 50 patients with AD dementia from the Amsterdam dementia cohort, with CSF at two time points (median[IQR] 2.1[1.4-2.7] years). We analyzed 17 synaptic proteins and neurofilament light (NfL). Using linear mixed models we assessed trajectories of protein levels, and associations with cognitive decline (repeated Mini-Mental State Examination). We used Cox regression models to assess predictive value of protein levels for progression to AD dementia. RESULTS: At baseline most proteins showed increased levels in AD dementia compared to the other groups. In contrast NPTX2 levels were lower in AD dementia. Higher baseline levels of SNAP25, β-syn, and 14-3-3 proteins were associated with faster cognitive decline (St.B[SE] -0.27[0.12] to -0.61[0.12]). Longitudinal analyses showed that SYT1 and NPTX levels decreased over time in AD dementia (st.B[SE] -0.10[0.04] to -0.15[0.05]) and SCD/MCI-A+ (St.B[SE] -0.07[0.03] to -0.12[0.03]), but not in SCD/MCI-A- (pinteraction < 0.05). Increase over time in NfL levels was associated with faster cognitive decline in AD dementia (St.B[SE] -1.75[0.58]), but not in the other groups (pinteraction < 0.05). CONCLUSIONS: CSF synaptic proteins showed different slopes over time, suggesting complex synaptic dynamics. High levels of especially SNAP-25 may have value for prediction of cognitive decline in early AD stages, while increase in NfL over time correlates better with cognitive decline in later stages.

Sildenafil as a Candidate Drug for Alzheimer's Disease: Real-World Patient Data Observation and Mechanistic Observations from Patient-Induced Pluripotent Stem Cell-Derived Neurons. - Gohel, Dhruv; Zhang, Pengyue; Gupta, Amit Kumar; Li, Yichen; Chiang, Chien-Wei; Li, Lang; Hou, Yuan; Pieper, Andrew A; Cummings, Jeffrey; Cheng, Feixiong (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a chronic neurodegenerative disease needing effective therapeutics urgently. Sildenafil, one of the approved phosphodiesterase-5 inhibitors, has been implicated as having potential effect in AD. OBJECTIVE: To investigate the potential therapeutic benefit of sildenafil on AD. METHODS: We performed real-world patient data analysis using the MarketScan® Medicare Supplemental and the Clinformatics® databases. We conducted propensity score-stratified analyses after adjusting confounding factors (i.e., sex, age, race, and comorbidities). We used both familial and sporadic AD patient induced pluripotent stem cells (iPSC) derived neurons to evaluate the sildenafil's mechanism-of-action. RESULTS: We showed that sildenafil usage is associated with reduced likelihood of AD across four new drug compactor cohorts, including bumetanide, furosemide, spironolactone, and nifedipine. For instance, sildenafil usage is associated with a 54% reduced incidence of AD in MarketScan® (hazard ratio [HR] = 0.46, 95% CI 0.32- 0.66) and a 30% reduced prevalence of AD in Clinformatics® (HR = 0.70, 95% CI 0.49- 1.00) compared to spironolactone. We found that sildenafil treatment reduced tau hyperphosphorylation (pTau181 and pTau205) in a dose-dependent manner in both familial and sporadic AD patient iPSC-derived neurons. RNA-sequencing data analysis of sildenafil-treated AD patient iPSC-derived neurons reveals that sildenafil specifically target AD related genes and pathobiological pathways, mechanistically supporting the beneficial effect of sildenafil in AD. CONCLUSIONS: These real-world patient data validation and mechanistic observations from patient iPSC-derived neurons further suggested that sildenafil is a potential repurposable drug for AD. Yet, randomized clinical trials are warranted to validate the causal treatment effects of sildenafil in AD.
Keywords: Aged; Alzheimer Disease; Humans; Induced Pluripotent Stem Cells; Medicare; Neurodegenerative Diseases; Neurons; Sildenafil Citrate; Spironolactone; tau Proteins; United States

Small RNA Profiles of Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Turchinovich, Andrey; Pletniková, Olga; Redding-Ochoa, Javier; Troncoso, Juan C; Hill, Andrew F; Mahairaki, Vasiliki; Zheng, Lei; Witwer, Kenneth W (J Alzheimers Dis, 2024)
BACKGROUND: Extracellular vesicles (EVs) and non-coding RNAs (ncRNAs) are emerging contributors to Alzheimer's disease (AD) pathophysiology. Differential abundance of ncRNAs carried by EVs may provide valuable insights into underlying disease mechanisms. Brain tissue-derived EVs (bdEVs) are particularly relevant, as they may offer valuable insights about the tissue of origin. However, there is limited research on diverse ncRNA species in bdEVs in AD. OBJECTIVE: This study explored whether the non-coding RNA composition of EVs isolated from post-mortem brain tissue is related to AD pathogenesis. METHODS: bdEVs from age-matched late-stage AD patients (n = 23) and controls (n = 10) that had been separated and characterized in our previous study were used for RNA extraction, small RNA sequencing, and qPCR verification. RESULTS: Significant differences of non-coding RNAs between AD and controls were found, especially for miRNAs and tRNAs. AD pathology-related miRNA and tRNA differences of bdEVs partially matched expression differences in source brain tissues. AD pathology had a more prominent association than biological sex with bdEV miRNA and tRNA components in late-stage AD brains. CONCLUSIONS: Our study provides further evidence that EV non-coding RNAs from human brain tissue, including but not limited to miRNAs, may be altered and contribute to AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Extracellular Vesicles; Female; Humans; Male; MicroRNAs; RNA, Small Untranslated; RNA, Transfer; RNA, Untranslated

Space-Like Irradiation Exacerbated Cognitive Deficits and Amyloid Pathology in CRND8 Mouse Model of Alzheimer's Disease. - Wang, Wenzhang; Zhao, Fanpeng; Torres, Sandy; Harris, Peggy L R; Wang, Xinglong; Peng, Lihua; Siedlak, Sandra L; Zhu, Xiongwei (J Alzheimers Dis, 2024)
BACKGROUND: Space radiation was linked to neurological damage and behavioral deficits which raised concerns of increased degenerative risk on the brain and development of Alzheimer's disease following space travel. OBJECTIVE: In this study, we investigated the effects of irradiation by 56Fe and 28Si in CRND8 mice, an Alzheimer's disease mouse model. METHODS: Six-month-old CRND8 mice were exposed to whole body irradiation by 56Fe and 28Si at 0.5 Gy and 2 Gy doses. Behavior tests were administered 1-month to 3-months post-irradiation. Amyloid deposition and other pathological changes were analyzed 3-months and/or 6-months post-irradiatio. RESULTS: The Novel Object Recognition test showed some decline in 8-month-old mice compared to non-irradiated CRND8 mice. Male mice also showed a loss of freezing behavior in the fear conditioning contextual test following irradiation. Golgi staining revealed a loss of spines in hippocampal neurons after irradiation. Total amyloid immunohistochemistry showed a robust increase in 3-months post-irradiation 56Fe groups which became normalized to non-irradiated group by 6-months post-irradiation. However, 2 Gy 28Si caused a trend towards increased plaque load at 3-months post-irradiation which became significant at 6-months post irradiation only in male CRND8 mice. While 0.5 Gy Fe did not induce obvious changes in the total number of iba-1 positive microglia, more hippocampal microglia were found to express PCNA after 0.5 Gy Fe treatment, suggesting potential involvement of microglial dysfunction. CONCLUSIONS: Overall, our study provides new evidence of gender-specific and ion-dependent effects of space radiation on cognition and amyloid pathology in AD models.

A 19-Year-Old Adolescent with Probable Alzheimer's Disease. - Jia, Jianping; Zhang, Yue; Shi, Yuqing; Yin, Xuping; Wang, Shiyuan; Li, Yan; Zhao, Tan; Liu, Wenying; Zhou, Aihong; Jia, Longfei (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) primarily affects older adults. In this report, we present the case of a 19-year-old male with gradual memory decline for 2 years and World Health Organization-University of California Los Angeles Auditory Verbal Learning Test (WHO-UCLA AVLT) results also showing memory impairment. Positron emission tomography-magnetic resonance imaging with 18F fluorodeoxyglucose revealed atrophy of the bilateral hippocampus and hypometabolism in the bilateral temporal lobe. Examination of the patient's cerebrospinal fluid showed an increased concentration of p-tau181 and a decreased amyloid-β 42/40 ratio. However, through whole-genome sequencing, no known gene mutations were identified. Considering the above, the patient was diagnosed with probable AD.
Keywords: Adolescent; Aged; Alzheimer Disease; Amyloid beta-Peptides; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Positron-Emission Tomography

Accumulation of pTau231 at the Postsynaptic Density in Early Alzheimer's Disease. - Lilek, Jaclyn; Ajroud, Kaouther; Feldman, Alexander Z; Krishnamachari, Sesha; Ghourchian, Shadi; Gefen, Tamar; Spencer, Callen L; Kawles, Allegra; Mao, Qinwen; Tranovich, Jessica F; Jack, Clifford R; Mesulam, M-Marsel; et al. (J Alzheimers Dis, 2023)

Alzheimer's Disease Pathology Outside of the Cerebrum Is Related to a Higher Odds of Dementia. - Buchman, Aron S; Leurgans, Sue E; Kim, Namhee; Agrawal, Sonal; Oveisgharan, Shahram; Zammit, Andrea R; VanderHorst, Veronique; Nag, Sukrit; Bennett, David A (J Alzheimers Dis, 2023)
BACKGROUND: Assessments of Alzheimer's disease pathology do not routinely include lower brainstem, olfactory bulb, and spinal cord. OBJECTIVE: Test if amyloid-β (Aβ) and paired helical filament (PHF) tau-tangles outside the cerebrum are associated with the odds of dementia. METHODS: Autopsies were obtained in decedents with cognitive testing (n = 300). Aβ plaques and PHF tau-tangles were assessed in 24 sites: cerebrum (n = 14), brainstem (n = 5), olfactory bulb, and four spinal cord levels. Since spinal Aβ were absent in the first 165 cases, it was not assessed in the remaining cases. RESULTS: Age at death was 91 years old. About 90% had Aβ in cerebrum and of these, half had Aβ in the brainstem. Of the latter, 85% showed Aβ in the olfactory bulb. All but one participant had tau-tangles in the cerebrum and 86% had brainstem tau-tangles. Of the latter, 80% had tau-tangles in olfactory bulb and 36% tau-tangles in one or more spinal cord levels. About 90% of adults with tau-tangles also had Aβ in one or more regions. In a logistic model controlling for demographics, Aβ and tau-tangles within the cerebrum, the presence of Aβ in olfactory bulb [OR, 1.74(1.00, 3.05)]; tau-tangles in brainstem [OR, 4.00(1.1.57,10.21)]; and spinal cord [OR, 1.87 (1.21,3.11)] were independently associated with higher odds of dementia. CONCLUSION: Regional differences in Aβ and tau-tangle accumulation extend beyond cerebrum to spinal cord and their presence outside the cerebrum are associated with a higher odds of dementia. Further studies are needed to clarify the extent, burden, and consequences of AD pathology outside of cerebrum.

Aspirin Use and Risk of Alzheimer's Disease: A 2-Sample Mendelian Randomization Study. - Ding, Pingjian; Gorenflo, Maria P; Zhu, Xiaofeng; Xu, Rong (J Alzheimers Dis, 2023)
BACKGROUND: Observational studies have shown inconsistent findings of the relationships between aspirin use and the risk of Alzheimer's disease (AD). OBJECTIVE: Since residual confounding and reverse causality were challenging issues inherent in observational studies, we conducted a 2-sample Mendelian randomization analysis (MR) to investigate whether aspirin use was causally associated with the risk of AD. METHODS: We conducted 2-sample MR analyses utilizing summary genetic association statistics to estimate the potential causal relationship between aspirin use and AD. Single-nucleotide variants associated with aspirin use in a genome-wide association study (GWAS) of UK Biobank were considered as genetic proxies for aspirin use. The GWAS summary-level data of AD were derived from a meta-analysis of GWAS data from the International Genomics of Alzheimer's Project (IGAP) stage I. RESULTS: Univariable MR analysis based on these two large GWAS data sources showed that genetically proxied aspirin use was associated with a decreased risk of AD (Odds Ratio (OR): 0.87; 95%CI: 0.77-0.99). In multivariate MR analyses, the causal estimates remained significant after adjusting for chronic pain, inflammation, heart failure (OR = 0.88, 95%CI = 0.78-0.98), or stroke (OR = 0.87, 95%CI = 0.77-0.99), but was attenuated when adjusting for coronary heart disease, blood pressure, and blood lipids. CONCLUSION: Findings from this MR analysis suggest a genetic protective effect of aspirin use on AD, possibly influenced by coronary heart disease, blood pressure, and lipid levels.

Association Between Oral Bacteria and Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Liu, Sixin; Dashper, Stuart G; Zhao, Rui (J Alzheimers Dis, 2023)
BACKGROUND: Pre-clinical evidence implicates oral bacteria in the pathogenesis of Alzheimer's disease (AD), while clinical studies show diverse results. OBJECTIVE: To comprehensively assess the association between oral bacteria and AD with clinical evidence. METHODS: Studies investigating the association between oral bacteria and AD were identified through a systematic search of six databases PubMed, Embase, Cochrane Central Library, Scopus, ScienceDirect, and Web of Science. Methodological quality ratings of the included studies were performed. A best evidence synthesis was employed to integrate the results. When applicable, a meta-analysis was conducted using a random-effect model. RESULTS: Of the 16 studies included, ten investigated periodontal pathobionts and six were microbiome-wide association studies. Samples from the brain, serum, and oral cavity were tested. We found over a ten-fold and six-fold increased risk of AD when there were oral bacteria (OR = 10.68 95% CI: 4.48-25.43; p < 0.00001, I2 = 0%) and Porphyromonas gingivalis (OR = 6.84 95% CI: 2.70-17.31; p < 0.0001, I2 = 0%) respectively in the brain. While AD patients exhibited lower alpha diversity of oral microbiota than healthy controls, the findings of bacterial communities were inconsistent among studies. The best evidence synthesis suggested a moderate level of evidence for an overall association between oral bacteria and AD and for oral bacteria being a risk factor for AD. CONCLUSION: Current evidence moderately supports the association between oral bacteria and AD, while the association was strong when oral bacteria were detectable in the brain. Further evidence is needed to clarify the interrelationship between both individual species and bacterial communities and the development of AD.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Microbiota; Porphyromonas gingivalis; Risk Factors

Cerebrospinal Fluid Panel of Synaptic Proteins in Cerebral Amyloid Angiopathy and Alzheimer's Disease. - van den Berg, Emma; Nilsson, Johanna; Kersten, Iris; Brinkmalm, Gunnar; de Kort, Anna M; Klijn, Catharina J M; Schreuder, Floris H B M; Jäkel, Lieke; Gobom, Johan; Portelius, Erik; Zetterberg, Henrik; Brinkmalm, Ann; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA) share pathogenic pathways related to amyloid-β deposition. Whereas AD is known to affect synaptic function, such an association for CAA remains yet unknown. OBJECTIVE: We therefore aimed to investigate synaptic dysfunction in CAA. METHODS: Multiple reaction monitoring mass spectrometry was used to quantify cerebrospinal fluid (CSF) concentrations of 15 synaptic proteins in CAA and AD patients, and age- and sex-matched cognitively unimpaired controls. RESULTS: We included 25 patients with CAA, 49 patients with AD, and 25 controls. Only neuronal pentraxin-2 levels were decreased in the CSF of CAA patients compared with controls (p = 0.04). CSF concentrations of 12 other synaptic proteins were all increased in AD compared with CAA or controls (all p≤0.01) and were unchanged between CAA and controls. Synaptic protein concentrations in the subgroup of CAA patients positive for AD biomarkers (CAA/ATN+; n = 6) were similar to AD patients, while levels in CAA/ATN- (n = 19) were comparable with those in controls. A regression model including all synaptic proteins differentiated CAA from AD at high accuracy levels (area under the curve 0.987). CONCLUSION: In contrast to AD, synaptic CSF biomarkers were found to be largely unchanged in CAA. Moreover, concomitant AD pathology in CAA is associated with abnormal synaptic protein levels. Impaired synaptic function in AD was confirmed in this independent cohort. Our findings support an apparent differential involvement of synaptic dysfunction in CAA and AD and may reflect distinct pathological mechanisms.

Chronic Sleep Disturbances Alters Sleep Structure and Tau Phosphorylation in AβPP/PS1 AD Mice and Their Wild-Type Littermates. - Zhang, Feng; Niu, Long; Zhong, Rujia; Li, Song; Le, Weidong (J Alzheimers Dis, 2023)
BACKGROUND: Emerging evidence indicates that sleep disorders are the common non-cognitive symptoms of Alzheimer's disease (AD), and they may contribute to the pathogenesis of this disease. OBJECTIVE: In this study, we aim to investigate the effect of chronic sleep deprivation (CSD) on AD-related pathologies with a focus on tau phosphorylation and the underlying DNA methylation regulation. METHODS: AβPPswe/PS1ΔE9 AD mice and their wild-type (WT) littermates were subjected to a two-month CSD followed by electroencephalography and electromyography recording. The mice were examined for learning and memory evaluation, then pathological, biochemical, and epigenetic assessments including western blotting, immunofluorescence, dot blotting, and bisulfite sequencing. RESULTS: The results show that CSD caused sleep disorders shown as sleep pattern change, poor sleep maintenance, and increased sleep fragmentation. CSD increased tau phosphorylation at different sites and increased the level of tau kinases in AD and WT mice. The increased expression of cyclin-dependent kinase 5 (CDK5) may result from decreased DNA methylation of CpG sites in the promoter region of CDK5 gene, which might be associated with the downregulation of DNA methyltransferase 3A and 3B. CONCLUSION: CSD altered AD-related tau phosphorylation through epigenetic modification of tau kinase gene. The findings in this study may give insights into the mechanisms underlying the effects of sleep disorders on AD pathology and provide new therapeutic targets for the treatment of this disease.

Coexistence of Amyotrophic Lateral Sclerosis and Alzheimer's Disease: Case Report and Review of the Literature. - Verde, Federico; Aiello, Edoardo Nicolò; Adobbati, Laura; Poletti, Barbara; Solca, Federica; Tiloca, Cinzia; Sangalli, Davide; Maranzano, Alessio; Muscio, Cristina; Ratti, Antonia; Zago, Stefano; Ticozzi, Nicola; et al. (J Alzheimers Dis, 2023)
We describe a case of amyotrophic lateral sclerosis (ALS) associated with Alzheimer's disease (AD) and review the literature about the coexistence of the two entities, highlighting the following: mean age at onset is 63.8 years, with slight female predominance; ALS tends to manifest after cognitive impairment and often begins in the bulbar region; average disease duration is 3 years; cognitive phenotype is mostly amnestic; the pattern of brain involvement is, in most cases, consistent with AD. Our case and the reviewed ones suggest that patients with ALS and dementia lacking unequivocal features of FTD should undergo additional examinations in order to recognize AD.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Brain; Cognitive Dysfunction; Female; Frontotemporal Dementia; Humans; Male

Costs During the Last Five Years of Life for Patients with Clinical and Pathological Confirmed Diagnosis of Lewy Body Dementia and Alzheimer's Disease. - Zhu, Carolyn W; Gu, Yian; Kociolek, Anton J; Fernandez, Kayri K; Cosentino, Stephanie; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: Little is known regarding healthcare expenditures for patients with dementia with Lewy bodies (DLB) during the end of life. OBJECTIVE: This study estimated Medicare expenditures during the last 5 years of life in a decedent sample of patients who were clinically diagnosed with Alzheimer's disease (AD) or DLB and had autopsy confirmed diagnosis. METHODS: The study included 58 participants clinically diagnosed with mild dementia at study entry (AD: n = 44, DLB: n = 14) and also had autopsy-confirmed diagnoses of pure AD (n = 32), mixed AD+Lewy body (LB) (n = 5), or pure LB (n = 11). Total Medicare expenditures were compared by clinical and pathology confirmed diagnosis, adjusting for sex, age at death, and patient's cognition, function, comorbidities, and psychiatric and extrapyramidal symptoms. RESULTS: When pathology diagnoses were not considered, predicted annualized total Medicare expenditures during the last 5 years of life were similar between clinically diagnosed AD ($7,465±1,098) and DLB ($7,783±1,803). When clinical diagnoses were not considered, predicted expenditures were substantially higher in patients with pathology confirmed mixed AD+LB ($12,005±2,455) than either pure AD ($6,173±941) or pure LB ($4,629±1,968) cases. Considering clinical and pathology diagnosis together, expenditures for patients with clinical DLB and pathology mixed AD+LB ($23,592±3,679) dwarfed other groups. CONCLUSION: Medicare expenditures during the last 5 years of life were substantially higher in patients with mixed AD+LB pathology compared to those with pure-AD and pure-DLB pathologies, particularly in those clinically diagnosed with DLB. Results highlight the importance of having both clinical and pathology diagnoses in examining healthcare costs.

Diagnostic Performance of Cerebrospinal Fluid Neurofilament Light Chain and Soluble Amyloid-β Protein Precursor β in the Subcortical Small Vessel Type of Dementia. - Axelsson Andrén, Elin; Kettunen, Petronella; Bjerke, Maria; Rolstad, Sindre; Zetterberg, Henrik; Blennow, Kaj; Wallin, Anders; Svensson, Johan (J Alzheimers Dis, 2023)
BACKGROUND: The subcortical small vessel type of dementia (SSVD) is a common subtype of vascular dementia, but there is a lack of disease-specific cerebrospinal fluid (CSF) biomarkers. OBJECTIVE: We investigated whether CSF concentrations of neurofilament light chain (NFL), soluble amyloid-β protein precursor α (sAβPPα), sAβPPβ, and CSF/serum albumin ratio could separate SSVD from healthy controls, Alzheimer's disease (AD), and mixed dementia (combined AD and SSVD). METHODS: This was a mono-center study of patients with SSVD (n = 38), AD (n = 121), mixed dementia (n = 62), and controls (n = 96). The CSF biomarkers were measured using immunoassays, and their independent contribution to the separation between groups were evaluated using the Wald test. Then, the area under the receiver operating characteristics curve (AUROC) and 95% confidence intervals (CIs) were calculated. RESULTS: Elevated neurofilament light chain (NFL) and decreased sAβPPβ independently separated SSVD from controls, and sAβPPβ also distinguished SSVD from AD and mixed dementia. The combination of NFL and sAβPPβ discriminated SSVD from controls with high accuracy (AUROC 0.903, 95% CI: 0.834-0.972). Additionally, sAβPPβ combined with the core AD biomarkers (amyloid-β42, total tau, and phosphorylated tau181) had a high ability to separate SSVD from AD (AUROC 0.886, 95% CI: 0.830-0.942) and mixed dementia (AUROC 0.903, 95% CI: 0.838-0.968). CONCLUSIONS: The high accuracy of NFL and sAβPPβ to separate SSVD from controls supports that SSVD is a specific diagnostic entity. Moreover, SSVD was distinguished from AD and mixed dementia using sAβPPβ in combination with the core AD biomarkers.

Disrupted excitation-inhibition balance in cognitively normal individuals at risk of Alzheimer's disease. - Fortel, Igor; Zhan, Liang; Ajilore, Olusola; Wu, Yichao; Mackin, Scott; Leow, Alex (bioRxiv, 2023)
BACKGROUND: Sex differences impact Alzheimer's disease (AD) neuropathology, but cell-to-network level dysfunctions in the prodromal phase are unclear. Alterations in hippocampal excitation-inhibition balance (EIB) have recently been linked to early AD pathology. OBJECTIVE: Examine how AD risk factors (age, APOE-ɛ4, amyloid-β) relate to hippocampal EIB in cognitively normal males and females using connectome-level measures. METHODS: Individuals from the OASIS-3 cohort (age 42-95) were studied (N = 437), with a subset aged 65+ undergoing neuropsychological testing (N = 231). RESULTS: In absence of AD risk factors (APOE-ɛ4/Aβ+), whole-brain EIB decreases with age more significantly in males than females (p = 0.021, β = -0.007). Regression modeling including APOE-ɛ4 allele carriers (Aβ-) yielded a significant positive AGE-by-APOE interaction in the right hippocampus for females only (p = 0.013, β = 0.014), persisting with inclusion of Aβ+ individuals (p = 0.012, β = 0.014). Partial correlation analyses of neuropsychological testing showed significant associations with EIB in females: positive correlations between right hippocampal EIB with categorical fluency and whole-brain EIB with the trail-making test (p < 0.05). CONCLUSION: Sex differences in EIB emerge during normal aging and progresses differently with AD risk. Results suggest APOE-ɛ4 disrupts hippocampal balance more than amyloid in females. Increased excitation correlates positively with neuropsychological performance in the female group, suggesting a duality in terms of potential beneficial effects prior to cognitive impairment. This underscores the translational relevance of APOE-ɛ4 related hyperexcitation in females, potentially informing therapeutic targets or early interventions to mitigate AD progression in this vulnerable population.

Early Diagnosis of Mild Cognitive Impairment due to Alzheimer's Disease Using a Composite of MemTrax and Blood Biomarkers. - Chen, Weineng; Lin, Cha; Su, Fengjuan; Fang, Yingying; Liu, Ganqiang; Chen, Yu-Chian; Zhou, Xianbo; Yao, Xiaoli; Ashford, Curtis B; Li, Feng; Ashford, J Wesson; Fu, Qingling; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Accessible measurements for the early detection of mild cognitive impairment (MCI) due to Alzheimer's disease (AD) are urgently needed to address the increasing prevalence of AD. OBJECTIVE: To determine the benefits of a composite MemTrax Memory Test and AD-related blood biomarker assessment for the early detection of MCI-AD in non-specialty clinics. METHODS: The MemTrax Memory Test and Montreal Cognitive Assessment were administered to 99 healthy seniors with normal cognitive function and 101 patients with MCI-AD; clinical manifestation and peripheral blood samples were collected. We evaluated correlations between the MemTrax Memory Test and blood biomarkers using Spearman's rank correlation analyses and then built discrimination models using various machine learning approaches that combined the MemTrax Memory Test and blood biomarker results. The models' performances were assessed according to the areas under the receiver operating characteristic curve. RESULTS: The MemTrax Memory Test and Montreal Cognitive Assessment areas under the curve for differentiating patients with MCI-AD from the healthy controls were similar. The MemTrax Memory Test strongly correlated with phosphorylated tau 181 and amyloid-β 42/40. The area under the curve for the best composite MemTrax Memory Test and blood biomarker model was 0.975 (95% confidence interval: 0.950-0.999). CONCLUSION: Combining MemTrax Memory Test and blood biomarker results is a promising new technique for the early detection of MCI-AD.

Effect of Metabolic Syndrome Risk Factors on Processing Speed and Executive Function in Three Racialized Groups. - Bouges, Shenikqua; Fischer, Barbara; Norton, Derek L; Wyman, Mary F; Lambrou, Nickolas; Zuelsdorff, Megan; Van Hulle, Carol A; Ennis, Gilda E; James, Taryn T; Johnson, Adrienne L; Chin, Nathaniel; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Metabolic syndrome (MetS) has been associated with increased risk for Alzheimer's disease and related dementias (ADRD). Understanding the association of MetS risk factors to processing speed and executive function in the pre-clinical stages of ADRD in under-represented groups would offer insight on potential mechanisms through which MetS associates with ADRD risk. OBJECTIVE: Examine association of MetS features and processing speed and executive function across three racial groups. METHODS: Cognitively unimpaired adults from the Wisconsin Alzheimer's Disease Research Center and the Wisconsin Registry for Alzheimer's Disease Prevention completed blood-draws and neuropsychological testing. Six cognitive outcomes were assessed in association to MetS risk factors: Trailmaking Tests A and B, Animal Fluency, Digit Symbol, and composite scores for Processing Speed and Executive Function. Linear mixed effect models were used to assess the relationship between MetS risk factor count and longitudinal cognitive performance across three racialized groups. RESULTS: Participant sample sizes varied by outcome analyzed (N = 714-1,088). African American and Native American groups exhibited higher rates of MetS than non-Hispanic Whites. MetS was associated with processing speed and executive function across all racialized groups. Three-way interaction by racialized group was limited to one cognitive outcome: Trailmaking Test A. CONCLUSION: Metabolic dysfunction incrementally affects cognitive trajectory, with generally similar associations across racial groups. Since racialized groups exhibit higher levels of both MetS and ADRD, MetS may represent a driving factor for increased ADRD risk experience by racialized group and an important and modifiable target through which to reduce risk of ADRD.

Effect of Pathway-Specific Polygenic Risk Scores for Alzheimer's Disease (AD) on Rate of Change in Cognitive Function and AD-Related Biomarkers Among Asymptomatic Individuals. - Xu, Yuexuan; Vasiljevic, Eva; Deming, Yuetiva K; Jonaitis, Erin M; Koscik, Rebecca L; Van Hulle, Carol A; Lu, Qiongshi; Carboni, Margherita; Kollmorgen, Gwendlyn; Wild, Norbert; Carlsson, Cynthia M; Johnson, Sterling C; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Genetic scores for late-onset Alzheimer's disease (LOAD) have been associated with preclinical cognitive decline and biomarker variations. Compared with an overall polygenic risk score (PRS), a pathway-specific PRS (p-PRS) may be more appropriate in predicting a specific biomarker or cognitive component underlying LOAD pathology earlier in the lifespan. OBJECTIVE: In this study, we leveraged longitudinal data from the Wisconsin Registry for Alzheimer's Prevention and explored changing patterns in cognition and biomarkers at various age points along six biological pathways. METHODS: PRS and p-PRSs with and without APOE were constructed separately based on the significant SNPs associated with LOAD in a recent genome-wide association study meta-analysis and compared to APOE alone. We used a linear mixed-effects model to assess the association between PRS/p-PRSs and cognitive trajectories among 1,175 individuals. We also applied the model to the outcomes of cerebrospinal fluid biomarkers in a subset. Replication analyses were performed in an independent sample. RESULTS: We found p-PRSs and the overall PRS can predict preclinical changes in cognition and biomarkers. The effects of PRS/p-PRSs on rate of change in cognition, amyloid-β, and tau outcomes are dependent on age and appear earlier in the lifespan when APOE is included in these risk scores compared to when APOE is excluded. CONCLUSION: In addition to APOE, the p-PRSs can predict age-dependent changes in amyloid-β, tau, and cognition. Once validated, they could be used to identify individuals with an elevated genetic risk of accumulating amyloid-β and tau, long before the onset of clinical symptoms.

Emerging Roles of Meningeal Lymphatic Vessels in Alzheimer's Disease. - Guo, Xiaodi; Zhang, Guoxin; Peng, Qinyu; Huang, Liqin; Zhang, Zhaohui; Zhang, Zhentao (J Alzheimers Dis, 2023)
Meningeal lymphatic vessels (mLVs), the functional lymphatic system present in the meninges, are the key drainage route responsible for the clearance of molecules, immune cells, and cellular debris from the cerebrospinal fluid and interstitial fluid into deep cervical lymph nodes. Aging and ApoE4, the two most important risk factors for Alzheimer's disease (AD), induce mLV dysfunction, decrease cerebrospinal fluid influx and outflux, and exacerbate amyloid pathology and cognitive dysfunction. Dysfunction of mLVs results in the deposition of metabolic products, accelerates neuroinflammation, and promotes the release of pro-inflammatory cytokines in the brain. Thus, mLVs represent a novel therapeutic target for treating neurodegenerative and neuroinflammatory diseases. This review aims to summarize the structure and function of mLVs and to discuss the potential effect of aging and ApoE4 on mLV dysfunction, as well as their roles in the pathogenesis of AD.
Keywords: Alzheimer Disease; Apolipoprotein E4; Glymphatic System; Humans; Lymphatic System; Lymphatic Vessels

Excessive Sedentary Time Is Associated with Cognitive Decline in Older Patients with Minor Ischemic Stroke. - Liang, Hongtao; Yin, Xiang; Chen, Tian; Zhang, Yan; Zhang, Qin; Lin, Jie; Yin, Huan; Tang, Jinghua; He, Yingyi; Xia, Ping; Zhu, Yongping; Li, Haihua; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Cognitive impairment is commonly seen after acute ischemic stroke (AIS). Sedentary behaviors increase the risk of dementia among community dwelling population. OBJECTIVE: This study aims to investigate the association of sedentary behaviors with poststroke cognitive impairment among older adults of minor AIS. METHODS: This cohort study recruited 594 older subjects with minor AIS from three hospitals in China during February 1, 2016, and December 31, 2018. Participants were followed up for two years and the sedentary time per day was self-reported at the endpoint of follow-up. Cognitive functions were assessed by Mini-Mental State Examination (MMSE). Participants were categorized into the high and low sedentary time group according to the median sedentary time of the participants. RESULTS: At two years of follow-up, the long sedentary time group had significantly lower MMSE scores than the short sedentary time group [median, (95% CI): 21 (18 to 25) versus 22 (18 to 25), p = 0.368]. The long sedentary time group had a higher speed of cognitive decline than the short sedentary time group. Excessive sedentary time was associated with a higher risk of longitudinal cognitive decline (OR: 2.267, 95% CI: 1.594 to 3.225), adjusting for age, sex, education, body mass index, APOE genotype, comorbidities, symptoms of depression, anxiety, and insomnia, baseline MMSE scores and National Institute of Health Stroke Scale scores, cognitive therapy, and TOAST ischemic stroke subtypes. CONCLUSIONS: This study identified a possible link between sedentary behaviors and longitudinal cognitive decline among older patients with minor AIS, suggesting that reducing sedentary time might be helpful for preventing poststroke dementia.

Genome-Wide Mapping Implicates 5-Hydroxymethylcytosines in Diabetes Mellitus and Alzheimer's Disease. - Beadell, Alana V; Zhang, Zhou; Capuano, Ana W; Bennett, David A; He, Chuan; Zhang, Wei; Arvanitakis, Zoe (J Alzheimers Dis, 2023)
BACKGROUND: Diabetes mellitus (DM) is a recognized risk factor for dementia. Because DM is a potentially modifiable condition, greater understanding of the mechanisms linking DM to the clinical expression of Alzheimer's disease dementia may provide insights into much needed dementia therapeutics. OBJECTIVE: In this feasibility study, we investigated DM as a dementia risk factor by examining genome-wide distributions of the epigenetic DNA modification 5-hydroxymethylcytosine (5hmC). METHODS: We obtained clinical samples from the Rush Memory and Aging Project and used the highly sensitive 5hmC-Seal technique to perform genome-wide profiling of 5hmC in circulating cell-free DNA (cfDNA) from antemortem serum samples and in genomic DNA from postmortem prefrontal cortex brain tissue from 80 individuals across four groups: Alzheimer's disease neuropathologically defined (AD), DM clinically defined, AD with DM, and individuals with neither disease (controls). RESULTS: Distinct 5hmC signatures and biological pathways were enriched in persons with both AD and DM versus AD alone, DM alone, or controls, including genes inhibited by EGFR signaling in oligodendroglia and those activated by constitutive RHOA. We also demonstrate the potential diagnostic value of 5hmC profiling in circulating cfDNA. Specifically, an 11-gene weighted model distinguished AD from non-AD/non-DM controls (AUC = 91.8% ; 95% CI, 82.9-100.0%), while a 4-gene model distinguished DM-associated AD from AD alone (AUC = 87.9% ; 95% CI, 77.5-98.3%). CONCLUSION: We demonstrate in this small sample the feasibility of detecting and characterizing 5hmC in DM-associated AD and of using 5hmC information contained in circulating cfDNA to detect AD in high-risk individuals, such as those with diabetes.

Helicobacter pylori Infection Is Associated with Long-Term Cognitive Decline in Older Adults: A Two-Year Follow-Up Study. - Wang, Jian; Yu, Neng-Wei; Wang, Duo-Zi; Guo, Lei; Yang, Shu; Zheng, Bo; Guo, Fu-Qiang; Wang, Jian-Hong (J Alzheimers Dis, 2023)
BACKGROUND: Previous cross-sectional studies have identified a possible link between Helicobacter pylori (H. pylori) infection and dementia. However, the association of H. pylori infection with longitudinal cognitive decline has rarely been investigated. OBJECTIVE: This cohort study aims to demonstrate the effects of H. pylori infection on longitudinal cognitive decline. METHODS: This cohort study recruited 268 subjects with memory complaints. Among these subjects, 72 had a history of H. pylori infection, and the rest 196 subjects had no H. pylori infection. These subjects were followed up for 24 months and received cognitive assessment in fixed intervals of 12 months. RESULTS: At baseline, H. pylori infected, and uninfected participants had no difference in MMSE scores. At 2 years of follow-up, H. pylori infected participants had lower MMSE scores than uninfected participants. H. pylori infection was associated with an increased risk of longitudinal cognitive decline, as defined by a decrease of MMSE of 3 points or more during follow-up, adjusting for age, sex, education, APOEɛ4 genotype, hypertension, diabetes, hyperlipidemia, and smoking history (HR: 2.701; 95% CI: 1.392 to 5.242). H. pylori infection was associated with larger cognitive decline during follow-up, adjusting for the above covariates (standardized coefficient: 0.282, p < 0.001). Furthermore, H. pylori infected subjects had significantly higher speed of cognitive decline than uninfected subjects during follow-up, adjusting for the above covariates. CONCLUSION: H. pylori infection increases the risk of longitudinal cognitive decline in older subjects with memory complaints. This study is helpful for further understanding the association between infection and dementia.

Hypermethylation at CREBBP Is Associated with Cognitive Impairment in a Mexican American Cohort. - Abraham Daniel, Ann; Silzer, Talisa; Sun, Jie; Zhou, Zhengyang; Hall, Courtney; Phillips, Nicole; Barber, Robert (J Alzheimers Dis, 2023)
BACKGROUND: The aging Mexican American (MA) population is the fastest growing ethnic minority group in the US. MAs have a unique metabolic-related risk for Alzheimer's disease (AD) and mild cognitive impairment (MCI), compared to non-Hispanic whites (NHW). This risk for cognitive impairment (CI) is multifactorial involving genetics, environmental, and lifestyle factors. Changes in environment and lifestyle can alter patterns and even possibly reverse derangement of DNA methylation (a form of epigenetic regulation). OBJECTIVE: We sought to identify ethnicity-specific DNA methylation profiles that may be associated with CI in MAs and NHWs. METHODS: DNA obtained from peripheral blood of 551 participants from the Texas Alzheimer's Research and Care Consortium was typed on the Illumina Infinium® MethylationEPIC chip array, which assesses over 850K CpG genomic sites. Within each ethnic group (N = 299 MAs, N = 252 NHWs), participants were stratified by cognitive status (control versus CI). Beta values, representing relative degree of methylation, were normalized using the Beta MIxture Quantile dilation method and assessed for differential methylation using the Chip Analysis Methylation Pipeline (ChAMP), limma and cate packages in R. RESULTS: Two differentially methylated sites were significant: cg13135255 (MAs) and cg27002303 (NHWs) based on an FDR p < 0.05. Three suggestive sites obtained were cg01887506 (MAs) and cg10607142 and cg13529380 (NHWs). Most methylation sites were hypermethylated in CI compared to controls, except cg13529380 which was hypomethylated. CONCLUSION: The strongest association with CI was at cg13135255 (FDR-adjusted p = 0.029 in MAs), within the CREBBP gene. Moving forward, identifying additional ethnicity-specific methylation sites may be useful to discern CI risk in MAs.

Ketogenic Diet as a Promising Non-Drug Intervention for Alzheimer's Disease: Mechanisms and Clinical Implications. - Xu, Yunlong; Zheng, Fuxiang; Zhong, Qi; Zhu, Yingjie (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is mainly characterized by cognitive deficits. Although many studies have been devoted to developing disease-modifying therapies, there has been no effective therapy until now. However, dietary interventions may be a potential strategy to treat AD. The ketogenic diet (KD) is a high-fat and low-carbohydrate diet with adequate protein. KD increases the levels of ketone bodies, providing an alternative energy source when there is not sufficient energy supply because of impaired glucose metabolism. Accumulating preclinical and clinical studies have shown that a KD is beneficial to AD. The potential underlying mechanisms include improved mitochondrial function, optimization of gut microbiota composition, and reduced neuroinflammation and oxidative stress. The review provides an update on clinical and preclinical research on the effects of KD or medium-chain triglyceride supplementation on symptoms and pathophysiology in AD. We also detail the potential mechanisms of KD, involving amyloid and tau proteins, neuroinflammation, gut microbiota, oxidative stress, and brain metabolism. We aimed to determine the function of the KD in AD and outline important aspects of the mechanism, providing a reference for the implementation of the KD as a potential therapeutic strategy for AD.
Keywords: Alzheimer Disease; Brain; Diet, Ketogenic; Humans; Ketone Bodies; Neuroinflammatory Diseases

Landscape of Double-Stranded DNA Breaks in Postmortem Brains from Alzheimer's Disease and Non-Demented Individuals. - Zhang, Xiaoyu; Liu, Yan; Huang, Ming; Gunewardena, Sumedha; Haeri, Mohammad; Swerdlow, Russell H; Wang, Ning (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) brains accumulate DNA double-strand breaks (DSBs), which could contribute to neurodegeneration and dysfunction. The genomic distribution of AD brain DSBs is unclear. OBJECTIVE: To map genome-wide DSB distributions in AD and age-matched control brains. METHODS: We obtained autopsy brain tissue from 3 AD and 3 age-matched control individuals. The donors were men between the ages of 78 to 91. Nuclei extracted from frontal cortex tissue were subjected to Cleavage Under Targets & Release Using Nuclease (CUT&RUN) assay with an antibody against γH2AX, a marker of DSB formation. γH2AX-enriched chromatins were purified and analyzed via high-throughput genomic sequencing. RESULTS: The AD brains contained 18 times more DSBs than the control brains and the pattern of AD DSBs differed from the control brain pattern. In conjunction with published genome, epigenome, and transcriptome analyses, our data revealed aberrant DSB formation correlates with AD-associated single-nucleotide polymorphisms, increased chromatin accessibility, and upregulated gene expression. CONCLUSION: To our knowledge, this study is the first to characterize the AD brain DSB landscape. Our data suggest in AD, an accumulation of DSBs at ectopic genomic loci could contribute to an aberrant upregulation of gene expression.

Mediation Effect of Brain Volume on the Relationship Between Peripheral Inflammation and Cognitive Decline. - Zhuo, Bingting; Zheng, Dashan; Cai, Miao; Wang, Chongjian; Zhang, Shiyu; Zhang, Zilong; Tian, Fei; Wang, Xiaojie; Lin, Hualiang (J Alzheimers Dis, 2023)
BACKGROUND: Studies have reported the associations between inflammation, brain volume, and cognition separately. It is reasonable to assume peripheral inflammation may contribute to cognitive decline through brain volume atrophy. OBJECTIVE: To examine the associations between peripheral inflammation, brain volume, and cognition among adults, and to investigate whether brain volume atrophy mediates the inflammation-cognition relationshipMethods:We retrieved 20,381 participants with available data on peripheral inflammation, brain volume, and cognition from the UK Biobank cohort. Cognitive function was assessed by performance on cognitive tasks probing various cognitive domains. Brain volumes were measured by magnetic resonance imaging (MRI). Multivariable linear models were used to investigate the associations between three peripheral inflammatory indexes (C-reactive protein, systemic immune-inflammatory index, neutrophil-to-lymphocyte ratio), brain volume, and cognition. Mediation analyses were conducted to assess the potential mediating effect of brain volume atrophy. All results were corrected for multiple comparisons using the false-discovery rate (FDR). RESULTS: Peripheral inflammation was inversely associated with grey matter volume (GMV), white matter volume (WMV), and cognition after adjusting for potential covariates. For instance, CRP was associated with the GMV of left parahippocampal gyrus (β= -0.05, 95% confidence interval [CI]: -0.06 to -0.04, pFDR =1.07×10-16) and general cognitive factor (β= -0.03, 95% CI: -0. -0.04 to -0.01, pFDR = 0.001). Brain volume atrophy mediated the inflammation-cognitive decline relationship, accounting for 15-29% of the overall impact. CONCLUSION: In this cohort study, peripheral inflammation was associated with brain volume atrophy and cognitive decline. Brain atrophy may mediate the inflammation-cognitive decline relationship.
Keywords: Atrophy; Brain; Cognition; Cognitive Dysfunction; Cohort Studies; Encephalitis; Humans; Inflammation; Magnetic Resonance Imaging

Microglia-Mediated Neurovascular Unit Dysfunction in Alzheimer's Disease. - Huang, Wenhao; Xia, Qing; Zheng, Feifei; Zhao, Xue; Ge, Fangliang; Xiao, Jiaying; Liu, Zijie; Shen, Yingying; Ye, Ke; Wang, Dayong; Li, Yanze (J Alzheimers Dis, 2023)
The neurovascular unit (NVU) is involved in the pathological changes in Alzheimer's disease (AD). The NVU is a structural and functional complex that maintains microenvironmental homeostasis and metabolic balance in the central nervous system. As one of the most important components of the NVU, microglia not only induce blood-brain barrier breakdown by promoting neuroinflammation, the infiltration of peripheral white blood cells and oxidative stress but also mediate neurovascular uncoupling by inducing mitochondrial dysfunction in neurons, abnormal contraction of cerebral vessels, and pericyte loss in AD. In addition, microglia-mediated dysfunction of cellular components in the NVU, such as astrocytes and pericytes, can destroy the integrity of the NVU and lead to NVU impairment. Therefore, we review the mechanisms of microglia-mediated NVU dysfunction in AD. Furthermore, existing therapeutic advancements aimed at restoring the function of microglia and the NVU in AD are discussed. Finally, we predict the role of pericytes in microglia-mediated NVU dysfunction in AD is the hotspot in the future.
Keywords: Alzheimer Disease; Astrocytes; Blood-Brain Barrier; Humans; Microglia; Neurons

Multi-Site Cross-Site Inter-Rater and Test-Retest Reliability and Construct Validity of the MarkVCID White Matter Hyperintensity Growth and Regression Protocol. - Bahrani, Ahmed A; Abner, Erin L; DeCarli, Charles S; Barber, Justin M; Sutton, Abigail C; Maillard, Pauline; Sandoval, Francisco; Arfanakis, Konstantinos; Yang, Yung-Chuan; Evia, Arnold M; Schneider, Julie A; Habes, Mohamad; et al. (J Alzheimers Dis, 2023)
BACKGROUND: White matter hyperintensities (WMH) that occur in the setting of vascular cognitive impairment and dementia (VCID) may be dynamic increasing or decreasing volumes or stable over time. Quantifying such changes may prove useful as a biomarker for clinical trials designed to address vascular cognitive-impairment and dementia and Alzheimer's Disease. OBJECTIVE: Conducting multi-site cross-site inter-rater and test-retest reliability of the MarkVCID white matter hyperintensity growth and regression protocol. METHODS: The NINDS-supported MarkVCID Consortium evaluated a neuroimaging biomarker developed to track WMH change. Test-retest and cross-site inter-rater reliability of the protocol were assessed. Cognitive test scores were analyzed in relation to WMH changes to explore its construct validity. RESULTS: ICC values for test-retest reliability of WMH growth and regression were 0.969 and 0.937 respectively, while for cross-site inter-rater ICC values for WMH growth and regression were 0.995 and 0.990 respectively. Word list long-delay free-recall was negatively associated with WMH growth (p < 0.028) but was not associated with WMH regression. CONCLUSIONS: The present data demonstrate robust ICC validity of a WMH growth/regression protocol over a one-year period as measured by cross-site inter-rater and test-retest reliability. These data suggest that this approach may serve an important role in clinical trials of disease-modifying agents for VCID that may preferentially affect WMH growth, stability, or regression.

Necroptosis and Alzheimer's Disease: Pathogenic Mechanisms and Therapeutic Opportunities. - Zhang, Ruxin; Song, Yanrong; Su, Xuefeng (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is considered to be the most common neurodegenerative disease, with clinical symptoms encompassing progressive memory loss and cognitive impairment. Necroptosis is a form of programmed necrosis that promotes cell death and neuroinflammation, which further mediates the pathogenesis of several neurodegenerative diseases, especially AD. Current evidence has strongly suggested that necroptosis is activated in AD brains, resulting in neuronal death and cognitive impairment. We searched the PubMed database, screening all articles published before September 28, 2022 related to necroptosis in the context of AD pathology. The keywords in the search included: "necroptosis", "Alzheimer's disease", "signaling pathways", "Aβ", Aβo", "Tau", "p-Tau", "neuronal death", "BBB damage", "neuroinflammation", "microglia", "mitochondrial dysfunction", "granulovacuolar degeneration", "synaptic loss", "axonal degeneration", "Nec-1", "Nec-1s", "GSK872", "NSA", "OGA", "RIPK1", "RIPK3", and "MLKL". Results show that necroptosis has been involved in multiple pathological processes of AD, including amyloid-β aggregation, Tau accumulation, neuronal death, and blood-brain barrier damage, etc. More importantly, existing research on AD necroptosis interventions, including drug intervention and potential gene targets, as well as its current clinical development status, was discussed. Finally, the issues pertaining to necroptosis in AD were presented. Accordingly, this review may provide further insight into clinical perspectives and challenges for the future treatment of AD by targeting the necroptosis pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apoptosis; Humans; Necrosis; Neurodegenerative Diseases

Non-Pharmacological Interventions for Feeding and Eating Disorders in Persons with Dementia: Systematic Review and Evidence Summary. - Chen, Hong-Li; Li, Cheng; Wang, Jing; Fei, Yang; Min, Min; Zhao, Yue; Shan, En-Fang; Yin, Yue-Heng; Liu, Chong-Yuan; Li, Xian-Wen (J Alzheimers Dis, 2023)
BACKGROUND: Feeding and eating disorders related to cognitive and psycho-behavioral symptoms are strongly associated with health status in persons with dementia (PWD). Non-pharmacological interventions have been the priority selection to address this significant issue. However, the direct targets of non-pharmacological interventions are unclear and there is no consistent evidence of recommendations on the intervention of different dementia stages and the settings of intervention practice. OBJECTIVE: To provide caregivers with a set of self-help non-pharmacological interventions for feeding and eating disorders in PWD. METHODS: Based on the process of evidence summary, a systematic literature search was performed on dementia websites and seven databases. Two researchers screened the studies independently and appraise the quality. The evidence was graded by Joanna Briggs Institute Grades of Recommendation. RESULTS: Twenty-eight articles were included. Twenty-three non-pharmacological intervention recommendations were categorized into six themes containing oral nutritional supplementation, assistance with eating and drinking, person-centered mealtime care, environmental modification, education or training, and multi-component intervention. These interventions corresponded to three direct targets including improving engagement, making up for loss ability, and increasing food intake directly. They were applied to different stages of dementia and most interventions were targeted at PWD in long-term care institutions. CONCLUSION: This article summarized the direct targets and the specific implementation of recommendations at different stages of dementia to provide caregivers with self-help non-pharmacological interventions. The practice of recommendations was more applicable to institutionalized PWD. When applied to PWD at home, caregivers need to identify the specific feeding and eating conditions at different stages and adopted the interventions in conjunction with the wishes of the PWD and professional advice.
Keywords: Caregivers; Dementia; Feeding and Eating Disorders; Health Status; Humans; Nutritional Status

A Novel Strategy for Alzheimer's Disease Based on the Regulatory Effect of Amyloid-β on Gut Flora. - Huang, Li; Lu, Zhaogang; Zhang, Hexin; Wen, Hongyong; Li, Zongji; Liu, Qibing; Wang, Rui (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is one of the most common neurodegenerative diseases worldwide. The accumulation of amyloid-β (Aβ) protein and plaque formation in the brain are two major causes of AD. Interestingly, growing evidence demonstrates that the gut flora can alleviate AD by affecting amyloid production and metabolism. However, the underlying mechanism remains largely unknown. This review will discuss the possible association between the gut flora and Aβ in an attempt to provide novel therapeutic directions for AD treatment based on the regulatory effect of Aβ on the gut flora.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidogenic Proteins; Brain; Gastrointestinal Microbiome; Humans

Pathogenesis, Animal Models, and Drug Discovery of Alzheimer's Disease. - Xia, Zhao-Di; Ma, Ruo-Xin; Wen, Jin-Feng; Zhai, Yu-Fei; Wang, Yu-Qi; Wang, Feng-Yun; Liu, Dan; Zhao, Xiao-Long; Sun, Bao; Jia, Pu; Zheng, Xiao-Hui (J Alzheimers Dis, 2023)
Alzheimer's disease (AD), the most common cause of dementia, is a chronic neurodegenerative disease induced by multiple factors. The high incidence and the aging of the global population make it a growing global health concern with huge implications for individuals and society. The clinical manifestations are progressive cognitive dysfunction and lack of behavioral ability, which not only seriously affect the health and quality of life of the elderly, but also bring a heavy burden to the family and society. Unfortunately, almost all the drugs targeting the classical pathogenesis have not achieved satisfactory clinical effects in the past two decades. Therefore, the present review provides more novel ideas on the complex pathophysiological mechanisms of AD, including classical pathogenesis and a variety of possible pathogenesis that have been proposed in recent years. It will be helpful to find out the key target and the effect pathway of potential drugs and mechanisms for the prevention and treatment of AD. In addition, the common animal models in AD research are outlined and we examine their prospect for the future. Finally, Phase I, II, III, and IV randomized clinical trials or on the market of drugs for AD treatment were searched in online databases (Drug Bank Online 5.0, the U.S. National Library of Medicine, and Alzforum). Therefore, this review may also provide useful information in the research and development of new AD-based drugs.
Keywords: Alzheimer Disease; Animals; Drug Discovery; Models, Animal; Neurodegenerative Diseases; Quality of Life

Poor Oral Health as a Risk Factor for Dementia in a Swedish Population: A Cohort Study with 40 Years of Follow-Up. - He, Fei; Luo, Huizi; Yin, Li; Roosaar, Ann; Axéll, Tony; Zhao, Hongwei; Ye, Weimin (J Alzheimers Dis, 2023)
BACKGROUND: Whether poor oral health is associated with dementia risk remains unclear. OBJECTIVE: We conducted a cohort study of 14,439 participants who were followed up for up to 40 years in Uppsala County, central Sweden, aiming to explore the association between poor oral health, namely the number of tooth loss, dental plaque status, and oral mucosal lesions, and the risk of dementia. METHODS: We used Cox proportional hazards regression model to derive cause-specific hazard ratios (HR) and corresponding 95% confidence intervals (CI), while adjusting for baseline potential confounders as well as a time-varying covariate, Charlson's Comorbidity Index score. RESULTS: Dementia risk was substantially higher among those with a higher number of tooth loss; compared to the group with tooth loss 0-10, the HRs were 1.21 (95% CI: 1.02, 1.42), 1.17 (95% CI: 0.97, 1.40), and 1.30 (95% CI: 1.09, 1.54) respectively for groups with increasing number of tooth loss. There was some evidence of dose-risk association in this study, with a HR of 1.10 (1.04, 1.18) comparing adjacent groups (ptrend = 0.001). In a stratified analysis by attained age, tooth loss was more pronouncedly associated with the risk of dementia onset before age 80 (those with 21-32 versus 0-10 lost teeth, HR = 1.82, (95% CI: 1.32, 2.51); HR = 1.22 (95% CI: 1.10, 1.35) comparing adjacent groups, ptrend < 0.001). CONCLUSION: In summary, there are some indications that poor oral health, as indicated by more tooth loss, is positively associated with an increased risk of dementia, especially for dementia onset before age 80.
Keywords: Aged, 80 and over; Cohort Studies; Dementia; Follow-Up Studies; Humans; Oral Health; Risk Factors; Sweden; Tooth Loss

Proteome Network Analysis Identifies Potential Biomarkers for Brain Aging. - Short, Meghan I; Fohner, Alison E; Skjellegrind, Håvard K; Beiser, Alexa; Gonzales, Mitzi M; Satizabal, Claudia L; Austin, Thomas R; Longstreth, W T; Bis, Joshua C; Lopez, Oscar; Hveem, Kristian; Selbæk, Geir; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease and related dementias (ADRD) involve biological processes that begin years to decades before onset of clinical symptoms. The plasma proteome can offer insight into brain aging and risk of incident dementia among cognitively healthy adults. OBJECTIVE: To identify biomarkers and biological pathways associated with neuroimaging measures and incident dementia in two large community-based cohorts by applying a correlation-based network analysis to the plasma proteome. METHODS: Weighted co-expression network analysis of 1,305 plasma proteins identified four modules of co-expressed proteins, which were related to MRI brain volumes and risk of incident dementia over a median 20-year follow-up in Framingham Heart Study (FHS) Offspring cohort participants (n = 1,861). Analyses were replicated in the Cardiovascular Health Study (CHS) (n = 2,117, mean 6-year follow-up). RESULTS: Two proteomic modules, one related to protein clearance and synaptic maintenance (M2) and a second to inflammation (M4), were associated with total brain volume in FHS (M2: p = 0.014; M4: p = 4.2×10-5). These modules were not significantly associated with hippocampal volume, white matter hyperintensities, or incident all-cause or AD dementia. Associations with TCBV did not replicate in CHS, an older cohort with a greater burden of comorbidities. CONCLUSIONS: Proteome networks implicate an early role for biological pathways involving inflammation and synaptic function in preclinical brain atrophy, with implications for clinical dementia.

Racial/Ethnic Disparities in Misidentification of Dementia in Medicare Claims: Results from the Washington Heights-Inwood Columbia Aging Project. - Zhu, Carolyn W; Gu, Yian; Cosentino, Stephanie; Kociolek, Anton J; Hernandez, Michelle; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: Misidentification of dementia in Medicare claims is quite common. OBJECTIVE: We examined potential race/ethnic disparities in misidentification of dementia in Medicare claims in a diverse cohort of older adults who underwent careful clinical assessment. METHODS: Participants were enrolled the Washington Heights-Inwood Columbia Aging Project (WHICAP), a multiethnic, population-based, prospective study of cognitive aging in which dementia status was assessed using a rigorous clinical protocol. ICD-9-CM and ICD-10-CM diagnosis codes in all available Medicare claims (1999-2019) were compared to clinical dementia diagnosis and categorized into three mutually exclusive groups: 1) congruent-, 2) over-, and 3) under- identification during the study period. Multinomial logistic regression model was used to examine the relationship between race (White, African American/Black, other) and ethnicity (Hispanic/Latinx, non-Hispanic/Latinx) and congruency of dementia identification after controlling for clinical (cognition, function, comorbidities) and demographic characteristics (age, sex, education), and inpatient and outpatient utilization. RESULTS: Across all person-years, 88.4% had congruent identification of dementia compared to clinical diagnosis, in 4.1% of the times participants were over-identified with dementia, and 7.5% of the times the participants were under-identified. Rates of misidentification was higher in minority participants than in White, non-Hispanic participants. Multivariable estimation results showed that the probability of over-identification with dementia was 2.2% higher for African American/Black than White (p = 0.05) and 2.7% higher for Hispanic participants than non-Hispanics (p = 0.03) participants. Differences in under-identification by race/ethnicity were not statistically significant. CONCLUSIONS: African American/Black and Hispanic participants were more likely over-identified with dementia in Medicare claims.

Refining Risk for Alzheimer's Disease Among Heterozygous APOEɛ4 Carriers. - Patel, Smita; Wei, Jun; Shi, Zhuqing; Rifkin, Andrew S; Zheng, S Lilly; Gelfman, Elizabeth; Duggan, David; Helfand, Brian T; Hulick, Peter J; Xu, Jianfeng (J Alzheimers Dis, 2023)
In a large population-based cohort, we show not all heterozygous APOEɛ4 carriers are at increased risk for Alzheimer's disease (AD); a significantly higher AD proportion was only found for ɛ3/ɛ4, not ɛ2/ɛ4. Among ɛ3/ɛ4 carriers (24% in the cohort), the AD proportion differed considerably by polygenic risk score (PRS). In particular, the AD proportion was lower than the entire cohort for subjects in the bottom 20-percentile PRS and was higher than that of homozygous ɛ4 carriers for subjects at the top 5th-percentile PRS. Family history was no longer a significant predictor of AD risk after adjusting APOE and PRS.
Keywords: Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Heterozygote; Homozygote; Humans

The Role of Interferon-α in Neurodegenerative Diseases: A Systematic Review. - Hui, Brendan Su Mee; Zhi, Lee Rui; Retinasamy, Thaarvena; Arulsamy, Alina; Law, Christine Shing Wei; Shaikh, Mohd Farooq; Yeong, Keng Yoon (J Alzheimers Dis, 2023)
BACKGROUND: Neurodegenerative diseases (NDs) impose significant financial and healthcare burden on populations all over the world. The prevalence and incidence of NDs have been observed to increase dramatically with age. Hence, the number of reported cases is projected to increase in the future, as life spans continues to rise. Despite this, there is limited effective treatment against most NDs. Interferons (IFNs), a family of cytokines, have been suggested as a promising therapeutic target for NDs, particularly IFN-α, which governs various pathological pathways in different NDs. OBJECTIVE: This systematic review aimed to critically appraise the currently available literature on the pathological role of IFN-α in neurodegeneration/NDs. METHODS: Three databases, Scopus, PubMed, and Ovid Medline, were utilized for the literature search. RESULTS: A total of 77 journal articles were selected for critical evaluation, based on the inclusion and exclusion criteria. The studies selected and elucidated in this current systematic review have showed that IFN-α may play a deleterious role in neurodegenerative diseases through its strong association with the inflammatory processes resulting in mainly neurocognitive impairments. IFN-α may be displaying its neurotoxic function via various mechanisms such as abnormal calcium mineralization, activation of STAT1-dependent mechanisms, and increased quinolinic acid production. CONCLUSION: The exact role IFN-α in these neurodegenerative diseases have yet to be determine due to a lack in more recent evidence, thereby creating a variability in the role of IFN-α. Future investigations should thus be conducted, so that the role played by IFN-α in neurodegenerative diseases could be delineated.
Keywords: Cytokines; Databases, Factual; Humans; Interferon-alpha; Neurodegenerative Diseases

Senescent Microglia Represent a Subset of Disease-Associated Microglia in P301S Mice. - Ng, Pei Y; Zhang, Cheng; Li, Hu; Baker, Darren J (J Alzheimers Dis, 2023)
BACKGROUND: The existence and contribution of microglia with senescent-like alterations in the pathogenesis of age-related neurodegenerative diseases like Alzheimer's disease (AD) have been suggested in recent years. However, the identification of this distinct microglial population in vivo has proven challenging, largely due to overlaps in the inflammatory phenotype of activated and senescent microglia. Furthermore, attempts at recapitulating senescence in microglia in vitro are limited. OBJECTIVE: To identify and characterize senescent microglia that occur in vivo in an animal model of neurodegeneration driven by pathologic tau. METHODS: We analyzed the RNA expression patterns of individual microglia from normal mice and the pathogenic tau P301 S PS19 mouse model. We have previously demonstrated that p16-expressing senescent microglia occur in these mice when neurodegeneration has occurred. RESULTS: Here we identify a subset of disease-associated microglia with senescent features, notably characterized by the expression of Ccl4. This signature overlaps with established markers of senescence from other cell types. CONCLUSION: Our characterization of senescent microglia can be used to better understand the role of senescent microglia in various age-related contexts, including whether clearance of senescent microglia represents a viable therapeutic option.

Soluble TREM2, Alzheimer's Disease Pathology, and Risk for Progression of Cerebral Small Vessel Disease: A Longitudinal Study. - Wu, Chao; Ma, Ya-Hui; Hu, Hao; Zhao, Bing; Tan, Lan (J Alzheimers Dis, 2023)
BackgroundUntil recently, studies on associations between neuroinflammation in vivo and cerebral small vessel disease (CSVD) are scarce. Cerebrospinal fluid (CSF) levels of soluble triggering receptor expressed on myeloid cells 2 (sTREM2), a candidate biomarker of microglial activation and neuroinflammation, were found elevated in Alzheimer's disease (AD), but they have not been fully explored in CSVD.ObjectiveTo determine whether CSF sTREM2 levels are associated with the increased risk of CSVD progression.MethodsA total of 426 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database were included in this study. All participants underwent measurements of CSF sTREM2 and AD pathology (Aβ1-42, P-tau181P). The progression of CSVD burden and imaging markers, including cerebral microbleeds (CMBs), white matter hyperintensities and lacunes, were estimated based on neuroimaging changes. Logistic regression and moderation effect models were applied to explore associations of sTREM2 with CSVD progression and AD pathology.Results Higher CSF sTREM2 levels at baseline were associated with increased CSVD burden (OR = 1.28 [95% CI, 1.01-1.62]) and CMBs counts (OR = 1.32 [95% CI, 1.03-1.68]). Similarly, increased change rates of CSF sTREM2 might predict elevated CMBs counts (OR = 1.44 [95% CI, 1.05-1.98]). Participants with AD pathology (Aβ1-42 and P-tau181P) showed a stronger association between CSF sTREM2 and CSVD progression.ConclusionThis longitudinal study found a positive association between CSF sTREM2 and CSVD progression, suggesting that neuroinflammation might promote CSVD. Furthermore, neuroinflammation could be a shared pathogenesis of CSVD and AD at the early stage. Targeting neuroinflammation to intervene the progression of CSVD and AD warrants further investigation.
Keywords: Alzheimer Disease; Biomarkers; Cerebral Small Vessel Diseases; Humans; Longitudinal Studies; Membrane Glycoproteins; Myeloid Cells; Neuroinflammatory Diseases; Receptors, Immunologic

Timing of Alzheimer's Disease by Intellectual Disability Level in Down Syndrome. - Hartley, Sigan L; Fleming, Victoria; Schworer, Emily K; Peven, Jamie; Handen, Benjamin L; Krinsky-McHale, Sharon; Hom, Christy; Lee, Laisze; Tudorascu, Dana L; Laymon, Charles; Minhas, Davneet; Luo, Weiquan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Trisomy 21 causes Down syndrome (DS) and is a recognized cause of early-onset Alzheimer's disease (AD). OBJECTIVE: The current study sought to determine if premorbid intellectual disability level (ID) was associated with variability in age-trajectories of AD biomarkers and cognitive impairments. General linear mixed models compared the age-trajectory of the AD biomarkers PET Aβ and tau and cognitive decline across premorbid ID levels (mild, moderate, and severe/profound), in models controlling trisomy type, APOE status, biological sex, and site. METHODS: Analyses involved adults with DS from the Alzheimer's Biomarkers Consortium-Down Syndrome. Participants completed measures of memory, mental status, and visuospatial ability. Premorbid ID level was based on IQ or mental age scores prior to dementia concerns. PET was acquired using [11C] PiB for Aβ, and [18F] AV-1451 for tau. RESULTS: Cognitive data was available for 361 participants with a mean age of 45.22 (SD = 9.92) and PET biomarker data was available for 154 participants. There was not a significant effect of premorbid ID level by age on cognitive outcomes. There was not a significant effect of premorbid ID by age on PET Aβ or on tau PET. There was not a significant difference in age at time of study visit of those with mild cognitive impairment-DS or dementia by premorbid ID level. CONCLUSION: Findings provide robust evidence of a similar time course in AD trajectory across premorbid ID levels, laying the groundwork for the inclusion of individuals with DS with a variety of IQ levels in clinical AD trials.

Two-Year Changes in Physical Activity and Concurrent Changes in Cognitive Function in a Cohort of Adults with Metabolic Syndrome. - Rognoni, Teresa; Fernández-Matarrubia, Marta; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Castañer, Olga; Martínez, J Alfredo; Alonso-Gómez, Ángel M; Gómez-Gracia, Enrique; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: It has been proposed that physical activity (PA) could prevent cognitive decline. OBJECTIVE: To evaluate the association between changes in PA and changes in cognitive function in a cohort of adults with metabolic syndrome. METHODS: Longitudinal observational study including 5,500 adults (mean age 65 years, SD = 5; women = 49.3%) with metabolic syndrome. Participants underwent physical activity measurements and cognitive evaluation at baseline and at two-years of follow-up. PA was quantified using the Minnesota questionnaire-shortened version. Cognitive function was evaluated using a battery of tests: Mini-Mental Test Examination, Clock Drawing Test, Trail Making Test A and B, Verbal Fluency Test, and Digit Span. The primary outcome was change in cognition at two-year follow-up, as measured through the Global Composite Score (GCS) of all neuropsychological tests. Multivariable-adjusted linear regression models were fitted with baseline PA and their changes as the main exposures and changes in cognitive function as the outcome. RESULTS: No significant association was found between PA levels (or their changes) and changes in cognitive function, as measured by the GCS. A greater increase in PA levels was associated with a more favorable two-year change in performance on the Trail Making Test A (Q4 versus Q1: b = -2.15, 95% CI -4.25 to -0.05; p-trend = 0.024). No significant association was found for other neuropsychological test. CONCLUSION: Our results do not support an association between increases in PA and the evolution of the global cognitive function at two-year follow-up, but they suggested a possible beneficial effect of PA on attentional function in older adults.

Validation of a Multivariate Prediction Model of the Clinical Progression of Alzheimer's Disease in a Community-Dwelling Multiethnic Cohort. - Stallard, Eric; Kociolek, Anton; Jin, Zhezhen; Ryu, Hyunnam; Lee, Seonjoo; Cosentino, Stephanie; Zhu, Carolyn; Gu, Yian; Fernandez, Kayri; Hernandez, Michelle; Kinosian, Bruce; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: The major aims of the three Predictors Studies have been to further our understanding of Alzheimer's disease (AD) progression sufficiently to predict the length of time from disease onset to major disease outcomes in individual patients with AD. OBJECTIVES: To validate a longitudinal Grade of Membership (L-GoM) prediction algorithm developed using clinic-based, mainly white patients from the Predictors 2 Study in a statistically representative community-based sample of Hispanic (N = 211) and non-Hispanic (N = 62) older adults (with 60 males and 213 females) from the Predictors 3 Study and extend the algorithm to mild cognitive impairment (MCI). METHODS: The L-GoM model was applied to data collected at the initial Predictors 3 visit for 150 subjects with AD and 123 with MCI. Participants were followed annually for up to seven years. Observed rates of survival and need for full-time care (FTC) were compared to those predicted by the algorithm. RESULTS: Initial MCI/AD severity in Predictors 3 was substantially higher than among clinic-based AD patients enrolled at the specialized Alzheimer's centers in Predictors 2. The observed survival and need for FTC followed the L-GoM model trajectories in individuals with MCI or AD, except for N = 32 subjects who were initially diagnosed with AD but reverted to a non-AD diagnosis on follow-up. CONCLUSION: These findings indicate that the L-GoM model is applicable to community-dwelling, multiethnic older adults with AD. They extend the use of the model to the prediction of outcomes for MCI. They also justify release of our L-GoM calculator at this time.

5-Hydroxymethylcytosine Signatures in Circulating Cell-Free DNA as Diagnostic Biomarkers for Late-Onset Alzheimer's Disease. - Chen, Lei; Shen, Qianqian; Xu, Shunliang; Yu, Hongzhuan; Pei, Shengjie; Zhang, Yangting; He, Xin; Wang, QiuZhen; Li, Duo (J Alzheimers Dis, 2022)
BACKGROUND: 5-Hydroxymethylcytosine (5hmC) is an epigenetic DNA modification that is highly abundant in central nervous system. It has been reported that DNA 5hmC dysregulation play a critical role in Alzheimer's disease (AD) pathology. Changes in 5hmC signatures can be detected in circulating cell-free DNA (cfDNA), which has shown potential as a non-invasive liquid biopsy material. OBJECTIVE: However, the genome-wide profiling of 5hmC in cfDNA and its potential for the diagnosis of AD has not been reported to date. METHODS: We carried out a case-control study and used a genome-wide chemical capture followed by high-throughput sequencing to detect the genome-wide profiles of 5hmC in human cfDNA and identified differentially hydroxymethylated regions (DhMRs) in late-onset AD patients and the control. RESULTS: We discovered significant differences of 5hmC enrichment in gene bodies which were linked to multiple AD pathogenesis-associated signaling pathways in AD patients compared with cognitively normal controls, indicating they can be well distinguished from normal controls by DhMRs in cfDNA. Specially, we identified 7 distinct genes (RABEP1, CPNE4, DNAJC15, REEP3, ROR1, CAMK1D, and RBFOX1) with predicting diagnostic potential based on their significant correlations with MMSE and MoCA scores of subjects. CONCLUSION: The present results suggest that 5hmC markers derived from plasma cfDNA can served as an effective, minimally invasive biomarkers for clinical auxiliary diagnosis of late-onset AD.
Keywords: 5-Methylcytosine; Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cell-Free Nucleic Acids; DNA Methylation; DNA, Neoplasm; Epigenesis, Genetic; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged

Anticholinergic Drug Burden and Neurocognitive Performance in the Study of Latinos-Investigation of Neurocognitive Aging. - Posis, Alexander Ivan B; Tarraf, Wassim; Gonzalez, Kevin A; Soria-Lopez, Jose A; Léger, Gabriel C; Stickel, Ariana M; Daviglus, Martha L; Lamar, Melissa; Zeng, Donglin; González, Hector M (J Alzheimers Dis, 2022)
BACKGROUND: Studies of cumulative anticholinergic drug burden on cognitive function and impairment are emerging, yet few for Hispanics/Latinos. OBJECTIVE: To examine associations between anticholinergic use and neurocognitive performance outcomes among diverse Hispanics/Latinos. METHODS: This prospective cohort study included diverse Hispanic/Latino participants, enrolled in the Study of Latinos-Investigation of Neurocognitive, from New York, Chicago, Miami, and San Diego (n = 6,249). Survey linear regression examined associations between anticholinergic use (measured during baseline [Visit 1] and average 7-year follow up [Visit 2]) with global cognition, episodic learning, memory, phonemic fluency, processing speed, executive functioning, and average 7-year change. RESULTS: Anticholinergic use was associated with lower cognitive global cognition (β= -0.21; 95% CI [-0.36; -0.05]), learning (β= -0.27; 95% CI [-0.47; -0.07]), memory (β= -0.22; 95% CI [-0.41; -0.03]), and executive functioning (β= -0.22; 95% CI [-0.40; -0.03]) scores, particularly among those who took anticholinergics at both visits. Anticholinergic use was associated with faster decline in global cognition, learning, and verbal fluency (β: -0.28 [95% CI: -0.55, -0.01]; β: -0.28 [95% CI: -0.55, -0.01]; β: -0.25, [95% CI -0.47, -0.04], respectively). Sex modified associations between anticholinergic use with global cognition, learning, and executive functioning (F3 = 3.59, F3 = 2.84, F3 = 3.88, respectively). CONCLUSION: Anticholinergic use was associated with lower neurocognitive performance, especially among those who used anticholinergics at both visits, among a study population of diverse Hispanics/Latinos. Findings will support evidence-based decisions regarding anticholinergic prescriptions and efforts to minimize cognitive impact.

Association Between High Serum Tetrahydrofolate and Low Cognitive Functions in the United States: A Cross-Sectional Study. - Fan, Yaohua; Liu, Wen; Chen, Si; Li, Mengzhu; Zhao, Lijun; Wu, Chunxiao; Liu, Helu; Zhu, Meiling (J Alzheimers Dis, 2022)
BACKGROUND: The relationship between serum folate status and cognitive functions is still controversial. OBJECTIVE: To evaluate the association between serum tetrahydrofolate and cognitive functions. METHODS: A total of 3,132 participants (60-80 years old) from the 2011-2014 NHANES were included in this cross-sectional study. The primary outcome measure was cognitive function assessment, determined by the Consortium to Establish a Registry for Alzheimer's Disease Word Learning Test (CERAD-WL), CERAD-Delayed Recall Test (CERAD-DR), Animal Fluency Test (AF), Digit Symbol Substitution Test (DSST), and global cognitive score. Generalized linear model (GLM), multivariate logistic regression models, weighted generalized additive models (GAM), and subgroup analyses were performed to evaluate the association between serum tetrahydrofolate and low cognitive functions. RESULTS: In GLM, and the crude model, model 1, model 2 of multivariate logistic regression models, increased serum tetrahydrofolate was associated with reduced cognitive functions via AF, DSST, CERAD-WL, CERAD-DR, and global cognitive score (p <  0.05). In GAM, the inflection points were 1.1, 2.8, and 2.8 nmol/L tetrahydrofolate, determined by a two-piece wise linear regression model of AF, DSST, and global cognitive score, respectively. Also, in GAM, there were no non-linear relationship between serum tetrahydrofolate and low cognitive functions, as determined by CERAD-WL or CERAD-DR. The results of subgroup analyses found that serum tetrahydrofolate levels and reduced cognitive functions as determined by AF had significant interactions for age and body mass index. The association between high serum tetrahydrofolate level and reduced cognitive functions as determined using DSST, CERAD-WL, CERAD-DR, or global cognitive score had no interaction with the associations between cognition and gender, or age, or so on. CONCLUSION: High serum tetrahydrofolate level is associated with significantly reduced cognitive function.

Association Between Serum Vitamins and the Risk of Alzheimer's Disease in Chinese Population. - Liu, Xi-Xi; Wu, Peng-Fei; Liu, Ying-Zi; Jiang, Ya-Ling; Wan, Mei-Dan; Xiao, Xue-Wen; Yang, Qi-Jie; Jiao, Bin; Liao, Xin-Xin; Wang, Jun-Ling; Liu, Shao-Hui; Zhang, Xuewei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is a chronic and fatal neurodegenerative disease; accumulating evidence suggests that vitamin deficiency is associated with the risk of AD. However, studies attempting to elucidate the relationship between vitamins and AD varied widely. OBJECTIVE: This study aimed to investigate the relationship between serum vitamin levels and AD in a cohort of the Chinese population. METHODS: A total of 368 AD patients and 574 healthy controls were recruited in this study; serum vitamin A, B1, B6, B9, B12, C, D, and E were measured in all participants. RESULTS: Compared with the controls, vitamin B2, B9, B12, D, and E were significantly reduced in AD patients. Lower levels of vitamin B2, B9, B12, D, and E were associated with the risk of AD. After adjusting for age and gender, low levels of vitamin B2, B9, and B12 were still related to the risk of AD. In addition, a negative correlation was determined between vitamin E concentration and Activity of Daily Living Scale score while no significant association was found between serum vitamins and age at onset, disease duration, Mini-Mental State Examination, and Neuropsychiatric Inventory Questionnaire score. CONCLUSION: We conclude that lower vitamin B2, B9, B12, D, and E might be associated with the risk of AD, especially vitamin B2, B9, and B12. And lower vitamin E might be related to severe ability impairment of daily activities.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Case-Control Studies; China; Female; Folic Acid; Humans; Logistic Models; Male; Mental Status and Dementia Tests; Middle Aged; Riboflavin; Risk; Vitamin B 12; Vitamin D; Vitamin E

Better Subjective Sleep Quality Partly Explains the Association Between Self-Reported Physical Activity and Better Cognitive Function. - Cheval, Boris; Maltagliati, Silvio; Sieber, Stefan; Cullati, Stéphane; Zou, Liye; Ihle, Andreas; Kramer, Arthur F; Yu, Qian; Sander, David; Boisgontier, Matthieu P (J Alzheimers Dis, 2022)
BACKGROUND: Physical activity has been associated with better cognitive function and better sleep quality. Yet, whether the beneficial effect of physical activity on cognitive function can be explained by an indirect pathway involving better sleep quality is unclear. OBJECTIVE: To investigate whether sleep quality mediates the association between physical activity and cognitive function in adults 50 years of age or older. METHODS: 86,541 community-dwelling European adults were included in the study. Physical activity and sleep quality were self-reported. Indicators of cognitive function (immediate recall, delayed recall, verbal fluency) were assessed using objective tests. All measures were collected six times between 2004 and 2017. The mediation was tested using multilevel mediation analyses. RESULTS: Results showed that self-reported physical activity was associated with better self-reported sleep quality, which was associated with better performance in all three indicators of cognitive function, demonstrating an indirect effect of physical activity on cognitive function through sleep quality. The mediating effect of sleep quality accounted for 0.41%, 1.46%, and 8.88% of the total association of physical activity with verbal fluency, immediate recall, and delayed recall, respectively. CONCLUSION: These findings suggest that self-reported sleep quality partly mediates the association between self-reported physical activity and cognitive function. These results need to be confirmed by device-based data of physical activity and sleep quality.
Keywords: Cognition; Exercise; Humans; Self Report; Sleep; Sleep Quality

Bifidobacterium breve MCC1274 Supplementation Increased the Plasma Levels of Metabolites with Potential Anti-Oxidative Activity in APP Knock-In Mice. - Ohno, Kazuya; Abdelhamid, Mona; Zhou, Chunyu; Jung, Cha-Gyun; Michikawa, Makoto (J Alzheimers Dis, 2022)
BACKGROUND: We previously reported the effects of a probiotic strain, Bifidobacterium breve MCC1274, in improving cognitive function in preclinical and clinical studies. Recently, we demonstrated that supplementation of this strain led to decreased amyloid-β production, attenuated microglial activation, and suppressed inflammation reaction in the brain of APP knock-in (AppNL - G - F) mice. OBJECTIVE: In this study, we investigated the plasma metabolites to reveal the mechanism of action of this probiotic strain in this Alzheimer's disease (AD)-like model. METHODS: Three-month-old mice were orally supplemented with B. breve MCC1274 or saline for four months and their plasma metabolites were comprehensively analyzed using CE-FTMS and LC-TOFMS. RESULTS: Principal component analysis showed a significant difference in the plasma metabolites between the probiotic and control groups (PERMANOVA, p = 0.03). The levels of soy isoflavones (e.g., genistein) and indole derivatives of tryptophan (e.g., 5-methoxyindoleacetic acid), metabolites with potent anti-oxidative activities were significantly increased in the probiotic group. Moreover, there were increased levels of glutathione-related metabolites (e.g., glutathione (GSSG)_divalent, ophthalmic acid) and TCA cycle-related metabolites (e.g., 2-Oxoglutaric acid, succinic acid levels) in the probiotic group. Similar alternations were observed in the wild-type mice by the probiotic supplementation. CONCLUSION: These results suggest that the supplementation of B. breve MCC1274 enhanced the bioavailability of potential anti-oxidative metabolites from the gut and addressed critical gaps in our understanding of the gut-brain axis underlying the mechanisms of the probiotic action of this strain in the improvement of cognitive function.

Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease Display Altered Key Protein Levels Including Cell Type-Specific Markers. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Rajapaksha, Harinda; Routenberg, David A; Nagaraj, Rajini; Redding, Javier; Arab, Tanina; Powell, Bonita H; Pletniková, Olga; Troncoso, Juan C; Zheng, Lei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Brain tissue-derived extracellular vesicles (bdEVs) play neurodegenerative and protective roles, including in Alzheimer's disease (AD). Extracellular vesicles (EVs) may also leave the brain to betray the state of the CNS in the periphery. Only a few studies have profiled the proteome of bdEVs and source brain tissue. Additionally, studies focusing on bdEV cell type-specific surface markers are rare. OBJECTIVE: We aimed to reveal the pathological mechanisms inside the brain by profiling the tissue and bdEV proteomes in AD patients. In addition, to indicate targets for capturing and molecular profiling of bdEVs in the periphery, CNS cell-specific markers were profiled on the intact bdEV surface. METHODS: bdEVs were separated and followed by EV counting and sizing. Brain tissue and bdEVs from age-matched AD patients and controls were then proteomically profiled. Total tau (t-tau), phosphorylated tau (p-tau), and antioxidant peroxiredoxins (PRDX) 1 and 6 were measured by immunoassay in an independent bdEV separation. Neuron, microglia, astrocyte, and endothelia markers were detected on intact EVs by multiplexed ELISA. RESULTS: Overall, concentration of recovered bdEVs was not affected by AD. Proteome differences between AD and control were more pronounced for bdEVs than for brain tissue. Levels of t-tau, p-tau, PRDX1, and PRDX6 were significantly elevated in AD bdEVs compared with controls. Release of certain cell-specific bdEV markers was increased in AD. CONCLUSION: Several bdEV proteins are involved in AD mechanisms and may be used for disease monitoring. The identified CNS cell markers may be useful tools for peripheral bdEV capture.

Cerebral Volumetric Correlates of Apathy in Alzheimer's Disease and Cognitively Normal Older Adults: Meta-Analysis, Label-Based Review, and Study of an Independent Cohort. - Chaudhary, Shefali; Zhornitsky, Simon; Chao, Herta H; van Dyck, Christopher H; Li, Chiang-Shan R (J Alzheimers Dis, 2022)
BACKGROUND: Affecting nearly half of the patients with Alzheimer's disease (AD), apathy is associated with higher morbidity and reduced quality of life. Basal ganglia and cortical atrophy have been implicated in apathy. However, the findings have varied across studies and left unclear whether subdomains of apathy may involve distinct neuroanatomical correlates. OBJECTIVE: To identify neuroanatomical correlates of AD-associated apathy. METHODS: We performed a meta-analysis and label-based review of the literature. Further, following published routines of voxel-based morphometry, we aimed to confirm the findings in an independent cohort of 19 patients with AD/mild cognitive impairment and 25 healthy controls assessed with the Apathy Evaluation Scale. RESULTS: Meta-analysis of 167 AD and 56 healthy controls showed convergence toward smaller basal ganglia gray matter volume (GMV) in apathy. Label-based review showed anterior cingulate, putamen, insula, inferior frontal gyrus (IFG) and middle temporal gyrus (MTG) atrophy in AD apathy. In the independent cohort, with small-volume-correction, right putamen and MTG showed GMVs in negative correlation with Apathy Evaluation Scale total, behavioral, and emotional scores, and right IFG with emotional score (p < 0.05 family-wise error (FWE)-corrected), controlling for age, education, intracranial volume, and depression. With the Mini-Mental State Examination scores included as an additional covariate, the correlation of right putamen GMV with behavioral and emotional score, right MTG GMV with total and emotional score, and right IFG GMV with emotional score were significant. CONCLUSION: The findings implicate putamen, MTG and IFG atrophy in AD associated apathy, potentially independent of cognitive impairment and depression, and suggest potentially distinct volumetric correlates of apathy.
Keywords: Aged; Alzheimer Disease; Apathy; Atrophy; Basal Ganglia; Brain; Cognitive Dysfunction; Cohort Studies; Gray Matter; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Prefrontal Cortex

Cerebrospinal Fluid Sphingomyelins in Alzheimer's Disease, Neurodegeneration, and Neuroinflammation. - Morrow, Autumn; Panyard, Daniel J; Deming, Yuetiva K; Jonaitis, Erin; Dong, Ruocheng; Vasiljevic, Eva; Betthauser, Tobey J; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Bayfield, Anna; Van Hulle, Carol A; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Sphingomyelin (SM) levels have been associated with Alzheimer's disease (AD), but the association direction has been inconsistent and research on cerebrospinal fluid (CSF) SMs has been limited by sample size, breadth of SMs examined, and diversity of biomarkers available. OBJECTIVE: Here, we seek to build on our understanding of the role of SM metabolites in AD by studying a broad range of CSF SMs and biomarkers of AD, neurodegeneration, and neuroinflammation. METHODS: Leveraging two longitudinal AD cohorts with metabolome-wide CSF metabolomics data (n = 502), we analyzed the relationship between the levels of 12 CSF SMs, and AD diagnosis and biomarkers of pathology, neurodegeneration, and neuroinflammation using logistic, linear, and linear mixed effects models. RESULTS: No SMs were significantly associated with AD diagnosis, mild cognitive impairment, or amyloid biomarkers. Phosphorylated tau, neurofilament light, α-synuclein, neurogranin, soluble triggering receptor expressed on myeloid cells 2, and chitinase-3-like-protein 1 were each significantly, positively associated with at least 5 of the SMs. CONCLUSION: The associations between SMs and biomarkers of neurodegeneration and neuroinflammation, but not biomarkers of amyloid or diagnosis of AD, point to SMs as potential biomarkers for neurodegeneration and neuroinflammation that may not be AD-specific.

The Correlation of Tau Levels with Blood Monocyte Count in Patients with Alzheimer's Disease. - Sun, Hao-Lun; Zhou, Fa-Ying; Chen, Dong-Wan; Tan, Cheng-Rong; Zeng, Gui-Hua; Liu, Yu-Hui; Wang, Jun; Bu, Xian-Le; Wang, Yan-Jiang; Li, Hui-Yun; Jin, Wang-Sheng (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies have shown that monocytes can phagocytize the tau protein, which may ameliorate tau-type pathology in Alzheimer's disease (AD). However, there are few clinical studies on the relationship between monocytes and tau-type pathology in AD patients. OBJECTIVE: We aimed to explore changes in peripheral monocytes and their association with tau protein in AD patients. METHODS: A total of 127 clinically diagnosed AD patients and 100 age- and sex-matched cognitively normal controls were recruited for analysis of the correlation of plasma tau levels with the blood monocyte count. Cerebrospinal fluid (CSF) samples from 46 AD patients and 88 controls were further collected to analyze the correlation of CSF tau and amyloid-β (Aβ) levels with the blood monocyte count. 105 clinically diagnosed mild cognitive impairment (MCI) patients and 149 age- and sex-matched cognitively normal controls were recruited from another cohort for verification. RESULTS: Compared to normal controls, AD patients showed a significant reduction in the blood monocyte count. In addition, the monocyte count of AD patients was negatively correlated with CSF t-tau and p-tau levels but not with plasma tau levels. In normal people, monocyte count lack correlation with tau levels both in plasma and CSF. Monocyte count were not correlated with CSF Aβ levels in either group but were negatively correlated with CSF tau/Aβ42 levels in the AD group. We had further verified the correlations of monocyte count with CSF tau levels in another cohort. CONCLUSION: This study suggests that monocytes may play an important role in the clearance of tau protein in the brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Cohort Studies; Female; Humans; Male; Monocytes; tau Proteins

Detecting Alzheimer's Disease Using Natural Language Processing of Referential Communication Task Transcripts. - Liu, Ziming; Paek, Eun Jin; Yoon, Si On; Casenhiser, Devin; Zhou, Wenjun; Zhao, Xiaopeng (J Alzheimers Dis, 2022)
BACKGROUND: People with Alzheimer's disease (AD) often demonstrate difficulties in discourse production. Referential communication tasks (RCTs) are used to examine a speaker's capability to select and verbally code the characteristics of an object in interactive conversation. OBJECTIVE: In this study, we used contextualized word representations from Natural language processing (NLP) to evaluate how well RCTs are able to distinguish between people with AD and cognitively healthy older adults. METHODS: We adapted machine learning techniques to analyze manually transcribed speech transcripts in an RCT from 28 older adults, including 12 with AD and 16 cognitively healthy older adults. Two approaches were applied to classify these speech transcript samples: 1) using clinically relevant linguistic features, 2) using machine learned representations derived by a state-of-art pretrained NLP transfer learning model, Bidirectional Encoder Representation from Transformer (BERT) based classification model. RESULTS: The results demonstrated the superior performance of AD detection using a designed transfer learning NLP algorithm. Moreover, the analysis showed that transcripts of a single image yielded high accuracies in AD detection. CONCLUSION: The results indicated that RCT may be useful as a diagnostic tool for AD, and that the task can be simplified to a subset of images without significant sacrifice to diagnostic accuracy, which can make RCT an easier and more practical tool for AD diagnosis. The results also demonstrate the potential of RCT as a tool to better understand cognitive deficits from the perspective of discourse production in people with AD.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Communication; Humans; Natural Language Processing; Speech

Evaluation of the Accuracy of Cognitive Screening Tests in Detecting Dementia Associated with Alzheimer's Disease: A Hierarchical Bayesian Latent Class Meta-Analysis. - Wang, Xiaonan; Li, Fengjie; Gao, Qi; Jiang, Zhen; Abudusaimaiti, Xiayidanmu; Yao, Jiangyue; Zhu, Huiping (J Alzheimers Dis, 2022)
BACKGROUND: Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) are neuropsychological tests commonly used by physicians for screening cognitive dysfunction of Alzheimer's disease (AD). Due to different imperfect reference standards, the performance of MoCA and MMSE do not reach consensus. It is necessary to evaluate the consistence and differentiation of MoCA and MMSE in the absence of a gold standard for AD. OBJECTIVE: We aimed to assess the accuracy of MoCA and MMSE in screening AD without a gold standard reference test. METHODS: Studies were identified from PubMed, Web of Science, CNKI, Chinese Wanfang Database, China Science and Technology Journal Database, and Cochrane Library. Our search was limited to studies published in English and Chinese before August 2021. A hierarchical Bayesian latent class model was performed in meta-analysis when the gold standard was absent. RESULTS: A total of 67 studies comprising 5,554 individuals evaluated for MoCA and 76,862 for MMSE were included in this meta-analysis. The pooled sensitivity was 0.934 (95% CI 0.905 to 0.954) for MoCA and 0.883 (95% CI 0.859 to 0.903) for MMSE, while the pooled specificity was 0.899 (95% CI 0.859 to 0.928) for MoCA and 0.903 (95% CI 0.879 to 0.923) for MMSE. MoCA was useful to rule out dementia associated with AD with lower negative likelihood ratio (LR-) (0.074, 95% CI 0.051 to 0.108). MoCA showed better performance with higher diagnostic odds ratio (DOR) (124.903, 95% CI 67.459 to 231.260). CONCLUSION: MoCA had better performance than MMSE in screening dementia associated with AD from patients with mild cognitive impairment or healthy controls.
Keywords: Alzheimer Disease; Bayes Theorem; Cognition; Cognitive Dysfunction; Humans; Mental Status and Dementia Tests; Neuropsychological Tests

Evoked Cortical Depolarizations Before and After the Amyloid Plaque Accumulation: Voltage Imaging Study. - Zhu, Mei Hong; Jogdand, Aditi H; Jang, Jinyoung; Nagella, Sai C; Das, Brati; Milosevic, Milena M; Yan, Riqiang; Antic, Srdjan D (J Alzheimers Dis, 2022)
BACKGROUND: In Alzheimer's disease (AD), synaptic dysfunction is thought to occur many years before the onset of cognitive decline. OBJECTIVE: Detecting synaptic dysfunctions at the earliest stage of AD would be desirable in both clinic and research settings. METHODS: Population voltage imaging allows monitoring of synaptic depolarizations, to which calcium imaging is relatively blind. We developed an AD mouse model (APPswe/PS1dE9 background) expressing a genetically-encoded voltage indicator (GEVI) in the neocortex. GEVI was restricted to the excitatory pyramidal neurons (unlike the voltage-sensitive dyes). RESULTS: Expression of GEVI did not disrupt AD model formation of amyloid plaques. GEVI expression was stable in both AD model mice and Control (healthy) littermates (CTRL) over 247 days postnatal. Brain slices were stimulated in layer 2/3. From the evoked voltage waveforms, we extracted several parameters for comparison AD versus CTRL. Some parameters (e.g., temporal summation, refractoriness, and peak latency) were weak predictors, while other parameters (e.g., signal amplitude, attenuation with distance, and duration (half-width) of the evoked transients) were stronger predictors of the AD condition. Around postnatal age 150 days (P150) and especially at P200, synaptically-evoked voltage signals in brain slices were weaker in the AD groups versus the age- and sex-matched CTRL groups, suggesting an AD-mediated synaptic weakening that coincides with the accumulation of plaques. However, at the youngest ages examined, P40 and P80, the AD groups showed differentially stronger signals, suggesting "hyperexcitability" prior to the formation of plaques. CONCLUSION: Our results indicate bidirectional alterations in cortical physiology in AD model mice; occurring both prior (P40-80), and after (P150-200) the amyloid deposition.

Excretion of Amyloid-β in the Gastrointestinal Tract and Regulation by the Gut Microbiota. - Wu, Shijing; Hu, Li; Lin, Jiajing; Li, Kanglan; Ye, Shicai; Zhu, Shaoping; Liu, Zhou (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) is important in the etiology of Alzheimer's disease (AD). Removal of Aβ from the brain is a major strategy for the prevention and treatment of AD. OBJECTIVE: To clarify whether Aβ 42 can be cleared by intestinal excretion and whether the gut microbiota (GM) can affect the excretory clearance of Aβ 42 in the peripheral blood and intestines. METHODS: Male 8-month-old C57BL6 mice were maintained on either normal chow or received broad-spectrum antibiotics in their drinking water for one week. Sterile saline, fluorescein isothiocyanate (FITC), or FITC-Aβ 42 (fluorescein isothiocyanate-labeled amyloid-β 42 peptides) was injected 1 h before FITC, or FITC-Aβ 42 was injected 1 h before sampling. Related changes of Aβ 42 before and after injection were evaluated. RESULTS: FITC-Aβ 42 was injected into mice through the tail vein and could later be detected in feces. Furthermore, the fecal concentrations of FITC-Aβ 42 were higher in mice that had been fed antibiotics to alter their GM than in normal mice. However, the FITC-Aβ 42 concentrations in blood showed the opposite pattern. CONCLUSION: Aβ 42 can be excreted into the intestinal lumen and is regulated by the GM.

HMGCS2-Induced Autophagic Degradation of Tau Involves Ketone Body and ANKRD24. - Hu, Li-Tian; Xie, Xiao-Yong; Zhou, Gui-Feng; Wen, Qi-Xin; Song, Li; Luo, Biao; Deng, Xiao-Juan; Pan, Qiu-Ling; Chen, Guo-Jun (J Alzheimers Dis, 2022)
BACKGROUND: Accumulation of hyperphosphorylated Tau (pTau) contributes to the formation of neurofibrillary tangles in Alzheimer's disease (AD), and targeting Tau/pTau metabolism has emerged as a therapeutic approach. We have previously reported that mitochondrial 3-hydroxy-3-methylglutaryl-COA synthase 2 (HMGCS2) is involved in AD by promoting autophagic clearance of amyloid-β protein precursor via ketone body-associated mechanism, whether HMGCS2 may also regulate Tau metabolism remains elusive. OBJECTIVE: The present study was to investigate the role of HMGCS2 in Tau/p degradation. METHODS: The protein levels of Tau and pTau including pT217 and pT181, as well as autophagic markers LAMP1 and LC3-II were assessed by western blotting. The differentially regulated genes by HMGCS2 were analyzed by RNA sequencing. Autophagosomes were assessed by transmission electron microscopy. RESULTS: HMGCS2 significantly decreased Tau/pTau levels, which was paralleled by enhanced formation of autophagic vacuoles and prevented by autophagic regulators chloroquine, bafilomycin A1, 3-methyladenine, and rapamycin. Moreover, HMGCS2-induced alterations of LAMP1/LC3-II and Tau/pTau levels were mimicked by ketone body acetoacetate or β-hydroxybutyrate. Further RNA-sequencing identified ankyrin repeat domain 24 (ANKRD24) as a target gene of HMGCS2, and silencing of ANKRD24 reduced LAMP1/LC3-II levels, which was accompanied by the altered formation of autophagic vacuoles, and diminished the effect of HMGCS2 on Tau/pTau. CONCLUSION: HMGCS2 promoted autophagic clearance of Tau/pTau, in which ketone body and ANKRD24 played an important role.

Impaired Experience-Dependent Refinement of Place Cells in a Rat Model of Alzheimer's Disease. - Broussard, John I; Redell, John B; Maynard, Mark E; Zhao, Jing; Moore, Anthony; Mills, Rachel W; Hood, Kimberly N; Underwood, Erica; Roysam, Badrinath; Dash, Pramod K (J Alzheimers Dis, 2022)
BACKGROUND: Hippocampal place cells play an integral role in generating spatial maps. Impaired spatial memory is a characteristic pathology of Alzheimer's disease (AD), yet it remains unclear how AD influences the properties of hippocampal place cells. OBJECTIVE: To record electrophysiological activity in hippocampal CA1 neurons in freely-moving 18-month-old male TgF344-AD and age-matched wild-type (WT) littermates to examine place cell properties. METHODS: We implanted 32-channel electrode arrays into the CA1 subfield of 18-month-old male WT and TgF344-AD (n = 6/group) rats. Ten days after implantation, single unit activity in an open field arena was recorded across days. The spatial information content, in-field firing rate, and stability of each place cell was compared across groups. Pathology was assessed by immunohistochemical staining, and a deep neural network approach was used to count cell profiles. RESULTS: Aged TgF344-AD rats exhibited hippocampal amyloid-β deposition, and a significant increase in Iba1 immunoreactivity and microglia cell counts. Place cells from WT and TgF344-AD rat showed equivalent spatial information, in-field firing rates, and place field stability when initially exposed to the arena. However, by day 3, the place cells in aged WT rats showed characteristic spatial tuning as evidenced by higher spatial information content, stability, and in-field firing rates, an effect not seen in TgF344-AD rats. CONCLUSION: These findings support the notion that altered electrophysiological properties of place cells may contribute to the learning and memory deficits observed in AD.

Improved Prediction of Amyloid-β and Tau Burden Using Hippocampal Surface Multivariate Morphometry Statistics and Sparse Coding. - Wu, Jianfeng; Su, Yi; Zhu, Wenhui; Jalili Mallak, Negar; Lepore, Natasha; Reiman, Eric M; Caselli, Richard J; Thompson, Paul M; Chen, Kewei; Wang, Yalin (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) plaques and tau protein tangles in the brain are the defining 'A' and 'T' hallmarks of Alzheimer's disease (AD), and together with structural atrophy detectable on brain magnetic resonance imaging (MRI) scans as one of the neurodegenerative ('N') biomarkers comprise the "ATN framework" of AD. Current methods to detect Aβ/tau pathology include cerebrospinal fluid (invasive), positron emission tomography (PET; costly and not widely available), and blood-based biomarkers (promising but mainly still in development). OBJECTIVE: To develop a non-invasive and widely available structural MRI-based framework to quantitatively predict the amyloid and tau measurements. METHODS: With MRI-based hippocampal multivariate morphometry statistics (MMS) features, we apply our Patch Analysis-based Surface Correntropy-induced Sparse coding and max-pooling (PASCS-MP) method combined with the ridge regression model to individual amyloid/tau measure prediction. RESULTS: We evaluate our framework on amyloid PET/MRI and tau PET/MRI datasets from the Alzheimer's Disease Neuroimaging Initiative. Each subject has one pair consisting of a PET image and MRI scan, collected at about the same time. Experimental results suggest that amyloid/tau measurements predicted with our PASCP-MP representations are closer to the real values than the measures derived from other approaches, such as hippocampal surface area, volume, and shape morphometry features based on spherical harmonics. CONCLUSION: The MMS-based PASCP-MP is an efficient tool that can bridge hippocampal atrophy with amyloid and tau pathology and thus help assess disease burden, progression, and treatment effects.

Investigating Casual Associations Among Gut Microbiota, Metabolites, and Neurodegenerative Diseases: A Mendelian Randomization Study. - Ning, Jing; Huang, Shu-Yi; Chen, Shi-Dong; Zhang, Ya-Ru; Huang, Yu-Yuan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies had explored that gut microbiota was associated with neurodegenerative diseases (including Alzheimer's disease (AD), Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS)) through the gut-brain axis, among which metabolic pathways played an important role. However, the underlying causality remained unclear. OBJECTIVE: Our study aimed to evaluate potential causal relationships between gut microbiota, metabolites, and neurodegenerative diseases through Mendelian randomization (MR) approach. METHODS: We selected genetic variants associated with gut microbiota traits (N = 18,340) and gut microbiota-derived metabolites (N = 7,824) from genome-wide association studies. Summary statistics of neurodegenerative diseases were obtained from IGAP (AD, 17,008 cases; 37,154 controls), IPDGC (PD, 37,688 cases; 141,779 controls), and IALSC (ALS, 20,806 cases; 59,804 controls) respectively. RESULTS: Greater abundance of Ruminococcus (OR, 1.245; 95% CI, 1.103-1.405; p = 0.0004) was found significantly related to higher risk of ALS. Besides, our study found suggestive associations of Actinobacteria, Lactobacillaceae, Faecalibacterium, Ruminiclostridium, and Lachnoclostridium with AD, of Lentisphaerae, Lentisphaeria, Oxalobacteraceae, Victivallales, Bacillales, Eubacteriumhalliigroup, Anaerostipes, and Clostridiumsensustricto1 with PD, and of Lachnospira, Fusicatenibacter, Catenibacterium, and Ruminococcusgnavusgroup with ALS. Our study also revealed suggestive associations between 12 gut microbiome-dependent metabolites and neurodegenerative diseases. Glutamine was related to lower risk of AD. For the serotonin pathway, serotonin was found as a protective factor of PD, while kynurenine as a risk factor for ALS. CONCLUSION: Our study firstly applied a two-sample MR approach to detect causal relationships among gut microbiota, gut metabolites, and neurodegenerative diseases. Our findings may provide new targets for treatments and may offer valuable insights for further studies on the underlying mechanisms.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Gastrointestinal Microbiome; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Neurodegenerative Diseases; Parkinson Disease; Risk Factors; Serotonin

Investigating Causal Relations Between Circulating Metabolites and Alzheimer's Disease: A Mendelian Randomization Study. - Huang, Shu-Yi; Yang, Yu-Xiang; Zhang, Ya-Ru; Kuo, Kevin; Li, Hong-Qi; Shen, Xue-Ning; Chen, Shi-Dong; Chen, Ke-Liang; Dong, Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: Metabolomics is a promising approach that can be used to understand pathophysiological pathways of Alzheimer's disease (AD). However, the causal relationships between metabolism and AD are poorly understood. OBJECTIVE: We aimed to investigate the causal association between circulating metabolites and risk of AD through two-sample Mendelian randomization (MR) approach. METHODS: Genetic associations with 123 circulating metabolic traits were utilized as exposures. Summary statistics data from International Genomics of Alzheimer's Project was used in primary analysis, including 21,982 AD cases and 41,944 controls. Validation was performed using family history of AD data from UK Biobank (27,696 cases of maternal AD, 14,338 cases of paternal AD, and 272,244 controls). We utilized inverse-variance weighted method as primary method. RESULTS: We found significantly increased risks of developing AD per standard deviation increase in the levels of circulating ApoB (odd ratio[OR] = 3.18; 95% confidence interval[CI]: 1.52-6.66, p = 0.0022), glycoprotein acetyls (OR = 1.21; 95% CI: 1.05-1.39, p = 0.0093), total cholesterol (OR = 2.73; 95% CI: 1.41-5.30, p = 0.0030), and low-density lipoprotein (LDL) cholesterol (OR = 2.34; 95% CI: 1.53-3.57, p = 0.0001). Whereas glutamine (OR = 0.81; 95% CI: 0.71-0.92, p = 0.0011) were significantly associated with lower risk of AD. We also detected causal effects of several different composition of LDL fractions on increased AD risk, which has been verified in validation. However, we found no association between circulating high-density lipoprotein cholesterol and AD. CONCLUSION: Our findings suggest causal effects of circulating glycoprotein acetyls, ApoB, LDL cholesterol, and serum total cholesterol on higher risk of AD, whereas glutamine showed the protective effect.
Keywords: Alzheimer Disease; Apolipoproteins B; Cholesterol; Genome-Wide Association Study; Glutamine; Humans; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Risk Factors

Low-Dose Radiation Therapy Reduces Amyloid Load in Young 3xTg-AD Mice. - Ceyzériat, Kelly; Tournier, Benjamin B; Millet, Philippe; Dipasquale, Giovanna; Koutsouvelis, Nikolaos; Frisoni, Giovanni B; Garibotto, Valentina; Zilli, Thomas (J Alzheimers Dis, 2022)
BACKGROUND: Low-dose radiation therapy (LD-RT) has been shown to decrease amyloidosis or inflammation in systemic diseases and has recently been proposed as possible treatment of Alzheimer's disease (AD). A positive effect of LD-RT on tauopathy, the other marker of AD, has also been suggested. These effects have been shown in preclinical studies, but their mechanisms are still not well understood. OBJECTIVE: This study aimed to evaluate if anti-amyloid and anti-inflammatory effects of LD-RT can be observed at an early stage of the disease. Its impact on tauopathy and behavioral alterations was also investigated. METHODS: The whole brain of 12-month-old 3xTg-AD mice was irradiated with 10 Gy in 5 daily fractions of 2 Gy. Mice underwent behavioral tests before and 8 weeks post treatment. Amyloid load, tauopathy, and neuroinflammation were measured using histology and/or ELISA. RESULTS: Compared with wild-type animals, 3xTg-AD mice showed a moderate amyloid and tau pathology restricted to the hippocampus, a glial reactivity restricted to the proximity of amyloid plaques. LD-RT significantly reduced Aβ 42 aggregated forms (-71%) in the hippocampus and tended to reduce other forms in the hippocampus and frontal cortex but did not affect tauopathy or cognitive performance. A trend for neuroinflammation markers reduction was also observed. CONCLUSION: When applied at an early stage, LD-RT reduced amyloid load and possibly neuroinflammation markers, with no impact on tauopathy. The long-term persistence of these beneficial effects of LD-RT should be evaluated in future studies.

Non-Alcoholic Fatty Liver Disease, Liver Fibrosis, and Regional Amyloid-β and Tau Pathology in Middle-Aged Adults: The Framingham Study. - Weinstein, Galit; O'Donnell, Adrienne; Davis-Plourde, Kendra; Zelber-Sagi, Shira; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Liver steatosis and fibrosis are emerging as risk factors for multiple extrahepatic health conditions; however, their relationship with Alzheimer's disease pathology is unclear. OBJECTIVE: To examine whether non-alcoholic fatty liver disease (NAFLD) and FIB-4, a non-invasive index of advanced fibrosis, are associated with brain amyloid-β (Aβ) and tau pathology. METHODS: The study sample included Framingham Study participants from the Offspring and Third generation cohorts who attended exams 9 (2011-2014) and 2 (2008-2011), respectively. Participants underwent 11C-Pittsburgh Compound-B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging and abdomen computed tomography, or had information on all components of the FIB-4 index. Linear regression models were used to assess the relationship of NAFLD and FIB-4 with regional tau and Aβ, adjusting for potential confounders and multiple comparisons. RESULTS: Of the subsample with NAFLD information (N = 169; mean age 52±9 y; 57% males), 57 (34%) had NAFLD. Of the subsample with information on liver fibrosis (N = 177; mean age 50±10 y; 51% males), 34 (19%) had advanced fibrosis (FIB-4 >  1.3). Prevalent NAFLD was not associated with Aβ or tau PET. However, FIB-4 index was significantly associated with increased rhinal tau (β= 1.03±0.33, p = 0.002). Among individuals with prevalent NAFLD, FIB-4 was related to inferior temporal, parahippocampal gyrus, entorhinal and rhinal tau (β= 2.01±0.47, p <  0.001; β= 1.60±0.53, p = 0.007, and β= 1.59±0.47, p = 0.003 and β= 1.60±0.42, p = 0.001, respectively) and to Aβ deposition overall and in the inferior temporal and parahippocampal regions (β= 1.93±0.47, p <  0.001; β= 1.59±0.38, p <  0.001, and β= 1.52±0.54, p = 0.008, respectively). CONCLUSION: This study suggests a possible association between liver fibrosis and early Alzheimer's disease pathology, independently of cardio-metabolic risk factors.

A Novel Panel of Plasma Proteins Predicts Progression in Prodromal Alzheimer's Disease. - Araújo, Daniella Castro; Veloso, Adriano Alonso; Gomes, Karina Braga; de Souza, Leonardo Cruz; Ziviani, Nivio; Caramelli, Paulo (J Alzheimers Dis, 2022)
BACKGROUND: A cheap and minimum-invasive method for early identification of Alzheimer's disease (AD) pathogenesis is key to disease management and the success of emerging treatments targeting the prodromal phases of the disease. OBJECTIVE: To develop a machine learning-based blood panel to predict the progression from mild cognitive impairment (MCI) to dementia due to AD within a four-year time-to-conversion horizon. METHODS: We created over one billion models to predict the probability of conversion from MCI to dementia due to AD and chose the best-performing one. We used Alzheimer's Disease Neuroimaging Initiative (ADNI) data of 379 MCI individuals in the baseline visit, from which 176 converted to AD dementia. RESULTS: We developed a machine learning-based panel composed of 12 plasma proteins (ApoB, Calcitonin, C-peptide, CRP, IGFBP-2, Interleukin-3, Interleukin-8, PARC, Serotransferrin, THP, TLSP 1-309, and TN-C), and which yielded an AUC of 0.91, accuracy of 0.91, sensitivity of 0.84, and specificity of 0.98 for predicting the risk of MCI patients converting to dementia due to AD in a horizon of up to four years. CONCLUSION: The proposed machine learning model was able to accurately predict the risk of MCI patients converting to dementia due to AD in a horizon of up to four years, suggesting that this model could be used as a minimum-invasive tool for clinical decision support. Further studies are needed to better clarify the possible pathophysiological links with the reported proteins.

Obesity-Associated Neurodegeneration Pattern Mimics Alzheimer's Disease in an Observational Cohort Study. - Morys, Filip; Potvin, Olivier; Zeighami, Yashar; Vogel, Jacob; Lamontagne-Caron, Rémi; Duchesne, Simon; Dagher, Alain (J Alzheimers Dis, 2022)
BACKGROUND: Excess weight in adulthood leads to health complications such as diabetes, hypertension, or dyslipidemia. Recently, excess weight has also been related to brain atrophy and cognitive decline. Reports show that obesity is linked with Alzheimer's disease (AD)-related changes, such as cerebrovascular damage or amyloid-β accumulation. However, to date no research has conducted a direct comparison between brain atrophy patterns in AD and obesity. OBJECTIVE: Here, we compared patterns of brain atrophy and amyloid-β/tau protein accumulation in obesity and AD using a sample of over 1,300 individuals from four groups: AD patients, healthy controls, obese otherwise healthy individuals, and lean individuals. METHODS: We age- and sex-matched all groups to the AD-patients group and created cortical thickness maps of AD and obesity. This was done by comparing AD patients with healthy controls, and obese individuals with lean individuals. We then compared the AD and obesity maps using correlation analyses and permutation-based tests that account for spatial autocorrelation. Similarly, we compared obesity and AD brain maps with amyloid-β and tau protein maps from other studies. RESULTS: Obesity maps were highly correlated with AD maps but were not correlated with amyloid-β/tau protein maps. This effect was not accounted for by the presence of obesity in the AD group. CONCLUSION: Our research confirms that obesity-related grey matter atrophy resembles that of AD. Excess weight management could lead to improved health outcomes, slow down cognitive decline in aging, and lower the risk for AD.

Perivascular Space Predicts Brain Hypometabolism of Individuals with Underlying Amyloid Pathology. - Shi, Xiaolei; Zhou, Nan; Sun, Bin; Wu, Yongshun; Hu, Yachun; Ning, Yuping (J Alzheimers Dis, 2022)
BACKGROUND: Reduced signal on fluorodeoxyglucose-positron emission tomography (FDG-PET) is a valid proxy for neurodegeneration in Alzheimer's disease (AD). Perivascular space (PVS) is believed to be associated with AD pathology and cognitive decline. OBJECTIVE: This study aimed to investigate the associations of PVS with FDG-PET and cognitive performance based on the burden of amyloid pathology. METHODS: We used magnetic resonance imaging (MRI) data from the Alzheimer's Disease Neuroimaging Initiative (ADNI). MRI-visible PVS in basal ganglia (BG) and centrum semi-oval (CSO) were visually classified as: none/mild, moderate or frequent/severe. The association of PVS with brain FDG-PET was explored based on the burden of amyloid pathology, where a cerebrospinal fluid (CSF) t-tau/Aβ42 with the ratio≥0.27 was defined as high amyloid pathology. Moreover, the relationships between PVS and cognitive performance variables (ADNI-MEM and ADNI-EF) were studied. RESULTS: For participants with higher tau/Aβ42 ratio, CSO-PVS severity was independently associated with lower FDG-PET. There were significant interaction effects between moderate or frequent/severe CSO-PVS and time on FDG decline in people with high amyloid pathology. The interaction between CSO-PVS and time (follow-up) was consistently associated with ADNI-MEM and ADNI-EF decline in individuals with high amyloid pathology. CONCLUSION: The study established the differential utility of PVS in BG and CSO for predicting brain metabolism. These findings suggest that CSO-PVS serves as a contributing factor to brain metabolism and cognitive decline associated with amyloid pathology.

Plasma Amyloid and in vivo Brain Amyloid in Late Middle-Aged Hispanics. - Rippon, Brady; Palta, Priya; Tahmi, Mouna; Sherwood, Greysi; Soto, Luisa; Cespedes, Sandino; Mesen, Yanette; He, Hengda; Laing, Krystal; Moreno, Herman; Teresi, Jeanne; Razlighi, Qolamreza; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Determining amyloid positivity is possible with cerebrospinal fluid and brain imaging of amyloid, but these methods are invasive and expensive. OBJECTIVE: To relate plasma amyloid-β (Aβ), measured using Single-molecule array (Simoatrademark) assays, to in vivo brain Aβ, measured using positron emission tomography (PET), examine the accuracy of plasma Aβ to predict brain Aβ positivity, and the relation of APOE ɛ4 with plasma Aβ. METHODS: We performed a cross-sectional analysis in a cohort of 345 late middle-aged Hispanic men and women (age 64 years, 72% women). Our primary plasma variable was Aβ 42/Aβ 40 ratio measured with Simoa. Brain Aβ burden was measured as global SUVR with 18F-Florbetaben PET examined continuously and categorically. RESULTS: Plasma Aβ 42/Aβ 40 ratio was inversely associated with global Aβ SUVR (β= -0.13, 95% Confidence Interval (CI): -0.23, -0.03; p = 0.013) and Aβ positivity (Odds Ratio: 0.59, 95% CI: 0.38, 0.91; p = 0.016), independent of demographics and APOE ɛ4. ROC curves (AUC = 0.73, 95% CI: 0.64, 0.82; p <  0.0001) showed that the optimal threshold for plasma Aβ 42/Aβ 40 ratio in relation to brain Aβ positivity was 0.060 with a sensitivity of 82.4% and specificity of 62.8% . APOE ɛ4 carriers had lower Aβ 42/Aβ 40 ratio and a higher Aβ positivity determined with the Aβ 42/Aβ 40 ratio threshold of 0.060. CONCLUSION: Plasma Aβ 42/Aβ 40 ratio assayed using Simoa is weakly correlated with in vivo brain amyloid and has limited accuracy in screening for amyloid positivity and for studying risk factors of brain amyloid burden when in vivo imaging is not feasible.

Probiotic Bifidobacterium breve Prevents Memory Impairment Through the Reduction of Both Amyloid-β Production and Microglia Activation in APP Knock-In Mouse. - Abdelhamid, Mona; Zhou, Chunyu; Ohno, Kazuya; Kuhara, Tetsuya; Taslima, Ferdous; Abdullah, Mohammad; Jung, Cha-Gyun; Michikawa, Makoto (J Alzheimers Dis, 2022)
BACKGROUND: Probiotic supplementation reestablishes microbiome diversity and improves brain function in Alzheimer's disease (AD); their molecular mechanisms, however, have not yet been fully illustrated. OBJECTIVE: We investigated the effects of orally supplemented Bifidobacterium breve MCC1274 on cognitive function and AD-like pathologies in AppNL-G-F mice. METHODS: Three-month-old AppNL-G-F mice were orally supplemented with B. breve MCC1274 for four months. The short-term memory function was evaluated using a novel object recognition test. Amyloid plaques, amyloid-β (Aβ) levels, Aβ fibril, amyloid-β protein precursor and its processing enzymes, its metabolic products, glial activity, and cell proliferation in the subgranular zone of the dentate gyrus were evaluated by immunohistochemistry, Aβ ELISA, western blotting, and immunofluorescence staining. The mRNA expression levels of pro- and anti-inflammatory cytokines were determined by qRT-PCR analysis. RESULTS: We found that the oral B. breve MCC1 274 supplementation prevented memory impairment in AppNL-G-F mice and decreased hippocampal Aβ levels through the enhancement of the a-disintegrin and metalloproteinase 10 (ADAM10) level. Moreover, administration of the probiotic activated the ERK/HIF-1α signaling pathway responsible for increasing the ADAM10 level and also attenuated microglial activation, which in turn led to reduction in the mRNA expression levels of pro-inflammatory cytokines in the brain. In addition, B. breve MCC1274 supplementation increased the level of synaptic proteins in the hippocampus. CONCLUSION: Our findings support the possibility that oral B. breve MCC1274 supplementation might be used as a potential preventive therapy for AD progression.
Keywords: Amyloid beta-Peptides; Animals; Bifidobacterium breve; Brain; Disease Models, Animal; Hippocampus; Memory Disorders; Mice; Mice, Transgenic; Microglia; Probiotics

Proteomic Profiles of Neurodegeneration Among Mexican Americans and Non-Hispanic Whites in the HABS-HD Study. - O'Bryant, Sid E; Zhang, Fan; Petersen, Melissa; Hall, James R; Johnson, Leigh A; Yaffe, Kristine; Braskie, Meredith; Vig, Rocky; Toga, Arthur W; Rissman, Robert A (J Alzheimers Dis, 2022)
BACKGROUND: Hispanics are expected to experience the largest increase in Alzheimer's disease (AD) and AD related dementias over the next several decades. However, few studies have examined biomarkers of AD among Mexican Americans, the largest segment of the U.S. Hispanic population. OBJECTIVE: We sought to examine proteomic profiles of an MRI-based marker of neurodegeneration from the AT(N) framework among a multi-ethnic, community-dwelling cohort. METHODS: Community-dwelling Mexican Americans and non-Hispanic white adults and elders were recruited. All participants underwent comprehensive assessments including an interview, functional exam, clinical labs, informant interview, neuropsychological testing, and 3T MRI of the brain. A neurodegeneration MRI meta-ROI biomarker for the AT(N) framework was calculated. RESULTS: Data was examined from n = 1,291 participants. Proteomic profiles were highly accurate for detecting neurodegeneration (i.e., N+) among both Mexican Americans (AUC = 1.0) and non-Hispanic whites (AUC = 0.98). The proteomic profile of N + was different between ethnic groups. Further analyses revealed that the proteomic profiles of N + varied by diagnostic status (control, MCI, dementia) and ethnicity (Mexican American versus non-Hispanic whites) though diagnostic accuracy was high for all classifications. CONCLUSION: A proteomic profile of neurodegeneration has tremendous value and point towards novel diagnostic and intervention opportunities. The current findings demonstrate that the underlying biological factors associated with neurodegeneration are different between Mexican Americans versus non-Hispanic whites as well as at different levels of disease progression.

Relationship Between Weight-Change Patterns and Cognitive Function: A Retrospective Study. - Gong, Hong-Jian; Tang, Xingyao; Chai, Yin-He; Qiao, Yu-Shun; Xu, Hui; Patel, Ikramulhaq; Zhang, Jin-Yan; Simó, Rafael; Zhou, Jian-Bo (J Alzheimers Dis, 2022)
BACKGROUND: Obesity has been linked to cognitive impairment. However, how changes in body mass index (BMI) over the life course influence cognitive function remains unclear. OBJECTIVE: The influence of distinct weight-change patterns from young adulthood to midlife and late adulthood on cognitive function in older adults was explored. METHODS: A total of 5,809 individuals aged≥60 years were included and categorized into four groups on the basis of BMI change patterns. Cognitive function was assessed using four cognition tests in the baseline survey. The relationship between the weight-change patterns and cognition was evaluated using regression models. RESULTS: In comparison with participants who remained at non-obese, those moving from the non-obese to obese weight-change pattern from young (25 years of age) to middle adulthood showed lower Digit Symbol Substitution Test (DSST) scores (β= -1.28; 95% confidence interval [CI]: -2.24 to -0.32). A non-obese to obese change pattern from age 25 years of age to 10 years before baseline was associated with a higher risk of DSST impairment (odds ratio = 1.40; 95% CI: 1.09 to 1.79). In comparison with participants whose heaviest weight was recorded after 60 years of age, those with the heaviest weight between 18 and 40 years of age had lower DSST scores (β= -1.46; 95% CI: -2.77 to -1.52). CONCLUSION: Our results suggest that the transition from the non-obese to obese category in early adulthood and appearance of the heaviest weight between 18 and 40 years of age are associated with lower cognitive function in later life.

Risk of Dementia in Cancer Survivors: A Meta-Analysis of Population-Based Cohort Studies. - Zhang, Dan-Dan; Ou, Ya-Nan; Fu, Yan; Wang, Zhi-Bo; Huang, Liang-Yu; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: A negative association between cancer and Alzheimer's disease (AD) was revealed. OBJECTIVE: We aimed to further explore the dementia risk among cancer survivors and then among cancer survivors who received cancer treatment in subsequent subgroup analyses. METHODS: Databases of PubMed, Embase, and Cochrane Library were systematically searched from inception to April 1, 2021, following PRISMA and MOOSE guidelines. Relative risks (RR) of dementia were pooled by a random-effects model stratifying the data by potential confounding factors to explore the heterogeneity. This study is registered with PROSPERO, number CRD42021250654. RESULTS: A total of 36 studies were included in this meta-analysis, of which 16 studies were about the risk of dementia in cancer survivors, and 20 studies were about the risk of dementia in survivors who accepted cancer treatment. The pooled RR reached 0.89 ([95% CI = 0.82-0.97], I2 = 97.9%) for dementia and 0.89 ([0.83-0.95], I2 = 92.6%) for AD in cancer survivors compared with non-cancer controls. Notably, both dementia risk and AD risk significantly decreased in survivors of colon, leukemia, small intestine, and thyroid cancers (RR ranged from 0.64 to 0.92). Furthermore, prostate cancer patients treated with androgen deprivation therapy exhibited a significantly increased risk of dementia (RR:1.18 [1.09-1.27], I2 = 89.5%) and AD (RR:1.17 [1.08-1.25], I2 = 81.3%), with evidence of between-study heterogeneity. CONCLUSION: Currently, available evidence suggests that the risk of dementia among cancer survivors is decreased. However, large-scale prospective cohort studies are warranted to further prove the association.

The Role of Amyloid, Tau, and APOE Genotype on the Relationship Between Informant-Reported Sleep Disturbance and Alzheimer's Disease Risks. - Kim, Hyun; Levine, Alina; Cohen, Daniel; Gehrman, Philip; Zhu, Xi; Devanand, Davangere P; Lee, Seonjoo; Goldberg, Terry E (J Alzheimers Dis, 2022)
BACKGROUND: The association between sleep and Alzheimer's disease (AD) biomarkers are well-established, but little is known about how they interact to change the course of AD. OBJECTIVE: To determine the potential interaction between sleep disturbance and Aβ, tau, and APOE4 on brain atrophy and cognitive decline. METHODS: Sample included 351 participants (mean age 72.01 ± 6.67, 50.4%female) who were followed for approximately 5 years as part of the Alzheimer's Disease Neuroimaging Initiative. Informant-reported sleep disturbance (IRSD) was measured using the Neuropsychiatric Inventory (NPI). Changes in magnetic resonance imaging (MRI)-measured AD signature brain regions and cognitive performance and IRSD's interaction with cerebrospinal fluid amyloid-β (Aβ42) and p-Tau depositions and APOE4 status were examined using the linear mixed models. RESULTS: Baseline IRSD was not significantly associated with the rate of atrophy after adjusting for covariates (age, sex, education, total NPI severity score, and sleep medications). However, there was a significant interaction between IRSD and AD biomarkers on faster atrophy rates in multiple brain regions, including the cortical and middle temporal volumes. Post-hoc analyses indicated that Aβ and p-Tau/Aβ predicted a faster decline in these regions/domains in IRSD, compared with biomarker-negative individuals with IRSD (ps≤0.001). There was a significant IRSD*APOE4 interaction for brain atrophy rate (ps≤0.02) but not for cognition. CONCLUSION: IRSD may increase the future risk of AD by contributing to faster brain atrophy and cognitive decline when combined with the presence of AD biomarkers and APOE4. Early intervention for sleep disturbance could help reduce the risk of developing AD.

The Role of Amyloid-β, Tau, and α-Synuclein Proteins as Putative Blood Biomarkers in Patients with Cerebral Amyloid Angiopathy. - Piccarducci, Rebecca; Caselli, Maria Chiara; Zappelli, Elisa; Ulivi, Leonardo; Daniele, Simona; Siciliano, Gabriele; Ceravolo, Roberto; Mancuso, Michelangelo; Baldacci, Filippo; Martini, Claudia (J Alzheimers Dis, 2022)
BACKGROUND: Cerebral amyloid angiopathy (CAA) is a cerebrovascular disorder characterized by the deposition of amyloid-β protein (Aβ) within brain blood vessels that develops in elderly people and Alzheimer's disease (AD) patients. Therefore, the investigation of biomarkers able to differentiate CAA patients from AD patients and healthy controls (HC) is of great interest, in particular in peripheral fluids. OBJECTIVE: The current study aimed to detect the neurodegenerative disease (ND)-related protein (i.e., Aβ 1 - 40, Aβ 1 - 42, tau, and α-synuclein) levels in both red blood cells (RBCs) and plasma of CAA patients and HC, evaluating their role as putative peripheral biomarkers for CAA. METHODS: For this purpose, the proteins' concentration was quantified in RBCs and plasma by homemade immunoenzymatic assays in an exploratory cohort of 20 CAA patients and 20 HC. RESULTS: The results highlighted a significant increase of Aβ 1 - 40 and α-synuclein concentrations in both RBCs and plasma of CAA patients, while higher Aβ 1 - 42 and t-tau levels were detected only in RBCs of CAA individuals compared to HC. Moreover, Aβ 1 - 42/Aβ 1 - 40 ratio increased in RBCs and decreased in plasma of CAA patients. The role of these proteins as candidate peripheral biomarkers easily measurable with a blood sample in CAA needs to be confirmed in larger studies. CONCLUSION: In conclusion, we provide evidence concerning the possible use of blood biomarkers for contributing to CAA diagnosis and differentiation from other NDs.

Safety and Efficacy of Monoclonal Antibodies for Alzheimer's Disease: A Systematic Review and Meta-Analysis of Published and Unpublished Clinical Trials. - Lacorte, Eleonora; Ancidoni, Antonio; Zaccaria, Valerio; Remoli, Giulia; Tariciotti, Leonardo; Bellomo, Guido; Sciancalepore, Francesco; Corbo, Massimo; Lombardo, Flavia L; Bacigalupo, Ilaria; Canevelli, Marco; Piscopo, Paola; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Monoclonal antibodies (mAbs) are currently among the most investigated targets for potential disease-modifying therapies in Alzheimer's disease (AD). OBJECTIVE: Our objectives were to identify all registered trials investigating mAbs in MCI due to AD or AD at any stage, retrieve available published and unpublished data from all registered trials, and analyze data on safety and efficacy outcomes. METHODS: A systematic search of all registered trials on ClinicalTrials.gov and EUCT was performed. Available results were searched on both platforms and on PubMed, ISI Web of Knowledge, and The Cochrane Library. RESULTS: Overall, 101 studies were identified on 27 mAbs. Results were available for 50 trials investigating 12 mAbs. For 18 trials, data were available from both published and unpublished sources, for 21 trials only from published sources, and for 11 trials only from unpublished sources. Meta-analyses of amyloid-related imaging abnormalities (ARIA) events showed overall risk ratios of 10.65 for ARIA-E and of 1.75 for ARIA-H. The meta-analysis of PET-SUVR showed an overall significant effect of mAbs in reducing amyloid (SMD -0.88), but when considering clinical efficacy, data on CDR-SB showed that treated patients had a statistically significant but clinically non-relevant lower worsening (MD -0.15). CONCLUSION: Our results suggest that the risk-benefit profile of mAbs remains unclear. Research should focus on clarifying the effect of amyloid on cognitive decline, providing data on treatment response rate, and accounting for minimal clinically important difference. Research on mAbs should also investigate the possible long-term impact of ARIA events, including potential factors predicting their onset.
Keywords: Alzheimer Disease; Amyloid; Amyloidogenic Proteins; Amyloidosis; Antibodies, Monoclonal; Cognitive Dysfunction; Humans

Scavenging Reactive Oxygen Species Decreases Amyloid-β Levels via Activation of PI3K/Akt/GLUT1 Pathway in N2a/APP695swe Cells. - Peng, Yan; Zhang, Li; Zhou, Fanlin; Wang, Yangyang; Zhang, Xiong; Fan, Jianing; Li, Shijie; Li, Xiaoju; Li, Yu (J Alzheimers Dis, 2022)
BACKGROUND: Dysregulated glucose metabolism in the brain is considered to be one of the key causes of Alzheimer's disease (AD). Abnormal glucose uptake in AD is tightly associated with decreased levels of glucose transporter 1 (GLUT1) and GLUT3 in the brain, but the underlying mechanisms remain unclear. OBJECTIVE: We aimed to explore the cause and mechanism of impaired glucose uptake in AD. METHODS: N2a/WT and N2a/APP695swe cells were cultured in vitro, and cellular glucose uptake and ATP content, as well as the expression of GLUT1, GLUT3, and PI3K/Akt pathway members, were detected. Intracellular reactive oxygen species (ROS) levels were detected by flow cytometry. After treatment with the ROS scavenger N-acetyl-L-cysteine (NAC), the above indicators were detected again. RESULTS: GLUT1 expression was significantly decreased (p = 0.0138) in N2a/APP695swe cells, while GLUT3 expression was no statistical difference (p >  0.05). After NAC treatment, PI3K and Akt phosphorylation levels, GLUT1 expression, glucose uptake and ATP levels were remarkably increased (p = 0.0006, p = 0.0008, p = 0.0009, p = 0.0001, p = 0.0013), while Aβ levels were significantly decreased (p = 0.0058, p = 0.0066). After addition of the PI3K inhibitor LY29004, GLUT1 expression was reduced (p = 0.0008), and Aβ levels were increased (p = 0.0009, p = 0.0117). In addition, increases in glucose uptake and ATP levels induced by the Akt activator SC79 were hindered by the GLUT1 inhibitor WZB117 (p = 0.0002, p = 0.0005). Aβ levels were decreased after SC79 treatment and increased after WZB117 treatment (p = 0.0212, p = 0.0006). CONCLUSION: Taken together, scavenging of ROS prevents from Aβ deposition via activation of the PI3K/Akt/GLUT1 pathway, and improved the impaired glucose uptake in N2a/APP695swe cells.

Serum Levels of α-Klotho Are Correlated with Cerebrospinal Fluid Levels and Predict Measures of Cognitive Function. - Kundu, Payel; Zimmerman, Benjamin; Quinn, Joseph F; Kaye, Jeffrey; Mattek, Nora; Westaway, Shawn K; Raber, Jacob (J Alzheimers Dis, 2022)
BACKGROUND: α-klotho might play a role in neurodegenerative diseases. OBJECTIVE: To determine levels of α-klotho and apoE in serum and cerebrospinal fluid (CSF) samples and their relationship with the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating (CDR). METHODS: All subjects were between age 39 to 83+ (n = 94). CDR and MMSE were administered to all participants. CSF was collected in the early afternoon by lumbar puncture. RESULTS: Serum and CSF levels of α-klotho are positively correlated and both predict scores on the MMSE and CDR, regardless of sex or apoE4 status. CONCLUSION: Our results demonstrate that α-klotho may be an important biomarker of cognitive health and neurodegeneration, and that relatively non-invasive sampling of α-klotho from serum is likely highly reflective of CSF levels.

The Spectrum of Alzheimer-Type Pathology in Cognitively Normal Individuals. - Walker, Jamie M; Dehkordi, Shiva Kazempour; Schaffert, Jeff; Goette, William; White Iii, Charles L; Richardson, Timothy E; Zare, Habil (J Alzheimers Dis, 2022)
BACKGROUND: The strongest risk factor for the development of Alzheimer's disease (AD) is age. The progression of Braak stage and Thal phase with age has been demonstrated. However, prior studies did not include cognitive status. OBJECTIVE: We set out to define normative values for Alzheimer-type pathologic changes in individuals without cognitive decline, and then define levels that would qualify them to be resistant to or resilient against these changes. METHODS: Utilizing neuropathology data obtained from the National Alzheimer's Coordinating Center (NACC), we demonstrate the age-related progression of Alzheimer-type pathologic changes in cognitively normal individuals (CDR = 0, n = 542). With plots generated from these data, we establish standard lines that may be utilized to measure the extent to which an individual's Alzheimer-type pathology varies from the estimated normal range of pathology. RESULTS: Although Braak stage and Thal phase progressively increase with age in cognitively normal individuals, the Consortium to Establish a Registry for Alzheimer's Disease neuritic plaque score and Alzheimer's disease neuropathologic change remain at low levels. CONCLUSION: These findings suggest that an increasing burden of neuritic plaques is a strong predictor of cognitive decline, whereas, neurofibrillary degeneration and amyloid-β (diffuse) plaque deposition, both to some degree, are normal pathologic changes of aging that occur in almost all individuals regardless of cognitive status. Furthermore, we have defined the amount of neuropathologic change in cognitively normal individuals that would qualify them to be "resilient" against the pathology (significantly above the normative values for age, but still cognitively normal) or "resistant" to the development of pathology (significantly below the normative values for age).

Subjective Cognitive Decline: Is a Resilient Personality Protective Against Progression to Objective Cognitive Impairment? Findings from Two Community-Based Cohort Studies. - Aschwanden, Damaris; Sutin, Angelina R; Ledermann, Thomas; Luchetti, Martina; Stephan, Yannick; Sesker, Amanda A; Zhu, Xianghe; Terracciano, Antonio (J Alzheimers Dis, 2022)
BACKGROUND: Subjective cognitive decline (SCD) is related to personality functioning and risk of subsequent objective cognitive impairment. OBJECTIVE: The aim of this study was to examine whether lower neuroticism and higher conscientiousness-resilient personality traits-protect against conversion from SCD to objective cognitive impairment in two longitudinal community-based cohorts. METHODS: Data from the Health and Retirement Study (N = 1,741, Mean age = 68.64 years, Follow-up mean = 7.34 years) and the National Health and Aging Trends Survey (N = 258, Mean age = 79.34 years, Follow-up mean = 4.31 years) were analyzed using Cox regression analysis, controlling for sociodemographic covariates, symptoms of anxiety and depression, and apolipoprotein ɛ4. RESULTS: The pooled results showed that lower neuroticism and higher conscientiousness were associated with decreased risk of conversion from SCD to objective cognitive impairment. CONCLUSION: Among individuals with SCD, those with a resilient personality may have more cognitive and psychological reserve to maintain cognitive functioning and delay conversion to objective cognitive impairment. The findings further contribute to a better understanding of personality along the cognitive continuum: The observed effect sizes were smaller than those reported in cognitively normal individuals but larger than in individuals with mild cognitive impairment. Personality could provide useful information to identify individuals with SCD who may develop objective cognitive impairment-namely those who hold a vulnerable personality (higher neuroticism, lower conscientiousness).

Weight Loss and Alzheimer's Disease in Down Syndrome. - Fleming, Victoria; Helsel, Brian C; Ptomey, Lauren T; Rosas, H Diana; Handen, Benjamin; Laymon, Charles; Christian, Bradley T; Head, Elizabeth; Mapstone, Mark; Lai, Florence; Krinsky-McHale, Sharon; Zaman, Shahid; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Virtually all adults with Down syndrome (DS) develop Alzheimer's disease (AD) pathology, but research gaps remain in understanding early signs of AD in DS. OBJECTIVE: The goal of the present study was to determine if unintentional weight loss is part of AD in DS. The specific aims were to: 1) examine relation between chronological age, weight, AD pathology, and AD-related cognitive decline were assessed in a large cohort of adults with DS, and 2) determine if baseline PET amyloid-β (Aβ) and tau PET status (-versus+) and/or decline in memory and mental status were associated with weight loss prior to AD progression. METHODS: Analyses included 261 adults with DS. PET data were acquired using [11C] PiB for Aβ and [18F] AV-1451 for tau. Body mass index (BMI) was calculated from weight and height. Direct measures assessed dementia and memory. Clinical AD status was determined using a case consensus process. Percent weight decline across 16-20 months was assessed in a subset of participants (n = 77). RESULTS: Polynomial regressions indicated an 0.23 kg/m2 decrease in BMI per year beginning at age 36.5 years, which occurs alongside the period during which Aβ and tau increase and memory and mental status decline. At a within-person level, elevated Aβ, decline in memory and mental status were associated with higher percent weight loss across 16-20 months. CONCLUSION: Unintentional weight loss occurs alongside Aβ deposition and prior to onset of AD dementia, and thus may be a useful sign of AD in DS.

Apolipoprotein E ɛ4 (APOE ɛ4) Allele is Associated with Long Sleep Duration Among Elderly with Cognitive Impairment. - Basta, Maria; Zaganas, Ioannis; Simos, Panagiotis; Koutentaki, Eirini; Dimovasili, Christina; Mathioudakis, Lambros; Bourbouli, Mara; Panagiotakis, Symeon; Kapetanaki, Stefania; Vgontzas, Alexandros (J Alzheimers Dis, 2021)
BACKGROUND: Apolipoprotein E gene (APOE) ɛ4 allele increases the risk for Alzheimer's disease (AD). Furthermore, among patients with cognitive impairment, longer sleep duration is associated with worse cognitive performance. To date, literature examining the associations between APOE ɛ4 allele and objective sleep duration is limited. OBJECTIVE: Our aim was to assess the association between APOE ɛ4 and objective sleep duration, among patients with mild cognitive impairment (MCI) and AD. A sub-sample of 89 patients with AD (n = 49) and MCI (n = 40) were recruited from a large, population-based cohort of 3,140 elders (>60 years) residing on Crete, Greece. METHODS: All participants underwent medical history/physical examination, extensive neuropsychiatric and neuropsychological evaluation, 3-day 24 h actigraphy and APOE ɛ4 allele genotyping. Comparisons of sleep duration variables between APOE ɛ4 allele carriers and non-carriers were assessed using ANCOVA, controlling for confounders. RESULTS: The sample included 18 APOE ɛ4 carriers and 71 non-carriers, aged 78.6±6.6 and 78.2±6.5 years, respectively. Comparisons between the APOE ɛ4 carriers and non-carriers revealed no significant differences in terms of demographic and clinical variables. In terms of objective sleep duration across the two groups, APOE ɛ4 carriers compared to non-carriers had significantly longer nighttime Total Sleep Time (nTST) (7.7±1.4 versus 7.2±1.3  h, respectively, p = 0.011), as well as 24 h TST (8.5±1.6 versus 7.8±1.5  h, respectively, p = 0.012). CONCLUSION: Among patients with MCI and AD, APOE ɛ4 carriers have longer objective nighttime and 24 h sleep duration compared to non-carriers. These findings further support that objective long sleep duration is a genetically-driven pre-clinical marker associated with worse prognosis in elderly with cognitive impairment.

B Vitamins Prevent Iron-Associated Brain Atrophy and Domain-Specific Effects of Iron, Copper, Aluminum, and Silicon on Cognition in Mild Cognitive Impairment. - Jakubowski, Hieronim; Zioła-Frankowska, Anetta; Frankowski, Marcin; Perła-Kaján, Joanna; Refsum, Helga; de Jager, Celeste A; Smith, A David (J Alzheimers Dis, 2021)

Central Obesity, Cardiometabolic Risk, and Cognitive Change in the Study of Latinos: Investigation of Neurocognitive Aging. - Stickel, Ariana M; Tarraf, Wassim; Gonzalez, Kevin A; Isasi, Carmen R; Kaplan, Robert; Gallo, Linda C; Zeng, Donglin; Cai, Jianwen; Pirzada, Amber; Daviglus, Martha L; Goodman, Zachary T; Schneiderman, Neil; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The relationships between obesity and cognitive decline in aging are mixed and understudied among Hispanics/Latinos. OBJECTIVE: To understand associations between central obesity, cognitive aging, and the role of concomitant cardiometabolic abnormalities among Hispanics/Latinos. METHODS: Participants included 6,377 diverse Hispanics/Latinos enrolled in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) and SOL-Investigation for Neurocognitive Aging (SOL-INCA). Participants were 45 years and older at the first cognitive testing session (Visit 1). Cognitive outcomes (z-score units) included global composite and domain specific (learning, memory, executive functioning, processing speed) measures at a second visit (SOL-INCA, on average, 7 years later), and 7-year change. We used survey linear regression to examine associations between central obesity (waist circumference≥88 cm and≥102 cm for women and men, respectively) and cognition. We also tested whether the relationships between obesity and cognition differed by cardiometabolic status (indication of/treatment for 2 + of the following: high triglycerides, hypertension, hyperglycemia, low high-density lipoprotein cholesterol). RESULTS: Central obesity was largely unassociated with cognitive outcomes, adjusting for covariates. However, among individuals with central obesity, cardiometabolic abnormality was linked to poorer cognitive function at SOL-INCA (ΔGlobalCognition =-0.165, p < 0.001) and to more pronounced cognitive declines over the average 7 years (ΔGlobalCognition = -0.109, p < 0.05); this was consistent across cognitive domains. CONCLUSION: Central obesity alone was not associated with cognitive function. However, presence of both central obesity and cardiometabolic abnormalities was robustly predictive of cognition and 7-year cognitive declines, suggesting that in combination these factors may alter the cognitive trajectories of middle-aged and older Hispanics/Latinos.

Cognitive Effects of Aerobic Exercise in Alzheimer's Disease: A Pilot Randomized Controlled Trial. - Yu, Fang; Vock, David M; Zhang, Lin; Salisbury, Dereck; Nelson, Nathaniel W; Chow, Lisa S; Smith, Glenn; Barclay, Terry R; Dysken, Maurice; Wyman, Jean F (J Alzheimers Dis, 2021)
BACKGROUND: Aerobic exercise has shown inconsistent cognitive effects in older adults with Alzheimer's disease (AD) dementia. OBJECTIVE: To examine the immediate and longitudinal effects of 6-month cycling on cognition in older adults with AD dementia. METHODS: This randomized controlled trial randomized 96 participants (64 to cycling and 32 to stretching for six months) and followed them for another six months. The intervention was supervised, moderate-intensity cycling for 20-50 minutes, 3 times a week for six months. The control was light-intensity stretching. Cognition was assessed at baseline, 3, 6, 9, and 12 months using the AD Assessment Scale-Cognition (ADAS-Cog). Discrete cognitive domains were measured using the AD Uniform Data Set battery. RESULTS: The participants were 77.4±6.8 years old with 15.6±2.9 years of education, and 55%were male. The 6-month change in ADAS-Cog was 1.0±4.6 (cycling) and 0.1±4.1 (stretching), which were both significantly less than the natural 3.2±6.3-point increase observed naturally with disease progression. The 12-month change was 2.4±5.2 (cycling) and 2.2±5.7 (control). ADAS-Cog did not differ between groups at 6 (p = 0.386) and 12 months (p = 0.856). There were no differences in the 12-month rate of change in ADAS-Cog (0.192 versus 0.197, p = 0.967), memory (-0.012 versus -0.019, p = 0.373), executive function (-0.020 versus -0.012, p = 0.383), attention (-0.035 versus -0.033, p = 0.908), or language (-0.028 versus -0.026, p = 0.756). CONCLUSION: Exercise may reduce decline in global cognition in older adults with mild-to-moderate AD dementia. Aerobic exercise did not show superior cognitive effects to stretching in our pilot trial, possibly due to the lack of power.

Cognitive Effects of the BET Protein Inhibitor Apabetalone: A Prespecified Montreal Cognitive Assessment Analysis Nested in the BETonMACE Randomized Controlled Trial. - Cummings, Jeffrey; Schwartz, Gregory G; Nicholls, Stephen J; Khan, Aziz; Halliday, Chris; Toth, Peter P; Sweeney, Michael; Johansson, Jan O; Wong, Norman C W; Kulikowski, Ewelina; Kalantar-Zadeh, Kamyar; Lebioda, Kenneth; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Epigenetic changes may contribute importantly to cognitive decline in late life including Alzheimer's disease (AD) and vascular dementia (VaD). Bromodomain and extra-terminal (BET) proteins are epigenetic "readers" that may distort normal gene expression and contribute to chronic disorders. OBJECTIVE: To assess the effects of apabetalone, a small molecule BET protein inhibitor, on cognitive performance of patients 70 years or older participating in a randomized trial of patients at high risk for major cardiovascular events (MACE). METHODS: The Montreal Cognitive Assessment (MoCA) was performed on all patients 70 years or older at the time of randomization. 464 participants were randomized to apabetalone or placebo in the cognition sub-study. In a prespecified analysis, participants were assigned to one of three groups: MoCA score≥26 (normal performance), MoCA score 25-22 (mild cognitive impairment), and MoCA score≤21 (dementia). Exposure to apabetalone was equivalent in the treatment groups in each MoCA-defined group. RESULTS: Apabetalone was associated with an increased total MoCA score in participants with baseline MoCA score of≤21 (p = 0.02). There was no significant difference in change from baseline in the treatment groups with higher MoCA scores. In the cognition study, more patients randomized to apabetalone discontinued study drug for adverse effects (11.3% versus 7.9%). CONCLUSION: In this randomized controlled study, apabetalone was associated with improved cognition as measured by MoCA scores in those with baseline scores of 21 or less. BET protein inhibitors warrant further investigation for late life cognitive disorders.
Keywords: Aged; Cardiovascular Diseases; Cognitive Dysfunction; Epigenesis, Genetic; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Quinazolinones

Cortical Thickness and Its Association with Clinical Cognitive and Neuroimaging Markers in Cerebral Amyloid Angiopathy. - Subotic, Arsenije; McCreary, Cheryl R; Saad, Feryal; Nguyen, Amanda; Alvarez-Veronesi, Ana; Zwiers, Angela M; Charlton, Anna; Beaudin, Andrew E; Ismail, Zahinoor; Bruce Pike, G; Smith, Eric E (J Alzheimers Dis, 2021)
BACKGROUND: Cerebral amyloid angiopathy (CAA) contributes to brain neurodegeneration and cognitive decline, but the relationship between these two processes is incompletely understood. OBJECTIVE: The purpose of this study is to examine cortical thickness and its association with cognition and neurodegenerative biomarkers in CAA. METHODS: Data were collected from the Functional Assessment of Vascular Reactivity study and the Calgary Normative Study. In total, 48 participants with probable CAA, 72 cognitively normal healthy controls, and 24 participants with mild dementia due to AD were included. Participants underwent an MRI scan, after which global and regional cortical thickness measurements were obtained using FreeSurfer. General linear models, adjusted for age and sex, were used to compare cortical thickness globally and in an AD signature region. RESULTS: Global cortical thickness was lower in CAA compared to healthy controls (mean difference (MD) -0.047 mm, 95% confidence interval (CI) -0.088, -0.005, p = 0.03), and lower in AD compared to CAA (MD -0.104 mm, 95% CI -0.165, -0.043, p = 0.001). In the AD signature region, cortical thickness was lower in CAA compared to healthy controls (MD -0.07 mm, 95% CI -0.13 to -0.01, p = 0.02). Within the CAA group, lower cortical thickness was associated with lower memory scores (R2 = 0.10; p = 0.05) and higher white matter hyperintensity volume (R2 = 0.09, p = 0.04). CONCLUSION: CAA contributes to neurodegeneration in the form of lower cortical thickness, and this could contribute to cognitive decline. Regional overlap with an AD cortical atrophy signature region suggests that co-existing AD pathology may contribute to lower cortical thickness observed in CAA.

A Cost-Consequence Analysis of Different Screening Procedures in Alzheimer's Disease: Results from the MOPEAD Project. - Wimo, Anders; Belger, Mark; Bon, Jaka; Jessen, Frank; Dumas, Annette; Kramberger, Milica G; Jamilis, Laura; Johansson, Gunilla; Rodrigo Salas, Adrián; Rodríguez Gómez, Octavio; Sannemann, Lena; Stoekenbroek, Malou; et al. (J Alzheimers Dis, 2021)
BACKGROUND: For care planning and support, under-detection and late diagnosis of Alzheimer's disease (AD) is a great challenge. Models of Patient-Engagement for Alzheimer's Disease (MOPEAD) is an EU-funded project aiming at testing different strategies to improve this situation. OBJECTIVE: To make a cost-consequence analysis of MOPEAD. METHODS: Four screening strategies were tested in five countries (Germany, the Netherlands, Slovenia, Spain, and Sweden): 1) a web-approach; 2) Open-House initiative; 3) in primary care; and 4) by diabetes specialists. Persons-at-risk of AD in all strategies were offered referral to a hospital-based specialist. The primary health-economic outcome was the cost per true-positive case (TP) of AD from the screened population. RESULTS: Of 2,847 screened persons, 1,121 screened positive (39%), 402 were evaluated at memory clinics (14%), and 236 got an AD diagnosis (8%). The cost per TP of those screened was 3,115€ with the web-approach, 2,722€ with the Open-House, 1,530€ in primary care, and 1,190€ by diabetes specialists. Sensitivity analyses that more likely reflect the real-world situation confirmed the results. The number-needed-to-screen was 30 with the web-approach, 8 with the Open-House and primary care, and 6 with the diabetes specialists.There were country differences in terms of screening rates, referrals to memory clinics, staff-types involved, and costs per TP. CONCLUSION: In primary care and by the diabetes specialist, the costs per TP/screened population were lowest, but the capacity of such settings to identify cases with AD-risk must be discussed. Hence new diagnostic strategies such as web-solutions and Open-House initiatives may be valuable after modifications.

Effects of Peroral Omega-3 Fatty Acid Supplementation on Cerebrospinal Fluid Biomarkers in Patients with Alzheimer's Disease: A Randomized Controlled Trial-The OmegAD Study. - Tofiq, Avin; Zetterberg, Henrik; Blennow, Kaj; Basun, Hans; Cederholm, Tommy; Eriksdotter, Maria; Faxen-Irving, Gerd; Hjorth, Erik; Jernerén, Fredrik; Schultzberg, Marianne; Wahlund, Lars-Olof; Palmblad, Jan; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Studies have suggested a connection between a decrease in the levels of polyunsaturated fatty acids (PUFAs) and Alzheimer's disease (AD). We aimed to assess the effect of supplementation with omega-3 fatty acids (n-3 FAs) on biomarkers analyzed in the cerebrospinal fluid (CSF) of patients diagnosed with AD. OBJECTIVE: To investigate the effects of daily supplementation with 2.3 g of PUFAs in AD patients on the biomarkers in CSF described below. We also explored the possible correlation between these biomarkers and the performance in the cognitive test Mini-Mental State Examination (MMSE). METHODS: Thirty-three patients diagnosed with AD were randomized to either treatment with a daily intake of 2.3 g of n-3 FAs (n  =  18) or placebo (n  =  15). CSF samples were collected at baseline and after six months of treatment, and the following biomarkers were analyzed: Aβ 38, Aβ 40, Aβ 42, t-tau, p-tau, neurofilament light (NfL), chitinase-3-like protein 1 (YKL-40), acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), soluble IL-1 receptor type II (sIL-1RII), and IL-6. RESULTS: There were no significant differences between the groups concerning the level of the different biomarkers in the CSF at baseline. Within the treatment group, there was a small but significant increase in both YKL-40 (p = 0.04) and NfL (p = 0.03), while the other CSF biomarkers remained stable. CONCLUSION: Supplementation with n-3 FAs had a statistically significant effect on NfL and YKL-40, resulting in an increase of both biomarkers, indicating a possible increase of inflammatory response and axonal damage. This increase in biomarkers did not correlate with MMSE score.

Enhancing the Sensitivity of Memory Tests: Reference Data for the Free and Cued Selective Reminding Test and the Logical Memory Task from Cognitively Healthy Subjects with Normal Alzheimer's Disease Cerebrospinal Fluid Biomarker Levels. - Brugulat-Serrat, Anna; Cañas, Alba; Canals, Lidia; Marne, Paula; Gramunt, Nina; Milà-Alomà, Marta; Suárez-Calvet, Marc; Arenaza-Urquijo, Eider M; Grau-Rivera, Oriol; González-de-Echávarri, José María; Minguillon, Carolina; Fauria, Karine; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Cognitive performance of a given individual should be interpreted in the context of reference standards obtained in cognitively healthy populations. Recent evidence has shown that removing asymptomatic individuals with biomarker evidence of Alzheimer's disease (AD) pathology from normative samples increases the sensitivity of norms to detect memory impairments. These kind of norms may be useful for defining subtle cognitive decline, the transitional cognitive decline between normal cognition and mild cognitive impairment. OBJECTIVE: The present study aims to provide norms for the Free and Cued Selective Reminding Test (FCSRT) and the Logical Memory subtest of the Wechsler Memory Scale-IV in a sample of individuals aged 50-70 years with normal levels of amyloid (A) and tau (T) cerebrospinal fluid (CSF) biomarkers. METHODS: The sample was composed of 248 individuals from the ALFA+ study with negative amyloid-β and tau CSF biomarker levels. Regression-based norms were developed, including adjustments for age, education, and sex when applicable. RESULTS: We found that education was associated with the performance in all the variables of both tests while age had a marginal effect only in the delayed free recall of the FCSRT. Sex was also related to the performance in the FCSRT, with women outperforming men. Equations to calculate z-scores and normative percentile tables were created. As compared with previously published norms the reference data presented were more sensitive but less specific, as expected. CONCLUSION: The use of the norms provided in this work, in combination with the already published conventional norms, may contribute to detecting subtle memory impairment.

Gut Microbiome Features of Chinese Patients Newly Diagnosed with Alzheimer's Disease or Mild Cognitive Impairment. - Guo, Mingyan; Peng, Jun; Huang, Xiaoyan; Xiao, Lingjun; Huang, Fenyan; Zuo, Zhiyi (J Alzheimers Dis, 2021)
BACKGROUND: Patients with Alzheimer's disease (AD) have gut microbiome alterations compared with healthy controls. However, previous studies often assess AD patients who have been on medications or other interventions for the disease. Also, simultaneous determination of gut microbiome in patients with mild cognitive impairment (MCI) or AD in a study is rare. OBJECTIVE: To determine whether there was a gut microbiome alteration in patients newly diagnosed with AD or MCI and whether the degree of gut microbiome alteration was more severe in patients with AD than patients with MCI. METHODS: Fecal samples of 18 patients with AD, 20 patients with MCI, and 18 age-matched healthy controls were collected in the morning for 16S ribosomal RNA sequencing. No patient had medications or interventions for AD or MCI before the samples were collected. RESULTS: Although there was no difference in the microbial α-diversity among the three groups, patients with AD or MCI had increased β-diversity compared with healthy controls. Patients with AD had decreased Bacteroides, Lachnospira, and Ruminiclostridium_9 and increased Prevotella at the genus level compared with healthy controls. The changing direction of these genera in patients with MCI was the same as patients with AD. However, Lachnospira was the only genus whose abundance in patients with MCI was statistically significantly lower than healthy controls. Bacteroides, Lachnospira, and Ruminiclostridium_9 were positively associated with better cognitive functions whereas Prevotella was on the contrary when subjects of all three groups were considered. The negative correlation of Prevotella with cognitive functions remained among patients with MCI. CONCLUSION: Patients newly diagnosed with AD or MCI have gut dysbiosis that includes the decrease of potentially protective microbiome, such as Bacteroides, and the increase of microbiome that can promote inflammation, such as Prevotella. Our results support a novel idea that the degree of gut dysbiosis is worsened with the disease stage from MCI to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asians; Biodiversity; China; Cognition; Cognitive Dysfunction; Disease Progression; Feces; Female; Gastrointestinal Microbiome; Humans; Male; Middle Aged; RNA, Ribosomal, 16S

Gut Microbiota Changes and Their Correlation with Cognitive and Neuropsychiatric Symptoms in Alzheimer's Disease. - Zhou, Yunzhe; Wang, Yan; Quan, Meina; Zhao, Huiying; Jia, Jianping (J Alzheimers Dis, 2021)
BACKGROUND: Gut microbiota can influence human brain function and behavior. Recent studies showed that gut microbiota might play an important role in the pathogenesis of Alzheimer's disease (AD). OBJECTIVE: To investigate the composition of gut microbiota in AD patients and their association with cognitive function and neuropsychiatric symptoms (NPS). METHODS: The fecal samples from 60 AD patients (30 with NPS and 30 without NPS) and 32 healthy control subjects (HC) were collected and analyzed by 16S ribosomal RNA sequencing. The functional variations of gut microbiota were predicted using Phylogenetic Investigation of Communities by Reconstruction of Unobserved States. The correlation between different bacterial taxa and cognitive (Mini-Mental State Examination (MMSE), Clinical Dementia Rating (CDR)), and NPS measures were analyzed. RESULTS: The fecal microbial composition of AD patients was quite distinct from HC. Bifidobacterium, Sphingomonas, Lactobacillus, and Blautia were enriched, while Odoribacter, Anaerobacterium, and Papillibacter were reduced. AD patients with NPS showed decreased Chitinophagaceae, Taibaiella, and Anaerobacterium compared with those without NPS. Functional pathways were different between AD and HC, and between AD patients with and without NPS. Correlation analysis showed that Sphingomonas correlated negatively with MMSE; Anaerobacterium and Papillibacter correlated positively with MMSE and negatively with CDR. Cytophagia, Rhodospirillaceae, and Cellvibrio correlated positively with NPS, while Chitinophagaceae, Taibaiella, and Anaerobacterium correlated negatively with NPS. CONCLUSION: AD patients have gut microbiota alterations related to cognition, and differential taxa between AD patients with and without NPS associated differently with NPS domains, which helps further understand the pathogenesis of AD and explore potential therapeutic targets.

Latent Cognitive Class at Enrollment Predicts Future Cognitive Trajectories of Decline in a Community Sample of Older Adults. - Zammit, Andrea R; Yang, Jingyun; Buchman, Aron S; Leurgans, Sue E; Muniz-Terrera, Graciela; Lipton, Richard B; Hall, Charles B; Boyle, Patricia; Bennett, David A (J Alzheimers Dis, 2021)
BACKGROUND: Methods that can identify subgroups with different trajectories of cognitive decline are crucial for isolating the biologic mechanisms which underlie these groupings. OBJECTIVE: This study grouped older adults based on their baseline cognitive profiles using a latent variable approach and tested the hypothesis that these groups would differ in their subsequent trajectories of cognitive change. METHODS: In this study we applied time-varying effects models (TVEMs) to examine the longitudinal trajectories of cognitive decline across different subgroups of older adults in the Rush Memory and Aging Project. RESULTS: A total of 1,662 individuals (mean age = 79.6 years, SD = 7.4, 75.4%female) participated in the study; these were categorized into five previously identified classes of older adults differing in their baseline cognitive profiles: Superior Cognition (n = 328, 19.7%), Average Cognition (n = 767, 46.1%), Mixed-Domains Impairment (n = 71, 4.3%), Memory-Specific Impairment (n = 274, 16.5%), and Frontal Impairment (n = 222, 13.4%). Differences in the trajectories of cognition for these five classes persisted during 8 years of follow-up. Compared with the Average Cognition class, The Mixed-Domains and Memory-Specific Impairment classes showed steeper rates of decline, while other classes showed moderate declines. CONCLUSION: Baseline cognitive classes of older adults derived through the use of latent variable methods were associated with distinct longitudinal trajectories of cognitive decline that did not converge during an average of 8 years of follow-up.

Memory-Related Frontal Brainwaves Predict Transition to Mild Cognitive Impairment in Healthy Older Individuals Five Years Before Diagnosis. - Jiang, Yang; Li, Juan; Schmitt, Frederick A; Jicha, Gregory A; Munro, Nancy B; Zhao, Xiaopeng; Smith, Charles D; Kryscio, Richard J; Abner, Erin L (J Alzheimers Dis, 2021)
BACKGROUND: Early prognosis of high-risk older adults for amnestic mild cognitive impairment (aMCI), using noninvasive and sensitive neuromarkers, is key for early prevention of Alzheimer's disease. We have developed individualized measures in electrophysiological brain signals during working memory that distinguish patients with aMCI from age-matched cognitively intact older individuals. OBJECTIVE: Here we test longitudinally the prognosis of the baseline neuromarkers for aMCI risk. We hypothesized that the older individuals diagnosed with incident aMCI already have aMCI-like brain signatures years before diagnosis. METHODS: Electroencephalogram (EEG) and memory performance were recorded during a working memory task at baseline. The individualized baseline neuromarkers, annual cognitive status, and longitudinal changes in memory recall scores up to 10 years were analyzed. RESULTS: Seven of the 19 cognitively normal older adults were diagnosed with incident aMCI for a median 5.2 years later. The seven converters' frontal brainwaves were statistically identical to those patients with diagnosed aMCI (n = 14) at baseline. Importantly, the converters' baseline memory-related brainwaves (reduced mean frontal responses to memory targets) were significantly different from those who remained normal. Furthermore, differentiation pattern of left frontal memory-related responses (targets versus nontargets) was associated with an increased risk hazard of aMCI (HR = 1.47, 95% CI 1.03, 2.08). CONCLUSION: The memory-related neuromarkers detect MCI-like brain signatures about five years before diagnosis. The individualized frontal neuromarkers index increased MCI risk at baseline. These noninvasive neuromarkers during our Bluegrass memory task have great potential to be used repeatedly for individualized prognosis of MCI risk and progression before clinical diagnosis.
Keywords: Aged; Brain Waves; Cognition; Cognitive Dysfunction; Electroencephalography; Female; Humans; Longitudinal Studies; Male; Memory, Short-Term; Neuropsychological Tests; Prodromal Symptoms

Metabolites Associated with Early Cognitive Changes Implicated in Alzheimer's Disease. - Darst, Burcu F; Huo, Zhiguang; Jonaitis, Erin M; Koscik, Rebecca L; Clark, Lindsay R; Lu, Qiongshi; Kremen, William S; Franz, Carol E; Rana, Brinda; Lyons, Michael J; Hogan, Kirk J; Zhao, Jinying; et al. (J Alzheimers Dis, 2021)

Mortality After Ischemic Stroke in Patients with Alzheimer's Disease Dementia and Other Dementia Disorders. - Zupanic, Eva; von Euler, Mia; Winblad, Bengt; Xu, Hong; Secnik, Juraj; Kramberger, Milica Gregoric; Religa, Dorota; Norrving, Bo; Garcia-Ptacek, Sara (J Alzheimers Dis, 2021)
BACKGROUND: Stroke and dementia are interrelated diseases and risk for both increases with age. Even though stroke incidence and age-standardized death rates have decreased due to prevention of stroke risk factors, increased utilization of reperfusion therapies, and other changes in healthcare, the absolute numbers are increasing due to population growth and aging. OBJECTIVE: To analyze predictors of death after stroke in patients with dementia and investigate possible time and treatment trends. METHODS: A national longitudinal cohort study 2007-2017 using Swedish national registries. We compared 12,629 ischemic stroke events in patients with dementia with matched 57,954 stroke events in non-dementia controls in different aspects of patient care and mortality. Relationship between dementia status and dementia type (Alzheimer's disease and mixed dementia, vascular dementia, other dementias) and death was analyzed using Cox regressions. RESULTS: Differences in receiving intravenous thrombolysis between patients with and without dementia disappeared after the year 2015 (administered to 11.1% dementia versus 12.3% non-dementia patients, p = 0.117). One year after stroke, nearly 50% dementia and 30% non-dementia patients had died. After adjustment for demographics, mobility, nursing home placement, and comorbidity index, dementia was an independent predictor of death compared with non-dementia patients (HR 1.26 [1.23-1.29]). CONCLUSION: Dementia before ischemic stroke is an independent predictor of death. Over time, early and delayed mortality in patients with dementia remained increased, regardless of dementia type. Patients with≤80 years with prior Alzheimer's disease or mixed dementia had higher mortality rates after stroke compared to patients with prior vascular dementia.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Fibrinolytic Agents; Humans; Incidence; Ischemic Stroke; Male; Registries; Survival Rate; Sweden; Thrombolytic Therapy

One-Year Aerobic Exercise Reduced Carotid Arterial Stiffness and Increased Cerebral Blood Flow in Amnestic Mild Cognitive Impairment. - Tomoto, Tsubasa; Liu, Jie; Tseng, Benjamin Y; Pasha, Evan P; Cardim, Danilo; Tarumi, Takashi; Hynan, Linda S; Munro Cullum, C; Zhang, Rong (J Alzheimers Dis, 2021)
BACKGROUND: Central arterial stiffness and brain hypoperfusion are emerging risk factors of Alzheimer's disease (AD). Aerobic exercise training (AET) may improve central arterial stiffness and brain perfusion. OBJECTIVE: To investigate the effects of AET on central arterial stiffness and cerebral blood flow (CBF) in patients with amnestic mild cognitive impairment (MCI), a prodromal stage of AD. METHODS: This is a proof-of-concept, randomized controlled trial that assigned 70 amnestic MCI patients into a 12-month program of moderate-to-vigorous AET or stretching-and-toning (SAT) intervention. Carotid β-stiffness index and CBF were measured by color-coded duplex ultrasonography and applanation tonometry. Total CBF was measured as the sum of CBF from both the internal carotid and vertebral arteries, and divided by total brain tissue mass assessed with MRI to obtain normalized CBF (nCBF). Episodic memory and executive function were assessed using standard neuropsychological tests (CVLT-II and D-KEFS). Changes in cardiorespiratory fitness were measured by peak oxygen uptake (VO2peak). RESULTS: Total 48 patients (29 in SAT and 19 in AET) were completed one-year training. AET improved VO2peak, decreased carotid β-stiffness index and CBF pulsatility, and increased nCBF. Changes in VO2peak were associated positively with changes in nCBF (r = 0.388, p = 0.034) and negatively with carotid β-stiffness index (r = -0.418, p = 0.007) and CBF pulsatility (r = -0.400, p = 0.014). Decreases in carotid β-stiffness were associated with increases in cerebral perfusion (r = -0.494, p = 0.003). AET effects on cognitive performance were minimal compared with SAT. CONCLUSION: AET reduced central arterial stiffness and increased CBF which may precede its effects on neurocognitive function in patients with MCI.
Keywords: Aged; Brain; Cardiorespiratory Fitness; Carotid Arteries; Cerebrovascular Circulation; Cognitive Dysfunction; Exercise; Humans; Magnetic Resonance Imaging; Neuropsychological Tests; Vascular Stiffness

Paraoxonase 1, B Vitamins Supplementation, and Mild Cognitive Impairment. - Perła-Kaján, Joanna; Włoczkowska, Olga; Zioła-Frankowska, Anetta; Frankowski, Marcin; David Smith, A; de Jager, Celeste A; Refsum, Helga; Jakubowski, Hieronim (J Alzheimers Dis, 2021)
BACKGROUND: Identification of modifiable risk factors that affect cognitive decline is important for the development of preventive and treatment strategies. Status of paraoxonase 1 (PON1), a high-density lipoprotein-associated enzyme, may play a role in the development of neurological diseases, including Alzheimer's disease. OBJECTIVE: We tested a hypothesis that PON1 status predicts cognition in individuals with mild cognitive impairment (MCI). METHODS: Individuals with MCI (n = 196, 76.8-years-old, 60% women) participating in a randomized, double-blind placebo-controlled trial (VITACOG) were assigned to receive a daily dose of folic acid (0.8 mg), vitamin B12 (0.5 mg) and B6 (20 mg) (n = 95) or placebo (n = 101) for 2 years. Cognition was analyzed by neuropsychological tests. Brain atrophy was quantified in a subset of participants (n = 168) by MRI. PON1 status, including PON1 Q192R genotype, was determined by quantifying enzymatic activity of PON1 using paraoxon and phenyl acetate as substrates. RESULTS: In the placebo group, baseline phenylacetate hydrolase (PhAcase) activity of PON1 (but not paraoxonase activity or PON1 Q192R genotype) was significantly associated with global cognition (Mini-Mental State Examination, MMSE; Telephone Inventory for Cognitive Status-modified, TICS-m), verbal episodic memory (Hopkins Verbal Learning Test-revised: Total Recall, HVLT-TR; Delayed Recall, HVLT-DR), and attention/processing speed (Trail Making A and Symbol Digits Modalities Test, SDMT) at the end of study. In addition to PhAcase, baseline iron and triglycerides predicted MMSE, baseline fatty acids predicted SDMT, baseline anti-N-Hcy-protein autoantibodies predicted TICS-m, SDMT, Trail Making A, while BDNF V66M genotype predicted HVLT-TR and HVLT-DR scores at the end of study. B-vitamins abrogated associations of PON1 and other variables with cognition. CONCLUSION: PON1 is a new factor associated with impaired cognition that can be ameliorated by B-vitamins in individuals with MCI.

Periodontal Disease and Risk of Dementia in Medicare Patients with Hepatitis C Virus. - Malone, Joseph; Jung, Jeah; Tran, Linh; Zhao, Chen (J Alzheimers Dis, 2021)
BACKGROUND: Periodontal disease and hepatitis C virus (HCV) represent chronic infectious states that are common in elderly adults. Both conditions have independently been associated with an increased risk for dementia. Chronic infections are thought to lead to neurodegenerative changes in the central nervous system possibly by promoting a proinflammatory state. This is consistent with growing literature on the etiological role of infections in dementia. Few studies have previously evaluated the association of periodontal disease with dementia in HCV patients. OBJECTIVE: To examine whether periodontal disease increases the risk of developing Alzheimer's disease and related dementias (ADRD) among HCV patients in Medicare claims data. METHODS: We used Medicare claims data for HCV patients to assess the incidence rate of ADRD with and without exposure to periodontal disease between 2014 and 2017. Cox multivariate regression was used to estimate the association between periodontal disease and development of ADRD, controlling for age, gender, race, ZIP-level income and education, and medical comorbidities. RESULTS: Of 439,760 HCV patients, the incidence rate of ADRD was higher in patients with periodontal diseases compared to those without (10.84% versus 9.26%, p <  0.001), and those with periodontal disease developed ADRD earlier compared to those without periodontal disease (13.99 versus 21.60 months, p <  0.001). The hazard of developing ADRD was 1.35 times higher in those with periodontal disease (95% CI, 1.30 to 1.40, p <  0.001) after adjusting for all covariates, including age. CONCLUSION: Periodontal disease increased the risk of developing ADRD among HCV patients in a national Medicare claims dataset.

Plasma Neurofilament Light Chain Predicts Cognitive Progression in Prodromal and Clinical Dementia with Lewy Bodies. - Pilotto, Andrea; Imarisio, Alberto; Carrarini, Claudia; Russo, Mirella; Masciocchi, Stefano; Gipponi, Stefano; Cottini, Elisabetta; Aarsland, Dag; Zetterberg, Henrik; Ashton, Nicholas J; Hye, Abdul; Bonanni, Laura; et al. (J Alzheimers Dis, 2021)
Plasma neurofilament light chain (NfL) is a marker of neuronal damage in different neurological disorders and might predict disease progression in dementia with Lewy bodies (DLB). The study enrolled 45 controls and 44 DLB patients (including 17 prodromal cases) who underwent an extensive assessment at baseline and at 2 years follow-up. At baseline, plasma NfL levels were higher in both probable DLB and prodromal cases compared to controls. Plasma NfL emerged as the best predictor of cognitive decline compared to age, sex, and baseline severity variables. The study supports the role of plasma NfL as a useful prognostic biomarker from the early stages of DLB.

Plasma Total-Tau and Neurofilament Light Chain as Diagnostic Biomarkers of Alzheimer's Disease Dementia and Mild Cognitive Impairment in Adults with Down Syndrome. - Petersen, Melissa E; Rafii, Michael S; Zhang, Fan; Hall, James; Julovich, David; Ances, Beau M; Schupf, Nicole; Krinsky-McHale, Sharon J; Mapstone, Mark; Silverman, Wayne; Lott, Ira; Klunk, William; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The need for diagnostic biomarkers of cognitive decline is particularly important among aging adults with Down syndrome (DS). Growing empirical support has identified the utility of plasma derived biomarkers among neurotypical adults with mild cognitive impairment (MCI) and Alzheimer's disease (AD); however, the application of such biomarkers has been limited among the DS population. OBJECTIVE: This study aimed to investigate the cross-sectional diagnostic performance of plasma neurofilament light chain (Nf-L) and total-tau, individually and in combination among a cohort of DS adults. METHODS: Plasma samples were analyzed from n = 305 (n = 225 cognitively stable (CS); n = 44 MCI-DS; n = 36 DS-AD) participants enrolled in the Alzheimer's Biomarker Consortium -Down Syndrome. RESULTS: In distinguishing DS-AD participants from CS, Nf-L alone produced an AUC of 90%, total-tau alone reached 74%, and combined reached an AUC of 86%. When age and gender were included, AUC increased to 93%. Higher values of Nf-L, total-tau, and age were all shown to be associated with increased risk for DS-AD. When distinguishing MCI-DS participants from CS, Nf-L alone produced an AUC of 65%, while total-tau alone reached 56%. A combined model with Nf-L, total-tau, age, and gender produced an AUC of 87%. Both higher values in age and total-tau were found to increase risk for MCI-DS; Nf-L levels were not associated with increased risk for MCI-DS. CONCLUSION: Advanced assay techniques make total-tau and particularly Nf-L useful biomarkers of both AD pathology and clinical status in DS and have the potential to serve as outcome measures in clinical trials for future disease-modifying drugs.

Porphyromonas Gingivalis Infection Induces Synaptic Failure via Increased IL-1β Production in Leptomeningeal Cells. - Huang, Wanyi; Zeng, Fan; Gu, Yebo; Jiang, Muzhou; Zhang, Xinwen; Yan, Xu; Kadowaki, Tomoko; Mizutani, Shinsuke; Kashiwazaki, Haruhiko; Ni, Junjun; Wu, Zhou (J Alzheimers Dis, 2021)
BACKGROUND: Studies have reported that synaptic failure occurs before the Alzheimer's disease (AD) onset. The systemic Porphyromonas gingivalis (P. gingivalis) infection is involved in memory decline. We previously showed that leptomeningeal cells, covering the brain, activate glial cells by releasing IL-1β in response to systemic inflammation. OBJECTIVE: In the present study, we focused on the impact of leptomeningeal cells on neurons during systemic P. gingivalis infection. METHODS: The responses of leptomeningeal cells and cortical neurons to systemic P. gingivalis infection were examined in 15-month-old mice. The mechanism of IL-1β production by P. gingivalis infected leptomeningeal cells was examined, and primary cortical neurons were treated with P. gingivalis infected leptomeningeal cells condition medium (Pg LCM). RESULTS: Systemic P. gingivalis infection increased the expression of IL-1β in leptomeninges and reduced the synaptophysin (SYP) expression in leptomeninges proximity cortex in mice. Leptomeningeal cells phagocytosed P. gingivalis resulting in lysosomal rupture and Cathepsin B (CatB) leakage. Leaked CatB mediated NLRP3 inflammasome activation inducing IL-1β secretion in leptomeningeal cells. Pg LCM decreased the expression of synaptic molecules, including SYP, which was inhibited by an IL-1 receptor antagonist pre-treatment. CONCLUSION: These observations demonstrate that P. gingivalis infection is involved in synaptic failure by inducing CatB/NLRP3 inflammasome-mediated IL-1β production in leptomeningeal cells. The periodontal bacteria-induced synaptic damage may accelerate the onset and cognitive decline of AD.

The Potential Role of Ferroptosis in Alzheimer's Disease. - Zhang, Guimei; Zhang, Yaru; Shen, Yanxin; Wang, Yongchun; Zhao, Meng; Sun, Li (J Alzheimers Dis, 2021)
Alzheimer's disease (AD) is the most prevalent cause of dementia, accounting for approximately 60%-80%of all cases. Although much effort has been made over the years, the precise mechanism of AD has not been completely elucidated. Recently, great attention has shifted to the roles of iron metabolism, lipid peroxidation, and oxidative stress in AD pathogenesis. We also note that these pathological events are the vital regulators of a novel regulatory cell death, termed ferroptosis-an iron-dependent, oxidative, non-apoptotic cell death. Ferroptosis differs from apoptosis, necrosis, and autophagy with respect to morphology, biochemistry, and genetics. Mounting evidence suggests that ferroptosis may be involved in neurological disorders, including AD. Here, we review the underlying mechanisms of ferroptosis; discuss the potential interaction between AD and ferroptosis in terms of iron metabolism, lipid peroxidation, and the glutathione/glutathione peroxidase 4 axis; and describe some associated studies that have explored the implication of ferroptosis in AD.
Keywords: Alzheimer Disease; Animals; Ferroptosis; Humans

Proteome Profiling Identified Amyloid-β Protein Precursor as a Novel Binding Partner and Modulator of VGLUT1. - Zhou, Jin-Wu; Zhao, Man; Rang, Wen-Liang; Zhang, Xiao-Yan; Liu, Zhen-Ming; Zhang, Liang-Ren; Wang, Tong-Xing; Wu, Chu-Tse; Cheng, Xiao-Rui; Zhou, Wen-Xia (J Alzheimers Dis, 2021)
BACKGROUND: The toxicity of excessive glutamate release has been implicated in various acute and chronic neurodegenerative conditions. Vesicular glutamate transporters (VGLUTs) are the major mediators for the uptake of glutamate into synaptic vesicles. However, the dynamics and mechanism of this process in glutamatergic neurons are still largely unknown. OBJECTIVE: This study aimed to investigate the candidate protein partners of VGLUT1 and their regulatory roles in the vesicles in rat brain. METHODS: Pull down assay, co-immunoprecipitation assay, or split-ubiquitin membrane yeast two hybrid screening coupled with nanoRPLC-MS/MS were used to identify the candidate protein partners of VGLUT1 in the vesicles in rat brain. The in vitro and in vivo models were used to test effects of AβPP, Atp6ap2, Gja1, and Synataxin on VGLUT1 expression. RESULTS: A total of 255 and 225 proteins and 172 known genes were identified in the pull down assay, co-immunoprecipitation assay, or split-ubiquitin yeast two-hybrid screening respectively. The physiological interactions of SV2A, Syntaxin 12, Gja1, AβPP, and Atp6ap2 to VGLUT1 were further confirmed. Knockdown of Atp6ap2, Gja1, and Synataxin increased VGLUT1 mRNA expression and only knockdown of AβPP increased both mRNA and protein levels of VGLUT1 in PC12 cells. The regulatory function of AβPP on VGLUT1 expression was further confirmed in the in vitro and in vivo models. CONCLUSION: These results elucidate that the AβPP and VGLUT1 interacts at vesicular level and AβPP plays a role in the regulation of VGLUT1 expression which is essential for maintaining vesicular activities.

Research Attitudes and Interest Among Elderly Latinxs: The Impact of a Collaborative Video and Community Peers. - Sewell, Margaret C; Neugroschl, Judith; Umpierre, Mari; Chin, Shehan; Zhu, Carolyn W; Velasco, Nelly; Gonzalez, Sabrina; Acabá-Berrocal, Alexandra; Bianchetti, Luca; Silva, Gabriela; Collazo, Alma; Sano, Mary (J Alzheimers Dis, 2021)
BACKGROUND: Latinx elders are underrepresented in dementia research. In a previous study we assessed research attitudes in urban minority elders and found a significant minority expressed neutral to negative attitudes relating to trust, safety, and personal responsibility to help research. OBJECTIVE: To assess the impact of a composite intervention on attitudes toward research and research participation among elderly Latinx. The intervention was a collaboratively produced research participation video shown during presentations with our elderly community advisory board (CAB) as co-presenters. METHODS: The video was created by the ADRC and CAB. All senior center attendees were eligible to participate. Afterwards, the Research Attitudes Questionnaire (RAQ) and a brief questionnaire on the impact of the video were administered. Using Wilcoxon Rank Sum Tests, Chi Square, and OLS regressions, RAQ responses were compared to those from a historical cohort from similar centers. RESULTS: 74 in the "Historical Cohort 1" and 104 in "Intervention Cohort 2" were included. RAQ total score was higher in Cohort 2 than Cohort 1 (28.5 versus 26.1, p <  0.05) after controlling for age, education, and country of origin. In response to the question "Has the video influenced your willingness and interest to participate in research", 88.7%of the participants in Cohort 2 reported being "more" or "much more" interested in research. CONCLUSION: Tailoring community research recruitment programs to include relatable peers using novel recruitment techniques may have positive implications for improving enrollment of diverse elderly individuals in research.

The Retinal Vessel Density Can Reflect Cognitive Function in Patients with Alzheimer's Disease: Evidence from Optical Coherence Tomography Angiography. - Yan, Yibing; Wu, Xingqi; Wang, Xiaojing; Geng, Zhi; Wang, Lu; Xiao, Guixian; Wu, Yue; Zhou, Shanshan; Liao, Rongfeng; Wei, Ling; Tian, Yanghua; Wang, Kai (J Alzheimers Dis, 2021)
BACKGROUND: There is increasing evidence that Alzheimer's disease (AD) patients may present decreased cerebral blood perfusion before pathological brain changes. Using the retina as a window to the brain, we can study disorders of the central nervous system through the eyes. OBJECTIVE: This study aimed to investigate differences in retinal structure and vessel density (VD) between patients with mild AD and healthy controls (HCs). Furthermore, we explored the relationship between retinal VD and cognitive function. METHODS: We enrolled 37 patients with AD and 29 age-matched HCs who underwent standard ophthalmic optical coherence tomography angiography (OCTA) for evaluation of the retinal layer thickness and VD parameters. Cognitive function was evaluated using a battery of neuropsychological assessments. Finally, the correlations among retinal layer thickness, VD parameters, and cognitive function were evaluated. RESULTS: The retinal fiber layer thickness and retinal VD of patients with AD were significantly reduced compared with HCs. The retinal VD was significantly correlated with overall cognition, memory, executive, and visual-spatial perception functions. However, there was no significant between-group difference in the macular thickness. CONCLUSION: Our findings indicate a positive correlation between retinal VD and some, but not all, cognitive function domains. Most importantly, we demonstrated the role of OCTA in detecting early capillary changes, which could be a noninvasive biomarker for early AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Retinal Vessels; Tomography, Optical Coherence

Synaptic Molecular and Neurophysiological Markers Are Independent Predictors of Progression in Alzheimer's Disease. - Smailovic, Una; Kåreholt, Ingemar; Koenig, Thomas; Ashton, Nicholas J; Winblad, Bengt; Höglund, Kina; Nilsson, Per; Zetterberg, Henrik; Blennow, Kaj; Jelic, Vesna (J Alzheimers Dis, 2021)
BACKGROUND: Cerebrospinal fluid (CSF) neurogranin and quantitative electroencephalography (qEEG) are potential molecular and functional markers of synaptic pathology in Alzheimer's disease (AD). Synaptic markers have emerged as candidate prognostic indicators of AD since synaptic degeneration was shown to be an early event and the best correlate of cognitive deficits in patients along the disease continuum. OBJECTIVE: The present study investigated the association between CSF neurogranin and qEEG measures as well as their potential to predict clinical deterioration in mild cognitive impairment (MCI) patients. METHODS: Patients diagnosed with MCI (n = 99) underwent CSF conventional AD biomarkers and neurogranin analysis and resting-state EEG recordings. The study population was further stratified into stable (n = 41) and progressive MCI (n = 31), based on the progression to AD dementia during two years follow-up. qEEG analysis included computation of global field power and global field synchronization in four conventional frequency bands. RESULTS: CSF neurogranin levels were associated with theta power and synchronization in the progressive MCI group. CSF neurogranin and qEEG measures were significant predictors of progression to AD dementia, independent of baseline amyloid status in MCI patients. A combination of CSF neurogranin with global EEG power in theta and global EEG synchronization in beta band exhibited the highest classification accuracy as compared to either of these markers alone. CONCLUSION: qEEG and CSF neurogranin are independent predictors of progression to AD dementia in MCI patients. Molecular and neurophysiological synaptic markers may have additive value in a multimodal diagnostic and prognostic approach to dementia.

Time Trends of Cerebrospinal Fluid Biomarkers of Neurodegeneration in Idiopathic Normal Pressure Hydrocephalus. - Lukkarinen, Heikki; Tesseur, Ina; Pemberton, Darrel; van der Ark, Peter; Timmers, Maarten; Slemmon, Randy; Janssens, Luc; Streffer, Johannes; Van Nueten, Luc; Bottelbergs, Astrid; Rauramaa, Tuomas; Koivisto, Anne M; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Longitudinal changes in cerebrospinal fluid (CSF) biomarkers are seldom studied. Furthermore, data on biomarker gradient between lumbar (L-) and ventricular (V-) compartments seems to be discordant. OBJECTIVE: To examine alteration of CSF biomarkers reflecting Alzheimer's disease (AD)-related amyloid-β (Aβ) aggregation, tau pathology, neurodegeneration, and early synaptic degeneration by CSF shunt surgery in idiopathic normal pressure hydrocephalus (iNPH) in relation to AD-related changes in brain biopsy. In addition, biomarker levels in L- and V-CSF were compared. METHODS: L-CSF was collected prior to shunt placement and, together with V-CSF, 3-73 months after surgery. Thereafter, additional CSF sampling took place at 3, 6, and 18 months after the baseline sample from 26 iNPH patients with confirmed Aβ plaques in frontal cortical brain biopsy and 13 iNPH patients without Aβ pathology. CSF Amyloid-β42 (Aβ42), total tau (T-tau), phosphorylated tau (P-tau181), neurofilament light (NFL), and neurogranin (NRGN) were analyzed with customized ELISAs. RESULTS: All biomarkers but Aβ42 increased notably by 140-810% in L-CSF after CSF diversion and then stabilized. Aβ42 instead showed divergent longitudinal decrease between Aβ-positive and -negative patients in L-CSF, and thereafter increase in Aβ-negative iNPH patients in both L- and V-CSF. All five biomarkers correlated highly between V-CSF and L-CSF (Aβ42 R = 0.87, T-tau R = 0.83, P-tau R = 0.92, NFL R = 0.94, NRGN R = 0.9; all p <  0.0001) but were systematically lower in V-CSF (Aβ42 14 %, T-tau 22%, P-tau 20%, NFL 32%, NRGN 19%). With APOE genotype-grouping, only Aβ42 showed higher concentration in non-carriers of allele ɛ4. CONCLUSION: Longitudinal follow up shows that after an initial post-surgery increase, T-tau, P-tau, and NRGN are stable in iNPH patients regardless of brain biopsy Aβ pathology, while NFL normalized toward its pre-shunt levels. Aβ42 as biomarker seems to be the least affected by the surgical procedure or shunt and may be the best predictor of AD risk in iNPH patients. All biomarker concentrations were lower in V- than L-CSF yet showing strong correlations.

Urban Air Pollution Nanoparticles from Los Angeles: Recently Decreased Neurotoxicity. - Zhang, Hongqiao; D'Agostino, Carla; Forman, Henry Jay; Cacciottolo, Mafalda; Thorwald, Max; Mack, William J; Liu, Qinghai; Shkirkova, Kristina; Lamorie-Foote, Krista; Sioutas, Constantinos; Pirhadi, Milad; Mack, Wendy Jean; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution is widely associated with accelerated cognitive decline at later ages and risk of Alzheimer's disease (AD). Correspondingly, rodent models demonstrate the neurotoxicity of ambient air pollution and its components. Our studies with nano-sized particulate matter (nPM) from urban Los Angeles collected since 2009 have shown pro-amyloidogenic and pro-inflammatory responses. However, recent batches of nPM have diminished induction of the glutamate receptor GluA1 subunit, Iba1, TNFα, Aβ42 peptide, and white matter damage. The same methods, materials, and mouse genotypes were used throughout. OBJECTIVE: Expand the nPM batch comparisons and evaluate archived brain samples to identify the earliest change in nPM potency. METHODS: Batches of nPM were analyzed by in vitro cell assays for NF-κB and Nrf2 induction for comparison with in vivo responses of mouse brain regions from mice exposed to these batches, analyzed by PCR and western blot. RESULTS: Five older nPM batches (2009-2017) and four recent nPM batches (2018, 2019) for NF-κB and Nrf2 induction showed declines in nPM potency after 2017 that paralleled declines of in vivo activity from independent exposures in different years. CONCLUSION: Transcription-based in vitro assays of nPM corresponded to the loss of in vivo potency for inflammatory and oxidative responses. These recent decreases of nPM neurotoxicity give a rationale for evaluating possible benefits to the risk of dementia and stroke in Los Angeles populations.

Angiotensin II Blood Levels Are Associated with Smaller Hippocampal and Cortical Volumes in Cognitively Normal Older Adults. - Yasar, Sevil; Moored, Kyle D; Adam, Atif; Zabel, Fiona; Chuang, Yi-Fang; Varma, Vijay R; Carlson, Michelle C (J Alzheimers Dis, 2020)
BACKGROUND: There is emerging evidence about possible involvement of the renin-angiotensin system (RAS) in the pathogenesis of Alzheimer's disease (AD) and decline of cognitive function. However, little is known about associations with brain biomarkers. OBJECTIVE: Our study aimed to examine associations between blood ACE-1 and ANG II levels and brain MRI based volumes in non-demented participants, and whether these associations were mediated by blood pressure. METHODS: This cross-sectional study was conducted in 34 older participants from the Baltimore Experience Corps Trial (BECT) Brain Health Sub-study (BHS). Blood ANGII and ACE-1 levels were measured by ELISA and brain MRI volumes were generated using FreeSurfer 6.0. Multiple linear regression analysis, adjusting for intracranial volume and confounders, was used to determine associations between log transformed ANGII and ACE-1 levels and MRI volumes (mm3). RESULTS: Participants were predominantly female (76%), African-American (94%), with mean age of 66.9 and education of 14.4 years. In the fully adjusted model we observed significant inverse associations between log ANGII levels and total grey matter (β=Angiotensin II associated with smaller hippocampus14,935.50, ±7,444.83, p = 0.05), total hippocampus (β=-129.97, ±105.27, p = 0.03), rostral middle frontal (β= -1580.40, ±584.74, p = 0.02), and supramarginal parietal (β= -978.90, ±365.54, p = 0.02) volumes. There were no associations between ANGII levels and total white matter or entorhinal cortex volumes, or ACE-1 levels and any brain volumes. CONCLUSION: We observed that increased blood ANGII levels were associated with lower total grey matter, hippocampal, rostral middle frontal, and supramarginal parietal volumes, which are associated with cognitive domains that decline in preclinical AD.

Anterior Cingulate Structure and Perfusion Is Associated with Cerebrospinal Fluid Tau Among Cognitively Normal Older Adult APOEɛ4 Carriers. - Hays, Chelsea C; Zlatar, Zvinka Z; Meloy, M J; Osuna, Jessica; Liu, Thomas T; Galasko, Douglas R; Wierenga, Christina E (J Alzheimers Dis, 2020)
Evidence suggests the ɛ4 allele of the apolipoprotein E gene (APOE) may accelerate an age-related process of cortical thickening and cerebral blood flow (CBF) reduction in the anterior cingulate cortex (ACC). Although the neural basis of this association remains unclear, evidence suggests it might reflect early neurodegenerative processes. However, to date, associations between cerebrospinal fluid (CSF) biomarkers of neurodegeneration, such as CSF tau, and APOE-related alterations in ACC cortical thickness (CTH) and CBF have yet to be explored. The current study explored the interaction of CSF tau and APOE genotype (ɛ4+, ɛ4-) on FreeSurfer-derived CTH and arterial spin labeling MRI-measured resting CBF in the ACC (caudal ACC [cACC] and rostral ACC [rACC]) among a sample of 45 cognitively normal older adults. Secondary analyses also examined associations between APOE, CTH/CBF, and cognitive performance. In the cACC, higher CSF tau was associated with higher CTH and lower CBF in ɛ4+, whereas these relationships were not evident in ɛ4-. In the rACC, higher CSF tau was associated with higher CTH for both ɛ4+ and ɛ4-, and with lower CBF only in ɛ4+. Significant interactions of CSF tau and APOE on CTH/CBF were not observed in two posterior reference regions implicated in Alzheimer's disease. Secondary analyses revealed a negative relationship between cACC CTH and executive functioning in ɛ4+ and a positive relationship in ɛ4-. Findings suggest the presence of an ɛ4-related pattern of increased CTH and CBF reduction in the ACC that is associated with biomarkers of neurodegeneration and subtle decrements in cognition.

The Association of Post-Stroke Cognitive Impairment and Gut Microbiota and its Corresponding Metabolites. - Liu, Yongqiang; Kong, Cheng; Gong, Li; Zhang, Xiaohui; Zhu, Yuefei; Wang, Haichao; Qu, Xiao; Gao, Renyuan; Yin, Fang; Liu, Xueyuan; Qin, Huanlong (J Alzheimers Dis, 2020)
BACKGROUND: Post-stroke cognitive impairment (PSCI) is an important factor causing disabilities after acute ischemic stroke (AIS). Emerging evidence suggested that gut microbiota play an important role in cognitive impairment. OBJECTIVE: This study aimed to explore the association between PSCI and gut microbiota. METHOD: 65 patients with newly diagnostic AIS finished the fecal collection on admission and cognitive assessment 3 months later in the clinic. Fecal samples were subjected to 16SrRNA gene sequencing and gas chromatography-mass spectrometry analysis. Additionally, we enrolled new 18 AIS patients, whose treatment was supplemented by probiotics, to assess the potential of microbial treatment in PSCI. RESULTS: PSCI patients were characterized by the significantly decreased alpha-diversity, disturbed microbial composition, and corresponding metabolites compared with non-PSCI patients. Increased Fusobacterium and deficiency of microbial metabolized short-chain fatty acids (SCFAs) were significantly associated with PSCI. A model based on gut microbiota and SCFAs could predict 3 months or longer PSCI early and accurately after stroke onset. While traditional probiotic administration had little effect on PSCI, it could ameliorate patients' mood, including depression and anxiety in the 3 months after stroke. CONCLUSION: Our study revealed the association between PSCI and gut microbiota and its corresponding metabolites for the first time, suggesting the potential for applying microbiota and its corresponding metabolites to early clinical diagnosis and treatment of PSCI.

Cerebrospinal Fluid Metals and the Association with Cerebral Small Vessel Disease. - Shams, Mana; Martola, Juha; Charidimou, Andreas; Granberg, Tobias; Ferreira, Daniel; Westman, Eric; Wintermark, Max; Iv, Michael; Larvie, Mykol; Kristoffersen Wiberg, Maria; Kaijser, Magnus; Forsgard, Niklas; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Brain metal homeostasis is essential for brain health, and deregulation can result in oxidative stress on the brain parenchyma. OBJECTIVE: Our objective in this study was to focus on two hemorrhagic MRI manifestations of small vessel disease [cerebral microbleeds (CMBs) and cortical superficial siderosis (cSS)] and associations with cerebrospinal fluid (CSF) iron levels. In addition, we aimed to analyze CSF biomarkers for dementia and associations with CSF metal levels. METHODS: This is a cross-sectional study of 196 patients who underwent memory clinic investigation, including brain MRI. CSF was collected and analyzed for metals, amyloid-β (Aβ) 42, total tau (T-tau), and phosphorylated tau (P-tau), and CSF/serum albumin ratios. Statistical analyses were performed using generalized linear models. RESULTS: No significant difference was found between CSF metal levels across diagnostic groups. Higher iron and copper levels were associated with higher CSF levels of Aβ42, T-tau, P-tau, and CSF/serum albumin ratios (p < 0.05). Zinc was associated with higher CSF/serum albumin ratios. There was no significant association between CMBs or cSS and CSF iron levels. An increase in CSF iron with the number of CMBs was seen in APOEɛ4 carriers. CONCLUSION: CSF iron levels are elevated with cerebral microbleeds in APOEɛ4 carriers, with no other association seen with hemorrhagic markers of small vessel disease. The association of elevated CSF iron and copper with tau could represent findings of increased neurodegeneration in these patients.

Circulating Vitamin D Levels and Alzheimer's Disease: A Mendelian Randomization Study in the IGAP and UK Biobank. - Wang, Longcai; Qiao, Yanchun; Zhang, Haihua; Zhang, Yan; Hua, Jiao; Jin, Shuilin; Liu, Guiyou (J Alzheimers Dis, 2020)
Observational studies strongly supported the association of low levels of circulating 25-hydroxyvitamin D (25OHD) and cognitive impairment or dementia in aging populations. However, randomized controlled trials have not shown clear evidence that vitamin D supplementation could improve cognitive outcomes. In fact, some studies reported the association between vitamin D and cognitive impairment based on individuals aged 60 years and over. However, it is still unclear that whether vitamin D levels are causally associated with Alzheimer's disease (AD) risk in individuals aged 60 years and over. Here, we performed a Mendelian randomization (MR) study to investigate the causal association between vitamin D levels and AD using a large-scale vitamin D genome-wide association study (GWAS) dataset and two large-scale AD GWAS datasets from the IGAP and UK Biobank with individuals aged 60 years and over. Our results showed that genetically increased 25OHD levels were significantly associated with reduced AD risk in individuals aged 60 years and over. Hence, our findings in combination with previous literature indicate that maintaining adequate vitamin D status in older people especially aged 60 years and over, may contribute to slow down cognitive decline and forestall AD. Long-term randomized controlled trials are required to test whether vitamin D supplementation may prevent AD in older people especially those aged 60 years and may be recommended as preventive agents.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biological Specimen Banks; Cognition Disorders; Databases, Factual; Female; Genome-Wide Association Study; Humans; Hydroxycholecalciferols; Male; Mendelian Randomization Analysis; Middle Aged; Nutritional Status; United Kingdom; Vitamin D; Vitamin D Deficiency

Clinical and Bacterial Markers of Periodontitis and Their Association with Incident All-Cause and Alzheimer's Disease Dementia in a Large National Survey. - Beydoun, May A; Beydoun, Hind A; Hossain, Sharmin; El-Hajj, Ziad W; Weiss, Jordan; Zonderman, Alan B (J Alzheimers Dis, 2020)
Microbial agents including periodontal pathogens have recently appeared as important actors in Alzheimer's disease (AD) pathology. We examined associations of clinical periodontal and bacterial parameters with incident all-cause and AD dementia as well as AD mortality among US middle-aged and older adults. Clinical [Attachment Loss (AL); probing pocket depth (PPD)] and bacterial [pathogen immunoglobulin G (IgG)] periodontal markers were investigated in relation to AD and all-cause dementia incidence and to AD mortality, using data from the third National Health and Nutrition Examination Surveys (NHANES III, 1988-1994) linked longitudinally with National Death Index and Medicare data through January 1, 2014, with up to 26 years of follow-up. Sex- and age-specific multivariable-adjusted Cox proportional hazards models were conducted. Among those ≥65 years, AD incidence and mortality were consistently associated with PPD, two factors and one cluster comprised of IgG titers against Porphyromonas gingivalis (P. gingivalis), Prevotella melaninogenica (P. melaninogenica) and Campylobacter rectus (C. rectus) among others. Specifically, AD incidence was linked to a composite of C. rectus and P. gingivalis titers (per SD, aHR = 1.22; 95% CI, 1.04-1.43, p = 0.012), while AD mortality risk was increased with another composite (per SD, aHR = 1.46; 95% CI, 1.09-1.96, p = 0.017) loading highly on IgG for P. gingivalis, Prevotella intermedia, Prevotella nigrescens, Fusobacterium nucleatum, C. rectus, Streptococcus intermedius, Capnocylophaga Ochracea, and P. melaninogenica. This study provides evidence for an association between periodontal pathogens and AD, which was stronger for older adults. Effectiveness of periodontal pathogen treatment on reducing sequelae of neurodegeneration should be tested in randomized controlled trials.

Costs of Early Stage Alzheimer's Disease in the United States: Cross-Sectional Analysis of a Prospective Cohort Study (GERAS-US)1. - Robinson, Rebecca L; Rentz, Dorene M; Andrews, Jeffrey Scott; Zagar, Anthony; Kim, Yongin; Bruemmer, Valerie; Schwartz, Ronald L; Ye, Wenyu; Fillit, Howard M (J Alzheimers Dis, 2020)
BACKGROUND: Costs associated with early stages of Alzheimer's disease (AD; mild cognitive impairment [MCI] and mild dementia [MILD]) are understudied. OBJECTIVE: To compare costs associated with MCI and MILD due to AD in the United States. METHODS: Data included baseline patient/study partner medical history, healthcare resource utilization, and outcome assessments as part of a prospective cohort study. Direct, indirect, and total societal costs were derived by applying standardized unit costs to resources for the 1-month pre-baseline period (USD2017). Costs/month for MCI and MILD cohorts were compared using analysis of variance models. To strengthen the confidence of diagnosis, amyloid-β (Aβ) tests were included and analyses were replicated stratifying within each cohort by amyloid status [+ /-]. RESULTS: Patients (N = 1327) with MILD versus MCI had higher total societal costs/month ($4243 versus $2816; p < 0.001). These costs were not significantly different within each severity cohort by amyloid status. The largest fraction of overall costs were informal caregiver costs (45.1%) for the MILD cohort, whereas direct medical patient costs were the largest for the MCI cohort (39.0%). Correspondingly, caregiver time spent on basic activities of daily living (ADLs), instrumental ADLs, and supervision time was twice as high for MILD versus MCI (all p < 0.001). CONCLUSION: Early AD poses a financial burden, and despite higher functioning among those with MCI, caregivers were significantly impacted. The major cost driver was the patient's clinical cognitive-functional status and not amyloid status. Differences were primarily due to rising need for caregiver support.

Detection of Mild Cognitive Impairment in an At-Risk Group of Older Adults: Can a Novel Self-Administered Serious Game-Based Screening Test Improve Diagnostic Accuracy? - Zygouris, Stelios; Iliadou, Paraskevi; Lazarou, Eftychia; Giakoumis, Dimitrios; Votis, Konstantinos; Alexiadis, Anastasios; Triantafyllidis, Andreas; Segkouli, Sofia; Tzovaras, Dimitrios; Tsiatsos, Thrasyvoulos; Papagianopoulos, Sotirios; Tsolaki, Magda (J Alzheimers Dis, 2020)
BACKGROUND: Literature supports the use of serious games and virtual environments to assess cognitive functions and detect cognitive decline. This promising assessment method, however, has not yet been translated into self-administered screening instruments for pre-clinical dementia. OBJECTIVE: The aim of this study is to assess the performance of a novel self-administered serious game-based test, namely the Virtual Supermarket Test (VST), in detecting mild cognitive impairment (MCI) in a sample of older adults with subjective memory complaints (SMC), in comparison with two well-established screening instruments, the Montreal Cognitive Assessment (MoCA) and the Mini-Mental State Examination (MMSE). METHODS: Two groups, one of healthy older adults with SMC (N = 48) and one of MCI patients (N = 47) were recruited from day centers for cognitive disorders and administered the VST, the MoCA, the MMSE, and an extended pencil and paper neuropsychological test battery. RESULTS: The VST displayed a correct classification rate (CCR) of 81.91% when differentiating between MCI patients and older adults with SMC, while the MoCA displayed of CCR of 72.04% and the MMSE displayed a CCR of 64.89%. CONCLUSION: The three instruments assessed in this study displayed significantly different performances in differentiating between healthy older adults with SMC and MCI patients. The VST displayed a good CCR, while the MoCA displayed an average CCR and the MMSE displayed a poor CCR. The VST appears to be a robust tool for detecting MCI in a population of older adults with SMC.

Development of Classification Models for the Prediction of Alzheimer's Disease Utilizing Circulating Sex Hormone Ratios. - Hayashi, Kentaro; Gonzales, Tina K; Kapoor, Amita; Ziegler, Toni E; Meethal, Sivan Vadakkadath; Atwood, Craig S (J Alzheimers Dis, 2020)
BACKGROUND: While sex hormones are essential for normal cognitive health, those individuals with greater endocrine dyscrasia around menopause and with andropause are more likely to develop cognitive loss and Alzheimer's disease (AD). OBJECTIVE: To assess whether circulating sex hormones may provide an etiologically significant, surrogate biomarker, for cognitive decline. METHODS: Plasma (n = 152) and serum (n = 107) samples from age- and gender-matched AD and control subjects from the Wisconsin Alzheimer's Disease Research Center (ADRC) were analyzed for11 steroids and follicle-stimulating hormone. Logistic regression (LR), correlation analyses, and recursive partitioning (RP) were used to examine the interactions of hormones and hormone ratios and their association with AD. Models generated were then tested on an additional 43 ADRC samples. RESULTS: The wide variation and substantial overlap in the concentrations of all circulating sex steroids across control and AD groups precluded their use for predicting AD. Classification tree analyses (RP) revealed interactions among single hormones and hormone ratios that associated with AD status, the most predictive including only the hormone ratios identified by LR. The strongest associations were observed between cortisol, cortisone, and androstenedione with AD, with contributions from progesterone and 17β-estradiol. Utilizing this model, we correctly predicted 81% of AD test cases and 64% of control test cases. CONCLUSION: We have developed a diagnostic model for AD, the Wisconsin Hormone Algorithm Test for Cognition (WHAT-Cog), that utilizes classification tree analyses of hormone ratios. Further refinement of this technology could provide a quick and cheap diagnostic method for screening those with AD.

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

Gamma Entrainment in a Large Retrospective Cohort: Implications for Photic Stimulation Therapy for Alzheimer's Disease. - Zibrandtsen, Ivan C; Agger, Mikkel; Kjaer, Troels W (J Alzheimers Dis, 2020)
BACKGROUND: Studies on mice models of Alzheimer's disease (AD) have suggested potential therapeutic benefits of intermittent photic stimulation at 40 Hz. OBJECTIVE: We examined the physiological response of 40 Hz intermittent photic stimulation (IPS) on routine EEG in a large retrospective cohort to investigate the effects of age on induced gamma oscillations by intermittent photic stimulation. Since most AD patients are elderly, it is important for future research to know if age affects photic stimulation. METHODS: Retrospective data from 1,464 subjects aged 0- 91. We performed frequency analysis and automatic peak detection and used regression analysis to investigate the effects of age and sex on peak frequencies and amplitude changes. To investigate the spread of the induced gamma oscillations, we assessed averaged topographies of 40 Hz band power. RESULTS: There was a statistically significant but very minor effect of age on amplitude change (- 0.002 normalized power per year, p < 0.0001) but not for sex (p = 0.728). Detection probability of induced peaks was significantly predicted by both age (OR = 0.988, CI 95 % [0.984, 0.993], p < 0.00001) and sex (OR = 0.625, CI 95 % [0.496, 0.787>], p < 0.0001). The induced 40 Hz gamma entrainment is spatially confined to the occipital area. CONCLUSION: There is a significant effect of age on induced gamma activity, but advanced age does not fundamentally change the behavior of the response in either magnitude or spatial distribution. This fact is important regarding future research into the possible therapeutic effects of photic stimulation in patients with AD.

An Immunomodulatory Therapeutic Vaccine Targeting Oligomeric Amyloid-β. - Song, Ge; Yang, Haiqiang; Shen, Ning; Pham, Phillip; Brown, Breanna; Lin, Xiaoyang; Hong, Yuzhu; Sinu, Paul; Cai, Jianfeng; Li, Xiaopeng; Leon, Michael; Gordon, Marcia; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Aging is considered the most important risk factor for Alzheimer's disease (AD). Recent research supports the theory that immunotherapy targeting the "oligomeric" forms of amyloid-β (Aβ) may halt the progression of AD. However, previous clinical trial of the vaccine against Aβ, called AN1792, was suspended due to cases of meningoencephalitis in patients. OBJECTIVE: To develop a peptide sensitized dendritic cells (DCs) vaccine that would target oligomer Aβ and prevent an autoimmune response. METHODS: Double transgenic APPswe/PS1ΔE9 (Tg) and C57BL/6J control mice were used in this study. Cytokine expression profile detection, characterization of antisera, brain GSK-3β, LC3 expression, and spatial working memory testing before and post-vaccination were obtained. RESULTS: Epitope prediction indicated that E22W42 could generate 13 new T cell epitopes which can strengthen immunity in aged subjects and silence several T cell epitopes of the wild type Aβ. The silenced T cell epitope could help avoid the autoimmune response that was seen in some patients of the AN-1792 vaccine. The E22W42 not only helped sensitize bone marrow-derived DCs for the development of an oligomeric Aβ-specific antibody, but also delayed memory impairment in the APP/PS1 mouse model. Most importantly, this E22W42 peptide will not alter the DC's natural immunomodulatory properties. CONCLUSION: The E22W42 vaccine is possibly safer for patients with impaired immune systems. Since there is increasing evidence that oligomeric form of Aβ are the toxic species to neurons, the E22W42 antibody's specificity for these "oligomeric" Aβ species could provide the opportunity to produce some clinical benefits in AD subjects.

lncRNA SNHG1 Knockdown Alleviates Amyloid-β-Induced Neuronal Injury by Regulating ZNF217 via Sponging miR-361-3p in Alzheimer's Disease. - Gao, Yiwen; Zhang, Nan; Lv, Chunmei; Li, Na; Li, Xueqin; Li, Weiwei (J Alzheimers Dis, 2020)
BACKGROUND: Long noncoding RNAs have been proven to play an important role in the progression of Alzheimer's disease (AD). However, the function of small nucleolar RNA host gene 1 (SNHG1) in AD progression remains to be studied. OBJECTIVE: To explore the role of SNHG1 in AD progression and clarify its potential mechanism. METHODS: Amyloid β-protein (Aβ) was used to construct an AD cell model in vitro. The expression levels of SNHG1 and miR-361-3p were determined by quantitative real-time polymerase chain reaction. Cell viability and apoptosis were measured by cell counting kit 8 assay and flow cytometry. The levels of apoptosis-related proteins and zinc finger gene 217 (ZNF217) protein were evaluated by western blot analysis. Additionally, the contents of inflammatory cytokines and oxidative stress markers were tested by enzyme-linked immunosorbent assay. Furthermore, dual-luciferase reporter and RNA immunoprecipitation assays were used to verify the interaction between miR-361-3p and SNHG1 or ZNF217. RESULTS: Aβ could induce cell injury, while resveratrol could reverse this effect. SNHG1 expression was positively regulated by Aβ and negatively regulated by resveratrol. SNHG1 knockdown could reverse the promotion effect of Aβ on cell injury. Moreover, SNHG1 sponged miR-361-3p, and miR-361-3p targeted ZNF217. Additionally, miR-361-3p overexpression reversed the promotion effect of SNHG1 overexpression on cell injury, and ZNF217 silencing also reversed the promotion effect of miR-361-3p inhibitor on cell injury. CONCLUSION: SNHG1 promoted cell injury by regulating the miR-361-3p/ZNF217 axis, which might provide a theoretical basis for molecular therapy of AD.

Resilience of Alzheimer's Disease to COVID-19. - Li, Jingwen; Long, Xi; Huang, Heqing; Tang, Jine; Zhu, Chunli; Hu, Shaoping; Wu, Jing; Li, Jinghong; Lin, Zhicheng; Xiong, Nian (J Alzheimers Dis, 2020)
BACKGROUND: Facing the novel coronavirus disease 2019 (COVID-19), most vulnerable individuals are seniors, especially those with comorbidities. More attention needs to been paid to the COVID-19 patients with Alzheimer's disease (AD), which is the top age-related neurodegenerative disease. OBJECTIVE: Since it is unclear whether AD patients are prone to COVID-19 infection and progression to severe stages, we report for the first time a retrospective analysis of the clinical characteristics of AD patients with COVID-19 pneumonia. METHODS: We conducted a retrospective cohort study of the clinical data of 19 AD patients with COVID-19 pneumonia, compared with 23 non-AD COVID-19 patients admitted at the same time to our hospital. Demographic, clinical, laboratory, radiological, and treatment data were collected and analyzed. RESULTS: Between AD patients and non-AD patients with COVID-19 pneumonia, the pneumonia severity was not significantly different. AD patients had a higher clustering onset than non-AD patients. The median duration from symptom onset to hospitalization were shorter in AD patients than non-AD patients, indicating the former were sent to the hospital by their family or from nursing home earlier than the later. The median duration from hospitalization to discharge seemed shorter in AD patients than non-AD patients. Dementia patients seemed less likely to report fatigue. It is noticed that more AD patients might have pericardial effusion than the non-AD patients. CONCLUSION: AD patients with COVID-19 were in milder conditions with a better prognosis than non-AD patients. AD patients who had adequate access to healthcare showed resilience to COVID-19 with shorter hospital stays.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cluster Analysis; Cohort Studies; Coronavirus Infections; COVID-19; Disease Progression; Fatigue; Female; Humans; Length of Stay; Male; Middle Aged; Pandemics; Patient Discharge; Pleural Effusion; Pneumonia; Pneumonia, Viral; Prognosis; Resilience, Psychological

A Review of the Brain-Gut-Microbiome Axis and the Potential Role of Microbiota in Alzheimer's Disease. - Sun, Miao; Ma, Kai; Wen, Jie; Wang, Guangxian; Zhang, Changliang; Li, Qi; Bao, Xiaofeng; Wang, Hui (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is a neurodegenerative process characterized by loss of neurons in the hippocampus and cerebral cortex, leading to progressive cognitive decline. Pathologically, the hallmark of AD is accumulation of "senile" plaques composed of amyloid-β (Aβ) protein surrounding neurons in affected regions. Despite extensive research into AD pathogenesis and therapeutic targets, there remains no breakthroughs in its management. In recent years, there has been a spark of interest in the connection between the brain and gastrointestinal tract, referred to as the brain-gut axis, and its potential implications for both metabolic and neurologic disease. Moreover, the gastrointestinal flora, referred to as the microbiome, appears to exert significant influence over the brain-gut axis. With the need for expanded horizons in understanding and treating AD, many have turned to the brain-gut-microbiome axis for answers. Here we provide a review of the brain-gut-microbiome axis and discuss the evidence supporting alterations of the axis in the pathogenesis of AD. Specifically, we highlight the role for the microbiome in disruption of Aβ metabolism/clearance, increased permeability of the blood-brain barrier and modulation of the neuroinflammatory response, and inhibition of hippocampal neurogenesis. The majority of the above described findings are the result of excellent, albeit basic and pre-clinical studies. Therefore, we conclude with a brief description of documented clinical support for brain-gut-microbiome axis alteration in AD, including potential microbiome-based therapeutics for AD. Collectively, these findings suggest that the brain-gut-microbiome axis may be a "lost link" in understanding and treating AD and call for future work.

Serum Hepcidin Levels in Cognitively Normal Older Adults with High Neocortical Amyloid-β Load. - Chatterjee, Pratishtha; Mohammadi, Maryam; Goozee, Kathryn; Shah, Tejal M; Sohrabi, Hamid R; Dias, Cintia B; Shen, Kaikai; Asih, Prita R; Dave, Preeti; Pedrini, Steve; Ashton, Nicholas J; Hye, Abdul; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Hepcidin, an iron-regulating hormone, suppresses the release of iron by binding to the iron exporter protein, ferroportin, resulting in intracellular iron accumulation. Given that iron dyshomeostasis has been observed in Alzheimer's disease (AD) together with elevated serum hepcidin levels, the current study examined whether elevated serum hepcidin levels are an early event in AD pathogenesis by measuring the hormone in cognitively normal older adults at risk of AD, based on high neocortical amyloid-β load (NAL). METHODS: Serum hepcidin levels in cognitively normal participants (n = 100) aged between 65-90 years were measured using ELISA. To evaluate NAL, all participants underwent 18F-florbetaben positron emission tomography. A standard uptake value ratio (SUVR) RESULTS: Serum hepcidin was significantly higher in participants with high NAL compared to those with low NAL before and after adjusting for covariates: age, gender, and APOEɛ4 carriage (p < 0.05). A receiver operating characteristic curve based on a logistic regression of the same covariates, the base model, distinguished high from low NAL (area under the curve, AUC = 0.766), but was outperformed when serum hepcidin was added to the base model (AUC = 0.794) and further improved with plasma Aβ42/40 ratio (AUC = 0.829). CONCLUSION: The present findings indicate that serum hepcidin is increased in individuals at risk for AD and contribute to the body of evidence supporting iron dyshomeostasis as an early event of AD. Further, hepcidin may add value to a panel of markers that contribute toward identifying individuals at risk of AD; however, further validation studies are required.

Tau Acetylation in Entorhinal Cortex Induces its Chronic Hippocampal Propagation and Cognitive Deficits in Mice. - Wang, Xin; Liu, En-Jie; Liu, Qian; Li, Shi-Hong; Li, Ting; Zhou, Qiu-Zhi; Liu, Yan-Chao; Zhang, Huaqiu; Wang, Jian-Zhi (J Alzheimers Dis, 2020)
BACKGROUND: Increased tau acetylation at K174, K274, K280, and K281 has been observed in the brains of Alzheimer's disease (AD) patients or in transgenic mice, but the role of acetylation in tau propagation is elusive. OBJECTIVE: To study the effect of tau acetylation in entorhinal cortex on tau transmission and learning and memory. METHODS: Stereotactic brain injection, behavioral test, electrophysiological recording, immunohistochemistry, and immunofluorescence were used. RESULTS: We constructed the hyperacetylation mimics of tau (AAV-Tau-4Q), the non-acetylation tau mutant (AAV-Tau-4R), and the wild-type tau (AAV-Tau-WT). By overexpressing these different tau proteins in the entorhinal cortex (EC) of 2-month-old mice, we found that overexpressing Tau-4Q in EC for 3 or 6 months (to 5 or 8 months of age) neither induces tau propagation to dentate gyrus (DG) nor glial activation in DG, nor spatial memory deficit. However, overexpressing Tau-WT and Tau-4Q in EC for 13.5 months (15.5 months of age) at 2 months promoted tau propagation respectively to granulosa and hilus of DG with glial activation, synaptic dysfunction, and memory deficit, while overexpressing Tau-4R abolished tau propagation with improved cellular pathologies and cognitive functions. Furthermore, overexpressing Tau-4Q in unilateral DG of 2-month-old mice for 8 weeks also promoted its contralateral transmission with glial activation, and mice with tau (Tau-WT, Tau-4Q, and Tau-4R) overexpression in DG showed cognitive deficits compared with the empty vector controls. CONCLUSION: Tau acetylation induces a time-dependent propagation from EC to DG, and only hippocampus but not EC tau accumulation induces cognitive deficits.

Telemedicine for Delivery of Care in Frontotemporal Lobar Degeneration During COVID-19 Pandemic: Results from Southern Italy. - Capozzo, Rosa; Zoccolella, Stefano; Frisullo, Maria Elisa; Barone, Roberta; Dell'Abate, Maria Teresa; Barulli, Maria Rosaria; Musio, Marco; Accogli, Miriam; Logroscino, Giancarlo (J Alzheimers Dis, 2020)
BACKGROUND: The COVID-19 pandemic is changing clinical practice in neurology, after the governments decided the introduction of social distancing and interruption of medical non-emergency services in many countries. Teleneurology is an effective tool for the remote evaluation of patients but its adoption for frontotemporal lobar dementia (FTD) is in a preliminary stage. OBJECTIVE: We evaluated multidisciplinary assessment of patients with FTD using telehealth during the COVID-19 pandemic. METHODS: All patients received a diagnosis of FTD during 2018-2019 according to international criteria. A structured questionnaire and Clinical Dementia Rating Scale (CDR)-FTD were used by the neurologist with patients and/or caregivers. Index symptoms of COVID-19 infection were searched. RESULTS: Twenty-eight clinical interviews were completed with caregivers and four with both patients/caregivers. Most patients and caregivers were satisfied with the neurological interview and expressed their willingness to continue to be included in remote evaluation programs (90%). Fifty percent of patients experienced significant worsening of clinical picture and quality of life since the start of social distancing. The CDR-FTD scale revealed a significant worsening of behavior (p = 0.01) and language functions (p = 0.009), compared to the last in-person evaluation at the center. One patient presented index symptoms of COVID-19 infection and was confirmed to be positive for COVID-19 with pharyngeal swab. CONCLUSION: The study was conducted in Italy, one of the countries hit particularly hard by the COVID-19 pandemic, with interruption of all non-emergency medical services. Our study indicates that telemedicine is a valid tool to triage patients with FTD to increase practice outreach and efficiency.
Keywords: Aged; Aged, 80 and over; Behavior; Coronavirus Infections; COVID-19; Delivery of Health Care; Disease Progression; Female; Frontotemporal Lobar Degeneration; Humans; Italy; Language; Male; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quality of Life; Quarantine; Surveys and Questionnaires; Telemedicine; Triage

Utility of MemTrax and Machine Learning Modeling in Classification of Mild Cognitive Impairment. - Bergeron, Michael F; Landset, Sara; Zhou, Xianbo; Ding, Tao; Khoshgoftaar, Taghi M; Zhao, Feng; Du, Bo; Chen, Xinjie; Wang, Xuan; Zhong, Lianmei; Liu, Xiaolei; Ashford, J Wesson (J Alzheimers Dis, 2020)
BACKGROUND: The widespread incidence and prevalence of Alzheimer's disease and mild cognitive impairment (MCI) has prompted an urgent call for research to validate early detection cognitive screening and assessment. OBJECTIVE: Our primary research aim was to determine if selected MemTrax performance metrics and relevant demographics and health profile characteristics can be effectively utilized in predictive models developed with machine learning to classify cognitive health (normal versus MCI), as would be indicated by the Montreal Cognitive Assessment (MoCA). METHODS: We conducted a cross-sectional study on 259 neurology, memory clinic, and internal medicine adult patients recruited from two hospitals in China. Each patient was given the Chinese-language MoCA and self-administered the continuous recognition MemTrax online episodic memory test on the same day. Predictive classification models were built using machine learning with 10-fold cross validation, and model performance was measured using Area Under the Receiver Operating Characteristic Curve (AUC). Models were built using two MemTrax performance metrics (percent correct, response time), along with the eight common demographic and personal history features. RESULTS: Comparing the learners across selected combinations of MoCA scores and thresholds, Naïve Bayes was generally the top-performing learner with an overall classification performance of 0.9093. Further, among the top three learners, MemTrax-based classification performance overall was superior using just the top-ranked four features (0.9119) compared to using all 10 common features (0.8999). CONCLUSION: MemTrax performance can be effectively utilized in a machine learning classification predictive model screening application for detecting early stage cognitive impairment.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

Vascular Risk Factors and Alzheimer's Disease: Blood-Brain Barrier Disruption, Metabolic Syndromes, and Molecular Links. - He, Jin-Ting; Zhao, Xin; Xu, Lei; Mao, Cui-Ying (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is a neurodegenerative disorder, marked by cortical and hippocampal deposition of amyloid-β (Aβ) plaques and neurofibrillary tangles and cognitive impairment. Studies indicate a prominent link between cerebrovascular abnormalities and the onset and progression of AD, where blood-brain barrier (BBB) dysfunction and metabolic disorders play key risk factors. Pericyte degeneration, endothelial cell damage, astrocyte depolarization, diminished tight junction integrity, and basement membrane disarray trigger BBB damage. Subsequently, the altered expression of low-density lipoprotein receptor-related protein 1 and receptor for advanced glycation end products at the microvascular endothelial cells dysregulate Aβ transport across the BBB. White matter lesions and microhemorrhages, dyslipidemia, altered brain insulin signaling, and insulin resistance contribute to tau and Aβ pathogenesis, and oxidative stress, mitochondrial damage, inflammation, and hypoperfusion serve as mechanistic links between pathophysiological features of AD and ischemia. Deregulated calcium homeostasis, voltage gated calcium channel functioning, and protein kinase C signaling are also common mechanisms for both AD pathogenesis and cerebrovascular abnormalities. Additionally, APOE polymorphic alleles that characterize impaired cerebrovascular integrity function as primary genetic determinants of AD. Overall, the current review enlightens key vascular risk factors for AD and underscores pathophysiologic relationship between AD and vascular dysfunction.

Adverse Vascular Risk Relates to Cerebrospinal Fluid Biomarker Evidence of Axonal Injury in the Presence of Alzheimer's Disease Pathology. - Osborn, Katie E; Alverio, Jonathan M; Dumitrescu, Logan; Pechman, Kimberly R; Gifford, Katherine A; Hohman, Timothy J; Blennow, Kaj; Zetterberg, Henrik; Jefferson, Angela L (J Alzheimers Dis, 2019)
BACKGROUND: Vascular risk factors promote cerebral small vessel disease and neuropathological changes, particularly in white matter where large-caliber axons are located. How Alzheimer's disease pathology influences the brain's vulnerability in this regard is not well understood. OBJECTIVE: Systemic vascular risk was assessed in relation to cerebrospinal fluid concentrations of neurofilament light, a biomarker of large-caliber axonal injury, evaluating for interactions by clinical and protein markers of Alzheimer's disease. METHODS: Among Alzheimer's Disease Neuroimaging Initiative participants with normal cognition (n = 117), mild cognitive impairment (n = 190), and Alzheimer's disease (n = 95), linear regression related vascular risk (as measured by the modified Framingham Stroke Risk Profile) to neurofilament light, adjusting for age, sex, education, and cognitive diagnosis. Interactions were assessed by cognitive diagnosis, and by cerebrospinal fluid markers of Aβ42, hyperphosphorylated tau, and total tau. RESULTS: Vascular risk and neurofilament light were not related in the main effect model (p = 0.08). However, interactions emerged for total tau (p = 0.01) and hyperphosphorylated tau (p = 0.002) reflecting vascular risk becoming more associated with cerebrospinal fluid neurofilament light in the context of greater concentrations of tau biomarkers. An interaction also emerged for the Alzheimer's disease biomarker profiles (p = 0.046) where in comparison to the referent 'normal' biomarker group, individuals with abnormal levels of both Aβ42 and total tau showed stronger associations between vascular risk and neurofilament light. CONCLUSION: Older adults may be more vulnerable to axonal injury in response to higher vascular risk burdens in the context of concomitant Alzheimer's disease pathology.

Choroid Plexus Acts as Gatekeeper for TREM2, Abnormal Accumulation of ApoE, and Fibrillary Tau in Alzheimer's Disease and in Down Syndrome Dementia. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Vuono, Romina; Bickerton, Anastasia; Jones, Elizabeth; Fincham, Robert; Allinson, Kieren; Holland, Anthony; Zaman, Shahid H (J Alzheimers Dis, 2019)
BACKGROUND: Genetic factors that influence Alzheimer's disease (AD) risk include mutations in TREM2 and allelic variants of Apolipoprotein E, influencing AD pathology in the general population and in Down syndrome (DS). Evidence shows that dysfunction of the choroid plexus may compromise the blood-cerebrospinal fluid (CSF) barrier, altering secretary, transport and immune function that can affect AD pathology. OBJECTIVE: To investigate the genotype and phenotype of DS individuals in relation to choroid plexus damage and blood-CSF barrier leakage to identify markers that could facilitate early diagnosis of AD in DS. METHODS: To assess allele frequency and haplotype associations ApoE, Tau, TREM2, and HLA-DR were analyzed by SNP analysis in DS participants (n = 47) and controls (n = 50). The corresponding plasma protein levels were measured by ELISA. Postmortem brains from DS, AD, and age-matched controls were analyzed by immunohistochemistry. RESULTS: Haplotype analysis showed that individuals with Tau H1/H1 and ApoEɛ4 genotypes were more prevalent among DS participants with an earlier diagnosis of dementia (17%) compared to H1/H2 haplotypes (6%). Plasma TREM2 levels decreased whereas phospho-tau levels increased with age in DS. In AD and DS brain, insoluble tau and ApoE were found to accumulate in the choroid plexus. CONCLUSION: Accumulation of tau and ApoE in the choroid plexus may increase the oligomerization rate of Aβ42 and impair tau trafficking, leading to AD pathology. We have identified a high-risk haplotype: ApoEɛ4, Tau/H1, and TREM2/T, that manifests age-related changes potentially opening a window for treatment many years prior to the manifestation of the AD dementia.

A Clinical Trial of Transcranial Electromagnetic Treatment in Alzheimer's Disease: Cognitive Enhancement and Associated Changes in Cerebrospinal Fluid, Blood, and Brain Imaging. - Arendash, Gary; Cao, Chuanhai; Abulaban, Haitham; Baranowski, Rob; Wisniewski, Gary; Becerra, Lino; Andel, Ross; Lin, Xiaoyang; Zhang, Xiaolin; Wittwer, David; Moulton, Jay; Arrington, John; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Small aggregates (oligomers) of the toxic proteins amyloid-β (Aβ) and phospho-tau (p-tau) are essential contributors to Alzheimer's disease (AD). In mouse models for AD or human AD brain extracts, Transcranial Electromagnetic Treatment (TEMT) disaggregates both Aβ and p-tau oligomers, and induces brain mitochondrial enhancement. These apparent "disease-modifying" actions of TEMT both prevent and reverse memory impairment in AD transgenic mice. OBJECTIVE: To evaluate the safety and initial clinical efficacy of TEMT against AD, a comprehensive open-label clinical trial was performed. METHODS: Eight mild/moderate AD patients were treated with TEMT in-home by their caregivers for 2 months utilizing a unique head device. TEMT was given for two 1-hour periods each day, with subjects primarily evaluated at baseline, end-of-treatment, and 2 weeks following treatment completion. RESULTS: No deleterious behavioral effects, discomfort, or physiologic changes resulted from 2 months of TEMT, as well as no evidence of tumor or microhemorrhage induction. TEMT induced clinically important and statistically significant improvements in ADAS-cog, as well as in the Rey AVLT. TEMT also produced increases in cerebrospinal fluid (CSF) levels of soluble Aβ1-40 and Aβ1-42, cognition-related changes in CSF oligomeric Aβ, a decreased CSF p-tau/Aβ1-42 ratio, and reduced levels of oligomeric Aβ in plasma. Pre- versus post-treatment FDG-PET brain scans revealed stable cerebral glucose utilization, with several subjects exhibiting enhanced glucose utilization. Evaluation of diffusion tensor imaging (fractional anisotropy) scans in individual subjects provided support for TEMT-induced increases in functional connectivity within the cognitively-important cingulate cortex/cingulum. CONCLUSION: TEMT administration to AD subjects appears to be safe, while providing cognitive enhancement, changes to CSF/blood AD markers, and evidence of stable/enhanced brain connectivity.

Exercise Training in Amnestic Mild Cognitive Impairment: A One-Year Randomized Controlled Trial. - Tarumi, Takashi; Rossetti, Heidi; Thomas, Binu P; Harris, Thomas; Tseng, Benjamin Y; Turner, Marcel; Wang, Ciwen; German, Zohre; Martin-Cook, Kristin; Stowe, Ann M; Womack, Kyle B; Mathews, Dana; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The current evidence is inconclusive to support the benefits of aerobic exercise training (AET) for preventing neurocognitive decline in patients with amnestic mild cognitive impairment (aMCI). OBJECTIVE: To examine the effect of a progressive, moderate-to-high intensity AET program on memory and executive function, brain volume, and cortical amyloid-β (Aβ) plaque deposition in aMCI patients. METHODS: This is a proof-of-concept trial that randomized 70 aMCI patients to 12 months of AET or stretching and toning (SAT, active control) interventions. Primary neuropsychological outcomes were assessed by using the California Verbal Learning Test-second edition (CVLT-II) and the Delis-Kaplan Executive Function System (D-KEFS). Secondary outcomes were the global and hippocampal brain volumes and the mean cortical and precuneus Aβ deposition. RESULTS: Baseline cognitive scores were similar between the groups. Memory and executive function performance improved over time but did not differ between the AET and SAT groups. Brain volume decreased and precuneus Aβ plaque deposition increased over time but did not differ between the groups. Cardiorespiratory fitness was significantly improved in the AET compared with SAT group. In amyloid positive patients, AET was associated with reduced hippocampal atrophy when compared with the SAT group. CONCLUSION: The AET and SAT groups both showed evidence of slightly improved neuropsychological scores in previously sedentary aMCI patients. However, these interventions did not prevent brain atrophy or increases in cortical Aβ deposition over 12 months. In amyloid positive patients, AET reduced hippocampal atrophy when compared with the SAT group.

Genome-Wide Methylation of Mild Cognitive Impairment in Mexican Americans Highlights Genes Involved in Synaptic Transport, Alzheimer's Disease-Precursor Phenotypes, and Metabolic Morbidities. - Pathak, Gita A; Silzer, Talisa K; Sun, Jie; Zhou, Zhengyang; Daniel, Ann A; Johnson, Leigh; O'Bryant, Sid; Phillips, Nicole R; Barber, Robert C (J Alzheimers Dis, 2019)
The Mexican American population is among the fastest growing aging population and has a younger onset of cognitive decline. This group is also heavily burdened with metabolic conditions such as hypertension, diabetes, and obesity. Unfortunately, limited research has been conducted in this group. Understanding methylation alterations, which are influenced by both genetic and lifestyle factors, is key to identifying and addressing the root cause for mild cognitive impairment, a clinical precursor for dementia. We conducted an epigenome-wide association study on a community-based Mexican American population using the Illumina EPIC array. Following rigorous quality control measures, we identified 10 CpG sites to be differentially methylated between normal controls and individuals with mild cognitive impairment annotated to PKIB, KLHL29, SEPT9, OR2C3, CPLX3, BCL2L2-PABPN1, and CCNY. We found four regions to be differentially methylated in TMEM232, SLC17A8, ALOX12, and SEPT8. Functional gene-set analysis identified four gene-sets, RIN3, SPEG, CTSG, and UBE2L3, as significant. The gene ontology and pathway analyses point to neuronal cell death, metabolic dysfunction, and inflammatory processes. We found 1,450 processes to be enriched using empirical Bayes gene-set enrichment. In conclusion, the functional overlap of differentially methylated genes associated with cognitive impairment in Mexican Americans implies cross-talk between metabolically-instigated systemic inflammation and disruption of synaptic vesicular transport.

Geographical Variation in the Diagnostic Rate and Quality of Dementia Diagnoses. - Zakarias, Johanne Købstrup; Jensen-Dahm, Christina; Nørgaard, Ane; Roos, Peter; Gasse, Christiane; Phung, Thien Kieu Thi; Waldemar, Gunhild (J Alzheimers Dis, 2019)
BACKGROUND: Early and accurate diagnosis of dementia opens the door to appropriate treatment, support, and counseling. Despite availability of evidence-based guidelines for diagnostic evaluation of dementia, the diagnostic rate in people with dementia is low and the quality of dementia diagnoses is unknown. OBJECTIVE: The overall aim of this register-based study was to analyze the quality of diagnostic evaluation of dementia by assessing nationwide geographical variations in a range of indicators. METHODS: A register-based cross-sectional study of the entire Danish population aged 65 years or older in 2015 was conducted. The surrogate indicators for diagnostic quality included 1) prevalence rates of dementia diagnoses, 2) incidence rates of dementia diagnoses, 3) age at first diagnosis of dementia, 4) medical specialty responsible for diagnosis, 5) diagnostic rate of dementia subtypes, and 6) use of anti-dementia medication. The indicators were compared across the five Danish regions. RESULTS: The national prevalence and incidence of registered dementia diagnoses was 3.0% and 0.5%, respectively. The proportion of patients diagnosed at a dementia specialist department ranged from 60.9% to 90.5% across the five regions, subtype specific diagnosis ranged from 45.3% to 75.5%, and use of anti-dementia medication ranged from 29.2% to 58.3%. CONCLUSION: The observed geographical variations in dementia diagnoses and treatment indicate inequality in the access to appropriate diagnostic evaluation and care for patients with dementia. Our findings call for more awareness of the benefits of timely diagnosis and for improvement in the quality of diagnostic evaluation of dementia.

Identifying Unmet Needs of Family Dementia Caregivers: Results of the Baseline Assessment of a Cluster-Randomized Controlled Intervention Trial. - Zwingmann, Ina; Michalowsky, Bernhard; Esser, Alexander; Kaczynski, Anika; Monsees, Jessica; Keller, Armin; Hertel, Johannes; Wucherer, Diana; Thyrian, Jochen René; Eichler, Tilly; Kilimann, Ingo; Teipel, Stefan; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Caregivers providing informal care for people with dementia (PwD) often report unmet needs, burden, and health impairments. Optimal support for family dementia caregivers will likely benefit from better understanding and assessment of the prevalence and types of caregivers' unmet needs and associated socio-demographic and clinical characteristics. OBJECTIVE: The present study investigates 1) the number and types of caregivers' unmet needs, 2) socio-demographic and clinical characteristics of both PwD and caregivers, and 3) caregivers' burden and health-related outcomes that are related to caregivers' unmet needs. METHODS: The present analyses are based on cross-sectional data of n = 226 dyads of caregivers and their community-dwelling PwD participating in a comprehensive standardized, computer-based caregivers' needs assessment within a general practitioner (GP)-based, cluster-randomized intervention trial. RESULTS: A total of n = 505 unmet needs were identified for n = 171 caregivers from the intervention group at baseline. Only 24.3% caregivers reported no unmet need (n = 55), whereas 75.7% caregivers had at least one unmet need (n = 171). Caregivers had on average 2.19 unmet needs (mean = 2.19, SD = 2.15). Specifically, 53.1% of caregivers had one up to three unmet needs (n = 120), 18.6% (n = 42) had three up to six unmet needs, and 4.0% (n = 9) had more than six unmet needs. DISCUSSION: Our results underline the importance of a comprehensive needs assessment for family dementia caregivers to develop and implement concepts that can provide family dementia caregivers with optimal support.

Impacts of Overweight and Obesity in Older Age on the Risk of Dementia: A Systematic Literature Review and a Meta-Analysis. - Danat, Isaac M; Clifford, Angela; Partridge, Martin; Zhou, Weiju; Bakre, Aishat T; Chen, Anthony; McFeeters, Danielle; Smith, Tina; Wan, Yuhui; Copeland, John; Anstey, Kaarin J; Chen, Ruoling (J Alzheimers Dis, 2019)
BACKGROUND: It is unclear whether overweight and obesity in older age reduces or increases the risk of incident dementia. OBJECTIVE: To assess the impacts of overweight and obesity in older age on incident dementia. METHODS: We searched cohort studies reporting body weight measured in older age and dementia through PubMed, Embase, Medline, PyschInfo, and Cochrane library until July 2016. Sixteen articles were identified for the review. We pooled data from them and a new unpublished study from China, to calculate relative risk (RR) of incident dementia in relation to body mass index (BMI) and waist circumference (WC). RESULTS: All 16 cohort studies were undertaken in high income countries, with follow-up periods ranging between 3 to 18 years. Thirteen studies showed an inverse association between BMI and dementia, and three studies demonstrated a positive association. Pooled RR of dementia in relation to continuous BMI from 14 studied populations, including the new Chinese data, was 0.97 (95% CI 0.95-1.00); in those followed up CONCLUSION: The current evidence did not support a paradox on beneficial impacts of overweight and obesity in older age on incident dementia. More studies with long term follow up are needed to clarify the association of body weight in older age with dementia risk.

Improved Differential Diagnosis of Alzheimer's Disease by Integrating ELISA and Mass Spectrometry-Based Cerebrospinal Fluid Biomarkers. - Khoonsari, Payam Emami; Shevchenko, Ganna; Herman, Stephanie; Remnestål, Julia; Giedraitis, Vilmantas; Brundin, RoseMarie; Degerman Gunnarsson, Malin; Kilander, Lena; Zetterberg, Henrik; Nilsson, Peter; Lannfelt, Lars; Ingelsson, Martin; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Alzheimer's disease (AD) is diagnosed based on a clinical evaluation as well as analyses of classical biomarkers: Aβ42, total tau (t-tau), and phosphorylated tau (p-tau) in cerebrospinal fluid (CSF). Although the sensitivities and specificities of the classical biomarkers are fairly good for detection of AD, there is still a need to develop novel biochemical markers for early detection of AD. OBJECTIVE: We explored if integration of novel proteins with classical biomarkers in CSF can better discriminate AD from non-AD subjects. METHODS: We applied ELISA, mass spectrometry, and multivariate modeling to investigate classical biomarkers and the CSF proteome in subjects (n = 206) with 76 AD patients, 74 mild cognitive impairment (MCI) patients, 11 frontotemporal dementia (FTD) patients, and 45 non-dementia controls. The MCI patients were followed for 4-9 years and 21 of these converted to AD, whereas 53 remained stable. RESULTS: By combining classical CSF biomarkers with twelve novel markers, the area of the ROC curves (AUROCS) of distinguishing AD and MCI/AD converters from non-AD were 93% and 96%, respectively. The FTDs and non-dementia controls were identified versus all other groups with AUROCS of 96% and 87%, respectively. CONCLUSIONS: Integration of new and classical CSF biomarkers in a model-based approach can improve the identification of AD, FTD, and non-dementia control subjects.

Inferring the Molecular Mechanisms of Noncoding Alzheimer's Disease-Associated Genetic Variants. - Amlie-Wolf, Alexandre; Tang, Mitchell; Way, Jessica; Dombroski, Beth; Jiang, Ming; Vrettos, Nicholas; Chou, Yi-Fan; Zhao, Yi; Kuzma, Amanda; Mlynarski, Elisabeth E; Leung, Yuk Yee; Brown, Christopher D; et al. (J Alzheimers Dis, 2019)
Most of the loci identified by genome-wide association studies (GWAS) for late-onset Alzheimer's disease (LOAD) are in strong linkage disequilibrium (LD) with nearby variants all of which could be the actual functional variants, often in non-protein-coding regions and implicating underlying gene regulatory mechanisms. We set out to characterize the causal variants, regulatory mechanisms, tissue contexts, and target genes underlying these associations. We applied our INFERNO algorithm to the top 19 non-APOE loci from the IGAP GWAS study. INFERNO annotated all LD-expanded variants at each locus with tissue-specific regulatory activity. Bayesian co-localization analysis of summary statistics and eQTL data was performed to identify tissue-specific target genes. INFERNO identified enhancer dysregulation in all 19 tag regions analyzed, significant enrichments of enhancer overlaps in the immune-related blood category, and co-localized eQTL signals overlapping enhancers from the matching tissue class in ten regions (ABCA7, BIN1, CASS4, CD2AP, CD33, CELF1, CLU, EPHA1, FERMT2, ZCWPW1). In several cases, we identified dysregulation of long noncoding RNA (lncRNA) transcripts and applied the lncRNA target identification algorithm from INFERNO to characterize their downstream biological effects. We also validated the allele-specific effects of several variants on enhancer function using luciferase expression assays. By integrating functional genomics with GWAS signals, our analysis yielded insights into the regulatory mechanisms, tissue contexts, genes, and biological processes affected by noncoding genetic variation associated with LOAD risk.

Neurodegenerative Disease-Related Proteins within the Epidermal Layer of the Human Skin. - Akerman, S Can; Hossain, Shireen; Shobo, Adeola; Zhong, Yifei; Jourdain, Roland; Hancock, Mark A; George, Kelly; Breton, Lionel; Multhaup, Gerhard (J Alzheimers Dis, 2019)
There is increasing evidence suggesting that amyloidogenic proteins might form deposits in non-neuronal tissues in neurodegenerative disorders such as Alzheimer's or Parkinson's diseases. However, the detection of these aggregation-prone proteins within the human skin has been controversial. Using immunohistochemistry (IHC) and mass spectrometry tissue imaging (MALDI-MSI), fresh frozen human skin samples were analyzed for the expression and localization of neurodegenerative disease-related proteins. While α-synuclein was detected throughout the epidermal layer of the auricular samples (IHC and MALDI-MSI), tau and Aβ34 were also localized to the epidermal layer (IHC). In addition to Aβ peptides of varying length (e.g., Aβ40, Aβ42, Aβ34), we also were able to detect inflammatory markers within the same sample sets (e.g., thymosin β-4, psoriasin). While previous literature has described α-synuclein in the nucleus of neurons (e.g., Parkinson's disease), our current detection of α-synuclein in the nucleus of skin cells is novel. Imaging of α-synuclein or tau revealed that their presence was similar between the young and old samples in our present study. Future work may reveal differences relevant for diagnosis between these proteins at the molecular level (e.g., age-dependent post-translational modifications). Our novel detection of Aβ34 in human skin suggests that, just like in the brain, it may represent a stable intermediate of the Aβ40 and Aβ42 degradation pathway.

Neuron-Specific Apolipoprotein E4 (1-272) Fragment Induces Tau Hyperphosphorylation and Axonopathy via Triggering Endoplasmic Reticulum Stress. - Liang, Tao; Xue, Feixiao; Hang, Weijian; Wen, Bin; Zhang, Qianying; Chen, Jiehui; Liu, Xiaofeng; Chen, Juan (J Alzheimers Dis, 2019)
Apolipoprotein (apo) E4 is the major genetic risk factor for Alzheimer's disease (AD). It is shown that apoE4 preferentially undergoes aberrant cleavage in neurons, yielding neurotoxic C-terminal-truncated apoE4 fragment. Endoplasmic reticulum (ER) stress has also been known to be involved in the pathogenesis of AD. However, little is known about the contribution of ER stress to the neurotoxicity of apoE4 fragment. In the present study, we established the neuron-specific expression human C-terminal-truncated apoE4(1-272) fragment transgenic mice and also transfected apoE4(1-272) fragment in neuroblastoma N2a cells. We found that human apoE4(1-272) fragment could trigger ER stress as evidenced by increasing the expression of ER stress markers both in vivo and in vitro. Meanwhile, the apoE4(1-272) transgenic mice presented obviously AD-like neuropathological changes, including the impairment of spatial learning and memory, prominent axonal morphological changes, and hyperphosphorylation of tau. At the same time, we also found that glycogen synthase kinase-3 activities were significantly increased. Furthermore, these neuropathological changes, especially tau hyperphosphorylation and axonal transport impairment, were significantly rescued by the ER stress protector 4-phenylbutyric acid (4-PBA) in apoE4(1-272)-transfected N2a cells. Pretreatment with 4-PBA not only decreased the protein expression of immunoglobulin binding protein (BiP) and C/EBP-homologous protein (CHOP), but also significantly reversed these defects in axonal transport. These results suggested that the neurotoxic effects of apoE4(1-272) fragment found in AD subjects, at least in part, through triggering ER stress and inducing tau hyperphosphorylation, led to the enduring impairment of axonal transport.

Porphyromonas gingivalis Infection Induces Amyloid-β Accumulation in Monocytes/Macrophages. - Nie, Ran; Wu, Zhou; Ni, Junjun; Zeng, Fan; Yu, Weixian; Zhang, Yufeng; Kadowaki, Tomoko; Kashiwazaki, Haruhiko; Teeling, Jessica L; Zhou, Yanmin (J Alzheimers Dis, 2019)
Abnormal accumulation of amyloid-β (Aβ) in the brain is the most significant pathological hallmark of Alzheimer's disease (AD). We have found that chronic systemic exposure to lipopolysaccharide of Porphyromonas gingivalis (P. gingivalis) induces the accumulation of Aβ in the brain of middle-aged mice. On the other hand, recent research has shown that circulating Aβ is transferred into the brain; however, the involvement of chronic systemic P. gingivalis infection in the peripheral Aβ metabolism is unknown. We hypothesized that chronic P. gingivalis infection expands Aβ pools in peripheral inflammatory tissues and thereby contributes to the accumulation of Aβ in the brain of patients with periodontitis. We showed that the increased expression of IL-1β, AβPP770, CatB, Aβ1-42, and Aβ3-42 was mainly co-localized with macrophages in the liver of P. gingivalis infected mice. Blocking CatB and NF-κB significantly inhibited the P. gingivalis-induced expression of IL-1β, AβPP770, Aβ1-42, and Aβ3-42 in RAW264.7 cells. Aβ3-42, but not Aβ1-42, induced the significant death of macrophages, and the reduction of phagocytic abilities induced by Aβ3-42 tended to be higher than that induced by Aβ1-42. Additionally, the expression of AβPP770, CatB, Aβ1-42, and Aβ3-42 was determined in the macrophages of gingival tissues from periodontitis patients. These findings indicate that chronic systemic P. gingivalis infection induces the Aβ accumulation in inflammatory monocytes/macrophages via the activation of CatB/NF-κB signaling, thus suggesting monocytes/macrophages serve as a circulating pool of Aβ in patients with periodontitis. Taken together, CatB may be a novel therapeutic target for preventing the periodontitis-related AD initiation and pathological progression.

Serum Insulin-Like Growth Factor I Deficiency Associates to Alzheimer's Disease Co-Morbidities. - Zegarra-Valdivia, Jonathan A; Santi, Andrea; Fernández de Sevilla, Maria Estrella; Nuñez, Angel; Torres Aleman, Ignacio (J Alzheimers Dis, 2019)
Increasing evidence supports the notion that Alzheimer's disease (AD), a condition that presents heterogeneous pathological disturbances, is also associated to perturbed metabolic function affecting insulin and insulin-like growth factor I (IGF-I). While impaired insulin activity leading to insulin resistance has been associated to AD, whether altered IGF-I function affects the disease is not entirely clear. Despite the limitations of mouse models to mimic AD pathology, we took advantage that serum IGF-I deficient mice (LID mice) present many functional perturbations present in AD, most prominently cognitive loss, which is reversed by treatment with systemic IGF-I. We analyzed whether these mice display other pathological traits that are usual co-morbidities of AD. We found that LID mice not only display cognitive disturbances, but also show altered mood and sociability, increased susceptibility to epileptiform activity, and a disturbed sleep/wake cycle. Collectively, these data suggest that reduced IGF-I activity contributes to heterogeneous deficits commonly associated to AD. We suggest that impaired IGF-I activity needs to be taken into consideration when modeling this condition.

Small Molecule Amyloid-β Protein Precursor Processing Modulators Lower Amyloid-β Peptide Levels via cKit Signaling. - Chen, Ci-Di; Zeldich, Ella; Khodr, Christina; Camara, Kaddy; Tung, Tze Yu; Lauder, Emma C; Mullen, Patrick; Polanco, Taryn J; Liu, Yen-Yu; Zeldich, Dean; Xia, Weiming; Van Nostrand, William E; et al. (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is characterized by the accumulation of neurotoxic amyloid-β (Aβ) peptides consisting of 39-43 amino acids, proteolytically derived fragments of the amyloid-β protein precursor (AβPP), and the accumulation of the hyperphosphorylated microtubule-associated protein tau. Inhibiting Aβ production may reduce neurodegeneration and cognitive dysfunction associated with AD. We have previously used an AβPP-firefly luciferase enzyme complementation assay to conduct a high throughput screen of a compound library for inhibitors of AβPP dimerization, and identified a compound that reduces Aβ levels. In the present study, we have identified an analog, compound Y10, which also reduced Aβ. Initial kinase profiling assays identified the receptor tyrosine kinase cKit as a putative Y10 target. To elucidate the precise mechanism involved, AβPP phosphorylation was examined by IP-western blotting. We found that Y10 inhibits cKit phosphorylation and increases AβPP phosphorylation mainly on tyrosine residue Y743, according to AβPP751 numbering. A known cKit inhibitor and siRNA specific to cKit were also found to increase AβPP phosphorylation and lower Aβ levels. We also investigated a cKit downstream signaling molecule, the Shp2 phosphatase, and found that known Shp2 inhibitors and siRNA specific to Shp2 also increase AβPP phosphorylation, suggesting that the cKit signaling pathway is also involved in AβPP phosphorylation and Aβ production. We further found that inhibitors of both cKit and Shp2 enhance AβPP surface localization. Thus, regulation of AβPP phosphorylation by small molecules should be considered as a novel therapeutic intervention for AD.

Spatially Distributed Amyloid-β Reduces Glucose Metabolism in Mild Cognitive Impairment. - Carbonell, Felix; Zijdenbos, Alex P; Bedell, Barry J (J Alzheimers Dis, 2019)
BACKGROUND: Several positron emission tomography (PET) studies have explored the relationship between amyloid-β (Aβ), glucose metabolism, and the APOEɛ4 genotype. It has been reported that APOEɛ4, and not aggregated Aβ, contributes to glucose hypometabolism in pre-clinical stages of Alzheimer's disease (AD) pathology. OBJECTIVE: We hypothesize that typical measurements of Aβ taken either from composite regions-of-interest with relatively high burden actually cover significant patterns of the relationship with glucose metabolism. In contrast, spatially weighted measures of Aβ are more related to glucose metabolism in cognitively normal (CN) aging and mild cognitive impairment (MCI). METHODS: We have generated a score of amyloid burden based on a joint singular value decomposition (SVD) of the cross-correlation structure between glucose metabolism, as measured by [18F]2-fluoro-2-deoxyglucose (FDG) PET, and Aβ, as measured by [18F]florbetapir PET, from the Alzheimer's Disease Neuroimaging Initiative study. This SVD-based score reveals cortical regions where a reduced glucose metabolism is maximally correlated with distributed patterns of Aβ. RESULTS: From an older population of CN and MCI subjects, we found that the SVD-based Aβ score was significantly correlated with glucose metabolism in several cortical regions. Additionally, the corresponding Aβ network has hubs that contribute to distributed glucose hypometabolism, which, in turn, are not necessarily foci of Aβ deposition. CONCLUSIONS: Our approach uncovered hidden patterns of the glucose metabolism-Aβ relationship. We showed that the SVD-based Aβ score produces a stronger relationship with decreasing glucose metabolism than either APOEɛ4 genotype or global measures of Aβ burden.

Two Year Outcomes, Cognitive and Behavioral Markers of Decline in Healthy, Cognitively Normal Older Persons with Global Deterioration Scale Stage 2 (Subjective Cognitive Decline with Impairment). - Reisberg, Barry; Torossian, Carol; Shulman, Melanie B; Monteiro, Isabel; Boksay, Istvan; Golomb, James; Guillo Benarous, Francoise; Ulysse, Anaztasia; Oo, Thet; Vedvyas, Alok; Rao, Julia A; Marsh, Karyn; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Little is known with respect to behavioral markers of subjective cognitive decline (SCD), a condition initially described in association with Global Deterioration Scale (GDS) stage 2. OBJECTIVE: Two-year interval behavioral markers were investigated herein. METHODS: Subjects from a published 7-year outcome study of GDS stage 2 subjects were selected. This study had demonstrated a hazard ratio of 4.5 for progression of GDS stage 2, in comparison with GDS stage 1 (no subjective or objective cognitive decline) subjects, after controlling for demographic and temporal variables. Because GDS 2 subjects have previously demonstrated impairment in comparison with healthy persons free of complaints, we herein suggest the terminology "SCD(I)" for these persons. 98 SCD(I) persons, 63 women and 35 men, mean baseline age, 67.12±8.75 years, with a mean educational background of 15.55±2.60 years, and mean baseline MMSE scores of 28.9±1.24 were followed for 2.13±0.30 years. RESULTS: Observed annual decline on the GDS was 6.701% per annum, very close to a 1986 published estimate. At follow up, the MMSE, and 7 of 8 psychometric tests did not decline significantly. Of 21 Hamilton Depression Scale items, 2 improved and the remainder were unchanged. Anxieties declined from multiple perspectives. The Brief Cognitive Rating Scale (BCRS) declined significantly (p < 0.001), with component declines in Remote memory (p < 0.01), and Functioning/self-care (p = 0.01). CONCLUSION: SCD(I) persons decline at an annual rate of approximately 6.7% /year from several recent studies. The BCRS assessments and the Digit Symbol Substitution Test can be sensitive measures for future studies of progression mitigation.

Ultrasensitive Detection of Plasma Amyloid-β as a Biomarker for Cognitively Normal Elderly Individuals at Risk of Alzheimer's Disease. - Chatterjee, Pratishtha; Elmi, Mitra; Goozee, Kathryn; Shah, Tejal; Sohrabi, Hamid R; Dias, Cintia B; Pedrini, Steve; Shen, Kaikai; Asih, Prita R; Dave, Preeti; Taddei, Kevin; Vanderstichele, Hugo; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Aberrant amyloid-β (Aβ) deposition in the brain occurs two decades prior to the manifestation of Alzheimer's disease (AD) clinical symptoms and therefore brain Aβ load measured using PET serves as a gold standard biomarker for the early diagnosis of AD. However, the uneconomical nature of PET makes blood markers, that reflect brain Aβ deposition, attractive candidates for investigation as surrogate markers. OBJECTIVE: Investigation of plasma Aβ as a surrogate marker for brain Aβ deposition in cognitively normal elderly individuals. METHODS: Plasma Aβ40 and Aβ42 concentrations were measured using the ultrasensitive Single Molecule Array (Simoa) assay in 95 cognitively normal elderly individuals, who have all undergone PET to assess brain Aβ deposition. Based on the standard uptake value ratios (SUVR) obtained from PET imaging, using the tracer 18F-Florbetaben, plasma Aβ was compared between 32 participants assessed to have low brain Aβ load (Aβ-, SUVR <1.35) and 63 assessed to have high brain Aβ load (Aβ+, SUVR ≥1.35). RESULTS: Plasma Aβ42/Aβ40 ratios were lower in the Aβ+ group compared to the Aβ-group. Plasma Aβ40 and Aβ42 levels were not significantly different between Aβ-and Aβ+ groups, although a trend of higher plasma Aβ40 was observed in the Aβ+ group. Additionally, plasma Aβ42/Aβ40 ratios along with the known AD risk factors, age and APOEɛ4 status, resulted in Aβ+ participants being distinguished from Aβ-participants based on an area under the receiver operating characteristic curve shown to be 78%. CONCLUSION: Plasma Aβ ratios in this study are a potential biomarker for brain Aβ deposition and therefore, for preclinical AD. However, this method to measure plasma Aβ needs further development to increase the accuracy of this promising AD blood biomarker.

Upregulation of Thioredoxin-Interacting Protein in Brain of Amyloid-β Protein Precursor/Presenilin 1 Transgenic Mice and Amyloid-β Treated Neuronal Cells. - Wang, Yiran; Wang, Ying; Bharti, Veni; Zhou, Hong; Hoi, Vanessa; Tan, Hua; Wu, Zijian; Nagakannan, Pandian; Eftekharpour, Eftekhar; Wang, Jun-Feng (J Alzheimers Dis, 2019)
Oxidative stress has been hypothesized to play a role in the pathophysiology of Alzheimer's disease (AD). Previously, we found that total nitrosylated protein levels were increased in the brain of amyloid-β protein precursor (AβPP) and presenilin 1 (PS1) double transgenic mice, an animal model for AD, suggesting that cysteine oxidative protein modification may contribute to this disease. Thioredoxin (Trx) is a major oxidoreductase that can reverse cysteine oxidative modifications such as sulfenylation and nitrosylation, and inhibit oxidative stress. Thioredoxin-interacting protein (Txnip) is an endogenous Trx inhibitor. To understand the involvement of Trx and Txnip in AD development, we investigated Trx and Txnip in the brain of AβPP/PS1 mice. Using immunoblotting analysis, we found that although Trx protein levels were not changed, Txnip protein levels were significantly increased in hippocampus and frontal cortex of 9- and 12-month-old AβPP/PS1 mice when compared to wild-type mice. Txnip protein levels were also increased by amyloid-β treatment in primary cultured mouse cerebral cortical neurons and HT22 mouse hippocampal cells. Using biotin switch and dimedone conjugation methods, we found that amyloid-β treatment increased protein nitrosylation and sulfenylation in HT22 cells. We also found that downregulation of Txnip, using CRISPR/Cas9 method in HT22 cells, attenuated amyloid-β-induced protein nitrosylation and sulfenylation. Our findings suggest that amyloid-β may increase Txnip levels, subsequently inhibiting Trx reducing capability and enhancing protein cysteine oxidative modification. Our findings also indicate that Txnip may be a potential target for the treatment of AD.

A 10-Year Follow-Up of Adiposity and Dementia in Swedish Adults Aged 70 Years and Older. - Arnoldussen, Ilse A C; Sundh, Valter; Bäckman, Kristoffer; Kern, Silke; Östling, Svante; Blennow, Kaj; Zetterberg, Henrik; Skoog, Ingmar; Kiliaan, Amanda J; Gustafson, Deborah R (J Alzheimers Dis, 2018)
BACKGROUND: Adiposity measured in mid- or late-life and estimated using anthropometric measures such as body mass index (BMI) and waist-to-hip ratio (WHR), or metabolic markers such as blood leptin and adiponectin levels, is associated with late-onset dementia risk. However, during later life, this association may reverse and aging- and dementia-related processes may differentially affect adiposity measures. OBJECTIVE: We explored associations of concurrent BMI, WHR, and blood leptin and high molecular weight adiponectin levels with dementia occurrence. METHODS: 924 Swedish community-dwelling elderly without dementia, aged 70 years and older, systematically-sampled by birth day and birth year population-based in the Gothenburg city region of Sweden. The Gothenburg Birth Cohort Studies are designed for evaluating risk and protective factors for dementia. All dementias diagnosed after age 70 for 10 years were identified. Multivariable logistic regression models were used to predict dementia occurrence between 2000-2005, 2005-2010, and 2000-2010 after excluding prevalent baseline (year 2000) dementias. Baseline levels of BMI, WHR, leptin, and adiponectin were used. RESULTS: Within 5 years of baseline, low BMI (<20 kg/m2) was associated with higher odds of dementia compared to those in the healthy BMI category (≥ 20-24.9 kg/m2). Compared to the lowest quartile, leptin levels in the second quartile were associated with lower odds of dementia in women (p < 0.05). CONCLUSION: In late-life, anthropometric and metabolic adiposity measures appear to be differentially associated with dementia risk. While BMI and leptin levels are highly positively correlated, our results show that their association with dementia at age ≥70 years, is asynchronous. These data suggest that with aging, the complexity of the adiposity exposure may increase and suggests metabolic dysregulation. Additional studies are needed to better understand this complexity.

Acute Stroke Care in Dementia: A Cohort Study from the Swedish Dementia and Stroke Registries. - Zupanic, Eva; Kåreholt, Ingemar; Norrving, Bo; Secnik, Juraj; von Euler, Mia; Winblad, Bengt; Religa, Dorota; Kramberger, Milica Gregoric; Johnell, Kristina; Eriksdotter, Maria; Garcia-Ptacek, Sara (J Alzheimers Dis, 2018)
BACKGROUND: Previous studies have shown that patients with dementia receive less testing and treatment for stroke. OBJECTIVES: Our aim was to investigate hospital management of acute ischemic stroke in patients with and without dementia. METHODS: Retrospective analysis of prospectively collected data 2010-2014 from the Swedish national dementia registry (SveDem) and the Swedish national stroke registry (Riksstroke). Patients with dementia who suffered an acute ischemic stroke (AIS) (n = 1,356) were compared with matched non-dementia AIS patients (n = 6,755). Outcomes included length of stay in a stroke unit, total length of hospitalization, and utilization of diagnostic tests and assessments. RESULTS: The median age at stroke onset was 83 years. While patients with dementia were equally likely to be directly admitted to a stroke unit as their non-dementia counterparts, their stroke unit and total hospitalization length were shorter (10.5 versus 11.2 days and 11.6 versus 13.5, respectively, p < 0.001). Dementia patients were less likely to receive carotid ultrasound (OR 0.36, 95% CI [0.30-0.42]) or undergo assessments by the interdisciplinary team members (physiotherapists, speech therapists, occupational therapists; p < 0.05 for all adjusted models). However, a similar proportion of patients received CT imaging (97.4% versus 98.6%, p = 0.001) and a swallowing assessment (90.7% versus 91.8%, p = 0.218). CONCLUSIONS: Patients with dementia who suffer an ischemic stroke have equal access to direct stroke unit care compared to non-dementia patients; however, on average, their stay in a stroke unit and total hospitalization are shorter. Dementia patients are also less likely to receive specific diagnostic tests and assessments by the interdisciplinary stroke team.

The Added Value of Diffusion-Weighted MRI-Derived Structural Connectome in Evaluating Mild Cognitive Impairment: A Multi-Cohort Validation1. - Wang, Qi; Guo, Lei; Thompson, Paul M; Jack, Clifford R; Dodge, Hiroko; Zhan, Liang; Zhou, Jiayu (J Alzheimers Dis, 2018)
T1-weighted MRI has been extensively used to extract imaging biomarkers and build classification models for differentiating Alzheimer's disease (AD) patients from healthy controls, but only recently have brain connectome networks derived from diffusion-weighted MRI been used to model AD progression and various stages of disease such as mild cognitive impairment (MCI). MCI, as a possible prodromal stage of AD, has gained intense interest recently, since it may be used to assess risk factors for AD. Little work has been done to combine information from both white matter and gray matter, and it is unknown how much classification power the diffusion-weighted MRI-derived structural connectome could provide beyond information available from T1-weighted MRI. In this paper, we focused on investigating whether diffusion-weighted MRI-derived structural connectome can improve differentiating healthy controls subjects from those with MCI. Specifically, we proposed a novel feature-ranking method to build classification models using the most highly ranked feature variables to classify MCI with healthy controls. We verified our method on two independent cohorts including the second stage of Alzheimer's Disease Neuroimaging Initiative (ADNI2) database and the National Alzheimer's Coordinating Center (NACC) database. Our results indicated that 1) diffusion-weighted MRI-derived structural connectome can complement T1-weighted MRI in the classification task; 2) the feature-rank method is effective because of the identified consistent T1-weighted MRI and network feature variables on ADNI2 and NACC. Furthermore, by comparing the top-ranked feature variables from ADNI2, NACC, and combined dataset, we concluded that cross-validation using independent cohorts is necessary and highly recommended.

Altered Expression of Circulating Cdc42 in Frontotemporal Lobar Degeneration. - Saraceno, Claudia; Catania, Marcella; Paterlini, Anna; Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Binetti, Giuliano; Di Fede, Giuseppe; Caroppo, Paola; Benussi, Luisa; Ghidoni, Roberta; Bolognin, Silvia (J Alzheimers Dis, 2018)
The term frontotemporal lobar degeneration (FTLD) defines a group of heterogeneous conditions histologically characterized by neuronal degeneration, inclusions of various proteins, and synaptic loss. However, the molecular mechanisms contributing to these alterations are still unknown. As the Rho-GTPase family member Cell division cycle 42 (Cdc42) plays a key role in the regulation of actin cytoskeleton dynamics and spine formation, we investigated whether Cdc42 protein levels were altered in the disease. Cdc42 was increased in the frontal cortex of FTLD patients compared to age-matched controls, but also in Alzheimer's disease (AD) patients included in the data-set. On the other hand, the pool of circulating Cdc42 in the plasma was altered in FTLD but not in AD patients. Interestingly, the stratification of the FTLD patients according to the different clinical variants showed a specific decrease of Cdc42 expression in the behavioral subgroup. This data support a role of Cdc42 in FTLD and specifically in the behavioral variant.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Case-Control Studies; cdc42 GTP-Binding Protein; Female; Frontotemporal Lobar Degeneration; Humans; Male; Middle Aged

Altered microRNA, mRNA, and Protein Expression of Neurodegeneration-Related Biomarkers and Their Transcriptional and Epigenetic Modifiers in a Human Tau Transgenic Mouse Model in Response to Developmental Lead Exposure. - Masoud, Anwar M; Bihaqi, Syed W; Alansi, Bothaina; Dash, Miriam; Subaiea, Gehad M; Renehan, William E; Zawia, Nasser H (J Alzheimers Dis, 2018)
Amyloid deposits originating from the amyloid-β protein precursor (AβPP) and aggregates of the microtubule associated protein tau (MAPT) are the hallmarks of Alzheimer's disease (AD). Animal studies have demonstrated a link between early life exposure to lead (Pb) and latent overexpression of the AβPP and MAPT genes and their products via epigenetic reprogramming. The present study monitored APP gene and epigenetic mediators and transcription factors known to regulate it. Western blot analysis and quantitative polymerase chain reaction (qPCR) were used to study the mRNA, miRNA, and proteins levels of AβPP, specificity protein 1 (SP1; a transcriptional regulator of amyloid and tau pathway), and epigenetic intermediates namely: DNA methyltransferase (DNMT) 1, DNMT3a and Methyl- CpG protein binding 2 (MeCP2) in the cerebral cortex of transgenic mice (Knock-in for human MAPT). These transgenic mice were developmentally exposed to Pb and the impact on mRNA, miRNA, and protein levels was scrutinized on postnatal days (PND) 20 and 50. The data revealed a consistent inverse relationship between miRNA and protein levels for SP1 and AβPP both in the basal and exposed conditions, which may influence the levels of their corresponding proteins. On the other hand, the relationship between miRNA and protein levels was not correlative for DNMT1 and DNMT3a. MeCP2 miRNA protein levels corresponded only following environmental exposure. These results suggest that developmental exposure to Pb and subsequent AβPP protein levels may be controlled through transcriptional regulators and epigenetic mechanisms that mainly involve miRNA regulation.

Alzheimer's Disease: Recent Concepts on the Relation of Mitochondrial Disturbances, Excitotoxicity, Neuroinflammation, and Kynurenines. - Zádori, Dénes; Veres, Gábor; Szalárdy, Levente; Klivenyi, Peter; Vecsei, Laszlo (J Alzheimers Dis, 2018)
The pathomechanism of Alzheimer's disease (AD) certainly involves mitochondrial disturbances, glutamate excitotoxicity, and neuroinflammation. The three main aspects of mitochondrial dysfunction in AD, i.e., the defects in dynamics, altered bioenergetics, and the deficient transport, act synergistically. In addition, glutamatergic neurotransmission is affected in several ways. The balance between synaptic and extrasynaptic glutamatergic transmission is shifted toward the extrasynaptic site contributing to glutamate excitotoxicity, a phenomenon augmented by increased glutamate release and decreased glutamate uptake. Neuroinflammation in AD is predominantly linked to central players of the innate immune system, with central nervous system (CNS)-resident microglia, astroglia, and perivascular macrophages having been implicated at the cellular level. Several abnormalities have been described regarding the activation of certain steps of the kynurenine (KYN) pathway of tryptophan metabolism in AD. First of all, the activation of indolamine 2,3-dioxygenase, the first and rate-limiting step of the pathway, is well-demonstrated. 3-Hydroxy-L-KYN and its metabolite, 3-hydroxy-anthranilic acid have pro-oxidant, antioxidant, and potent immunomodulatory features, giving relevance to their alterations in AD. Another metabolite, quinolinic acid, has been demonstrated to be neurotoxic, promoting glutamate excitotoxicity, reactive oxygen species production, lipid peroxidation, and microglial neuroinflammation, and its abundant presence in AD pathologies has been demonstrated. Finally, the neuroprotective metabolite, kynurenic acid, has been associated with antagonistic effects at glutamate receptors, free radical scavenging, and immunomodulation, giving rise to potential therapeutic implications. This review presents the multiple connections of KYN pathway-related alterations to three main domains of AD pathomechanism, such as mitochondrial dysfunction, excitotoxicity, and neuroinflammation, implicating possible therapeutic options.
Keywords: Alzheimer Disease; Animals; Central Nervous System; Disease Models, Animal; Energy Metabolism; Glutamic Acid; Humans; Immunity, Innate; Inflammation; Kynurenine; Mitochondria; Quinolinic Acid; Reactive Oxygen Species; Receptors, Glutamate; Signal Transduction

Alzheimer's Disease rs11767557 Variant Regulates EPHA1 Gene Expression Specifically in Human Whole Blood. - Liu, Guiyou; Zhang, Yan; Wang, Longcai; Xu, Jianyong; Chen, Xiaoyun; Bao, Yunjuan; Hu, Yang; Jin, Shuilin; Tian, Rui; Bai, Weiyang; Zhou, Wenyang; Wang, Tao; et al. (J Alzheimers Dis, 2018)
Large-scale genome-wide association studies have reported EPHA1 rs11767557 variant to be associated with Alzheimer's disease (AD) risk in the European population. However, it is still unclear how this variant functionally contributes to the underlying disease pathogenesis. The rs11767557 variant is located approximately 3 kb upstream of EPHA1 gene. We think that rs11767557 may modify the expression of nearby genes such as EPHA1 and further cause AD risk. Until now, the potential association between rs11767557 and the expression of nearby genes has not been reported in previous studies. Here, we evaluate the potential expression association between rs11767557 and EPHA1 using multiple large-scale eQTLs datasets in human brain tissues and the whole blood. The results show that rs11767557 variant could significantly regulate EPHA1 gene expression specifically in human whole blood. These findings may further provide important supplementary information about the regulating mechanisms of rs11767557 variant in AD risk.
Keywords: Alzheimer Disease; Case-Control Studies; China; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Receptor, EphA1; Risk Assessment

Amyloid-β Induces AMPA Receptor Ubiquitination and Degradation in Primary Neurons and Human Brains of Alzheimer's Disease. - Zhang, Yanmin; Guo, Ouyang; Huo, Yuda; Wang, Guan; Man, Heng-Ye (J Alzheimers Dis, 2018)
As the primary mediator for synaptic transmission, AMPA receptors (AMPARs) are crucial for synaptic plasticity and higher brain functions. A downregulation of AMPAR expression has been indicated as one of the early pathological molecular alterations in Alzheimer's disease (AD), presumably via amyloid-β (Aβ). However, the molecular mechanisms leading to the loss of AMPARs remain less clear. We report that in primary neurons, application of Aβ triggers AMPAR internalization accompanied with a decrease in cell-surface AMPAR expression. Importantly, in both Aβ-treated neurons and human brain tissue from AD patients, we observed a significant decrease in total AMPAR amount and an enhancement in AMPAR ubiquitination. Consistent with facilitated receptor degradation, AMPARs show higher turnover rates in the presence of Aβ. Furthermore, AD brain lysates and Aβ-incubated neurons show increased expression of the AMPAR E3 ligase Nedd4 and decreased expression of AMPAR deubiquitinase USP46. Changes in these enzymes are responsible for the Aβ-dependent AMPAR reduction. These findings indicate that AMPAR ubiquitination acts as the key molecular event leading to the loss of AMPARs and thus suppressed synaptic transmission in AD.

Analyses of Clinical Features and Investigations on Potential Mechanisms in Patients with Alzheimer's Disease and Olfactory Dysfunction. - Zuo, Li-Jun; Guo, Peng; Liu, Li; Yu, Shu-Yang; Lian, Teng-Hong; Yu, Qiu-Jin; Hu, Yang; Jin, Zhao; Wang, Rui-Dan; Piao, Ying-Shan; Li, Li-Xia; Wang, Ya-Jie; et al. (J Alzheimers Dis, 2018)
BACKGROUND: OD is common in patients with Alzheimer's disease (AD). However, the relationship between OD and clinical symptoms and the potential mechanisms of OD in AD patients are still unknown. OBJECTIVE: To explore the relationship between OD and clinical symptoms and the potential mechanisms of OD in AD patients. METHODS: We evaluated OD using the Hyposmia Rating Scale (HRS), classified patients into AD with OD (AD-OD) and AD with no OD (AD-NOD) groups, and detected the levels of free radicals and inflammatory factors, including hydroxyl radical (•OH), hydrogen peroxide (H2O2), nitric oxide, interleukin-1β, interleukin-6, tumor necrosis factor-α, and prostaglandin E2 in serum from AD patients. RESULTS: It was shown that the scores of the Mini-Mental State Examination, Animal Fluency Test, Boston Naming Test (BNT), and Auditory Verbal Learning Test-delayed recall were all significantly lower and the score of overall activity of daily living (ADL) and instrumental ADL were significantly higher in AD-OD group than those in AD-NOD group. Compared with AD-NOD group, •OH level in serum was prominently elevated, and H2O2 level was dramatically declined in AD-OD group. In the correlation analysis, HRS score was significantly and positively correlated with the score of BNT, and negatively correlated with •OH level in serum. CONCLUSIONS: AD-OD patients suffered from severe cognitive impairment in the domain of language. Oxidative stress might be correlated with AD-OD featured by the drastically increased •OH level in serum.

Analysis of Brain Donors' Demographic and Medical Characteristics to Facilitate the Construction of a Human Brain Bank in China. - Zhang, Hanlin; Chen, Kang; Wang, Naili; Zhang, Di; Yang, Qian; Zhang, Qing; Liu, Pan; Wan, Mengyao; Gong, Changlin; Hong, Xinyu; Qiu, Wenying; Qian, Xiaojing; et al. (J Alzheimers Dis, 2018)
The Chinese Academy of Medical Sciences and Peking Union Medical College (CAMS/PUMC) Human Brain Bank was established in December 2012 and had accomplished 197 brain donations by November 2017. The brain bank was based on a large-scale willed body donation program in CAMS/PUMC starting from 1999. Demographic and medical characteristic analysis of brain donors was conducted to facilitate the construction of the brain bank. The average postmortem delay of brain donors was 17.7 h and 77.7% of these donors died less than 15 km away from the brain bank. Donors were predominantly with higher-level education (p < 0.001) and at an older age when registration (p < 0.001) and donation (p < 0.001) occurred. Our results elucidated the characteristics of donors in the CAMS/PUMC Human Brain Bank, which may provide useful information to target potential donors and improve the quality and quantity of brain specimens. The current study may pave the way for the construction of a nationwide network of standardized human brain banks in China.

Application of Weighted Gene Co-Expression Network Analysis to Explore the Key Genes in Alzheimer's Disease. - Liang, Jia-Wei; Fang, Zheng-Yu; Huang, Yong; Liuyang, Zhen-Yu; Zhang, Xiao-Lin; Wang, Jing-Lin; Wei, Hui; Wang, Jian-Zhi; Wang, Xiao-Chuan; Zeng, Ji; Liu, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Weighted co-expression network analysis (WGCNA) is a powerful systems biology method to describe the correlation of gene expression based on the microarray database, which can be used to facilitate the discovery of therapeutic targets or candidate biomarkers in diseases. OBJECTIVE: To explore the key genes in the development of Alzheimer's disease (AD) by using WGCNA. METHODS: The whole gene expression data GSE1297 from AD and control human hippocampus was obtained from the GEO database in NCBI. Co-expressed genes were clustered into different modules. Modules of interest were identified through calculating the correlation coefficient between the module and phenotypic traits. GO and pathway enrichment analyses were conducted, and the central players (key hub genes) within the modules of interest were identified through network analysis. The expression of the identified key genes was confirmed in AD transgenic mice through using qRT-PCR. RESULTS: Two modules were found to be associated with AD clinical severity, which functioning mainly in mineral absorption, NF-κB signaling, and cGMP-PKG signaling pathways. Through analysis of the two modules, we found that metallothionein (MT), Notch2, MSX1, ADD3, and RAB31 were highly correlated with AD phenotype. Increase in expression of these genes was confirmed in aged AD transgenic mice. CONCLUSION: WGCNA analysis can be used to analyze and predict the key genes in AD. MT1, MT2, MSX1, NOTCH2, ADD3, and RAB31 are identified to be the most relevant genes, which may be potential targets for AD therapy.

The Association of Mid- and Late-Life Systemic Inflammation with Brain Amyloid Deposition: The ARIC-PET Study. - Walker, Keenan A; Windham, B Gwen; Brown, Charles H; Knopman, David S; Jack, Clifford R; Mosley, Thomas H; Selvin, Elizabeth; Wong, Dean F; Hughes, Timothy M; Zhou, Yun; Gross, Alden L; Gottesman, Rebecca F (J Alzheimers Dis, 2018)
BACKGROUND: Although inflammation has been implicated in the pathogenesis of Alzheimer's disease, the effects of systemic inflammation on brain amyloid deposition remain unclear. OBJECTIVE: We examined the association of midlife and late-life systemic inflammation with late-life brain amyloid levels in a community sample of non-demented older adults from the Atherosclerosis Risk in Communities (ARIC) - PET Study. METHODS: 339 non-demented participants (age: 75 [SD 5]) were recruited from the ARIC Study to undergo florbetapir PET (amyloid) imaging. Blood levels of high sensitivity C-reactive protein (CRP), a marker of systemic inflammation, were measured 22 years (Visit 2), 16 years (Visit 4), and up to 2 years before PET imaging (Visit 5). Elevated brain amyloid deposition (standardized uptake value ratio >1.2) was the primary outcome. RESULTS: Our primary analyses found no association of midlife and late-life CRP with late-life brain amyloid levels. However, in secondary stratified analyses, we found that higher midlife (Visit 2) CRP was associated with elevated amyloid among males (OR 1.65, 95% CI: 1.13-2.42), and among white (OR 1.33, 95% CI: 1.02-1.75), but not African American, participants (p-interactions<0.05). Among male participants, those who maintained high CRP levels (≥3 mg/L) throughout mid- and late-life were most likely to have elevated brain amyloid (OR, 8.81; 95% CI: 1.23, 62.91). CONCLUSIONS: Although our primary analysis does not support an association between systemic inflammation and brain amyloid deposition, we found evidence for sex- and race-dependent associations. However, findings from subgroup analyses should be interpreted with caution.

Association of Plasma Neurofilament Light Chain with Neocortical Amyloid-β Load and Cognitive Performance in Cognitively Normal Elderly Participants. - Chatterjee, Pratishtha; Goozee, Kathryn; Sohrabi, Hamid R; Shen, Kaikai; Shah, Tejal; Asih, Prita R; Dave, Preeti; ManYan, Candice; Taddei, Kevin; Chung, Roger; Zetterberg, Henrik; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The disruption of neurofilament, an axonal cytoskeletal protein, in neurodegenerative conditions may result in neuronal damage and its release into the cerebrospinal fluid and blood. In Alzheimer's disease (AD), neurofilament light chain (NFL), a neurofilament subunit, is elevated in the cerebrospinal fluid and blood. OBJECTIVE: Investigate the association of plasma NFL with preclinical-AD features, such as high neocortical amyloid-β load (NAL) and subjective memory complaints, and cognitive performance in cognitively normal older adults. METHODS: Plasma NFL concentrations were measured employing the single molecule array platform in participants from the Kerr Anglican Retirement Village Initiative in Ageing Health cohort, aged 65- 90 years. Participants underwent a battery of neuropsychological testing to evaluate cognitive performance and were categorized as low NAL (NAL-, n = 65) and high NAL (NAL+, n = 35) assessed via PET, and further stratified into subjective memory complainers (SMC; nNAL- = 51, nNAL+ = 25) and non-SMC (nNAL- = 14, nNAL+ = 10) based on the Memory Assessment Clinic- Questionnaire. RESULTS: Plasma NFL inversely correlated with cognitive performance. No significant difference in NFL was observed between NAL+ and NAL- participants; however, within APOEɛ4 non-carriers, higher NAL was observed in individuals with NFL concentrations within quartiles 3 and 4 (versus quartile 1). Additionally, within the NAL+ participants, SMC had a trend of higher NFL compared to non-SMC. CONCLUSION: Plasma NFL is inversely associated with cognitive performance in elderly individuals. While plasma NFL may not reflect NAL in individuals with normal global cognition, the current observations indicate that onset of axonal injury, reflected by increased plasma NFL, within the preclinical phase of AD may contribute to the pathogenesis of AD.

Automated Multi-Atlas Segmentation of Hippocampal and Extrahippocampal Subregions in Alzheimer's Disease at 3T and 7T: What Atlas Composition Works Best? - Xie, Long; Shinohara, Russell T; Ittyerah, Ranjit; Kuijf, Hugo J; Pluta, John B; Blom, Kim; Kooistra, Minke; Reijmer, Yael D; Koek, Huiberdina L; Zwanenburg, Jaco J M; Wang, Hongzhi; Luijten, Peter R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Multi-atlas segmentation, a popular technique implemented in the Automated Segmentation of Hippocampal Subfields (ASHS) software, utilizes multiple expert-labelled images ("atlases") to delineate medial temporal lobe substructures. This multi-atlas method is increasingly being employed in early Alzheimer's disease (AD) research, it is therefore becoming important to know how the construction of the atlas set in terms of proportions of controls and patients with mild cognitive impairment (MCI) and/or AD affects segmentation accuracy. OBJECTIVE: To evaluate whether the proportion of controls in the training sets affects the segmentation accuracy of both controls and patients with MCI and/or early AD at 3T and 7T. METHODS: We performed cross-validation experiments varying the proportion of control subjects in the training set, ranging from a patient-only to a control-only set. Segmentation accuracy of the test set was evaluated by the Dice similarity coeffiecient (DSC). A two-stage statistical analysis was applied to determine whether atlas composition is linked to segmentation accuracy in control subjects and patients, for 3T and 7T. RESULTS: The different atlas compositions did not significantly affect segmentation accuracy at 3T and for patients at 7T. For controls at 7T, including more control subjects in the training set significantly improves the segmentation accuracy, but only marginally, with the maximum of 0.0003 DSC improvement per percent increment of control subject in the training set. CONCLUSION: ASHS is robust in this study, and the results indicate that future studies investigating hippocampal subfields in early AD populations can be flexible in the selection of their atlas compositions.

Aβ42/Aβ40 and Aβ42/Aβ38 Ratios Are Associated with Measures of Gait Variability and Activities of Daily Living in Mild Alzheimer's Disease: A Pilot Study. - Koychev, Ivan; Galna, Brook; Zetterberg, Henrik; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil H; Rowe, James B; Thomas, Alan; Howard, Robert; Malhotra, Paresh; Ritchie, Craig; Lovestone, Simon; et al. (J Alzheimers Dis, 2018)
Gait disturbances are some of the earliest changes in dementia and their monitoring presents an opportunity for early diagnosis. The exact relationship between gait and well-established biomarkers of Alzheimer's disease (AD) remains to be clarified. In this study we compared gait-related measures with cerebrospinal fluid (CSF) markers of AD pathology. We recruited seventeen participants with mild AD in a multi-site study and performed gait assessment as well as lumbar punctures to obtain CSF. CSF Aβ42/Aβ40 and Aβ42/Aβ38 correlated positively with measures of variability (step time and step length) in the clinic-based assessments. This was driven by a negative relationship between gait variability and Aβ40 and Aβ38 but not Aβ42.The amyloid ratios and gait variability measures were also associated with more severe functional impairment. We interpret these data as an indication that increasing amyloid production (i.e., increasing Aβ40 and Aβ38) is associated with diminishing cognitive-motor control of gait. These preliminary results suggest that the two amyloid ratios may be a marker of the earliest disturbances in the interplay between cognitive and motor control which characterize dementia.

Berberine Alleviates Tau Hyperphosphorylation and Axonopathy-Associated with Diabetic Encephalopathy via Restoring PI3K/Akt/GSK3β Pathway. - Wang, Shanshan; He, Benhong; Hang, Weijian; Wu, NingHua; Xia, Liangtao; Wang, Xu; Zhang, Qianying; Zhou, Xinwen; Feng, Zuohua; Chen, Qingjie; Chen, Juan (J Alzheimers Dis, 2018)
BACKGROUND: Axonopathy is closely linked to the development of diabetic encephalopathy induced by type II diabetes (T2D). Berberine has been shown to cross the blood-brain barrier and holds promising effect for neuronal damage in diabetes. OBJECTIVE: The present study investigated the protective effect and the underlying mechanism of berberine on neuronal axonopathy in both in vitro and in vivo models. METHODS: High glucose/high fat diet and streptozotocin injection-induced T2D rat model was used. Berberine was administered p.o. to T2D rat model for 10 weeks. Morris water maze test, in vivo neuronal tracing, immunohistochemistry, and western blot analysis were performed to evaluate the protective effects of berberine in T2D-induced diabetic encephalopathy rats. Primary cultured neurons were used to further explore the underlying mechanisms in vitro. RESULTS: Berberine dramatically reduced blood glucose and serum insulin levels and alleviated insulin resistance. Berberine significantly attenuated memory impairment, axonopathy, and tau hyperphosphorylation, and also restored PI3K/Akt/GSK3β signaling pathway in T2D rats. In vitro, berberine induced an increase in the phosphorylation of PI3K/Akt as well as GSK3β in high glucose-treated primary neurons. Furthermore, berberine-induced PI3K/Akt activation also resulted in the dephosphorylation of tau protein, which could improve axonal transport impairment in high glucose-treated primary neurons. Pretreated neurons with LY294002, an inhibitor of PI3K, partially blocked berberine-inhibited tau phosphorylation and berberine-activated PI3K/Akt signaling pathway. CONCLUSIONS: Berberine exerts the protective effect against cognitive deficits by improving tau hyperphosphorylation and the axonal damage through restoring PI3K/Akt/GSK3β signaling pathway.

Brazilian Green Propolis Prevents Cognitive Decline into Mild Cognitive Impairment in Elderly People Living at High Altitude. - Zhu, Aiqin; Wu, Zhou; Zhong, Xin; Ni, Junjun; Li, Yinglan; Meng, Jie; Du, Can; Zhao, Xue; Nakanishi, Hiroshi; Wu, Shizheng (J Alzheimers Dis, 2018)
BACKGROUND: Systemic inflammation is known as a risk factor of cognitive decline. OBJECTIVE: To investigate the effects of propolis on cognitive decline and systemic inflammation in elderly people living at high altitude. METHODS: Sixty participants (average 72.8 years) living at altitude (2,260 meters) were randomized to receive propolis (0.83 g, n = 30) or placebo (n = 30) for 24 months. Cognitive outcomes were assessed using MMSE and serum cytokine levels were measured for 24 months in a double-blind study. RESULTS: MMSE scores were 26.17 at baseline and 23.87 at 24 months in placebo group. Compared to placebo group, improvements of MMSE scores were significant in propolis-treated subjects (p = 0.007) with a response emerging over time (time points×group interaction, p = 0.016). In addition, the serum IL-1β and IL-6 levels were significantly different across treatments (p < 0.0001) showing upward and downward trends in placebo- and propolis-treated subjects, respectively (p < 0.0001). Serum levels of TNF-α were not significantly different across treatment (p = 0.0528) but with a response emerging over time (time points×group interaction, p = 0.016). In contrast, serum levels of TGFβ1 were significantly different across treatments (p < 0.0001) showing downward and upward trends in placebo- and propolis-treated subjects, respectively. Serum levels of IL-10 were significant for the effect of groups (p = 0.0411). Furthermore, MMSE scores correlated with the decrease in IL-1β and the increase in TGFβ1 in serum. CONCLUSION: Elderly people living at high altitude developed to MCI in 24 months with exacerbation of systemic inflammation. Ingestion of propolis (>12 months) protected against cognitive decline after systemic inflammation was reduced.

Cannabinoid Receptor 2-Deficiency Ameliorates Disease Symptoms in a Mouse Model with Alzheimer's Disease-Like Pathology. - Schmöle, Anne-Caroline; Lundt, Ramona; Toporowski, Gregor; Hansen, Jan N; Beins, Eva; Halle, Annett; Zimmer, Andreas (J Alzheimers Dis, 2018)
It is widely accepted that the endocannabinoid system (ECS) is a modulator of neuroinflammation associated with neurodegenerative disorders, including Alzheimer's disease (AD). Thus, expression of the cannabinoid receptor 2 (CB2) is induced in plaque-associated microglia and astrocytes in brain tissues from AD patients and in genetic mouse models expressing pathogenic variants of the amyloid precursor protein (APP). However, the exact mechanism of CB2 signaling in this mouse model remains elusive, because the genetic deletion of CB2 and the pharmacological activation of CB2 both reduced neuroinflammation. Here, we demonstrate that CB2 deletion also improved cognitive and learning deficits in APP/PS1*CB2-/- mice. This was accompanied by reduced neuronal loss and decreased plaque levels and coincided with increased expression of Aβ degrading enzymes. Interestingly, plaque-associated microglia in APP/PS1*CB2-/- mice showed a less activated morphology, while plaques were smaller and more condensed than in APP/PS1 mice. Taken together, these results indicate a beneficial effect of CB2-deficiency in APP transgenic mice. CB2 appears to be part of a protective system that may be detrimental when engaged continuously.

Cardiorespiratory Fitness and White Matter Neuronal Fiber Integrity in Mild Cognitive Impairment. - Ding, Kan; Tarumi, Takashi; Zhu, David C; Tseng, Benjamin Y; Thomas, Binu P; Turner, Marcel; Repshas, Justin; Kerwin, Diana R; Womack, Kyle B; Lu, Hanzhang; Cullum, C Munro; Zhang, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Mounting evidence showed the self-reported levels of physical activity are positively associated with white matter (WM) integrity and cognitive performance in normal adults and patients with mild cognitive impairment (MCI). However, the objective measure of cardiorespiratory fitness (CRF) was not used in these studies. OBJECTIVE: To determine the associations of CRF measured by maximal oxygen uptake (VO2max) with WM fiber integrity and neurocognitive performance in older adults with MCI. METHODS: Eighty-one participants (age = 65±7 years, 43 women), including 26 cognitively normal older adults and 55 amnestic MCI patients, underwent VO2max test to measure CRF, diffusion tensor imaging (DTI) to assess WM fiber integrity, and neurocognitive assessment focused on memory and executive function. DTI data were analyzed by the tract-based spatial statistics and region-of-interest approach. RESULTS: Cognitively normal older adults and MCI patients were not different in global WM fiber integrity and VO2max. VO2max was associated positively with DTI metrics of fractional anisotropy in ∼54% WM fiber tracts, and negatively with mean and radial diffusivities in ∼46% and ∼56% of the WM fiber tracts. The associations of VO2max with DTI metrics remained statistically significant after adjustment of age, sex, body mass index, WM lesion burden, and MCI status. The DTI metrics obtained from the area that correlated to VO2max were associated with executive function performance in MCI patients. CONCLUSIONS: Higher levels of CRF are associated with better WM fiber integrity, which in turn is correlated with better executive function performance in MCI patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anisotropy; Cardiorespiratory Fitness; Case-Control Studies; Cognition; Cognitive Dysfunction; Diffusion Tensor Imaging; Executive Function; Female; Humans; Linear Models; Male; Memory; Middle Aged; Nerve Fibers, Myelinated; Neuropsychological Tests; Texas; White Matter

Ceftriaxone Improves Cognitive Function and Upregulates GLT-1-Related Glutamate-Glutamine Cycle in APP/PS1 Mice. - Fan, ShuJuan; Xian, XiaoHui; Li, Li; Yao, XiaoGuang; Hu, YuYan; Zhang, Min; Li, WenBin (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by progressive impairment of learning, memory, and cognitive deficits. Glutamate is the major excitatory neurotransmitter in the central nervous system and plays an important role in learning, memory, and cognition. The homeostasis and reutilization of glutamate are dependent on astrocytic uptake by glutamate transporter-1 (GLT-1) and the subsequent glutamate-glutamine cycle. Increasing evidence showed impairments in GLT-1 expression and uptake activity and glutamate-glutamine cycle in AD. Ceftriaxone (Cef) has been reported to upregulate the expression and uptake of GLT-1. Therefore, the present study was undertaken to explore whether Cef can improve cognitive deficits of APP/PS1 mice in early stage of AD by upregulating GLT-1 expression, and then promoting the glutamate-glutamine cycle. It was shown that Cef treatment significantly alleviated the cognitive deficits measured by Morris water maze test and upregulated GLT-1 protein expression in the hippocampus of APP/PS1 mice. Particularly, the activity of glutamine synthetase (GS) and the protein expression of system N glutamine transporter 1 (SN1), which are the key factors involved in the glutamate-glutamine cycle, were significantly upregulated as well after the Cef treatment. Furthermore, inhibition of GLT-1 uptake activity by dihydrokainic acid, an inhibitor of GLT-1, blocked the Cef-induced improvement on the cognitive deficits, GS activity, and SN1 expression. The above results suggested that Cef could improve cognitive deficits of APP/PS1 mice in early stage of AD by upregulating the GLT-1 expression, GS activity, and SN1 expression, which would lead to stimulating the glutamate-glutamine cycle.

Cerebral Amyloid Angiopathy: Similarity in African-Americans and Caucasians with Alzheimer's Disease. - Kamara, Dennis M; Gangishetti, Umesh; Gearing, Marla; Willis-Parker, Monica; Zhao, Liping; Hu, William T; Walker, Lary C (J Alzheimers Dis, 2018)
Cerebral amyloid angiopathy (CAA) of the Aβ type is variably present in the brains of patients with Alzheimer's disease (AD). CAA contributes to cognitive decline and increases the risk of lobar hemorrhage; because both AD-typical dementia and lobar hemorrhage are more common in African-Americans than in Caucasians, we postulated that African-Americans with AD might be particularly susceptible to CAA. To test this hypothesis, we analyzed CAA histopathologically in the large vessels and capillaries of autopsy-derived frontal, temporal, parietal, and occipital cortical samples from African-Americans (n = 18) and Caucasians (n = 19) with end-stage AD. In the combined cohort of 37 subjects, 22% of the subjects had severe CAA in large vessels, and 11% had severe CAA in capillaries. However, the prevalence and histopathologic characteristics of CAA were similar in the African-Americans and Caucasians. This conclusion was substantiated in an independent sample from the National Alzheimer's Coordinating Center database, in which the degree of CAA was comparable in 1,554 Caucasians and 68 African-Americans with end-stage AD. These findings support a growing consensus that the fundamental histopathologic features of AD are largely impartial to the race of the afflicted.

Cerebrospinal Fluid Amyloid-β Levels are Increased in Patients with Insomnia. - Chen, Dong-Wan; Wang, Jun; Zhang, Li-Li; Wang, Yan-Jiang; Gao, Chang-Yue (J Alzheimers Dis, 2018)
Previous studies demonstrate that patients with sleep disorders are at risk of developing Alzheimer's disease (AD), with the mechanism unknown. It is suggested that acute sleep deprivation induces an increase of amyloid-β (Aβ), the major pathological agent in AD, in the cerebrospinal fluid (CSF). In the present study, we recruited 23 patients with chronic insomnia aged between 46 to 67 years and 23 healthy controls aged between 43 to 67 years. We investigated the CSF levels of Aβ and tau, another pathological hallmark in the AD pathogenesis. We found that CSF Aβ42 levels were significantly increased in insomnia patients. However, no significant difference was found in Aβ40, total tau (t-Tau), and phosphorylated tau (p-Tau) between the two groups. Furthermore, we found that CSF Aβ40 and Aβ42 levels are significantly correlated with the sleep quality, as reflected by the Pittsburgh Sleep Quality Index (PSQI) scores. But no significant correlation was found in CSF t-Tau and p-Tau levels with PSQI. Our results indicate that chronic sleep disorders may induce the disruption of Aβ metabolism in the brain, thus increase the risk for developing AD.
Keywords: Adult; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Humans; Male; Middle Aged; Phosphorylation; Sleep Initiation and Maintenance Disorders; tau Proteins

Cerebrospinal Fluid and Plasma Levels of Inflammation Differentially Relate to CNS Markers of Alzheimer's Disease Pathology and Neuronal Damage. - Bettcher, Brianne M; Johnson, Sterling C; Fitch, Ryan; Casaletto, Kaitlin B; Heffernan, Kate S; Asthana, Sanjay; Zetterberg, Henrik; Blennow, Kaj; Carlsson, Cynthia M; Neuhaus, John; Bendlin, Barbara B; Kramer, Joel H (J Alzheimers Dis, 2018)
Inflammatory markers have been shown to predict neurocognitive outcomes in aging adults; however, the degree to which peripheral markers mirror the central nervous system remains unknown. We investigated the association between plasma and cerebrospinal fluid (CSF) markers of inflammation, and explored whether these markers independently predict CSF indicators of Alzheimer's disease (AD) pathology or neuronal damage. Plasma and CSF samples were analyzed for inflammatory markers in a cohort of asymptomatic older adults (n = 173). CSF samples were analyzed for markers of AD pathology (Aβ42, phosphorylated tau [p-tau], sAβPPβ) or neuronal damage (total tau; neurofilament light chain) (n = 147). Separate linear models for each analyte were conducted with CSF and plasma levels entered simultaneously as predictors and markers of AD pathology or neuronal damage as outcome measures. Strong associations were noted between CSF and plasma MIP-1β levels, and modest associations were observed for remaining analytes. With respect to AD pathology, higher levels of plasma and CSF IL-8, CSF MIP-1β, and CSF IP-10 were associated with higher levels of p-tau. Higher levels of CSF IL-8 were associated with higher levels of CSF Aβ42. Higher CSF sAβPPβ levels were associated with higher plasma markers only (IL-8; MCP-1). In terms of neuronal injury, higher levels of plasma and CSF IL-8, CSF IP-10, and CSF MIP-1β were associated with higher levels of CSF total tau. Exploratory analyses indicated that CSF Aβ42 modifies the relationship between plasma inflammatory levels and CSF tau levels. Results suggest that both plasma and CSF inflammatory markers independently relay integral information about AD pathology and neuronal damage.

Cerebrospinal Fluid Biomarkers are Differentially Related to Structural and Functional Changes in Dementia of the Alzheimer's Type. - Malpas, Charles B; Saling, Michael M; Velakoulis, Dennis; Desmond, Patricia; Hicks, Rodney J; Zetterberg, Henrik; Blennow, Kaj; O'Brien, Terence J (J Alzheimers Dis, 2018)
The two cardinal pathologies of Alzheimer's disease (AD) develop according to distinct anatomical trajectories. Cerebral tau-related pathology first accumulates in the mesial temporal region, while amyloid-related pathology first appears in neocortex. The eventual distributions of these pathologies reflect their anatomical origins. An implication is that the cardinal pathologies might exert preferential effects on the structurofunctional brain changes observed in AD. We investigated this hypothesis in 39 patients with dementia of the Alzheimer's type. Interrelationships were analyzed between cerebrospinal fluid biomarkers of the cardinal pathologies, volumetric brain changes using magnetic resonance imaging, and brain metabolism using [18F]-FDG-PET. Amyloid-related pathology was preferentially associated with structurofunctional changes in the precuneus and lateral temporal regions. Tau-related pathology was not associated with changes in these regions. These findings support the hypothesis that tau- and amyloid-pathology exert differential effects on structurofunctional changes in the AD brain. These findings have implications for future therapeutic trials and hint at a more complex relationship between the cardinal pathologies and disruption of brain networks.

CFH and ARMS2 Polymorphisms Interact with Zinc Supplements in Cognitive Impairment in the Women's Health Initiative Hormone Trial. - Kustra, Rafal; Awh, Carl C; Rojas-Fernandez, Carlos; Zanke, Brent (J Alzheimers Dis, 2018)
BACKGROUND: An interaction between genetic variants in complement factor H (CFH) and age-related maculopathy susceptibility 2 (ARMS2) and high-dose zinc supplementation on progression to advanced age-related macular degeneration (AMD) exists. Because cognitive impairment (CI) is associated with AMD, we used data from the Women's Health Initiative (WHI) to search for a zinc/genetics interaction. OBJECTIVE: To study the interaction of chronic zinc supplementation with genetic variants in CFH and ARMS2 on the development of CI. BACKGROUND: Zinc dietary supplements, CFH and ARMS2 genotypes, and serial mental status was analyzed in participants with available genetic data (n = 7,483). Cognition was assessed using the Modified Mini-Mental State Examination. The development of CI over 5 years was analyzed by genotype and zinc intake using a repeated measures logistic regression model. RESULTS: Zinc supplementation of approximately 15 mg/day was associated with decreased development of CI in women with 1 or 2 CFH and no ARMS2 risk alleles (OR = 0.46: 1 CFH risk allele; 0.20: 2 CFH risk alleles; p = 0.002). CONCLUSION: Low-dose zinc (approximately 15 mg) is associated with reduced CI in women with 2 CFH and 0 ARMS2 AMD risk alleles. This interaction is opposite in direction to that observed in AMD, where patients with 2 CFH and 0 ARMS2 risk alleles had increased progression to neovascular AMD if treated with 80 mg/day of zinc. This may be due to a zinc dose-response or to a fundamental difference in the role of zinc in the progression of early CI versus advanced AMD.

Chinese Herbal Medicine for Vascular Dementia: A Systematic Review and Meta-Analysis of High-Quality Randomized Controlled Trials. - Xu, Qing-Qing; Shan, Chun-Shuo; Wang, Yong; Shi, Yi-Hua; Zhang, Qi-Hao; Zheng, Guo-Qing (J Alzheimers Dis, 2018)
BACKGROUND: Vascular dementia (VaD) is the second common form of dementia and Chinese herbal medicine (CHM) has been used for aging-related disorders for thousands of years. However, there is still a lack of scientific evidence using CHM for VaD. OBJECTIVE: To conduct a systematic review to assess the current evidence available for the effectiveness and safety of CHM for VaD. METHODS: Six databases were searched for high-quality randomized-controlled clinical trials that met the requirements of at least 4 of the 7 domains of the Cochrane risk of bias tool from their inception to February 2017. RevMan 5.3 was applied for data analysis. RESULTS: Forty studies with 42 comparisons and 3,572 individuals were included. The studies investigated the CHM versus placebo (n = 4), CHM versus western conventional treatment (WCT) (n = 36), and CHM plus WCT versus WCT (n = 2). Meta-analysis showed that CHM for VaD could improve Mini-Mental State Examination (MMSE), the Activities of Daily Living, Hasegawa's dementia scale, and clinical effective rate but had statistically similar effect based on Blessed Behavior Scale (BBS) outcome when compared with WCTs. When compared with placebo, CHMs were more beneficial in improving MMSE but showed no significant difference in BBS scores. CHM as adjuvant therapy exerted an additive anti-VaD benefit on MMSE scores. The participants of CHM group had fewer adverse events than that of the placebo group or WCT group. CONCLUSION: The findings of the present study support, at least to an extent, that CHM can be recommended for routine use for treatment of VaD.

Chinese Herbal Medicine Xueshuantong Enhances Cerebral Blood Flow and Improves Neural Functions in Alzheimer's Disease Mice. - Huang, Yangmei; Guo, Baihong; Shi, Bihua; Gao, Qingtao; Zhou, Qiang (J Alzheimers Dis, 2018)
Reduced cerebral blood flow in Alzheimer's disease (AD) may occur in early AD, which contributes to the pathogenesis and/or pathological progression of AD. Reversing this deficit may have therapeutic potential. Certain traditional Chinese herbal medicines (e.g., Saponin and its major component Xueshuantong [XST]) increase blood flow in humans, but whether they could be effective in treating AD patients has not been tested. We found that systemic XST injection elevated cerebral blood flow in APP/PS1 transgenic mice using two-photon time-lapse imaging in the same microvessels before and after injection. Subchronic XST treatment led to improved spatial learning and memory and motor performance in the APP/PS1 mice, suggesting improved neural plasticity and functions. Two-photon time lapse imaging of the same plaques revealed a reduction in plaque size after XST treatment. In addition, western blots experiments showed that XST treatment led to reduced processing of amyloid-β protein precursor (AβPP) and enhanced clearance of amyloid-β (Aβ) without altering the total level of AβPP. We also found increased synapse density in the immediate vicinity of amyloid plaques, suggesting enhanced synaptic function. We conclude that targeting cerebral blood flow can be an effective strategy in treating AD.

Chronic Traumatic Encephalopathy and Neurodegeneration in Contact Sports and American Football. - Zuckerman, Scott L; Brett, Benjamin L; Jeckell, Aaron; Yengo-Kahn, Aaron M; Solomon, Gary S (J Alzheimers Dis, 2018)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease characterized by the presence of abnormally phosphorylated tau protein in the depths of one or more cortical sulci. Controversy over the risk of CTE and neurologic disorders later in life among contact sport athletes has taken hold in the public spotlight, most notably in American football. Players, parents, coaches, and legislators have taken action based on the commonly held notion that contact sports invariably lead to neurodegenerative disorders. However, to fully understand the science behind this assumed association, a critical appraisal of the evidence is warranted. With regards to CTE in sports, the objectives of the current report are to: 1) describe the history of CTE, 2) review current CTE definitions, 3) critically evaluate the empiric data, divided into all contact sports and exclusively American football, and 4) summarize notable themes for future research.

Circulatory Levels of Toxic Metals (Aluminum, Cadmium, Mercury, Lead) in Patients with Alzheimer's Disease: A Quantitative Meta-Analysis and Systematic Review. - Xu, Lin; Zhang, Wenchao; Liu, Xianchen; Zhang, Cuili; Wang, Pin; Zhao, Xiulan (J Alzheimers Dis, 2018)
BACKGROUND: Environmental exposure to toxic metals has been postulated to play a role in the pathophysiological processes of Alzheimer's disease (AD). However, the circulatory levels of toxic metals in AD patients are not consistent in previous studies. OBJECTIVE: To systematically assess levels of toxic metals (aluminum, mercury, cadmium, lead) in the circulation (blood, serum/plasma) of AD patients and controls. METHODS: PubMed, Web of Science, Science Direct, Cochrane Library, and the China National Knowledge Infrastructure (CNKI) were systematically searched to identify studies published up to January 1, 2017. Meta-analyses were performed using random-effects models and the pooled standardized mean difference (SMD) were reported with 95% confidence intervals (CI). RESULTS: We identified 17, 7, 8, and 10 studies for aluminum, mercury, cadmium, and lead, respectively. Meta-analyses showed significantly elevated circulatory levels of aluminum (SMD = 1.08, 95% CI: 0.66, 1.50), mercury (SMD = 0.55, 95% CI, 0.15, 0.95), and cadmium (SMD = 0.62, 95% CI: 0.12, 1.11), whereas lower levels of lead (SMD = -0.23, 95% CI: -0.38, -0.07) in AD patients than in controls. Publication bias was only observed for aluminum studies, but the "trim and fill" analysis showed that the publication bias did not alter the direction of the effect. Sensitivity analyses showed no studies from the pooled analysis changed the results. CONCLUSION: Compared to controls, circulatory levels of aluminum, mercury, and cadmium are significantly higher but the levels of lead were reduced in AD patients. These findings suggest that elevated aluminum, mercury, and cadmium in the circulation, especially in serum may play a role in the progression of AD.

Class-Specific Incidence of All-Cause Dementia and Alzheimer's Disease: A Latent Class Approach. - Zammit, Andrea R; Hall, Charles B; Katz, Mindy J; Muniz-Terrera, Graciela; Ezzati, Ali; Bennett, David A; Lipton, Richard B (J Alzheimers Dis, 2018)
Identifying preclinical Alzheimer's disease (AD) is an important step toward developing approaches to early treatment and dementia prevention. We applied latent class analysis (LCA) to 10 baseline neuropsychological assessments for 1,345 participants from Einstein Aging Study. Time-to-event models for all-cause dementia and AD were run examining events in 4-year intervals. Five classes were identified: Mixed-Domain Impairment (n = 107), Memory-Specific Impairment (n = 457), Average (n = 539), Frontal Impairment (n = 118), and Superior Cognition (n = 124). Compared to the Average class, the Mixed-Domain Impairment and Memory-Specific Impairment classes were at higher risk of incident all-cause dementia and AD in the first 4 years from baseline, while the Frontal Impairment class was associated with higher risk between 4 and 8 years of follow-up. LCA identified classes which differ in cross-sectional cognitive patterns and in risk of dementia over specific follow-up intervals.

Clinical Trials for Disease-Modifying Therapies in Alzheimer's Disease: A Primer, Lessons Learned, and a Blueprint for the Future. - Cummings, Jeffrey; Ritter, Aaron; Zhong, Kate (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) has no currently approved disease-modifying therapies (DMTs), and treatments to prevent, delay the onset, or slow the progression are urgently needed. A delay of 5 years if available by 2025 would decrease the total number of patients with AD by 50% in 2050. To meet the definition of DMT, an agent must produce an enduring change in the course of AD; clinical trials of DMTs have the goal of demonstrating this effect. AD drug discovery entails target identification followed by high throughput screening and lead optimization of drug-like compounds. Once an optimized agent is available and has been assessed for efficacy and toxicity in animals, it progresses through Phase I testing with healthy volunteers, Phase II learning trials to establish proof-of-mechanism and dose, and Phase III confirmatory trials to demonstrate efficacy and safety in larger populations. Phase III is followed by Food and Drug Administration review and, if appropriate, market access. Trial populations include cognitively normal at-risk participants in prevention trials, mildly impaired participants with biomarker evidence of AD in prodromal AD trials, and subjects with cognitive and functional impairment in AD dementia trials. Biomarkers are critical in trials of DMTs, assisting in participant characterization and diagnosis, target engagement and proof-of-pharmacology, demonstration of disease-modification, and monitoring side effects. Clinical trial designs include randomized, parallel group; delayed start; staggered withdrawal; and adaptive. Lessons learned from completed trials inform future trials and increase the likelihood of success.
Keywords: Alzheimer Disease; Animals; Clinical Trials as Topic; Humans

Co-Expression of Glia Maturation Factor and Apolipoprotein E4 in Alzheimer's Disease Brain. - Thangavel, Ramasamy; Bhagavan, Sachin M; Ramaswamy, Swathi Beladakere; Surpur, Spurthi; Govindarajan, Raghav; Kempuraj, Duraisamy; Zaheer, Smita; Raikwar, Sudhanshu; Ahmed, Mohammad E; Selvakumar, Govindhasamy Pushpavathi; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Apolipoprotein E4 (ApoE4) is a major genetic risk factor for Alzheimer's disease (AD). The E4 allele of ApoE plays a crucial role in the inflammatory and neurodegenerative processes associated with AD. This is evident from the multiple effects of the ApoE isoforms in amyloid-β (Aβ) aggregation. Glia maturation factor (GMF) is a brain-specific neuroinflammatory protein that we have previously demonstrated to be significantly upregulated in various regions of AD brains compared to non-AD control brains and that it induces neurodegeneration. We have previously reported that GMF is predominantly expressed in the reactive astrocytes surrounding amyloid plaques (APs) in AD brain. In the present study, using immunohistochemical and dual immunofluorescence staining, we show the expression and colocalization of GMF and ApoE4 in AD brains. Our results show that ApoE4 is present within the APs of AD brain. Further, we found that GMF and ApoE4 were strongly expressed and co-associated in APs and in the reactive astrocytes surrounding APs in AD. An increased expression of GMF in APs and neurofibrillary tangles in the AD brain, and the co-localization of GMF and ApoE4 in APs suggest that GMF and ApoE4 together should be contributing to the neuropathological changes associated with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Case-Control Studies; Fluorescent Antibody Technique; Glia Maturation Factor; Humans; Neurofibrillary Tangles; Plaque, Amyloid

Cognitive Training Improves Ratio Processing and Decision Making in Patients with Mild Cognitive Impairment. - Burgio, Francesca; Delazer, Margarete; Meneghello, Francesca; Pertl, Marie-Theres; Semenza, Carlo; Zamarian, Laura (J Alzheimers Dis, 2018)
BACKGROUND: Patients with mild cognitive impairment (MCI) show lower decision making and ratio processing abilities as compared to healthy peers. OBJECTIVE: To evaluate whether cognitive training on number processing and/or executive functions improves performance on ratio processing and decision making under risk. METHODS: In a controlled cross-over study, patients with MCI (n = 23; mean MMSE 26.48, SD 2.43) underwent a week of numerical training followed by a week of executive-functions training (subgroup A), or vice versa (subgroup B). Before training (T1), patients performed experimental tasks of decision making (Game of Dice Task, GDT; Probability-Associated Gambling task, PAG-60 task) and of ratio processing as well as a neuropsychological background assessment. Experimental tasks were also administered after the first (T2) and the second (T3) training week. RESULTS: The numerical training and the training of executive functions had a differential effect on experimental tasks of ratio processing. Only the numerical training proved to be effective. The effects of the two training types on decision making under risk were less clear-cut. While no changes over time were observed in the GDT, performance on the PAG-60 task improved in both training subgroups. These improvements were apparent in one subgroup after a period of executive-functions training, in the other subgroup after both training weeks. That means, improvements are not attributable to one specific training type. CONCLUSION: Patients with MCI can profit from a cognitive training on number processing and executive functions. Improvements are reflected in higher ratio processing abilities and more advantageous decisions after training. These results are consistent with assumptions of current cognitive models.

Combined Socio-Behavioral Evaluation Improves the Differential Diagnosis Between the Behavioral Variant of Frontotemporal Dementia and Alzheimer's Disease: In Search of Neuropsychological Markers. - Dodich, Alessandra; Cerami, Chiara; Cappa, Stefano F; Marcone, Alessandra; Golzi, Valeria; Zamboni, Michele; Giusti, Maria Cristina; Iannaccone, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Current diagnostic criteria for behavioral variant of frontotemporal dementia (bvFTD) and typical Alzheimer's disease (AD) include a differential pattern of neuropsychological impairments (episodic memory deficit in typical AD and dysexecutive syndrome in bvFTD). There is, however, large evidence of a frequent overlap in neuropsychological features, making the differential diagnosis extremely difficult. OBJECTIVES: In this retrospective study, we evaluated the diagnostic value of different cognitive and neurobehavioral markers in bvFTD and AD patient groups. METHODS: We included 95 dementia patients with a clinical and biomarker evidence of bvFTD (n = 48) or typical AD (n = 47) pathology. A clinical 2-year follow-up confirmed clinical classification. Performances at basic cognitive tasks (memory, executive functions, visuo-spatial, language) as well as social cognition skills and neurobehavioral profiles have been recorded. A stepwise logistic regression model compared the neuropsychological profiles between groups and assessed the accuracy of cognitive and neurobehavioral markers in discriminating bvFTD from AD. RESULTS: Statistical comparison between patient groups proved social cognition and episodic memory impairments as main cognitive signatures of bvFTD and AD neuropsychological profiles, respectively. Only half of bvFTD patients showed attentive/executive deficits, questioning their role as cognitive marker of bvFTD. Notably, the large majority of bvFTD sample (i.e., 70%) poorly performed at delayed recall tasks. Logistic regression analysis identified social cognition performances, Frontal Behavioral Inventory and Mini-Mental State Examination scores as the best combination in distinguishing bvFTD from AD. CONCLUSION: Social cognition tasks and socio-behavioral questionnaires are recommended in clinical settings to improve the accuracy of early diagnosis of bvFTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognition; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Logistic Models; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Retrospective Studies; Social Skills

Cysteine-Rich Repeat Domains 2 and 4 are Amyloid-β Binding Domains of Neurotrophin Receptor p75NTR and Potential Targets to Block Amyloid-β Neurotoxicity. - Wang, Ye-Ran; Wang, Jun; Liu, Yu-Hui; Hu, Gong-Ling; Gao, Chang-Yue; Wang, Yan-Jiang; Zhou, Xin-Fu; Zeng, Fan (J Alzheimers Dis, 2018)
The p75 neurotrophin receptor (p75NTR) is an amyloid-β (Aβ) receptor that both mediates Aβ neurotoxicity and regulates Aβ production and deposition, thus playing an important role in the pathogenesis of Alzheimer's disease (AD). The extracellular domain of p75NTR (p75ECD), consisting of four cysteine-rich repeat domains (CRDs), was recently reported to be an endogenous anti-Aβ scavenger to block p75NTR-mediated neuronal death and neurite degeneration signaling of Aβ and pro-neurotrophins. Identification of the specific Aβ binding domains of p75NTR is crucial for illuminating their interactions and the etiology of AD. CRDs of p75ECD were obtained by expression of recombinant plasmids or direct synthesis. Aβ aggregation inhibiting test and immunoprecipitation assay were applied to locate the specific binding domains of Aβ to p75ECD. The Aβ neurotoxicity antagonistic effects of different CRDs were examined by cytotoxicity experiments including neurite outgrowth assay, propidium iodide (PI) staining, and MTT assay. In the Aβ aggregation inhibiting test, the fluorescence intensity in the CRD2 and CRD4 treatment groups was significantly lower than that in the CRD1 and CRD3 treatment groups. Immunoprecipitation assay and western blot confirmed that Aβ could bind to CRD2 and CRD4. Besides, CRD2 and CRD4 antagonized Aβ neurotoxicity suggested by longer neurite length, less PI labelled cells, and higher cell viability than the control group. Our results indicate that CRD2 and CRD4 are Aβ binding domains of p75NTR and capable of antagonizing Aβ neurotoxicity, and therefore are potential therapeutic targets to block the interaction of Aβ and p75NTR in the pathogenesis of AD.

Decreased Prefrontal Activation during Matrix Reasoning in Predementia Progranulin Mutation Carriers. - Alexander, Courtney; Zeithamova, Dagmar; Hsiung, Ging-Yuek R; Mackenzie, Ian R; Jacova, Claudia (J Alzheimers Dis, 2018)
We tested the potential of task-based functional neuroimaging as a biomarker of emerging prefrontal brain changes in progranulin (GRN) mutations carriers. Five GRN mutation carriers free of frontotemporal dementia (FTD) and 11 non-carriers from families with FTD-GRN underwent functional MRI while solving matrix-reasoning problems. Mutation carriers displayed slower responses for more difficult problems and lower lateral prefrontal activation across all problems. Overall task-evoked posterior ventrolateral prefrontal activation predicted mutation status with 100% sensitivity and 91% specificity. Volumetric differences did not account for activation differences. Prefrontal activation may have utility as a biomarker in GRN mutation.
Keywords: Adult; Biomarkers; Female; Frontotemporal Dementia; Functional Neuroimaging; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Prefrontal Cortex; Progranulins

Deep Brain Stimulation of Frontal Lobe Networks to Treat Alzheimer's Disease. - Scharre, Douglas W; Weichart, Emily; Nielson, Dylan; Zhang, Jun; Agrawal, Punit; Sederberg, Per B; Knopp, Michael V; Rezai, Ali R (J Alzheimers Dis, 2018)
The study objective was to evaluate the safety and efficacy of deep brain stimulation (DBS) at the ventral capsule/ventral striatum (VC/VS) region to specifically modulate frontal lobe behavioral and cognitive networks as a novel treatment approach for Alzheimer's disease (AD) patients. This is a non-randomized phase I prospective open label interventional trial of three subjects with matched comparison groups. AD participants given DBS for at least 18 months at the VC/VS target were compared on the Clinical Dementia Rating-Sum of Boxes (CDR-SB), our primary outcome clinical measure, to matched groups without DBS from the AD Neuroimaging Initiative (ADNI) cohort. Serial 2-Deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) images of AD participants were also compared longitudinally over time. Three AD DBS participants were matched to subjects from the ADNI cohort. All participants tolerated DBS well without significant adverse events. All three AD DBS participants had less performance decline and two of them meaningfully less decline over time on our primary outcome measure, CDR-SB, relative to matched comparison groups from the ADNI using score trajectory slopes. Minimal changes or increased metabolism on FDG-PET were seen in frontal cortical regions after chronic DBS at the VC/VS target. The first use of DBS in AD at a frontal lobe behavior regulation target (VC/VS) was well-tolerated and revealed less performance decline in CDR-SB. Frontal network modulation to improve executive and behavioral deficits should be furthered studied in AD.
Keywords: Aged; Alzheimer Disease; Deep Brain Stimulation; Female; Frontal Lobe; Humans; Male; Middle Aged; Ohio; Pilot Projects; Positron-Emission Tomography; Prospective Studies

Default Mode Network Lateralization and Memory in Healthy Aging and Alzheimer's Disease. - Banks, Sarah J; Zhuang, Xiaowei; Bayram, Ece; Bird, Chris; Cordes, Dietmar; Caldwell, Jessica Z K; Cummings, Jeffrey L (J Alzheimers Dis, 2018)
Lateralization of default mode network (DMN) functioning has been shown to change with age. Similarly, lateralization of frontal lobe function has been shown to decline in age. The impact of amyloid pathology and the progression of Alzheimer's disease (AD) on resting state lateralization has not been investigated. Due to the preferential involvement of the left hemisphere in verbal tasks, there may be a benefit to higher levels of left-lateralization in the performance of verbal memory tasks. Here we compared functional lateralization of the anterior and posterior DMN between four groups of participants: amyloid negative (Aβ-) and amyloid positive (Aβ+) groups with normal cognition (NC), and Aβ+ groups with mild cognitive impairment (Aβ+MCI) or dementia (Aβ+AD). Differences were evident between groups in posterior DMN; the Aβ-NC group was more left-lateralized than both cognitively impaired Aβ+ groups. There was no difference in anterior DMN. No differences in overall network connectivity between groups were observed, suggesting that the functional lateralization finding is not secondary to general changes in connectivity. Left-lateralization of both networks was associated with better verbal recall performance. Older subjects, overall, had less left functional lateralization of the anterior DMN.

Depressive Symptoms Are Associated with Cognitive Function in the Elderly with Type 2 Diabetes. - Guerrero-Berroa, Elizabeth; Ravona-Springer, Ramit; Schmeidler, James; Heymann, Anthony; Soleimani, Laili; Sano, Mary; Leroith, Derek; Preiss, Rachel; Zukran, Ruth; Silverman, Jeremy M; Beeri, Michal Schnaider (J Alzheimers Dis, 2018)
BACKGROUND: Type 2 diabetes (T2D) is a metabolic condition associated with poor clinical and cognitive outcomes including vascular disease, depressive symptoms, cognitive impairment, and dementia. In the general elderly population, depression has been consistently identified as a risk factor for cognitive impairment/decline. However, the association between depression and cognitive function in T2D has been understudied. OBJECTIVE: We investigated the association between depression and cognitive function in a large sample of cognitively normal elderly with T2D. METHODS: In this cross-sectional study, we examined 738 participants, aged 65-88 years old, enrolled in the Israel Diabetes and Cognitive Decline study. For each cognitive domain (Episodic Memory, Executive Function, Attention/Working Memory, Language/Semantic Categorization) and Overall Cognition, multiple linear regressions assessed its association with depression (score greater than 5 on the 15-item version of the Geriatric Depression Scale [GDS]), adjusting for age, sex, and education. RESULTS: Depression (n = 66, 8.9%) was associated with worse performance on tasks of Executive Function (p = 0.004), Language/Semantic Categorization (p < 0.001), and Overall Cognition (p < 0.002), but not Episodic Memory (p = 0.643) or Attention/Working Memory (p = 0.488). Secondary analyses using GDS as a continuous variable did not substantially change the results. Adjusting also for a history of antidepressant medication use slightly weakened the findings. CONCLUSION: Significant associations of depression with several cognitive domains and Overall Cognition even in cognitively normal elderly with T2D, suggest that depression may have a role in impaired cognitive function in T2D, which may be attenuated by antidepressants.

Dipeptidyl-Peptidase Activity of Meprin β Links N-truncation of Aβ with Glutaminyl Cyclase-Catalyzed pGlu-Aβ Formation. - Schlenzig, Dagmar; Cynis, Holger; Hartlage-Rübsamen, Maike; Zeitschel, Ulrike; Menge, Katja; Fothe, Anja; Ramsbeck, Daniel; Spahn, Claudia; Wermann, Michael; Roßner, Steffen; Buchholz, Mirko; Schilling, Stephan; et al. (J Alzheimers Dis, 2018)
The formation of amyloid-β (Aβ) peptides is causally involved in the development of Alzheimer's disease (AD). A significant proportion of deposited Aβ is N-terminally truncated and modified at the N-terminus by a pGlu-residue (pGlu-Aβ). These forms show enhanced neurotoxicity compared to full-length Aβ. Although the truncation may occur by aminopeptidases after formation of Aβ, recently discovered processing pathways of amyloid-β protein precursor (AβPP) by proteases such as meprin β may also be involved. Here, we assessed a role of meprin β in forming Aβ3-40/42, which is the precursor of pGlu-Aβ3-40/42 generated by glutaminyl cyclase (QC). Similar to QC, meprin β mRNA is significantly upregulated in postmortem brain from AD patients. A histochemical analysis supports the presence of meprin β in neurons and astrocytes in the vicinity of pGlu-Aβ containing deposits. Cleavage of AβPP-derived peptides by meprin β in vitro results in peptides Aβ1-x, Aβ2-x, and Aβ3-x. The formation of N-truncated Aβ by meprin β was also corroborated in cell culture. A subset of the generated peptides was converted into pGlu-Aβ3-40 by an addition of glutaminyl cyclase, supporting the preceding formation of Aβ3-40. Further analysis of the meprin β cleavage revealed a yet unknown dipeptidyl-peptidase-like activity specific for the N-terminus of Aβ1-x. Thus, our data suggest that meprin β contributes to the formation of N-truncated Aβ by endopeptidase and exopeptidase activity to generate the substrate for QC-catalyzed pGlu-Aβ formation.

The Distribution of Urinary Alzheimer-Associated Neuronal Thread Protein and Its Association with Common Chronic Diseases in the General Population. - Jin, He; Guan, Shaochen; Wang, Rong; Fang, Xianghua; Liu, Hongjun; Wu, Yanchuan; Zhang, Yanlei; Liu, Chunxiao (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer-associated neuronal thread protein (AD7c-NTP) has been found to be a biomarker for Alzheimer's disease (AD). OBJECTIVE: The aim of the present study was to investigate the distribution of Alzheimer-associated neuronal thread protein and its relationship to common chronic diseases in the general population. METHODS: Urine samples of 1,805 participants were collected from four districts (Xi Cheng, Fang Shan, Tong Zhou, and Yan Qing) in Beijing. The assessment in this study included a questionnaire that captured participants' demographic information, use of medication and histories of disease, neurological examinations, psychometric evaluations, physical and clinical examinations, and laboratory tests. RESULTS: Urine AD7c-NTP level was increased among the population over 60 years old and females exhibited higher levels than males. These results controlled for other demographic factors such as education levels, employment status, body mass index and current residence. The urine AD7c-NTP levels exhibited no association with non-neurological diseases (0.3346±0.4482 ng/ml), such as hypertension (0.3445±0.4187), stroke (0.3652±0.4010), diabetes (0.3319±0.4371), dyslipidemia (0.3440±0.4314), renal insufficiency (0.3223±0.3909), cancer (0.5055±1.0006), chronic lung disease (0.2911±0.2852), chronic liver disease (0.5579±0.6726), severe depression symptoms (0.5186±0.7040), and mild depression symptoms (0.3669±0.3811). CONCLUSIONS: Cut-off values for urine AD7c-NTP levels for different age groups and genders should be established. AD7c-NTP levels proved relatively stable in the body and were not impacted by demographic factors or common chronic diseases.

DJ-1 Suppresses Cytoplasmic TDP-43 Aggregation in Oxidative Stress-Induced Cell Injury. - Lei, Yang; Zhang, Zhi-Feng; Lei, Rui-Xue; Wang, Shu; Zhuang, Yang; Liu, An-Chun; Wu, Yan; Chen, Juan; Tang, Jun-Chun; Pan, Meng-Xian; Liu, Rui; Liao, Wei-Jing; et al. (J Alzheimers Dis, 2018)
DJ-1 (also called PARK7) is a multifunctional redox-sensitive protein that is protective against oxidative stress-induced cell death. TAR DNA-binding protein 43 (TDP-43) is a major protein component of pathological inclusions in amyotrophic lateral sclerosis and frontotemporal dementia. Reducing aberrant aggregation of TDP-43 is a potential approach to prevent cell death. To investigate whether DJ-1 might inhibit TDP-43 aggregation to exert a protective effect in oxidative stress-induced injury, we tested the protein level and subcellular localization of TDP-43 and DJ-1 in SH-SY5Y cells transfected with wild-type DJ-1, DJ-1 mutant (L166P) cDNA, or DJ-1 siRNA. We show that oxidative stress induced by paraquat leads to the formation of cytosolic TDP-43 aggregation in SH-SY5Y cells. DJ-1 overexpression decreases paraquat-induced cytoplasmic accumulation of TDP-43 in SH-SY5Y cells and protects against paraquat-induced cell death. Transfection of DJ-1 L166P mutant or DJ-1 siRNA leads to increased cytosolic aggregation of TDP-43 in paraquat-treated SH-SY5Y cells and promotes cell death. These data suggest that DJ-1 may protect against oxidative stress-induced cell death through the suppression of cytoplasmic TDP-43 aggregation.

Does the Genetic Feature of the Chinese Tree Shrew (Tupaia belangeri chinensis) Support Its Potential as a Viable Model for Alzheimer's Disease Research? - Fan, Yu; Luo, Rongcan; Su, Ling-Yan; Xiang, Qun; Yu, Dandan; Xu, Ling; Chen, Jia-Qi; Bi, Rui; Wu, Dong-Dong; Zheng, Ping; Yao, Yong-Gang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease with increasing incidence across the world and no cure at the present time. An ideal animal model would facilitate the understanding of the pathogenesis of AD and discovery of potential therapeutic targets. The Chinese tree shrew (Tupaia belangeri chinensis) has a closer genetic affinity to primates relative to rodents, and can attain ages of 8 years or older, which represents another advantage for the study of neurodegenerative diseases such as AD compared to primates. Here, we analyzed 131 AD-related genes in the Chinese tree shrew brain tissues based on protein sequence identity, positive selection, mRNA, and protein expression by comparing with those of human, rhesus monkey, and mouse. In particular, we focused on the Aβ and neurofibrillary tangles formation pathways, which are crucial to AD pathogenesis. The Chinese tree shrew had a generally higher sequence identity with human than that of mouse versus human for the AD pathway genes. There was no apparent selection on the tree shrew lineage for the AD-related genes. Moreover, expression pattern of the Aβ and neurofibrillary tangle formation pathway genes in tree shrew brain tissues resembled that of human brain tissues, with a similar aging-dependent effect. Our results provided an essential genetic basis for future AD research using the tree shrew as a viable model.
Keywords: Alzheimer Disease; Amino Acid Sequence; Animals; Biomedical Research; Disease Models, Animal; Gene Expression Profiling; Humans; Male; Mice; Tupaia

The Down-Expression of ACE and IDE Exacerbates Exogenous Amyloid-β Neurotoxicity in CB2R-/- Mice. - Wang, Lin; Shi, Fang-Xiao; Xu, Wei-Qi; Cao, Yun; Li, Na; Li, Man; Wang, Qun; Wang, Jian-Zhi; Tian, Qing; Yu, Li-Kai; Zhou, Xin-Wen (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by neuritic plaques and neurofibrillary tangles. It is reported that enzymatic degradation of amyloid-β (Aβ) plays a pivotal role in Aβ accumulation and type-2 cannabinoid receptor (CB2R) participates in Aβ processing in the brain; however, the underlying mechanisms remain unclear. We determined that Aβ degradation-related proteins are significantly different between CB2R-/- mice and wild-type (WT) mice via proteomic analysis. Moreover, the data demonstrated that the angiotensin converting enzyme (ACE) and insulin-degrading enzyme (IDE) levels are substantially attenuated, and the Aβ level is significantly enhanced in CB2R-/--Aβ1 - 42 mice compared with that of WT-Aβ1 - 42 mice. Furthermore, Aβ-mediated synaptic dysfunction, the loss of memory associated proteins, and the suppression of glutamatergic transmission are more severe in CB2R-/--Aβ1 - 42 mice than that in WT-Aβ1 - 42 mice. CB2R activation could decrease Aβ1 - 40 and Aβ1 - 42 levels and enhance ACE and IDE levels with its selective agonist JWH133; however, AM630 (CB2R antagonist) abrogates all changes induced by JWH133 in N2a cells with AβPP overexpression. Taken together, our study demonstrated that the deletion of CB2R reduces exogenous Aβ degradation and aggravates the toxicity of Aβ via the reduction of ACE and IDE, which suggests that CB2R is involved in the onset of AD and a potential therapeutic target for AD.

Dysregulation and Dislocation of SFPQ Disturbed DNA Organization in Alzheimer's Disease and Frontotemporal Dementia. - Lu, Jing; Shu, Runzhe; Zhu, Yan (J Alzheimers Dis, 2018)
SFPQ (Splicing factor proline- and glutamine-rich) is a DNA and RNA binding protein involved in transcription, pre-mRNA splicing, and DNA damage repair. SFPQ was found dysregulated in a few tauopathies such as Alzheimer's disease (AD) and frontotemporal dementia (FTD). In addition, knock-down of SFPQ induced FTD-like behavior in mouse. To confirm the role of SFPQ in AD and FTD, we analyzed the brain sections from the AD and FTD brain samples with SFPQ upregulation and dislocation. Specifically, we observed SFPQ dislocated to the cytoplasm and nuclear envelopes, and DNA structures and organizations were associated with these dislocation phenotypes in AD and FTD brains. Consistently, we also found decreased DAPI intensities and smaller chromocenters associated with SFPQ dislocation in nerural-2a (N2a) cells. As the upregulation and hyperphosphorylation of tau protein is a hallmark of AD and FTD, our study sought to investigate potential interactions between tau and SFPQ by co-transfection and co-immunoprecipitation assays in N2a cells. SFPQ dislocation was found enhanced with tau co-transfection and tau co-transfection further resulted in extended DNA disorganization in N2a cells. Overall, our results indicate that dysregulation and dislocation of SFPQ and subsequent DNA disorganization might be a novel pathway in the progression of AD and FTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Animals; Brain; Cell Line, Tumor; DNA Damage; Female; Frontotemporal Dementia; Gene Expression Regulation; Humans; Male; Mice; PTB-Associated Splicing Factor; tau Proteins; Translocation, Genetic

Early Candidate Urine Biomarkers for Detecting Alzheimer's Disease Before Amyloid-β Plaque Deposition in an APP (swe)/PSEN1dE9 Transgenic Mouse Model. - Zhang, Fanshuang; Wei, Jing; Li, Xundou; Ma, Chao; Gao, Youhe (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is an incurable age-associated neurodegenerative disorder that is characterized by irreversible progressive cognitive deficits and extensive brain damage. The identification of candidate biomarkers before amyloid-β plaque deposition occurs is therefore of great importance for the early intervention of AD. Urine, which is not regulated by homeostatic mechanisms, theoretically accumulates changes associated with AD earlier than cerebrospinal fluid and blood. In this study, an APP (swe)/PSEN1dE9 transgenic mouse model was used to identify candidate biomarkers for early AD. Urine samples were collected from 4-, 6-, and 8-month-old transgenic mouse models, and the urinary proteomes were profiled using liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). The levels of 29 proteins differed significantly between wild type and 4-month-old mice, which had not started to accumulate amyloid-β plaques. Among these proteins, 13 have been associated with the mechanisms of AD, while 9 have been suggested as AD biomarkers. Our results indicated that urine proteins enable detection of AD before amyloid-β plaque deposition, which may present an opportunity for intervention.

Early Impairments of Hippocampal Neurogenesis in 5xFAD Mouse Model of Alzheimer's Disease Are Associated with Altered Expression of SOXB Transcription Factors. - Zaletel, Ivan; Schwirtlich, Marija; Perović, Milka; Jovanović, Mirna; Stevanović, Milena; Kanazir, Selma; Puškaš, Nela (J Alzheimers Dis, 2018)
Dysregulation of neurogenesis in the subgranular zone (SGZ) of the hippocampal dentate gyrus has been related to cognitive deficits and memory loss in neurodegenerative diseases, such as Alzheimer's disease (AD). Members of the B group of SOX transcription factors play critical roles in regulating neurogenesis in the embryonic and adult nervous system, including maintaining the multipotency, renewal, and cell fate decision of neural stem/progenitor cells. The aim of the present study was to evaluate the expression patterns of selected SOXB proteins in the SGZ, of 8-week-old male and female 5xFAD mice, which represent a transgenic model of AD with a severe and very early development of amyloid pathology. Immunohistochemical analysis showed a significant decrease in the number of cells expressing SOX1, SOX2, and SOX21 transcription factors within the SGZ of 5xFAD mice in comparison to their non-transgenic counterparts which coincidences with reduced number of doublecortin immunoreactive immature neurons found in Tg males. Despite observed changes in expressional pattern of examined SOXB proteins, the proliferative capacity evaluated by the number of Ki-67 immunoreactive cells remained unaffected in transgenic mice of both genders. Based on our results, we suggest that SOXB proteins might be considered as new biomarkers for the detection of early impairments in adult neurogenesis in different animal models or/and new targets in human regenerative medicine.

Effectiveness of a Personalized Brain-Computer Interface System for Cognitive Training in Healthy Elderly: A Randomized Controlled Trial. - Yeo, Si Ning; Lee, Tih Shih; Sng, Wei Theng; Heo, Min Quan; Bautista, Dianne; Cheung, Yin Bun; Zhang, Hai Hong; Wang, Chuanchu; Chin, Zheng Yang; Feng, Lei; Zhou, Juan; Chong, Mei Sian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive training has been demonstrated to improve cognitive performance in older adults. To date, no study has explored personalized training that targets the brain activity of each individual. OBJECTIVE: This is the first large-scale trial that examines the usefulness of personalized neurofeedback cognitive training. METHODS: We conducted a randomized-controlled trial with participants who were 60-80 years old, with Clinical Dementia Rating (CDR) score of 0-0.5, Mini-Mental State Examination (MMSE) score of 24 and above, and with no neuropsychiatric diagnosis. Participants were randomly assigned to the Intervention or Waitlist-Control group. The training system, BRAINMEM, has attention, working memory, and delayed recall game components. The intervention schedule comprised 24 sessions over eight weeks and three monthly booster sessions. The primary outcome was the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) total score after the 24-session training. RESULTS: There were no significant between-subjects differences in overall cognitive performance post-intervention. However, a sex moderation effect (p = 0.014) was present. Men in the intervention group performed better than those in the waitlist group (mean difference, +4.03 (95% CI 0.1 to 8.0), p = 0.046. Among females, however, both waitlist-control and intervention participants improved from baseline, although the between-group difference in improvement did not reach significance. BRAINMEM also received positive appraisal and intervention adherence from the participants. CONCLUSION: A personalized neurofeedback intervention is potentially feasible for use in cognitive training for older males. The sex moderation effect warrants further investigation and highlights the importance of taking sex into account during cognitive training.

Effects of Gender and Other Confounding Factors on Leptin Concentrations in Alzheimer's Disease: Evidence from the Combined Analysis of 27 Case-Control Studies. - Zhou, Futao; Chen, Shuangrong (J Alzheimers Dis, 2018)
Leptin, as a link between fat mass and the brain, has been reported to be associated with gender. The gender differences in leptin levels between Alzheimer's disease (AD) and healthy elderly controls are inconclusive so far. To quantitatively summarize the leptin data available from female and male patients with AD, we searched PubMed and EMBASE for articles published from inception to July 20, 2017. Data were extracted from 27 studies, consisting of 3,014 participants. The pooled results showed that the overall leptin levels were lower in AD (Hedges' g = -0.481; p = 0.002) than in controls, and the leptin levels in whole blood and serum were decreased with moderate and large effect sizes (g = -0.677, -0.839; respectively; both of p-values <0.001) in AD compared with controls. In blood, there were significantly lower concentrations of leptin in female AD than in female controls (g = -0.590; p = 0.014), but not in male case-control group (g = -0.666; p = 0.067). Meta-regression analysis demonstrated that the decreased extent of leptin levels in AD paralleled the degree of the severity of dementia symptoms, as well as the alterations of body mass index (p-values ≤0.002). The findings provide strong evidence that 1) the blood concentrations of leptin are lower in female AD patients than in female controls; and 2) the greater the severity of dementia symptoms, the greater the decreases in the blood leptin levels. But more future investigations on the blood leptin levels in male AD patients is warranted.

The Effects of Music Therapy on Cognition, Psychiatric Symptoms, and Activities of Daily Living in Patients with Alzheimer's Disease. - Lyu, Jihui; Zhang, Jingnan; Mu, Haiyan; Li, Wenjie; Champ, Mei; Xiong, Qian; Gao, Tian; Xie, Lijuan; Jin, Weiye; Yang, Wan; Cui, Mengnan; Gao, Maolong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most common type of dementia, affecting millions of older people worldwide. However, pharmacological therapies have not achieved desirable clinical efficacy in the past decades. Non-pharmacological therapies have been receiving increased attention to treat dementia in recent years. OBJECTIVE: This study explores the effects of music therapy on cognitive function and mental wellbeing of patients with AD. METHODS: A total number of 298 AD patients with mild, moderate, or severe dementia participated in the study. The participants with each grade of severity were randomly divided into three groups, which were a singing group, a lyric reading group, and a control group. These three groups received different interventions for three months. All participants underwent a series of tests on cognitive functions, neuropsychological symptoms, and activities of daily living at baseline, three months, and six months. RESULTS: The analysis shows that music therapy is more effective for improving verbal fluency and for alleviating the psychiatric symptoms and caregiver distress than lyrics reading in patients with AD. Stratified analysis shows that music therapy is effective for enhancing memory and language ability in patients with mild AD and reducing the psychiatric symptoms and caregiver distress in patients with moderate or severe AD. However, no significant effect was found for activities of daily living in patients with mild, moderate, or severe AD. CONCLUSION: This study suggests that music therapy is effective in enhancing cognitive function and mental wellbeing and can be recommended as an alternative approach to manage AD associated symptoms.

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

Exercise Training on Locomotion in Patients with Alzheimer's Disease: A Feasibility Study. - Pedrinolla, Anna; Venturelli, Massimo; Fonte, Cristina; Munari, Daniele; Benetti, Maria Vittoria; Rudi, Doriana; Tamburin, Stefano; Muti, Ettore; Zanolla, Luisa; Smania, Nicola; Schena, Federico (J Alzheimers Dis, 2018)
BACKGROUND: Although current literature has shown that patients with Alzheimer's disease (AD) have worse locomotion compared with healthy counterparts, no studies have focused on the efficacy of exercise training in improving gait abnormalities including biomechanics and metabolic aspects, in this population. OBJECTIVE: To verify the effectiveness of exercise training (ET) on gait parameters (i.e., speed, step and stride length, single and double support, and energy cost of walking (Cw)) in patients with AD with respect to a standard cognitive treatment (CT). METHODS: In this study, we included a small portion of data belonging to a larger study (ClinicalTrials.gov number, NCT03034746). Patients with AD (Mini-Mental State Examination 22±5) were included in the study. Gait parameters and Cw were assessed at baseline and after 6 months (72 treatment sessions) of treatment. ET included 90 min of aerobic and strength training. CT included 90 min of cognitive stimuli. RESULTS: The 16 patients assigned to ET exhibited significant improvement of Cw (-0.9±0.1 J/kg·m-1), while differences in gait parameters were negligible. The effect on gait parameters were undetectable in the 18 patients assigned to CT (-0.2±0.5 J/kg·m-1). CONCLUSIONS: Data from this study showed that ET program seems effective in improving Cw in patients with AD. Interestingly, the positive effect of ET on Cw was not coupled with ameliorations of patient's gait parameters, suggesting that the gain of metabolic aspects of locomotion were the main factors responsible for this positive result.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomechanical Phenomena; Exercise Test; Exercise Therapy; Feasibility Studies; Female; Gait; Humans; Italy; Male; Single-Blind Method

A 'Framingham-like' Algorithm for Predicting 4-Year Risk of Progression to Amnestic Mild Cognitive Impairment or Alzheimer's Disease Using Multidomain Information. - Steenland, Kyle; Zhao, Liping; John, Samantha E; Goldstein, Felicia C; Levey, Allan; Alvaro, Alonso (J Alzheimers Dis, 2018)
BACKGROUND: There are no agreed-upon variables for predicting progression from unimpaired cognition to amnestic mild cognitive impairment (aMCI), or from aMCI to Alzheimer's disease (AD). OBJECTIVE: Use ADNI data to develop a 'Framingham-like' prediction model for a 4-year period. METHODS: We developed models using the strongest baseline predictors from six domains (demographics, neuroimaging, CSF biomarkers, genetics, cognitive tests, and functional ability). We chose the best predictor from each domain, which was dichotomized into more versus less harmful. RESULTS: There were 224 unimpaired individuals and 424 aMCI subjects with baseline data on all predictors, of whom 37 (17% ) and 150 (35% ) converted to aMCI and AD, respectively, during 4 years of follow-up. For the unimpaired, CSF tau/Aβ ratio, hippocampal volume, and a memory score predicted progression. For those aMCI at baseline, the same predictors plus APOE4 status and functional ability predicted progression. Demographics and family history were not important predictors for progression for either group. The fit statistic was good for the unimpaired-aMCI model (C-statistic 0.80) and very good for the aMCI-AD model (C-statistic 0.91). Among the unimpaired, those with no harmful risk factors had a 4-year predicted 2% risk of progression, while those with the most harmful risk factors had a predicted 35% risk. The aMCI subjects with no harmful risk factors had a predicted 1% risk of progression those with all six harmful risk factors had a predicted 90% risk. CONCLUSION: Our parsimonious model accurately predicted progression from unimpaired to aMCI with three variables, and from aMCI to AD with five variables.

Frequency and Correlates of Subjective Memory Complaints in Parkinson's Disease with and without Mild Cognitive Impairment: Data from the Parkinson's Disease Cognitive Impairment Study. - Baschi, Roberta; Nicoletti, Alessandra; Restivo, Vincenzo; Recca, Deborah; Zappia, Mario; Monastero, Roberto (J Alzheimers Dis, 2018)
Subjective memory complaints (SMC) may represent the preclinical phase of mild cognitive impairment (MCI) due to Alzheimer's disease. Dementia/MCI have been described with a high prevalence in Parkinson's disease (PD), but whether SMC may predict the development of cognitive impairment has been barely explored. To evaluate the frequency and clinical correlates of isolated SMC (PD-SMC) or within the construct of MCI in subjects with PD, 147 PD patients from the PArkinson's disease COgnitive impairment Study (PACOS) were consecutively recruited for the study. This is a multicenter study involving two Movement Disorder Centers in south Italy. All subjects underwent comprehensive neuropsychological evaluation and PD-MCI was diagnosed according to Litvan's criteria. The Memory Assessment Clinics Questionnaire was used to assess SMC. Logistic regression analysis, adjusted for demographics and significant covariates, was used to evaluate clinical differences between groups. Forty-two (28.6%) individuals presented with PD without SMC and/or MCI (PDw), 40 (27,2%) with PD-SMC, 48 (32,6%) PD-SMC-MCI, and 17 (11,6%) PD-MCI without SMC (PD-MCI). When compared to PDw, PD-SMC was significantly associated with anxiety (OR = 3.93, 95% CI = 1.18-13.03), while PD-SMC-MCI related to motor progression (OR = 5.29, 95% CI = 1.12-24.86), and instrumental disability (OR = 6.98, 95% CI = 2.08-23.38). About 60% of patients showed SMC, in isolation or within the MCI frame. The role of SMC in PD seems to have a different etiology depending on the presence/absence of MCI. In particular, PD-SMC would represent a subjective reaction to the disease, while PD-SMC-MCI would depict motor progression and disability.

From Cerebrospinal Fluid to Blood: The Third Wave of Fluid Biomarkers for Alzheimer's Disease. - Zetterberg, Henrik; Blennow, Kaj (J Alzheimers Dis, 2018)
The past five years have seen an enormous development in the field of fluid biomarkers for Alzheimer's disease (AD) and related disorders. The proteins that constitute the foundation for the cerebrospinal fluid (CSF) tests for the classical AD pathologies are now being explored as potential blood-based biomarkers, thanks to the recent implementation of ultrasensitive measurement technologies in academic and clinical laboratories worldwide. The current blood-derived data are still less clear than those obtained using CSF as the sample type, but independent research suggests that there are biomarker signals in blood that relate to plaque and tangle pathologies in AD, which are relevant to explore further. Additionally, neurofilament light has emerged as the first robust blood-based biomarker for neurodegeneration in a broad range of central nervous system disorders, as well as for acute brain injuries. Here, we briefly recapitulate the first and second waves of fluid biomarker analysis in AD, i.e., the development and validation of established and novel CSF biomarkers for the disorder, followed by a focused discussion on blood-based biomarkers for AD, which we describe as the third wave of fluid biomarker analysis that hopefully will gain further momentum during the coming five years.

Gait in Mild Alzheimer's Disease: Feasibility of Multi-Center Measurement in the Clinic and Home with Body-Worn Sensors: A Pilot Study. - Mc Ardle, Ríona; Morris, Rosie; Hickey, Aodhán; Del Din, Silvia; Koychev, Ivan; Gunn, Roger N; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; et al. (J Alzheimers Dis, 2018)
Gait is emerging as a potential diagnostic tool for cognitive decline. The 'Deep and Frequent Phenotyping for Experimental Medicine in Dementia Study' (D&FP) is a multicenter feasibility study embedded in the United Kingdom Dementia Platform designed to determine participant acceptability and feasibility of extensive and repeated phenotyping to determine the optimal combination of biomarkers to detect disease progression and identify early risk of Alzheimer's disease (AD). Gait is included as a clinical biomarker. The tools to quantify gait in the clinic and home, and suitability for multi-center application have not been examined. Six centers from the National Institute for Health Research Translational Research Collaboration in Dementia initiative recruited 20 individuals with early onset AD. Participants wore a single wearable (tri-axial accelerometer) and completed both clinic-based and free-living gait assessment. A series of macro (behavioral) and micro (spatiotemporal) characteristics were derived from the resultant data using previously validated algorithms. Results indicate good participant acceptability, and potential for use of body-worn sensors in both the clinic and the home. Recommendations for future studies have been provided. Gait has been demonstrated to be a feasible and suitable measure, and future research should examine its suitability as a biomarker in AD.

GDF11 Rejuvenates Cerebrovascular Structure and Function in an Animal Model of Alzheimer's Disease. - Zhang, Wei; Guo, Yi; Li, Bo; Zhang, Qi; Liu, Jian-Hui; Gu, Guo-Jun; Wang, Jin-Hong; Bao, Rui-Kang; Chen, Yu-Jie; Xu, Jian-Rong (J Alzheimers Dis, 2018)
Cerebral amyloid angiopathy (CAA) is present in up to 90% of patients with Alzheimer's disease (AD), and may interact with classical neuropathology to exacerbate cognitive decline. Since growth differentiation factor 11 (GDF11) can activate vascular remodeling, we tested its effects on cognitive function and neuroinflammatory changes of AD model mice. We intravenously administered GDF11 or vehicle daily to 12-month-old transgenic mice overexpressing the amyloid-β protein precursor (AβPP)/PS1). Cognitive function was monitored using the Morris water maze, and after conclusion of the treatment, we assessed the morphology and presence of inflammatory markers in the cerebral vasculature. Subchronic treatment of adult AβPP/PS1 mice with GDF11 rescued cognitive function and ameliorated cerebrovascular function. In particular, the de novo genesis of small blood vessels and the expression of vascular-related proteins were significantly higher than in the vehicle-treated AβPP/PS1 mice, whereas the expressions of the inflammatory markers Iba-1 and GFAP significantly decreased in proportion to the lower ratio of two forms of amyloid-β (Aβ40/42). Daily intravenous treatment with GDF11-injection can rejuvenate respects of cognition and cerebrovascular changes in AD mice.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Behavior, Animal; Cerebral Amyloid Angiopathy; Disease Models, Animal; Growth Differentiation Factors; Maze Learning; Mice; Mice, Transgenic; Prefrontal Cortex; Presenilin-1

Ginkgo biloba Extract EGb 761 and Its Specific Components Elicit Protective Protein Clearance Through the Autophagy-Lysosomal Pathway in Tau-Transgenic Mice and Cultured Neurons. - Qin, Yiren; Zhang, Yu; Tomic, Inge; Hao, Wenlin; Menger, Michael D; Liu, Chunfeng; Fassbender, Klaus; Liu, Yang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease pathologically characterized by extracellular amyloid-β (Aβ) deposits and intracellular neurofibrillary tangles (NFT) in many brain regions. NFT are primarily composed of hyperphosphorylated tau protein (p-Tau). Aβ and p-Tau are two major pathogenic molecules with tau acting downstream to Aβ to induce neuronal degeneration. In this study, we investigated whether Ginkgo biloba extract EGb 761 reduces cerebral p-Tau level and prevents AD pathogenesis. Human P301S tau mutant-transgenic mice were fed with EGb 761, added to the regular diet for 2 or 5 months. We observed that treatment with EGb 761 for 5 months significantly improved the cognitive function of mice, attenuated the loss of synaptophysin and recovered the phosphorylation of CREB in the mouse brain. Treatment with EGb 761 for 5 but not 2 months also decreased p-Tau protein amount and shifted microglial pro-inflammatory to anti-inflammatory activation in the brain. As potential therapeutic mechanisms, we demonstrated that treatment with EGb 761, especially the components of ginkgolide A, bilobalide, and flavonoids, but not with purified ginkgolide B or C, increased autophagic activity and degradation of p-Tau in lysosomes of neurons. Inhibiting ATG5 function or treating cells with Bafilomycin B1 abolished EGb 761-enhanced degradation of p-Tau in cultured neurons. Additionally, we observed that 5- instead of 2-month-treatment with EGb 761 inhibited the activity of p38-MAPK and GSK-3β. Therefore, long-term treatment with Ginkgo biloba extract EGb 761, a clinically available and well-tolerated herbal medication, ameliorates AD pathology through mechanisms against multiple AD pathogenic processes.

Glia Maturation Factor and Mast Cell-Dependent Expression of Inflammatory Mediators and Proteinase Activated Receptor-2 in Neuroinflammation. - Kempuraj, Duraisamy; Selvakumar, Govindhasamy Pushpavathi; Thangavel, Ramasamy; Ahmed, Mohammad Ejaz; Zaheer, Smita; Kumar, Keerthana Kuppamma; Yelam, Anudeep; Kaur, Harleen; Dubova, Iuliia; Raikwar, Sudhanshu P; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Parkinson's disease (PD) is characterized by the presence of inflammation-mediated dopaminergic neurodegeneration in the substantia nigra. Inflammatory mediators from activated microglia, astrocytes, neurons, T-cells and mast cells mediate neuroinflammation and neurodegeneration. Administration of neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induces PD like motor deficits in rodents. 1-methyl-4-phenylpyridinium (MPP+), a toxic metabolite of MPTP activates glial cells, neurons and mast cells to release neuroinflammatory mediators. Glia maturation factor (GMF), mast cells and proteinase activated receptor-2 (PAR-2) are implicated in neuroinflammation. Alpha-synuclein which induces neurodegeneration increases PAR-2 expression in the brain. However, the exact mechanisms are not yet understood. In this study, we quantified inflammatory mediators in the brains of MPTP-administered wild type (Wt), GMF-knockout (GMF-KO), and mast cell knockout (MC-KO) mice. Additionally, we analyzed the effect of MPP+, GMF, and mast cell proteases on PAR-2 expression in astrocytes and neurons in vitro. Results show that the levels of interleukin-1beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and the chemokine (C-C motif) ligand 2 (CCL2) were lesser in the brains of GMF-KO mice and MC-KO mice when compared to Wt mice brain after MPTP administration. Incubation of astrocytes and neurons with MPP+, GMF, and mouse mast cell protease-6 (MMCP-6) and MMCP-7 increased the expression of PAR-2. Our studies show that the absence of mast cells and GMF reduce the expression of neuroinflammatory mediators in the brain. We conclude that GMF along with mast cell interactions with glial cells and neurons during neuroinflammation can be explored as a new therapeutic target for PD and other neuroinflammatory disorders.

Glucagon-Like Peptide-2 Receptor is Involved in Spatial Cognitive Dysfunction in Rats After Chronic Cerebral Hypoperfusion. - Xie, Yan-Chun; Yao, Zhao-Hui; Yao, Xiao-Li; Pan, Jian-Zhen; Zhang, Shao-Feng; Zhang, Yong; Hu, Ji-Chang (J Alzheimers Dis, 2018)
Chronic cerebral hypoperfusion (CCH) affects the aging population and especially patients with neurodegenerative diseases, such as Alzheimer's disease or Parkinson's disease. CCH is closely related to the cognitive dysfunction in these diseases. Glucagon-like peptide-2 receptor (GLP2R) mRNA and protein are highly expressed in the gut and in hippocampal neurons. This receptor is involved in the regulation of food intake and the control of energy balance and glucose homeostasis. The present study employed behavioral techniques, electrophysiology, western blotting, immunohistochemistry, quantitative real time polymerase chain reaction (qRT-PCR), and Golgi staining to investigate whether the expression of GLP2R changes after CCH and whether GLP2R is involved in cognitive impairment caused by CCH. Our findings show that CCH significantly decreased hippocampal GLP2R mRNA and protein levels. GLP2R upregulation could prevent CCH-induced cognitive impairment. It also improved the CCH-induced impairment of long-term potentiation and long-term depression. Additionally, GLP2R modulated after CCH the AKT-mTOR-p70S6K pathway in the hippocampus. Moreover, an upregulation of the GLP2R increased the neurogenesis in the dentate gyrus, neuronal activity, and density of dendritic spines and mushroom spines in hippocampal neurons. Our findings reveal the involvement of GLP2R via a modulation of the AKT-mTOR-p70S6K pathway in the mechanisms underlying CCH-induced impairments of spatial learning and memory. We suggest that the GLP2R and the AKT-mTOR-p70S6K pathway in the hippocampus are promising targets to treat cognition deficits in CCH.

Gut Microbiome is Altered in Patients with Alzheimer's Disease. - Zhuang, Zhen-Qian; Shen, Lin-Lin; Li, Wei-Wei; Fu, Xue; Zeng, Fan; Gui, Li; Lü, Yang; Cai, Min; Zhu, Chi; Tan, Yin-Ling; Zheng, Peng; Li, Hui-Yun; et al. (J Alzheimers Dis, 2018)
Previous studies suggest that gut microbiota is associated with neuropsychiatric disorders, such as Parkinson's disease, amyotrophic lateral sclerosis, and depression. However, whether the composition and diversity of gut microbiota is altered in patients with Alzheimer's disease (AD) remain largely unknown. In the present study, we collected fecal samples from 43 AD patients and 43 age- and gender-matched cognitively normal controls. 16S ribosomal RNA sequencing technique was used to analyze the microbiota composition in feces. The composition of gut microbiota was different between the two groups. Several bacteria taxa in AD patients were different from those in controls at taxonomic levels, such as Bacteroides, Actinobacteria, Ruminococcus, Lachnospiraceae, and Selenomonadales. Our findings suggest that gut microbiota is altered in AD patients and may be involved in the pathogenesis of AD.

The GWAS Risk Genes for Depression May Be Actively Involved in Alzheimer's Disease. - Ni, Hua; Xu, Min; Zhan, Gui-Lai; Fan, Yu; Zhou, Hejiang; Jiang, Hong-Yan; Lu, Wei-Hong; Tan, Liwen; Zhang, Deng-Feng; Yao, Yong-Gang; Zhang, Chen (J Alzheimers Dis, 2018)
Depression is one of the most frequent psychiatric symptoms observed in people during the development of Alzheimer's disease (AD). We hypothesized that genetic factors conferring risk of depression might affect AD development. In this study, we screened 31 genes, which were located in 19 risk loci for major depressive disorder (MDD) identified by two recent large genome-wide association studies (GWAS), in AD patients at the genomic and transcriptomic levels. Association analysis of common variants was performed by using summary statistics of the International Genomics of Alzheimer's Project (IGAP), and association analysis of rare variants was conducted by sequencing the entire coding region of the 31 MDD risk genes in 107 Han Chinese patients with early-onset and/or familial AD. We also quantified the mRNA expression alterations of these MDD risk genes in brain tissues of AD patients and AD mouse models, followed by protein-protein interaction network prediction to show their potential effects in AD pathways. We found that common and rare variants of L3MBTL2 were significantly associated with AD. mRNA expression levels of 18 MDD risk genes, in particular SORCS3 and OAT, were differentially expressed in AD brain tissues. 13 MDD risk genes were predicted to physically interact with core AD genes. The involvement of HACE1, NEGR1, and SLC6A15 in AD was supported by convergent lines of evidence. Taken together, our results showed that MDD risk genes might play an active role in AD pathology and supported the notion that depression might be the "common cold" of psychiatry.

Harpagoside Rescues the Memory Impairments in Chronic Cerebral Hypoperfusion Rats by Inhibiting PTEN Activity. - Chen, Chen; Zhang, Haifeng; Xu, Hongliang; Xue, Rui; Zheng, Yake; Wu, Tianwen; Lian, Yajun (J Alzheimers Dis, 2018)
Vascular dementia (VaD) is the second most common dementia worldwide. Unlike Alzheimer's disease, VaD does not yet have effective therapeutic drugs. Harpagoside is the most important component extracted from Harpagophytum procumbens, a traditional Chinese medicine that has been widely used. The neuroprotective effects of harpagoside have been studied in Aβ- and MPTP-induced neurotoxicity. However, whether harpagoside is protective against VaD is not clear. In this study, with the use of chronic cerebral hypoperfusion rats, a well-known VaD model, we demonstrated that chronic administration (two months) of harpagoside was able to restore both the spatial learning/memory and fear memory impairments. Importantly, the protective effects of harpagoside were not due to alterations in the physiological conditions, metabolic parameters, or locomotor abilities of the rats. Meanwhile, we found that harpagoside suppressed the overactivation of PTEN induced by CCH by enhancing PTEN phosphorylation. Furthermore, harpagoside elevated the activity of Akt and inhibited the activity of GSK-3β, downstream effectors of PTEN. Overall, our study suggested that harpagoside treatment might be a potential therapeutic drug targeting the cognitive impairments of VaD.

Heme Oxygenase 1 Induces Tau Oligomer Formation and Synapse Aberrations in Hippocampal Neurons. - Si, Zizhen; Wang, Xidi; Zhang, Zhujun; Wang, Jinxin; Li, Jihong; Li, Jing; Li, Ling; Li, Yuanxin; Peng, Yahui; Sun, Chongran; Hui, Yang; Gao, Xu (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by behavioral changes and cognitive decline. Recent evidence suggests that it is the soluble forms of tau oligomers (Tau-O) and Aβ oligomers (oAβ) rather than the well-studied insoluble protein aggregates that possess the neurotoxicity, infectivity, and amplification underlying disease progression. Heme oxygenase 1 (HO-1), an inducible enzyme upregulated in the cortex and hippocampus of AD brains, was reported to damage neural structures and disrupt brain function, suggesting possible contributions to Tau-O-mediated neurodegeneration. In this study, we focused on the effects of HO-1 on Tau-O formation. In hippocampus of HO-1-overexpressing transgenic mice and neural 2a (N2a) cells, Tau-O was co-localized with HO-1 as visualized by immunofluorescence staining. Furthermore, primary cultured hippocampal neurons from HO-1 transgenic mice showed elevated Tau-O and concomitant reductions in spine density and length as well as dendritic length, diameter, and arborization. Blocking Tau-O formation by isoprenaline reversed these HO-1-induced morphological changes. These results indicated that HO-1 contributes to Tau-O formation and ensuing synaptic damage. Thus, HO-1 is a promising target for AD drug development.

The Heritability of Frontotemporal Lobar Degeneration: Validation of Pedigree Classification Criteria in a Northern Italy Cohort. - Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Zanetti, Orazio; Binetti, Giuliano; Ghidoni, Roberta; Benussi, Luisa (J Alzheimers Dis, 2018)
A large portion of frontotemporal lobar degeneration (FTLD) patients has a family history of disease and the presence of a pathogenic mutation confirms the clinical diagnosis. Recently, standardized criteria to evaluate FTLD pedigree, based on first- and second-degree affected relatives, their age at onset, and clinical phenotype, were proposed and validated in an American cohort. Herein we applied these criteria to 402 Italian FTLD pedigrees and assessed mutation frequencies in GRN, C9orf72, and MAPT genes with the aim of validating these criteria. Moreover, we evaluated whether genetic counseling requests reflect the estimated family risk. 12.4% of pedigrees had high family history, 6.5% medium, 15.4% low; 39% were apparent sporadic cases and 26.6% had family history of unknown significance. Mutations frequencies were in line with the categorization proposed: the highest rate was found in the most at-risk families (74%) and decreased in other categories (medium: 15.4%; low: 9.7%; sporadic: 1.3%). Mutation carriers with unknown family history (5.6%) were mostly early-onset patients. Detected mutation frequency was comparable with the US-cohort (13.7%), but mutations distribution among genes was different, with higher frequency of GRN mutations (9.4%) in our cohort. An elevated proportion of FTLD patients belonging to "high risk" pedigrees asked for genetic counseling (42%); requests decreased according to the estimated family risk (medium: 26.9%; low: 17.7%; sporadic: 5.1%). In conclusion, the proposed pedigree classification criteria, herein further validated, should be incorporated in the FTLD diagnostic work-up. Moreover, our data suggest to extend genetic screening to early-onset patients with unknown family history.
Keywords: Age of Onset; Aged; C9orf72 Protein; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Middle Aged; Mutation; Pedigree; Progranulins; tau Proteins

High Caregiver Burden in Young Onset Dementia: What Factors Need Attention? - Lim, Linda; Zhang, Angeline; Lim, Levinia; Choong, Tanya-Marie; Silva, Eveline; Ng, Adeline; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
BACKGROUND: There is an increase in prevalence of young onset dementia (YOD). The specific problems among YOD patients and levels of caregiver burden (CB) in this group warrants further evaluation. OBJECTIVE: To evaluate and compare level of CB in YOD and late onset dementia (LOD). Also, we sought to understand the specific factors, such as neuropsychiatric symptoms, that may affect the levels of caregiver burden in the YOD group. METHODS: Patient-caregiver dyads with YOD and LOD were recruited from a tertiary neurology center. Levels of CB between YOD and LOD were compared among 183 patient-caregiver dyads. CB was quantified using the Zarit Burden Inventory (ZBI). Neuropsychological evaluations as well as the Neuropsychiatric Inventory were performed. Factors that influenced level of CB in YOD group was investigated with regression analyses. RESULTS: There were 57 YOD and 126 LOD dyads. Caregivers of YOD subjects reported significantly higher levels of burden compared to caregivers of LOD subjects (ZBI: 17.3 versus 13.94; p = 0.015). 52.6% of YOD caregivers reported a high caregiver burden. When compared to caregivers of LOD, the odds of a caregiver of YOD reporting high caregiver burden was 2.34 (95% CI: 1.22-4.49: p = 0.010). YOD dyads with a high caregiver burden had significantly higher neuropsychiatric inventory scores. Risk factors for high caregiver burden in YOD included family history of dementia and behavioral symptoms including disinhibited behavior, delusions, and apathy. CONCLUSION: Targeted support for caregivers of patients with YOD is needed to address the higher CB in this group.
Keywords: Adaptation, Psychological; Age of Onset; Aged; Aged, 80 and over; Behavioral Symptoms; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Stress, Psychological; Surveys and Questionnaires

The Impact of Hospitalization on Readmission, Institutionalization, and Mortality of People with Dementia: A Systematic Review and Meta-Analysis. - Lehmann, Jana; Michalowsky, Bernhard; Kaczynski, Anika; Thyrian, Jochen René; Schenk, Nele Sophie; Esser, Alexander; Zwingmann, Ina; Hoffmann, Wolfgang (J Alzheimers Dis, 2018)
BACKGROUND: People with dementia (PwD) are at a high risk of hospitalization. Hospitals are often not adequately equipped for PwD and discharges often come unexpected. Therefore, PwD are at a risk of adverse outcomes. However, information about those outcomes is rare but crucial for the development of preventive strategies. OBJECTIVES: To conduct a quantitative systematic review and meta-analyses on the impact of a hospitalization on readmission, institutionalization, and mortality in PwD. To identify factors associated with these outcomes. METHODS: PubMed, CENTRAL, and ScienceDirect were searched for studies including terms for dementia, hospital, readmission, institutionalization, and mortality. Relevant were assessed by a quality criteria sheet. Results were summarized in a table. Meta-analysis was conducted with Review Manager 5.3. RESULTS: The search yielded 1,108 studies; 20 fulfilled the inclusion criteria and 10 studies were eligible for meta-analyses. The incidence and relative risk (RR) of mortality (RR 1.74 CI95 % 1.50, 2.05) and institutionalization (RR: 2.16 CI95 % 1.31, 3.56) of PwD was significantly higher when compared to people without dementia. Results according to readmission rate were inconsistent. Factors significantly associated with the examined adverse outcomes were severity of dementia, number of medications, and deficits in daily living activities. CONCLUSION: Hospitalization of PwD lead to adverse outcomes. An improvement in the identification of and care for PwD in the acute setting as well as in after care in the community setting, especially in the interface between both settings, is required to prevent adverse outcomes in hospitalized PwD.

Impact of Untimely Access to Formal Care on Costs and Quality of Life in Community Dwelling People with Dementia. - Janssen, Niels; Handels, Ron L; Sköldunger, Anders; Woods, Bob; Jelley, Hannah; Edwards, Rhiannon Tudor; Orrell, Martin; Selbæk, Geir; Røsvik, Janne; Gonçalves-Pereira, Manuel; Marques, Maria J; Zanetti, Orazio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Access to formal care is not always timely and a better understanding on the impact of untimely access is needed. OBJECTIVE: To examine, from a societal perspective, the impact of untimely access to formal care in terms of total costs and quality of life over one year in community dwelling people with dementia. METHODS: Within the Actifcare study, needs, resource use, and quality of life were observed for one year in a cohort of 451 community dwelling people with dementia in 8 European countries. Untimely access to care was operationalized as having at least one unmet need for care identified by the Camberwell Assessment of Need for the Elderly (CANE) instrument. Two regression models were built for both total costs and quality of life measured by the EQ-5D-5L, one using sum of unmet needs and one using a predefined selection of need items. RESULTS: Unmet needs were not associated with higher total costs but they were associated with a lower quality of life of people with dementia. Of all CANE items, only an unmet need for "company" was significantly related to lower total costs. CONCLUSION: Total costs did not seem to differ between participants with unmet and met needs. Only few associations between specific unmet needs and costs and quality of life were found. Furthermore, quality of life of people with dementia decreases when multiple unmet needs are experienced, indicating that assessing and meeting needs is important to improve quality of life.

In Vitro Potency and Preclinical Pharmacokinetic Comparison of All-D-Enantiomeric Peptides Developed for the Treatment of Alzheimer's Disease. - Schartmann, Elena; Schemmert, Sarah; Niemietz, Nicole; Honold, Dominik; Ziehm, Tamar; Tusche, Markus; Elfgen, Anne; Gering, Ian; Brener, Oleksandr; Shah, Nadim Joni; Langen, Karl-Josef; Kutzsche, Janine; et al. (J Alzheimers Dis, 2018)
Diffusible amyloid-β (Aβ) oligomers are currently presumed to be the most cytotoxic Aβ assembly and held responsible to trigger the pathogenesis of Alzheimer's disease (AD). Thus, Aβ oligomers are a prominent target in AD drug development. Previously, we reported on our solely D-enantiomeric peptide D3 and its derivatives as AD drug candidates. Here, we compare one of the most promising D3 derivatives, ANK6, with its tandem version (tANK6), and its head-to-tail cyclized isoform (cANK6r). In vitro tests investigating the D-peptides' potencies to inhibit Aβ aggregation, eliminate Aβ oligomers, and reduce Aβ-induced cytotoxicity revealed that all three D-peptides efficiently target Aβ. Subsequent preclinical pharmacokinetic studies of the three all-D-peptides in wildtype mice showed promising blood-brain barrier permeability with cANK6r yielding the highest levels in brain. The peptides' potencies to lower Aβ toxicity and their remarkable brain/plasma ratios make them promising AD drug candidates.

In Vivo Visualization of Tau Accumulation, Microglial Activation, and Brain Atrophy in a Mouse Model of Tauopathy rTg4510. - Ishikawa, Ai; Tokunaga, Masaki; Maeda, Jun; Minamihisamatsu, Takeharu; Shimojo, Masafumi; Takuwa, Hiroyuki; Ono, Maiko; Ni, Ruiqing; Hirano, Shigeki; Kuwabara, Satoshi; Ji, Bin; Zhang, Ming-Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Tau imaging using PET is a promising tool for the diagnosis and evaluation of tau-related neurodegenerative disorders, but the relationship among PET-detectable tau, neuroinflammation, and neurodegeneration is not yet fully understood. OBJECTIVE: We aimed to elucidate sequential changes in tau accumulation, neuroinflammation, and brain atrophy by PET and MRI in a tauopathy mouse model. METHODS: rTg4510 transgenic (tg) mice expressing P301L mutated tau and non-tg mice were examined with brain MRI and PET imaging (analyzed numbers: tg = 17, non-tg = 13; age 2.5∼14 months). As PET probes, [11C]PBB3 (Pyridinyl-Butadienyl-Benzothiazole 3) and [11C]AC-5216 were used to visualize tau pathology and 18-kDa translocator protein (TSPO) neuroinflammation. Tau pathology and microglia activation were subsequently analyzed by histochemistry. RESULTS: PET studies revealed age-dependent increases in [11C]PBB3 and [11C]AC-5216 signals, which were correlated with age-dependent volume reduction in the forebrain on MRI. However, the increase in [11C]PBB3 signals reached a plateau at age 7 months, and therefore its significant correlation with [11C]AC-5216 disappeared after age 7 months. In contrast, [11C]AC-5216 showed a strong correlation with both age and volume reduction until age 14 months. Histochemical analyses confirmed the relevance of pathological tau accumulation and elevated TSPO immunoreactivity in putative microglia. CONCLUSION: Our results showed that tau accumulation is associated with neuroinflammation and brain atrophy in a tauopathy mouse model. The time-course of the [11C]PBB3- and TSPO-PET finding suggests that tau deposition triggers progressive neuroinflammation, and the sequential changes can be evaluated in vivo in mouse brains.
Keywords: Animals; Atrophy; Benzothiazoles; Brain; Disease Models, Animal; Female; Magnetic Resonance Imaging; Male; Mice; Mice, Transgenic; Microglia; Positron-Emission Tomography; Receptors, GABA; tau Proteins; Tauopathies

Increased Serum Acylated Ghrelin Levels in Patients with Mild Cognitive Impairment. - Cao, Xi; Zhu, Min; He, Yan; Chu, Wenzheng; Du, Yifeng; Du, Heng (J Alzheimers Dis, 2018)
Ghrelin is a stomach-derived circulating hormone. In addition to its function as an orexigenic stimulant, the role of ghrelin in the consolidation of learning and memory has been implicated in recent years. However, the status of circulating acylated ghrelin (AG, that is, the functional form of ghrelin) in the symptomatic predementia stage of Alzheimer's disease (AD) has rarely been investigated. In the current study, we examined the serum levels of acylated and total ghrelin in 22 patients with mild cognitive impairment (MCI) and 30 cognitively normal controls. We have found that patients with MCI had significantly increased serum AG levels, which were inversely associated with defected short- and long-term memory as well as language skills. Of note, the levels of total circulating ghrelin were similar between the two groups. Intriguingly, serum AG but not total ghrelin was associated with AD risk factors including the age, hypertension, and hyperlipidemia. Therefore, circulating AG may serve as a potential early systemic biomarker for AD-related cognitive impairments. Nevertheless, the simplest interpretation of the results is that the levels of circulating AG are associated with cognitive impairments in patients with MCI, thereby forming the groundwork for our future studies on the systemic mechanisms of AD pertaining to the ghrelin system.
Keywords: Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Female; Ghrelin; Humans; Male; Middle Aged; Risk Factors

Increasing Diagnostic Accuracy of Mild Cognitive Impairment due to Alzheimer's Disease by User-Independent, Web-Based Whole-Brain Volumetry. - Hedderich, Dennis M; Spiro, Judith E; Goldhardt, Oliver; Kaesmacher, Johannes; Wiestler, Benedikt; Yakushev, Igor; Zimmer, Claus; Boeckh-Behrens, Tobias; Grimmer, Timo (J Alzheimers Dis, 2018)
BACKGROUND: Volumetric quantification of structural MRI has been shown to increase the diagnostic accuracy of patients with mild cognitive impairment (MCI); however, its implementation in clinical routine is usually technically difficult and time-consuming. OBJECTIVE: The purpose of this study was to investigate whether volumetric information obtained from the free and easy-to-use online tool volBrain can improve correct identification of MCI patients with Alzheimer's disease (AD) compared to visual reading. METHODS: The study cohort consisted of 27 patients with MCI due to AD (AD positive) as determined by biomarker information and 26 cognitively normal controls (CN). Three blinded readers, 2 radiologists and 1 clinical dementia expert, assessed the patients' MRI regarding brain atrophy and probability of underlying AD two times, without and with supporting volumetric information from volBrain. To assess diagnostic accuracy of volBrain measures alone, a simple sum score based on basic volumetric measures was developed and tested. RESULTS: Correct patient classification by readers 1, 2, and 3 without a volumetric report was 73.6%, 77.4%, and 83.0%. With a volumetric report, correct classification increased for the radiological readers to 77.4% and 81.1%, respectively and decreased to 77.4% for reader 3. Usage of the volumetric report alone yielded the highest diagnostic accuracy of 84.9%. Diagnostic confidence increased significantly for radiological readers. CONCLUSION: Volumetric information from volBrain increases the radiologist's diagnostic performance and confidence in identifying MCI patients with AD. We propose that such tools may be implemented in the routine diagnostic work-up of patients with suspected AD.

Induction of Amyloid-β42 Production by Fipronil and Other Pyrazole Insecticides. - Cam, Morgane; Durieu, Emilie; Bodin, Marion; Manousopoulou, Antigoni; Koslowski, Svenja; Vasylieva, Natalia; Barnych, Bogdan; Hammock, Bruce D; Bohl, Bettina; Koch, Philipp; Omori, Chiori; Yamamoto, Kazuo; et al. (J Alzheimers Dis, 2018)
Generation of amyloid-β peptides (Aβs) by proteolytic cleavage of the amyloid-β protein precursor (AβPP), especially increased production of Aβ42/Aβ43 over Aβ40, and their aggregation as oligomers and plaques, represent a characteristic feature of Alzheimer's disease (AD). In familial AD (FAD), altered Aβ production originates from specific mutations of AβPP or presenilins 1/2 (PS1/PS2), the catalytic subunits of γ-secretase. In sporadic AD, the origin of altered production of Aβs remains unknown. We hypothesize that the 'human chemical exposome' contains products able to favor the production of Aβ42/Aβ43 over Aβ40 and shorter Aβs. To detect such products, we screened a library of 3500 + compounds in a cell-based assay for enhanced Aβ42/Aβ43 production. Nine pyrazole insecticides were found to induce a β- and γ-secretase-dependent, 3-10-fold increase in the production of extracellular Aβ42 in various cell lines and neurons differentiated from induced pluripotent stem cells derived from healthy and FAD patients. Immunoprecipitation/mass spectrometry analyses showed increased production of Aβs cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and shorter. Strongly supporting a direct effect on γ-secretase activity, pyrazoles shifted the cleavage pattern of another γ-secretase substrate, alcadeinα, and shifted the cleavage of AβPP by highly purified γ-secretase toward Aβ42/Aβ43. Focusing on fipronil, we showed that some of its metabolites, in particular the persistent fipronil sulfone, also favor the production of Aβ42/Aβ43 in both cell-based and cell-free systems. Fipronil administered orally to mice and rats is known to be metabolized rapidly, mostly to fipronil sulfone, which stably accumulates in adipose tissue and brain. In conclusion, several widely used pyrazole insecticides enhance the production of toxic, aggregation prone Aβ42/Aβ43 peptides, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in sporadic AD.

Inflammatory Cytokine, IL-1β, Regulates Glial Glutamate Transporter via microRNA-181a in vitro. - Zumkehr, Joannee; Rodriguez-Ortiz, Carlos J; Medeiros, Rodrigo; Kitazawa, Masashi (J Alzheimers Dis, 2018)
Glutamate overload triggers synaptic and neuronal loss that potentially contributes to neurodegenerative diseases including Alzheimer's disease (AD). Glutamate clearance and regulation at synaptic clefts is primarily mediated by glial glutamate transporter 1 (GLT-1). We determined that inflammatory cytokines significantly upregulated GLT-1 through microRNA-181a-mediated post-transcriptional modifications. Unveiling the key underlying mechanisms modulating GLT-1 helps better understand its physiological and pathological interactions with cytokines. Primary murine astrocyte and neuron co-culture received 20 ng/mL IL-1β, TNF-α, or IL-6 for 48 h. Soluble proteins or total RNA were extracted after treatment for further analyses. Treatment with inflammatory cytokines, IL-1β and TNF-α, but not IL-6, significantly increased GLT-1 steady-state levels (p≤0.05) without affecting mRNA levels, suggesting the cytokine-induced GLT-1 was regulated through post-transcriptional modifications. Among the candidate microRNAs predicted to modulate GLT-1, only microRNA-181a was significantly decreased following the IL-1β treatment (p≤0.05). Co-treatment of microRNA-181a mimic in IL-1β-treated primary astrocytes and neurons effectively blocked the IL-1β-induced upregulation of GLT-1. Lastly, we attempted to determine the link between GLT-1 and microRNA-181a in human AD brains. A significant reduction of GLT-1 was found in AD hippocampus tissues, and the ratio of mature microRNA-181a over primary microRNA-181a had an increasing tendency in AD. MicroRNA-181a controls rapid modifications of GLT-1 levels in astrocytes. Cytokine-induced inhibition of microRNA-181a and subsequent upregulation of GLT-1 may have physiological implications in synaptic plasticity while aberrant maturation of microRNA-181a may be involved in pathological consequences in AD.

Inhibition of Histone Acetylation by ANP32A Induces Memory Deficits. - Chai, Gao-Shang; Feng, Qiong; Ma, Rong-Hong; Qian, Xiao-Hang; Luo, Dan-Ju; Wang, Zhi-Hao; Hu, Yu; Sun, Dong-Sheng; Zhang, Jun-Fei; Li, Xiao; Li, Xiao-Guang; Ke, Dan; et al. (J Alzheimers Dis, 2018)
There is accumulating evidence that decreased histone acetylation is involved in normal aging and neurodegenerative diseases. Recently, we found that ANP32A, a key component of INHAT (inhibitor of acetyltransferases) that suppresses histone acetylation, increased in aged and cognitively impaired C57 mice and expressing wild-type human full length tau (htau) transgenic mice. Downregulating ANP32A restored cognitive function and synaptic plasticity through upregulation of the expressions of synaptic-related proteins via increasing histone acetylation. However, there is no direct evidence that ANP32A can induce neurodegeneration and memory deficits. In the present study, we overexpressed ANP32A in the hippocampal CA3 region of C57 mice and found that ANP32A overexpression induced cognitive abilities and synaptic plasticity deficits, with decreased synaptic-related protein expression and histone acetylation. Combined with our recent studies, our findings reveal that upregulated ANP32A induced-suppressing histone acetylation may underlie the cognitive decline in neurodegenerative disease, and suppression of ANP32A may represent a promising therapeutic approach for neurodegenerative diseases including Alzheimer's disease.

Interactive Effect of Depression and Cognitive Impairment on Olfactory Identification in Elderly People. - Chen, Ben; Zhong, Xiaomei; Mai, Naikeng; Peng, Qi; Zhang, Min; Chen, Xinru; Wu, Zhangying; Zou, Laiquan; Liang, Wanyuan; Ouyang, Cong; Wu, Yujie; Ning, Yuping (J Alzheimers Dis, 2018)
Olfactory identification (OI) deficits have been regarded as an indicator of cognitive impairment in the elderly, but few studies have analyzed the mixed effect of depression on OI. Since depression is common in the elderly and strongly associated with OI, we aimed to explore whether the comorbidity of depression and cognitive impairment may be associated with worse outcomes. In total, 153 elderly patients with depression and 154 normal elderly were recruited. Subjects underwent assessments of depression, cognitive function, and OI. Information on the factors that may affect OI performance was collected (age, sex, smoking history, diabetes, etc.). Correlation analysis showed that several factors had a significant influence on OI performance in the elderly, including severity of depression, cognitive scores, age, sex, and years of education (p < 0.05). Among the different cognitive domains, OI was positively associated with global cognition, memory, language, executive function, and attention performance (p < 0.05). The multiple linear regression analysis indicated that memory scores, age, HAMD scores, and sex were the most relevant factors to OI scores across all elderly participants. The factorial analysis suggested that elderly with comorbidity of depression and cognitive impairment (memory deficits or language deficits) had worse OI impairment, and there was an interactive effect of depression and memory deficits on OI in elderly people. The present study suggested that the coexistence of depressive symptoms and cognitive impairment was associated with worse OI in the elderly. Studies exploring the association between OI and cognitive function should include an assessment of depression and adjust the interactive effects of depression.

Involvement of Activation of Asparaginyl Endopeptidase in Tau Hyperphosphorylation in Repetitive Mild Traumatic Brain Injury. - Hu, Wen; Tung, Yunn Chyn; Zhang, Yanchong; Liu, Fei; Iqbal, Khalid (J Alzheimers Dis, 2018)
Traumatic brain injury (TBI) is an established risk factor for the development of neurodegeneration and dementia late in life. Repetitive mild TBI (r-mTBI) is directly associated with chronic traumatic encephalopathy (CTE), a progressive neurodegenerative disorder characterized by focal perivascular to widespread Alzheimer-type neurofibrillary pathology of hyperphosphorylated tau. Studies in animal models have shown hyperphosphorylation of tau after TBI. However, the molecular mechanisms by which TBI leads to tau pathology are not understood. In this study, we employed western blots and immunohistochemistry to test, in triple-transgenic mouse model of Alzheimer's disease (3xTg-AD), the effect of r-mTBI on tau hyperphosphorylation and activation of asparaginyl endopeptidase (AEP), a cysteine proteinase which is known to be involved in tau hyperphosphorylation. We found that the level of active AEP was increased and correlated with the level of tau hyperphosphorylation following r-mTBI, and that fimbria showed increased immunoreactivity to phospho-tau. In addition, inhibitor 2 of protein phosphatase 2A (I2PP2A) was translocated from neuronal nucleus to the cytoplasm and colocalized with hyperphosphorylated tau. These data suggest the involvement of AEP-I2PP2A-PP2A-ptau pathway in tau pathology in TBI.

Kainic Acid Impairs the Memory Behavior of APP23 Mice by Increasing Brain Amyloid Load through a Tumor Necrosis Factor-α-Dependent Mechanism. - Ruan, Yang; Guo, Shi-Jie; Wang, Xu; Dong, Dong; Shen, Dong-Hui; Zhu, Jie; Zheng, Xiang-Yu (J Alzheimers Dis, 2018)
Kainic acid (KA) was recently identified as an epileptogenic and neuroexcitotoxic agent that is responsible for inducing learning and memory deficits in various neurodegenerative diseases, such as Alzheimer's disease (AD). However, the mechanism by which KA acts upon AD remains unclear. To this end, we presently investigated the roles of KA in processing amyloid-β protein precursor (AβPP) and amyloid-β protein (Aβ) loads during the course of AD development and progression. Specifically, KA treatment clearly caused the upregulation of tumor necrosis factor α (TNF-α) via activation of the PI3-K/AKT, ERK1/2, and p65 pathways in glial cells. TNF-α secreted from glial cells was then found to be responsible for stimulating the expression of BACE-1 and PS1/2, which resulted in the production and deposition of Aβ in neurons. Finally, the accumulation and aggregation of Aβ lead to the cognitive decline of APP23 mice. These results indicate that KA accelerates the progression of AD by inducing the crosstalk between glial cells and neurons.

Lentivirus-Mediated HDAC3 Inhibition Attenuates Oxidative Stress in APPswe/PS1dE9 Mice. - Yu, Linjie; Liu, Yi; Jin, Yuexinzi; Cao, Xiang; Chen, Jian; Jin, Jiali; Gu, Yue; Bao, Xinyu; Ren, Zhuoying; Xu, Yun; Zhu, Xiaolei (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) induces a burst of oxidative stress and plays a critical role in the pathogenesis of Alzheimer's disease (AD). Our previous results have shown that histone deacetylase 3 (HDAC3) inhibition ameliorates spatial memory deficits and decreases the Aβ burden in the brains of 9-month-old APPswe/PS1dE9 (APP/PS1) mice. In this study, we investigated the role of HDAC3 inhibition in oxidative stress in vivo and in vitro models of AD. HDAC3 was detected mainly in the neurons, and HDAC3 inhibition significantly decreased reactive oxygen species generation and improved primary cortical neuron viability. In addition, HDAC3 inhibition attenuated spatial memory dysfunction in 6-month-old APP/PS1 mice, and decreased the apoptotic rate in the hippocampi as demonstrated by TUNEL staining. HDAC3 inhibition also reduced markers of lipid peroxidation, protein oxidation, and DNA/RNA oxidation in the hippocampi of APP/PS1 mice. Moreover, HDAC3 inhibition inactivated the c-Abl/MST1/YAP signaling pathway in the hippocampi of APP/PS1 mice. In conclusion, our data show that HDAC3 inhibition can attenuate spatial memory deficits and inhibit oxidative stress in APP/PS1 mice; these results indicate a potential strategy for AD treatment.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Hippocampus; Histone Deacetylases; Lentivirus; Male; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurons; Oxidative Stress; Plaque, Amyloid; Primary Cell Culture; Reactive Oxygen Species; Spatial Memory; tau Proteins

The Level of Plasma Amyloid-β40 Is Correlated with Peripheral Transport Proteins in Cognitively Normal Adults: A Population-Based Cross-Sectional Study. - Gao, Ling; Jiang, Yu; Wei, Shan; Shang, Suhang; Li, Pei; Chen, Chen; Dang, Liangjun; Wang, Jin; Huo, Kang; Deng, Meiying; Wang, Jingyi; Zhang, Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Transport proteins, soluble low-density lipoprotein receptor-related protein-1 (sLRP1), and soluble receptor of advanced glycation end products (sRAGE), play an important role in the clearance of plasma amyloid-β (Aβ). However, their relationship is not clear. OBJECTIVE: The aim was to explore the relationship between plasma levels of sLRP1, sRAGE, and Aβ in a cross-sectional study. METHODS: A total of 1,185 cognitively normal participants (age above 40) from a village in the suburbs of Xi'an, China were enrolled from October 8, 2014 to March 30, 2015. Plasma Aβ40, Aβ42, sLRP1, and sRAGE were tested using a commercial ELISA. Apolipoprotein E (APOE) genotyping was conducted using PCR and sequencing. The relationship between plasma levels of sLRP1, sRAGE, and Aβ was analyzed using Pearson's correlation analysis and multiple linear regression. RESULTS: In the total population, Log sLRP1 and Log sRAGE were positively correlated with plasma Aβ40 (r= 0.103, p < 0.001; r= 0.064, p = 0.027, respectively), but neither were associated with plasma Aβ42. After multivariable adjustment in the regression model, Log sLRP1 and Log sRAGE were still positively related with plasma Aβ40 (β= 2.969, p < 0.001; β= 1.936, p = 0.017, respectively) but not Aβ42. Furthermore, the positive correlations between transport proteins and plasma Aβ40 remained significant only in APOEɛ4 non-carriers after Pearson's analysis and multiple regression analysis after stratification by gene status. CONCLUSION: The concentrations of plasma sLRP1 and sRAGE had a significant impact on the level of plasma Aβ40 in cognitively normal adults, especially in APOEɛ4 non-carriers. However, the mechanism by which the transport proteins are involved in peripheral Aβ clearance and the relationship between transporters and amyloid burden in the brain needs further validation.

Lipid Metabolism and Survival Across the Frontotemporal Dementia-Amyotrophic Lateral Sclerosis Spectrum: Relationships to Eating Behavior and Cognition. - Ahmed, Rebekah M; Highton-Williamson, Elizabeth; Caga, Jashelle; Thornton, Nicolette; Ramsey, Eleanor; Zoing, Margaret; Kim, Woojin Scott; Halliday, Glenda M; Piguet, Olivier; Hodges, John R; Farooqi, I Sadaf; Kiernan, Matthew C (J Alzheimers Dis, 2018)
BACKGROUND: Patients with frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) exhibit changes in eating behavior that could potentially affect lipid levels. OBJECTIVE: This study aimed to document changes in lipid metabolism across the ALS-FTD spectrum to identify potential relationships to eating behavior (including fat intake), cognitive change, body mass index (BMI), and effect on survival. METHODS: One hundred and twenty-eight participants were recruited: 37 ALS patients, 15 ALS patients with cognitive and behavioral change (ALS-Plus), 13 ALS-FTD, 31 behavioral variant FTD, and 32 healthy controls. Fasting total cholesterol, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL) and triglyceride levels were measured and correlated to eating behavior (caloric, fat intake), cognitive change, and BMI; effect on survival was examined using cox regression analyses. RESULTS: There was a spectrum of lipid changes from ALS to FTD with increased triglyceride (p < 0.001), total cholesterol/HDL ratio (p < 0.001), and lower HDL levels (p = 0.001) in all patient groups compared to controls. While there was no increase in total cholesterol levels, a higher cholesterol level was found to correlate with 3.25 times improved survival (p = 0.008). Triglyceride and HDL cholesterol levels correlated to fat intake, BMI, and measures of cognition and disease duration. CONCLUSION: A spectrum of changes in lipid metabolism has been identified in ALS-FTD, with total cholesterol levels found to potentially impact on survival. These changes were mediated by changes in fat intake, and BMI, and may also be mediated by the neurodegenerative process, offering the potential to modify these factors to slow disease progression and improve survival.
Keywords: Adult; Aged; Amyotrophic Lateral Sclerosis; Australia; Body Mass Index; Case-Control Studies; Cholesterol; Cholesterol, HDL; Cognition; Energy Intake; Feeding Behavior; Female; Frontotemporal Dementia; Humans; Lipid Metabolism; Male; Middle Aged; Neuropsychological Tests; Survival Analysis

A Longitudinal Study of Total and Phosphorylated α-Synuclein with Other Biomarkers in Cerebrospinal Fluid of Alzheimer's Disease and Mild Cognitive Impairment. - Wang, Hua; Stewart, Tessandra; Toledo, Jon B; Ginghina, Carmen; Tang, Lu; Atik, Anzari; Aro, Patrick; Shaw, Leslie M; Trojanowski, John Q; Galasko, Douglas R; Edland, Steven; Jensen, Poul H; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) features a dynamic sequence of amyloid deposition, neurodegeneration, and cognitive impairment. A significant fraction of AD brains also displays Lewy body pathology, suggesting that addition of classically Parkinson's disease-related proteins to the AD biomarker panel may be of value. To determine whether addition of cerebrospinal fluid (CSF) total α-synuclein and its form phosphorylated at S129 (pS129) to the AD biomarker panel [Amyloid-β1-42 (Aβ42), tau, and phosphorylated tau (p-tau181)] improves its performance, we examined CSF samples collected longitudinally up to 7 years as part of the Alzheimer's Disease Neuroimaging Initiative. From 87 AD, 177 mild cognitive impairment (MCI), and 104 age-matched healthy controls, 792 baseline and longitudinal CSF samples were tested for total α-synuclein, pS129, Aβ42, tau, and p-tau181. pS129, but not total α-synuclein, was weakly associated with diagnosis at baseline when t-tau/Aβ42 was included in the statistical model (β= 0.0026, p = 0.041, 95% CI [(0.0001)-(0.005)]). CSF α-synuclein predicted Alzheimer's Disease Assessment Scale-Cognitive (β= -0.59, p = 0.0015, 95% CI [(-0.96)-(-0.23)]), memory (β= 0.4, p = 0.00025, 95% CI [(0.16)-(0.59)]), and executive (0.62,<0.0001, 95% CI [(0.31)-(0.93)]) function composite scores, and progression from MCI to AD (β= 0.019, p = 0.0011, 95% CI [(0.002)-(0.20)]). pS129 was associated with executive function (β= -2.55, p = 0.0085, 95% CI [(-4.45)-(-0.66)]). Lower values in the mismatch between α-synuclein and p-tau181 predicted faster cognitive decline (β= 0.64, p = 0.0012, 95% CI [(0.48)-(0.84)]). Longitudinal biomarker changes did not differ between groups, and may not reflect AD progression. The α-synuclein-p-tau181-Mismatch could better predict longitudinal cognitive changes than classical AD markers alone, and its pathological correlates should be investigated further.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Executive Function; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory Disorders; Multivariate Analysis; Neuropsychological Tests; Phosphorylation; tau Proteins

Low Cerebrospinal Fluid Aβ42 and Aβ40 are Related to White Matter Lesions in Cognitively Normal Elderly. - Skoog, Ingmar; Kern, Silke; Zetterberg, Henrik; Östling, Svante; Börjesson-Hanson, Anne; Guo, Xinxin; Blennow, Kaj (J Alzheimers Dis, 2018)
BACKGROUND: Low cerebrospinal fluid (CSF) levels of Aβ42 may be the earliest manifestation of Alzheimer's disease (AD). Knowledge on how CSF Aβ interacts with different brain pathologies early in the disease process is limited. We examined how CSF Aβ markers relate to brain atrophy and white matter lesions (WMLs) in octogenarians with and without dementia to explore the earliest pathogenetic pathways of AD in the oldest old. OBJECTIVE: To study CSF amyloid biomarkers in relation to brain atrophy and WMLs in 85-year-olds with and without dementia. METHODS: 53 octogenarians took part in neuropsychiatric examinations and underwent both a lumbar puncture and a brain CT scan. CSF levels of Aβ42 and Aβ40 were examined in relation to cerebral atrophy and WMLs. Dementia was diagnosed. RESULTS: In 85-year-olds without dementia, lower levels of both CSF Aβ42 and CSF Aβ40 were associated with WMLs. CSF Aβ42 also correlated with measures of central atrophy, but not with cortical atrophy. In participants with dementia, lower CSF levels of Aβ42 were related to frontal, temporal, and parietal cortical atrophy but not to WMLs. CONCLUSIONS: Our findings may suggest that there is an interrelationship between Aβ and subcortical WMLs in older persons without dementia. After onset of dementia, low CSF Aβ42, probably representing amyloid deposition in plaques, is associated with cortical atrophy. WMLs may be an earlier manifestation of Aβ deposition than cortical degeneration.

Melatonin in Synaptic Impairments of Alzheimer's Disease. - Shi, Yan; Fang, Ying-Yan; Wei, Yu-Ping; Jiang, Qian; Zeng, Peng; Tang, Na; Lu, Youming; Tian, Qing (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) underlies dementia for millions of people worldwide with no effective treatment. The dementia of AD is thought stem from the impairments of the synapses because of their critical roles in cognition. Melatonin is a neurohormone mainly released by the pineal gland in a circadian manner and it regulates brain functions in various manners. It is reported that both the melatonin deficit and synaptic impairments are present in the very early stage of AD and strongly contribute to the progress of AD. In the mammalian brains, the effects of melatonin are mainly relayed by two of its receptors, melatonin receptor type 1a (MT1) and 1b (MT2). To have a clear idea on the roles of melatonin in synaptic impairments of AD, this review discussed the actions of melatonin and its receptors in the stabilization of synapses, modulation of long-term potentiation, as well as their contributions in the transmissions of glutamatergic, GABAergic and dopaminergic synapses, which are the three main types of synapses relevant to the synaptic strength. The synaptic protective roles of melatonin in AD treatment were also summarized. Regarding its protective roles against amyloid-β neurotoxicity, tau hyperphosphorylation, oxygenation, inflammation as well as synaptic dysfunctions, melatonin may be an ideal therapeutic agent against AD at early stage.

Memory Binding Test Predicts Incident Dementia: Results from the Einstein Aging Study. - Mowrey, Wenzhu B; Lipton, Richard B; Katz, Mindy J; Ramratan, Wendy S; Loewenstein, David A; Zimmerman, Molly E; Buschke, Herman (J Alzheimers Dis, 2018)
BACKGROUND: The Memory Binding Test (MBT) demonstrated good cross-sectional discriminative validity and predicted incident aMCI. OBJECTIVE: To assess whether the MBT predicts incident dementia better than a conventional list learning test in a longitudinal community-based study. METHODS: As a sub-study in the Einstein Aging Study, 309 participants age≥70 initially free of dementia were administered the MBT and followed annually for incident dementia for up to 13 years. Based on previous work, poor memory binding was defined using an optimal empirical cut-score of≤17 on the binding measure of the MBT, Total Items in the Paired condition (TIP). Cox proportional hazards models were used to assess predictive validity adjusting for covariates. We compared the predictive validity of MBT TIP to that of the free and cued selective reminding test free recall score (FCSRT-FR; cut-score:≤24) and the single list recall measure of the MBT, Cued Recalled from List 1 (CR-L1; cut-score:≤12). RESULTS: Thirty-five of 309 participants developed incident dementia. When assessing each test alone, the hazard ratio (HR) for dementia was significant for MBT TIP (HR = 8.58, 95% CI: (3.58, 20.58), p < 0.0001), FCSRT-FR (HR = 4.19, 95% CI: (1.94, 9.04), p = 0.0003) and MBT CR-L1 (HR = 2.91, 95% CI: (1.37, 6.18), p = 0.006). MBT TIP remained a significant predictor of dementia (p = 0.0002) when adjusting for FCSRT-FR or CR-L1. CONCLUSIONS: Older adults with poor memory binding as measured by the MBT TIP were at increased risk for incident dementia. This measure outperforms conventional episodic memory measures of free and cued recall, supporting the memory binding hypothesis.

Metabolomics Analyses of Saliva Detect Novel Biomarkers of Alzheimer's Disease. - Huan, Tao; Tran, Tran; Zheng, Jiamin; Sapkota, Shraddha; MacDonald, Stuart W; Camicioli, Richard; Dixon, Roger A; Li, Liang (J Alzheimers Dis, 2018)
Using a non-invasive biofluid (saliva), we apply a powerful metabolomics workflow for unbiased biomarker discovery in Alzheimer's disease (AD). We profile and differentiate Cognitively Normal (CN), Mild Cognitive Impairment (MCI), and AD groups. The workflow involves differential chemical isotope labeling liquid chromatography mass spectrometry using dansylation derivatization for in-depth profiling of the amine/phenol submetabolome. The total sample (N = 109) was divided in to the Discovery Phase (DP) (n = 82; 35 CN, 25 MCI, 22 AD) and a provisional Validation Phase (VP) (n = 27; 10 CN, 10 MCI, 7 AD). In DP we detected 6,230 metabolites. Pairwise analyses confirmed biomarkers for AD versus CN (63), AD versus MCI (47), and MCI versus CN (2). We then determined the top discriminating biomarkers and diagnostic panels. A 3-metabolite panel distinguished AD from CN and MCI (DP and VP: Area Under the Curve [AUC] = 1.000). The MCI and CN groups were best discriminated with a 2-metabolite panel (DP: AUC = 0.779; VP: AUC = 0.889). In addition, using positively confirmed metabolites, we were able to distinguish AD from CN and MCI with good diagnostic performance (AUC > 0.8). Saliva is a promising biofluid for both unbiased and targeted AD biomarker discovery and mechanism detection. Given its wide availability and convenient accessibility, saliva is a biofluid that can promote diversification of global AD biomarker research.

Microglia CREB-Phosphorylation Mediates Amyloid-β-Induced Neuronal Toxicity. - Gao, Yuan; Liu, En-Jie; Wang, Wei-Jin; Wang, Ya-Li; Li, Xiao-Guang; Wang, Xin; Li, Shi-Hong; Zhang, Shu-Juan; Li, Meng-Zhu; Zhou, Qiu-Zhi; Long, Xiao-Bing; Zhang, Hua-Qiu; et al. (J Alzheimers Dis, 2018)
Extracellular accumulation of amyloid-β (Aβ) forming senile plaques is one of the hallmark pathologies in Alzheimer's disease (AD), while the mechanisms underlying the neuronal toxic effect of Aβ are not fully understood. Here, we found that intracerebroventricular infusion of the aged Aβ42 in mice only induces memory deficit at 24 h but not at 7 days. Interestingly, a remarkably increased CREB (cAMP response element-binding protein) Ser133-phosphorylation (pS133-CREB) with microglial activation was detected at 24 h but not at 7 days after Aβ infusion. Aβ treatment for 24 h increased pS133-CREB level in microglia of the hippocampal non-granular cell layers with remarkably decreased pS133-CREB immunoreactivity in neurons of the hippocampal granular cell layers, including CA1, CA3, and DG subsets. Inhibition of microglia activation by minocycline or CREB phosphorylation by H89, an inhibitor of protein kinase A (PKA), abolished Aβ-induced microglia CREB hyperphosphorylation with restoration of neuronal function and attenuation of inflammatory response, i.e., reduced levels of interleukin-6 (IL6) and pCREB binding of matrix metalloproteinase-9 (MMP9) DNA. Finally, treatment of the primary hippocampal neurons with Aβ-potentiated microglia media decreased neuronal GluN1 and GluA2 levels, while simultaneous inhibition of PKA restored the levels. These novel findings reveal that intracerebroventricular infusion of Aβ only induces transient memory deficit in mice and the molecular mechanisms involve a stimulated microglial CREB phosphorylation.

Midlife Physical Activity, Psychological Distress, and Dementia Risk: The HUNT Study. - Zotcheva, Ekaterina; Bergh, Sverre; Selbæk, Geir; Krokstad, Steinar; Håberg, Asta Kristine; Strand, Bjørn Heine; Ernstsen, Linda (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity (PA) is associated with a decreased dementia risk, whereas psychological distress (distress) is linked to an increased dementia risk. OBJECTIVE: We investigated independent and joint associations of midlife moderate-to-vigorous PA (MVPA) and distress with incident dementia. METHODS: Our study comprised 28,916 participants aged 30-60 years from the Nord-Trøndelag Health Study (HUNT1, 1984-1986). Data on MVPA and distress from HUNT1 was linked to the Health and Memory Study in Nord-Trøndelag for dementia case identification. Participants were followed from 1995 until 2011. We used adjusted Cox regression models to estimate hazard ratios (HRs) and 95% confidence intervals (95% CI). RESULTS: In fully adjusted analyses, MVPA was associated with a reduced dementia risk (HR 0.81, 95% CI 0.62-1.06), compared to no MVPA. Distress was associated with an increased dementia risk (HR 1.30, 95% CI 0.99-1.70). Compared to distressed participants not taking part in MVPA, non-distressed no-MVPA participants had a reduced dementia risk (HR 0.72, 95% CI 0.54-0.96). The same applied to distressed MVPA participants (HR 0.50, 95% CI 0.22-1.14), and non-distressed MVPA participants (HR 0.63, 95% CI 0.44-0.90). Our results indicated an additive interaction between MVPA and distress on dementia risk. CONCLUSION: Our results suggest that midlife MVPA reduces risk of incident dementia among both distressed and non-distressed individuals.

Moringa Oleifera Alleviates Homocysteine-Induced Alzheimer's Disease-Like Pathology and Cognitive Impairments. - Mahaman, Yacoubou Abdoul Razak; Huang, Fang; Wu, Mengjuan; Wang, Yuman; Wei, Zhen; Bao, Jian; Salissou, Maibouge Tanko Mahamane; Ke, Dan; Wang, Qun; Liu, Rong; Wang, Jian-Zhi; Zhang, Bin; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is multifactorial with unclear etiopathology. Due to the complexity of AD, many attempted single therapy treatments, like Aβ immunization, have generally failed. Therefore, there is a need for drugs with multiple benefits. Naturally occurring phytochemicals with neuroprotective, anti-amyloidogenic, antioxidative, and anti-inflammatory properties could be a possible way out. In this study, the effect of Moringa oleifera (MO), a naturally occurring plant with high antioxidative, anti-inflammatory, and neuroprotective effects, was evaluated on hyperhomocysteinemia (HHcy) induced AD-like pathology in rats. Homocysteine (Hcy) injection for 14 days was used to induce AD-like pathology. Simultaneous MO extract gavage followed the injection as a preventive treatment or, after injection completion, MO gavage was performed for another 14 days as a curative treatment. MO was found to not only prevent but also rescue the oxidative stress and cognitive impairments induced by Hcy treatment. Moreover, MO recovered the decreased synaptic proteins PSD93, PSD95, Synapsin 1 and Synaptophysin, and improved neurodegeneration. Interestingly, MO decreased the Hyc-induced tau hyperphosphorylation at different sites including S-199, T-231, S-396, and S-404, and at the same time decreased Aβ production through downregulation of BACE1. These effects in HHcy rats were accompanied by a decrease in calpain activity under MO treatment, supporting that calpain activation might be involved in AD pathogenesis in HHcy rats. Taken together, our data, for the first time, provided evidence that MO alleviates tau hyperphosphorylation and Aβ pathology in a HHcy AD rat model. This and previous other studies support MO as a good candidate for, and could provide new insights into, the treatment of AD and other tauopathies.

Morphological and Pathological Characteristics of Brain in Diabetic Encephalopathy. - Chen, Rui; Shi, Jiangwei; Yin, Qingsheng; Li, Xiaojin; Sheng, Yanyuan; Han, Juan; Zhuang, Pengwei; Zhang, Yanjun (J Alzheimers Dis, 2018)
Diabetes mellitus is a metabolic disease often accompanied by a series of complications, such as diabetic nephropathy, retinopathy, and diabetic foot. The survival time of diabetics has been significantly prolonged due to advancements in medicine. However, the prolonged survival time for diabetics can increase the prevalence of diabetic central nervous system disease. Diabetic encephalopathy (DE) has become one of the main complications of the disease, and the main clinical manifestation of DE is cognitive dysfunction. However, the typical morphological and pathological characteristics of the brain in DE are rarely systematically reported. Thus, this phenomenon severely restricts the diagnosis and treatment of DE. This article presents a description of the pathology characteristics of DE, including atrophy of the brain (gray matter, white matter, and hippocampus), changes in cerebrovascular morphology and function, impairment of synaptic plasticity, and dysfunction of neuroglia. In addition, abnormalities in the glymphatic clearance system of the brain are closely related to the progression of DE. A review of typical brain morphological and pathological characteristics would aid in the diagnosis and treatment of DE.

Multivariate Approach for Alzheimer's Disease Detection Using Stationary Wavelet Entropy and Predator-Prey Particle Swarm Optimization. - Zhang, Yudong; Wang, Shuihua; Sui, Yuxiu; Yang, Ming; Liu, Bin; Cheng, Hong; Sun, Junding; Jia, Wenjuan; Phillips, Preetha; Górriz, Juan Manuel (J Alzheimers Dis, 2018)
BACKGROUND: The number of patients with Alzheimer's disease is increasing rapidly every year. Scholars often use computer vision and machine learning methods to develop an automatic diagnosis system. OBJECTIVE: In this study, we developed a novel machine learning system that can make diagnoses automatically from brain magnetic resonance images. METHODS: First, the brain imaging was processed, including skull stripping and spatial normalization. Second, one axial slice was selected from the volumetric image, and stationary wavelet entropy (SWE) was done to extract the texture features. Third, a single-hidden-layer neural network was used as the classifier. Finally, a predator-prey particle swarm optimization was proposed to train the weights and biases of the classifier. RESULTS: Our method used 4-level decomposition and yielded 13 SWE features. The classification yielded an overall accuracy of 92.73±1.03%, a sensitivity of 92.69±1.29%, and a specificity of 92.78±1.51%. The area under the curve is 0.95±0.02. Additionally, this method only cost 0.88 s to identify a subject in online stage, after its volumetric image is preprocessed. CONCLUSION: In terms of classification performance, our method performs better than 10 state-of-the-art approaches and the performance of human observers. Therefore, this proposed method is effective in the detection of Alzheimer's disease.

Mutation Screening of the CHCHD2 Gene for Alzheimer's Disease and Frontotemporal Dementia in Chinese Mainland Population. - Che, Xiang-Qian; Zhao, Qian-Hua; Huang, Yue; Li, Xia; Ren, Ru-Jing; Chen, Sheng-Di; Guo, Qi-Hao; Wang, Gang (J Alzheimers Dis, 2018)
As an important multifunctional protein involved in regulation of mitochondrial metabolism, CHCHD2 was identified as a causative gene for Parkinson's disease (PD), yet the relationship between CHCHD2 and neurodegenerative dementia is not well understood. We directly sequenced the entire coding region of CHCHD2 gene in 150 AD patients, 84 FTD patients, and 417 controls. Four rare putative pathogenic variants of CHCHD2, including rs142444896 (c.5C>T, p.P2L), rs752705344 (c.15C>G, p.S5R), rs145190179 (c.94G>A, p.A32T), and rs182992574 (c.255T>A, p.S85R) were identified from a cohort composed of 150 AD and 84 FTD patients. These results suggest that CH CHD2 gene play an important role in other neurodegenerative disorders from our dementia study in China.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Genetic Association Studies; Humans; Male; Middle Aged; Mitochondrial Proteins; Mutation; Transcription Factors

Neuroepigenetics and Alzheimer's Disease: An Update. - Zusso, Morena; Barbierato, Massimo; Facci, Laura; Skaper, Stephen D; Giusti, Pietro (J Alzheimers Dis, 2018)
Epigenetics is the study of changes in gene expression which may be triggered by both genetic and environmental factors, and independent from changes to the underlying DNA sequence-a change in phenotype without a change in genotype-which in turn affects how cells read genes. Epigenetic changes represent a regular and natural occurrence but can be influenced also by factors such as age, environment, and disease state. Epigenetic modifications can manifest themselves not only as the manner in which cells terminally differentiate, but can have also deleterious effects, resulting in diseases such as cancer. At least three systems including DNA methylation, histone modification, and non-coding RNA (ncRNA)-associated gene silencing are thought to initiate and sustain epigenetic change. For example, in Alzheimer's disease (AD), both genetic and non-genetic factors contribute to disease etiopathology. While over 250 gene mutations have been related to familial AD, less than 5% of AD cases are explained by known disease genes. More than likely, non-genetic factors, probably triggered by environmental factors, are causative factors of late-onset AD. AD is associated with dysregulation of DNA methylation, histone modifications, and ncRNAs. Among the classes of ncRNA, microRNAs (miRNAs) have a well-established regulatory relevance. MicroRNAs are highly expressed in CNS neurons, where they play a major role in neuron differentiation, synaptogenesis, and plasticity. MicroRNAs impact higher cognitive functions, as their functional impairment is involved in the etiology of neurological diseases, including AD. Alterations in the miRNA network contribute to AD disease processes, e.g., in the regulation of amyloid peptides, tau, lipid metabolism, and neuroinflammation. MicroRNAs, both as biomarkers for AD and therapeutic targets, are in the early stages of exploration. In addition, emerging data suggest that altered transcription of long ncRNAs, endogenous, ncRNAs longer than 200 nucleotides, may be involved in an elevated risk for AD.

Neuro-Immuno-Gene- and Genome-Editing-Therapy for Alzheimer's Disease: Are We There Yet? - Raikwar, Sudhanshu P; Thangavel, Ramasamy; Dubova, Iuliia; Ahmed, Mohammad Ejaz; Selvakumar, Pushpavathi Govindhasamy; Kempuraj, Duraisamy; Zaheer, Smita; Iyer, Shankar; Zaheer, Asgar (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a highly complex neurodegenerative disorder and the current treatment strategies are largely ineffective thereby leading to irreversible and progressive cognitive decline in AD patients. AD continues to defy successful treatment despite significant advancements in the field of molecular medicine. Repeatedly, early promising preclinical and clinical results have catapulted into devastating setbacks leading to multi-billion dollar losses not only to the top pharmaceutical companies but also to the AD patients and their families. Thus, it is very timely to review the progress in the emerging fields of gene therapy and stem cell-based precision medicine. Here, we have made sincere efforts to feature the ongoing progress especially in the field of AD gene therapy and stem cell-based regenerative medicine. Further, we also provide highlights in elucidating the molecular mechanisms underlying AD pathogenesis and describe novel AD therapeutic targets and strategies for the new drug discovery. We hope that the quantum leap in the scientific advancements and improved funding will bolster novel concepts that will propel the momentum toward a trajectory leading to a robust AD patient-specific next generation precision medicine with improved cognitive function and excellent life quality.

Neuroprotective Effects of Ferruginol, Jatrophone, and Junicedric Acid Against Amyloid-β Injury in Hippocampal Neurons. - Zolezzi, Juan M; Lindsay, Carolina B; Serrano, Felipe G; Ureta, Roxana C; Theoduloz, Cristina; Schmeda-Hirschmann, Guillermo; Inestrosa, Nibaldo C (J Alzheimers Dis, 2018)
Soluble amyloid-β (Aβ) oligomers have been recognized as early neurotoxic intermediates with a key role in the synaptic dysfunction observed in Alzheimer's disease (AD). Aβ oligomers block hippocampal long-term potentiation (LTP) and impair rodent spatial memory. Additionally, the presence of Aβ oligomers is associated with imbalanced intracellular calcium levels and apoptosis in neurons. In this context, we evaluated the effects of three diterpenes (ferruginol, jatrophone, and junicedric acid) that are found in medicinal plants and have several forms of biological activity. The intracellular calcium levels in hippocampal neurons increased in the presence of ferruginol, jatrophone, and junicedric acid, a result that was consistent with the observed increase in CA1 synaptic transmission in mouse hippocampal slices. Additionally, assays using Aβ peptide demonstrated that diterpenes, particularly ferruginol, restore LTP and reduce apoptosis. Recovery of the Aβ oligomer-induced loss of the synaptic proteins PSD-95, synapsin, VGlut, and NMDA receptor subunit 2A was observed in mouse hippocampal slices treated with junicedric acid. This cascade of events may be associated with the regulation of kinases, e.g., protein kinase C (PKC) and calcium/calmodulin-dependent protein kinase II (CaMKII), in addition to the activation of the canonical Wnt signaling pathway and could thus provide protection against Aβ oligomers, which trigger synaptic dysfunction. Our results suggest a potential neuroprotective role for diterpenes against the Aβ oligomers-induced neurodegenerative alterations, which make them interesting molecules to be further studied in the context of AD.

New Beginnings in Alzheimer's Disease: The Most Prevalent Tauopathy. - Hernández, Félix; Llorens-Martín, María; Bolós, Marta; Pérez, Mar; Cuadros, Raquel; Pallas-Bazarra, Noemí; Zabala, Juan C; Avila, Jesús (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by the presence of two aberrant structures: namely senile plaques, composed of amyloid-β peptide (Aβ), and neurofibrillary tangles, composed of tau protein. In this regard, Aβ and tau protein have been widely studied in research efforts aiming to find a therapy for AD. Aβ and tau pathologies do not always overlap. The precursor of Aβ is expressed in peripheral tissues and in the central nervous system (CNS), whereas tau is mainly a neuronal protein. Since AD is a disease of the CNS, it has been proposed that Aβ may initiate the disease process, with tau being the executor. In this review, we will focus on future studies of tau pathology, although we will comment on new beginnings for AD, as other molecules other than Aβ and tau may be involved in the onset of dementia.

New Insights into the Spontaneous Human Alzheimer's Disease-Like Model Octodon degus: Unraveling Amyloid-β Peptide Aggregation and Age-Related Amyloid Pathology. - Cisternas, Pedro; Zolezzi, Juan M; Lindsay, Carolina; Rivera, Daniela S; Martinez, Alexis; Bozinovic, Francisco; Inestrosa, Nibaldo C (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common cause of dementia worldwide. Despite advances in our understanding of the molecular milieu driving AD pathophysiology, no effective therapy is currently available. Moreover, various clinical trials have continued to fail, suggesting that our approach to AD must be revised. Accordingly, the development and validation of new models are highly desirable. Over the last decade, we have been working with Octodon degus (degu), a Chilean rodent, which spontaneously develops AD-like neuropathology, including increased amyloid-β (Aβ) aggregates, tau hyperphosphorylation, and postsynaptic dysfunction. However, for proper validation of degu as an AD model, the aggregation properties of its Aβ peptide must be analyzed. Thus, in this study, we examined the capacity of the degu Aβ peptide to aggregate in vitro. Then, we analyzed the age-dependent variation in soluble Aβ levels in the hippocampus and cortex of third- to fifth-generation captive-born degu. We also assessed the appearance and spatial distribution of amyloid plaques in O. degus and compared them with the plaques in two AD transgenic mouse models. In agreement with our previous studies, degu Aβ was able to aggregate, forming fibrillar species in vitro. Furthermore, amyloid plaques appeared in the anterior brain structures of O. degus at approximately 32 months of age and in the whole brain at 56 months, along with concomitant increases in Aβ levels and the Aβ42/Aβ40 ratio, indicating that O. degus spontaneously develops AD-like pathology earlier than other spontaneous models. Based on these results, we can confirm that O. degus constitutes a valuable model to improve AD research.

Novel Lipidized Analog of Prolactin-Releasing Peptide Improves Memory Impairment and Attenuates Hyperphosphorylation of Tau Protein in a Mouse Model of Tauopathy. - Popelová, Andrea; Pražienková, Veronika; Neprašová, Barbora; Kasperová, Barbora Judita; Hrubá, Lucie; Holubová, Martina; Zemenová, Jana; Blum, David; Železná, Blanka; Galas, Marie-Christine; Kuneš, Jaroslav; Maletínská, Lenka (J Alzheimers Dis, 2018)
Obesity and type 2 diabetes mellitus (T2DM) were characterized as risk factors for Alzheimer's disease (AD) development. Subsequently, T2DM drugs, such as liraglutide, were proven to be neuroprotective compounds attenuating levels of amyloid deposits, and tau hyperphosphorylation, both hallmarks of AD. The central anorexigenic effects of liraglutide inspired us to examine the potential neuroprotective effects of palm11-PrRP31, a strong anorexigenic analog with glucose-lowering properties, in THY-Tau22 mice overexpressing mutated human tau, a model of AD-like tau pathology. Seven-month-old THY-Tau22 mice were subcutaneously infused with palm11-PrRP31 for 2 months. Spatial memory was tested before and after the treatment, using a Y-maze. At the end of the treatment, mice were sacrificed by decapitation and hippocampi were dissected and analyzed by immunoblotting with specific antibodies. Treatment with palm11-PrRP31 resulted in significantly improved spatial memory. In the hippocampi of palm11-PrRP31-treated THY-Tau22 mice, tau protein phosphorylation was attenuated at Thr231, Ser396, and Ser404, the epitopes linked to AD progression. The mechanism of this attenuation remains unclear, since the activation of those kinases most implicated in tau hyperphosphorylation, such as GSK-3β, JNK, or MAPK/ERK1/2, remained unchanged by palm11-PrRP31 treatment. Furthermore, we observed a significant increase in the amount of postsynaptic density protein PSD95, and a non-significant increase of synaptophysin, both markers of increased synaptic plasticity, which could also result in improved spatial memory of THY-Tau22 mice treated with palm11-PrRP31. Palm11-PrRP31 seems to be a potential tool for the attenuation of neurodegenerative disorders in the brain. However, the exact mechanism of its action must be elucidated.

Optical Depolarization of DCX-Expressing Cells Promoted Cognitive Recovery and Maturation of Newborn Neurons via the Wnt/β-Catenin Pathway. - Zhao, Ming-Liang; Chen, Shi-Jin; Li, Xiao-Hong; Wang, Li-Na; Chen, Feng; Zhong, Shi-Jiang; Yang, Cheng; Sun, Sheng-Kai; Li, Jian-Jun; Dong, Hua-Jiang; Dong, Yue-Qing; Wang, Yi; et al. (J Alzheimers Dis, 2018)
Electrical excitability by membrane depolarization is crucial for survival and maturation of newborn cells in the dentate gyrus of the hippocampus. However, traditional technology for membrane depolarization lacks temporal and spatial precision. Optogenetics can be used to activate channelrhodopsin-2 (ChR2), allowing cationic current to depolarize genetically targeted cells. In this study, we used ChR2-EGFP driven by doublecortin (DCX) to promote survival and maturation of newborn cells in the dentate gyrus after traumatic brain injury (TBI). C57BL/6 mice underwent lateral fluid percussion TBI. TBI mice were transfected with a lentivirus carrying the DCX-ChR2-EGFP gene. We observed that not only immature neurons but also type-2b intermediate progenitor (IPs) and neuroblasts expressed DCX-EGFP, indicating that DCX-expressing newborn cells could provide a long time window for electrical activity regulation. Quantitative results showed that the number of EGFP-expressing cells began to rise at 3 days after TBI and peaked at 9 days after TBI. By optical depolarization of DCX-EGFP-expressing cells between 3 and 12 days, we observed significantly improved cognitive deficits after TBI with enhanced survival and maturation of newborn cells in the dentate gyrus. We also investigated the role of optical depolarization in neural stem cells transfected with a lentivirus carrying the ChR2-DCX-EGFP gene in vitro. By administrating verapamil to block L-type calcium channels, we verified that the up-regulation of MAP2, NeuN, Neurog2, NeuroD1 and GluR2 in newborn cells was mediated by ChR2-elicted depolarization. By using β-catenin inhibitor Dkk1, we demonstrated that optical depolarization of DCX-EGFP-expressing cells facilitated survival and maturation probably through the Wnt/β-catenin signaling cascade.

Overactive BRCA1 Affects Presenilin 1 in Induced Pluripotent Stem Cell-Derived Neurons in Alzheimer's Disease. - Wezyk, Michalina; Szybinska, Aleksandra; Wojsiat, Joanna; Szczerba, Marcelina; Day, Kelly; Ronnholm, Harriet; Kele, Malin; Berdynski, Mariusz; Peplonska, Beata; Fichna, Jakub Piotr; Ilkowski, Jan; Styczyńska, Maria; et al. (J Alzheimers Dis, 2018)
The BRCA1 protein, one of the major players responsible for DNA damage response has recently been linked to Alzheimer's disease (AD). Using primary fibroblasts and neurons reprogrammed from induced pluripotent stem cells (iPSC) derived from familial AD (FAD) patients, we studied the role of the BRCA1 protein underlying molecular neurodegeneration. By whole-transcriptome approach, we have found wide range of disturbances in cell cycle and DNA damage response in FAD fibroblasts. This was manifested by significantly increased content of BRCA1 phosphorylated on Ser1524 and abnormal ubiquitination and subcellular distribution of presenilin 1 (PS1). Accordingly, the iPSC-derived FAD neurons showed increased content of BRCA1(Ser1524) colocalized with degraded PS1, accompanied by an enhanced immunostaining pattern of amyloid-β. Finally, overactivation of BRCA1 was followed by an increased content of Cdc25C phosphorylated on Ser216, likely triggering cell cycle re-entry in FAD neurons. This study suggests that overactivated BRCA1 could both influence PS1 turnover leading to amyloid-β pathology and promote cell cycle re-entry-driven cell death of postmitotic neurons in AD.

Ozone Atmospheric Pollution and Alzheimer's Disease: From Epidemiological Facts to Molecular Mechanisms. - Croze, Marine L; Zimmer, Luc (J Alzheimers Dis, 2018)
Atmospheric pollution is a well-known environmental hazard, especially in developing countries where millions of people are exposed to airborne pollutant levels above safety standards. Accordingly, several epidemiological and animal studies confirmed its role in respiratory and cardiovascular pathologies and identified a strong link between ambient air pollution exposure and adverse health outcomes such as hospitalization and mortality. More recently, the potential deleterious effect of air pollution inhalation on the central nervous system was also investigated and mounting evidence supports a link between air pollution exposure and neurodegenerative pathologies, especially Alzheimer's disease (AD). The focus of this review is to highlight the possible link between ozone air pollution exposure and AD incidence. This review's approach will go from observational and epidemiological facts to the proposal of molecular mechanisms. First, epidemiological and postmortem human study data concerning residents of ozone-severely polluted megacities will be presented and discussed. Then, the more particular role of ozone air pollution in AD pathology will be described and evidenced by toxicological studies in rat or mouse with ozone pollution exposure only. The experimental paradigms used to reproduce in rodent the human exposure to ozone air pollution will be described. Finally, current insights into the molecular mechanisms through which ozone inhalation can affect the brain and play a role in AD development or progression will be recapitulated.
Keywords: Air Pollution; Alzheimer Disease; Animals; Central Nervous System; Humans; Incidence; Inhalation Exposure; Ozone; Particulate Matter

The Past and the Future of Alzheimer's Disease Fluid Biomarkers. - Blennow, Kaj; Zetterberg, Henrik (J Alzheimers Dis, 2018)
Following the development of the first methods to measure the core Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers total-tau (T-tau), phosphorylated tau (P-tau) and the 42 amino acid form of amyloid-β (Aβ42), there has been an enormous expansion of this scientific research area. Today, it is generally acknowledged that these biochemical tests reflect several central pathophysiological features of AD and contribute diagnostically relevant information, also for prodromal AD. In this article in the 20th anniversary issue of the Journal of Alzheimer's Disease, we review the AD biomarkers, from early assay development to their entrance into diagnostic criteria. We also summarize the long journey of standardization and the development of assays on fully automated instruments, where we now have high precision and stable assays that will serve as the basis for common cut-off levels and a more general introduction of these diagnostic tests in clinical routine practice. We also discuss the latest expansion of the AD CSF biomarker toolbox that now also contains synaptic proteins such as neurogranin, which seemingly is specific for AD and predicts rate of future cognitive deterioration. Last, we are at the brink of having blood biomarkers that may be implemented as screening tools in the early clinical management of patients with cognitive problems and suspected AD. Whether this will become true, and whether it will be plasma Aβ42, the Aβ42/40 ratio, or neurofilament light, or a combination of these, remains to be established in future clinical neurochemical studies.
Keywords: Alzheimer Disease; Animals; Biomarkers; Humans

Patients with Dementia in Primary Care: Who Is Referred to a Neurologist/Psychiatrist and What Patient-Oriented Factors Are Associated with the Visit? - Strohmaier, Urs; Keller, Felix; Kilimann, Ingo; Michalowsky, Bernhard; Wucherer, Diana; Zwingmann, Ina; Teipel, Stefan; Hoffmann, Wolfgang; Thyrian, Jochen René (J Alzheimers Dis, 2018)
BACKGROUND: The current guidelines imply that basic medical diagnostics for dementia should be provided by general practitioners in cooperation with other specialists such as neurologists and psychiatrists. OBJECTIVES: The aims of this paper were to 1) compare the dementia patients of general practice residents whose care is co-managed by neurology/psychiatry residents with those whose care is not; 2) identify the patient variables associated with the utilization of neurological and psychiatric specialists; and 3) describe the frequency of imaging used for dementia patients in primary care. METHODS: The analyses utilized data from 485 individuals who screened positive for dementia in primary care (PWD). Clinical variables and the utilization of specialists were assessed via medical records and face-to-face interviews. The factors associated with the utilization of specialists were assessed using multivariate linear regression and included age, sex, relationship status, cognitive impairment, depression, activities of daily living, and formal diagnosis of dementia. RESULTS: Our results show that 89 out of 485 study participants (18.4%) were referred to specialists 12 months prior to assessment. Of these 89 individuals, 14.6% (n = 13) did not receive imaging diagnostics, while 39.3% (n = 35) received brain imaging by CT scan and 46.1% (n = 41) by MRI. PWD referred to specialists differed from those not referred, in age, relationship status, and the presence of a formal diagnosis. Our multivariate analysis revealed that younger age (OR = 0.95; 95% -confidence interval 0.90-0.99; p = 0.04) and higher functional impairment (OR = 1.15; 95% -confidence interval 1.02-1.30; p = 0.02) were associated with a visit to a specialist. DISCUSSION: Only 1 out of every 4 to 5 individuals who have screened positive for dementia have visited a specialist in psychiatry or neurology. While in general, women utilized specialists less often than men, younger and more functionally impaired patients were more likely to be sent to a specialist by their treating general practitioner. Almost 90% of the patients sent to a specialist received cranial neuroimaging, suggesting high adherence to diagnostic guidelines in specialized care.

Plasma Amyloid-β (Aβ42) Correlates with Cerebrospinal Fluid Aβ42 in Alzheimer's Disease. - Teunissen, Charlotte E; Chiu, Ming-Jang; Yang, Che-Chuan; Yang, Shieh-Yueh; Scheltens, Philip; Zetterberg, Henrik; Blennow, Kaj (J Alzheimers Dis, 2018)
The 42 amino acid form of amyloid-β (Aβ42) plays a key role in the pathogenesis of Alzheimer's disease (AD) and is a core biomarker for the diagnosis of AD. Numerous studies have shown that cerebrospinal fluid (CSF) Aβ42 concentrations are decreased in AD, when measured by enzyme-linked immunosorbent assay (ELISA) and other conventional immunoassays. While most studies report no change in plasma Aβ42, independent studies using the immunomagnetic reduction (IMR) technique report an increase in plasma Aβ42 levels in AD. To confirm the opposite changes of Aβ42 levels in CSF and plasma for AD, we assayed the levels of Aβ42 in plasma of subjects with known CSF Aβ42 levels. In total 43 controls and 63 AD patients were selected at two sites: the VU University Medical Center (n = 55) and Sahlgrenska University Hospital (n = 51). IMR and ELISA were applied to assay Aβ42 in plasma and CSF, respectively. We found a moderately negative correlation between plasma and CSF Aβ42 levels in AD patients (r = -0.352), and a weakly positive correlation in controls (r = 0.186). These findings further corroborate that there are opposite changes of Aβ42 levels in CSF and plasma in AD. The possible causes for the negative correlation are discussed by taken assay technologies, Aβ42 transport from brain to peripheral blood, and sample matrix into account.

Postsynaptic Proteome of Non-Demented Individuals with Alzheimer's Disease Neuropathology. - Zolochevska, Olga; Bjorklund, Nicole; Woltjer, Randall; Wiktorowicz, John E; Taglialatela, Giulio (J Alzheimers Dis, 2018)
Some individuals, here referred to as Non-Demented with Alzheimer's Neuropathology (NDAN), retain their cognitive function despite the presence of amyloid plaques and tau tangles typical of symptomatic Alzheimer's disease (AD). In NDAN, unlike AD, toxic amyloid-β oligomers do not localize to the postsynaptic densities (PSDs). Synaptic resistance to amyloid-β in NDAN may thus enable these individuals to remain cognitively intact despite the AD-like pathology. The mechanism(s) responsible for this resistance remains unresolved and understanding such protective biological processes could reveal novel targets for the development of effective treatments for AD. The present study uses a proteomic approach to compare the hippocampal postsynaptic densities of NDAN, AD, and healthy age-matched persons to identify protein signatures characteristic for these groups. Subcellular fractionation followed by 2D gel electrophoresis and mass spectrometry were used to analyze the PSDs. We describe fifteen proteins which comprise the unique proteomic signature of NDAN PSDs, thus setting them apart from control subjects and AD patients.

Pramlintide: The Effects of a Single Drug Injection on Blood Phosphatidylcholine Profile for Alzheimer's Disease. - Tao, Qiushan; Zhu, Haihao; Chen, Xi; Stern, Robert A; Kowall, Neil; Au, Rhoda; Blusztajn, Jan Krzysztof; Qiu, Wei Qiao (J Alzheimers Dis, 2018)
Studies suggest that a single injection of pramlintide, an amylin analog, induces changes in Alzheimer's disease (AD) biomarkers in the blood of AD mouse models and AD patients. The aim of this study was to examine whether a pramlintide challenge combined with a phosphatidylcholine (PC) profile diagnoses of AD and mild cognitive impairment (MCI) better than PC alone. Non-diabetic subjects with cognitive status were administered a single subcutaneous injection of 60 mcg of pramlintide under fasting condition. A total of 71 PCs, amyloid-β peptide (Aβ), and total tau (t-tau) in plasma at different time points were measured and treated as individual variables. A single injection of pramlintide altered the levels of 7 PCs in the blood, while a pramlintide injection plus food modulated the levels of 10 PCs in the blood (p < 0.05). The levels of 2 PCs in MCI and 12 PCs in AD in the pramlintide challenge were significantly lower than the ones in controls. We found that while some PCs were associated with only Aβ levels, other PCs were associated with both Aβ and t-tau levels. A receiver operating characteristic analysis of the PCs was combined with the Aβ and t-tau data to produce an area under the curve predictive value of 0.9799 between MCI subjects and controls, 0.9794 between AD subjects and controls, and 0.9490 between AD and MCI subjects. A combination of AD biomarkers and a group of PCs post a pramlintide challenge may provide a valuable diagnostic and prognostic test for AD and MCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Female; Humans; Islet Amyloid Polypeptide; Logistic Models; Male; Middle Aged; Phosphatidylcholines; ROC Curve; tau Proteins

A Precision Medicine Model for Targeted NSAID Therapy in Alzheimer's Disease. - O'Bryant, Sid E; Zhang, Fan; Johnson, Leigh A; Hall, James; Edwards, Melissa; Grammas, Paula; Oh, Esther; Lyketsos, Constantine G; Rissman, Robert A (J Alzheimers Dis, 2018)
BACKGROUND: To date, the therapeutic paradigm for Alzheimer's disease (AD) has focused on a single intervention for all patients. However, a large literature in oncology supports the therapeutic benefits of a precision medicine approach to therapy. Here we test a precision-medicine approach to AD therapy. OBJECTIVE: To determine if a baseline, blood-based proteomic companion diagnostic predicts response to NSAID therapy. METHODS: Proteomic assays of plasma from a multicenter, randomized, double-blind, placebo-controlled, parallel group trial, with 1-year exposure to rofecoxib (25 mg once daily), naproxen (220 mg twice-daily) or placebo. RESULTS: 474 participants with mild-to-moderate AD were screened with 351 enrolled into the trial. Using support vector machine (SVM) analyses, 89% of the subjects randomized to either NSAID treatment arms were correctly classified using a general NSAID companion diagnostic. Drug-specific companion diagnostics yielded 98% theragnostic accuracy in the rofecoxib arm and 97% accuracy in the naproxen arm. CONCLUSION: Inflammatory-based companion diagnostics have significant potential to identify select patients with AD who have a high likelihood of responding to NSAID therapy. This work provides empirical support for a precision medicine model approach to treating AD.

Protofibrillar and Fibrillar Amyloid-β Binding Proteins in Cerebrospinal Fluid. - Rahman, M Mahafuzur; Westermark, Gunilla T; Zetterberg, Henrik; Härd, Torleif; Sandgren, Mats (J Alzheimers Dis, 2018)
Aggregation and deposition of misfolded amyloid-β (Aβ) peptide in the brain is central to Alzheimer's disease (AD). Oligomeric, protofibrillar, and fibrillar forms of Aβ are believed to be neurotoxic and cause neurodegeneration in AD, but the toxicity mechanisms are not well understood and may involve Aβ-interacting molecular partners. In a previous study, we identified potential Aβ42 protofibrillar-binding proteins in serum and cerebrospinal fluid (CSF) using an engineered version of Aβ42 (Aβ42CC) that forms protofibrils, but not fibrils. Here we studied binding of proteins to Aβ42 fibrils in AD and non-AD CSF and compared these with protofibrillar Aβ42CC-binding partners. Aβ42 fibrils sequestered 2.4-fold more proteins than Aβ42CC protofibrils. Proteins with selective binding to fibrillar aggregates with low nanomolar affinity were identified. We also found that protofibrillar and fibrillar Aβ-binding proteins represent distinct functional categories. Aβ42CC protofibrils triggered interactions with proteins involved in catalytic activities, like transferases and oxidoreductases, while Aβ42 fibrils were more likely involved in binding to proteoglycans, growth factors and neuron-associated proteins, e.g., neurexin-1, -2, and -3. Interestingly, 10 brain-enriched proteins were identified among the fibril-binding proteins, while protofibril-extracted proteins had more general expression patterns. Both types of Aβ aggregates bound several extracellular proteins. Additionally, we list a set of CSF proteins that might have potential to discriminate between AD and non-AD CSF samples. The results may be of relevance both for biomarker studies and for studies of Aβ-related toxicity mechanisms.

Quality of Life, Care Resource Use, and Costs of Dementia in 8 European Countries in a Cross-Sectional Cohort of the Actifcare Study. - Handels, Ron L H; Sköldunger, Anders; Bieber, Anja; Edwards, Rhiannon Tudor; Gonçalves-Pereira, Manuel; Hopper, Louise; Irving, Kate; Jelley, Hannah; Kerpershoek, Liselot; Marques, Maria J; Meyer, Gabriele; Michelet, Mona; et al. (J Alzheimers Dis, 2018)
BACKGROUND: With 10.5 million people with dementia in Europe and $301 billion associated costs, governments face challenges organizing access to care. OBJECTIVE: To examine the costs related to formal and informal care use and quality of life for people with dementia in eight European countries, and explore the association with unmet needs. METHODS: Cross-sectional data from 451 persons with dementia and their informal caregivers of the Actifcare cohort study were obtained. Formal and informal care use was multiplied by country specific unit prices of services. Needs were measured using the CANE and health-related quality of life (HRQOL) of the person with dementia (both self- and proxy-rated) and informal caregiver's quality of life using EQ-5D-5L, ICECAP-O, DEMQOL-U, and CarerQol utility scores. The association between costs and country, European region, and unmet needs was assessed using multi-level linear regression. RESULTS: Self-rated EQ-5D-5L utility score was higher than proxy-rated (0.84 and 0.71, respectively). Informal caregivers' utility score was 0.84. Across eight countries annual mean costs of formal and informal care were approximately € 17,000. Unmet needs were not associated with annual costs of care, nor with proxy-rated HRQOL, but were associated with self-rated HRQOL. CONCLUSION: We found varying relationships between unmet needs and quality of life, and no association between unmet needs and care costs, although the results were sensitive to various factors. Future research should further investigate the relation between unmet needs, quality of life and costs to generate a better understanding of the effects of (un)timely access to care.

Rare Variants in PLD3 Increase Risk for Alzheimer's Disease in Han Chinese. - Tan, Meng-Shan; Zhu, Jun-Xia; Cao, Xi-Peng; Yu, Jin-Tai; Tan, Lan (J Alzheimers Dis, 2018)
Next-generation sequencing studies had reported that a rare coding variant p.V232M in PLD3 was associated with Alzheimer's disease (AD) and a two-fold increased AD risk in European cohorts. To test whether coding region variants of PLD3 were associated with AD in a large Han Chinese cohort, we performed sequencing to analyze all exons of PLD3, and demonstrated that rare variants p.I163M and c.1020-8G>A conferred considerable risk of late-onset AD (LOAD) in our cohort. Meanwhile, the previously reported p.V232M variant was identified in our AD group. These findings indicate that rare variants of PLD3 may play an important role in LOAD in northern Han Chinese.

Reappraisal of Aβ40 and Aβ42 Peptides Measurements in Cerebrospinal Fluid of Patients with Alzheimer's Disease. - Fiorini, Michele; Bongianni, Matilde; Benedetti, Maria Donata; Monaco, Salvatore; Zanusso, Gianluigi (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers are currently included in the diagnostic criteria for Alzheimer's disease (AD), in particular, decreased concentrations of amyloid-β peptide 1-42 (Aβ42) in the CSF, coupled with increased levels of tau and phosphorylated tau proteins, are supportive of AD diagnosis. To date, the quantification of Aβ42 levels with antibody-dependent immunoassay shows a marked variability among different laboratories and is also affected by different pre-analytical factors, suggesting that part of Aβ42 peptides might be aggregated and thus undetected by antibodies. To bypass an antibody-dependent measurement, we determined the Aβ40 and Aβ42 levels by immunoblot. We analyzed CSF samples from 35 patients with clinical diagnosis of probable AD and from 15 age-matched normal controls; CSF Aβ levels were determined by two different ELISA kits and by immunoblot analysis. Aβ40 levels measured by ELISA were comparable to those obtained by immunoblot, whereas CSF concentrations of Aβ42 measured by ELISA were significantly lower compared to values obtained by immunoblot quantification. Biochemical analysis, following 1D- and 2D-PAGE analysis, showed that the qualitative composition of Aβ peptides in the CSF is similar in AD and controls but different from that of AD brain tissues. Moreover, sedimentation velocity in sucrose gradient of CSF and brain homogenate from AD demonstrated that Aβ42 in CSF is different from Aβ42 in brain in terms of solubility and aggregation state.

Regional White Matter Hyperintensity Influences Grey Matter Atrophy in Mild Cognitive Impairment. - Vipin, Ashwati; Foo, Heidi Jing Ling; Lim, Joseph Kai Wei; Chander, Russell Jude; Yong, Ting Ting; Ng, Adeline Su Lyn; Hameed, Shahul; Ting, Simon Kang Seng; Zhou, Juan; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
The association between cerebrovascular disease pathology (measured by white matter hyperintensities, WMH) and brain atrophy in early Alzheimer's disease (AD) remain to be elucidated. Thus, we investigated how WMH influence neurodegeneration and cognition in prodromal and clinical AD. We examined 51 healthy controls, 35 subjects with mild cognitive impairment (MCI), and 30 AD patients. We tested how total and regional WMH is related to specific grey matter volume (GMV) reductions in MCI and AD compared to controls. Stepwise regression analysis was further performed to investigate the association of GMV and regional WMH volume with global cognition. We found that total WMH volume was highest in AD but showed the strongest association with lower GMV in MCI. Frontal and parietal WMH had the most extensive influence on GMV loss in MCI. Additionally, parietal lobe WMH volume (but not hippocampal atrophy) was significantly associated with global cognition in MCI while smaller hippocampal volume (but not WMH volume) was associated with lower global cognition in AD. Thus, although WMH volume was highest in AD subjects, it had a more pervasive influence on brain structure and cognitive impairment in MCI. Our study thus highlights the importance of early detection of cerebrovascular disease, as its intervention at the MCI stage might potentially slow down neurodegeneration.

Risk of Conversion to Dementia in a Mild Behavioral Impairment Group Compared to a Psychiatric Group and to a Mild Cognitive Impairment Group. - Taragano, Fernando E; Allegri, Ricardo F; Heisecke, Silvina L; Martelli, María I; Feldman, Mónica L; Sánchez, Viviana; García, Virginia A; Tufro, Graciela; Castro, Diego M; Leguizamón, Patricio Perez; Guelar, Verónica; Ruotolo, Eva; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is insufficient available information on behavioral changes in the absence of cognitive impairment as factors increasing the risk of conversion to dementia. OBJECTIVE: To observe and analyze patients with mild behavioral impairment (MBI), mild cognitive impairment (MCI), and a psychiatry group (PG) to compare the risk of progression to dementia. METHODS: From 677 initially assessed ≥60-year-old patients, a series of 348 patients was studied for a five-year period until censoring or conversion to dementia: 96 with MBI, 87 with MCI, and 165 with general psychiatry disorders, including 4 subgroups: Anxiety, Depression, Psychosis and Others. All patients were assessed with clinical, psychiatric, neurological, neuropsychological, and neuroimaging studies. RESULTS: From 348 patients, 126 evolved to dementia (36.2%). Conversion was significantly higher in MBI (71.5%), followed by the MCI-MBI overlap (59.6%) and MCI (37.8%) groups, compared to PG (13.9%) (Log-rank p < 0.001). MCI patients mostly converted to Alzheimer's dementia, while MBI converted to frontotemporal dementia and Lewy body dementia. Patients in PG converted to Lewy body dementia and frontotemporal dementia. CONCLUSION: Conversion to dementia is significantly higher in patients with neuropsychiatric symptoms. The MBI concept generates a new milestone in the refining of diagnosis of neurodegenerative diseases and the possibility of creating neuropsychiatric profiles. Its earlier identification will allow new possibilities for therapeutic intervention.

Role of Blood-Brain Barrier in Alzheimer's Disease. - Cai, Zhiyou; Qiao, Pei-Feng; Wan, Cheng-Qun; Cai, Min; Zhou, Nan-Kai; Li, Qin (J Alzheimers Dis, 2018)
The blood-brain barrier (BBB) is involved in the pathogenesis of Alzheimer's disease (AD). BBB is a highly selective semipermeable structural and chemical barrier which ensures a stable internal environment of the brain and prevents foreign objects invading the brain tissue. BBB dysfunction induces the failure of Aβ transport from brain to the peripheral circulation across the BBB. Especially, decreased levels of LRP-1 (low density lipoprotein receptor-related protein 1) and increased levels of RAGE (receptor for advanced glycation endproducts) at the BBB can cause the failure of Aβ transport. The pathogenesis of AD is related to the BBB structural components, including pericytes, astrocytes, vascular endothelial cells, and tight junctions. BBB dysfunction will trigger neuroinflammation and oxidative stress, then enhance the activity of β-secretase and γ-secretase, and finally promote Aβ generation. A progressive accumulation of Aβ in brain and BBB dysfunction may become a feedback loop that gives rise to cognitive impairment and the onset of dementia. The correlation between BBB dysfunction and tau pathology has been well-reported. Therefore, regulating BBB function may be a new therapeutic target for treating AD.

S-[18F]THK-5117-PET and [11C]PIB-PET Imaging in Idiopathic Normal Pressure Hydrocephalus in Relation to Confirmed Amyloid-β Plaques and Tau in Brain Biopsies. - Leinonen, Ville; Rauramaa, Tuomas; Johansson, Jarkko; Bottelbergs, Astrid; Tesseur, Ina; van der Ark, Peter; Pemberton, Darrel; Koivisto, Anne M; Jääskeläinen, Juha E; Hiltunen, Mikko; Herukka, Sanna-Kaisa; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Detection of pathological tau aggregates could facilitate clinical diagnosis of Alzheimer's disease (AD) and monitor drug effects in clinical trials. S-[18F]THK-5117 could be a potential tracer to detect pathological tau deposits in brain. However, no previous study have correlated S-[18F]THK-5117 uptake in PET with brain biopsy verified tau pathology in vivo. OBJECTIVE: Here we aim to evaluate the association between cerebrospinal fluid (CSF) AD biomarkers, S-[18F]THK-5117, and [11C]PIB PET against tau and amyloid lesions in brain biopsy. METHODS: Fourteen patients with idiopathic normal pressure hydrocephalus (iNPH) with previous shunt surgery including right frontal cortical brain biopsy and CSF Aβ1 - 42, total tau, and P-tau181 measures, underwent brain MRI, [11C]PIB PET, and S-[18F]THK-5117 PET imaging. RESULTS: Seven patients had amyloid-β (Aβ, 4G8) plaques, two both Aβ and phosphorylated tau (Pτ, AT8) and one only Pτ in biopsy. As expected, increased brain biopsy Aβ was well associated with higher [11C]PIB uptake in PET. However, S-[18F]THK-5117 uptake did not show any statistically significant correlation with either brain biopsy Pτ or CSF P-tau181 or total tau. CONCLUSIONS: S-[18F]THK-5117 lacked clear association with neuropathologically verified tau pathology in brain biopsy probably, at least partially, due to off-target binding. Further studies with larger samples of patients with different tau tracers are urgently needed. The detection of simultaneous Aβ and tau pathology in iNPH is important since that may indicate poorer and especially shorter response for CSF shunt surgery compared with no pathology.

Serum C-Peptide, Visfatin, Resistin, and Ghrelin are Altered in Sporadic and GRN-Associated Frontotemporal Lobar Degeneration. - Zanardini, Roberta; Benussi, Luisa; Fostinelli, Silvia; Saraceno, Claudia; Ciani, Miriam; Borroni, Barbara; Padovani, Alessandro; Binetti, Giuliano; Ghidoni, Roberta (J Alzheimers Dis, 2018)
Frontotemporal lobar degeneration (FTLD) is a group of complex neurodegenerative disease characterized by progressive deterioration of the frontal and anterior temporal lobes of the brain resulting in different heterogeneous conditions, mainly characterized by personality changes, behavioral disturbances, such as binge eating, and deficits in language and executive functions. Null mutations in progranulin gene (GRN) are one of the most frequent genetic determinants in familial frontotemporal dementia. Recently, progranulin was recognized as an adipokine involved in diet-induced obesity and insulin resistance revealing its metabolic function. Increasing evidence suggests that neurodegenerative dementias are associated with a higher prevalence of metabolic changes than in the general population. According to these findings, the aim of this study is to investigate putative alterations in markers linked to metabolic functions (i.e., C-peptide, ghrelin, glucose-dependent insulinotropic polypeptide, glucagon-like peptide-1, glucagon, insulin, resistin, and three adipokines as visfatin, leptin, and plasminogen activator inhibitor-1 total) in sporadic and GRN-related FTLD. We found that 1) C-peptide is increased in sporadic and GRN-mutated FTLD patients; in addition, we demonstrated an anticipation of the disease in patients with the highest C-peptide concentrations; 2) visfatin is slightly reduced in the whole FTLD group; 3) resistin, an adipokine involved in inflammatory-related diseases, is specifically increased in FTLD due to GRN null mutations; 4) ghrelin concentration is specifically increased in pre-symptomatic subjects and FTLD patients with GRN mutations. These findings support the hypothesis that alterations in metabolic pattern are involved in FTLD progression highlighting novel putative targets for the development of preventive and personalized therapies.
Keywords: Aged; Biomarkers; C-Peptide; Female; Frontotemporal Lobar Degeneration; Ghrelin; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Mutation; Nicotinamide Phosphoribosyltransferase; Progranulins; Resistin

Sex-Dependent Differences in Spontaneous Autoimmunity in Adult 3xTg-AD Mice. - Kapadia, Minesh; Mian, M Firoz; Michalski, Bernadeta; Azam, Amber B; Ma, Donglai; Salwierz, Patrick; Christopher, Adam; Rosa, Elyse; Zovkic, Iva B; Forsythe, Paul; Fahnestock, Margaret; Sakic, Boris (J Alzheimers Dis, 2018)
The triple-transgenic (3xTg-AD) mouse strain is a valuable model of Alzheimer's disease (AD) because it develops both amyloid-β (Aβ) and tau brain pathology. However, 1-year-old 3xTg-AD males no longer show plaques and tangles, yet early in life they exhibit diverse signs of systemic autoimmunity. The current study aimed to address whether females, which exhibit more severe plaque/tangle pathology at 1 year of age, show similar autoimmune phenomena and if so, whether these immunological changes coincide with prodromal markers of AD pathology, markers of learning and memory formation, and epigenetic markers of neurodegenerative disease. Six-month-old 3xTg-AD and wild-type mice of both sexes were examined for T-cell phenotype (CD3+, CD8+, and CD4+ populations), serological measures (autoantibodies, hematocrit), soluble tau/phospho-tau and Aβ levels, brain-derived neurotrophic factor (BDNF) expression, and expression of histone H2A variants. Although no significant group differences were seen in tau/phospho-tau levels, 3xTg-AD mice had lower brain mass and showed increased levels of soluble Aβ and downregulation of BDNF expression in the cortex. Splenomegaly, depleted CD+ T-splenocytes, increased autoantibody levels and low hematocrit were more pronounced in 3xTg-AD males than in females. Diseased mice also failed to exhibit sex-specific changes in histone H2A variant expression shown by wild-type mice, implicating altered nucleosome composition in these immune differences. Our study reveals that the current 3xTg-AD model is characterized by systemic autoimmunity that is worse in males, as well as transcriptional changes in epigenetic factors of unknown origin. Given the previously observed lack of plaque/tangle pathology in 1-year-old males, an early, sex-dependent autoimmune mechanism that interferes with the formation and/or deposition of aggregated protein species is hypothesized. These results suggest that more attention should be given to studying sex-dependent differences in the immunological profiles of human patients.

Some Methodological Characteristics of Alzheimer-Associated Urine Neuronal Thread Protein Detected by Enzyme-Linked Immunosorbent Assay. - Jin, He; Wang, Rong; Liu, Zhaohui; Jia, Qiang; Wu, Yanchuan; Zhao, Zhiwei; Wang, Yulan; Zhang, Xu (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer-associated neuronal thread protein (AD7c-NTP) has been found to be a candidate biomarker of Alzheimer's disease (AD). OBJECTIVE: To investigate the effects of urine collected time, different preservatives addition, and storage condition on the measurement of urine AD7c-NTP by enzyme-linked immunosorbent assay (ELISA). METHODS: Three hundred urine samples were collected from 20 participants at three time points on five consecutive days. These samples were immediately placed at 4°C and detected within 2 h. The single spot samples of the first day morning were split into eleven duplicate aliquots (a-k) of 1 ml each, (a) without any preservative (untreated), (b) containing boric acid (2 g/L), (c) containing NaHCO3 (5 g/L), (a-c) were detected at six different time points. For the other eight preservative-free samples, (d-g) were stored at -20°C and (h-k) were stored at -70°C, respectively, detected at different time points. All of the results were compared with the baseline urine. RESULTS: The urine AD7c-NTP levels at different time points behaved stably (p > 0.05). Urine samples without any preservative increased over time, and compared with the NaHCO3 addition group, boric acid addition group behaved stably. Samples stored at -20°C and -70°C led to an obviously false positive. CONCLUSIONS: AD7c-NTP can be tested using random urine instead of the first morning urine. If the specimen cannot be tested in time, boric acid appears to be an acceptable preservative with storage at 4°C, freezing is not recommended.

Spatial Navigation in the Elderly with Alzheimer's Disease: A Cross-Sectional Study. - Zanco, Marcos; Plácido, Jessica; Marinho, Valeska; Ferreira, José Vinicius; de Oliveira, Felipe; Monteiro-Junior, Renato; Barca, Maria; Engedal, Knut; Laks, Jerson; Deslandes, Andrea (J Alzheimers Dis, 2018)
BACKGROUND: Spatial navigation is a fundamental cognitive ability that allows an individual to maintain independence by facilitating the safe movement from one place to another. It emerges as one of the first deficits in patients with Alzheimer's disease (AD). OBJECTIVE: To compare spatial navigation performance in the healthy elderly and AD patients through use of the Floor Maze Test (FMT)- an easy-to-apply two-dimensional (2D) maze- and determine which cognitive and functional capacities were associated with performance in this task. METHODS: The FMT was administered to 24 AD patients and 36 healthy controls. Spatial navigation was evaluated through the FMT. Functional capacity was evaluated through the Senior Fitness Test battery of tests. Cognitive functions were evaluated through the Mini-Mental State Examination (MMSE), verbal fluency, digit span test, and the Rey Auditory Verbal Learning Test (RAVLT). RESULTS: The group with AD was significantly slower and presented more errors at all stages of the FMT. Planning Time (PT) performance was associated with cardiorespiratory resistance (Step test) and delayed memory according to the RAVLT (R2 = 0.395, p < 0.001). Performance in the Immediate Maze Time (IMT) and Delayed Maze Time (DMT) was associated with global cognitive status (MMSE) (R2 = 0.509) and delayed memory (R2 = 0.540). CONCLUSION: Patients with AD present significant spatial navigation deficits. Their performance on the FMT is influenced by cardiorespiratory capacity, memory, and global cognitive function. As exercise helps to improve executive function and functional capacity, future intervention studies should be carried out to analyze the possible effects of physical exercise on spatial navigation.

Stereological Investigation of the Effects of Treadmill Running Exercise on the Hippocampal Neurons in Middle-Aged APP/PS1 Transgenic Mice. - Chao, Fenglei; Jiang, Lin; Zhang, Yi; Zhou, Chunni; Zhang, Lei; Tang, Jing; Liang, Xin; Qi, Yingqiang; Zhu, Yanqing; Ma, Jing; Tang, Yong (J Alzheimers Dis, 2018)
The risk of cognitive decline during Alzheimer's disease (AD) can be reduced if physical activity is maintained; however, the specific neural events underlying this beneficial effect are still uncertain. To quantitatively investigate the neural events underlying the effect of running exercise on middle-aged AD subjects, 12-month-old male APP/PS1 mice were randomly assigned to a control group or running group, and age-matched non-transgenic littermates were used as a wild-type group. AD running group mice were subjected to a treadmill running protocol (regular and moderate intensity) for four months. Spatial learning and memory abilities were assessed using the Morris water maze. Hippocampal amyloid plaques were observed using Thioflavin S staining and immunohistochemistry. Hippocampal volume, number of neurons, and number of newborn cells (BrdU+ cells) in the hippocampus were estimated using stereological techniques, and newborn neurons were observed using double-labelling immunofluorescence. Marked neuronal loss in both the CA1 field and dentate gyrus (DG) and deficits in both the neurogenesis and survival of new neurons in the DG of middle-aged APP/PS1 mice were observed. Running exercise could improve the spatial learning and memory abilities, reduce amyloid plaques in the hippocampi, delay neuronal loss, induce neurogenesis, and promote the survival of newborn neurons in the DG of middle-aged APP/PS1 mice. Exercise-induced protection of neurons and adult neurogenesis within the DG might be part of the important structural basis of the improved spatial learning and memory abilities observed in AD mice.

Subjective Cognitive Decline, Objective Cognition, and Depression in Older Hispanics Screened for Memory Impairment. - Zlatar, Zvinka Z; Muniz, Martha C; Espinoza, Sarah G; Gratianne, Roberto; Gollan, Tamar H; Galasko, Douglas; Salmon, David P (J Alzheimers Dis, 2018)
Subjective cognitive decline (SCD) is common in older adults and may be an early marker of future cognitive decline. Research suggest that SCD is more closely related to concurrent symptoms of depression than to objective cognitive performance in non-Hispanic Whites, but it is unknown whether the associations of SCD, cognition, and depression manifest differently in Hispanic older adults. We examined if SCD is associated with objective cognitive performance or with depression symptoms in 145 Hispanic individuals ages 60 or older referred by community health clinics for screening of cognitive complaints. All participants lived near the U.S.-Mexico border, spoke Spanish only, or were Spanish-English bilingual. Memory-only and global cognitive composites were created from scores on Spanish versions of several neuropsychological tests. The Geriatric Depression Scale (GDS) and a five-item SCD questionnaire developed by our group were also completed. Multiple regression analyses showed no significant associations between SCD and memory or global cognitive composite scores after adjusting for age, sex, education, and GDS score. In contrast, there was a significant association between GDS and SCD after adjusting for age, sex, education, global and memory composite scores. Findings suggest that SCD does not accurately reflect current cognitive status in older Hispanics who present to their primary care physician with cognitive complaints. Clinicians should interpret SCD in this population within the context of information about symptoms of depression. Longitudinal research is needed in older Hispanics to better characterize SCD in this population and to determine if it can predict future cognitive decline.

Subjective Cognitive Decline Prediction of Mortality: Results from the Einstein Aging Study. - Katz, Mindy J; Wang, Cuiling; Derby, Carol A; Lipton, Richard B; Zimmerman, Molly E; Sliwinski, Martin J; Rabin, Laura A (J Alzheimers Dis, 2018)
BACKGROUND: The relation of pre-dementia stages to mortality has not been fully explored. Previous work examining subjective cognitive decline (SCD) and mortality is limited and mixed regarding methods used and consistency of findings. OBJECTIVE: To examine SCD and mortality in a longitudinal, community-based cohort, using item response theory (IRT) methodology to form a composite SCD measure. Also, to assess whether this relationship was independent of clinical cognitive status. METHODS: The Einstein Aging Study is a diverse longitudinal cohort of adults aged ≥70. SCD items were extracted from baseline CERAD questionnaires and a composite score was formed using IRT methodology. A total of 1,741 participants with complete data were clinically diagnosed as cognitively normal, or as having amnestic mild cognitive impairment (aMCI), nonamnestic mild cognitive impairment (naMCI), or dementia. 645 deaths occurred over a period of 8,912 person-years of follow-up. Cox proportional hazard models predicted time to death adjusting for covariates. RESULTS: A one standard deviation unit increase in level of SCD was associated with >20% higher risk of mortality. However, when models were adjusted for clinical cognitive status, the association was no longer significant. Both dementia and aMCI predicted mortality. Furthermore, when analyses focused only on those without cognitive impairment, SCD level did not predict mortality. CONCLUSIONS: The association of SCD with mortality may be due to the association of SCD with clinical cognitive status. Thus, SCD may be used as a community-based screen to initially identify those with cognitive impairment who may be at greatest risk for death.

Subtypes Based on Neuropsychological Performance Predict Incident Dementia: Findings from the Rush Memory and Aging Project. - Zammit, Andrea R; Muniz-Terrera, Graciela; Katz, Mindy J; Hall, Charles B; Ezzati, Ali; Bennett, David A; Lipton, Richard B (J Alzheimers Dis, 2018)
BACKGROUND: In a previous report, we used latent class analysis (LCA) to identify natural subgroups of older adults in the Einstein Aging Study (EAS) based on neuropsychological performance. These subgroups differed in demographics, genetic profile, and prognosis. Herein, we assess the generalizability of these findings to an independent sample, the Rush Memory and Aging Project (MAP), which used an overlapping, but distinct neuropsychological battery. OBJECTIVE: Our aim was to identify the association of natural subgroups based on neuropsychological performance in the MAP cohort with incident dementia and compare them with the associations identified in the EAS. METHODS: MAP is a community-dwelling cohort of older adults living in the northeastern Illinois, Chicago. Latent class models were applied to baseline scores of 10 neuropsychological measures across 1,662 dementia-free MAP participants. Results were compared to prior findings from the EAS. RESULTS: LCA resulted in a 5-class model: Mixed-Domain Impairment (n = 71, 4.3%), Memory-specific-Impairment (n = 274, 16.5%), Average (n = 767, 46.1%), Frontal Impairment (n = 222, 13.4%), and a class of Superior Cognition (n = 328, 19.7%). Similar to the EAS, the Mixed-Domain Impairment, the Memory-Specific Impairment, and the Frontal Impairment classes had higher risk of incident Alzheimer's disease when compared to the Average class. By contrast, the Superior Cognition had a lower risk of Alzheimer's disease when compared to the Average class. CONCLUSIONS: Natural cognitive subgroups in MAP are similar to those identified in EAS. These similarities, despite study differences in geography, sampling strategy, and cognitive tests, suggest that LCA is capable of identifying classes that are not limited to a single sample or a set of cognitive tests.

Targeting Alzheimer's Disease at the Right Time and the Right Place: Validation of a Personalized Approach to Diagnosis and Treatment. - Gauthier, Serge; Ng, Kok Pin; Pascoal, Tharick A; Zhang, Hua; Rosa-Neto, Pedro (J Alzheimers Dis, 2018)
Cautious optimism is appropriate for a near future (five years) time frame for a number of drugs acting on the different pathophysiological components of Alzheimer's disease (amyloid deposition, tau hyperphosphorylation, neuroinflammation, vascular changes, to name the most important known so far). Since the relative weight of these components will be different between individuals and will even change over time for each individual, a 'one drug fit for all' approach is no longer defensible. Precision medicine using biomarkers in the diagnosis and treatment of Alzheimer's disease is the new strategy.

Tauopathies: Mechanisms and Therapeutic Strategies. - Tan, Chen-Chen; Zhang, Xiao-Yan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2018)
Tauopathies are morphologically, biochemically, and clinically heterogeneous neurodegenerative diseases defined by the accumulation of abnormal tau proteins in the brain. There is no effective method to prevent and reverse the tauopathies, but this gloomy picture has been changed by recent research advances. Evidences from genetic studies, experimental animal models, and molecular and cell biology have shed light on the main mechanisms of the diseases. The development of radiology and biochemistry, especially the development of PET imaging, will provide important biomarkers for the clinical diagnosis and treatment. Given the central role of tau in tauopathies, many treatments have constantly emerged, including targeting phosphorylation, targeting aggregation, increasing microtubule stabilization, tau immunization, clearance of tau, anti-inflammatory treatment, and other therapeutics. There is still a long way to go before we obtain drug therapy targeted at multifactor mechanisms.
Keywords: Animals; Biomarkers; Brain; Disease Models, Animal; Humans; Neuroimaging; Phosphorylation; Positron-Emission Tomography; tau Proteins; Tauopathies

Testing Hippocampal Memory in Prodromal Dementia with Lewy Bodies. - Bussè, Cinzia; Caffarra, Paolo; Rossi, Alice; Zorzi, Giovanni; Fragiacomo, Federica; Camporese, Giulia; Pompanin, Sara; Di Bernardo, Gian Antonio; Cagnin, Annachiara (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding test (FCSRT) was used to assess memory in 19 patients with prodromal dementia with Lewy bodies (DLB) and 25 Alzheimer's disease (AD) patients. DLB scored better than AD in selective measures of the FCSRT: immediate total recall (p = 0.01) and index of sensitivity of cueing (p = 0.001), while free delayed and total memory scores were similarly impaired. The index of sensitivity of cueing held a sensitivity of 76% and specificity of 79% in distinguishing DLB. FCSRT could help in disentangling hippocampal memory deficits from memory impairment due to ineffective recall strategies.

TRPC1 Null Exacerbates Memory Deficit and Apoptosis Induced by Amyloid-β. - Li, Mengzhu; Liu, Enjie; Zhou, Qiuzhi; Li, Shihong; Wang, Xin; Liu, Yanchao; Wang, Lin; Sun, Dongsheng; Ye, Jinwang; Gao, Yuan; Yang, Xifei; Liu, Jianjun; et al. (J Alzheimers Dis, 2018)
The transient receptor potential cation (TRPC) channels are widely expressed in nervous system but their functions remain largely unclear. Here, we found that TRPC1 deletion did not affect learning and memory in physiological conditions, while it aggravated learning and memory deficits induced by amyloid-β (Aβ), the major component of the senile plaques observed in the brains of Alzheimer's disease (AD). Further studies demonstrated that TRPC1 deletion did not affect cell apoptosis in physiological condition, but it exacerbated the Aβ-induced cell death in mouse hippocampus. Moreover, the level of TRPC1 was decreased in AD cell and mouse models, and upregulation of TRPC1 decreased Aβ levels with attenuation of apoptosis in the cells stably overexpressing amyloid-β protein precursor (AβPP). Finally, the transmembrane domain of TRPC1 could bind to AβPP and thus decreased Aβ production. These findings indicate that loss of TRPC1 exacerbates Aβ-induced memory deficit and cell apoptosis, though it does not impair cognitive function or induce cell death in physiological conditions.

TTC7 and Hyccin Regulate Neuronal Aβ42 Accumulation and its Associated Neural Deficits in Aβ42-Expressing Drosophila. - Sun, Minghao; Zhao, Yinghui; Han, Men; Zhang, Baozhu; Zhang, Xiao; Zhang, Qichao; Lim, Nastasia K-H; Wang, Wen-An; Huang, Fu-De (J Alzheimers Dis, 2018)
Neuronal amyloid-β (Aβ) accumulation plays an important role in the pathogenesis of Alzheimer's disease (AD). The conformation and toxicity of Aβ are regulated by lipids on the plasma membrane. Previously, we found downregulation of Rolling Blackout (RBO) or phosphatidylinositol-4-kinase type IIIα (PI4KIIIα) reduces neuronal Aβ accumulation and associated neural deficits in a Drosophila model expressing Aβ42. In mammals, the homologs of RBO and PI4KIIIα were reported to form a plasma membrane-localized complex with a scaffold protein TTC7 and cytosolic protein Hyccin/FAM126A to tightly control the plasmalemmal level of phosphatidylinositol-4-phosphate. Here, we show genetic downregulation of Drosophila TTC7 and Hyccin also reduces neuronal Aβ accumulation and associated synaptic and motor defects as well as premature death in Aβ42-expressing flies, while overexpression of TTC7 and Hyccin produced the opposite effect. These results, together with our previous study, demonstrate that RBO/TTC7/PI4KIIIα/Hyccin regulate neuronal Aβ accumulation and associated neural deficits in the Drosophila model, further supporting the RBO/Efr3-PI4KIIIα complex as a potential therapeutic target for AD.

Urine-Based Biomarkers for Alzheimer's Disease Identified Through Coupling Computational and Experimental Methods. - Yao, Fang; Hong, Xiaoyu; Li, Shuiming; Zhang, Yan; Zhao, Qing; Du, Wei; Wang, Yong; Ni, Jiazuan (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder contributing to nearly 70% of dementia cases. However, no diagnostic protein biomarkers are available in urine. In this study, we combined computational and experimental methods to identify urinary biomarkers for AD. First, by analyzing brain tissue-based gene expression data of AD, 2,754 differentially expressed genes were identified, 559 of which were predicted to encode urine-excretory proteins that might act as candidate protein biomarkers of AD. GO enrichment analyses implied that they were mainly involved in microtubule-based process, myelin sheath, and calcium ion binding, suggesting that they might be associated with AD pathogenesis. In order to verify these proteins in urine, an iTRAQ experiment was carried out to analyze urine samples from AD patients and healthy controls, and 15 proteins were detected. Based on the expression changes of these proteins, 4 proteins were chosen for further validation by ELISA experiment, and SPP1, GSN, and IGFBP7 were found to be differentially expressed in the urine of AD patients. After a literature survey, we found that they were involved in AD pathophysiology and might serve as new urine biomarkers for AD. To our knowledge, this is the first time that urine biomarkers for AD were identified by combining computational and experimental methods. Furthermore, this is the first time SPP1, GSN, and IGFBP7 have been reported as potential urine protein biomarkers for AD. Therefore, our findings might provide significant guidance for finding early biomarkers of AD in urine.

Validation of the Delayed Matching-to-Sample Task 48 (DMS48) in Elderly Chinese. - Feng, Xueyan; Zhou, Aihong; Liu, Zhixin; Li, Fangyu; Wei, Cuibai; Zhang, Guili; Jia, Jianping (J Alzheimers Dis, 2018)
BACKGROUND: Delayed Matching-to-Sample Task 48 (DMS48), a brief tool measuring visual recognition memory, is valid to identify the early stage of Alzheimer's disease (AD) in Caucasians. However, little data is available in Chinese. OBJECTIVE: To develop norms and optimal cutoff points for the DMS48 in Chinese elders. METHODS: A cross-sectional study was conducted in seven memory clinics from five cities across China. DMS48 was applied to 369 Chinese aged 50 or older (138 cognitively normal [CN], 112 mild cognitive impairment due to AD (MCI-A), and 119 mild AD dementia). The demographic factors which influence DMS48 scores were investigated and the norms were established considering those factors. Receiver operating characteristic (ROC) analysis was used to determine the optimal cutoff points. RESULTS: Age was shown to influence DMS48 scores (r = -0.36, p < 0.05), and we presented the age-stratified normative data for the DMS48. The optimal cutoff point is 42/43 for identifying cognitive impairment (MCI-A and AD dementia) against CN (sensitivity 97.80% and specificity 89.13%) and MCI-A against CN (sensitivity 86.60% and specificity 94.20%). A cutoff of 39/40 obtained good sensitivity (100.00%) and specificity (94.90%) in discriminating AD dementia from CN. The age-stratified optimal cutoff points for identifying MCI-A were 43/44 for individuals aged 50 to 59 years old, 42/43 for 60 to 69 years old, 41/42 for 70 to 79 years old, and 40/41 for 80 or older, respectively (sensitivity 84.80% and specificity 95.70%). CONCLUSION: This study proved that DMS48 is of good validation in screening MCI-A in elderly Chinese.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; ROC Curve; Sensitivity and Specificity; Severity of Illness Index

Vascular Cognitive Impairment and the Gut Microbiota. - Li, Sinian; Shao, Yiming; Li, Kanglan; HuangFu, Changmei; Wang, Wenjie; Liu, Zhou; Cai, Zhiyou; Zhao, Bin (J Alzheimers Dis, 2018)
Vascular cognitive impairment (VCI), the second most common cause of dementia in elderly people, is a term that refers to all forms of cognitive disorders that can be attributed to cerebrovascular disease such as manifestations of discrete infarctions, brain hemorrhages, and white matter lesions. The gut microbiota (GM) has emerged recently as an essential player in the development of VCI. The GM may affect the brain's physiological, behavioral, and cognitive functions through the brain-gut axis via neural, immune, endocrine, and metabolic pathways. Therefore, microbiota dysbiosis may mediate or affect atherosclerosis, cerebrovascular disease, and endothelial dysfunction, which are the predominant risk factors for VCI. Moreover, the composition of the GM includes the bacterial component lipopolysaccharides and their metabolic products including trimethylamine-N-oxide and short-chain fatty acids. These products may increase the permeability of the intestinal epithelium, leading to systemic immune responses, low-grade inflammation, and altered signaling pathways that are associated with the pathogenesis of VCI. In this review, we discuss the proposed mechanisms of the GM in the maintenance of VCI and how it is implicated in acquired metabolic diseases, particularly in VCI regulation.

Voxel-Based Acetylcholinesterase PET Study in Early and Late Onset Alzheimer's Disease. - Hirano, Shigeki; Shinotoh, Hitoshi; Shimada, Hitoshi; Ota, Tsuneyoshi; Sato, Koichi; Tanaka, Noriko; Zhang, Ming-Rong; Higuchi, Makoto; Fukushi, Kiyoshi; Irie, Toshiaki; Kuwabara, Satoshi; Suhara, Tetsuya (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by chronic progressive cognitive decline and displays underlying brain cholinergic dysfunction, providing a rationale for treatment with cholinomimetic medication. The clinical presentations and courses of AD patients may differ by age of onset. OBJECTIVE: The objective of the present study was to illustrate the regional differences of brain acetylcholinesterase (AChE) activity as quantified by N-[11C]methylpiperidinyl-4-acetate ([11C]MP4A) and PET using parametric whole brain analysis and clarify those differences as a function of age. METHODS: 22 early onset AD (EOAD) with age at onset under 65, the remaining 26 as late onset AD (LOAD), and 16 healthy controls (HC) were enrolled. Voxel-based AChE activity estimation of [11C]MP4A PET images was conducted by arterial input and unconstrained nonlinear least-squares method with subsequent parametrical analyses. Statistical threshold was set as Family Wise Error corrected, p-value <0.05 on cluster-level and cluster extent over 30 voxels. RESULTS: Voxel-based group comparison showed that, compared to HC, both EOAD and LOAD showed cortical AChE decrement in parietal, temporal, and occipital cortices, with wider and stringent cortical involvement in the EOAD group, most prominently demonstrated in the temporal region. There was no significant correlation between age and regional cerebral AChE activity except for a small left superior temporal region in the AD group (Brodmann's area 22, Zmax = 5.13, 396 voxels), whereas no significant cluster was found in the HC counterpart. CONCLUSION: Difference in cortical cholinergic dysfunction between EOAD and LOAD may shed some light on the cholinomimetic drug efficacy in AD.

Which Risk Factors Causally Influence Dementia? A Systematic Review of Mendelian Randomization Studies. - Kuźma, Elżbieta; Hannon, Eilis; Zhou, Ang; Lourida, Ilianna; Bethel, Alison; Levine, Deborah A; Lunnon, Katie; Thompson-Coon, Jo; Hyppönen, Elina; Llewellyn, David J (J Alzheimers Dis, 2018)
BACKGROUND: Numerous risk factors for dementia are well established, though the causal nature of these associations remains unclear. OBJECTIVE: To systematically review Mendelian randomization (MR) studies investigating causal relationships between risk factors and global cognitive function or dementia. METHODS: We searched five databases from inception to February 2017 and conducted citation searches including MR studies investigating the association between any risk factor and global cognitive function, all-cause dementia or dementia subtypes. Two reviewers independently assessed titles and abstracts, full-texts, and study quality. RESULTS: We included 18 MR studies investigating education, lifestyle factors, cardiovascular factors and related biomarkers, diabetes related and other endocrine factors, and telomere length. Studies were of predominantly good quality, however eight received low ratings for sample size and statistical power. The most convincing causal evidence was found for an association of shorter telomeres with increased risk of Alzheimer's disease (AD). Causal evidence was weaker for smoking quantity, vitamin D, homocysteine, systolic blood pressure, fasting glucose, insulin sensitivity, and high-density lipoprotein cholesterol. Well-replicated associations were not present for most exposures and we cannot fully discount survival and diagnostic bias, or the potential for pleiotropic effects. CONCLUSIONS: Genetic evidence supported a causal association between telomere length and AD, whereas limited evidence for other risk factors was largely inconclusive with tentative evidence for smoking quantity, vitamin D, homocysteine, and selected metabolic markers. The lack of stronger evidence for other risk factors may reflect insufficient statistical power. Larger well-designed MR studies would therefore help establish the causal status of these dementia risk factors.

White Matter Hyperintensity Predicts the Risk of Incident Cognitive Decline in Community Dwelling Elderly. - Ding, Ding; Xiong, Yunyun; Zhao, Qianhua; Guo, Qihao; Chu, Shuguang; Chu, Winnie W C; Luo, Jianfeng; Liang, Xiaoniu; Zheng, Li; Hong, Zhen; Wong, Lawrence K S; Mok, Vincent C T (J Alzheimers Dis, 2018)
BACKGROUND: Unlike western countries, data on white matter hyperintensity (WMH) in community dwelling elderly in Asian population is very limited. OBJECTIVE: To examine the relation between baseline WMH burden and the risk of incident cognitive decline in a community-based cohort with Chinese-dwelling elderly. METHODS: We prospectively evaluated the incident cognitive decline for 226 participants in the Shanghai Aging Study. Baseline WMH severity was visually rated by the age-related white matter changes (ARWMC) scale based on MRI. Cox proportional hazards regression model was used to estimate the relative risk (RR) of total ARWMC scale, global ARWMC score, presence of lacune and microbleed, for incident cognitive decline by adjusting potential confounders. RESULTS: Forty subjects were identified with incident cognitive decline (new onset 34 mild cognitive impairment and 6 dementia) during a median duration of 6 years follow-up. The incidence of cognitive decline was 3.0 (95% confidence interval [CI] 2.2-4.1) per 100 person-years. Increasing total ARWMC scale [RR1.21 (95% CI 1.06-1.39), p = 0.004)], confluent WMH [RR3.16 (95% CI 1.50-6.64), p = 0.002), and presence of lacunes [RR 2.73 (95% CI 1.21-6.15)] at baseline were independent predictors of incident cognitive decline. CONCLUSION: Our study demonstrated that confluent WMH may increase the risk of incident cognitive decline by 3 folds in community dwelling subjects. Small vessel disease may cause heavy burden of cognitive impairment in the elderly in China.
Keywords: Aged; China; Cognitive Dysfunction; Female; Humans; Independent Living; Kaplan-Meier Estimate; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; White Matter

A 9-microRNA Signature in Serum Serves as a Noninvasive Biomarker in Early Diagnosis of Alzheimer's Disease. - Guo, Rui; Fan, Gang; Zhang, Jian; Wu, Chunxiao; Du, Yifeng; Ye, Hui; Li, Zhang; Wang, Lili; Zhang, Zhihui; Zhang, Lu; Zhao, Yueran; Lu, Zhiming (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common type of age-related neurodegenerative disorder; nevertheless, nowadays there are no reliable biomarkers or non-invasive techniques available for its early detection. Recent studies have indicated that the circulating level profiles of microRNAs (miRNAs) have the potential to be used as valuable biomarkers for diagnosis, staging, and progress monitoring of various diseases. Here we report a novel 9-miRNA signature (hsa-miR-26a-5p, hsa-miR-181c-3p, hsa-miR-126-5p, hsa-miR-22-3p, hsa-miR-148b-5p, hsa-miR-106b-3p, hsa-miR-6119-5p, hsa-miR-1246, and hsa-miR-660-5p) that can be utilized as biomarker for detecting AD. We respectively profiled the serum miRNAs from 19 AD patients and 9 healthy control (HC) participants using the Next-Generation Sequencing (NGS). The NGS results were validated by quantitative real-time polymerase chain reaction (qRT-PCR) on a larger cohort of 121 AD and 86 HC cases. All the patients were divided into three groups (mild, moderate, and severe AD) based on the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating (CDR). Our research indicates that abnormal expression of distinct serum miRNAs occurs at different stages of AD. The difference of the area under the receiver operator characteristics curve (AUC) between the AD and the HC is between 70% and 85%. Among the 9 miRNAs, hsa-miR-22-3p has the best sensitivity (81.8%) and specificity (70.9%). The miRNA-panel is more valuable for AD diagnosis. The data suggest that the differentially expressed serum miRNAs could be used as biomarkers to improve the diagnosis of AD, particularly at the early stage, and to classify its clinical stages.

Abnormalities of Cerebral Deep Medullary Veins on 7 Tesla MRI in Amnestic Mild Cognitive Impairment and Early Alzheimer's Disease: A Pilot Study. - Bouvy, Willem H; Kuijf, Hugo J; Zwanenburg, Jaco J M; Koek, Huiberdina L; Kappelle, L Jaap; Luijten, Peter R; Ikram, M Kamran; Biessels, Geert Jan (J Alzheimers Dis, 2017)
Cerebral small vessel disease (SVD) contributes to cognitive impairment and dementia. SVD may affect veins, but veins are difficult to detect with 1.5 and 3T MRI. We compared deep medullary veins (DMVs) visualized on 7T-MRI between patients with early Alzheimer's disease (eAD; n = 17) or amnestic MCI (aMCI; n = 12) and controls (n = 40). The number and density of DMVs was similar in patients and controls, but tortuosity was higher in eAD (Cohen's d = 0.7, 95% CI: 0.1-1.2, p = 0.02) and aMCI (Cohen's d = 0.8, 95% CI: 0.2-1.5, p = 0.01), independent of brain atrophy. Venous changes provide a new perspective on vascular involvement in dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Brain; Cerebral Small Vessel Diseases; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male

Aerosol Delivery of Curcumin Reduced Amyloid-β Deposition and Improved Cognitive Performance in a Transgenic Model of Alzheimer's Disease. - McClure, Richard; Ong, Henry; Janve, Vaibhab; Barton, Shawn; Zhu, Meiying; Li, Bo; Dawes, Mary; Jerome, W Gray; Anderson, Adam; Massion, Pierre; Gore, John C; Pham, Wellington (J Alzheimers Dis, 2017)
We report a novel approach for the delivery of curcumin to the brain via inhalation of the aerosol for the potential treatment of Alzheimer's disease. The percentage of plaque fraction in the subiculum and hippocampus reduced significantly when young 5XFAD mice were treated with inhalable curcumin over an extended period of time compared to age-matched nontreated counterparts. Further, treated animals demonstrated remarkably improved overall cognitive function, no registered systemic or pulmonary toxicity associated with inhalable curcumin observed during the course of this work.

The Alteration of ZiBuPiYin Recipe on Proteomic Profiling of Forebrain Postsynaptic Density of db/db Mice with Diabetes-Associated Cognitive Decline. - Chen, Jing; Zhan, Libin; Lu, Xiaoguang; Xiao, Chi; Sun, Nijing (J Alzheimers Dis, 2017)
Diabetes-associated cognitive decline (DACD) is a brain injury induced by diabetes mellitus, with cognitive impairment as the major symptom. Growing evidence has revealed that DACD is correlated with disruptions in synapses involved in cognition. Within synapses, more specifically in areas of postsynaptic density (PSD), there is a high concentration of proteins that receive and transduce synaptic information. In the present study, to identify the differentially expressed PSD proteins among DACD mice, ZiBuPiYin recipe (ZBPYR)-treated DACD mice and control mice, we applied isobaric tags for relative and absolute quantitation (iTRAQ) with LC-MS/MS technology, by which three biological replicates and three technical replicates were examined. A total of 24 and 23 differentially expressed proteins were observed in control versus DACD mice and in DACD versus ZBPYR-treated DACD mice, respectively. Notably, we found 'Protein processing in endoplasmic reticulum' and 'PI3K-Akt signaling pathway' might be impaired in DACD pathogenesis, while Growth factor receptor-bound protein 2 might be a crucial protein as a molecular target of the neuroprotective effects of ZBPYR. To our knowledge, this is the first study to provide a reference proteome map for DACD and ZBPYR-treated DACD mouse forebrain PSD to aid understanding the underlying mechanisms of DACD and ZBPYR.

Alterations in the Balance of Amyloid-β Protein Precursor Species in the Cerebrospinal Fluid of Alzheimer's Disease Patients. - Lopez-Font, Inmaculada; Boix, Claudia P; Zetterberg, Henrik; Blennow, Kaj; Sáez-Valero, Javier (J Alzheimers Dis, 2017)
We recently demonstrated that soluble forms of the amyloid-β protein precursor (sAβPP) assemble into multimeric complexes in cerebrospinal fluid (CSF), which contributes to the underestimation of specific sAβPP species when assessed by ELISA. To circumvent this issue, we analyzed by SDS-PAGE large fragments of sAβPP and their variants in the CSF from Alzheimer's disease (AD; n = 20) and control (n = 20) subjects, probing with specific antibodies against particular domains. Similar levels of sAβPPα and sAβPPβ protein were found in CSF samples from AD and controls, yet there appeared to be a shift in the balance of the soluble full-length AβPP (sAβPPf) species in AD samples, with a decrease in the proportion of the lower (∼100 kDa) band relative to the upper (∼120 kDa) band. Similar differences were observed in the contribution of the major KPI-immunoreactive AβPP species. CSF samples also displayed differences in the correlations of AβPP species with classical AD biomarkers, particularly with respect to the Aβ42 peptide. The differences reveal alterations that probably reflect pathophysiological changes in the brain.

Altered Gut Microbiota in a Mouse Model of Alzheimer's Disease. - Zhang, Ling; Wang, Ying; Xiayu, Xia; Shi, Changhua; Chen, Wei; Song, Nan; Fu, Xinjing; Zhou, Rui; Xu, Yan-Feng; Huang, Lan; Zhu, Hua; Han, Yunlin; et al. (J Alzheimers Dis, 2017)
The topic of gut microbiota is currently attracting considerable interest as a potential factor in Alzheimer's disease (AD). However, the extent and time course of alterations in the gut microbiota, and their effects on AD pathology remain uncertain. Herein, we compared the fecal microbiomes and fecal short chain fatty acid composition (SCFAs) between wild-type and AD model mice at different ages under strictly controlled specific pathogen free conditions, and also conducted microscopic investigations of intestinal structures. Our results showed that the microbiota composition and diversity were perturbed and the level of SCFAs was reduced in AD mice, predicting alterations in more than 30 metabolic pathways, which may be associated with amyloid deposition and ultrastructural abnormalities in AD mouse intestine. These findings indicate that AD pathology might not only affect brain function directly, but also exacerbate cognitive deficits through reducing the level of SCFAs via alterations of gut microbiota induced by intestinal amyloid deposition. Our data may support a role of gut microbiota, and suggest a novel route for therapeutic intervention in AD.

Alzheimer's Disease-Associated Cerebrospinal Fluid (CSF) Biomarkers do not Correlate with CSF Volumes or CSF Production Rate. - Edsbagge, Mikael; Andreasson, Ulf; Ambarki, Khalid; Wikkelsø, Carsten; Eklund, Anders; Blennow, Kaj; Zetterberg, Henrik; Tullberg, Mats (J Alzheimers Dis, 2017)
BACKGROUND: Neuropathologically, Alzheimer's disease (AD) is characterized by accumulation of a 42 amino acid peptide called amyloid-β (Aβ42) in extracellular senile plaques together with intraneuronal inclusions of hyperphosphorylated tau protein in neurofibrillary tangles and neuronal degeneration. These changes are reflected in the cerebrospinal fluid (CSF), the volumes and production rates of which vary considerably between individuals, by reduced concentration of Aβ42, increased concentration of phosphorylated tau (P-tau) protein, and increased concentration of total tau (T-tau) protein, respectively. OBJECTIVE: To examine the outstanding question if CSF concentrations of AD associated biomarkers are influenced by variations in CSF volumes, CSF production rate, and intracranial pressure in healthy individuals. METHODS: CSF concentrations of Aβ42, P-tau, and T-tau, as well as a number of other AD-related CSF biomarkers were analyzed together with intracranial subarachnoid, ventricular, and spinal CSF volumes, as assessed by magnetic resonance imaging volumetric measurements, and CSF production rate in 19 cognitively normal healthy subjects (mean age 70.6, SD 3.6 years). RESULTS: Negative correlations were seen between the concentrations of three CSF biomarkers (albumin ratio, Aβ38, and Aβ40), and ventricular CSF volume, but apart from this finding, no significant correlations were observed. CONCLUSION: These results speak against inter-individual variations in CSF volume and production rate as important confounds in the AD biomarker research field.

Amylin Enhances Amyloid-β Peptide Brain to Blood Efflux Across the Blood-Brain Barrier. - Mohamed, Loqman A; Zhu, Haihao; Mousa, Youssef M; Wang, Erming; Qiu, Wei Qiao; Kaddoumi, Amal (J Alzheimers Dis, 2017)
Findings from Alzheimer's disease (AD) mouse models showed that amylin treatment improved AD pathology and enhanced amyloid-β (Aβ) brain to blood clearance; however, the mechanism was not investigated. Using the Tg2576 AD mouse model, a single intraperitoneal injection of amylin significantly increased Aβ serum levels, and the effect was abolished by AC253, an amylin receptor antagonist, suggesting that amylin effect could be mediated by its receptor. Subsequent mechanistic studies showed amylin enhanced Aβ transport across a cell-based model of the blood-brain barrier (BBB), an effect that was abolished when the amylin receptor was inhibited by two amylin antagonists and by siRNA knockdown of amylin receptor Ramp3. To explain this finding, amylin effect on Aβ transport proteins expressed at the BBB was evaluated. Findings indicated that cells treated with amylin induced LRP1 expression, a major receptor involved in brain Aβ efflux, in plasma membrane fraction, suggesting intracellular translocation of LRP1 from the cytoplasmic pool. Increased LRP1 in membrane fraction could explain, at least in part, the enhanced uptake and transport of Aβ across the BBB. Collectively, our findings indicated that amylin induced Aβ brain to blood clearance through amylin receptor by inducing LRP1 subcellular translocation to the plasma membrane of the BBB endothelium.

Amylin Treatment Reduces Neuroinflammation and Ameliorates Abnormal Patterns of Gene Expression in the Cerebral Cortex of an Alzheimer's Disease Mouse Model. - Wang, Erming; Zhu, Haihao; Wang, Xiaofan; Gower, Adam; Wallack, Max; Blusztajn, Jan Krzysztof; Kowall, Neil; Qiu, Wei Qiao (J Alzheimers Dis, 2017)
Our recent study has demonstrated that peripheral amylin treatment reduces the amyloid pathology in the brain of Alzheimer's disease (AD) mouse models, and improves their learning and memory. We hypothesized that the beneficial effects of amylin for AD was beyond reducing the amyloids in the brain, and have now directly tested the actions of amylin on other aspects of AD pathogenesis, especially neuroinflammation. A 10-week course of peripheral amylin treatment significantly reduced levels of cerebral inflammation markers, Cd68 and Iba1, in amyloid precursor protein (APP) transgenic mice. Mechanistic studies indicated the protective effect of amylin required interaction with its cognate receptor because silencing the amylin receptor expression blocked the amylin effect on Cd68 in microglia. Using weighted gene co-expression network analysis, we discovered that amylin treatment influenced two gene modules linked with amyloid pathology: 1) a module related to proinflammation and transport/vesicle process that included a hub gene of Cd68, and 2) a module related to mitochondria function that included a hub gene of Atp5b. Amylin treatment restored the expression of most genes in the APP cortex toward levels observed in the wild-type (WT) cortex in these two modules including Cd68 and Atp5b. Using a human dataset, we found that the expression levels of Cd68 and Atp5b were significantly correlated with the neurofibrillary tangle burden in the AD brain and with their cognition. These data suggest that amylin acts on the pathological cascade in animal models of AD, and further supports the therapeutic potential of amylin-type peptides for AD.

Amyloid-Related Imaging Abnormalities in an Aged Squirrel Monkey with Cerebral Amyloid Angiopathy. - Heuer, Eric; Jacobs, Jessica; Du, Rebecca; Wang, Silun; Keifer, Orion P; Cintron, Amarallys F; Dooyema, Jeromy; Meng, Yuguang; Zhang, Xiaodong; Walker, Lary C (J Alzheimers Dis, 2017)
Amyloid-related imaging abnormalities (ARIA) in magnetic resonance imaging scans have emerged as indicators of potentially serious side effects in clinical trials of therapeutics for Alzheimer's disease. These anomalies include an edematous type (ARIA-E) that appears as hyperintense (bright) regions by T2-weighted MRI, and a type characterized by the deposition of hemosiderin (ARIA-H) that elicits a hypointense signal, especially in T2* susceptibility weighted images. ARIA in general has been linked to the presence of amyloid-β (Aβ)-type cerebral amyloid angiopathy, an accumulation of misfolded Aβ protein in the vascular wall that impairs the integrity of brain blood vessels. However, the pathobiology of ARIA remains poorly understood, in part due to the absence of an animal model of the disorder that would enable a contemporaneous analysis of tissue integrity in the affected region. Here we describe both ARIA-E and ARIA-H in an aged squirrel monkey (Saimiri sciureus), a nonhuman primate model of naturally occurring cerebral amyloid angiopathy. Histopathologic examination of the anomalous region revealed reactive astrocytosis and microgliosis, infiltration of systemic inflammatory/immune cells, damage to axons and myelin, and hemosiderin deposition. The disruption of axons in particular suggests that ARIA-E could have functional consequences for affected regions. The squirrel monkey model can be useful for studying the pathogenesis and long-term effects of ARIA, and for testing the safety and efficacy of emerging therapies for Alzheimer's disease.

Anesthesia/Surgery Induces Cognitive Impairment in Female Alzheimer's Disease Transgenic Mice. - Zhang, Ce; Zhang, Yiying; Shen, Yuan; Zhao, Guoqing; Xie, Zhongcong; Dong, Yuanlin (J Alzheimers Dis, 2017)
Anesthesia and/or surgery may promote Alzheimer's disease (AD) by accelerating its neuropathogenesis. Other studies showed different findings. However, the potential sex difference among these studies has not been well considered, and it is unknown whether male or female AD patients are more vulnerable to develop postoperative cognitive dysfunction. We therefore set out to perform a proof of concept study to determine whether anesthesia and surgery can have different effects in male and female AD transgenic (Tg) mice, and in female AD Tg plus Cyclophilin D knockout (CypD KO) mice. The mice received an abdominal surgery under sevoflurane anesthesia (anesthesia/surgery). Fear Conditioning System (FCS) was used to assess the cognitive function. Hippocampal levels of synaptic marker postsynaptic density 95 (PSD-95) and synaptophysin (SVP) were measured using western blot analysis. Here we showed that the anesthesia/surgery decreased the freezing time in context test of FCS at 7 days after the anesthesia/surgery in female, but not male, mice. The anesthesia/surgery reduced hippocampus levels of synaptic marker PSD-95 and SVP in female, but not male, mice. The anesthesia/surgery induced neither reduction in freezing time in FCS nor decreased hippocampus levels of PSD-95 and SVP in the AD Tg plus CypD KO mice. These data suggest that the anesthesia/surgery induced a sex-dependent cognitive impairment and reduction in hippocampus levels of synaptic markers in AD Tg mice, potentially via a mitochondria-associated mechanism. These findings could promote clinical investigations to determine whether female AD patients are more vulnerable to the development of postoperative cognitive dysfunction.

The Anti-Amyloid-β and Neuroprotective Properties of a Novel Tricyclic Pyrone Molecule. - Maezawa, Izumi; Zou, Bende; Di Lucente, Jacopo; Cao, William S; Pascual, Conrado; Weerasekara, Sahani; Zhang, Man; Xie, Xinmin Simon; Hua, Duy H; Jin, Lee-Way (J Alzheimers Dis, 2017)
There is an urgent unmet need for new therapeutics for Alzheimer's disease (AD), the most common cause of dementia in the elderly. Therapeutic approaches targeting amyloid-β (Aβ) and its downstream toxicities have become major strategies in AD drug development. We have taken a rational design approach and synthesized a class of tricyclic pyrone (TP) compounds that show anti-Aβ and other neuroprotective actions. The in vivo efficacy of a lead TP named CP2 to ameliorate AD-like pathologies has been shown in mouse models. Here we report the selection and initial characterization of a new lead TP70, which exhibited an anti-Aβ therapeutic index even higher than CP2. Moreover, TP70 was able to reduce oxidative stress, inhibit acyl-coenzyme A:cholesterol acyltransferase (ACAT), and upregulate the expression of ATP-binding cassette subfamily A, member 1 (ABCA1), actions considered neuroprotective in AD. TP70 further showed excellent pharmacokinetic properties, including brain penetration and oral availability. When administered to 5xFAD mice via intraperitoneal or oral route, TP70 enhanced the overall solubility and decreased the level of cerebral Aβ, including both fibrillary and soluble Aβ species. Interestingly, TP70 enhanced N-methyl-D-aspartate (NMDA) receptor-mediated excitatory post-synaptic potential (EPSP) in the hippocampal CA1 area, increased the magnitude of NMDA-dependent hippocampal long-term potentiation (LTP), a cellular model of learning and memory, and prevented the Aβ oligomer-impaired LTP. Significantly, a single dose of TP70 administered to aged 5xFAD mice was effective in mitigating the impaired LTP induction, recorded at 24 h after administration. Our results support a potential of TP70 in clinical development for AD in view of its synergistic neuroprotective actions, ability to positively modulate NMDA receptor-mediated hippocampal plasticity, and favorable pharmacokinetic properties in rodents.

Apolipoprotein E Isoforms Differentially Regulate Alzheimer's Disease and Amyloid-β-Induced Inflammatory Response in vivo and in vitro. - Dorey, Evan; Bamji-Mirza, Michelle; Najem, Dema; Li, Yan; Liu, Hong; Callaghan, Debbie; Walker, Douglas; Lue, Lih-Fen; Stanimirovic, Danica; Zhang, Wandong (J Alzheimers Dis, 2017)
Neuroinflammation plays a critical role in neuronal dysfunction and death of Alzheimer's disease (AD). ApoE4 is a major risk factor of AD, while ApoE2 is neuroprotective. Little is known about the roles of ApoE isoforms in the neuroinflammation seen in AD. Their roles and mechanisms in Aβ-induced/neuroinflammation were investigated in this study using in vivo and in vitro models. Rat astrocytes were treated with lipid-poor recombinant hApoE and/or Aβ42. Mouse astrocyte lines-expressing lipidated hApoE were treated with Aβ42 and/or vitamin D receptor (VDR) agonist, 1α,25-dihydroxyvitamin D3. Cells and media were harvested for cytokine ELISA, RNA isolated for qRT-PCR, and nuclear protein for transcription factor (TF) arrays and EMSA. hApoE-transgenic and AD mice were mated to generate hApoE2/AD and hApoE4/AD mice. Mice were euthanized at 6 months of age. Brain tissues were collected for cytokine ELISA array, Aβ ELISA, immunoblotting, and immunohistochemistry. hApoE4/AD mice had significantly higher levels of inflammatory cytokines than hApoE2/AD mice. Lipidated hApoE4 significantly promoted inflammatory gene expression induced by Aβ42 but not recombinant hApoE4 in astrocytes as compared to controls. Lipidated hApoE3 provided a certain degree of protection against Aβ42-induced inflammatory response but not recombinant hApoE3 as compared to controls. Both lipidated and recombinant hApoE2 provided protection against Aβ42-induced inflammatory response compared to controls. TF array revealed that ApoE2 strongly activated VDR in Aβ42-treated astrocytes. Application of 1α,25-dihydroxyvitamin D3 completely inhibited Aβ-induced inflammatory gene expression in hApoE4-expressing astrocytes. The results suggest that ApoE4 promotes, but ApoE2 inhibits, AD/Aβ-induced neuroinflammation via VDR signaling. Targeting VDR signaling or active form of VD3 may relieve AD neuroinflammation or/and neurodegeneration.

AQP4 Association with Amyloid Deposition and Astrocyte Pathology in the Tg-ArcSwe Mouse Model of Alzheimer's Disease. - Yang, Jing; Zhang, Rui; Shi, Changhe; Mao, Chengyuan; Yang, Zhihua; Suo, Zhenhe; Torp, Reidun; Xu, Yuming (J Alzheimers Dis, 2017)
Amyloid-β deposition in senile plaques is one of the main pathological changes in Alzheimer's disease (AD). We previously reported that aquaporin-4 (AQP4) is redistributed within the astrocytes in cerebral amyloid angiopathy in the tg-ArcSwe mouse model of AD, suggesting that AQP4 may participate in amyloid-β deposition. However, the role of AQP4 in plaque formation is not currently clear. The objective of the current study was to explore the AQP4 distribution within plaques in the tg-ArcSwe mice in more depth by the combined application of immunofluorescence cytochemistry and immunogold electron microscopy. In addition, the astrocyte marker, glial fibrillary acidic protein (GFAP), was studied in association with AQP4. We demonstrated a robust upregulation of AQP4 expression in areas of plaques. Compared to GFAP, AQP4 appeared predominantly at later stages of plaque formation, in older mice, and within the processes of astrocytes. In combination with GFAP, AQP4 differentiated plaques into three progression stages under light microscopy. This suggests that AQP4 expression was associated with amyloid deposition and astrocyte pathology in the Tg-ArcSwe mouse model of AD. This provides novel proof for the involvement of AQP4 in the process of amyloid deposition in AD.

Association between Cognitive Status before Surgery and Outcomes in Elderly Patients with Hip Fracture in a Dedicated Orthogeriatric Care Pathway. - Zerah, Lorene; Cohen-Bittan, Judith; Raux, Mathieu; Meziere, Anthony; Tourette, Cendrine; Neri, Christian; Verny, Marc; Riou, Bruno; Khiami, Frederic; Boddaert, Jacques (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is associated with a worse prognosis of hip fracture, but the impact of a dedicated geriatric care pathway on the prognosis of these patients has not been evaluated. OBJECTIVE: According to the cognitive status before surgery, our main objective was to compare mortality rate at 6 months; secondary outcomes were to compare in-hospital complications, the risk of new institutionalization, and the ability to walk at 6 months. METHODS: Between 2009 and 2015, all patients (>70 years) admitted after hip fracture surgery into a dedicated unit of peri-operative geriatric care were included: patients with dementia (DP), without dementia (NDP), and with cognitive status not determined (CSND). Data are expressed as hazard ratio (HR) for multivariate cox analysis or odds ratio (OR) for multivariate logistic regression analysis and their 95% confidence interval (CI). RESULTS: We included 650 patients (86±6 years): 168 DP, 400 NDP, and 82 CSND. After adjustment for age, sex, comorbidities, polypharmacy, pre-fracture autonomy, time-to-surgery, and delirium, there were no significant differences for 6-month mortality (DP versus NDP: HR = 0.7[0.4-1.2], DP versus CSND: HR = 0.6[0.3-1.4], CSND versus NDP: HR = 0.8[0.4-1.7]); but DP and CSND were more likely to be newly institutionalized after 6 months compared to NDP (OR DP = 2.6[1.4-4.9], p = 0.003, OR CSND = 2.9[1.4-6.1], p = 0.004). 92% of population was walking after 6 months (63% with assistance): no difference was found between the three groups. CONCLUSION: In a dedicated geriatric care pathway, DP and CSND undergoing hip surgery have the same 6-month mortality and walking ability as NDP.

Association of Kidney Function Biomarkers with Brain MRI Findings: The BRINK Study. - Vemuri, Prashanthi; Knopman, David S; Jack, Clifford R; Lundt, Emily S; Weigand, Stephen D; Zuk, Samantha M; Thostenson, Kaely B; Reid, Robert I; Kantarci, Kejal; Slinin, Yelena; Lakshminarayan, Kamakshi; Davey, Cynthia S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Chronic kidney disease (CKD) studies have reported variable prevalence of brain pathologies, in part due to low inclusion of participants with moderate to severe CKD. OBJECTIVE: To measure the association between kidney function biomarkers and brain MRI findings in CKD. METHODS: In the BRINK (BRain IN Kidney Disease) study, MRI was used to measure gray matter volumes, cerebrovascular pathologies (white matter hyperintensity (WMH), infarctions, microhemorrhages), and microstructural changes using diffusion tensor imaging (DTI). We performed regression analyses with estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR) as primary predictors, and joint models that included both predictors, adjusted for vascular risk factors. RESULTS: We obtained 240 baseline MRI scans (150 CKD with eGFR <45 in ml/min/1.73 m2; 16 mild CKD: eGFR 45-59; 74 controls: eGFR≥60). Lower eGFR was associated with greater WMH burden, increased odds of cortical infarctions, and worsening diffusion changes throughout the brain. In eGFR models adjusted for UACR, only cortical infarction associations persisted. However, after adjusting for eGFR, higher UACR provided additional information related to temporal lobe atrophy, increased WMH, and whole brain microstructural changes as measured by increased DTI mean diffusivity. CONCLUSIONS: Biomarkers of kidney disease (eGFR and UACR) were associated with MRI brain changes, even after accounting for vascular risk factors. UACR adds unique additional information to eGFR regarding brain structural and diffusion biomarkers. There was a greater impact of kidney function biomarkers on cerebrovascular pathologies and microstructural brain changes, suggesting that cerebrovascular etiology may be the primary driver of cognitive impairment in CKD.

Autophagy-ERK1/2-Involved Disinhibition of Hippocampal Neurons Contributes to the Pre-Synaptic Toxicity Induced by Aβ42 Exposure. - Yin, Yanling; Zhao, Yuanyuan; Han, Song; Zhang, Nan; Chen, Hanyu; Wang, Xiaomin (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disease and the most frequent cause of progressive cognitive decline in the elderly population. To date, there is still no effective treatment for AD, requiring more underlying mechanisms. In the present study, we investigated the effects of Aβ42 on the inhibitory synaptic transmission in the cultured hippocampal neurons, and explored the possible mechanism. The frequency, but not amplitude, of miniature inhibitory post-synaptic currents was significantly suppressed by Aβ42, indicating that Aβ42 played its role in inhibitory transmitter release at the pre-synaptic sites. Aβ42 had no effect on miniature excitatory post-synaptic currents, suggesting GABAergic synapses are more susceptible to Aβ42 exposure. However, the number of GABAergic neurons or synapses was not influenced, suggesting the corresponding stage may be a preclinical one. The effect of Aβ42 can be mimicked by PD98059 (an inhibitor of ERK1/2) and blocked by curcumin (an activator of MEK), which reveals Aβ-involved influence is via the decreased phosphorylation of MAPK-ERK1/2. In addition, synaptophysin is confirmed to be a downstream protein of MAPK-ERK1/2 at the pre-synaptic site. At the same time, suppressed autophagy was observed after Aβ42 exposure, and the activation of autophagy increased pERK1/2 level and salvaged the disinhibition of hippocampal neurons. These data suggest that diminished GABAergic tone likely starts from the preclinical stage of AD, so some GABAergic stress test may be effective for identifying cognitively normal elder adults. Strategies against the dysfunction of autophagy should be adopted in the early stage of AD because of its initial effects.

CD44 Splice Variants as Potential Players in Alzheimer's Disease Pathology. - Pinner, Elhanan; Gruper, Yaron; Ben Zimra, Micha; Kristt, Don; Laudon, Moshe; Naor, David; Zisapel, Nava (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by cognitive deficits, deposition of amyloid-β (Aβ) plaques, intracellular neurofibrillary tangles, and neuronal cell death. Neuroinflammation is commonly believed to participate in AD pathogenesis. CD44 is an inflammation-related gene encoding a widely-distributed family of alternatively spliced cell surface glycoproteins that have been implicated in inflammation, metastases, and inflammation-linked neuronal injuries. Here we investigated the expression patterns of CD44S (which does not contain any alternative exon) and CD44 splice variants in postmortem hippocampal samples from AD patients and matched non-AD controls. The expression of CD44S and CD44 splice variants CD44V3, CD44V6, and CD44V10 was significantly higher in AD patients compared to non-AD controls. Immunohistochemistry of human hippocampal sections revealed that CD44S differentially localized to neuritic plaques and astrocytes, whereas CD44V3, CD44V6, and CD44V10 expression was mostly neuronal. Consistent with these findings, we found that the expression of CD44V6 and CD44V10 was induced by Aβ peptide in neuroblastoma cells and primary neurons. Furthermore, in loss of function studies we found that both CD44V10-specific siRNA and CD44V10 antibody protected neuronal cells from Aβ-induced toxicity, suggesting a causal relationship between CD44V10 and neuronal cell death. These data indicate that certain CD44 splice variants contribute to AD pathology and that CD44V10 inhibition may serve as a new neuroprotective treatment strategy for this disease.

Cerebrospinal Fluid Neurogranin as a Biomarker of Neurodegenerative Diseases: A Cross-Sectional Study. - Lista, Simone; Toschi, Nicola; Baldacci, Filippo; Zetterberg, Henrik; Blennow, Kaj; Kilimann, Ingo; Teipel, Stefan J; Cavedo, Enrica; Dos Santos, Antonio Melo; Epelbaum, Stéphane; Lamari, Foudil; Dubois, Bruno; et al. (J Alzheimers Dis, 2017)
We investigated cerebrospinal fluid (CSF) concentrations of the postsynaptic biomarker neurogranin at baseline in cognitively healthy controls (HC) compared to individuals with mild cognitive impairment (MCI), patients with Alzheimer's disease (AD) dementia, and patients with frontotemporal dementia (FTD). CSF neurogranin was quantified using an in-house immunoassay in a cross-sectional multicenter study of 108 participants [AD dementia (n = 35), FTD (n = 9), MCI (n = 41), cognitively HC (n = 23)]. CSF neurogranin concentrations were significantly higher in AD patients compared with both HC subjects and FTD patients, suggesting that increased CSF neurogranin concentrations may indicate AD-related pathophysiology. CSF neurogranin was independently associated with both total tau and hyperphosphorylated tau proteins, whereas a non-significant correlation with the 42-amino acid-long amyloid-β peptide was evident. CSF neurogranin, however, was not superior to core AD biomarkers in differentiating HC from the three diagnostic groups, and it did not improve their diagnostic accuracy. We conclude that further classification and longitudinal studies are required to shed more light into the potential role of neurogranin as a pathophysiological biomarker of neurodegenerative diseases.

Chronic Verubecestat Treatment Suppresses Amyloid Accumulation in Advanced Aged Tg2576-AβPPswe Mice Without Inducing Microhemorrhage. - Villarreal, Stephanie; Zhao, Fuqiang; Hyde, Lynn A; Holder, Daniel; Forest, Thomas; Sondey, Marie; Chen, Xia; Sur, Cyrille; Parker, Eric M; Kennedy, Matthew E (J Alzheimers Dis, 2017)
Verubecestat is a potent BACE1 enzyme inhibitor currently being investigated in Phase III trials for the treatment of mild-to-moderate and prodromal Alzheimer's disease. Multiple anti-amyloid immunotherapies have been dose-limited by adverse amyloid related imaging abnormalities such as vasogenic edema (ARIA-E) and microhemorrhage (ARIA-H) observed in human trials and mice. Verubecestat was tested in a 12-week nonclinical study for the potential to exacerbate microhemorrhage (ARIA-H) profiles in 18-22-month-old post-plaque Tg2576-AβPPswe mice. Animals were treated with verubecestat or controls including the anti-Aβ antibody analog of bapineuzumab (3D6) as a positive control for ARIA induction. ARIA-H was measured using in-life longitudinal T2*-MRI and Prussian blue histochemistry at study end. Verubecestat reduced plasma and cerebrospinal fluid Aβ40 and Aβ42 by >90% and 62% to 68%, respectively. The ARIA-H profile of verubecestat-treated mice was not significantly different than controls. Anti-Aβ treatment significantly increased ARIA-H detected by Prussian blue staining; however, anti-Aβ antibody treatment did not impact plaque status. Verubecestat treatment significantly suppressed the accumulation of total levels of brain Aβ40 and Aβ42 and Thioflavin S positive plaque load. Stereological analysis of cortex and hippocampus plaque load similarly revealed significantly reduced area of Aβ immunoreactivity and reduced plaque number in verubecestat-treated animals compared to controls. The absence of elevated ARIA events in verubecestat-treated mice was associated with a significant reduction in the level of accumulated CNS amyloid pathology and brain Aβ peptides; effects consistent with the desired therapeutic mechanism of verubecestat in AD patients. These data will be compared with longitudinal MRI profiles from ongoing clinical trials.

The Clinical Use of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease Diagnosis: The Italian Selfie. - Sancesario, Giulia M; Toniolo, Sofia; Chiasserini, Davide; Di Santo, Simona G; Zegeer, Josh; Bernardi, Gaetano; Musicco, Massimo; Caltagirone, Carlo; Parnetti, Lucilla; Bernardini, Sergio (J Alzheimers Dis, 2017)
Although the use of cerebrospinal fluid (CSF) amyloid β1-42 (Aβ42), tau (T-tau), and phosphorylated tau (p-tau181) gives added diagnostic and prognostic values, the diffusion is still limited in clinical practice and only a restricted number of patients receive an integrated clinico-biological diagnosis. By a survey, we aimed to do a "selfie" of the use and diffusion of CSF biomarkers of dementia in Italy, the standardization of pre-analytical procedures, the harmonization of ranges, and the participation to Quality Control programs. An online questionnaire was sent to the members of SIBioC and SINdem-ITALPLANED and to main neurological clinics all over Italy. In Italy, 25 laboratories provide biomarkers analysis in addition to a network of 15 neighboring hospitals. In sum, 40 neurological centers require CSF analyses. 7/20 regions (35%) lack CSF laboratories. Standardization of pre-analytical procedures is present in 62.02% of the laboratories; only 56.00% of the laboratories participate in International Quality Control. There is no harmonization of cut-offs. In Italy, the use of CSF biomarkers is still limited in clinical practice. Standardization and harmonization of normal ranges are needed. To optimize and expand the use of CSF biomarkers, a cost-benefit analysis should be promoted by scientific societies and national health services.

Colivelin Ameliorates Impairments in Cognitive Behaviors and Synaptic Plasticity in APP/PS1 Transgenic Mice. - Wu, Meina; Shi, Hui; He, Yexin; Yuan, Li; Qu, Xuesong; Zhang, Jun; Wang, Zhaojun; Cai, Hongyan; Qi, Jinshun (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common cause of dementia, and effective therapeutics are lacking. Colivelin (CLN), a novel, strong humanin derivative, is effective in vitro in preventing cell death induced by AD-causative genes and amyloid-β protein (Aβ) even at a low concentration. We recently demonstrated that intrahippocampal injection of CLN prevents Aβ25-35-induced deficits in spatial memory and synaptic plasticity in normal rats. Here, we further observed the effects of chronically intranasally (i.n.) administered CLN on cognitive behaviors and pathological hallmarks in 9-month-old APPswe/PS1dE9 (APP/PS1) AD mice using multiple behavioral tests and immunochemistry. The electrophysiological mechanism of CLN neuroprotection was also investigated by recording in vivo hippocampal long-term potentiation (LTP). CLN pretreatment effectively prevented impairments in new object recognition, working memory, and long-term spatial memory and reversed the depression of in vivo hippocampal LTP in APP/PS1 mice. Additionally, chronic application of CLN obviously reduced Aβ deposition in the hippocampus in APP/PS1 mice. These results indicate that CLN has strong neuroprotective effects on learning and memory behaviors in APP/PS1 mice and that this behavioral improvement is closely associated with the reduction of Aβ deposition and alleviation of LTP suppression in the hippocampus, supporting the potential of CLN for the prevention and treatment of AD.

Co-Localization of Glia Maturation Factor with NLRP3 Inflammasome and Autophagosome Markers in Human Alzheimer's Disease Brain. - Ahmed, Mohammad Ejaz; Iyer, Shankar; Thangavel, Ramasamy; Kempuraj, Duraisamy; Selvakumar, Govindhasamy Pushpavathi; Raikwar, Sudhanshu P; Zaheer, Smita; Zaheer, Asgar (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by the presence of intracellular neurofibrillary tangles (NFTs) containing hyperphosphorylated tau, and the extracellular deposition of amyloid plaques (APs) with misfolded amyloid-β (Aβ) peptide. Glia maturation factor (GMF), a highly conserved pro-inflammatory protein, isolated and cloned in our laboratory, has been shown to activate glial cells leading to neuroinflammation and neurodegeneration in AD. We hypothesized that inflammatory reactions promoted by NLRP3-Caspase-1inflammasome pathway trigger dysfunction in autophagy and accumulation of Aβ which is amplified and regulated by GMF in AD. In this study, using immunohistochemical techniques we analyzed components of the NLRP3 inflammasome and autophagy- lysosomal markers in relation to Aβ, p-tau and GMF in human postmortem AD and age-matched non-AD brains. Tissue sections were prepared from the temporal cortex of human postmortem brains. Here, we demonstrate an increased expression of the inflammasome components NLRP3 and Caspase-1 and the products of inflammasome activation IL-1β and IL-18 along with GMF in the temporal cortex of AD brains. These inflammasome components and the pro-inflammatory cytokines co-localized with GMF in the vicinity and periphery of the APs and NFTs. Moreover, using double immunofluorescence staining, AD brain displayed an increase in the autophagy SQSTM1/p62 and LC3 positive vesicles and the lysosomal marker LAMP1 that also co-localized with GMF, Aβ and hyperphosphorylated p-tau. Our results indicate that in AD, the neuroinflammation promoted by the NLRP3 inflammasome may be amplified and regulated by GMF, which further impairs clearance of protein aggregates mediated by the auto-phagosomal pathway.

Comparison of Model-Based Indices of Cerebral Autoregulation and Vasomotor Reactivity Using Transcranial Doppler versus Near-Infrared Spectroscopy in Patients with Amnestic Mild Cognitive Impairment. - Marmarelis, Vasilis Z; Shin, Dae C; Tarumi, Takashi; Zhang, Rong (J Alzheimers Dis, 2017)
We recently introduced model-based "physiomarkers" of dynamic cerebral autoregulation and CO2 vasomotor reactivity as an aid for diagnosis of early-stage Alzheimer's disease (AD) [1], where significant impairment of dynamic vasomotor reactivity (DVR) was observed in early-stage AD patients relative to age-matched controls. Milder impairment of DVR was shown in patients with amnestic mild cognitive impairment (MCI) using the same approach in a subsequent study [2]. The advocated approach utilizes subject-specific data-based models of cerebral hemodynamics to quantify the dynamic effects of resting-state changes in arterial blood pressure and end-tidal CO2 (the putative inputs) upon cerebral blood flow velocity (the putative output) measured at the middle cerebral artery via transcranial Doppler (TCD). The obtained input-output models are then used to compute model-based indices of DCA and DVR from model-predicted responses to an input pressure pulse or an input CO2 pulse, respectively. In this paper, we compare these model-based indices of DVR and DCA in 46 amnestic MCI patients, relative to 20 age-matched controls, using TCD measurements with their counterparts using Near-Infrared Spectroscopy (NIRS) measurements of blood oxygenation at the lateral prefrontal cortex in 43 patients and 22 age-matched controls. The goal of the study is to assess whether NIRS measurements can be used instead of TCD measurements to obtain model-based physiomarkers with comparable diagnostic utility. The results corroborate this view in terms of the ability of either output to yield model-based physiomarkers that can differentiate the group of aMCI patients from age-matched healthy controls.

Comprehensive Quantitative Profiling of Tau and Phosphorylated Tau Peptides in Cerebrospinal Fluid by Mass Spectrometry Provides New Biomarker Candidates. - Russell, Claire L; Mitra, Vikram; Hansson, Karl; Blennow, Kaj; Gobom, Johan; Zetterberg, Henrik; Hiltunen, Mikko; Ward, Malcolm; Pike, Ian (J Alzheimers Dis, 2017)
Aberrant tau phosphorylation is a hallmark in Alzheimer's disease (AD), believed to promote formation of paired helical filaments, the main constituent of neurofibrillary tangles in the brain. While cerebrospinal fluid (CSF) levels of total tau and tau phosphorylated at threonine residue 181 (pThr181) are established core biomarkers for AD, the value of alternative phosphorylation sites, which may have more direct relevance to pathology, for early diagnosis is not yet known, largely due to their low levels in CSF and lack of standardized detection methods. To overcome sensitivity limitations for analysis of phosphorylated tau in CSF, we have applied an innovative mass spectrometry (MS) workflow, TMTcalibratortrademark, to enrich and enhance the detection of phosphoproteome components of AD brain tissue in CSF, and enable the quantitation of these analytes. We aimed to identify which tau species present in the AD brain are also detectable in CSF and which, if any, are differentially regulated with disease. Over 75% coverage of full-length (2N4R) tau was detected in the CSF with 47 phosphopeptides covering 31 different phosphorylation sites. Of these, 11 phosphopeptides were upregulated by at least 40%, along with an overall increase in tau levels in the CSF of AD patients relative to controls. Use of the TMTcalibratortrademark workflow dramatically improved our ability to detect tau-derived peptides that are directly related to human AD pathology. Further validation of regulated tau peptides as early biomarkers of AD is warranted and is currently being undertaken.

Cortical Thickness and Microstructural White Matter Changes Detect Amnestic Mild Cognitive Impairment. - Wang, Zan; Dai, Zhengjia; Shu, Hao; Liu, Duan; Guo, Qihao; He, Yong; Zhang, Zhijun (J Alzheimers Dis, 2017)
Both the apolipoprotein E (APOE) ɛ4 allele and amnestic mild cognitive impairment (aMCI) are considered to be risk factors for Alzheimer's disease (AD). The primary aim of this study was to determine whether the aMCI-related abnormality in gray matter (GM) cortical thickness and white matter (WM) tracts integrity would be modified by the APOE genotype. A total of 146 older adults, including 64 aMCI patients (28 ɛ4 carriers and 36 non-carriers) and 82 healthy controls (39 ɛ4 carriers and 43 non-carriers), underwent a standardized clinical interview, neuropsychological battery assessment, and multi-modal brain magnetic resonance imaging scans. Compared with control subjects, the patients with aMCI showed significantly reduced cortical thickness bilaterally in the parahippocampal gyrus and disrupted WM integrity in the limbic tracts (e.g., increased mean diffusivity in the right parahippocampal cingulum and bilateral uncinate fasciculus). However, no significant main effects of the APOE genotype and diagnosis-by-genotype interaction on GM thickness and WM integrity were observed. Further, diffusivity measures of the limbic WM tracts were significantly correlated with the parahippocampal atrophy in aMCI. Importantly, the parahippocampal thickness and diffusivity measures of the limbic WM tracts were significantly correlated with the cognitive performance (i.e., episodic memory Z score) in patients with aMCI. These results demonstrate that WM microstructural disruptions in the limbic tracts are present at the early stage of AD in an APOE-independent manner; and this degeneration may occur progressively, in parallel with parahippocampal atrophy, and may specifically contribute to early initial impairment in episodic memory.

Diabetes is Not Associated with Alzheimer's Disease Neuropathology. - Dos Santos Matioli, Maria Niures Pimentel; Suemoto, Claudia Kimie; Rodriguez, Roberta Diehl; Farias, Daniela Souza; da Silva, Magnólia Moreira; Leite, Renata Elaine Paraizo; Ferretti-Rebustini, Renata Eloah Lucena; Farfel, José Marcelo; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Arvanitakis, Zoe; Naslavsky, Michel Satya; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Previous evidence linking diabetes to Alzheimer's disease (AD) neuropathology is mixed and scant data are available from low- and middle-income countries. OBJECTIVE: To investigate the association between diabetes and AD neuropathology in a large autopsy study of older Brazilian adults. METHODS: In this cross-sectional study, diabetes was defined by diagnosis during life or use of antidiabetic medication. A standardized neuropathological examination was performed using immunohistochemistry. The associations of diabetes with Consortium to Establish and Registry for Alzheimer Disease (CERAD) scores for neuritic plaques and Braak-Braak (BB) scores for neurofibrillary tangles were investigated using multivariable ordinal logistic regression. We investigated effect modification of education, race, and APOE on these associations. RESULTS: Among 1,037 subjects (mean age = 74.4±11.5 y; mean education = 4.0±3.7 y; 48% male, 61% White), diabetes was present in 279 subjects. Diabetes was not associated with BB (OR = 1.12, 95% CI = 0.81-1.54, p = 0.48) or with CERAD (OR = 0.97, 95% CI = 0.68-1.38, p = 0.86) scores on analyses adjusted for sociodemographic and clinical variables. We observed effect modification by the APOE allele ɛ4 on the association between diabetes mellitus and BB scores. CONCLUSION: No evidence of an association between diabetes and AD neuropathology was found in a large sample of Brazilians; however, certain subgroups, such as APOE allele ɛ4 carriers, had higher odds of accumulation of neurofibrillary tangles.

Dickkopf 3 (Dkk3) Improves Amyloid-β Pathology, Cognitive Dysfunction, and Cerebral Glucose Metabolism in a Transgenic Mouse Model of Alzheimer's Disease. - Zhang, Li; Sun, Caixian; Jin, Yaxi; Gao, Kai; Shi, Xudong; Qiu, Wenying; Ma, Chao; Zhang, Lianfeng (J Alzheimers Dis, 2017)
Dysfunctional Wnt signaling is associated with Alzheimer's disease (AD), and activation of the Wnt signaling pathway inhibits AD development. Dickkopf 3 (Dkk3) is a modulator of the Wnt signaling pathway and is physiologically expressed in the brain. The role of Dkk3 in the pathogenesis of AD has not been evaluated. In the present study, we determined that Dkk3 expression was significantly decreased in brain tissue from AD patients and the AD transgenic mouse model APPswe/PS1dE9 (AD mice). Transgenic mice with brain tissue-specific Dkk3 expression were generated or crossed with AD mice to study the effects of Dkk3 on AD. In AD mice, transgenic expression of Dkk3 improved abnormalities in learning, memory, and locomotor activity, reduced the accumulation of amyloid-β, and ameliorated glucose uptake deficits. Furthermore, we determined that Dkk3 downregulated GSK-3β, a central negative regulator in canonical Wnt signaling, and upregulated PKCβ1, a factor implicated in noncanonical Wnt signaling. This indicates that increased activation of GSK-3β and the inhibition of PKCβ1 in AD patients may be responsible for the dysfunctional Wnt signaling in AD. In summary, our data suggest that Dkk3 is an agonist of Wnt signaling, and the ability of transgenic expression of Dkk3 to compensate for the decrease in Dkk3 expression in AD mice, reverse dysfunctional Wnt signaling, and partially inhibit the pathological development of AD suggests that Dkk3 could serve as a therapeutic target for the treatment of AD.

Disinhibition in Alzheimer's Disease is Associated with Reduced Right Frontal Pole Cortical Thickness. - Finger, Elizabeth; Zhang, Jing; Dickerson, Bradford; Bureau, Yves; Masellis, Mario (J Alzheimers Dis, 2017)
Neuropsychiatric symptoms in Alzheimer's disease are among the most disabling and difficult aspects for caregivers and treating health professionals to manage. Despite the high prevalence of these behaviors, little is known about the factors which lead some patients to develop florid behavioral symptoms while others may progress to severe dementia without such phenomenon. We examined whether regional brain volumes as measured by cortical thickness would predict the presence or absence of disinhibition in patients with Alzheimer's disease. Using data from the ADNI, we identified 758 patients with caregiver ratings on the Neuropsychiatric Inventory and a volumetric MRI scan with cortical thickness measurements completed in FreeSurfer by the UCSF core. Of these, 177 patients were found to have disinhibition. Logistic regression models demonstrated that reduced cortical thickness in the right frontal pole was associated with the presence of disinhibition even when controlling for age, disease severity, total intracranial volume, gender, and APOE genotype. The results are considered in the context of leading models of the functions of frontopolar cortex.

The Distinction of Amyloid-β Protein Precursor (AβPP) Ratio in Platelet Between Alzheimer's Disease Patients and Controls: A Systematic Review and Meta-Analysis. - Shi, Yachen; Gu, Lihua; Alsharif, Abdul Azeez; Zhang, Zhijun (J Alzheimers Dis, 2017)
To systematically assess the clinical significance of platelet amyloid-β protein precursor (AβPP) ratio between Alzheimer's disease (AD) patients and controls. 14 articles were selected in this analysis by search of databases including PubMed and Web of Science up to December 2016. Random effects models were used to calculate the standardized mean difference (SMD). Subgroup analyses were used to detect the cause of heterogeneity. The result showed a significant drop in platelet AβPP ratio in AD patients compared to controls [SMD: -1.871; 95% CI: (-2.33, -1.41); p < 0.001; I2 = 88.0% ]. Subgroup analysis revealed races or the quality of studies may be the cause of high heterogeneity. This meta-analysis concluded that there is a close association between platelet AβPP ratio and AD. It is necessary to design a sizable sample study to further support that platelet AβPP ratio can be a biomarker of AD.

DNA Methylation and Tag SNPs of the BDNF Gene in Conversion of Amnestic Mild Cognitive Impairment into Alzheimer's Disease: A Cross-Sectional Cohort Study. - Xie, Bing; Liu, Zanchao; Liu, Wenxuan; Jiang, Lei; Zhang, Rui; Cui, Dongsheng; Zhang, Qingfu; Xu, Shunjiang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a complex multifactorial disease influenced by both genetic and epigenetic factors. This study was aimed to evaluate the interaction between brain-derived neurotrophic factor (BDNF) promoter methylation status and tag single nucleotide polymorphisms (tag SNPs) on amnestic mild cognitive impairment (aMCI) and its conversion to AD. A total of 506 aMCI patients and 728 cognitive normal controls were included in the cross-sectional analysis. Patients (n = 458) from aMCI cohort were selected in the 5-year longitudinal study and classified into two groups: aMCI-stable group (n = 330) and AD-conversion group (n = 128). BDNF promoter methylation was detected by bisulfite-PCR amplification and pyrosequencing. Seven tag SNPs were genotyped by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Elevation of BDNF promoter methylation status was associated with aMCI and AD conversion. The higher methylation levels at CpG5 site showed significant main interactive effects between group and time (F = 8.827, p = 0.005). Genetic analysis revealed rs2030324 and rs6265 were associated with aMCI and rs6265 was associated with AD conversion. The interaction between DNA methylation of CpG5 and AA genotype of rs6265 had a risk role in the development of aMCI (p = 0.019, OR = 1.233, 95% CI: 1.117-1.303) and its progression to AD (p = 0.003, OR = 1.399, 95% CI: 1.198-1.477). The interactions between DNA methylation (CpG5) of the BDNF gene promoter and the tag SNP (rs6265) play important roles in the etiology of aMCI and its conversion to AD.

Effect of Spinal Manometers on Cerebrospinal Fluid Amyloid-β Concentration. - Toombs, Jamie; Foiani, Martha S; Paterson, Ross W; Heslegrave, Amanda; Wray, Selina; Schott, Jonathan M; Fox, Nick C; Lunn, Michael P; Blennow, Kaj; Zetterberg, Henrik (J Alzheimers Dis, 2017)
The effect of spinal manometers on cerebrospinal fluid (CSF) amyloid-β (Aβ) concentration was investigated. Pooled human CSF samples were divided in two, one half passed through a manometer into a collection tube, the other transferred directly to a collection tube. CSF was analyzed for Aβ38/40/42 using an electrochemiluminescence immunoassay. Relative to control, use of a manometer decreased Aβ38/40/42 concentration by 5.6% (±1.5SE), 4.4% (±1.7SE), and 4.3% (±2.4SE), respectively. The ratios of Aβ42 :40, Aβ42 :38, and Aβ40 :38 were not affected by manometer treatment. Factors which artificially lower CSF Aβ concentrations are relevant to clinical diagnosis for AD and study design.

The Effect of Traumatic Brain Injury History with Loss of Consciousness on Rate of Cognitive Decline Among Older Adults with Normal Cognition and Alzheimer's Disease Dementia. - Tripodis, Yorghos; Alosco, Michael L; Zirogiannis, Nikolaos; Gavett, Brandon E; Chaisson, Christine; Martin, Brett; McClean, Michael D; Mez, Jesse; Kowall, Neil; Stern, Robert A (J Alzheimers Dis, 2017)
Traumatic brain injury (TBI) is thought to be a risk factor for dementia, including dementia due to Alzheimer's disease (AD). However, the influence of TBI history on the neuropsychological course of AD is unknown and, more broadly, the effect of TBI history on age-related cognitive change is poorly understood. We examined the relationship between history of TBI with loss of consciousness (LOC) history and cognitive change in participants with normal cognition and probable AD, stratified by APOEɛ4 allele status. The sample included 706 participants (432 with normal cognition; 274 probable AD) from the National Alzheimer's Coordinating Center (NACC) dataset that completed the Uniform Data Set evaluation between 2005 and 2014. Normal and probable AD participants with a history of TBI were matched to an equal number of demographically and clinically similar participants without a TBI history. In this dataset, TBI with LOC was defined as brain trauma with brief or extended unconsciousness. For the normal and probable AD cohorts, there was an average of 3.2±1.9 and 1.8±1.1 years of follow-up, respectively. 30.8% of the normal cohort were APOEɛ4 carriers, whereas 70.8% of probable AD participants were carriers. Mixed effects regressions showed TBI with LOC history did not affect rates of cognitive change in APOEɛ4 carriers and non-carriers. Findings from this study suggest that TBI with LOC may not alter the course of cognitive function in older adults with and without probable AD. Future studies that better characterize TBI (e.g., severity, number of TBIs, history of subconconcussive exposure) are needed to clarify the association between TBI and long-term neurocognitive outcomes.

The Effects of an APOE Promoter Polymorphism on Human White Matter Connectivity during Non-Demented Aging. - Chang, Peifen; Li, Xin; Ma, Chao; Zhang, Sisi; Liu, Zhen; Chen, Kewei; Ai, Lin; Chang, Jingling; Zhang, Zhanjun (J Alzheimers Dis, 2017)
Polymorphisms of the apolipoprotein E (APOE) promoter rs405509 are related to Alzheimer's disease (AD). The T/T allele of rs405509 decreases the transcription of the APOE gene and leads to impairments in a specific brain structural network in aged individuals; thus, it is an important risk factor for AD. However, it remains unknown whether rs405509 affects white matter networks during aging. Here, we investigated the effect of the rs405509 genotype (T/T versus G-allele) on age-related brain white matter structural networks via construction of the graph theory-based structural connectome using diffusion MRI data in a large cohort. Network communication efficiency was quantified, along with the network's betweenness centrality (Bc), global efficiency, local efficiency, and shortest path length. Regarding cognition, TT carriers had significant negative correlations between age and memory performance and between age and executive functions. A network analysis showed that TT carriers had an accelerated age-related loss of Bc and that regional Bc decreased in the left inferior frontal gyrus pars opercularis, the left posterior cingulate cortex, the right inferior occipital gyrus (IOG.R), and the left angular gyrus (ANG.L). Additional brain-behavior relationship analyses showed that polymorphism of rs405509 and age have strong interaction effects on the association of nodal Bc and cognition, mainly in the IOG.R and ANG.L. These results demonstrate that the rs405509 T/T allele of APOE causes an age-related cognitive decline in non-demented elderly people, possibly by modulating brain network communication efficiency, which may be beneficial for understanding the neural mechanisms of rs405509-related cognitive aging and AD pathogenesis.

Effects of DHA Supplementation on Hippocampal Volume and Cognitive Function in Older Adults with Mild Cognitive Impairment: A 12-Month Randomized, Double-Blind, Placebo-Controlled Trial. - Zhang, Yan-Ping; Miao, Rujuan; Li, Qing; Wu, Tianfeng; Ma, Fei (J Alzheimers Dis, 2017)
Docosahexaenoic acid (DHA) is important for brain function, and higher DHA intake is inversely correlated with relative risk of Alzheimer's disease. The potential benefits of DHA supplementation in people with mild cognitive impairment (MCI) have not been fully examined. Our study aimed to determine the effect of DHA supplementation on cognitive function and hippocampal atrophy in elderly subjects with MCI. This was a randomized, double-blind, placebo-controlled trial in Tianjin, China. 240 individuals with MCI aged 65 years and over were recruited and equalized randomly allocated to the DHA or the placebo group. Participants received 12-month DHA supplementation (2 g/day) or corn oil as placebo. Both global and specific subdomains of cognitive function and hippocampal volume were measured at baseline, 6 months, and 12 months. Both changes were analyzed by repeated-measure analysis of variance (ANOVA). This trial has been registered: ChiCTR-IOR-15006058. A total of 219 participants (DHA: 110, Placebo: 109) completed the trial. The change in mean serum DHA levels was greater in the intervention group (+3.85%) compared to the control group (+1.06%). Repeated-measures analyses of covariance showed that, over 12 months, there was a significant difference in the Full-Scale Intelligence Quotient (ηp2 = 0.084; p = 0.039), Information (ηp2 = 0.439; p = 0.000), and Digit Span (ηp2 = 0.375; p = 0.000) between DHA-treated versus the placebo group. In addition, there were significant differences in volumes of left hippocampus (ηp2 = 0.121, p = 0.016), right hippocampus (ηp2 = 0.757, p = 0.008), total hippocampus (ηp2 = 0.124, p = 0.023), and global cerebrum (ηp2 = 0.145, p = 0.032) between the two groups. These findings suggest that DHA supplementation (2 g/day) for 12 months in MCI subjects can significantly improve cognitive function and slow the progression of hippocampal atrophy. Larger, longer-term confirmatory studies are warranted.

Effects of Healthy Aging and Mild Cognitive Impairment on a Real-Life Decision-Making Task. - Pertl, Marie-Theres; Benke, Thomas; Zamarian, Laura; Delazer, Margarete (J Alzheimers Dis, 2017)
In this study, we investigated the effects of age and of mild cognitive impairment (MCI) on decision making under risk by adopting a task representing real-life health-related situations and involving complex numerical information. Moreover, we assessed the relationship of real-life decision making to other cognitive functions such as number processing, executive functions, language, memory, and attention. For this reason, we compared the performance of 19 healthy, relatively younger adults with that of 18 healthy older adults and the performance of the 18 healthy older adults with that of 17 patients with MCI. Results indicated difficulties in real-life decision making for the healthy older adults compared with the healthy, relatively younger adults. Difficulties of patients with MCI relative to the healthy older adults arose in particular in difficult items requiring processing of frequencies and fractions. Significant effects of age and of MCI in processing frequencies were also evident in a ratio number comparison task. Decision-making performance of healthy participants and of the patient group correlated significantly with number processing. There was a further significant correlation with executive functions for the healthy participants and with reading comprehension for the patients. Our results suggest that healthy older individuals and patients with MCI make less advantageous decisions when the information is complex and high demands are put on executive functions and numerical abilities. Moreover, we show that executive functions and numerical abilities are not only essential in laboratory gambling tasks but also in more realistic and ecological decision situations within the health context.

The Effects of LW-AFC on the Hippocampal Transcriptome in Senescence-Accelerated Mouse Prone 8 Strain, a Mouse Model of Alzheimer's Disease. - Wang, Jianhui; Liu, Yang; Cheng, Xiaorui; Zhang, Xiaorui; Liu, Feng; Liu, Gang; Qiao, Shanyi; Ni, Ming; Zhou, Wenxia; Zhang, Yongxiang; Li, Fei (J Alzheimers Dis, 2017)
The senescence-accelerated mouse prone 8 (SAMP8) strain is considered a robust experimental model for developing preventative and therapeutic treatments for Alzheimer's disease (AD), a neurodegenerative disease which cannot be effectively prevented, halted, or cured. Our previous studies showed that LW-AFC, a new formula derived from the classical traditional Chinese medicinal prescription Liuwei Dihuang decoction, ameliorates cognitive deterioration in PrP-hAβPPswe/PS1ΔE9 transgenic mice and SAMP8 mice. This study aims to investigate the mechanism that mediates how LW-AFC improves cognitive deficit on the basis of the transcriptome. We conducted a genome-wide survey of gene expression in the hippocampus in mice from the senescence accelerated mouse resistant 1 (SAMR1) strain, from SAMP8 and from LW-AFC treated SAMP8. The results showed that LW-AFC reversed the transcriptome in the hippocampus of SAMP8 mice. The specific investigation of altered gene expression in subtypes defined by cognitive profiles indicated that the systemic lupus erythematosus pathway, spliceosomes, amyotrophic lateral sclerosis, and the insulin signaling were involved in the improvement of cognitive ability by LW-AFC. The expression of genes Enpp2, Etnk1, Epdr1, and Gm5900 in the hippocampus were correlated with that of LW-AFC's ameliorating cognitive impairment in SAMP8 mice. Because LW-AFC is composed of polysaccharides, glycosides, and oligosaccharides, we infer that LW-AFC has direct or indirect effects on altering gene expressions and regulating pathways in the hippocampus of SAMP8 mice. These data are helpful for the enhanced identification of LW-AFC as new therapeutic modalities to AD.

Effects of Short-Term Exercise Interventions on Behavioral and Psychological Symptoms in Patients with Dementia: A Systematic Review. - Fleiner, Tim; Leucht, Stefan; Förstl, Hans; Zijlstra, Wiebren; Haussermann, Peter (J Alzheimers Dis, 2017)
Observational and interventional studies indicate a direct link between the patients' physical activity and the extent of behavioral and psychological symptoms of dementia (BPSD). At present, there are no evidence-based recommendations for physical exercise in the acute dementia care settings. Hence, this systematic review investigates the effects of short-term exercise trials on BPSD. Trials with a length up to three months investigating the effects of structured exercise interventions on BPSD in acute dementia care settings were included. Five trials, referring to a total of N = 206 patients, met the inclusion criteria. The trial durations ranged from three up to twelve weeks. All trials conducted three sessions per week of 30 to 45 minutes. Three trials reported significant reductions of BPSD and differences in comparison to the pre-test and control groups. Out of the three trials investigating the effects of exercise interventions on depressive symptoms, one reported significant reduction and two reported no differences in pre-post analysis. Exercise represents a potentially worthwhile approach for the treatment of patients suffering from BPSD. Given the scarcity of available studies, more randomized controlled short-term exercise trials in acute dementia care settings are needed to define appropriate exercise recommendations for clinicians treating these patients.

Efficacy and Safety of Donepezil in Chinese Patients with Severe Alzheimer's Disease: A Randomized Controlled Trial. - Jia, Jianping; Wei, Cuibai; Jia, Longfei; Tang, Yi; Liang, Junhua; Zhou, Aihong; Li, Fangyu; Shi, Lu; Doody, Rachelle S (J Alzheimers Dis, 2017)
BACKGROUND: Donepezil has been used worldwide for the treatment of severe Alzheimer's disease (AD). Whether it is also appropriate for severe AD in Chinese patients remains unknown. OBJECTIVE: To determine whether donepezil is effective and tolerable for Chinese patients with severe AD. METHODS: The present study was a 24-week, multicenter, double-blind, randomized, placebo-controlled, parallel-group study conducted at 38 investigational hospitals in China. Patients with severe AD were enrolled in this trial. Patients were randomly assigned in a 1:1 ratio to receive either donepezil or placebo (5 mg for 6 weeks and10 mg for the remaining 18 weeks). The efficacy for donepezil were evaluated by the SIB, the Clinician's Interview-Based Impression of Change-Plus caregiver input (CIBIC-plus) and the MMSE. Safety parameters were monitored throughout. RESULTS: A total of 313 patients included the donepezil (n = 157) and the placebo groups (n = 156). Donepezil group improved more in SIB scores (least squares [LS] mean difference: 4.8, 95% CI 1.56 to 8.08, p = 0.004) and CIBIC-plus scores (drug-placebo difference: -0.4, 95% CI -0.66 to 0.03, p = 0.04) than placebo groups at Week 24. The MMSE scores between drug and placebo groups did not differ significantly. Twenty-nine patients with serious adverse events (SAEs) were reported in donepezil (n = 11) and placebo groups (n = 18) (p = 0.08). Most SAEs were not considered drug-related. CONCLUSION: Donepezil for 24 weeks was more effective than placebo and showed good safety and tolerability in Chinese patients with severe AD. This study supports utility of the drug in severe stages of AD in the Chinese population.

Elevation of Peripheral BDNF Promoter Methylation Predicts Conversion from Amnestic Mild Cognitive Impairment to Alzheimer's Disease: A 5-Year Longitudinal Study. - Xie, Bing; Xu, Yao; Liu, Zanchao; Liu, Wenxuan; Jiang, Lei; Zhang, Rui; Cui, Dongsheng; Zhang, Qingfu; Xu, Shunjiang (J Alzheimers Dis, 2017)
Epigenetic aberrations have been identified as biomarkers to predict the risk of Alzheimer's disease (AD). This study aimed to evaluate whether altered DNA methylation status of BDNF promoter could be used as potential epigenetic biomarkers for predicting the progression from amnestic mild cognitive impairment (aMCI) to AD. A total of 506 aMCI patients and 728 cognitively normal controls were recruited in the cross-sectional analyses. Patients (n = 458) from aMCI cohort were classified into two groups after 5-year follow-up: aMCI-stable group (n = 330) and AD-conversion group (n = 128). DNA methylation of BDNF promoter was detected by bisulfite-PCR amplification and pyrosequencing. The DNA methylation levels of CpG1 and CpG2 in promoter I and CpG5 and CpG6 in promoter IV of BDNF gene were significantly higher in the aMCI group than in the control group at baseline and also were increased in the conversion group compared with the non-conversion group at 5-year follow up time point. CpG5 in BDNF promoter IV had the highest AUC of 0.910 (95% CI: 0.817-0.983, p < 0.05). Kaplan-Meier analysis showed a significant AD conversion propensity for aMCI patients with high methylation levels of CpG5 (HR = 1.96, 95% CI: 1.07-2.98, p < 0.001). Multivariate Cox regression analysis revealed elevated methylation status of CpG5 was a significant independent predictor for AD conversion (HR = 3.51, p = 0.013). These results suggest that elevation of peripheral BDNF promoter methylation might be used as potential epigenetic biomarkers for predicting the conversion from aMCI to AD.

Evaluation of the Reliability, Validity, and Predictive Validity of the Subscales of the Perceived Stress Scale in Older Adults. - Jiang, Julie M; Seng, Elizabeth K; Zimmerman, Molly E; Sliwinski, Martin; Kim, Mimi; Lipton, Richard B (J Alzheimers Dis, 2017)
BACKGROUND: The Perceived Stress Scale (PSS) is made up of two subscales but is typically used as a single summary measure. However, research has shown that the two subscales may have differential properties in older adults. OBJECTIVE: To evaluate the internal consistency, test-retest reliability, and the concurrent and predictive validity for development of amnestic mild cognitive impairment (aMCI) of the positively-worded (PSS-PW) and negatively-worded (PSS-NW) subscale scores of the PSS in older adults. METHODS: We recruited community residing older adults free of dementia from the Einstein Aging Study. Reliability of the PSS-PW and PSS-NW was assessed using Cronbach's alpha for internal consistency and intraclass correlation for one year test-retest reliability. Concurrent validity was evaluated by examining the relationship between the PSS subscales and depression, anxiety, neuroticism, and positive and negative affect. Predictive validity was assessed using multivariate Cox regression analyses to examine the relationship between baseline PSS-PW and PSS-NW score and subsequent onset of aMCI. RESULTS: Both PSS-PW and PSS-NW showed adequate internal consistency and retest reliabilities. Both the PSS-PW and PSS-NW were associated with depression, neuroticism, and negative affect. The PSS-NW was uniquely associated with anxiety while the PSS-PW was uniquely associated with positive affect. Only the PSS-PW was associated with a statistically significant increased risk of incident aMCI (HR = 1.27; 95% CI: 1.06-1.51 for every 5-point increase in PSS-PW). CONCLUSIONS: Evaluating the separate effects of the two PSS subscales may reveal more information than simply using a single summation score. Future research should investigate the PSS-PW and PSS-NW as separate subscales.

The Experiences of People with Dementia and Their Caregivers in Dementia Diagnosis. - Lian, Yan; Xiao, Lily Dongxia; Zeng, Fan; Wu, Xianmu; Wang, Zhen; Ren, Hui (J Alzheimers Dis, 2017)
BACKGROUND: People can live well with dementia if they are diagnosed early and receive early interventions and appropriate dementia management and care. However, dementia is currently under-detected and under-diagnosed. The diagnosis rate is around 50% only in higher-income countries and 5-10% only in low- and middle-income countries. Studies on consumers' experiences in engaging in dementia diagnosis in a socio-cultural context are much needed in order to generate research evidence to inform person-centered dementia care and services. OBJECTIVE: The aim of the study was to understand the experiences of people with dementia and their caregivers in engaging in dementia diagnosis. METHODS: An interpretative study design informed by Gadamer's hermeneutic principles was applied to the present study to achieve the aim of the study. The study was strengthened by applying a social ecological framework to the study design. In total, 23 participants contributed to the interviews or focus group. Thematic analysis was applied to data analysis. RESULTS: Four themes were determined from data and described as: capabilities to detect the memory loss in an early stage, perceptions and beliefs of dementia in the community, different journeys toward the diagnosis and expectations of a smooth journey for others. These findings illuminate a social ecological perspective of improving early detection and timely diagnosis of dementia in the community settings. CONCLUSION: The findings of this study have implications for policy, resource, and practice development. Consumers expect that government subsidized dementia care services in primary care and specialist care settings are needed in order to enable consumer-driven timely diagnosis and dementia management in home care settings.

Exploring Potential Electrophysiological Biomarkers in Mild Cognitive Impairment: A Systematic Review and Meta-Analysis of Event-Related Potential Studies. - Gu, Lihua; Zhang, Zhijun (J Alzheimers Dis, 2017)
BACKGROUND: Early diagnosis and effective management are pivotal steps in preventing the transition from mild cognitive impairment (MCI) to Alzheimer's disease. Previous investigations indicated that some event-related potential (ERP) components in MCI are sensitive to cognitive decline. However, several comparative analyses of these components in MCI and healthy controls (HC) yielded inconsistent results. OBJECTIVE: The aim was to perform a systematic review and meta-analysis of ERP studies on MCI patients. METHODS: We systematically searched on PubMed and Web of Science for MCI-related ERP studies published from April 1986 to August 2016. Standard mean difference estimates of all components were compared between MCI and HC. RESULTS: Our study showed increased P50 amplitude at the Cz site; reduced N2pc amplitude and delayed P200 latency at the Cz site; N200 latency at the Cz and Pz sites, and P300 latency at the Cz and Pz sites in MCI patients compared to HC. CONCLUSIONS: In summary, our study indicated that some ERP components, such as P50 and N2pc amplitude, P200, N200, and P300 latency might be potential electrophysiological biomarkers for MCI diagnosis.

Four Decades of Research in Alzheimer's Disease (1975-2014): A Bibliometric and Scientometric Analysis. - Serrano-Pozo, Alberto; Aldridge, Georgina M; Zhang, Qiang (J Alzheimers Dis, 2017)
BACKGROUND: Bibliometric and scientometric methods can be applied to the study of a research field. OBJECTIVE: We hypothesized that a bibliometric and scientometric analysis of the Alzheimer's disease (AD) research field could render trends that provide researchers and funding agencies valuable insight into the history of the field, current tendencies, and potential future directions. METHODS: We performed searches in publicly available databases including PubMed, Scopus, Web of Science, and Alzheimer's Funding Analyzer for the period 1975-2014, and conducted a curve fitting analysis with non-linear regression. RESULTS: While the rate and impact of publications continue to increase, the number of patents per year is currently declining after peaking in the late 2000s, and the funding budget has plateaued in the last 5-10 years analyzed. Genetics is the area growing at a fastest pace, whereas pathophysiology and therapy have not grown further in the last decade. Among the targets of pathophysiology research, amyloid-β continues to be the focus of greatest interest, with tau and apolipoprotein E stagnant after a surge in the 1990s. The role of inflammation, microglia, and the synapse are other research topics with growing interest. Regarding preventative strategies, education attainment, diet, and exercise are recently gaining some momentum, whereas NSAIDs and statins have lost the spotlight they once had. CONCLUSION: Our bibliometric and scientometric analysis provides distinct trends in AD research in the last four decades, including publication and patent output, funding, impact, and topics. Our findings could inform the decision-making of research funding agencies in the near future.

Functional Reserve: Experience Participating in Instrumental Activities of Daily Living is Associated with Gender and Functional Independence in Mild Cognitive Impairment. - Berezuk, Courtney; Zakzanis, Konstantine K; Ramirez, Joel; Ruocco, Anthony C; Edwards, Jodi D; Callahan, Brandy L; Black, Sandra E (J Alzheimers Dis, 2017)
BACKGROUND: Gender differences in instrumental activities of daily living (IADLs) in mild cognitive impairment (MCI) and Alzheimer's disease may be explained by gender differences in IADL involvement. OBJECTIVE: We introduce a novel theoretical construct, termed functional reserve, and empirically examine gender differences in IADL experience as a proxy of this reserve. METHODS: We cross-sectionally examined men (n = 502) and women (n = 340) with MCI from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Demographic factors, depressive symptoms, neuropsychological scores, and IADL experience were included as independent variables and total Functional Activities Questionnaire (FAQ) scores as the dependent variable. Regression analyses were performed on the full cohort and stratified by gender to identify differential predictive relationships for men and women. RESULTS: Gender was associated with total FAQ (p < 0.05) until adjusting for IADL experience. Furthermore, the combination of cognitive measures accounted for the most variance in functional dependence (12% explained, p < 0.001), although IADL experience was the most important single variable (4.8% explained, p < 0.001). Stratification by gender revealed that IADL experience accounted for 6.6% of the variance in FAQ score in men (p < 0.001) but only 2.4% in women (p = 0.001); however, the interaction between gender and experience was not statistically significant. DISCUSSION: A small effect of men showing greater functional dependence in MCI may be explained by lower IADL experience. Additionally, IADL experience was associated with superior functioning in all analyses, potentially through increased functional reserve. This concept of functional reserve may have implications for identifying individuals at risk for IADL dependence, preventing or delaying decline, and potentially treating functional impairment.

Genetic Deletion of Tumor Necrosis Factor-α Attenuates Amyloid-β Production and Decreases Amyloid Plaque Formation and Glial Response in the 5XFAD Model of Alzheimer's Disease. - Paouri, Evi; Tzara, Ourania; Zenelak, Sofia; Georgopoulos, Spiros (J Alzheimers Dis, 2017)
Increasing evidence suggests that neuroinflammation comprises a major characteristic of Alzheimer's disease (AD). Tumor necrosis factor-α (TNF-α) is a pleiotropic pro-inflammatory cytokine implicated in neurodegenerative diseases including AD, and has been proposed as a potent therapeutic target for AD. Although a number of studies focusing on pharmacological or genetic manipulation of TNF-α and its receptors in AD mice have provided significant knowledge regarding the role of TNF-α signaling pathway in the pathogenesis of AD, the consequences of TNF-α genetic deletion have not been thoroughly examined. Here, we focused on the effect of TNF-α deficiency on the amyloid phenotype of 5XFAD mice. Our analysis revealed that amyloid deposition, amyloid-β (Aβ) levels, and AβPP-carboxyterminal fragments are significantly reduced in the brains of 5XFAD/TNF-α-/- mice compared to the 5XFAD/TNF-α+/+. We found decreased protein levels of β- and α-secretases in the 5XFAD/TNF-α-/- brains, suggesting for an effect of TNF-α on AβPP processing and Aβ generation. We also show for the first time that TNF-α affects PS1in vivo, as 5XFAD mice lacking TNF-α expression display reduced PS1-carboxyterminal fragments implying for diminished PS1 activity. Moreover, TNF-α deficiency decreases microglial and astrocytic activation and significantly restricts the phagocytic activity of macrophages against Aβ, supporting for reduced responsiveness of phagocytes toward Aβ. Overall, our results reveal that TNF-α genetic deletion in 5XFAD mice attenuates amyloid plaque formation by lowering Aβ generation through the reduction of functionally active PS1 and β-secretase rather than promoting Aβ clearance by phagocytic cells. Our data further suggest TNF-α inhibition as a therapeutic approach for AD.

The Gut Microbiota and Alzheimer's Disease. - Jiang, Chunmei; Li, Guangning; Huang, Pengru; Liu, Zhou; Zhao, Bin (J Alzheimers Dis, 2017)
The gut microbiota comprises a complex community of microorganism species that resides in our gastrointestinal ecosystem and whose alterations influence not only various gut disorders but also central nervous system disorders such as Alzheimer's disease (AD). AD, the most common form of dementia, is a neurodegenerative disorder associated with impaired cognition and cerebral accumulation of amyloid-β peptides (Aβ). Most notably, the microbiota-gut-brain axis is a bidirectional communication system that is not fully understood, but includes neural, immune, endocrine, and metabolic pathways. Studies in germ-free animals and in animals exposed to pathogenic microbial infections, antibiotics, probiotics, or fecal microbiota transplantation suggest a role for the gut microbiota in host cognition or AD-related pathogenesis. The increased permeability of the gut and blood-brain barrier induced by microbiota dysbiosis may mediate or affect AD pathogenesis and other neurodegenerative disorders, especially those associated with aging. In addition, bacteria populating the gut microbiota can secrete large amounts of amyloids and lipopolysaccharides, which might contribute to the modulation of signaling pathways and the production of proinflammatory cytokines associated with the pathogenesis of AD. Moreover, imbalances in the gut microbiota can induce inflammation that is associated with the pathogenesis of obesity, type 2 diabetes mellitus, and AD. The purpose of this review is to summarize and discuss the current findings that may elucidate the role of the gut microbiota in the development of AD. Understanding the underlying mechanisms may provide new insights into novel therapeutic strategies for AD.

Higher Peripheral TREM2 mRNA Levels Relate to Cognitive Deficits and Hippocampal Atrophy in Alzheimer's Disease and Amnestic Mild Cognitive Impairment. - Tan, Yi Jayne; Ng, Adeline S L; Vipin, Ashwati; Lim, Joseph K W; Chander, Russell J; Ji, Fang; Qiu, Yingwei; Ting, Simon K S; Hameed, Shahul; Lee, Tih-Shih; Zeng, Li; Kandiah, Nagaendran; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Variants in triggering receptor expressed on myeloid cells 2 (TREM2) are associated with increased Alzheimer's disease (AD) risk. Recent studies have reported inconsistent peripheral TREM2 mRNA expression levels and relationship with cognitive scores in AD and mild cognitive impairment (MCI). Additionally, no study has examined the association of peripheral TREM2 levels with neuroimaging measures in AD and MCI. OBJECTIVE: To determine peripheral TREM2 mRNA levels in AD, amnestic MCI (aMCI) and healthy controls, and the association with cognitive performance and brain structural changes. METHODS: We measured peripheral TREM2 mRNA levels in 80 AD, 30 aMCI, and 86 healthy controls using real time polymerase chain reaction. TREM2 levels were correlated with various cognitive performance and brain volumes, correcting for APOE4 status. RESULTS: TREM2 mRNA levels were significantly higher in AD compared to controls and aMCI. Levels did not differ between aMCI and controls. Corrected for APOE4, higher TREM2 levels correlated with lower Mini-Mental State Examination, Montreal Cognitive Assessment (MoCA) and episodic memory scores, and lower total grey matter and right hippocampal volumes. Whole-brain voxel-based morphometry analysis found negative association between TREM2 mRNA levels and grey matter volumes in temporal, parietal and frontal regions. AD subjects with MoCA scores ≤20 had higher TREM2 levels correlating with smaller total grey matter, left hippocampal and right hippocampal volumes. CONCLUSION: Peripheral TREM2 mRNA levels are higher in AD and are associated with AD-related cognitive deficits and hippocampal atrophy. Our findings suggest that TREM2 may be a potential non-invasive peripheral biomarker for AD diagnosis.

Impaired Center-Surround Suppression in Patients with Alzheimer's Disease. - Zhuang, Xianbo; Chen, Yanxiu; Zhuang, Xianpeng; Xing, Tao; Chen, Tuanzhi; Jiang, Guisheng; Yang, Xiafeng (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is often associated with declined visual processing abilities. Here we tested whether the functions of center-surround suppression- a hallmark property in the visual system- are altered by AD. To this end, we recruited three groups of participants (AD, elderly, and young) in a motion direction discrimination task, in which we measured the temporal duration threshold of a  drifting Gabor with varying stimulus sizes. We first replicated the phenomena of center-surround suppression that the required duration for discriminating a high contrast grating decreases with increasing stimulus size. We then showed that the magnitudes of suppression varied among the three groups. There was progressive reduction of suppression in the elderly and AD groups compared with the young group. Interestingly, we found that the levels of suppression can predict the severity of dementia in the AD group. Our results suggest that AD is associated with impaired center-surround functions in the visual motion processing pathway.

Implication of the APP Gene in Intellectual Abilities. - Myrum, Craig; Nikolaienko, Oleksii; Bramham, Clive R; Haavik, Jan; Zayats, Tetyana (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive functions are highly heritable and polygenic, though the source of this genetic influence is unclear. On the neurobiological level, these functions rely on effective neuroplasticity, in which the activity-regulated cytoskeleton associated protein (ARC) plays an essential role. OBJECTIVES: To examine whether the ARC gene complex may contribute to the genetic components of intellectual function given the crucial role of ARC in brain plasticity and memory formation. METHODS: The ARC complex was tested for association with intelligence (IQ) in children from the Avon Longitudinal Study of Parents and Children (ALSPAC, N = 5,165). As Alzheimer's disease (AD) shares genetics with cognitive functioning, the association was followed up in an AD sample (17,008 cases, 37,154 controls). RESULTS: The ARC complex revealed association with verbal and total IQ (empirical p = 0.027 and 0.041, respectively) in the ALSPAC. The strongest single variant signal (rs2830077; empirical p = 0.018), within the APP gene, was confirmed in the AD sample (p = 2.76E-03). Functional analyses of this variant showed its preferential binding to the transcription factor CP2. DISCUSSION: This study implicates APP in childhood IQ. While follow-up studies are needed, this observation could help elucidate the etiology of disorders associated with cognitive dysfunction, such as AD.

Incident Cerebral Microbleeds Detected by Susceptibility Weight-Imaging Help to Identify Patients with Mild Cognitive Impairment Progressing to Alzheimer's Disease. - Basselerie, Hubert; Bracoud, Luc; Zeestraten, Eva; Bouguen, Eva; Kiyasova, Vera; Pueyo, Maria; Cognard, Christophe; Dumas, Hervé; Gramada, Raluca; Ousset, Pierre Jean; Vellas, Bruno; Bonneville, Fabrice (J Alzheimers Dis, 2017)
BACKGROUND: The relationship between cerebral microbleeds (CMB) and Alzheimer's disease (AD) has not yet been clearly determined, particularly with susceptibility weight-imaging (SWI). OBJECTIVE: To evaluate the SWI sequence using 3T MRI for the detection of CMB, and its ability to differentiate elderly control subjects (CS), stable mild cognitive impairment patients (MCI-s), MCI patients progressing to AD (MCI-p), and AD patients. METHODS: It was a prospective, monocentric, observational study that took place in Toulouse, France. Participants were 65 years and older, enrolled in three groups: CS, MCI, and AD. Based on the longitudinal analysis of cognitive decline, MCI subjects were retrospectively classified as MCI-s or MCI-p. Each patient had a 4-year follow-up with MRI at baseline (MRI#1) and during the fourth year (MRI#3). CMB were counted on native SWI images juxtaposed to minIP reformatted images. RESULTS: 150 patients were enrolled: 48 CS, 25 MCI-s, 18 MCI-p, 59 AD. At MRI#1 and at MRI#3, there was no significant difference in the prevalence of CMB between groups (p = 0.75 and p = 0.87). In the MCI-p + AD group, significantly more subjects had≥4 incident CMB compared to the CS + MCI-s group (p = 0.016). In the MCI-p + AD group, the prevalence of patients with >4 CMB was significantly higher at MRI#3 than at MRI#1 (p = 0.008). CONCLUSION: Using SWI, AD and MCI-p patients had developed significantly more new CMB than CS and MCI-s patients during the follow-up. Incident CMB might be suggested as a potential imaging marker of AD progression.

Increased PCSK9 Cerebrospinal Fluid Concentrations in Alzheimer's Disease. - Zimetti, Francesca; Caffarra, Paolo; Ronda, Nicoletta; Favari, Elda; Adorni, Maria Pia; Zanotti, Ilaria; Bernini, Franco; Barocco, Federica; Spallazzi, Marco; Galimberti, Daniela; Ricci, Chiara; Ruscica, Massimiliano; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) has been associated with dysregulation of brain cholesterol trafficking and abnormal production of apolipoprotein E isoform 4 (apoE4). Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a protein present in serum and cerebrospinal fluid (CSF) degrading the low-density lipoprotein receptor (LDLr) and other apoE-binding receptors involved in neuron cholesterol uptake. The role of PCSK9 in AD is controversial. OBJECTIVE: We compared PCSK9 levels in CSF of AD patients and non-AD controls and looked at correlations with CSF total apoE and apoE4. METHODS: CSF from AD (n = 30) and from age and sex-matched non-AD patients (n = 30) was collected by lumbar puncture for routine diagnosis. CSF PCSK9, total apoE, and apoE4 levels were measured by ELISA. AD patients showed the typical CSF neurobiomarker pattern (decreased Aβ42 and increased tau and phospho-tau) and impaired cognitive performances, as indicated by the scores of the Mini-Mental State Examination test. RESULTS: PCSK9 levels in CSF were higher in AD than in non-AD subjects (+1.45 fold; p = 0.0049). CSF total apoE concentrations did not differ between the two groups, while apoE4 levels were higher in AD subjects (+3.34 fold; p = 0.0068). Considering all samples, a significant positive correlation was found between PCSK9 and apoE4 (r = 0.4409; p = 0.0006). PCSK9 levels were higher in APOE ɛ4 carriers, reaching statistical significance in the AD group (+1.45 fold; p = 0.0454). CONCLUSION: These results report for the first time an alteration of CSF PCSK9 levels in AD and suggest a pathophysiological link between PCSK9, apoE4, and AD.

Increased Serum miR-206 Level Predicts Conversion from Amnestic Mild Cognitive Impairment to Alzheimer's Disease: A 5-Year Follow-up Study. - Xie, Bing; Liu, Zanchao; Jiang, Lei; Liu, Wei; Song, Mei; Zhang, Qingfu; Zhang, Rui; Cui, Dongsheng; Wang, Xueyi; Xu, Shunjiang (J Alzheimers Dis, 2017)
Evidence suggests that individuals with amnestic mild cognitive impairment (aMCI) tend to progress to probable Alzheimer's disease (AD) with aging. This study was performed to examine whether circulating miRNAs could be potential predictors for the progression of aMCI to AD. A total of 458 patients with aMCI were included in this study, and the clinical data were collected at two time points: the baseline and the follow-up assessment. These aMCI patients were classified into two groups after 5 years: aMCI-stable group (n = 330) and AD-conversion group (n = 128). The expression of miR-206 and miR-132 and the levels of BDNF and SIRT1 in serum were detected using a quantitative real-time RT-PCR (qPCR) and the ELISA method, respectively. Kaplan-Meier method (Log-rank test) was used for univariate survival analysis. Cox proportional hazard model was used to estimate the prognostic value of miRNAs in conversion from aMCI to AD. At the baseline, serum levels of miR-206 in aMCI-AD group were significantly elevated compared to aMCI-aMCI group and the same trend was found at 5-year follow-up time point as well. There were no significant differences in serum levels of miR-132 between the conversion and non-conversion group at both time points. Kaplan-Meier analysis showed significant correlation between AD conversion and higher serum levels of miR-206 for aMCI patients (HR = 3.60, 95% CI: 2.51- 5.36, p < 0.001). Multivariate Cox regression analysis revealed that serum miR-206 and its target BDNF were significant independent predictors for AD conversion (HR = 4.22, p < 0.001). These results suggested that increased serum miR-206 level might be a potential predictor of conversion from aMCI to AD.

Inflammation, Amyloid, and Atrophy in The Aging Brain: Relationships with Longitudinal Changes in Cognition. - Sala-Llonch, Roser; Idland, Ane-Victoria; Borza, Tom; Watne, Leiv Otto; Wyller, Torgeir Bruun; Brækhus, Anne; Zetterberg, Henrik; Blennow, Kaj; Walhovd, Kristine Beate; Fjell, Anders Martin (J Alzheimers Dis, 2017)
Amyloid deposition occurs in aging, even in individuals free from cognitive symptoms, and is often interpreted as preclinical Alzheimer's disease (AD) pathophysiology. YKL-40 is a marker of neuroinflammation, being increased in AD, and hypothesized to interact with amyloid-β (Aβ) in causing cognitive decline early in the cascade of AD pathophysiology. Whether and how Aβ and YKL-40 affect brain and cognitive changes in cognitively healthy older adults is still unknown. We studied 89 participants (mean age: 73.1 years) with cerebrospinal fluid samples at baseline, and both MRI and cognitive assessments from two time-points separated by two years. We tested how baseline levels of Aβ42 and YKL-40 correlated with changes in cortical thickness and cognition. Thickness change correlated with Aβ42 only in Aβ42+ participants (<600 pg/mL, n = 27) in the left motor and premotor cortices. Aβ42 was unrelated to cognitive change. Increased YKL-40 was associated with less preservation of scores on the animal naming test in the total sample (r = -0.28, p = 0.012) and less preservation of a score reflecting global cognitive function for Aβ42+ participants (r = -0.58, p = 0.004). Our results suggest a role for inflammation in brain atrophy and cognitive changes in cognitively normal older adults, which partly depended on Aβ accumulation.

Inflection Point in Course of Mild Cognitive Impairment: Increased Functional Connectivity of Default Mode Network. - Tao, Wuhai; Li, Xin; Zhang, Junying; Chen, Yaojing; Ma, Chao; Liu, Zhen; Yang, Caishui; Wang, Wenxiao; Chen, Kewei; Wang, Jun; Zhang, Zhanjun (J Alzheimers Dis, 2017)
The alteration of the default mode network (DMN) functional connectivity (FC) has been reported in patients with amnestic mild cognitive impairment (aMCI) as a predictor of Alzheimer's disease (AD). However, no studies exist that examined stage-dependent DMN FC changes throughout the course of aMCI. The present study aims to characterize patterns of DMN FC over three aMCI stages as first defined. Utilizing the extreme groups approach on the performance of memory tasks, aMCI subjects were divided into mild, moderate, and severe stages. Independent component analysis was used to assess DMN for individual patients in each of the three cross-sectionally defined stages. Instead of finding that continued monotonic decline was the case for the hippocampus volume, which we also investigated in this study, we observed an increase in DMN functional connectivity from mild aMCI to moderate aMCI and a decrease to severe aMCI, mainly in the left precuneus and superior parietal lobe. Moreover, the FC was significantly associated with cognitive performance. Though a longitudinal study is needed to confirm these results, our cross-sectional finding is that non-linear FC changes in DMN could be a characteristic of prodromal early disease development.

Integration of Multilocus Genetic Risk into the Default Mode Network Longitudinal Trajectory during the Alzheimer's Disease Process. - Su, Fan; Shu, Hao; Ye, Qing; Xie, Chunming; Yuan, Baoyu; Zhang, Zhijun; Bai, Feng (J Alzheimers Dis, 2017)
The aim of the study was to investigate the cognitive significance of the changes in default mode network (DMN) during the process of Alzheimer's disease (AD) and the genetic basis that drives the alteration. Eighty-seven subjects with mild cognitive impairment (MCI) and 131 healthy controls (HC) were employed at baseline, and they had the genetic risk scores (GRS) based on the GWAS-validated AD-related top loci. Eleven MCIs who converted to AD (c-MCIs), 32 subjects who remained stable (nc-MCIs), and 56 HCs participated in the follow-up analyses after an average of 35 months. Decreased functional connectivity (FC) within temporal cortex was identified for MCIs at baseline, which was partially determined by the GRS; moreover, compensations may occur within the frontal-parietal brain to maintain relatively intact cognition. During the follow-ups, c-MCIs exhibited more FC declines within the prefrontal-parietal lobes and parahippocampal gyrus/hippocampus than the HCs and nc-MCIs. The GRS did not significantly vary among the three groups, whereas associations were identified at risky alleles and FC declines in all AD spectra. Interestingly, the influence of APOEɛ4 varied as the disease progressed; APOEɛ4 was associated with longitudinal FC decreases only for HCs in the single variance-based analyses and deteriorated DMN integration in nc-MCIs by combining the effects of other loci. However, the GRS without APOEɛ4 predicted FC decline for converters. It is suggested that the integration of multilocus genetic risk predicted the longitudinal trajectory of DMN and may be used as a clinical strategy to track AD progression.

Interactive Effects of Dementia Severity and Comorbidities on Medicare Expenditures. - Zhu, Carolyn W; Cosentino, Stephanie; Ornstein, Katherine A; Gu, Yian; Andrews, Howard; Stern, Yaakov (J Alzheimers Dis, 2017)
BACKGROUND: Few studies have examined how dementia and comorbidities may interact to affect healthcare expenditures. OBJECTIVE: To examine whether effects of dementia severity on Medicare expenditures differed for individuals with different levels of comorbidities. METHODS: Data are drawn from the Washington Heights-Inwood Columbia Aging Project (WHICAP). Comprehensive clinical assessments of dementia severity were systematically carried out at ∼18 month intervals. Dementia severity was measured by Clinical Dementia Rating (CDR). Comorbidities were measured by a modified Elixhauser comorbidities index. Generalized linear models examined effects of dementia severity, comorbidities, and their interactions on Medicare expenditures (1999-2010). RESULTS: At baseline, 1,280 subjects were dementia free (CDR = 0, 66.4%), 490 had very mild dementia (CDR = 0.5, 25.4%), 108 had mild dementia (CDR = 1, 5.6%), and 49 had moderate/severe dementia (CDR = 2/3, 2.5%). Average annual Medicare expenditures for individuals with moderate/severe dementia were more than twice as high as those who were dementia free (CDR = 0: $9,108, CDR = 0.5/1: $11,664, CDR≥2: $19,604, p < 0.01). Expenditures were approximately 10 times higher among those with≥3 comorbidities than among those with no comorbidities ($2,612 for those with no comorbidities, to $6,109 for those with 1, $10,656 for those with 2, and $30,244 for those with≥3 comorbidities, p < 0.001). Dementia severity was associated with higher expenditures, but comorbidities were the most important predictor of expenditures. We did not find strong interaction effects between number of comorbidities and dementia severity. CONCLUSIONS: Increasing dementia severity and higher comorbidities are associated with higher Medicare expenditures. Care of individuals with dementia should focus on management of comorbidities.

Intracranial Arterial 4D Flow in Individuals with Mild Cognitive Impairment is Associated with Cognitive Performance and Amyloid Positivity. - Berman, Sara E; Clark, Lindsay R; Rivera-Rivera, Leonardo A; Norton, Derek; Racine, Annie M; Rowley, Howard A; Bendlin, Barbara B; Blennow, Kaj; Zetterberg, Henrik; Carlsson, Cynthia M; Asthana, Sanjay; Turski, Patrick; et al. (J Alzheimers Dis, 2017)
It is becoming increasingly recognized that cerebrovascular disease is a contributing factor in the pathogenesis of Alzheimer's disease (AD). A unique 4D-Flow magnetic resonance imaging (MRI) technique, phase contrast vastly undersampled isotropic projection imaging (PC VIPR), enables examination of angiographic and quantitative metrics of blood flow in the arteries of the Circle of Willis within a single MRI acquisition. Thirty-eight participants with mild cognitive impairment (MCI) underwent a comprehensive neuroimaging protocol (including 4D-Flow imaging) and a standard neuropsychological battery. A subset of participants (n = 22) also underwent lumbar puncture and had cerebrospinal fluid (CSF) assayed for AD biomarkers. Cut-offs for biomarker positivity in CSF resulting from a receiver operating characteristic curve analysis of AD cases and controls from the larger Wisconsin Alzheimer's Disease Research Center cohort were used to classify MCI participants as biomarker positive or negative on amyloid-β (Aβ42), total-tau and total-tau/Aβ42 ratio. Internal carotid artery (ICA) and middle cerebral artery (MCA) mean flow were associated with executive functioning performance, with lower mean flow corresponding to worse performance. MCI participants who were biomarker positive for Aβ42 had lower ICA mean flow than did those who were Aβ42 negative. In sum, mean ICA and MCA arterial flow was associated with cognitive performance in participants with MCI and lower flow in the ICA was associated with amyloid positivity. This provides further evidence for vascular health as a contributing factor in the etiopathogenesis of AD, and could represent a point to intervene in the disease process.

Investigation on the Role of BDNF in the Benefits of Blueberry Extracts for the Improvement of Learning and Memory in Alzheimer's Disease Mouse Model. - Tan, Long; Yang, Hongpeng; Pang, Wei; Li, Haiqiang; Liu, Wei; Sun, Shoudan; Song, Nan; Zhang, Wanqi; Jiang, Yugang (J Alzheimers Dis, 2017)
BACKGROUND: Blueberry (BB) can provide a wide range of antioxidant benefits for AD. There is evidence that BB extracts could improve brain functions. However, the details are still unknown. OBJECTIVE: In the present study, we aimed to investigate the possible mechanism involved in the improvement of learning and memory capacity from BB extracts in AD. METHODS: APP/PS1 transgenic mice were fed BB extracts for 16 weeks. The capacity of learning and memory was assessed by Morris water maze (MWM) test, and long-term potentiation (LTP) was determined to evaluate hippocampal neuronal plasticity at the end of administration. Pathological changes in the brain were observed, and the expressions of brain-derived neurotrophic factor (BDNF) and extracellular signal-related kinase (ERK1/2) were determined to explore the mechanism of BB extract-induced benefits. RESULTS: AD mice exhibited more difficulties to learn and remember the exact position of the platform in the MWM test. The data showed that AD mice lacked effective learning in the platform search. In contrast, AD mice exhibited better performance both in the training phase and probe test of MWM after the BB treatment. Moreover, LTP was enhanced and the neuron loss was alleviated with BB treatment, while we did not find any obvious effect on the elimination of amyloid-β. In the AD mice, the expression of ERK1/2 was significantly increased (p < 0.05), while the level of BDNF was decreased (p < 0.05). CONCLUSIONS: BB treatment was beneficial for the improvement of learning and memory of AD, and these effects might be related to the regulation of BDNF.

Meta-Analysis of Parkinson's Disease and Alzheimer's Disease Revealed Commonly Impaired Pathways and Dysregulation of NRF2-Dependent Genes. - Wang, Qian; Li, Wen-Xing; Dai, Shao-Xing; Guo, Yi-Cheng; Han, Fei-Fei; Zheng, Jun-Juan; Li, Gong-Hua; Huang, Jing-Fei (J Alzheimers Dis, 2017)
Many lines of evidence suggest that Parkinson's disease (PD) and Alzheimer's disease (AD) have common characteristics, such as mitochondrial dysfunction and oxidative stress. As the underlying molecular mechanisms are unclear, we perform a meta-analysis with 9 microarray datasets of PD studies and 7 of AD studies to explore it. Functional enrichment analysis revealed that PD and AD both showed dysfunction in the synaptic vesicle cycle, GABAergic synapses, phagosomes, oxidative phosphorylation, and TCA cycle pathways, and AD had more enriched genes. Comparing the differentially expressed genes between AD and PD, we identified 54 common genes shared by more than six tissues. Among them, 31 downregulated genes contained the antioxidant response element (ARE) consensus sequence bound by NRF2. NRF2 is a transcription factor, which protects cells against oxidative stress through coordinated upregulation of ARE-driven genes. To our surprise, although NRF2 was upregulated, its target genes were all downregulated. Further exploration found that MAFF was upregulated in all tissues and significantly negatively correlated with the 31 NRF2-dependent genes in diseased conditions. Previous studies have demonstrated over-expressed small MAFs can form homodimers and act as transcriptional repressors. Therefore, MAFF might play an important role in dysfunction of NRF2 regulatory network in PD and AD.

Microglial and Neuronal TDP-43 Pathology in Anti-IgLON5-Related Tauopathy. - Cagnin, Annachiara; Mariotto, Sara; Fiorini, Michele; Gaule, Marina; Bonetto, Nicola; Tagliapietra, Matteo; Buratti, Emanuele; Zanusso, Gianluigi; Ferrari, Sergio; Monaco, Salvatore (J Alzheimers Dis, 2017)
A novel neuronal tauopathy, mainly confined to hypothalamus and brainstem tegmentum, has recently been reported in patients with autoantibodies to the neuronal cell-adhesion molecule IgLON5. We describe a patient with anti-IgLON5 syndrome, who presented with dysautonomia and sleep disorder, followed by subacute dementia. Postmortem brain examination disclosed neuronal tau pathology prevailing in the hippocampus, amygdala, and locus coeruleus, in addition to microglial/neuronal TDP-43 pathology, with overexpression of aberrantly phosphorylated forms and neurotoxic truncated fragments, in basal ganglia, nucleus basalis, thalamus, and midbrain. These findings suggest that neurodegeneration in anti-IgLON5 syndrome might also occur via a microglia-triggered non-cell autonomous pathway.

Modulating the Balance of Synaptic and Extrasynaptic NMDA Receptors Shows Positive Effects against Amyloid-β-Induced Neurotoxicity. - Huang, Yan; Shen, Wei; Su, Jie; Cheng, Bin; Li, Dong; Liu, Gang; Zhou, Wen-Xia; Zhang, Yong-Xiang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) patients suffer a disturbance in the balance between synaptic (GluN2A, mediating the protective pathway) and extrasynaptic NMDA receptors (NMDARs) (GluN2B, mediating the excitotoxic pathway), and, therefore, restoring the balance of GluN2A and GluN2B should be beneficial for AD. In this study, the GluN2B-selective antagonist, ifenprodil, and the non-selective NMDAR agonist, NMDA, had little effect on amyloid-β (Aβ)-induced long-term potentiation deficits. Enhancing the activity of GluN2A had a protective effect against Aβ, and specific activation of GluN2A and inhibition of GluN2B showed a better protective effect. In Aβ ICV-injected animals, the combination of ifenprodil and D-cycloserine (a co-activator of NMDRs similar to D-serine) led to greater improvement in behavior tests (nest building, novel object recognition, and Morris water maze) than ifenprodil (Morris water maze) or D-cycloserine (nest building) alone. Signal pathway analysis showed that Aβ disturbed the GluN2A/GluN2B-related pathway. The ratio of GluN2A to GluN2B decreased in Aβ-treated animals, and TORC dephosphorylation and ERK1/2 activation, which could be initiated by GluN2A, also decreased in the hippocampal tissues of Aβ-treated animals. As a result, the activation of CREB and the content of brain-derived BDNF decreased. The combination of ifenprodil and D-cycloserine reversed the signal pathway more significantly than ifenprodil or D-cycloserine alone, indicating that Aβ-induced toxicology was mediated both by functionally inhibiting GluN2A and enhancing GluN2B. These results indicate that enhancing synaptic NMDARs and inhibiting extrasynaptic NMDARs concurrently showed protective effects against Aβ-induced neurotoxicity, suggesting that modulation of the balance between GluN2A and GluN2B could be a potential strategy for AD drug development and therapy.
Keywords: Amyloid beta-Peptides; Animals; Antimetabolites; Cycloserine; Disease Models, Animal; Excitatory Amino Acid Antagonists; Excitatory Postsynaptic Potentials; Hippocampus; Locomotion; Male; Maze Learning; N-Methylaspartate; Nesting Behavior; Neurotoxicity Syndromes; Peptide Fragments; Piperidines; Rats; Rats, Wistar; Receptors, N-Methyl-D-Aspartate; Recognition (Psychology); Signal Transduction; Synapses

Modulation of Immune Responses to Herpes Simplex Virus Type 1 by IFNL3 and IRF7 Polymorphisms: A Study in Alzheimer's Disease. - Costa, Andrea Saul; Agostini, Simone; Guerini, Franca Rosa; Mancuso, Roberta; Zanzottera, Milena; Ripamonti, Enrico; Racca, Vittorio; Nemni, Raffaello; Clerici, Mario (J Alzheimers Dis, 2017)
Herpes simplex virus type 1 (HSV-1) has long been suspected to play a role in Alzheimer's disease (AD), the most common form of dementia. IFN-lambda (IFN-λ) is one of the key cytokine in innate antiviral defenses and, in particular, has an appreciable antiviral activity against HSV-1 infection. IFN-λ expression is regulated by the interaction between two different proteins: Mediator Complex 23 (MED23) and Interferon-Responsive Transcription Factor 7 (IRF7); single nucleotide polymorphisms (SNPs) in these genes as well as in IFNL3 were shown to be differently distributed in AD patients. In this study, allelic discrimination analysis for IFNL3 rs12979860, MED23 rs3756784, and IRF7 rs6598008, as well as IFN-λ serum concentration and anti-HSV-1 antibody (Ab) titers were performed in 79 AD patients, 57 mild cognitive impairment (MCI) individuals, and 81 healthy controls (HC) who were HSV-1-seropositive. Results showed that INF-λ serum concentration was increased in AD and MCI carrying the IFNL3 T allele compared to HC (AD versus HC: p = 0.014; MCI versus HC: p = 0.029), with the highest anti-HSV-1 Ab titers seen in AD patients carrying the IFNL3 CC genotype (p = 0.012 versus HC). Notably, anti-HSV-1 Ab titers were higher in AD and MCI individuals carrying the IRF7 AA genotype compared to HC (p = 0.018 for both). MED23 polymorphisms did not show any statistical association either with serum IFN-λ or with anti-HSV-1 Ab. Data herein suggest that the IFNL3 rs12979860 and IRF7 rs6598008 polymorphisms modulate immune responses against HSV-1 via their effect on the IFN-λ pathway. These results help to clarify the possible role of HSV-1 infection in AD pathogenesis.

Motor Phenotype in Neurodegenerative Disorders: Gait and Balance Platform Study Design Protocol for the Ontario Neurodegenerative Research Initiative (ONDRI). - Montero-Odasso, Manuel; Pieruccini-Faria, Frederico; Bartha, Robert; Black, Sandra E; Finger, Elizabeth; Freedman, Morris; Greenberg, Barry; Grimes, David A; Hegele, Robert A; Hudson, Christopher; Kleinstiver, Peter W; Lang, Anthony E; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The association of cognitive and motor impairments in Alzheimer's disease and other neurodegenerative diseases is thought to be related to damage in the common brain networks shared by cognitive and cortical motor control processes. These common brain networks play a pivotal role in selecting movements and postural synergies that meet an individual's needs. Pathology in this "highest level" of motor control produces abnormalities of gait and posture referred to as highest-level gait disorders. Impairments in cognition and mobility, including falls, are present in almost all neurodegenerative diseases, suggesting common mechanisms that still need to be unraveled. OBJECTIVE: To identify motor-cognitive profiles across neurodegenerative diseases in a large cohort of patients. METHODS: Cohort study that includes up to 500 participants, followed every year for three years, across five neurodegenerative disease groups: Alzheimer's disease/mild cognitive impairment, frontotemporal degeneration, vascular cognitive impairment, amyotrophic lateral sclerosis, and Parkinson's disease. Gait and balance will be assessed using accelerometers and electronic walkways, evaluated at different levels of cognitive and sensory complexity, using the dual-task paradigm. RESULTS: Comparison of cognitive and motor performances across neurodegenerative groups will allow the identification of motor-cognitive phenotypes through the standardized evaluation of gait and balance characteristics. CONCLUSIONS: As part of the Ontario Neurodegenerative Research Initiative (ONDRI), the gait and balance platform aims to identify motor-cognitive profiles across neurodegenerative diseases. Gait assessment, particularly while dual-tasking, will help dissect the cognitive and motor contribution in mobility and cognitive decline, progression to dementia syndromes, and future adverse outcomes including falls and mortality.

Multifunctional Compound AD-35 Improves Cognitive Impairment and Attenuates the Production of TNF-α and IL-1β in an Aβ25-35-induced Rat Model of Alzheimer's Disease. - Li, Lin; Xu, Shaofeng; Liu, Lifei; Feng, Rentian; Gong, Yongxiang; Zhao, Xuyang; Li, Jiang; Cai, Jie; Feng, Nan; Wang, Ling; Wang, Xiaoliang; Peng, Ying (J Alzheimers Dis, 2017)
The dyshomeostasis of transition metal ions, accumulation of amyloid-β (Aβ) senile plaques and neuroinflammatory response found in the brain of patients with Alzheimer's disease (AD) have been suggested to be involved in AD pathogenesis. Novel compounds capable of targeting metal-Aβ species and neuroinflammation would be valuable. AD-35 is such a patented small-molecule compound derived from innovative modification of the chemical structure of donepezil. This compound could moderately inhibit acetylcholinesterase and metal-induced Aβ aggregation in vitro and showed disassembly of Aβ aggregates. The effects of AD-35 on cognitive impairments and neuroinflammatory changes caused by intracerebroventricular injection of Aβ25-35 were studied in rats. Compared to sham group, Aβ25-35 injection significantly led to learning and memory deficits, astrocyte activation, and pro-inflammatory cytokines releases (TNF-α and IL-1β). Further studies indicated that the phosphorylation of extracellular signal-regulated kinase was involved in astrocyte activation and pro-inflammatory cytokines production. Oral administration of AD-35 could markedly attenuate Aβ25-35 injection-induced astrocyte activation, pro-inflammatory cytokines TNF-α and IL-1β release, and memory deficits. On the contrary, donepezil only showed inhibition of IL-1β production, but failed to block astrocyte activation and TNF-α production. These results showed that AD-35 would be a novel multi-mechanism drug for the prevention and/or treatment of AD.

Neuronal Expression of Truncated Tau Efficiently Promotes Neurodegeneration in Animal Models: Pitfalls of Toxic Oligomer Analysis. - Skrabana, Rostislav; Kovacech, Branislav; Filipcik, Peter; Zilka, Norbert; Jadhav, Santosh; Smolek, Tomas; Kontsekova, Eva; Novak, Michal (J Alzheimers Dis, 2017)
Animal models of neurodegeneration induced by neuronal expression of truncated tau protein emerge as an important tool for understanding the pathogenesis of human tauopathies and for therapy development. Here we highlight common features of truncated tau models and make a critical assessment of possible pitfalls in their analysis. Particularly, the amount of soluble tau oligomers, which are suspected to be neurotoxic agents participating on the spreading of pathology inside the brain, may be overestimated due to a post-lysis oxidative tau oligomerization. Using a mouse brain lysate spiked with recombinant truncated and full length tau forms, we show that tau oligomers might inadvertently be produced during the isolation procedure. This finding is further corroborated by the analysis of brain lysates originated from a mouse model expressing truncated tau variant. Our results underline the necessity of thiol-protecting conditions during the analysis of tau oligomers involved in the etiopathogenesis of various tauopathies including Alzheimer's disease.

Neuroprotective Effect of TREM-2 in Aging and Alzheimer's Disease Model. - Raha, Animesh Alexander; Henderson, James W; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Friedland, Robert P; Zaman, Shahid H; Raha-Chowdhury, Ruma (J Alzheimers Dis, 2017)
Neuroinflammation and activation of innate immunity are early events in neurodegenerative diseases including Alzheimer's disease (AD). Recently, a rare mutation in the gene Triggering receptor expressed on myeloid cells 2 (TREM2) has been associated with a substantial increase in the risk of developing late onset AD. To uncover the molecular mechanisms underlying this association, we investigated the RNA and protein expression of TREM2 in APP/PS1 transgenic mice. Our findings suggest that TREM2 not only plays a critical role in inflammation, but is also involved in neuronal cell survival and in neurogenesis. We have shown that TREM2 is a soluble protein transported by macrophages through ventricle walls and choroid plexus, and then enters the brain parenchyma via radial glial cells. TREM2 protein is essential for neuroplasticity and myelination. During the late stages of life, a lack of TREM2 protein may accelerate aging processes and neuronal cell loss and reduce microglial activity, ultimately leading to neuroinflammation. As inflammation plays a major role in neurodegenerative diseases, a lack of TREM2 could be a missing link between immunomodulation and neuroprotection.

Neuropsychological Symptoms in Sporadic Creutzfeldt-Jakob Disease Patients in Germany. - Krasnianski, Anna; Bohling, Geeske T; Heinemann, Uta; Varges, Daniela; Meissner, Bettina; Schulz-Schaeffer, Walter J; Reif, Andreas; Zerr, Inga (J Alzheimers Dis, 2017)
BACKGROUND: The polymorphism at codon 129 of the prion protein gene (PRNP) and the PrPSc types 1 and 2 belong to a molecular classification of sporadic Creutzfeldt-Jakob disease (sCJD) that correlates well with the clinical and neuropathological phenotype of sCJD. OBJECTIVE: The aim of the study was to perform the first detailed evaluation of neuropsychological deficits in a large group of definite sCJD patients with known molecular subtype. METHODS: We analyzed neuropsychological symptoms in a cohort of 248 sCJD patients with known M129 V polymorphism of PRNP and prion protein type. RESULTS: Neuropsychological symptoms were very frequent in our patients (96%) and occurred as early as in the first third of the disease course. Besides amnesia and impaired attention (89% each), frontal lobe syndrome (75%), aphasia (63%), and apraxia (57%) were the most common neuropsychological deficits. There was no statistically significant difference with regard to frequency of neuropsychological symptoms between the subtypes. In MV2 and VV2 patients, the onset of neuropsychological symptoms was significantly later than in all other subtypes. CONCLUSION: We provide the first detailed analysis of neuropsychological symptoms in a large group of sCJD patients with known M129 V genotype and prion protein type. We suggest that the rate of progression of neuropsychological symptoms is subtype-specific. These data may improve the diagnosis in atypical sCJD subtypes.

Nitrosylation of Vesicular Transporters in Brain of Amyloid Precursor Protein/Presenilin 1 Double Transgenic Mice. - Wang, Ying; Zhou, Zhu; Tan, Hua; Zhu, Shenghua; Wang, Yiran; Sun, Yingxia; Li, Xin-Min; Wang, Jun-Feng (J Alzheimers Dis, 2017)
Nitric oxide can attack thiol groups of cysteine residues in proteins and induce protein cysteine S-nitrosylation. Cholinergic and glutamatergic systems are dysregulated in Alzheimer's disease. Vesicular acetylcholine transporter (VAChT) and vesicular glutamate transporter 1 (VGLUT1) are important in packaging acetylcholine and glutamate into vesicles, which is an important step for neurotransmission. Previously we found that VAChT and VGLUT1 can be nitrosylated and that S-nitrosylation of these transporters inhibits vesicular uptake of acetylcholine and glutamate. To understand the role of VAChT and VGLUT1 nitrosylation in the pathophysiological development of Alzheimer's disease, we analyzed nitrosylation of VAChT and VGLUT1 in brain of amyloid precursor protein (APP) and presenilin 1 (PS1) double transgenic mice, an animal model for Alzheimer's disease. Using a Morris water maze test, we found that 9- and 12-month-old APP/PS1 mice showed memory deficit, compared to wild type mice. We further found that total protein nitrosylation was increased in frontal cortex and hippocampus of 9- and 12-month-old APP/PS1 mice. Although nitrosylation of VAChT and VGLUT1 was not changed in hippocampus of 9- and 12-month-old APP/PS1 mice, nitrosylation of VAChT and VGLUT1 was significantly increased in frontal cortex of APP/PS1 mice at these ages. We also found that nitrosylation of VAChT and VGLUT1 was increased in hippocampus (but not frontal cortex) of 3-month-old APP/PS1 mice. These findings suggest that nitrosylation of VAChT and VGLUT1 may be associated with dysfunctional acetylcholinergic and glutamatergic neurotransmission in Alzheimer's disease.

Non-Phosphorylated Tau as a Potential Biomarker of Alzheimer's Disease: Analytical and Diagnostic Characterization. - Lewczuk, Piotr; Lelental, Natalia; Lachmann, Ingolf; Holzer, Max; Flach, Katharina; Brandner, Sebastian; Engelborghs, Sebastiaan; Teunissen, Charlotte E; Zetterberg, Henrik; Molinuevo, José Luis; Mroczko, Barbara; Blennow, Kaj; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Virtually nothing is known about a potential diagnostic role of non-phospho-epitopes of Tau (Non-P-Tau) in cerebrospinal fluid (CSF). OBJECTIVE: To establish and analytically and clinically characterize the first assay capable to measure concentrations of Non-P-Tau in human CSF. METHODS: An antibody (1G2) was developed that selectively binds to the Tau molecule non-phosphorylated at the positions T175 and T181, and was used in establishing a sandwich ELISA capable to measure Non-P-Tau in human CSF, following analytical and clinical validation of the method. RESULTS: The 1G2 antibody shows decreasing reactivity to tau peptides containing phosphorylation mainly at positions T175 and T181. Detection limit of the assay is 25 pg/ml; the coefficients of variation (CVs) of the optical densities of the repeated standard curves were between 3.6-15.9%. Median intra-assay imprecision of double measurements was 4.8%; inter-assay imprecision was in the range of 11.2% - 15.3%. Non-P-Tau concentrations are stable in the CSF samples sent to distinct laboratories under ambient temperature; inter-laboratory variation was approximately 30%. The Non-P-Tau CSF concentrations were highly significantly increased in patients with Alzheimer's disease in stage of mild cognitive impairment or dementia (AD/MCI, n = 58, 109.2±32.0 pg/mL) compared to the non-demented Controls (n = 42, 62.1±9.3 pg/mL, p < 0.001). At the cut-off of 78.3 pg/mL, the sensitivity and the specificity were 94.8% and 97.6%, respectively. CONCLUSION: For the first time, an assay is reported to reliably measure concentrations of non-phosphorylated Tau in human CSF.

Novel Blood-Based Biomarkers of Cognition, Stress, and Physical or Cognitive Training in Older Adults at Risk of Dementia: Preliminary Evidence for a Role of BDNF, Irisin, and the Kynurenine Pathway. - Küster, Olivia C; Laptinskaya, Daria; Fissler, Patrick; Schnack, Cathrin; Zügel, Martina; Nold, Verena; Thurm, Franka; Pleiner, Sina; Karabatsiakis, Alexander; von Einem, Björn; Weydt, Patrick; Liesener, André; et al. (J Alzheimers Dis, 2017)
Psychosocial stress and physical, cognitive, and social activity predict the risk of cognitive decline and dementia. The aim of this study was to elucidate brain-derived neurotrophic factor (BDNF), irisin, and the kynurenine pathway (KP) as potential underlying biological correlates. We evaluated associations of irisin and the KP with BDNF in serum and with cognition, stress, and activities. Furthermore, changes in serum concentrations of BDNF, irisin, and KP metabolites were investigated after physical or cognitive training. Forty-seven older adults at risk of dementia were assigned to 10 weeks of physical training, cognitive training, or a wait-list control condition. Previous physical, cognitive, and social activities and stressful life events were recorded; global cognition, episodic memory, and executive functions were assessed. Serum levels of L-kynurenine, kynurenic acid, 3-hydroxykynurenine (3-HK), and quinolinic acid (QUIN) were determined by validated assays based on liquid chromatography coupled to tandem mass spectrometry. BDNF and irisin serum levels were determined with enzyme-linked immunosorbent assays. BDNF and irisin correlated positively with global cognition and episodic memory, while the neurotoxic metabolite QUIN correlated negatively with executive functions. Stressful life events were associated with reduced BDNF and increased 3-HK. 3-HK decreased after cognitive training, while BDNF tended to increase after physical training. This suggests that psychosocial stress as well as cognitive and physical training may impact BDNF serum levels and the KP. Irisin and QUIN may constitute novel serum biomarkers of cognitive impairment, in addition to BDNF. Larger scale trials are needed to replicate and extend these novel findings.

Pathway-Specific Polygenic Risk Scores as Predictors of Amyloid-β Deposition and Cognitive Function in a Sample at Increased Risk for Alzheimer's Disease. - Darst, Burcu F; Koscik, Rebecca L; Racine, Annie M; Oh, Jennifer M; Krause, Rachel A; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Christian, Bradley T; Bendlin, Barbara B; Okonkwo, Ozioma C; Hogan, Kirk J; et al. (J Alzheimers Dis, 2017)
Polygenic risk scores (PRSs) have been used to combine the effects of variants with small effects identified by genome-wide association studies. We explore the potential for using pathway-specific PRSs as predictors of early changes in Alzheimer's disease (AD)-related biomarkers and cognitive function. Participants were from the Wisconsin Registry for Alzheimer's Prevention, a longitudinal study of adults who were cognitively asymptomatic at enrollment and enriched for a parental history of AD. Using genes associated with AD in the International Genomics of Alzheimer's Project's meta-analysis, we identified clusters of genes that grouped into pathways involved in amyloid-β (Aβ) deposition and neurodegeneration: Aβ clearance, cholesterol metabolism, and immune response. Weighted pathway-specific and overall PRSs were developed and compared to APOE alone. Mixed models were used to assess whether each PRS was associated with cognition in 1,200 individuals, cerebral Aβ deposition measured using amyloid ligand (Pittsburgh compound B) positron emission imaging in 168 individuals, and cerebrospinal fluid Aβ deposition, neurodegeneration, and tau pathology in 111 individuals, with replication performed in an independent sample. We found that PRSs including APOE appeared to be driven by the inclusion of APOE, suggesting that the pathway-specific PRSs used here were not more predictive than an overall PRS or APOE alone. However, pathway-specific PRSs could prove to be useful as more knowledge is gained on the genetic variants involved in specific biological pathways of AD.

Pen-2 and Presenilin are Sufficient to Catalyze Notch Processing. - Hu, Chen; Xu, Junjie; Zeng, Linlin; Li, Ting; Cui, Mei-Zhen; Xu, Xuemin (J Alzheimers Dis, 2017)
Presenilin-1 (PS1) or presenilin-2 (PS2), nicastrin (NCT), anterior pharynx-defective 1 (Aph-1), and presenilin enhancer-2 (Pen-2) have been considered the minimal essential subunits required to form an active γ-secretase complex. Besides PS, which has been widely believed to function as the catalytic subunit of the complex, the functional roles of the other subunits in the γ-secretase complex remain debatable. In the current study, we set out to determine the role of Pen-2 in γ-secretase activity. To this end, using knockout cells in combination with siRNA and immunoprecipitation approaches, our results revealed that Pen-2 together with presenilin are sufficient to form a functionally active enzyme to process Notch. Specifically, our data demonstrated that Pen-2 plays a crucial role in substrate binding, a mechanism by which Pen-2 contributes directly to the catalytic mechanism of γ-secretase activity. Our data also suggested that there may be different requirements for components to process AβPP and Notch. This information would be important for therapeutic strategy aimed at inhibition or modulation of γ-secretase activity.

PET Tau and Amyloid-β Burden in Mild Alzheimer's Disease: Divergent Relationship with Age, Cognition, and Cerebrospinal Fluid Biomarkers. - Koychev, Ivan; Gunn, Roger N; Firouzian, Azadeh; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; Rochester, Lynn; Ffytche, Dominic; Howard, Robert; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Combining PET amyloid-β (Aβ) and tau imaging may be critical for tracking disease progression in Alzheimer's disease (AD). OBJECTIVE: We sought to characterize the relationship between Aβ and tau ligands as well as with other measures of pathology. METHODS: We conducted a multi-center observational study in early AD (MMSE >20) participants aged 50 to 85 y. The schedule included cognitive assessments (ADAS-Cog) and CSF measurement of Aβ and tau at baseline and 6 months; PET-CT imaging with Aβ ([18F]AV45) and tau ([18F]AV1451) ligands at baseline. RESULTS: 22 participants took part in the study with 20 completing its 6-month duration and 12 having both tau and amyloid PET. The PET biomarker analysis revealed a strong negative correlation between age and tau in multiple regions. Entorhinal cortex tau and age interacted significantly in terms of cognitive change over 6 months which may have been to older participants deteriorating faster despite lower levels of cortical tau. Cortical Aβ associated with entorhinal cortex tau while CSF tau/Aβ ratio correlated strongly with cortical tau but not Aβ. CONCLUSION: The negative relationship between age and cortical tau whereby younger patients with mild AD had relatively greater tau burden is potentially important. It suggests that younger-age onset AD may be primarily driven by tau pathology while AD developing later may depend on a multitude of pathological mechanisms. These data also suggest that PET-tau performs better than PET-amyloid in predicting the best validated AD diagnostic marker- the CSF total tau/Aβ ratio.

Phenotype-Dependent Interactions between N-acetyl-L-Aspartate and Acetyl-CoA in Septal SN56 Cholinergic Cells Exposed to an Excess of Zinc. - Zyśk, Marlena; Bielarczyk, Hanna; Gul-Hinc, Sylwia; Dyś, Aleksandra; Gapys, Beata; Ronowska, Anna; Sakowicz-Burkiewicz, Monika; Szutowicz, Andrzej (J Alzheimers Dis, 2017)
Pyruvate dehydrogenase reaction utilizing glucose-derived pyruvate is an almost exclusive source of acetyl-CoA in different cell mitochondrial compartments of the brain. In neuronal mitochondria, the largest fraction of acetyl-CoA is utilized for energy production and the much smaller one for N-acetyl-L-aspartate (NAA) synthesis. Cholinergic neurons, unlike others, require additional amounts of acetyl-CoA for acetylcholine synthesis. Therefore, several neurotoxic signals, which inhibit pyruvate dehydrogenase, generate deeper shortages of acetyl-CoA and greater mortality of cholinergic neurons than noncholinergic ones. NAA is considered to be a marker of neuronal energy status in neuropathic brains. However, there is no data on putative differential fractional distribution of the acetyl-CoA pool between energy producing and NAA or acetylcholine synthesizing pathways in noncholinergic and cholinergic neurons, respectively. Therefore, the aim of this study was to investigate whether zinc-excess, a common excitotoxic signal, may evoke differential effects on the NAA metabolism in neuronal cells with low and high expression of the cholinergic phenotype. Differentiated SN56 neuronal cells, displaying a high activity of choline acetyltransferase and rates of acetylcholine synthesis, contained lower levels of acetyl-CoA and NAA, being more susceptible to ZnCl2 exposition that the nondifferentiated SN56 or differentiated dopaminergic SHSY5Y neuronal and astroglial C6 cells. Differentiated SN56 accumulated greater amounts of Zn2 + from extracellular space than the other ones, and displayed a stronger suppression of pyruvate dehydrogenase complex activity and acetyl-CoA, NAA, ATP, acetylcholine levels, and loss of viability. These data indicate that the acetyl-CoA synthesizing system in neurons constitutes functional unity with energy generating and NAA or acetylcholine pathways of its utilization, which are uniformly affected by neurotoxic conditions.

Plasma Tau Association with Brain Atrophy in Mild Cognitive Impairment and Alzheimer's Disease. - Deters, Kacie D; Risacher, Shannon L; Kim, Sungeun; Nho, Kwangsik; West, John D; Blennow, Kaj; Zetterberg, Henrik; Shaw, Leslie M; Trojanowski, John Q; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2017)
BACKGROUND: Peripheral (plasma) and central (cerebrospinal fluid, CSF) measures of tau are higher in Alzheimer's disease (AD) relative to prodromal stages and controls. While elevated CSF tau concentrations have been shown to be associated with lower grey matter density (GMD) in AD-specific regions, this correlation has yet to be examined for plasma in a large study. OBJECTIVE: Determine the neuroanatomical correlates of plasma tau using voxel-based analysis. METHODS: Cross-sectional data for 508 ADNI participants were collected for clinical, plasma total-tau (t-tau), CSF amyloid (Aβ42) and tau, and MRI variables. The relationship between plasma tau and GMD and between CSF t-tau and GMD were assessed on a voxel-by-voxel basis using regression models. Age, sex, APOEɛ4 status, diagnosis, and total intracranial volume were used as covariates where appropriate. Participants were defined as amyloid positive (Aβ+) if CSF Aβ42 was <192 pg/mL. RESULTS: Plasma tau was negatively correlated with GMD in the medial temporal lobe (MTL), precuneus, thalamus, and striatum. The associations with thalamus and striatum were independent of diagnosis. A negative correlation also existed between plasma tau and GMD in Aβ+ participants in the MTL, precuneus, and frontal lobe. When compared to CSF t-tau, plasma tau showed a notably different associated brain atrophy pattern, with only small overlapping regions in the fusiform gyrus. CONCLUSION: Plasma tau may serve as a non-specific marker for neurodegeneration but is still relevant to AD considering low GMD was associated with plasma tau in Aβ+ participants and not Aβ-participants.

Preclinical Amyloid-β and Axonal Degeneration Pathology in Delirium. - Idland, Ane-Victoria; Wyller, Torgeir Bruun; Støen, Randi; Eri, Lars Magne; Frihagen, Frede; Ræder, Johan; Chaudhry, Farrukh Abbas; Hansson, Oskar; Zetterberg, Henrik; Blennow, Kaj; Bogdanovic, Nenad; Brækhus, Anne; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The clinical relevance of brain β-amyloidosis in older adults without dementia is not established. As delirium and dementia are strongly related, studies on patients with delirium may give pathophysiological clues. OBJECTIVE: To determine whether the Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers amyloid-β 1-42 (Aβ42), total tau (T-tau), and phosphorylated tau (P-tau) are associated with delirium in hip fracture patients with and without dementia. METHODS: CSF was collected in conjunction to spinal anesthesia in 129 patients. Delirium was assessed using the Confusion Assessment Method once daily in all patients, both pre- and postoperatively. The diagnosis of dementia at admission was based upon clinical consensus. CSF levels of Aβ42, T-tau, and P-tau were analyzed. RESULTS: In patients without dementia, we found lower CSF Aβ42 levels (median, 310 ng/L versus 489 ng/L, p = 0.006), higher T-tau levels (median, 505 ng/L versus 351 ng/L, p = 0.02), but no change in P-tau in patients who developed delirium (n = 16) compared to those who remained lucid (n = 49). Delirious patients also had lower ratios of Aβ42 to T-tau (p < 0.001) and P-tau (p = 0.001) relative to those without delirium. CSF Aβ42 and T-tau remained significantly associated with delirium status in adjusted analyses. In patients with dementia, CSF biomarker levels did not differ between those with (n = 54) and without delirium (n = 10). CONCLUSION: The reduction in CSF Aβ42, indicating β-amyloidosis, and increase in T-tau, indicating neurodegeneration, in hip fracture patients without dementia developing delirium indicates that preclinical AD brain pathology is clinically relevant and possibly plays a role in delirium pathophysiology.

A Preliminary Study on the Feasibility of Using a Virtual Reality Cognitive Training Application for Remote Detection of Mild Cognitive Impairment. - Zygouris, Stelios; Ntovas, Konstantinos; Giakoumis, Dimitrios; Votis, Konstantinos; Doumpoulakis, Stefanos; Segkouli, Sofia; Karagiannidis, Charalampos; Tzovaras, Dimitrios; Tsolaki, Magda (J Alzheimers Dis, 2017)
BACKGROUND: It has been demonstrated that virtual reality (VR) applications can be used for the detection of mild cognitive impairment (MCI). OBJECTIVE: The aim of this study is to provide a preliminary investigation on whether a VR cognitive training application can be used to detect MCI in persons using the application at home without the help of an examiner. METHODS: Two groups, one of healthy older adults (n = 6) and one of MCI patients (n = 6) were recruited from Thessaloniki day centers for cognitive disorders and provided with a tablet PC with custom software enabling the self-administration of the Virtual Super Market (VSM) cognitive training exercise. The average performance (from 20 administrations of the exercise) of the two groups was compared and was also correlated with performance in established neuropsychological tests. RESULTS: Average performance in terms of duration to complete the given exercise differed significantly between healthy(μ  = 247.41 s/ sd = 89.006) and MCI (μ= 454.52 s/ sd = 177.604) groups, yielding a correct classification rate of 91.8% with a sensitivity and specificity of 94% and 89% respectively for MCI detection. Average performance also correlated significantly with performance in Functional Cognitive Assessment Scale (FUCAS), Test of Everyday Attention (TEA), and Rey Osterrieth Complex Figure test (ROCFT). DISCUSSION: The VR application exhibited very high accuracy in detecting MCI while all participants were able to operate the tablet and application on their own. Diagnostic accuracy was improved compared to a previous study using data from only one administration of the exercise. The results of the present study suggest that remote MCI detection through VR applications can be feasible.

Prevalence, Risk Factors, and Complaints Screening Tool Exploration of Subjective Cognitive Decline in a Large Cohort of the Chinese Population. - Hao, Lixiao; Wang, Xiaoni; Zhang, Ling; Xing, Yue; Guo, Qihao; Hu, Xiaochen; Mu, Bin; Chen, Yili; Chen, Guanqun; Cao, Jing; Zhi, Xiaodong; Liu, Jiaojiao; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Substantial studies have reported the prevalence and the affecting factors of subjective cognitive decline (SCD). The complaints screening scale has also been used for probing. However, little is known in China. OBJECTIVE: To investigate the prevalence and risk factors of SCD, and explore an SCD complaints screening scale in China. METHODS: Stratified cluster random sampling was conducted. 2,689 residents aged 60-80 years completed questionnaire 1. 814 residents were included for clinical and neuropsychological evaluations. Two standards were used to make the diagnosis of mild cognitive impairment (MCI) and SCD, and a preliminary screening rate comparison was carried out. Finally, we assessed the risk factors of SCD and the correlation between the SCD-questionnaire 9 (SCD-Q9) and the Auditory Verbal Learning Test-Long Delay Free Recall (AVLT-LR). RESULTS: 1) Standard 1 (ADNI2): the prevalence of SCD was 18.8% (95% CI = 14.7-22.9%) and zero conformed to six criteria (SCD plus). 2) Standard 2 (Jak/Bondi): the prevalence of SCD was 14.4% (95% CI = 10.7-18.1%). 3) Standard 1 had a relatively higher "false" positive rate, whereas Standard 2 had higher "false" negative rate. 4) Age, low education, fewer close friends, and daily drinking were independent risk factors for SCD progressing to MCI. 5) Total points of SCD-Q9 were negatively correlated to the value of AVLT-LR. CONCLUSIONS: The prevalence of SCD is high in the ShunYi District in Beijing, China. Age, low education, less social support, and daily drinking are independent risk factors. The brief SCD-Q9 can be used as a reference.

Prion Protein Interactome: Identifying Novel Targets in Slowly and Rapidly Progressive Forms of Alzheimer's Disease. - Zafar, Saima; Shafiq, Mohsin; Younas, Neelam; Schmitz, Matthias; Ferrer, Isidre; Zerr, Inga (J Alzheimers Dis, 2017)
Rapidly progressive Alzheimer's disease (rpAD) is a variant of AD distinguished by a rapid decline in cognition and short disease duration from onset to death. While attempts to identify rpAD based on biomarker profile classifications have been initiated, the mechanisms which contribute to the rapid decline and prion mimicking heterogeneity in clinical signs are still largely unknown. In this study, we characterized prion protein (PrP) expression, localization, and interactome in rpAD, slow progressive AD, and in non-dementia controls. PrP along with its interacting proteins were affinity purified with magnetic Dynabeads Protein-G, and were identified using Q-TOF-ESI/MS analysis. Our data demonstrated a significant 1.2-fold decrease in di-glycosylated PrP isoforms specifically in rpAD patients. Fifteen proteins appeared to interact with PrP and only two proteins3/4histone H2B-type1-B and zinc alpha-2 protein3/4were specifically bound with PrP isoform isolated from rpAD cases. Our data suggest distinct PrP involvement in association with the altered PrP interacting protein in rpAD, though the pathophysiological significance of these interactions remains to be established.

proBDNF Accelerates Brain Amyloid-β Deposition and Learning and Memory Impairment in APPswePS1dE9 Transgenic Mice. - Chen, Jia; Zhang, Tao; Jiao, Shusheng; Zhou, Xinfu; Zhong, Jinhua; Wang, Yanjiang; Liu, Juan; Deng, Juan; Wang, Shuiping; Xu, Zhiqiang (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is pathologically known for the amyloid-β (Aβ) deposition, neurofibrillary tangles, and neuronal loss in the brain. The precursor of brain-derived neurotrophic factor (proBDNF) before proteolysis has opposing functions to its mature form in neuronal survival and neurite growth. However, the role of proBDNF in the pathogenesis of AD remains unclear. OBJECTIVE: To investigate the effects of proBDNF on neurons in vitro, and on learning and memory impairment and brain Aβ production in a transgenic AD mouse model (APPswePS1dE9). METHODS: We here examined the effects of proBDNF on the viability (MTT assay) and neurite growth (morphologic measurement) of the primary neurons in vitro. After the intracerebroventricular injection of adeno-associated virus-proBDNF (AAV-proBDNF), we then investigated the learning and memory impairment (Morris water maze) and Aβ deposition in the brains of the AD mice. RESULTS: The results showed that proBDNF could inhibit neuronal viability and neurite growth in vitro, enhance Aβ levels, and accelerate its deposition in the brain, which was consistent with the learning and memory impairment of AD mice, likely dependent on the membrane receptor of p75NTR. CONCLUSIONS: Our findings suggest that proBDNF may exert a crucially negative effect during AD pathogenesis andprogression.

A Prospective Study on the Association between Uric Acid and Cognitive Function among Middle-Aged and Older Chinese. - Wang, Tong; Wu, Yili; Sun, Yongye; Zhai, Long; Zhang, Dongfeng (J Alzheimers Dis, 2017)
BACKGROUND: Uric acid (UA) is a powerful antioxidant that may have neuroprotective properties, yet it is also a risk factor of vascular disease that predisposes individuals to cognitive impairment. Results from longitudinal studies on UA and cognitive decline remain controversial. OBJECTIVE: We examined the associations of baseline plasma UA level with follow-up cognitive function as well as cognitive decline over time among a large sample of middle-aged and older Chinese. METHODS: Data from China Health and Retirement Longitudinal Study (CHARLS) were used. Cognitive function, including episodic memory, mental intactness, and global cognition, were tested twice with 2-year interval. Plasma UA was measured at baseline. Basic demographics, life habits, and health status were considered as potential confounders. Multiple linear regression models and mixed-effects regression models were fitted. RESULTS: A total of 12,798 individuals aged above 45 years were eligible with the follow-up time ranging from 1.33 to 2.42 years. Both global cognitive function and mental intactness declined, while episodic memory remained stable over time. In multiple linear regression models, compared with the lowest baseline UA level, 3rd baseline UA quartile was associated with better follow-up global cognitive function (b = 0.425, p = 0.041) and episodic memory (b = 0.413, p = 0.004), and highest baseline UA quartile was associated with better follow-up mental intactness (b = 0.253, p = 0.041) in males; highest baseline UA level was associated with better follow-up cognition for each measure (b = 0.281∼0.768, p≤0.046) in females. Mixed-effects regression models suggested no significant baseline UA-by-time interactions on any cognitive measure. CONCLUSION: Higher baseline UA level was associated with better cognition in later life but not with rates of cognitive decline among middle-aged and older Chinese.

Proteomics Analysis of Blood Serums from Alzheimer's Disease Patients Using iTRAQ Labeling Technology. - Shen, Liming; Liao, Liping; Chen, Cheng; Guo, Yi; Song, Dalin; Wang, Yong; Chen, Youjiao; Zhang, Kaoyuan; Ying, Ming; Li, Shuiming; Liu, Qiong; Ni, Jiazuan (J Alzheimers Dis, 2017)
Alzheimer' disease (AD) is the most common form of dementia affecting up to 6% of the population over the age of 65. In order to discover differentially expressed proteins that might serve as potential biomarkers, the serums from AD patients and healthy controls were compared and analyzed using the proteomics approach of isobaric tagging for relative and absolute quantitation (iTRAQ). For the first time, AD biomarkers in serums are investigated in the Han Chinese population using iTRAQ labeled proteomics strategy. Twenty-two differentially expressed proteins were identified and out of which nine proteins were further validated with more sample test. Another three proteins that have been reported in the literature to be potentially associated with AD were also investigated for alteration in expression level. Functions of those proteins were mainly related to the following processes: amyloid-β (Aβ) metabolism, cholesterol transport, complement and coagulation cascades, immune response, inflammation, hemostasis, hyaluronan metabolism, and oxidative stress. These results support current views on the molecular mechanism of AD. For the first time, differential expression of zinc-alpha-2-glycoprotein (AZGP1), fibulin-1 (FBLN1), platelet basic protein (PPBP), thrombospondin-1 (THBS1), S100 calcium-binding protein A8 (S100A8), and S100 calcium-binding protein A9 (S100A9) were detected in the serums of AD patients compared with healthy controls. These proteins might play a role in AD pathophysiology and serve as potential biomarkers for AD diagnosis. Specifically, our results strengthened the crucial role of Aβ metabolism and blood coagulation in AD pathogenesis and proteins related to these two processes may be used as peripheral blood biomarkers for AD.

PSD-93 Attenuates Amyloid-β-Mediated Cognitive Dysfunction by Promoting the Catabolism of Amyloid-β. - Yu, Linjie; Liu, Yi; Yang, Hui; Zhu, Xiaolei; Cao, Xiang; Gao, Jun; Zhao, Hui; Xu, Yun (J Alzheimers Dis, 2017)
Amyloid-β (Aβ) is a key neuropathological hallmark of Alzheimer's disease (AD). Postsynaptic density protein 93 (PSD-93) is a key scaffolding protein enriched at postsynaptic sites. The aim of the present study was to examine whether PSD-93 overexpression could alleviate Aβ-induced cognitive dysfunction in APPswe/PS1dE9 (APP/PS1) mice by reducing Aβ levels in the brain. The level of PSD-93 was significantly decreased in the hippocampus of 6-month-old APP/PS1 mice compared with that in wild-type mice. Following lentivirus-mediated PSD-93 overexpression, cognitive function, synaptic function, and amyloid burden were investigated. The open field test, Morris water maze test, and fear condition test revealed that PSD-93 overexpression ameliorated spatial memory deficits in APP/PS1 mice. The facilitation of long-term potentiation induction was observed in APP/PS1 mice after PSD-93 overexpression. The expression of somatostatin receptor 4 (SSTR4) and neprilysin was increased, while the amyloid plaque load and Aβ levels were decreased in the brains of APP/PS1 mice. Moreover, PSD-93 interacted with SSTR4 and affected the level of SSTR4 on cell membrane, which was associated with the ubiquitination. Together, these findings suggest that PSD-93 attenuates spatial memory deficits and decreases amyloid levels in APP/PS1 mice, which might be associated with Aβ catabolism, and overexpression of PSD-93 might be a potential therapy for AD.

Quantitative Comparison of Dense-Core Amyloid Plaque Accumulation in Amyloid-β Protein Precursor Transgenic Mice. - Liu, Peng; Reichl, John H; Rao, Eshaan R; McNellis, Brittany M; Huang, Eric S; Hemmy, Laura S; Forster, Colleen L; Kuskowski, Michael A; Borchelt, David R; Vassar, Robert; Ashe, Karen H; Zahs, Kathleen R (J Alzheimers Dis, 2017)
There exist several dozen lines of transgenic mice that express human amyloid-β protein precursor (AβPP) with Alzheimer's disease (AD)-linked mutations. AβPP transgenic mouse lines differ in the types and amounts of Aβ that they generate and in their spatiotemporal patterns of expression of Aβ assemblies, providing a toolkit to study Aβ amyloidosis and the influence of Aβ aggregation on brain function. More complete quantitative descriptions of the types of Aβ assemblies present in transgenic mice and in humans during disease progression should add to our understanding of how Aβ toxicity in mice relates to the pathogenesis of AD. Here, we provide a direct quantitative comparison of amyloid plaque burdens and plaque sizes in four lines of AβPP transgenic mice. We measured the fraction of cortex and hippocampus occupied by dense-core plaques, visualized by staining with Thioflavin S, in mice from young adulthood through advanced age. We found that the plaque burdens among the transgenic lines varied by an order of magnitude: at 15 months of age, the oldest age studied, the median cortical plaque burden in 5XFAD mice was already ∼4.5 times that of 21-month-old Tg2576 mice and ∼15 times that of 21-24-month-old rTg9191 mice. Plaque-size distributions changed across the lifespan in a line- and region-dependent manner. We also compared the dense-core plaque burdens in the mice to those measured in a set of pathologically-confirmed AD cases from the Nun Study. Cortical plaque burdens in Tg2576, APPSwePS1ΔE9, and 5XFAD mice eventually far exceeded those measured in the human cohort.

Reduced Cardiovascular Functions in Patients with Alzheimer's Disease. - Jin, Wang-Sheng; Bu, Xian-Le; Wang, Ye-Ran; Li, Ling; Li, Wei-Wei; Liu, Yu-Hui; Zhu, Chi; Yao, Xiu-Qing; Chen, Yang; Gao, Chang-Yue; Zhang, Tao; Gao, Chang-Yue; et al. (J Alzheimers Dis, 2017)
Previous studies have suggested that cardiovascular functions might play a critical role in Alzheimer's disease (AD) pathogenesis. However, the relationship among heart function, blood flow of cerebral vessels, and AD remains unclear. In the present study, AD patients (n = 34) and age- and gender-matched cognitively normal controls (n = 34) were recruited. Comorbidity information was collected. The ejection fraction was measured using echocardiography, and the mean velocity, pulsatility index (PI), and resistance index (RI) of the basilar artery (BA), left terminal internal carotid artery (LTICA), and right terminal internal carotid artery (RTICA) were measured using transcranial Doppler. The lacunae, white matter changes, and plaque in the aortic arch and carotid arteries were collected from brain magnetic resonance imaging and computed tomography angiography images. Compared with normal controls, AD patients had lower ejection fractions and cerebral blood flow velocities and a higher RI and PI in the BA, LTICA, and RTICA, as well as more plaques in the aortic and carotid arteries. In the multivariate logistic regression analysis, the ejection fraction and the mean velocity of the BA and LTICA were independently associated with AD after adjusting for age, gender, education, vascular risk factors, arterial plaques, and brain ischemic lesions detected in the brain images. These findings suggest that heart function and vascular condition may play important roles in AD pathogenesis. Improving cardiovascular functions could be a promising approach for the prevention and treatment of AD.

Reduced Cerebral Blood Flow in Mild Cognitive Impairment Assessed Using Phase-Contrast MRI. - de Eulate, Reyes García; Goñi, Irene; Galiano, Alvaro; Vidorreta, Marta; Recio, Miriam; Riverol, Mario; Zubieta, José L; Fernández-Seara, María A (J Alzheimers Dis, 2017)
There is increasing evidence of a vascular contribution to Alzheimer's disease (AD). In some cases, prior work suggests that chronic brain hypoperfusion could play a prime pathogenic role contributing to the accumulation of amyloid-β,while other studies favor the hypothesis that vascular dysfunction and amyloid pathology are independent, although synergistic, mechanisms contributing to cognitive impairment. Vascular dysfunction can be evaluated by assessing cerebral blood flow impairment. Phase contrast velocity mapping by MRI offers a non-invasive means of quantifying the total inflow of blood to the brain. This quantitative parameter could be a sensitive indicator of vascular disease at early stages of AD. In this work, phase contrast MRI was used to evaluate cerebral hemodynamics in patients with subjective memory complaints, amnestic mild cognitive impairment, and mild to moderate AD, and compare them with control subjects. Results showed that blood flow and velocity were decreased in the patients with cognitive dysfunction and the decrease correlated with the degree of cognitive impairment as assessed by means of neuropsychological tests. Total cerebral blood flow measurements were clearly reduced in AD patients, but more importantly appeared to be sensitive enough to distinguish between healthy subjects and those with mild cognitive impairment. A quantitative measurement of total brain blood flow could potentially predict vascular dysfunction and compromised brain perfusion in early stages of AD.

Reduced Cerebrospinal Fluid Concentration of Apolipoprotein A-I in Patients with Alzheimer's Disease. - Johansson, Per; Almqvist, Erik G; Bjerke, Maria; Wallin, Anders; Johansson, Jan-Ove; Andreasson, Ulf; Blennow, Kaj; Zetterberg, Henrik; Svensson, Johan (J Alzheimers Dis, 2017)
BACKGROUND: Apolipoprotein E (ApoE) has been extensively studied in Alzheimer's disease (AD), but little is known of apolipoprotein A-I (ApoA-I) in cerebrospinal fluid (CSF). OBJECTIVE: Plasma lipids as well as ApoA-I and ApoE in plasma and CSF were determined and related to Mini-Mental State Examination (MMSE) score, APOE genotype, and CSF AD biomarkers. METHODS: Consecutive patients with AD (n = 29), stable mild cognitive impairment (n = 13), other dementias (n = 14), and healthy controls (n = 18) were included at a single center. RESULTS: AD patients had higher plasma triglycerides and lower CSF ApoA-I concentration than controls (both p < 0.05). CSF ApoE concentration was reduced in other dementias (p < 0.01). In AD as well as other dementias, the ratios between CSF and plasma concentrations of both ApoA-I and ApoE were lower than those in the controls. ApoA-I and ApoE in plasma and CSF were not influenced by APOEɛ4 allele distribution. In the total study population (n = 74), CSF ApoA-I correlated positively with MMSE score (r = 0.26, p < 0.05) and negatively with CSF P-tau (r = -0.25, p < 0.05). CSF ApoE correlated positively with CSF concentrations of T-tau and P-tau in the total study population and in AD patients. CONCLUSION: CSF ApoA-I was reduced in AD patients and associated with measures of cognitive function and AD disease status. The mechanisms underlying the decreased CSF:plasma ratios of ApoA-I and ApoE in AD and other dementias need to be explored in further studies.

Remyelination: A Potential Therapeutic Strategy for Alzheimer's Disease? - Sun, Junjun; Zhou, Hong; Bai, Feng; Zhang, Zhijun; Ren, Qingguo (J Alzheimers Dis, 2017)
Myelin is a lipid-rich multilamellar membrane that wraps around long segments of neuronal axons and it increases the conduction of action potentials, transports the necessary trophic support to the neuronal axons, and reduces the energy consumed by the neuronal axons. Together with axons, myelin is a prerequisite for the higher functions of the central nervous system and complex forms of network integration. Myelin impairments have been suggested to lead to neuronal dysfunction and cognitive decline. Accumulating evidence, including brain imaging and postmortem and genetic association studies, has implicated myelin impairments in Alzheimer's disease (AD). Increasing data link myelin impairments with amyloid-β (Aβ) plaques and tau hyperphosphorylation, which are both present in patients with AD. Moreover, aging and apolipoprotein E (ApoE) may be involved in the myelin impairments observed in patients with AD. Decreased neuronal activity, increased Aβ levels, and inflammation further damage myelin in patients with AD. Furthermore, treatments that promote myelination contribute to the recovery of neuronal function and improve cognition. Therefore, strategies targeting myelin impairment may provide therapeutic opportunities for patients with AD.

Role of Niemann-Pick Type C Disease Mutations in Dementia. - Cupidi, Chiara; Frangipane, Francesca; Gallo, Maura; Clodomiro, Alessandra; Colao, Rosanna; Bernardi, Livia; Anfossi, Maria; Conidi, Maria Elena; Vasso, Franca; Curcio, Sabrina Anna Maria; Mirabelli, Maria; Smirne, Nicoletta; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Several neurological and systemic diseases can cause dementia, beyond Alzheimer's disease. Rare genetic causes are often responsible for dementia with atypical features. Recently, mutations causative for Niemann-Pick type C disease (NPC) have also been implicated in neurodegenerative diseases. NPC is an autosomal recessive lipid storage disorder caused by mutations in NPC1 and NPC2 genes. In adults, clinical presentation mimicking other neurodegenerative diseases makes diagnosis difficult. Recent evidence suggests that heterozygous mutations in NPC genes may take on etiological significance. OBJECTIVE: To investigate the presence of NPC1 and NPC2 mutations in adults affected by neurodegenerative dementia plus. METHODS: We performed a genetic screening on 50 patients using a wide clinical and biochemical approach to characterize the phenotype of mutated patients. RESULTS: Sequencing analysis revealed four different and known heterozygous mutations in NPC1 and NPC2 genes. Patient 1 carried the p. F284LfsX26 in NPC1 and was affected by progressive supranuclear palsy-like syndrome. The remaining three patients showed a corticobasal syndrome and harbored the c.441+1G>A variant of NPC2 (patient 2), the missense p.N222 S mutation associated with the c.1947+8G>C variant in the splice region of intron 12 in NPC1 (patient 3), and the p.V30M mutation in NPC2 (patient 4), respectively. Filipin staining was abnormal in patients 1 and 2. mRNA analysis revealed an altered splicing of the NPC2 gene in patient 2. CONCLUSIONS: Heterozygous mutations of NPC1 and NPC2 genes could contribute to dementia plus, at least in a subset of patients. We highlight the occurrence of NPC1 and NPC2 heterozygous variants in dementia-plus as pathological event.

Selenomethionine Attenuates the Amyloid-β Level by Both Inhibiting Amyloid-β Production and Modulating Autophagy in Neuron-2a/AβPPswe Cells. - Zhang, Zhong-Hao; Wu, Qiu-Yan; Chen, Chen; Zheng, Rui; Chen, Yao; Liu, Qiong; Ni, Jia-Zuan; Song, Guo-Li (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a complex and progressive neurological disorder, and amyloid-β (Aβ) has been recognized as the major cause of AD. Inhibiting Aβ production and/or enhancing the clearance of Aβ to reduce its levels are still the effective therapeutic strategies pursued in anti-AD research. In previous studies, we have reported that selenomethionine (Se-Met), a major form of selenium in animals and humans with significant antioxidant capacity, can reduce both amyloid-β (Aβ) deposition and tau hyperphosphorylation in a triple transgenic mouse model of AD. In this study, a Se-Met treatment significantly decreased the Aβ levels in Neuron-2a/AβPPswe (N2asw) cells, and the anti-amyloid effect of Se-Met was attributed to its ability to inhibit Aβ generation by suppressing the activity of BACE1. Furthermore, both the LC3-II/LC3-I ratio and the number of LC3-positive puncta were significantly decreased in Se-Met-treated cells, suggesting that Se-Met also promoted Aβ clearance by modulating the autophagy pathway. Subsequently, Se-Met inhibited the initiation of autophagy through the AKT-mTOR-p70S6K signaling pathway and enhanced autophagic turnover by promoting autophagosome-lysosome fusion and autophagic clearance. Our results further highlight the potential therapeutic effects of Se-Met on AD.

Sleep Deprivation Induced Plasma Amyloid-β Transport Disturbance in Healthy Young Adults. - Wei, Meng; Zhao, Beiyu; Huo, Kang; Deng, Yongning; Shang, Suhang; Liu, Jie; Li, Yanbo; Ma, Louyan; Jiang, Yu; Dang, Liangjun; Chen, Chen; Wei, Shan; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sleep is an important physiological process and beneficial in the removal of brain metabolites and functional recovery. Prior studies have shown that sleep disorders are significant risk factors for Alzheimer's disease (AD). OBJECTIVE: The present study was designed to characterize the effect of short-term total sleep deprivation (TSD) on plasma amyloid-β (Aβ) concentrations. METHODS: A clinical trial was conducted between March 1, 2016, and April 1, 2016. Twenty volunteers (age 27.3±3.4 years) with normal cognitive function and sleeping habits were recruited from the local population. Participants underwent 24 h of TSD. Periprocedural blood samples were collected to compare the changes of plasma Aβ42, Aβ40, low-density lipoprotein receptor-related protein (sLRP-1), soluble receptors for advanced glycation end products (sRAGE), and serum superoxide dismutase (SOD) and malonaldehyde (MDA). RESULTS: TSD increased morning plasma Aβ40 levels by 32.6% (p < 0.001) and decreased the Aβ42/Aβ40 ratio by 19.3% (p < 0.001). A positive relationship was found between TSD duration and plasma Aβ40 level (r = 0.51, p < 0.001) and Aβ40/Aβ42 ratio (r = 0.25, p = 0.003). Plasma concentrations of sLRP1 (p = 0.018) and sRAGE (p = 0.001) decreased significantly after TSD. Aβ40 and Aβ42 plasma concentrations correlated with plasma levels of sLRP1 and sRAGE. Serum SOD decreased after TSD (p = 0.005), whereas serum MDA was increased (p = 0.001). CONCLUSION: Sleep deprivation can lead to an elevation of plasma Aβ40 and decrease of the Aβ42/Aβ40 ratio. The underlying mechanisms may be related to increased oxidative stress and impaired peripheral Aβ clearance as pathomechanisms of AD.
Keywords: Adult; Amyloid beta-Peptides; Female; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Malondialdehyde; Peptide Fragments; Receptor for Advanced Glycation End Products; Sleep Deprivation; Superoxide Dismutase; Time Factors; Young Adult

Specific Verbal Memory Measures May Distinguish Alzheimer's Disease from Dementia with Lewy Bodies. - Bussè, Cinzia; Anselmi, Pasquale; Pompanin, Sara; Zorzi, Giovanni; Fragiacomo, Federica; Camporese, Giulia; Di Bernardo, Gian Antonio; Semenza, Carlo; Caffarra, Paolo; Cagnin, Annachiara (J Alzheimers Dis, 2017)
BACKGROUND: Standard measures of commonly used memory tests may not be appropriate to distinguish different neurodegenerative diseases affecting memory. OBJECTIVE: To study whether specific measures of verbal memory obtained with the Rey Auditory Verbal Learning test (RAVLT) could help distinguish dementia with Lewy bodies (DLB) from Alzheimer's disease (AD). METHODS: Twenty-nine DLB and 32 AD patients participated in the study and were followed longitudinally for 3 years until the diagnosis was confirmed according to standard clinical criteria. Twenty-eight healthy elderly subjects served as controls. The following verbal memory measures were evaluated: verbal learning (VL), verbal forgetting (VF), percentage of verbal forgetting (VF%), and serial position effects of the immediate recall performance. RESULTS: DLB and AD groups have comparable performances at the RAVLT immediate and delayed recall tasks. However, VL was higher in DLB than AD while VF% was greater in AD. With a VF% cut-off ≥75%, AD and DLB patients were differently distributed, with 58% of AD versus 21% of DLB above this cut-off. The recency effect was significant higher in AD than DLB. DISCUSSION: DLB patients had a better performance in VL than AD, but worse VF and recency effect. These specific measures of verbal memory could be used as cognitive markers in the differential diagnosis between these two conditions.

State of Play in Alzheimer's Disease Genetics. - Zhu, Jin-Bao; Tan, Chen-Chen; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2017)
Alzheimer's disease (AD), the main form of dementia in the elderly, is the most common progressive neurodegenerative disease characterized by rapidly progressive cognitive dysfunction and behavior impairment. AD exhibits a considerable heritability and great advances have been made in approaches to searching the genetic etiology of AD. In AD genetic studies, methods have developed from classic linkage-based and candidate-gene-based association studies to genome-wide association studies (GWAS) and next generation sequencing (NGS). The identification of new susceptibility genes has provided deeper insights to understand the mechanisms underlying AD. In addition to searching novel genes associated with AD in large samples, the NGS technologies can also be used to shed light on the 'black matter' discovery even in smaller samples. The shift in AD genetics between traditional studies and individual sequencing will allow biomaterials of each patient as the central unit of genetic studies. This review will cover genetic findings in AD and consequences of AD genetic findings. Firstly, we will discuss the discovery of mutations in APP, PSEN1, PSEN2, APOE, and ADAM10. Then we will summarize and evaluate the information obtained from GWAS of AD. Finally, we will outline the efforts to identify rare variants associated with AD using NGS.

Tai Chi Chuan and Baduanjin Increase Grey Matter Volume in Older Adults: A Brain Imaging Study. - Tao, Jing; Liu, Jiao; Liu, Weilin; Huang, Jia; Xue, Xiehua; Chen, Xiangli; Wu, Jinsong; Zheng, Guohua; Chen, Bai; Li, Ming; Sun, Sharon; Jorgenson, Kristen; et al. (J Alzheimers Dis, 2017)
The aim of this study is to investigate and compare how 12-weeks of Tai Chi Chuan and Baduanjin exercise can modulate brain structure and memory function in older adults. Magnetic resonance imaging and memory function measurements (Wechsler Memory Scale-Chinese revised, WMS-CR) were applied at both the beginning and end of the study. Results showed that both Tai Chi Chuan and Baduanjin could significantly increase grey matter volume (GMV) in the insula, medial temporal lobe, and putamen after 12-weeks of exercise. No significant differences were observed in GMV between the Tai Chi Chuan and Baduanjin groups. We also found that compared to healthy controls, Tai Chi Chuan and Baduanjin significantly improved visual reproduction subscores on the WMS-CR. Baduanjin also improved mental control, recognition, touch, and comprehension memory subscores of the WMS-CR compared to the control group. Memory quotient and visual reproduction subscores were both associated with GMV increases in the putamen and hippocampus. Our results demonstrate the potential of Tai Chi Chuan and Baduanjin exercise for the prevention of memory deficits in older adults.

Tau Oligomers Associate with Inflammation in the Brain and Retina of Tauopathy Mice and in Neurodegenerative Diseases. - Nilson, Ashley N; English, Kelsey C; Gerson, Julia E; Whittle, T Barton; Crain, C Nicolas; Xue, Judy; Sengupta, Urmi; Castillo-Carranza, Diana L; Zhang, Wenbo; Gupta, Praveena; Kayed, Rakez (J Alzheimers Dis, 2017)
It is well-established that inflammation plays an important role in Alzheimer's disease (AD) and frontotemporal lobar dementia (FTLD). Inflammation and synapse loss occur in disease prior to the formation of larger aggregates, but the contribution of tau to inflammation has not yet been thoroughly investigated. Tau pathologically aggregates to form large fibrillar structures known as tangles. However, evidence suggests that smaller soluble aggregates, called oligomers, are the most toxic species and form prior to tangles. Furthermore, tau oligomers can spread to neighboring cells and between anatomically connected brain regions. In addition, recent evidence suggests that inspecting the retina may be a window to brain pathology. We hypothesized that there is a relationship between tau oligomers and inflammation, which are hallmarks of early disease. We conducted immunofluorescence and biochemical analyses on tauopathy mice, FTLD, and AD subjects. We showed that oligomers co-localize with astrocytes, microglia, and HMGB1, a pro-inflammatory cytokine. Additionally, we show that tau oligomers are present in the retina and are associated with inflammatory cells suggesting that the retina may be a valid non-invasive biomarker for brain pathology. These results suggest that there may be a toxic relationship between tau oligomers and inflammation. Therefore, the ability of tau oligomers to spread may initiate a feed-forward cycle in which tau oligomers induce inflammation, leading to neuronal damage, and thus more inflammation. Further mechanistic studies are warranted in order to understand this relationship, which may have critical implications for improving the treatment of tauopathies.

Tau Pathology Promotes the Reorganization of the Extracellular Matrix and Inhibits the Formation of Perineuronal Nets by Regulating the Expression and the Distribution of Hyaluronic Acid Synthases. - Li, Yin; Li, Ze-Xu; Jin, Tan; Wang, Zhan-You; Zhao, Pu (J Alzheimers Dis, 2017)
Hyaluronic acid (HA) is the backbone of the extracellular matrix (ECM) and provides biochemical and physical support to aggrecan-based perineuronal nets (PNNs), which are associated with the selective vulnerability of neurons in Alzheimer's disease (AD). Here, we showed that HA synthases (HASs), including Has1, Has2, and Has3, were widely expressed in murine central nervous system. All types of HASs were localized to cell bodies of neurons; only Has1 existed in the membranes of neural axons. By using TauP301S transgenic (Tg) mouse model, we found that the axonal-localization of Has1 was abolished in TauP301S overexpressed mouse brain, and the redistribution of Has1 was also observed in human AD brains, suggesting that the localization of Has1 is dependent on intact microtubules which are regulated partially by the phosphorylation and dephosphorylation cycles of tau proteins. Furthermore, Has1 was reduced and Has3 was increased in TauP301S Tg mouse brain, resulting in the upregulation of shorter-chain HA in the ECM. These findings suggest that by abolishing the axonal-localization of Has1 and promoting the expression of Has3 and the synthesis of shorter-chain HA, the tau pathology breaks the balance of ECM components, promotes the reorganization of the ECM, and inhibits the formation of PNNs in the hippocampus, and then regulates neuronal plasticity during the progression of AD.

Tau Proteins Cross the Blood-Brain Barrier. - Banks, William A; Kovac, Andrej; Majerova, Petra; Bullock, Kristin M; Shi, Min; Zhang, Jing (J Alzheimers Dis, 2017)
Tauopathies are a hallmark of many neurodegenerative diseases, including Alzheimer's disease and traumatic brain injuries. It has been demonstrated that amyloid-beta peptides, alpha-synuclein, and prion proteins cross the blood-brain barrier (BBB), contributing to their abilities to induce disease. Very little is known about whether tau proteins can cross the BBB. Here we systematically characterized several key forms of tau proteins to cross the BBB, including Tau-441 (2N4R), Tau-410 (2N3R), truncated tau 151-391 (0N4R), and truncated tau 121-227. All of these tau proteins crossed the BBB readily and bidirectonally; however, only Tau-410 had a saturable component to its influx. The tau proteins also entered the blood after their injection into the brain, with Tau 121-227 having the slowest exit from brain. The tau proteins varied in regards to their enzymatic stability in brain and blood and in their peripheral pharmacokinetics. These results show that blood-borne tau proteins could contribute to brain tauopathies. The result also suggest that the CNS can contribute to blood levels of tau, raising the possibility that, as suggested for other misfolded proteins, blood levels of tau proteins could be used as a biomarker of CNS disease.

Topological Alterations and Symptom-Relevant Modules in the Whole-Brain Structural Network in Semantic Dementia. - Ding, Junhua; Chen, Keliang; Zhang, Weibin; Li, Ming; Chen, Yan; Yang, Qing; Lv, Yingru; Guo, Qihao; Han, Zaizhu (J Alzheimers Dis, 2017)
BACKGROUND: Semantic dementia (SD) is characterized by a selective decline in semantic processing. Although the neuropsychological pattern of this disease has been identified, its topological global alterations and symptom-relevant modules in the whole-brain anatomical network have not been fully elucidated. OBJECTIVE: This study aims to explore the topological alteration of anatomical network in SD and reveal the modules associated with semantic deficits in this disease. METHODS: We first constructed the whole-brain white-matter networks of 20 healthy controls and 19 patients with SD. Then, the network metrics of graph theory were compared between these two groups. Finally, we separated the network of SD patients into different modules and correlated the structural integrity of each module with the severity of the semantic deficits across patients. RESULTS: The network of the SD patients presented a significantly reduced global efficiency, indicating that the long-distance connections were damaged. The network was divided into the following four distinctive modules: the left temporal/occipital/parietal, frontal, right temporal/occipital, and frontal/parietal modules. The first two modules were associated with the semantic deficits of SD. CONCLUSION: These findings illustrate the skeleton of the neuroanatomical network of SD patients and highlight the key role of the left temporal/occipital/parietal module and the left frontal module in semantic processing.

Trajectories of Multidimensional Caregiver Burden in Chinese Informal Caregivers for Dementia: Evidence from Exploratory and Confirmatory Factor Analysis of the Zarit Burden Interview. - Li, Dan; Hu, Nan; Yu, Yueyi; Zhou, Aihong; Li, Fangyu; Jia, Jianping (J Alzheimers Dis, 2017)
BACKGROUND: Despite its popularity, the latent structure of 22-item Zarit Burden Interview (ZBI) remains unclear. There has been no study exploring how caregiver multidimensional burden changed. OBJECTIVE: The aim of the work was to validate the latent structure of ZBI and to investigate how multidimensional burden evolves with increasing global burden. METHODS: We studied 1,132 dyads of dementia patients and their informal caregivers. The caregivers completed the ZBI and a questionnaire regarding caregiving. The total sample was randomly split into two equal subsamples. Exploratory factor analysis (EFA) was performed in the first subsample. In the second subsample, confirmatory factor analysis (CFA) was conducted to validate models generated from EFA. The mean of weighted factor score was calculated to assess the change of dimension burden against the increasing ZBI total score. RESULTS: The result of EFA and CFA supported that a five-factor structure, including role strain, personal strain, incompetency, dependency, and guilt, had the best goodness-of-fit. The trajectories of multidimensional burden suggested that three different dimensions (guilt, role strain and personal strain) became the main subtype of burden in sequence as the ZBI total score increased from mild to moderate. Factor dependency contributed prominently to the total burden in severe stage. CONCLUSION: The five-factor ZBI is a psychometrically robust measure for assessing multidimensional burden in Chinese caregivers. The changes of multidimensional burden have deepened our understanding of the psychological characteristics of caregiving beyond a single total score and may be useful for developing interventions to reduce caregiver burden.

Treadmill Exercise Exerts Neuroprotection and Regulates Microglial Polarization and Oxidative Stress in a Streptozotocin-Induced Rat Model of Sporadic Alzheimer's Disease. - Lu, Yujiao; Dong, Yan; Tucker, Donovan; Wang, Ruimin; Ahmed, Mohammad Ejaz; Brann, Darrell; Zhang, Quanguang (J Alzheimers Dis, 2017)
Recent work has suggested that exercise may be beneficial in preventing or ameliorating symptoms of several neurological disorders, although the mechanism is not entirely understood. The current study was designed to examine the potential beneficial effect of treadmill exercise upon cognitive function in a streptozotocin (STZ)-induced rat model of Alzheimer's disease (AD). Animals underwent treadmill exercise (30 min/day, 5 days/week) for 4 weeks after bilateral STZ intracerebroventricular injection (2.4 mg/kg). We demonstrated that treadmill exercise significantly attenuated STZ-induced neurodegeneration in the rat hippocampal CA1 region and strongly preserved hippocampal-dependent cognitive functioning. Further mechanistic investigation displayed a marked suppression of STZ-induced amyloid-β accumulation and tau phosphorylation. Intriguingly, treadmill exercise remarkably inhibited reactive gliosis following STZ insult and effectively shifted activated microglia from a pro-inflammatory M1 to an anti-inflammatory M2 phenotype, which was correlated with a significantly reduced expression of pro-inflammatory mediators and a corresponding enhancement of anti-inflammatory cytokine expression in the hippocampus. Furthermore, treadmill exercise caused a robust suppression of oxidative damage as evidenced by significantly reduced peroxynitrite production, lipid peroxidation, and oxidized DNA damage. Finally, treadmill exercise strongly attenuated STZ-induced mitochondrial dysfunction manifested by a dramatically elevated intra-mitochondrial cytochrome c oxidase activity and ATP synthesis, and markedly inhibited neuronal apoptosis in the hippocampus. These findings demonstrate that treadmill exercise has a multifactorial effect to attenuate many of the pathological processes that play a key role in AD, and provide further support for the beneficial role of exercise as a potential therapeutic option in AD treatment.

Trends, Predictors, and Outcomes of Healthcare Resources Used in Patients Hospitalized with Alzheimer's Disease with at Least One Procedure: The Nationwide Inpatient Sample. - Beydoun, May A; Gamaldo, Alyssa A; Beydoun, Hind A; Shaked, Danielle; Zonderman, Alan B; Eid, Shaker M (J Alzheimers Dis, 2017)
We assessed trends, predictors and outcomes of resource utilization in hospital inpatient discharges with a principal diagnosis of Alzheimer's disease (AD) with at least one procedure. Using Nationwide Inpatient Sample data (NIS, 2002-2012), discharges primarily diagnosed with AD, aged ≥60 y and with ≥1 procedure, were selected (Weighted N = 92,300). Hospital resource utilization were assessed using ICD-9-CM codes, while hospitalization outcomes included total charges (TC, 2012$), length of stay (LOS, days), and mortality risk (MR, %). Brain and respiratory/gastrointestinal procedure utilization both dropped annually by 3-7%, while cardiovascular procedures/evaluations, blood evaluations, blood transfusion, and resuscitation ("CVD/Blood") as well as neurophysiological and psychological evaluation and treatment ("Neuro") procedures increased by 5-8%. Total charges, length of stay, and mortality risk were all markedly higher with use of respiratory/gastrointestinal procedures as opposed to being reduced with use of "Brain" procedures. Procedure count was positively associated with all three hospitalization outcomes. In sum, patterns of hospital resources that were used among AD inpatients changed over-time, and were associated with hospitalization outcomes such as total charges, length of stay, and mortality risk.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Female; Health Resources; Hospitalization; Humans; Inpatients; Length of Stay; Male; Middle Aged; Morbidity; Outcome Assessment (Health Care); Predictive Value of Tests; United States

Urine AD7c-NTP Predicts Amyloid Deposition and Symptom of Agitation in Patients with Alzheimer's Disease and Mild Cognitive Impairment. - Zhang, Nan; Zhang, Liling; Li, Yan; Gordon, Marc L; Cai, Li; Wang, Ying; Xing, Mengya; Cheng, Yan (J Alzheimers Dis, 2017)
BACKGROUND: Expression of neuronal thread protein (NTP), which is considered to be related to neuritic sprouting and neuronal death, may be elevated in brain tissue, cerebrospinal fluid, and even urine in patients with Alzheimer's disease (AD). OBJECTIVE: In this study, we analyzed the correlation between urine AD-associated NTP (AD7c-NTP) level, and amyloid-β (Aβ) deposition, and clinical symptoms in AD and mild cognitive impairment (MCI). METHODS: Twenty-two patients with mild to moderate AD and 8 subjects with MCI were recruited. Aβ deposition was measured with [11C]-labeled Pittsburgh compound B (PiB)-positron emission tomography (PET) in all participants. Urine AD7c-NTP levels were measured using enzyme-linked immunosorbent assay. Mini-Mental State Examination (MMSE) and Neuropsychiatric Inventory (NPI) were used to evaluate cognitive function and behavioral psychological symptoms, respectively. RESULTS: Fourteen (63.6%) of AD patients and 2 (25.0%) of MCI subjects were Aβ positive on PiB-PET. There was a significant difference in urine AD7c-NTP level between Aβ positive (2.27±2.22 ng/ml) and negative (0.55±0.60 ng/ml) subjects (p = 0.018). Using 1.46 ng/ml as a cut-off value, 68.8% of Aβ positive subjects showed elevated urine AD7c-NTP level, and 92.9% of Aβ negative subjects showed normal urine AD7c-NTP level. There were no relationships between urine AD7c-NTP level and MMSE and total NPI scores. However, AD7c-NTP level positively correlated with agitation score on NPI. CONCLUSIONS: Urine AD7c-NTP had high specificity and moderate sensitivity in predicting Aβ deposition among patients with cognitive impairment. Furthermore, urine AD7c-NTP level strongly correlated with the symptom of agitation.

Utility of Molecular and Structural Brain Imaging to Predict Progression from Mild Cognitive Impairment to Dementia. - Lan, Martin J; Ogden, R Todd; Kumar, Dileep; Stern, Yaakov; Parsey, Ramin V; Pelton, Gregory H; Rubin-Falcone, Harry; Pradhaban, Gnanavalli; Zanderigo, Francesca; Miller, Jeffrey M; Mann, J John; Devanand, D P (J Alzheimers Dis, 2017)
This project compares three neuroimaging biomarkers to predict progression to dementia in subjects with mild cognitive impairment (MCI). Eighty-eight subjects with MCI and 40 healthy controls (HCs) were recruited. Subjects had a 3T magnetic resonance imaging (MRI) scan, and two positron emission tomography (PET) scans, one with Pittsburgh compound B ([11C]PIB) and one with fluorodeoxyglucose ([18F]FDG). MCI subjects were followed for up to 4 y and progression to dementia was assessed on an annual basis. MCI subjects had higher [11C]PIB binding potential (BPND) than HCs in multiple brain regions, and lower hippocampus volumes. [11C]PIB BPND, [18F]FDG standard uptake value ratio (SUVR), and hippocampus volume were associated with time to progression to dementia using a Cox proportional hazards model. [18F]FDG SUVR demonstrated the most statistically significant association with progression, followed by [11C]PIB BPND and then hippocampus volume. [11C]PIB BPND and [18F]FDG SUVR were independently predictive, suggesting that combining these measures is useful to increase accuracy in the prediction of progression to dementia. Hippocampus volume also had independent predictive properties to [11C]PIB BPND, but did not add predictive power when combined with the [18F]FDG SUVR data. This work suggests that PET imaging with both [11C]PIB and [18F]FDG may help to determine which MCI subjects are likely to progress to AD, possibly directing future treatment options.

The Utility of the Cognitive Function Instrument (CFI) to Detect Cognitive Decline in Non-Demented Older Adults. - Li, Clara; Neugroschl, Judith; Luo, Xiaodong; Zhu, Carolyn; Aisen, Paul; Ferris, Steven; Sano, Mary (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive complaint is a sensitive marker of decline. OBJECTIVE: This study aimed to (1) examine reliability of subjective cognitive complaint using the Cognitive Function Instrument (CFI), and (2) assess the utility of the CFI to detect cognitive decline in non-demented elders. METHODS: Data from a four-year longitudinal study at multiple Alzheimer's Disease Cooperative Study (ADCS) sites were extracted (n = 644). Of these, 497 had Clinical Dementia Rating (CDR) global scores of 0 and 147 had a CDR of 0.5. Mean age and education were 79.5±3.6 and 15.0±3.1 years, respectively. All participants and their study partners completed the subject and study partner CFI yearly. Modified Mini-Mental State Exam (mMMSE) and Free and Cued Selective Reminding Test (FCSRT) were administered. Scores below the predetermined cut-off scores on either measure at annual visit were triggers for a full diagnostic evaluation. Cognitive decline was defined by the absence/presence of the trigger. RESULTS: Three-month test retest reliability showed that inter-class coefficients for subject and study partner CFI were 0.76 and 0.78, respectively. Generalized estimating equation method revealed that both subject and study partner CFI change scores and scores from previous year were sensitive to cognitive decline in the CDR 0 group (p < 0.05). In the CDR 0.5 group, only the study partner CFI change score predicted cognitive decline (p < 0.05). CONCLUSION: Cognitive decline was predicted differentially by CDR level with subject CFI scores providing the best prediction for those with CDR 0 while study partner CFI predicted best for those at CDR 0.5.

Validation of a Latent Construct for Dementia in a Population-Wide Dataset from Singapore. - Peh, Chao Xu; Abdin, Edimansyah; Vaingankar, Janhavi A; Verma, Swapna; Chua, Boon Yiang; Sagayadevan, Vathsala; Seow, Esmond; Zhang, YunJue; Shahwan, Shazana; Ng, Li Ling; Prince, Martin; Chong, Siow Ann; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The latent variable δ has been proposed as a proxy for dementia. Previous validation studies have been conducted using convenience samples. It is currently unknown how δ performs in population-wide data. OBJECTIVE: To validate δ in Singapore using population-wide epidemiological study data on persons aged 60 and above. METHODS: δ was constructed using items from the Community Screening Instrument for Dementia (CSI'D) and World Health Organization Disability Assessment Schedule (WHODAS II). Confirmatory factor analysis (CFA) was conducted to examine δ model fit. Convergent validity was examined with the Clinical Dementia Rating scale (CDR) and GMS-AGECAT dementia. Divergent validity was examined with GMS-AGECAT depression. RESULTS: The δ model demonstrated fit to the data, χ2(df) = 249.71(55), p < 0.001, CFI = 0.990, TLI = 0.997, RMSEA = 0.037. Latent variable δ was significantly associated with CDR and GMS-AGECAT dementia (range: β= 0.32 to 0.63), and was not associated with GMS-AGECAT depression. Compared to unadjusted models, δ model fit was poor when adjusted for age, gender, ethnicity, and education. CONCLUSION: The study found some support for δ as a proxy for dementia in Singapore based on population data. Both convergent and divergent validity were established. In addition, the δ model structure appeared to be influenced by age, gender, ethnicity, and education covariates.

Vitamin D and the Risk of Dementia: The Rotterdam Study. - Licher, Silvan; de Bruijn, Renée F A G; Wolters, Frank J; Zillikens, M Carola; Ikram, M Arfan; Ikram, M Kamran (J Alzheimers Dis, 2017)
BACKGROUND: Vitamin D has gained interest as a potentially modifiable risk factor for dementia because of its putative neuroprotective effects. However, longitudinal studies examining the association between vitamin D and dementia have provided inconsistent results. OBJECTIVE: To determine the relationship of serum vitamin D with prevalent and incident dementia in the general population. METHODS: Within the prospective Rotterdam Study, we measured serum 25-hydroxyvitamin D concentrations between 1997 and 2001 using electrochemiluminescence-immunoassay in 6220 participants 55 years or older. We assessed dementia at baseline and continuously during follow-up until 1 January 2015. We used appropriate regression models to determine the relationship of vitamin D with prevalent and incident dementia, including Alzheimer's disease (AD). We adjusted models for age, sex, and season of blood collection. Additionally, we adjusted for ethnicity, education, cardiovascular risk factors, serum calcium, kidney function, depression, outdoor-activity and APOEɛ4 carriership. RESULTS: At baseline, 127 of 6,220 participants had dementia, of whom 97 had AD. Lower vitamin D concentrations were associated with a non-significantly higher prevalence of dementia (adjusted OR, per SD decrease 1.20, 95% CI 0.95;1.52), but not with AD (adjusted OR: 0.97, 95% CI 0.74;1.29). Among 6,087 non-demented participants with 68,884 person-years of follow-up, 795 participants developed dementia, of whom 641 had AD. Lower vitamin D concentrations were associated with higher risk of dementia (adjusted HR, per SD decrease 1.11, 95% CI 1.02;1.20) and AD (adjusted HR: 1.13, 95% CI 1.03;1.24). CONCLUSION: Lower serum vitamin D concentrations are associated with a higher incidence of dementia.

Voluptuary Habits and Risk of Frontotemporal Dementia: A Case Control Retrospective Study. - Tremolizzo, Lucio; Bianchi, Elisa; Susani, Emanuela; Pupillo, Elisabetta; Messina, Paolo; Aliprandi, Angelo; Salmaggi, Andrea; Cosseddu, Maura; Pilotto, Andrea; Borroni, Barbara; Padovani, Alessandro; Bonomini, Cristina; et al. (J Alzheimers Dis, 2017)
Alcohol, coffee, and tobacco consumption was assessed on 151 FTD outpatients and 151 matched controls in a multicenter retrospective case-control design. No association was found for smoking and coffee intake. The risk of FTD was decreased by alcohol consumption (adj. OR 0.30, 95% CI 0.14-0.63); risk reduction was significant in current alcohol consumers (adj. OR 0.22, 95% CI 0.10-0.51). The risk of FTD inversely correlated with the duration of exposure (adj. OR 0.88, 95% CI 0.81-0.95, for every 5 years of exposure increase). Retrospective information and the unknown amount of consumed alcohol are limits of the present work.

ABCA7 Genotypes Confer Alzheimer's Disease Risk by Modulating Amyloid-β Pathology. - Zhao, Qing-Fei; Wan, Yu; Wang, Hui-Fu; Sun, Fu-Rong; Hao, Xiao-Ke; Tan, Meng-Shan; Tan, Chen-Chen; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
ABCA7 gene has been identified as a strong genetic locus for Alzheimer's disease (AD) susceptibility in genome wide association studies (GWAS). However, the possible roles of ABCA7 variants in AD pathology were not specifically assessed. Using tagger methods, we extracted 15 targeted ABCA7 loci to investigate their associations with cerebrospinal fluid (CSF) and neuroimaging markers in Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset. Finally, although we did not detect any significant associations of previously published GWAS SNPs (rs3764650 and rs78117248) with all the CSF (Aβ1 - 42, T-tau, and P-tau) and neuroimaging markers, three other variants (rs3752242, rs3752240, and rs4147912) at ABCA7 loci were detected to show significant associations with amyloid deposition on AV-45 PET in brain. Moreover, haplotype and subgroup analysis confirmed these significant findings. Furthermore, there were no remarkable correlations between ABCA7 variants and neuronal degeneration biomarkers (elevated CSF tau, brain structure atrophy, and hypometabolism on imaging) in this study. Thus, our study suggested that ABCA7 genotypes contribute to the AD risk through involvement in amyloid-β deposition on in vivo imaging, but not in tau pathology, brain atrophy, or decreased glucose metabolism.

Aberrant Spontaneous Brain Activity in Patients with Mild Cognitive Impairment and concomitant Lacunar Infarction: A Resting-State Functional MRI Study. - Ni, Ling; Liu, Renyuan; Yin, Zhenyu; Zhao, Hui; Nedelska, Zuzana; Hort, Jakub; Zhou, Fei; Wu, Wenbo; Zhang, Xin; Li, Ming; Yu, Haiping; Zhu, Bin; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Lacunar infarctions (LI) have been associated with a cognitive decline and an increased risk of dementia. Whether and how the pattern of spontaneous brain activity in patients with mild cognitive impairment (MCI) differs in subjects with and without concomitant LI remains unclear. OBJECTIVE: To compare the pattern of spontaneous brain activity in MCI patients with versus those without LI using resting-state functional magnetic resonance imaging (rs-fMRI). METHODS: Forty-eight MCI patients, including 22 with LI [MCI-LI] and 26 without LI [MCI-no LI], and 28 cognitive normal subjects underwent rs-fMRI post-processed using regional homogeneity (ReHo) and the amplitude of low-frequency fluctuation (ALFF) methods. RESULTS: Compared with cognitively normal subjects, the MCI-LI patients had decreased ReHo in the precuneus/cuneus (Pcu/CU) and insula; decreased ALFF in the Pcu/CU and frontal lobe; and increased ALFF and ReHo in the temporal lobe. While the MCI-no LI group had increased ReHo and ALFF in the bilateral hippocampus and parahippocampal gyrus, frontal lobe, and decreased ALFF and ReHo in the temporal lobe. Compared with the MCI-no LI patients, those with MCI-LI had decreased ALFF in the frontal lobe; decreased ReHo in the Pcu/CU and insula; and increased ALFF and ReHo in the temporal lobe (p <  0.05, AlphaSim corrected). In MCI-LI patients, the MOCA scores showed a relatively weak correlation with ALFF values in the medial frontal gyrus (r = 0.432, p = 0.045) (of borderline significance after Bonferroni correction). CONCLUSIONS: The spontaneous brain activities in MCI-LI were distinct from MCI-no LI. The probable compensatory mechanism observed in MCI-no LI might be disrupted in MCI with LI due to vascular damage.
Keywords: Aged; Aged, 80 and over; Brain; Brain Mapping; Cognitive Dysfunction; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Rest; Stroke, Lacunar

Age and its association with low insulin and high amyloid-β peptides in blood. - Li, Huajie; Zhu, Haihao; Wallack, Max; Mwamburi, Mkaya; Abdul-Hay, Samer O; Leissring, Malcolm A; Qiu, Wei Qiao (J Alzheimers Dis, 2016)
Age is the major risk factor for developing Alzheimer's disease (AD), and modifying age-related factors may help to delay the onset of the disease. The goal of this study was to investigate the relationship between age and the metabolic factors related to the risk of developing AD. The concentrations of insulin, amylin, and amyloid-β peptide (Aβ) in plasma were measured. We further measured the activity of serum Aβ degradation by using fluorescein- and biotin-labeled Aβ40. Apolipoprotein E4 allele (ApoE4) and cognitive impairment were characterized. Subjects were divided into three age groups: 60-70, 70-80, and ≥80 years old. We found that the older the subjects, the lower the concentration of insulin (p = 0.001) and the higher the concentration of Aβ1-40 (p = 0.004) in plasma. However, age was not associated with the concentration of another pancreatic peptide, amylin, and only marginally with Aβ1-42. These relationships remained in the absence of diabetes, cardiovascular disease, and stroke, and regardless of the presence of ApoE4 and cognitive impairment. Both age and ApoE4 were inversely associated with, while insulin was positively associated with, the activities of Aβ degradation in serum. Our study suggested that low concentration of insulin and high concentration of Aβ40 are aging factors related to the risk of AD.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Cognition Disorders; Cross-Sectional Studies; Female; Humans; Insulin; Islet Amyloid Polypeptide; Linear Models; Male; Middle Aged; Multivariate Analysis; Peptide Fragments

Aging as a Precipitating Factor in Chronic Restraint Stress-Induced Tau Aggregation Pathology, and the Protective Effects of Rosmarinic Acid. - Shan, Ye; Wang, Dan-Dan; Xu, Yu-Xia; Wang, Chu; Cao, Lan; Liu, Yun-Sheng; Zhu, Cui-Qing (J Alzheimers Dis, 2016)
Stress is an important risk factor of Alzheimer's disease (AD). It has been evidenced that stress could induce tau phosphorylation and increase tau insolubility in brain; however, little is known about the interactional effect of stress with aging on tauopathy. Therefore, we explored the effects of aging on stress-induced tauopathy and the potential mechanism in mouse model of chronic restraint stress (CRS). Here we found that in general, the level of phosphorylated tau (P-tau) was higher in brain of middle-aged mice than that in adult mice under physiological conditions. CRS-induced tau phosphorylation and its insolubility were more prominent in middle-aged mice. The increase of AT8-labeled insoluble P-tau was dramatic in middle-aged mice, which was highly ubiquitinated but did not form PHF structures. The levels of chaperones were relatively lower in middle-aged mice brain; CRS further reduced the expression, especially for HDJ2/HSP40. CRS also suppressed the expression of Pin1, the peptidylprolyl cis/trans isomerase, in middle-aged mice but not in adult mice. Downregulation of HSP40 or Pin1 caused an increase of transfected extraneous tau in 293 cells. Rosmarinic acid (RA) could effectively suppress the elevation of P-tau and insoluble P-tau formation induced by CRS, and reversed the abnormal changes of chaperones and Pin1 particularly in middle-aged mice. Taken together, our findings provided evidence that aging could be a promoting factor in stress-induced tauopathy, which was relevant with malregulation of chaperones and Pin1, and RA might be a promising beneficial agent for stress-induced tauopathy.
Keywords: Aging; Animals; Antioxidants; Brain; Cinnamates; Corticotropin-Releasing Hormone; Depsides; Disease Models, Animal; HEK293 Cells; HSP90 Heat-Shock Proteins; Humans; Male; Mice; Mice, Inbred C57BL; Microscopy, Immunoelectron; NIMA-Interacting Peptidylprolyl Isomerase; Peptidylprolyl Isomerase; Phosphorylation; Precipitating Factors; Receptors, Corticotropin; Restraint, Physical; Stress, Psychological; tau Proteins; Transfection

Antioxidative and Neuroprotective Effects of Curcumin in an Alzheimer's Disease Rat Model Co-Treated with Intracerebroventricular Streptozotocin and Subcutaneous D-Galactose. - Huang, Han-Chang; Zheng, Bo-Wen; Guo, Yu; Zhao, Jian; Zhao, Jiang-Yan; Ma, Xiao-Wei; Jiang, Zhao-Feng (J Alzheimers Dis, 2016)
Epidemiological data imply links between the increasing incidences of Alzheimer's disease (AD) and type 2 diabetes mellitus. In this study, an AD rat model was established by combining treatments with intracerebroventricular streptozotocin (icv-STZ) and subcutaneous D-galactose, and the effects of curcumin on depressing AD-like symptoms were investigated. In the AD model group, rats were treated with icv-STZ in each hippocampus with 3.0 mg/kg of bodyweight once and then were subcutaneously injected with D-galactose daily (125 mg/kg of bodyweight) for 7 weeks. In the curcumin-protective group, after icv-STZ treatment, rats were treated with D-galactose (the same as in the AD model group) and intraperitoneally injected with curcumin daily (10 mg/kg of bodyweight) for 7 weeks. Vehicle-treated rats were treated as control. Compared with the vehicle control, the amount of protein carbonylation and glutathione in liver, as well as malondialdehyde in serum, were upregulated but glutathione peroxidase activity in blood was downregulated in the AD model group. The shuttle index and locomotor activity of rats in the AD model group were decreased compared with the vehicle control group. Furthermore, AD model rats showed neuronal damage and neuron loss with formation of amyloid-like substances and neurofibrillary tangles, and the levels of both β-cleavage of AβPP and phosphorylation of tau (Ser396) were significantly increased compared with the vehicle control group. Notably, compared with the AD model group, oxidative stress was decreased and the abilities of active avoidance and locomotor activity were improved, as well as attenuated neurodegeneration, in the curcumin-protective group. These results imply the applications of this animal model for AD research and of curcumin in the treatment of AD.

Application of the IWG-2 Diagnostic Criteria for Alzheimer's Disease to the ADNI. - Wang, Hui-Fu; Tan, Lan; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Liu, Ying; Wang, Chong; Tsai, Richard M; Jia, Jian-Ping; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: The International Working Group (IWG) recently proposed the revised diagnostic criteria for Alzheimer's disease (AD) to define and refine several types of AD, and to reclassify AD-related biomarkers into diagnostic and progression markers, but its performance is not known. OBJECTIVE: This study was designed to describe the application of the revised IWG criteria in the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, and to ascertain whether diagnostic and progression markers show significant differences in their relationships to AD severity and progression. METHODS: Based on the requirements of the refined criteria, 857 ADNI subjects with memory evaluation and at least one pathophysiological marker (CSF or amyloid imaging biomarkers) were eligible and reclassified in this study, and we calculated the associations of diagnostic (CSF and amyloid PET) and progression markers (MRI and fluorodeoxyglucose-PET) with AD severity and progression respectively. RESULTS: The majority (84.2% ) of ADNI AD group (n = 117) and 173 MCI (37.4% ) subjects in ADNI met the definition of typical AD; and 105 cognitively normal (41.0% ) individuals were diagnosed as asymptomatic AD. Furthermore, diagnostic and progression markers showed significant differences when correlated to AD severity and progression. CONCLUSION: A large proportion of AD dementia subjects were categorized as typical AD, and the revised criteria could identify typical AD from MCI status as well as asymptomatic AD at the asymptomatic stage. Moreover, the significant differences between diagnostic and progression markers further supported the new biomarkers categorization in the refined criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognitive Dysfunction; Databases, Factual; Disease Progression; Female; Humans; Longitudinal Studies; Male; Multicenter Studies as Topic; Neuroimaging; Psychiatric Status Rating Scales; tau Proteins

Association between Antipsychotic Drugs and Mortality in Older Persons with Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Zhai, Yaoming; Yin, Song; Zhang, Dongfeng (J Alzheimers Dis, 2016)
Antipsychotic drugs have been inconsistently associated with death risk of Alzheimer's disease (AD) patients. Herein we review and quantitatively summarize the evidence from epidemiological studies. Pertinent studies were identified by searching PubMed and Cochrane Library Register of Controlled Trials through 20 December 2015. The DerSimonian and Laird random effect model was adopted as the pooling method. Twelve studies from nine articles with 11,463 participants were included. The pooled RR of observational studies was 1.36 (95% CI, 0.83-2.24; I2 = 94.9%) for antipsychotic drugs users versus individuals who were not exposed to antipsychotic drugs. When the three studies that were key contributors to the high heterogeneity were excluded, the pooled RR was 2.08 (95% CI 1.39 to 3.13). The result of one double-blind randomized clinical trial indicated that antipsychotic drugs nearly doubled the risk of death in AD patients. In conclusion, there is no evidence of absence of association between antipsychotic drugs' use with death risk of AD patients. Careful assessments of potential benefits and risks should be made before prescribing antipsychotics for treatment of psychosis symptoms and behavioral problems of AD patients.

The Association Between Retinal Neuronal Layer and Brain Structure is Disrupted in Patients with Cognitive Impairment and Alzheimer's Disease. - Liu, Siwei; Ong, Yi-Ting; Hilal, Saima; Loke, Yng Miin; Wong, Tien Y; Chen, Christopher Li-Hsian; Cheung, Carol Y; Zhou, Juan (J Alzheimers Dis, 2016)
Both healthy and pathological aging due to Alzheimer's disease (AD) are associated with decreased brain grey matter volume (GMV) and disrupted white matter (WM) microstructure. Thinner macular ganglion cell-inner plexiform layer (GC-IPL) measured by spectral-domain optical coherence tomography has been reported in patients with AD and mild cognitive impairment. Emerging evidence suggested a link between thinner GC-IPL and lower GMV in subjects with no dementia using region-of-interest-based approach. However, it remains unknown whether GC-IPL thickness is associated with brain WM microstructure and how such association differed between normal and cognitively impaired subjects. Here, for subjects with no cognitive impairment (NCI), thinner GC-IPL was associated with lower WM microstructure integrity in the superior longitudinal fasciculus, inferior fronto-occipital fasciculus, corticospinal tracts, anterior thalamic radiation, and cingulum regions, while it was weakly associated with lower GMV in visual cortex and cerebellum. Nevertheless, these retina-brain associations were disrupted in the presence of cognitive impairment. Correlations between GMV and GC-IPL were lost in patients with cognitive impairment but no dementia (CIND) and AD patients. GC-IPL was related to WM microstructural disruption in similar regions with decreased significance. In contrast, lower WM microstructure integrity in the fornix showed a trend of correlation with thinner GC-IPL in both CIND and AD but not NCI. Collectively, our findings suggest the possible physiological retina-brain relationship in healthy aging, which might be disrupted by disease-induced changes in patients with cognitive impairment. Longitudinal study with larger patient sample should follow to confirm the disease mechanism behind these retina-brain relationship changes.

Association of Frontotemporal Dementia GWAS Loci with Late-Onset Alzheimer's Disease in a Northern Han Chinese Population. - Tan, Chen-Chen; Wan, Yu; Tan, Meng-Shan; Zhang, Wei; Wang, Zi-Xuan; Sun, Fu-Rong; Miao, Dan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Both Alzheimer's disease (AD) and frontotemporal dementia (FTD) are a class of neurodegenerative diseases. Strong similarities in cerebrospinal fluid biomarker, imaging markers, and disease progression profiles suggest that some or most of the pathophysiology is shared between AD and FTD. A recent large genome-wide association study reported several single nucleotide polymorphisms (SNPs) at the RAB38, RAB38/CTSC, HLA-DRA/HLA-DRB5, and BTNL2 in association with FTD. OBJECTIVE: To explore whether these SNPs are associated with AD risk. METHODS: We conducted a case-control study to investigate the association of FTD-associated loci in 2338 Han Chinese subjects. RESULTS: We observed significant differences in genotype distributions of rs302668 (pc = 0.025), rs9268877 (pc = 0.025), rs9268856 (p <  0.001), and rs1980493 (pc = 0.045) between cases and controls. The SNPs rs16913634 for RAB38/CTSC was unrelated to LOAD risk (p = 0.088). CONCLUSION: The SNPs rs302668 in RAB38, rs9268877 and rs9268856 polymorphism in HLA-DRA/HLA-DRB5, and rs1980493 polymorphism in BTNL2 might play a role in the susceptibility to late-onset AD in the Han Chinese population.
Keywords: Age of Onset; Aged; Alzheimer Disease; Apolipoprotein E4; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Genotyping Techniques; Humans; Linkage Disequilibrium; Male; Mental Status Schedule; Polymorphism, Single Nucleotide

The Associations between a Capsaicin-Rich Diet and Blood Amyloid-β Levels and Cognitive Function. - Liu, Cheng-Hui; Bu, Xian-Le; Wang, Jun; Zhang, Tao; Xiang, Yang; Shen, Lin-Lin; Wang, Qing-Hua; Deng, Bo; Wang, Xin; Zhu, Chi; Yao, Xiu-Qing; Zhang, Meng; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Capsaicin-rich diets are common worldwide. Capsaicin has been shown to have favorable effects on various diseases including atherosclerosis, cardiovascular diseases, stroke, obesity, hypertension, cancer, and gastrointestinal and inflammatory diseases. The impact of capsaicin on Alzheimer's disease (AD), which is the most common form of dementia in the elderly, remains unknown. OBJECTIVE: To investigate the correlations of capsaicin intake with cognition and blood markers of AD. METHODS: A total of 338 participants aged 40 years or older were enrolled from communities. Dietary habits regarding chili pepper consumption were collected using a Food Frequency Questionnaire (FFQ). Cognitive function was measured using the Chinese version of the Mini-Mental State Examination (MMSE). Blood amyloid-β (Aβ)40 and Aβ42 were measured with ELISA kits. RESULTS: In univariate analysis, MMSE scores (r = 0.209, p < 0.001), serum Aβ40 levels (r = -0.149, p = 0.006), the ratio of Aβ42/Aβ40 (r = 0.11, p = 0.043) and total serum Aβ levels (r = -0.097, p = 0.075), but not serum Aβ42 levels (r = 0.17, p = 0.757), were significantly correlated with total capsaicin diet scores. In multivariate analysis, total capsaicin diet scores were positively associated with MMSE scores and inversely associated with serum Aβ40 levels, and total serum Aβ levels, but not serum Aβ42 levels and the ratio of Aβ42/Aβ40, after adjustment for age, gender, educational level, smoking history, alcohol consumption, body mass index (BMI) and comorbidities. CONCLUSION: These findings suggest that a capsaicin-rich diet may exert favorable effects on AD blood biomarkers and cognitive function in middle-aged and elderly adults.

Associations between Performance on an Abbreviated CogState Battery, Other Measures of Cognitive Function, and Biomarkers in People at Risk for Alzheimer's Disease. - Racine, Annie M; Clark, Lindsay R; Berman, Sara E; Koscik, Rebecca L; Mueller, Kimberly D; Norton, Derek; Nicholas, Christopher R; Blennow, Kaj; Zetterberg, Henrik; Jedynak, Bruno; Bilgel, Murat; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2016)
It is not known whether computerized cognitive assessments, like the CogState battery, are sensitive to preclinical cognitive changes or pathology in people at risk for Alzheimer's disease(AD). In 469 late middle-aged participants from the Wisconsin Registry for Alzheimer's Prevention(mean age 63.8±7 years at testing; 67% female; 39% APOE4+), we examined relationships between a CogState abbreviated battery(CAB) of seven tests and demographic characteristics, traditional paper-based neuropsychological tests as well as a composite cognitive impairment index, cognitive impairment status(determined by consensus review), and biomarkers for amyloid and tau(CSF phosphorylated-tau/Aβ42 and global PET-PiB burden) and neural injury(CSF neurofilament light protein). CSF and PET-PiB were collected in n = 71 and n = 91 participants, respectively, approximately four years prior to CAB testing. For comparison, we examined three traditional tests of delayed memory in parallel. Similar to studies in older samples, the CAB was less influenced by demographic factors than traditional tests. CAB tests were generally correlated with most paper-based cognitive tests examined and mapped onto the same cognitive domains. Greater composite cognitive impairment index was associated with worse performance on all CAB tests. Cognitively impaired participants performed significantly worse compared to normal controls on all but one CAB test. Poorer One Card Learning test performance was associated with higher levels of CSF phosphorylated-tau/Aβ42. These results support the use of the CogState battery as measures of early cognitive impairment in studies of people at risk for AD.

Astrocytic GluN2A and GluN2B Oppose the Synaptotoxic Effects of Amyloid-β1-40 in Hippocampal Cells. - Li, Yan; Chang, Lirong; Song, Yizhi; Gao, Xianghong; Roselli, Francesco; Liu, Jinping; Zhou, Wei; Fang, Yuan; Ling, Wei; Li, Hui; Almeida, Osborne F X; Wu, Yan (J Alzheimers Dis, 2016)
Early-stage Alzheimer's disease (AD) is characterized by synaptic dysfunction, a phenomenon in which soluble oligomers of amyloid-beta (Aβ) and N-methyl-D-aspartate receptor (NMDAR) are implicated. Here, we demonstrated that astrocytes express NMDARs and therefore have the potential to modulate the synaptotoxic actions of Aβ. We found that specific pharmacological antagonism of two of the major NMDAR subunits, GluN2A and GluN2B, exacerbates Aβ-induced synaptotoxicity suggesting, for the first time, that astrocytic GluN2A and GluN2B mediate synaptoprotection. From the perspective of the pathogenic mechanisms of Alzheimer's disease, in which Aβ and NMDAR play significant roles, these observations are striking since neuronal GluN2A and GluN2B are well known modulators of neurodegeneration. We did initial studies to understand the basis for the differential effects of astrocytic and neuronal GluN2A and GluN2B in the promotion of synapse survival, and identified a neurotrophin produced by astrocytes, nerve growth factor β (β-NGF), as a likely mediator of the synaptoprotective effects of astrocytic GluN2A and GluN2B activation. The results presented suggest that astrocytes may be suitable druggable targets for the prevention and/or delay of the synaptic loss that occurs during early stages of AD.

Biofunctionalized Silica Nanoparticles: Standards in Amyloid-β Oligomer-Based Diagnosis of Alzheimer's Disease. - Hülsemann, Maren; Zafiu, Christian; Kühbach, Katja; Lühmann, Nicole; Herrmann, Yvonne; Peters, Luriano; Linnartz, Christina; Willbold, Johannes; Kravchenko, Kateryna; Kulawik, Andreas; Willbold, Sabine; Bannach, Oliver; et al. (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) oligomers represent a promising biomarker for the early diagnosis of Alzheimer's disease (AD). However, state-of-the-art methods for immunodetection of Aβ oligomers in body fluids show a large variability and lack a reliable and stable standard that enables the reproducible quantitation of Aβ oligomers. At present, the only available standard applied in these assays is based on a random aggregation process of synthetic Aβ and has neither a defined size nor a known number of epitopes. In this report, we generated a highly stable standard in the size range of native Aβ oligomers that exposes a defined number of epitopes. The standard consists of a silica nanoparticle (SiNaP), which is functionalized with Aβ peptides on its surface (Aβ-SiNaP). The different steps of Aβ-SiNaP synthesis were followed by microscopic, spectroscopic and biochemical analyses. To investigate the performance of Aβ-SiNaPs as an appropriate standard in Aβ oligomer immunodetection, Aβ-SiNaPs were diluted in cerebrospinal fluid and quantified down to a concentration of 10 fM in the sFIDA (surface-based fluorescence intensity distribution analysis) assay. This detection limit corresponds to an Aβ concentration of 1.9 ng l-1 and lies in the sensitivity range of currently applied diagnostic tools based on Aβ oligomer quantitation. Thus, we developed a highly stable and well-characterized standard for the application in Aβ oligomer immunodetection assays that finally allows the reproducible quantitation of Aβ oligomers down to single molecule level and provides a fundamental improvement for the worldwide standardization process of diagnostic methods in AD research.

Bridging Integrator 1 (BIN1) Genotypes Mediate Alzheimer's Disease Risk by Altering Neuronal Degeneration. - Wang, Hui-Fu; Wan, Yu; Hao, Xiao-Ke; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Tan, Lin; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Bridging integrator 1 (BIN1) has been identified as one of the most associated loci for Alzheimer's disease (AD), and recently was reported to modulate tau pathology to mediate AD in vitro. However, the effects of BIN1 on the AD related biomarkers in AD continuum were not specifically assessed. OBJECTIVE: We explored the effects of BIN1 loci on AD specific biomarkers (CSF proteins, brain structures, glucose and amyloid-β (Aβ) metabolisms) to investigate the role BIN1 in AD pathogenesis. METHODS: We calculated the associations of BIN1 loci with these markers at baseline and follow-up in multiple linear models in 812 ADNI subjects. RESULTS: BIN1 loci were significantly associated with the levels of T-tau (rs744373: pc = 0.047, rs13031703: pc = 0.042) and P-tau (rs744373: pc = 0.044, rs13031703: pc = 0.019), but not with Aβ in CSF test. BIN1 genotypes were strongly related to atrophy of hippocampus (rs7561528: pc = 0.011), CA1 (rs1469980: pc = 0.029) and parahippocampus (rs72838284, pc = 0.017) on MRI, and to glucose metabolism on FDG-PET, but not to Aβ deposition on AV45-PET imaging. Furthermore, haplotype and subgroup analysis confirmed these significant findings. In addition, the loci associated with these markers were also identified to influence the risk for AD in the meta-analysis of 74 046 European individuals. CONCLUSION: This study supported that BIN1 contributes to the risk of AD by altering neural degeneration (abnormal tau, brain atrophy and glucose metabolism) but not Aβ pathology.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Databases, Factual; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Glucose; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Degeneration; Nuclear Proteins; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Risk; tau Proteins; Tumor Suppressor Proteins

Cerebrospinal Fluid Fatty Acid-Binding Protein 3 is Related to Dementia Development in a Population-Based Sample of Older Adult Women Followed for 8 Years. - Bjerke, Maria; Kern, Silke; Blennow, Kaj; Zetterberg, Henrik; Waern, Margda; Börjesson-Hanson, Anne; Östling, Svante; Kern, Jürgen; Skoog, Ingmar (J Alzheimers Dis, 2016)
BACKGROUND: Increased fatty acid-binding protein 3 (FABP-3) levels have been reported in neurodegenerative diseases, including Alzheimer's disease (AD). Cerebrospinal fluid (CSF) FABP-3 has therefore been proposed as a putative marker for dementia. Population-based studies examining whether CSF FABP-3 predicts later development of dementia are lacking. OBJECTIVE: The aim of this study was to examine CSF levels of FABP-3 in relation to later development of dementia in elderly women and in relation to Aβ42, T-tau, P-tau181, and CSF: serum albumin ratio. METHODS: 86 non-demented women aged 70-84 years who participated in the Prospective Population Study of Women in Gothenburg, Sweden took part in a lumbar puncture in 1992-93. CSF-FABP-3, Aβ42, T-tau, P-tau181, and the CSF: serum albumin ratio were measured at baseline. Participants were examined with a neuropsychiatric exam at baseline and at follow-up in 2000. Dementia was diagnosed in accordance with DSM-III-R criteria. RESULTS: Between 1992 and 2000, 8 women developed dementia (4 AD, 3 vascular dementia, 1 mixed vascular dementia and AD). Higher levels of CSF-FABP-3 at baseline were related to development of dementia (OR 1.36 CI [1.05-1.76] p = 0.022) and the subtype AD (OR 1.38 CI [1.06-1.82), p = 0.019) during follow-up. FABP-3 correlated with CSF T-tau (r = 0.88, p <  0.001), P-tau181 (r = 0.619, p <  0.001), and CSF:serum albumin ratio (r = 0.233, p = 0.031), but not with Aβ42 (r = -0.08, p = 0.444)CONCLUSION:CSF FABP-3 may be an early marker for later development of dementia, probably related to neuronal degeneration, but independent of Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Albumins; Amyloid beta-Peptides; Community Health Planning; Dementia; Fatty Acid-Binding Proteins; Female; Humans; Longitudinal Studies; Peptide Fragments; Sweden; tau Proteins

Cerebrospinal Fluid Markers of Alzheimer's Disease Pathology and Microglial Activation are Associated with Altered White Matter Microstructure in Asymptomatic Adults at Risk for Alzheimer's Disease. - Melah, Kelsey E; Lu, Sharon Yuan-Fu; Hoscheidt, Siobhan M; Alexander, Andrew L; Adluru, Nagesh; Destiche, Daniel J; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Okonkwo, Ozioma C; Gleason, Carey E; Dowling, N Maritza; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The immune response in Alzheimer's disease (AD) involves activation of microglia which may remove amyloid-β (Aβ). However, overproduction of inflammatory compounds may exacerbate neural damage in AD. AD pathology accumulates years before diagnosis, yet the extent to which neuroinflammation is involved in the earliest disease stages is unknown. OBJECTIVE: To determine whether neuroinflammation exacerbates neural damage in preclinical AD. METHODS: We utilized cerebrospinal fluid (CSF) and magnetic resonance imaging collected in 192 asymptomatic late-middle-aged adults (mean age = 60.98 years). Neuroinflammatory markers chitinase-3-like protein 1 (YKL-40) and monocyte chemoattractant protein-1 (MCP-1) in CSF were utilized as markers of neuroinflammation. Neural cell damage was assessed using CSF neurofilament light chain protein (NFL), CSF total tau (T-Tau), and neural microstructure assessed with diffusion tensor imaging (DTI). With regard to AD pathology, CSF Aβ42 and tau phosphorylated at threonine 181 (P-Tau181) were used as markers of amyloid and tau pathology, respectively. We hypothesized that higher YKL-40 and MCP-1 in the presence of AD pathology would be associated with higher NFL, T-Tau, and altered microstructure on DTI. RESULTS: Neuroinflammation was associated with markers of neural damage. Higher CSF YKL-40 was associated with both higher CSF NFL and T-Tau. Inflammation interacted with AD pathology, such that greater MCP-1 and lower Aβ42 was associated with altered microstructure in bilateral frontal and right temporal lobe and that greater MCP-1 and greater P-Tau181 was associated with altered microstructure in precuneus. CONCLUSION: Inflammation may play a role in neural damage in preclinical AD.
Keywords: Adipokines; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chemokine CCL2; Chitinase-3-Like Protein 1; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Lectins; Male; Microglia; Middle Aged; Peptide Fragments; tau Proteins; White Matter

Characterization of Amyloid-β Deposits in Bovine Brains. - Vallino Costassa, Elena; Fiorini, Michele; Zanusso, Gianluigi; Peletto, Simone; Acutis, Pierluigi; Baioni, Elisa; Maurella, Cristiana; Tagliavini, Fabrizio; Catania, Marcella; Gallo, Marina; Faro, Monica Lo; Chieppa, Maria Novella; et al. (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) deposits are seen in aged individuals of many mammalian species that possess the same aminoacid sequence as humans. This study describes Aβ deposition in 102 clinically characterized cattle brains from animals aged 0 to 20 years. Extracellular and intracellular Aβ deposition was detected with 4G8 antibody in the cortex, hippocampus, and cerebellum. X-34 staining failed to stain Aβ deposits, indicating the non β-pleated nature of these deposits. Western blot analysis and surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF) mass spectrometry revealed in Tris, Triton, and formic acid fractions the presence of different Aβ peptides, characterized mainly by C-terminally truncated forms. Exploration of the genetic variability of APOE, PSEN1, and PSEN2 genes involved in Alzheimer's disease pathogenesis revealed several previously unreported polymorphisms. This study demonstrates certain similarities between Aβ deposition patterns exhibited in cattle brains and those in the human brain in early stages of aging. Furthermore, the identification of the same Aβ peptides reported in humans, but unable to form aggregates, supports the hypothesis that cattle may be protected against amyloid plaque formation.
Keywords: Aging; Amyloid beta-Peptides; Animals; Apolipoproteins E; Blotting, Western; Brain; Cattle; Extracellular Space; Gene Frequency; Genotyping Techniques; Glial Fibrillary Acidic Protein; Immunohistochemistry; Intracellular Space; Neuroglia; Neurons; Polymorphism, Genetic; Presenilin-1; Presenilin-2; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization

CHRNA7 Gene and Response to Cholinesterase Inhibitors in an Italian Cohort of Alzheimer's Disease Patients. - Clarelli, Ferdinando; Mascia, Elisabetta; Santangelo, Roberto; Mazzeo, Salvatore; Giacalone, Giacomo; Galimberti, Daniela; Fusco, Federica; Zuffi, Marta; Fenoglio, Chiara; Franceschi, Massimo; Scarpini, Elio; Forloni, Gianluigi; et al. (J Alzheimers Dis, 2016)
Previous studies suggest that genetic variants in CHRNA7, which encodes for the major subunit of the acetylcholine receptor (α7-nAChR), are associated with the clinical response to cholinesterase inhibitors (ChEI) in Alzheimer's disease (AD) patients. We sought to replicate the association of two SNPs in the CHRNA7 gene, rs6494223 and rs8024987, with response to ChEI treatment in an Italian cohort of 169 AD patients, further extending the study to gene-level analysis. None of the tested variants was associated with clinical response. However, rs6494223 showed a consistent effect direction (OR = 1.4; p = 0.17), which after meta-analysis with previous study yielded a significant result (OR = 1.57, p = 0.02, I2 = 0%).

Chronic Cerebral Hypoperfusion Accelerates Alzheimer's Disease Pathology with Cerebrovascular Remodeling in a Novel Mouse Model. - Zhai, Yun; Yamashita, Toru; Nakano, Yumiko; Sun, Zhuoran; Shang, Jingwei; Feng, Tian; Morihara, Ryuta; Fukui, Yusuke; Ohta, Yasuyuki; Hishikawa, Nozomi; Abe, Koji (J Alzheimers Dis, 2016)
Recently, aging societies have been showing an increasingly strong relationship between Alzheimer's disease (AD) and chronic cerebral hypoperfusion (HP). In the present study, we created a new mouse model for AD with HP, and investigated its clinical and pathological characteristics. Alzheimer's disease transgenic mice (APP23) were subjected to bilateral common carotid arteries stenosis with ameroid constrictors for slowly progressive cerebral HP. In contrast to simple APP23 mice, cerebral HP exacerbated motor and cognitive dysfunctions with white matter lesions and meningo-parenchymal amyloid-β (Aβ) burdens. Strong cerebrovascular inflammation and severe amyloid angiopathy with cerebrovascular remodeling were also observed in APP23 + HP mouse brains. An acetylcholinesterase inhibitor galantamine improved such clinical dysfunctions, retrieved above neuropathological characteristics, and enhanced nicotinic acetylcholine receptor (nAChR)-binding activity. The present study demonstrates that chronic cerebral HP enhanced cognitive/motor dysfunctions with parenchymal/cerebrovascular Aβ accumulation and cerebrovascular remodeling. These neuropathological abnormalities were greatly ameliorated by galantamine treatment associated with nAChR-mediated neuroprotection by allosterically potentiating ligand action.

Chronic Obstructive Pulmonary Disease as a Risk Factor for Cognitive Dysfunction: A Meta-Analysis of Current Studies. - Zhang, Ximeng; Cai, Xiaoying; Shi, Xiaolei; Zheng, Zhenyang; Zhang, Aiwu; Guo, Junliang; Fang, Yannan (J Alzheimers Dis, 2016)
Cognitive dysfunction has been shown to be associated with many risk factors, such as smoking, diabetes, and body mass index. Chronic obstructive pulmonary disease (COPD), a common disease within the elderly population, has also been found to be related to cognitive decline. However, whether COPD is a risk factor of cognitive dysfunction is not well established. The purpose of this meta-analysis is to investigate the role COPD plays in cognitive dysfunction. PubMed, Cochrane library and Web of Science databases were searched. Three cohort studies and eleven cross-sectional studies were found to be eligible. According to our results, COPD patients had a higher risk of cognitive dysfunction than controls (OR [odds ratio]: 1.72; 95% CI, 1.12-2.65; p = 0.01). The exacerbation of COPD was strongly correlated with cognitive decline. COPD patients performed worse than controls on the Mini- Mental State Examination test, but the results were not statistically significant (OR: -0.79; 95% CI, [-1.78, 0.19]; p = 0.11). Thus, more attention should be given to the occurrence of cognitive decline in COPD patients. The prevention and control of COPD exacerbation are critical.
Keywords: Cognitive Dysfunction; Humans; Pulmonary Disease, Chronic Obstructive; Risk Factors

Chronic Sleep Deprivation Exacerbates Learning-Memory Disability and Alzheimer's Disease-Like Pathologies in AβPP(swe)/PS1(ΔE9) Mice. - Qiu, Hongyan; Zhong, Rujia; Liu, Hui; Zhang, Feng; Li, Song; Le, Weidong (J Alzheimers Dis, 2016)
Recently, there is an increasing concern over the association between sleep disorders and Alzheimer's disease (AD). Clinical observations have reported that chronic sleep deprivation (SD) may serve as a risk factor for AD. However, the pathological evidence for this assumption is still lacking. In the present study, we examined the potential impacts of chronic SD on learning-memory and AD-related pathologies in AβPP(swe)/PS1(ΔE9) transgenic (TG) mice and their wild-type (WT) littermates. Results indicated that mice (both TG and WT) exposed to 2-month SD showed an altered amyloid-β protein precursor processing, an elevated level of phosphorylated tau protein, and impaired cognitive performance as compared to non-sleep deprivation (NSD) controls. Moreover, the SD-treated TG mice exhibited more amyloid-β(1-42) production and developed more senile plaques in the cortex and hippocampus than NSD-treated TG mice. In addition, SD caused a striking neuronal mitochondrial damage, caspase cascade activation, and neuronal apoptosis in the hippocampus of both TG and WT mice. More importantly, all these behavioral, neuropathological, and biochemical changes induced by chronic SD were long lasting and were irreversible during a 3-month normal housing condition. Collectively, these results indicate that chronic SD impairs learning and memory, exacerbates AD pathologies, and aggravates the mitochondria-mediated neuronal apoptosis in a long-lasting manner. Our findings provide important experimental evidence to prove that chronic SD is a risk factor for AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apoptosis; Brain; Cognition Disorders; Disease Models, Animal; Humans; In Situ Nick-End Labeling; Learning Disorders; Mice; Mice, Transgenic; Mitochondrial Diseases; Mutation; Phosphorylation; Plaque, Amyloid; Presenilin-1; Reversal Learning; Sleep Deprivation; tau Proteins

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Cycloheximide Treatment Causes a ZVAD-Sensitive Protease-Dependent Cleavage of Human Tau in Drosophila Cells. - Geng, Junhua; Xia, Lu; Li, Wanjie; Zhao, Changqi; Dou, Fei (J Alzheimers Dis, 2016)
Neurofibrillary tangles are the main pathological feature of Alzheimer's disease. Insoluble tau protein is the major component of neurofibrillary tangles. Defects in the tau protein degradation pathway in neurons can lead to the accumulation of tau and its subsequent aggregation. Currently, contradictory results on the tau degradation pathway have been reported by different groups. This discrepancy is most likely due to different cell lines and methods used in those studies. In this study, we found that cycloheximide treatment induced mild activation of a ZVAD-sensitive protease in Drosophila Kc cells, resulting in cleavage of tau at its C-terminus; this cleavage could generate misleading tau protein degradation pattern results depending on the antibodies used in the assay. Because cycloheximide is a broadly used chemical reagent for the study of protein degradation, the unexpected artificial effect we observed here indicates that cycloheximide is not suitable for the study of tau degradation. Other methods, such as inducible expression systems and pulse-chase assays, may be more appropriate for studying tau degradation under physiological conditions.
Keywords: Animals; Apoptosis; Caspase 3; Cell Line; Cycloheximide; Drosophila; Drosophila Proteins; Drug Evaluation, Preclinical; Humans; Oligopeptides; Peptide Hydrolases; Protease Inhibitors; Protein Synthesis Inhibitors; tau Proteins; Time

Decreased Inter-Hemispheric Functional Connectivity in Cognitively Intact Elderly APOE ɛ4 Carriers: A Preliminary Study. - Luo, Xiao; Qiu, Tiantian; Xu, Xiaojun; Huang, Peiyu; Gu, Quanquan; Shen, Zhujing; Yu, Xinfeng; Jia, YunLu; Guan, Xiaojun; Song, Ruirui; Zhang, Minming (J Alzheimers Dis, 2016)
The apolipoprotein E (APOE) ɛ4 allele is the best-known genetic risk factor for developing sporadic Alzheimer's disease (AD). According to neuroimaging studies, the APOE ɛ4 allele is associated with localized altered brain function. However, in long-range circuitry, APOE ɛ4 allele-related alterations in functional communication between hemispheres have rarely been directly investigated. We examined the alteration of resting-state functional connectivity (RSFC) between inter-hemispheric homotopic regions in cognitively intact, elderly APOE ɛ4 carriers. The voxel-mirrored homotopic connectivity method was used to assess the inter-hemispheric RSFC. The current study included 13 cognitively intact, elderly APOE ɛ4 carriers (with at least one copy of APOE ɛ4 allele) and 22 well-matched ɛ3 homozygotes. Comparisons between the two groups were conducted, and subsequently, the correlation between the differential inter-hemispheric RSFC and cognitive ability was analyzed. Compared with ɛ3 homozygotes, APOE ɛ4 carriers showed decreased inter-hemispheric RSFC in the bilateral medial temporal lobe (MTL) and orbital frontal cortex (OFC). Moreover, in APOE ɛ4 carriers, the inter-hemispheric RSFC of the MTL correlated with the Wechsler Memory Scale-Logical Memory (WMS-LM) (immediate and delayed performance, r = 0.64, p <  0.05; r = 0.65, p <  0.05, respectively), and the inter-hemispheric RSFC of the OFC correlated with the WMS-LM delayed performance (r = 0.71, p <  0.05). In our study, the presence of the APOE ɛ4 allele was linked with decreased inter-hemispheric RSFC, which was attributed to memory performance in carriers.
Keywords: Aged; Aging; Apolipoprotein E4; Brain; Brain Mapping; Female; Functional Laterality; Genotyping Techniques; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Memory; Neuropsychological Tests; Rest

Dementia Risk and Protective Factors Differ in the Context of Memory Trajectory Groups. - Zahodne, Laura B; Schupf, Nicole; Brickman, Adam M; Mayeux, Richard; Wall, Melanie M; Stern, Yaakov; Manly, Jennifer J (J Alzheimers Dis, 2016)
BACKGROUND: Previous research has identified multiple risk and protective factors for late onset Alzheimer's disease (LOAD). However, it is not known whether these risk and protective factors differ for individuals who are cognitively stable versus those already experiencing declines. OBJECTIVE: This study examined how dementia risk factors differ across subgroups of older adults defined by memory trajectory. This line of research may lead to more individualized risk profiles. METHODS: Risk factors for incident LOAD were compared across previously-validated groups of older adults exhibiting different memory trajectories ("Stable-High," "Stable-Low," "Decliner," "Rapid Decliner") using stratified Cox regressions. Participants included 2,593 racially/ethnically diverse older adults (mean age of 76 at study entry) in the Washington Heights-Inwood Columbia Aging Project. RESULTS: Predictors of incident dementia differed across trajectory groups: older age only incurred independent risk in stable groups, education did not incur independent protection in the rapidly declining group, depression only incurred independent risk in the stable-low group, stroke incurred independent risk in the two extreme groups, and APOE-ɛ4 only incurred independent risk in the rapidly declining group. CONCLUSION: The finding that different risk factors for LOAD were associated with specific memory trajectories may reflect the existence of resilience or vulnerability factors that modify the individual influences of risk/protective factors. This study highlights the utility of considering interactions between dementia risk factors and a patient's unique cognitive history.

Detection of Alzheimer's Disease by Three-Dimensional Displacement Field Estimation in Structural Magnetic Resonance Imaging. - Wang, Shuihua; Zhang, Yudong; Liu, Ge; Phillips, Preetha; Yuan, Ti-Fei (J Alzheimers Dis, 2016)
BACKGROUND: Within the past decade, computer scientists have developed many methods using computer vision and machine learning techniques to detect Alzheimer's disease (AD) in its early stages. OBJECTIVE: However, some of these methods are unable to achieve excellent detection accuracy, and several other methods are unable to locate AD-related regions. Hence, our goal was to develop a novel AD brain detection method. METHODS: In this study, our method was based on the three-dimensional (3D) displacement-field (DF) estimation between subjects in the healthy elder control group and AD group. The 3D-DF was treated with AD-related features. The three feature selection measures were used in the Bhattacharyya distance, Student's t-test, and Welch's t-test (WTT). Two non-parallel support vector machines, i.e., generalized eigenvalue proximal support vector machine and twin support vector machine (TSVM), were then used for classification. A 50 × 10-fold cross validation was implemented for statistical analysis. RESULTS: The results showed that "3D-DF+WTT+TSVM" achieved the best performance, with an accuracy of 93.05 ± 2.18, a sensitivity of 92.57 ± 3.80, a specificity of 93.18 ± 3.35, and a precision of 79.51 ± 2.86. This method also exceled in 13 state-of-the-art approaches. Additionally, we were able to detect 17 regions related to AD by using the pure computer-vision technique. These regions include sub-gyral, inferior parietal lobule, precuneus, angular gyrus, lingual gyrus, supramarginal gyrus, postcentral gyrus, third ventricle, superior parietal lobule, thalamus, middle temporal gyrus, precentral gyrus, superior temporal gyrus, superior occipital gyrus, cingulate gyrus, culmen, and insula. These regions were reported in recent publications. CONCLUSIONS: The 3D-DF is effective in AD subject and related region detection.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Brain Mapping; Datasets as Topic; Female; Humans; Imaging, Three-Dimensional; Machine Learning; Magnetic Resonance Imaging; Male

Detection of Striatal Amyloid Plaques with [18F]flutemetamol: Validation with Postmortem Histopathology. - Beach, Thomas G; Thal, Dietmar Rudolf; Zanette, Michelle; Smith, Adrian; Buckley, Christopher (J Alzheimers Dis, 2016)
Amyloid imaging is limited by an inconsistent relationship between cerebral cortex amyloid- β (Aβ) plaques and dementia. Autopsy studies suggest that Aβ plaques first appear in the cerebral cortex while subcortical plaques are present only later in the disease course. The presence of abundant plaques in both cortex and striatum is more strongly correlated with the presence of dementia than cortical Aβ plaques alone. Additionally, detection of striatal plaques may allow, for the first time, pathology-based clinical staging of AD. Striatal plaques are reportedly identifiable by amyloid imaging but the accuracy and reliability of striatal amyloid imaging has never been tested against postmortem histopathology. To determine this, we correlated the presence of histopathologically-demonstrated striatal Aβ deposits with a visually positive panel consensus decision of a positive [18F]flutemetamol striatal PET signal in 68 subjects that later came to autopsy. The sensitivity of [18F]flutemetamol PET striatal amyloid imaging, for several defined density levels of histological striatal Aβ deposits, ranged between 69% and 87% while the specificity ranged between 96% and 100%. Sensitivity increased with higher histological density thresholds while the reverse was found for specificity. In general, as compared with PET alone, PET with CT had slightly higher sensitivities but slightly lower specificities. In conclusion, amyloid imaging of the striatum with [18F]flutemetamol PET has reasonable accuracy for the detection of histologically-demonstrated striatal Aβ plaques when present at moderate or frequent densities. Amyloid imaging of the cerebral cortex and striatum together may allow for a more accurate clinicopathological diagnosis of AD and enable pathology-based clinical staging of AD.

Diagnosing Dementia in the Clinical Setting: Can Amyloid PET Provide Additional Value Over Cerebrospinal Fluid? - Weston, Philip S J; Paterson, Ross W; Dickson, John; Barnes, Anna; Bomanji, Jamshed B; Kayani, Irfan; Lunn, Michael P; Mummery, Catherine J; Warren, Jason D; Rossor, Martin N; Fox, Nick C; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of amyloid and tau are the first-line Alzheimer's disease biomarkers in many clinical centers. We assessed if and when the addition of amyloid PET following CSF measurements provides added diagnostic value. Twenty patients from a cognitive clinic, who had undergone detailed assessment including CSF measures, went on to have amyloid PET. The treating neurologist's working diagnosis, and degree of diagnostic certainty, was assessed both before and after the PET. Amyloid PET changed the diagnosis in 7/20 cases. Amyloid PET can provide added diagnostic value, particularly in young-onset, atypical dementias, where CSF results are borderline and diagnostic uncertainty remains.

Differential Effects of APOE Genotypes on the Anterior and Posterior Subnetworks of Default Mode Network in Amnestic Mild Cognitive Impairment. - Yuan, Baoyu; Xie, Chunming; Shu, Hao; Liao, Wenxiang; Wang, Zan; Liu, Duan; Zhang, Zhijun (J Alzheimers Dis, 2016)
BACKGROUND: The apolipoprotein E (APOE) ɛ4 carriers are at increased risk of developing Alzheimer's disease (AD) while the ɛ2 carriers appear to be protected against the disease. The default mode network (DMN), based in ventromedial prefrontal cortex (vmPFC) and posterior cingulate cortex (PCC), consists of functionally differentiable anterior and posterior subnetworks. OBJECTIVE: This study was to investigate whether there are differential effects of APOE polymorphisms on DMN subnetworks in amnestic mild cognitive impairment (aMCI). METHODS: Functional connectivity (FC) analyses were performed in DMN subnetworks in 74 aMCI (9 APOE ɛ2ɛ3, 44 ɛ3ɛ3, and 21 ɛ3ɛ4) and 105 healthy controls (HC; 32 APOE ɛ2ɛ3, 39 ɛ3ɛ3, and 34 ɛ3ɛ4). Logistic regression analysis was performed to obtain a model for classifying aMCI and HC. RESULTS: Significant interactions of APOE by aMCI on FCs were found in right cerebellum posterior lobe, left lingual gyrus, and right middle cingulate cortex in the vmPFC subnetwork, and bilateral fusiform gyrus, left inferior frontal gyrus, and left precuneus in the PCC subnetwork. The impairment of episodic memory for ɛ4-carriers in aMCI negatively correlated with altered FC between vmPFC and right middle cingulate cortex, while positively correlated with altered FC between PCC and left fusiform gyrus. A model composed of episodic memory and FCs dexterity correctly classified 89.4% of aMCI and HC. CONCLUSIONS: APOE ɛ4 and ɛ2 alleles differentially mediate anterior and posterior DMN subnetworks. Furthermore, it further suggests that the anterior and posterior DMN subnetworks in aMCI play an opposing role on the impairment of episodic memory.

Differential Regulation of N-Methyl-D-Aspartate Receptor Subunits is an Early Event in the Actions of Soluble Amyloid-β(1-40) Oligomers on Hippocampal Neurons. - Chang, Lirong; Zhang, Yali; Liu, Jinping; Song, Yizhi; Lv, Angchu; Li, Yan; Zhou, Wei; Yan, Zhen; Almeida, Osborne F X; Wu, Yan (J Alzheimers Dis, 2016)
Synaptic dysfunction during early stages of Alzheimer's disease (AD) is triggered by soluble amyloid-β (Aβ) oligomers that interact with NMDA receptors (NMDARs). We previously showed that Aβ induces synaptic protein loss through NMDARs, albeit through undefined mechanisms. Accordingly, we here examined the contribution of individual NMDAR subunits to synaptotoxicity and demonstrate that Aβ exerts differential effects on the levels and distribution of GluN2A and GluN2B subunits of NMDAR in dendrites. Treatment of cultured hippocampal neurons with Aβ1-40 (10 μM, 1 h) induced a significant increase of dendritic and synaptic GluN2B puncta densities with parallel decreases in the puncta densities of denritic and synaptic pTyr1472-GluN2B. Conversely, Aβ significantly decreased dendritic and synaptic GluN2A and dendritic pTyr1325-GluN2A puncta densities and increased synaptic pTyr1325-GluN2A puncta densities. Unexpectedly, Aβ treatment resulted in a significant reduction of GluN2B and pTyr1472-GluN2B protein levels but did not influence GluN2A and pTyr1325-GluN2A levels. These results show that Aβ exerts complex and distinct regulatory effects on the trafficking and phosphorylation of GluN2A and GluN2B, as well as on their localization within synaptic and non-synaptic sites. Increased understanding of these early events in Aβ-induced synaptic dysfunction is likely to be important for the development of timely preventive and therapeutic interventions.
Keywords: Amyloid beta-Peptides; Animals; Animals, Newborn; Cells, Cultured; Dendrites; Gene Expression Regulation; Hippocampus; Male; Neurons; Peptide Fragments; Phosphorylation; Rats; Rats, Wistar; Receptors, N-Methyl-D-Aspartate

Dihydropyridine Derivatives Modulate Heat Shock Responses and have a Neuroprotective Effect in a Transgenic Mouse Model of Alzheimer's Disease. - Kasza, Ágnes; Hunya, Ákos; Frank, Zsuzsa; Fülöp, Ferenc; Török, Zsolt; Balogh, Gábor; Sántha, Miklós; Bálind, Árpád; Bernáth, Sándor; Blundell, Katie L I M; Prodromou, Chrisostomos; Horváth, Ibolya; et al. (J Alzheimers Dis, 2016)
Heat shock proteins (Hsps) have chaperone activity and play a pivotal role in the homeostasis of proteins by preventing misfolding, by clearing aggregated and damaged proteins from cells, and by maintaining proteins in an active state. Alzheimer's disease (AD) is thought to be caused by amyloid-β peptide that triggers tau hyperphosphorylation, which is neurotoxic. Although proteostasis capacity declines with age and facilitates the manifestation of neurodegenerative diseases such as AD, the upregulation of chaperones improves prognosis. Our research goal is to identify potent Hsp co-inducers that enhance protein homeostasis for the treatment of AD, especially 1,4-dihydropyridine derivatives optimized for their ability to modulate cellular stress responses. Based on favorable toxicological data and Hsp co-inducing activity, LA1011 was selected for the in vivo analysis of its neuroprotective effect in the APPxPS1 mouse model of AD. Here, we report that 6 months of LA1011 administration effectively improved the spatial learning and memory functions in wild type mice and eliminated neurodegeneration in double mutant mice. Furthermore, Hsp co-inducer therapy preserves the number of neurons, increases dendritic spine density, and reduces tau pathology and amyloid plaque formation in transgenic AD mice. In conclusion, the Hsp co-inducer LA1011 is neuroprotective and therefore is a potential pharmaceutical candidate for the therapy of neurodegenerative diseases, particularly AD.

Disrupted Brain Network in Progressive Mild Cognitive Impairment Measured by Eigenvector Centrality Mapping is Linked to Cognition and Cerebrospinal Fluid Biomarkers. - Qiu, Tiantian; Luo, Xiao; Shen, Zhujing; Huang, Peiyu; Xu, Xiaojun; Zhou, Jiong; Zhang, Minming (J Alzheimers Dis, 2016)
Mild cognitive impairment (MCI) is a heterogeneous condition associated with a high risk of progressing to Alzheimer's disease (AD). Although functional brain network alterations have been observed in progressive MCI (pMCI), the underlying pathological mechanisms of network alterations remain unclear. In the present study, we evaluated neuropsychological, imaging, and cerebrospinal fluid (CSF) data at baseline across a cohort of: 21 pMCI patients, 33 stable MCI (sMCI) patients, and 29 normal controls. Fast eigenvector centrality mapping (fECM) based on resting-state functional MRI (rsfMRI) was used to investigate brain network organization differences among these groups, and we further assessed its relation to cognition and AD-related pathology. Our results demonstrated that pMCI had decreased eigenvector centrality (EC) in left temporal pole and parahippocampal gyrus, and increased EC in left middle frontal gyrus compared to sMCI. In addition, compared to normal controls, patients with pMCI showed decreased EC in right hippocampus and bilateral parahippocampal gyrus, and sMCI had decreased EC in right middle frontal gyrus and superior parietal lobule. Correlation analysis showed that EC in the left temporal pole was related to Wechsler Memory Scale-Revised Logical Memory (WMS-LM) delay score (r = 0.467, p = 0.044) and total tau (t-tau) level in CSF (r = -0.509, p = 0.026) in pMCI. Our findings implicate EC changes of different brain network nodes in the prognosis of pMCI and sMCI. Importantly, the association between decreased EC of brain network node and pathological changes may provide a deeper understanding of the underlying pathophysiology of pMCI.

Disrupted White Matter Network and Cognitive Decline in Type 2 Diabetes Patients. - Zhang, Junying; Liu, Zhen; Li, Zixiao; Wang, Yunxia; Chen, Yaojing; Li, Xin; Chen, Kewei; Shu, Ni; Zhang, Zhanjun (J Alzheimers Dis, 2016)
Type 2 diabetes mellitus is accompanied by cognitive impairment and is associated with an increased risk of dementia. Damage to brain structures such as white matter network disruption may underlie this cognitive disturbance. In the present study, 886 non-diabetic and 163 type 2 diabetic participants completed a battery of neuropsychological tests. Among them, 38 diabetic patients and 34 non-diabetic participants that matched the patients for age/sex/education received a magnetic resonance imaging-based diffusion tensor imaging. Then we calculated the topological properties of the white matter network using a graph theoretical method to investigate network efficiency differences between groups. We found that type 2 diabetic patients had inferior performances compared to the non-diabetic controls, in several cognitive domains involving executive function, spatial processing, memory, and attention. We also found that diabetic patients exhibited a disrupted topological organization of the white matter network (including the global network properties, i.e., network strength, global efficiency, local efficiency and shortest path length, and the nodal efficiency of the right rolandic operculum) in the brain. Moreover, those global network properties and the nodal efficiency of the right rolandic operculum both had positive correlations with executive function in the patient group. The results suggest that type 2 diabetes mellitus leads to an alteration in the topological organization of the cortical white matter network and this alteration may account for the observed cognitive decline.

Disruption of White Matter Integrity by Chronic Cerebral Hypoperfusion in Alzheimer's Disease Mouse Model. - Zhai, Yun; Yamashita, Toru; Nakano, Yumiko; Sun, Zhuoran; Morihara, Ryuta; Fukui, Yusuke; Ohta, Yasuyuki; Hishikawa, Nozomi; Abe, Koji (J Alzheimers Dis, 2016)
A rapidly progressing aging society has raised attention to white matter lesions in Alzheimer's disease. In the present study, we applied an AD plus cerebral hypoperfusion (HP) mouse model and investigated the alternation of key protein molecules in the nodal, paranodal, and intermodal sites in the white matter as well as the efficacy of galantamine. Cerebral HP was induced in APP23 mice by bilateral common carotid arteries stenosis with ameroid constrictors. Compared with the wild type and simple APP23 mice, APP23 + HP mice showed a progressive loss of MAG and NF186 from 6 to 12 months, broken misdistribution of MBP, and extended relocation of Nav1.6 and AnkG beyond the primary nodal region in the corpus callosum. Such abnormal neuropathological processes were retrieved with galantamine treatment. The present study demonstrated that cerebral HP strongly disrupted white matter integrity (WMI) at intermodal, paranodal, and Ranvier's nodal sites which may be associated with cognitive decline. Galantamine treatment significantly protected such WMI probably by allosterically potentiating ligand action.

Distinct Patterns of Cognitive Aging Modified by Education Level and Gender among Adults with Limited or No Formal Education: A Normative Study of the Mini-Mental State Examination. - Xie, Haiqun; Zhang, Chengguo; Wang, Yukai; Huang, Shuyun; Cui, Wei; Yang, Wenbin; Koski, Lisa; Xu, Xiping; Li, Youbao; Zheng, Meili; He, Mingli; Fu, Jia; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is increasingly prevalent due to rapid aging of the population, but under-recognized among people with low education levels. This is partly due to a lack of appropriate and precise normative data, which underestimates cognitive aging in the use of screening tools for dementia. OBJECTIVE: We aimed to improve the precision of screening for cognitive impairment, by characterizing the patterns of cognitive aging and derived normative data of the Mini-Mental State Examination (MMSE) for illiterate and low-educated populations. METHODS: This community-based study included data from 2,280 individuals aged 40 years or older from two rural areas. Multiple linear modeling examined the effect of aging on cognition reflected by the MMSE, stratified by education level and gender. Threshold effect of age on cognition was performed using a smoothing function. RESULTS: The majority of participants (60.4%) were illiterate or had attended only primary school (24.6%). The effect of aging on cognition varied by gender and education. Primary-school educated females and males remained cognitively stable up to 62 and 71 years of age, respectively, with MMSE score declining 0.4 and 0.8 points/year in females and males thereafter. Illiterates females scored 2.3 points lower than illiterate males, and scores for both declined 0.2 points/year. According to these results, normative data stratified by age, education and gender was generated. CONCLUSION: This study suggests gender and educational differences exist in cognitive aging among adults with limited or no formal education. To improve screening precision for cognitive impairment with the use of MMSE in low-educated population, age, gender, and education level should be considered.
Keywords: Adult; Aged; Aged, 80 and over; China; Cognition Disorders; Cognitive Aging; Educational Status; Female; Humans; Male; Mental Status Schedule; Middle Aged; Reference Values; Rural Population; Sex Characteristics

Do Chinese Researchers Conduct Ethical Research and Use Ethics Committee Review in Clinical Trials of Anti-Dementia Drugs? An Analysis of Biomedical Publications Originating from China. - Zeng, Lingfeng; Liang, Weixiong; Pan, Jianke; Cao, Ye; Liu, Jun; Wang, Qi; Wang, Lu; Zou, Yuanping; Wang, Kezhu; Kong, Lingshuo; Xie, Hui; Xu, Weihua; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Medical research using human participants must conform to the basic ethical principles found in the Declaration of Helsinki (DoH) of the World Medical Association. OBJECTIVE: The purpose of this review was to assess whether journals in China have improved in regard to the fulfillment of ethical disclosure procedures for clinical trials of anti-dementia drugs. METHODS: Four medical databases were searched for articles reporting clinical trials of oral anti-dementia drugs published in China in 2003, 2009, and 2014. The frequencies of reporting of informed consent from participants (ICP), approval of a regional ethical committee (REC), reference to DoH, and study registration were estimated respectively. Statistical analyses were conducted with SPSS v21 software. RESULTS: Among those randomized controlled trials published in 2003, 2009, and 2014, disclosure of REC approval was present for 2.67%, 1.15%, and 6.84%; statements of ICP were included in 9.33%, 7.76%, and 17.34%; reference to DoH was found for 4.00%, 1.44%, and 7.45%; and study registration reporting was included in 2.67%, 2.59%, and 9.28%, respectively. Improvements to reporting rates between 2009 and 2014 were seen, with more than twice as many trials reporting REC approval, ICP, reference to DoH, and study registration compared with 2009. CONCLUSION: Compared with 2003 and 2009, reporting rates for REC approval, ICP, reference to DoH, and study registration for clinical trials of anti-dementia drugs were enhanced in 2014 in the major medical journals of China. However, biomedical publications without definite statements of ethical considerations remain common, and this continues to be seen in Chinese journals. It is imperative that measures are taken to reinforce the ethical protection in clinical trials in China.

Dose-Dependent Neuroprotection and Neurotoxicity of Simvastatin through Reduction of Farnesyl Pyrophosphate in Mice Treated with Intracerebroventricular Injection of Aβ 1-42. - Jin, Huafeng; Chen, Tingting; Li, Guoxi; Wang, Conghui; Zhang, Baofeng; Cao, Xinyuan; Sha, Sha; Wan, Qi; Chen, Ling (J Alzheimers Dis, 2016)
BACKGROUND: Simvastatin (SV) has been reported to improve dementia and slow progression of Alzheimer's disease (AD), however there are conflicting reports. OBJECTIVE & METHODS: Intracerebroventricular injection of aggregated Aβ1-42 in mice (Aβ1-42-mice) caused spatial cognitive deficits, long-term potentiation (LTP) impairment, and death of hippocampal pyramidal cells. The present study focused on exploring the dose-dependent effects of SV (10-80 mg/kg) on Aβ1-42-impaired spatial memory and the underlying mechanisms. RESULTS: The treatment of Aβ1-42-mice with SV for continuous 15 days could attenuate the spatial cognitive deficits and recover the LTP induction in a "U" type dose-dependent manner. The death of pyramidal cells in Aβ1-42-mice was significantly reduced by the SV-treatment at 20 mg/kg, but not at a dose of 10 or 40 mg/kg, even was aggravated at a dose of 80 mg/kg. Hippocampal NMDA receptor (NMDAr) NR2B phosphorylation (phospho-NR2B) was elevated in Aβ1-42-mice, which was further dose-dependently increased by SV-treatment. Replenishment of isoprenoid farnesyl pyrophosphate (FPP) by applying farnesol (FOH) could abolish the SV-increased phospho-NR2B in Aβ1-42-mice, but had no effect on the Aβ1-42-enhanced phospho-NR2B. NMDAr antagonist blocked the neurotoxicity of Aβ1-42 and SV (80 mg/kg) in Aβ1-42-mice, whereas FOH only inhibited SV (80 mg/kg)-neurotoxicity. The SV-treatment in Aβ1-42-mice corrected the decrease in hippocampal Akt phosphorylation. The PI3K inhibitor abolished the SV (20 mg/kg)-neuroprotection in Aβ1-42-mice. CONCLUSION: SV-treatment in Aβ1-42-mice exerts dose-dependent neuroprotection and neurotoxicity by reducing FPP to enhance the phosphorylation of NR2B and Akt.
Keywords: Amyloid beta-Peptides; Animals; Dose-Response Relationship, Drug; Hippocampus; Injections, Intraventricular; Male; Maze Learning; Mice; Neuroprotective Agents; Peptide Fragments; Phosphorylation; Polyisoprenyl Phosphates; Receptors, N-Methyl-D-Aspartate; Sesquiterpenes; Simvastatin; Spatial Memory

Dysregulation of Elongation Factor 1A Expression is Correlated with Synaptic Plasticity Impairments in Alzheimer's Disease. - Beckelman, Brenna C; Day, Stephen; Zhou, Xueyan; Donohue, Maggie; Gouras, Gunnar K; Klann, Eric; Keene, C Dirk; Ma, Tao (J Alzheimers Dis, 2016)
Synaptic dysfunction may represent an early and crucial pathophysiology in Alzheimer's disease (AD). Recent studies implicate a connection between synaptic plasticity deficits and compromised capacity of de novo protein synthesis in AD. The mRNA translational factor eukaryotic elongation factor 1A (eEF1A) is critically involved in several forms of long-lasting synaptic plasticity. By examining postmortem human brain samples, a transgenic mouse model, and application of synthetic human Aβ42 on mouse hippocampal slices, we demonstrated that eEF1A protein levels were significantly decreased in AD, particularly in the hippocampus. In contrast, brain levels of eukaryotic elongation factor 2 were unaltered in AD. Further, upregulation of eEF1A expression by the adenylyl cyclase activator forskolin, which induces long-lasting synaptic plasticity, was blunted in hippocampal slices derived from Tg2576 AD model mice. Finally, Aβ-induced hippocampal long-term potentiation defects were alleviated by upregulation of eEF1A signaling via brain-specific knockdown of the gene encoding tuberous sclerosis 2. In summary, our findings suggest a strong correlation between the dysregulation of eEF1A synthesis and AD-associated synaptic failure. These findings provide insights into the understanding of molecular mechanisms underlying AD etiology and may aid in identification of novel biomarkers and therapeutic targets.

Early Postmenopausal Transdermal 17β-Estradiol Therapy and Amyloid-β Deposition. - Kantarci, Kejal; Lowe, Val J; Lesnick, Timothy G; Tosakulwong, Nirubol; Bailey, Kent R; Fields, Julie A; Shuster, Lynne T; Zuk, Samantha M; Senjem, Matthew L; Mielke, Michelle M; Gleason, Carey; Jack, Clifford R; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It remains controversial whether hormone therapy in recently postmenopausal women modifies the risk of Alzheimer's disease (AD). OBJECTIVE: To investigate the effects of hormone therapy on amyloid-β deposition in recently postmenopausal women. METHODS: Participants within 5-36 months past menopause in the Kronos Early Estrogen Prevention Study, a randomized, double blinded placebo-controlled clinical trial, were randomized to: 1) 0.45 mg/day oral conjugated equine estrogens (CEE); 2) 50μg/day transdermal 17β-estradiol; or 3) placebo pills and patch for four years. Oral progesterone (200 mg/day) was given to active treatment groups for 12 days each month. 11C Pittsburgh compound B (PiB) PET imaging was performed in 68 of the 118 participants at Mayo Clinic approximately seven years post randomization and three years after stopping randomized treatment. PiB Standard unit value ratio (SUVR) was calculated. RESULTS: Women (age = 52-65) randomized to transdermal 17β-estradiol (n = 21) had lower PiB SUVR compared to placebo (n = 30) after adjusting for age [odds ratio (95% CI) = 0.31(0.11-0.83)]. In the APOEɛ4 carriers, transdermal 17β-estradiol treated women (n = 10) had lower PiB SUVR compared to either placebo (n = 5) [odds ratio (95% CI) = 0.04(0.004-0.44)], or the oral CEE treated group (n = 3) [odds ratio (95% CI) = 0.01(0.0006-0.23)] after adjusting for age. Hormone therapy was not associated with PiB SUVR in the APOEɛ4 non-carriers. CONCLUSION: In this pilot study, transdermal 17β-estradiol therapy in recently postmenopausal women was associated with a reduced amyloid-β deposition, particularly in APOEɛ4 carriers. This finding may have important implications for the prevention of AD in postmenopausal women, and needs to be confirmed in a larger sample.

Early-Life Exposure to Lead (Pb) Alters the Expression of microRNA that Target Proteins Associated with Alzheimer's Disease. - Masoud, Anwar M; Bihaqi, Syed W; Machan, Jason T; Zawia, Nasser H; Renehan, William E (J Alzheimers Dis, 2016)
There is a growing recognition of the impact of environmental toxins on the epigenetic regulation of gene expression, including the genes that play a critical role in neural development, neural function, and neurodegeneration. We have shown previously that exposure to the heavy metal lead (Pb) in early life results in a latent over-expression of AD-related proteins in rodents and primates. The present study provides evidence that early postnatal exposure to Pb also alters the expression of select miRNA. Mice were exposed to 0.2% Pb acetate from Postnatal Day 1 (PND 1, first 24 h after birth) to PND 20 via their mother's milk. Brain tissue was harvested at PND 20, 180, or 700, and miRNA were isolated and quantified by qPCR. This exposure produced a transient increase (relative to control) in the expression of miR-106b (binds to AβPP mRNA), miR-29b (targets the mRNA for the transcription factor SP1) and two miRNAs (miR-29b and miR-132) that have the ability to inhibit translation of proteins involved in promoter methylation. The expression of miR-106b decreased over time in the Pb-exposed animals and was significantly less than the levels exhibited by the control animals at PND700. The level of miR-124, which binds to SP1 mRNA, was also reduced (relative to controls) at PND700. In summary, we show that exposure to the heavy metal Pb in early life has a significant impact on the short- and long-term expression of miRNA that target epigenetic mediators and neurotoxic proteins.
Keywords: Age Factors; Amyloid beta-Protein Precursor; Animals; Animals, Newborn; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gene Expression Regulation, Developmental; Lead; Male; Mice; Mice, Inbred C57BL; MicroRNAs; Pregnancy; RNA, Messenger; Sp1 Transcription Factor

Effect of Normal Aging and of Mild Cognitive Impairment on Event-Related Potentials to a Stroop Color-Word Task. - Ramos-Goicoa, Marta; Galdo-Álvarez, Santiago; Díaz, Fernando; Zurrón, Montserrat (J Alzheimers Dis, 2016)
Event-related potentials (ERPs) were recorded from 84 adults (51 to 87 years old) with the aim of exploring the effects of aging (middle-aged and older groups) and cognitive status (healthy or with amnestic mild cognitive impairment, aMCI) on the neural functioning associated with stimulus and response processing in a Stroop color-word task. An interference (or Stroop) effect was observed in the Reaction Time (RT), and the RT and number of errors results were consistent with the age-related decline in performance. Cognitive status did not affect the behavioral performance of the task, but age and cognitive status affected several ERP parameters. Aging was associated with a) slowing of the neural processing of the stimuli (P150, N2, and P3b latencies were longer), b) greater activation of the motor cortex for response preparation (LRP-R amplitude was larger), and c) use of more neural resources for cognitive control of stimuli (N2 amplitude was larger to the congruent and incongruent stimuli than to the colored X-strings, in the older group). Independent of age, aMCI dedicated more neural resources to processing the irrelevant dimension of the stimulus (they showed a greater difference than the control participants between the P3b amplitude to the colored X-strings and to the congruent/incongruent stimuli) and showed a deficit in the selection and preparation of the motor response (with smaller LRP-S and LRP-R amplitudes). Furthermore, the middle-aged aMCI participants evaluated and classified both congruent and incongruent stimuli more slowly (they showed longer P3b latencies) relative to middle-aged controls.

The Effects of LW-AFC on Intestinal Microbiome in Senescence-Accelerated Mouse Prone 8 Strain, a Mouse Model of Alzheimer's Disease. - Wang, Jianhui; Ye, Fuqiang; Cheng, Xiaorui; Zhang, Xiaorui; Liu, Feng; Liu, Gang; Ni, Ming; Qiao, Shanyi; Zhou, Wenxia; Zhang, Yongxiang (J Alzheimers Dis, 2016)
Microbes have deserved broader attention as causal factors in Alzheimer's disease (AD), a neurodegenerative disorder. The senescence-accelerated mouse prone 8 (SAMP8) strain, a spontaneous mice of accelerated aging, are considered a robust model for sporadic AD. LW-AFC, an herbal medicine, was prepared from LiuweiDihuang decoction, which is a classical traditional Chinese medicine prescription. Here, we showed that the treatment of LW-AFC improved cognitive impairments of SAMP8 mice, including spatial learning and memory ability, active avoidance response, and object recognition memory capability. Our data indicated that there were significantly 8 increased and 12 decreased operational taxonomic units (OTUs) in the gut microbiota of SAMP8 mice compared with senescence accelerated mouse resistant 1 (SAMR1) strains, the control of SAMP8 mice. The treatment of LW-AFC altered 22 (16 increased and 6 decreased) OTUs in SAMP8 mice and among them, 15 OTUs could be reversed by LW-AFC treatment resulting in a microbial composition similar to that of SAMR1 mice. We further showed that there were 7 (3 negative and 4 positive correlation) OTUs significantly correlated with all the three types of cognitive abilities, at the order level, including Bacteroidales, Clostridiales, Desulfovibrionales, CW040, and two unclassified orders. LW-AFC had influences on bacterial taxa correlated with the abilities of learning and memory in SAMP8 mice and restored them to SAMR1 mice. Our results indicate that the effects of LW-AFC on improving cognitive impairments of SAMP8 mice might be via modulating intestinal microbiome and LW-AFC could be used as a potential anti-AD agent.

Formulaic Language in People with Probable Alzheimer's Disease: A Frequency-Based Approach. - Zimmerer, Vitor C; Wibrow, Mark; Varley, Rosemary A (J Alzheimers Dis, 2016)
BACKGROUND: Language change can be a valuable biological marker of overall cognitive change in Alzheimer's disease (AD) and other forms of dementia. Previous reports have described increased use of language formulas in AD, i.e., combinations likely processed in a holistic manner. Words that commonly occur together are more likely to become a formula. OBJECTIVE: To determine if frequency of co-occurrence as one indicator for formulaic language can distinguish people with probable AD from controls and if variables are sensitive to time post-symptom onset. METHODS: We developed the Frequency in Language Analysis Tool (FLAT), which indicates degrees of formulaicity in an individual language sample. The FLAT accomplishes this by comparing individual language samples to co-occurrence data from the British National Corpus (BNC). Our analysis also contained more conventional language variables in order to assess novel contributions of the FLAT. We analyzed data from the Pitt Corpus, which is part of DementiaBank. RESULTS: Both conventional and co-occurrence variables were able to distinguish AD and control groups. According to co-occurrence data, people with probable AD produced more formulaic language than controls. Only co-occurrence variables correlated with disease progression. DISCUSSION: Frequency of word co-occurrences is one indicator for formulaicity and a valuable contribution to characterizing language change in AD.

Gene Expression of Quaking in Sporadic Alzheimer's Disease Patients is Both Upregulated and Related to Expression Levels of Genes Involved in Amyloid Plaque and Neurofibrillary Tangle Formation. - Farnsworth, Bryn; Peuckert, Christiane; Zimmermann, Bettina; Jazin, Elena; Kettunen, Petronella; Emilsson, Lina Sors (J Alzheimers Dis, 2016)
Quaking (QKI) is a gene exclusively expressed within glial cells. QKI has previously been implicated in various neurological disorders and diseases, including Alzheimer's disease (AD), a condition for which increasing evidence suggests a central role of glia cells. The objective of the present study was to investigate the expression levels of QKI and three QKI isoforms (QKI5, QKI6, and QKI7) in AD. Genes that have previously been related to the ontogeny and progression of AD, specifically APP, PSEN1, PSEN2, and MAPT, were also investigated. A real-time PCR assay of 123 samples from human postmortem sporadic AD patients and control brains was performed. The expression values were analyzed with an analysis of covariance model and subsequent multiple regressions to explore the possibility of related expression values between QKI, QKI isoforms, and AD-related genes. Further, the sequences of AD-related genes were analyzed for the presence of QKI binding domains. QKI and all measured QKI isoforms were found to be significantly upregulated in AD samples, relative to control samples. However, APP, PSEN1, PSEN2, and MAPT were not found to be significantly different. QKI and QKI isoforms were found to be predictive for the variance of APP, PSEN1, PSEN2, and MAPT, and putative QKI binding sites suggests an interaction with QKI. Overall, these results implicate a possible role of QKI in AD, although the exact mechanism by which this occurs remains to be uncovered.

A Genetic Variant of the Sortilin 1 Gene is Associated with Reduced Risk of Alzheimer's Disease. - Andersson, Carl-Henrik; Hansson, Oskar; Minthon, Lennart; Andreasen, Niels; Blennow, Kaj; Zetterberg, Henrik; Skoog, Ingmar; Wallin, Anders; Nilsson, Staffan; Kettunen, Petronella (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative disorder represented by the accumulation of intracellular tau protein and extracellular deposits of amyloid-β (Aβ) in the brain. The gene sortilin 1 (SORT1) has previously been associated with cardiovascular disease in gene association studies. It has also been proposed to be involved in AD pathogenesis through facilitating Aβ clearance by binding apoE/Aβ complexes prior to cellular uptake. However, the neuropathological role of SORT1 in AD is not fully understood. To evaluate the associations between gene variants of SORT1 and risk of AD, we performed genetic analyses in a Swedish case-control cohort. Ten single nucleotide polymorphisms (SNPs), covering the whole SORT1 gene, were selected and genotyped in 620 AD patients and 1107 controls. The SNP rs17646665, located in a non-coding region of the SORT1 gene, remained significantly associated with decreased risk of AD after multiple testing (pc = 0.0061). In addition, other SNPs were found to be nominally associated with risk of AD, as well as altered cognitive function and the CSF biomarker Aβ42, but these associations did not survive correction for multiple testing. The fact that SORT1 has been strongly associated with risk of cardiovascular disease is intriguing as cardiovascular disease is also regarded as a risk factor for AD. Finally, increased knowledge about SORT1 function has a potential to increase our understanding of APOE, the strongest risk factor for AD.

Genetic Variations in ABCA7 Can Increase Secreted Levels of Amyloid-β40 and Amyloid-β42 Peptides and ABCA7 Transcription in Cell Culture Models. - Bamji-Mirza, Michelle; Li, Yan; Najem, Dema; Liu, Qing Yan; Walker, Douglas; Lue, Lih-Fen; Stupak, Jacek; Chan, Kenneth; Li, Jianjun; Ghani, Mahdi; Yang, Ze; Rogaeva, Ekaterina; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by extracellular deposits of amyloid-β (Aβ) in the brain. ABCA7 is highly expressed in the brain and a susceptibility gene for late-onset AD (LOAD). The minor alleles at two ABCA7 single-nucleotide polymorphisms (SNPs), rs3764650 (T>G; intron13) and rs3752246 at a predicted myristoylation site (C>G; exon33; p.Gly1527Ala), are significantly associated with LOAD risk; however, the mechanism of this association is unknown. Functional consequences of both SNPs were examined in HEK293 and CHO cells stably expressing AβPPSwe. Luciferase reporter assays in HEK293 cells suggested that intron13 carrying rs3764650 major T-allele (int13-T) possessed promoter-enhancing capabilities. Co-transfection experiments with hABCA7 and int13-T resulted in significantly increased ABCA7 protein level relative to that with int13-G. Expression of hABCA7 carrying rs3752246 risk allele led to increases in secreted Aβ40 and Aβ42 and β-secretase activity in CHO- and HEK-AβPPSwe cells. Hydroxymyristic acid treatment of cells expressing hABCA7 carrying the rs3752246 major G allele resulted in increased β-secretase activity and levels of Aβ, suggesting that lack of myristoylation contributes to the observed cell-phenotypes. Molecular weight determination, by gel-electrophoresis and mass spectrometry, of hABCA7 peptides spanning position 1527 showed loss of post-translational modification in the risk-allele peptide. These results suggest that decreased expression, or impaired function, of ABCA7 may contribute to AD pathology.

Geographical Variation in Antipsychotic Drug Use in Elderly Patients with Dementia: A Nationwide Study. - Zakarias, Johanne Købstrup; Jensen-Dahm, Christina; Nørgaard, Ane; Stevnsborg, Lea; Gasse, Christiane; Andersen, Bodil Gramkow; Søren, Jakobsen; Waldorff, Frans Boch; Moos, Torben; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Use of antipsychotics in elderly patients with dementia has decreased in the past decade due to safety regulations; however use is still high. Geographical variation may indicate discrepancies in clinical practice and lack of adherence to evidence-based guidelines for the management of behavioral symptoms. OBJECTIVE: To investigate potential geographical variances in use of antipsychotic drugs in dementia care. METHODS: A registry-based cross-sectional study in the entire elderly population of Denmark (≥65 years) conducted in 2012. Data included place of residence, prescriptions filled, and hospital discharge diagnoses. Antipsychotic drug use among elderly with (n = 34,536) and without (n = 931,203) a dementia diagnosis was compared across the five regions and 98 municipalities in Denmark, adjusted for age and sex. RESULTS: In 2012, the national prevalence of antipsychotic drug use was 20.7% for elderly patients with dementia, with a national incidence of 3.9%. The prevalence ranged from 17.0% to 23.3% in the five regions and from 7.5% to 33.1% in the 98 municipalities, demonstrating an over four-fold difference. CONCLUSION: The observed geographical variation was more pronounced at municipal level as compared to regional level, suggesting that the variation may be related to variances in clinical practice in primary care. This study highlights an urgent need for further educating professional carers and physicians to guide non-pharmacological as well as pharmacological management of neuropsychiatric symptoms in elderly patients with dementia.

The Gesture Imitation in Alzheimer's Disease Dementia and Amnestic Mild Cognitive Impairment. - Li, Xudong; Jia, Shuhong; Zhou, Zhi; Hou, Chunlei; Zheng, Wenjing; Rong, Pei; Jiao, Jinsong (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease dementia (ADD) has become an important health problem in the world. Visuospatial deficits are considered to be an early symptom besides memory disorder. OBJECTIVES: The gesture imitation test was devised to detect ADD and amnestic mild cognitive impairment (aMCI). METHODS: A total of 117 patients with ADD, 118 with aMCI, and 95 normal controls were included in this study. All participants were administered our gesture imitation test, the Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA), the Clock Drawing Test (CDT), and the Clinical Dementia Rating Scale (CDR). RESULTS: Patients with ADD performed worse than normal controls on global scores and had a lower success rate on every item (p < 0.001). The area under the curve (AUC) for the global scores when comparing the ADD and control groups was 0.869 (p < 0.001). Item 4 was a better discriminator with a sensitivity of 84.62% and a specificity of 67.37%. The AUC for the global scores decreased to 0.621 when applied to the aMCI and control groups (p = 0.002). After controlling for age and education, the gesture imitation test scores were positively correlated with the MMSE (r = 0.637, p < 0.001), the MoCA (r = 0.572, p < 0.001), and the CDT (r = 0.514, p < 0.001) and were negatively correlated with the CDR scores (r = -0.558, p < 0.001). CONCLUSIONS: The gesture imitation test is an easy, rapid tool for detecting ADD, and is suitable for the patients suspected of mild ADD and aMCI in outpatient clinics.

Greater specificity for cerebrospinal fluid P-tau231 over P-tau181 in the differentiation of healthy controls from Alzheimer's disease. - Spiegel, Jonathan; Pirraglia, Elizabeth; Osorio, Ricardo S; Glodzik, Lidia; Li, Yi; Tsui, Wai; Saint Louis, Leslie A; Randall, Catherine; Butler, Tracy; Xu, Jinfeng; Zinkowski, Raymond P; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of phosphorylated-tau (P-tau) 231 and P-tau181 are two biomarkers for the identification of tau pathology as related to Alzheimer's disease (AD). While both are pathologically validated, their relative diagnostic performances are not well known. This cross-sectional diagnostic study of 87 normal (NL) subjects and 28 AD subjects compared CSF P-tau231 with CSF P-tau181. Logistic regression modeling demonstrated that the P-tau231 was superior to the P-tau181 in the diagnostic classifications. At a fixed 85% sensitivity cutoff, the ROC analysis shows that P-tau231 has greater overall specificity than P-tau181. While both P-tau analytes demonstrated equivalent negative predictive accuracies, P-tau231 yielded significantly fewer false positives. Moreover, P-tau231, but not P-tau181, demonstrated sensitivity to the E4 genotype. A postmortem validation with 9 AD subjects confirmed the superiority of the CSF P-tau231 specificity. This study suggests that P-tau231 has the potential to improve the CSF tau biomarker diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Phosphorylation; ROC Curve; Sensitivity and Specificity; tau Proteins

Gypenoside XVII Enhances Lysosome Biogenesis and Autophagy Flux and Accelerates Autophagic Clearance of Amyloid-β through TFEB Activation. - Meng, Xiangbao; Luo, Yun; Liang, Tian; Wang, Mengxia; Zhao, Jingyu; Sun, Guibo; Sun, Xiaobo (J Alzheimers Dis, 2016)
A strategy for activating transcription factor EB (TFEB) to restore autophagy flux may provide neuroprotection against Alzheimer's disease. Our previous study reported that gypenoside XVII (GP-17), which is a major saponin abundant in ginseng and Panax notoginseng, ameliorated amyloid-β (Aβ)25-35-induced apoptosis in PC12 cells by regulating autophagy. In the present study, we aimed to determine whether GP-17 has neuroprotective effects on PC12 cells expressing the Swedish mutant of APP695 (APP695swe) and APP/PS1 mice. We also investigated the underlying mechanism. We found that GP-17 could significantly increase Atg5 expression and the conversion of LC3-I to LC3-II in APP695 cells, which was associated with a reduction in p62 expression. GP-17 also elevated the number of LC3 puncta in APP695 cells transduced with pCMV-GFP-LC3. GP-17 promoted the autophagy-based elimination of AβPP, Aβ40, and Aβ42 in APP695swe cells and prevented the formation of Aβ plaques in the hippocampus and cortex of APP/PS1 mice. Furthermore, spatial learning and memory deficits were cured. Atg5 knockdown could abrogate the GP-17-mediated removal of AβPP, Aβ40, and Aβ42 in APP695swe cells. GP-17 upregulated LAMP-1, increased LysoTracker staining, and augmented LAMP-1/LC3-II co-localization. GP-17 could release TFEB from TFEB/14-3-3 complexes, which led to TFEB nuclear translocation and the induction of autophagy and lysosome biogenesis and resulted in the amelioration of autophagy flux. The knockdown of TFEB could abolish these effects of GP-17. In summary, these results demonstrated that GP-17 conferred protective effects to the cellular and rodent models of Alzheimer's disease by activating TFEB.

High-Sodium Diet Has Opposing Effects on Mean Arterial Blood Pressure and Cerebral Perfusion in a Transgenic Mouse Model of Alzheimer's Disease. - Taheri, Saeid; Yu, Jin; Zhu, Hong; Kindy, Mark S (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral ionic homeostasis impairment, especially Ca2+, has been observed in Alzheimer's disease (AD) and also with hypertension. Hypertension and AD both have been implicated in impaired cerebral autoregulation. However, the relationship between the ionic homeostasis impairment in AD and hypertension and cerebral blood flow (CBF) autoregulation is not clear. OBJECTIVE: To test the hypothesis that a high-salt diet regimen influences the accumulation of amyloid-β (Aβand CBF) and CBF, exacerbates cognitive decline, and increases the propensity to AD. METHODS: Double transgenic mice harboring the amyloid-β protein precursor (APPswe), and presenilin-1 (PSEN1) along with control littermates, 2 months of age at initiation of special diet, were divided into 4 groups: Group A, APP/PS1 and Group B, controls fed a high-sodium (4.00%) chow diet for 3 months; Group C, APP/PS1 and Group D, controls fed a low-sodium (0.08%) regular chow diet for 3 months. Mean arterial blood pressure (MAP) and CBF were measured noninvasively using the tail MAP measurement device and magnetic resonance imaging, respectively. Aβ plaques numbers in the cortex and hippocampus of APP/PS1 were quantified. RESULTS: In contrary to controls, APP/PS1 mice fed a high-salt diet did not show markedly elevated mean systolic and diastolic blood pressure (134±4.8 compared with 162±2.8 mmHg, and 114±5.0 compared with 137±20 mmHg, p< 0.0001). However, a high-salt diet increased CBF in both APP/PS1 and controls and did not alter the cerebral tissue integrity. Aβ plaques were significantly reduced in the cortex and hippocampus of mice fed a high-salt diet. CONCLUSION: These data suggest that a high-salt diet differently affects MAP and CBF in APP/PS1 mice and controls.

Human ApoE ɛ2 Promotes Regulatory Mechanisms of Bioenergetic and Synaptic Function in Female Brain: A Focus on V-type H+-ATPase. - Woody, Sarah K; Zhou, Helen; Ibrahimi, Shaher; Dong, Yafeng; Zhao, Liqin (J Alzheimers Dis, 2016)
Humans possess three major isoforms of the apolipoprotein E (ApoE) gene encoded by three alleles: ApoE ɛ2 (ApoE2), ApoE ɛ3 (ApoE3), and ApoE ɛ4 (ApoE4). It is established that the three ApoE isoforms confer differential susceptibility to Alzheimer's disease (AD); however, an in-depth molecular understanding of the underlying mechanisms is currently unavailable. In this study, we examined the cortical proteome differences among the three ApoE isoforms using 6-month-old female, human ApoE2, ApoE3, and ApoE4 gene-targeted replacement mice and two-dimensional proteomic analyses. The results reveal that the three ApoE brains differ primarily in two areas: cellular bioenergetics and synaptic transmission. Of particular significance, we show for the first time that the three ApoE brains differentially express a key component of the catalytic domain of the V-type H+-ATPase (Atp6v), a proton pump that mediates the concentration of neurotransmitters into synaptic vesicles and thus is crucial in synaptic transmission. Specifically, our data demonstrate that ApoE2 brain exhibits significantly higher levels of the B subunit of Atp6v (Atp6v1B2) when compared to both ApoE3 and ApoE4 brains, with ApoE4 brain exhibiting the lowest expression. Our additional analyses show that Atp6v1B2 is significantly impacted by aging and AD pathology and the data suggest that Atp6v1B2 deficiency could be involved in the progressive loss of synaptic integrity during early development of AD. Collectively, our findings indicate that human ApoE isoforms differentially modulate regulatory mechanisms of bioenergetic and synaptic function in female brain. A more efficient and robust status in both areas-in which Atp6v may play a role-could serve as a potential mechanism contributing to the neuroprotective and cognition-favoring properties associated with the ApoE2 genotype.

Human Truncated Tau Induces Mature Neurofibrillary Pathology in a Mouse Model of Human Tauopathy. - Zimova, Ivana; Brezovakova, Veronika; Hromadka, Tomas; Weisova, Petronela; Cubinkova, Veronika; Valachova, Bernadeta; Filipcik, Peter; Jadhav, Santosh; Smolek, Tomas; Novak, Michal; Zilka, Norbert (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) represents the most common neurodegenerative disorder. Several animal models have been developed in order to test pathophysiological mechanisms of the disease and to predict effects of pharmacological interventions. Here we examine the molecular and behavioral features of R3m/4 transgenic mice expressing human non-mutated truncated tau protein (3R tau, aa151-391) that were previously used for efficacy testing of passive tau vaccine. The mouse model reliably recapitulated crucial histopathological features of human AD, such as pre-tangles, neurofibrillary tangles, and neuropil threads. The pathology was predominantly located in the brain stem. Transgenic mice developed mature sarkosyl insoluble tau complexes consisting of mouse endogenous and human truncated and hyperphosphorylated forms of tau protein. The histopathological and biochemical features were accompanied by significant sensorimotor impairment and reduced lifespan. The sensorimotor impairment was monitored by a highly sensitive, fully-automated tool that allowed us to assess early deficit in gait and locomotion. We suggest that the novel transgenic mouse model can serve as a valuable tool for analysis of the therapeutic efficacy of tau vaccines for AD therapy.

Impacts of High Serum Total Cholesterol Level on Brain Functional Connectivity in Non-Demented Elderly. - Zhang, Ting; Li, He; Zhang, Junying; Li, Xin; Qi, Di; Wang, Nuo; Zhang, Zhanjun (J Alzheimers Dis, 2016)
Epidemiological and clinical studies suggest that high serum cholesterol is a risk factor of dementia. However, the effects of cholesterol on cognition and brain remain largely unclear. This study aims to investigate the associations between serum total cholesterol (TC) and neuropsychological performance, and intrinsic functional networks in non-demented elderly. Among a cohort of 120 community-dwelling Beijing residents, 29 subjects in the high-TC group (1st quartile) and 31 in the low-TC group (4th quartile) were included in this study, and underwent a battery of neuropsychological tests and magnetic resonance imaging (MRI) scans, including T2- and T1-weighted imaging, and resting-state functional MRI. No significant group difference was found in any of the neuropsychological tests used. Stronger connectivity in the default mode network was observed in the high-TC group compared to that in the low-TC group (p <  0.001, uncorrected). While in the salience network (SN), the high-TC group showed lower connectivity in the anterior cingulate cortex and frontal regions, compared to the low-TC group (p <  0.05, FWE corrected). Our findings suggest that in non-demented elderly persons, high serum cholesterol is associated with disruption of functional connectivity in the SN. The results not only deepen our understanding of how cholesterol affects the brain, but are also significant for selecting sensitive indicators for monitoring the impairments of cholesterol on the neural system.
Keywords: Aged; Brain; Brain Mapping; Cholesterol; Cognition; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Net; Neuropsychological Tests

Impaired Parahippocampus Connectivity in Mild Cognitive Impairment and Alzheimer's Disease. - Liu, Jieqiong; Zhang, Xinqing; Yu, Chunshui; Duan, Yunyun; Zhuo, Junjie; Cui, Yue; Liu, Bing; Li, Kuncheng; Jiang, Tianzi; Liu, Yong (J Alzheimers Dis, 2016)
BACKGROUND: The parahippocampal gyrus (PHG) is an important region of the limbic system that plays an important role in episodic memory. Elucidation of the PHG connectivity pattern will aid in the understanding of memory deficits in neurodegenerative diseases. OBJECTIVE: To investigate if disease severity associated altered PHG connectivity in Alzheimer's disease (AD) exists. METHODS: We evaluated resting-state functional magnetic resonance imaging data from 18 patients with amnestic mild cognitive impairment (MCI), 35 patients with AD, and 21 controls. The PHG connectivity pattern was examined by calculating Pearson's correlation coefficients between the bilateral PHG and whole brain. Group comparisons were performed after controlling for the effects of age and gender. The functional connectivity strength in each identified region was correlated with the MMSE score to evaluate the relationship between connectivity and cognitive ability. RESULTS: Several brain regions of the default mode network showed reduced PHG connectivity in the AD patients, and PHG connectivity was associated with disease severity in the MCI and AD subjects. More importantly, correlation analyses showed that there were positive correlations between the connectivity strengths of the left PHG-PCC/Pcu and left PHG-left MTG and the Mini-Mental State Examination, indicating that with disease progression from MCI to severe AD, damage to the functional connectivity of the PHG becomes increasingly severe. CONCLUSIONS: These results indicate that disease severity is associated with altered PHG connectivity, contributing to knowledge about the reduction in cognitive ability and impaired brain activity that occur in AD/MCI. These early changes in the functional connectivity of the PHG might provide some potential clues for identification of imaging markers for the early detection of MCI and AD.
Keywords: Aged; Alzheimer Disease; Apolipoproteins E; Brain Mapping; Cognitive Dysfunction; Female; Hippocampus; Humans; Limbic System; Magnetic Resonance Imaging; Male; Mental Status Schedule; Neural Pathways; Rest; Severity of Illness Index

Increased Electron Paramagnetic Resonance Signal Correlates with Mitochondrial Dysfunction and Oxidative Stress in an Alzheimer's disease Mouse Brain. - Fang, Du; Zhang, Zhihua; Li, Hang; Yu, Qing; Douglas, Justin T; Bratasz, Anna; Kuppusamy, Periannan; Yan, Shirley ShiDu (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized clinically by cognitive decline and memory loss. The pathological features are amyloid-β peptide (Aβ) plaques and intracellular neurofibrillary tangles. Many studies have suggested that oxidative damage induced by reactive oxygen species (ROS) is an important mechanism for AD progression. Our recent study demonstrated that oxidative stress could further impair mitochondrial function. In the present study, we adopted a transgenic mouse model of AD (mAPP, overexpressing AβPP/Aβ in neurons) and performed redox measurements using in vivo electron paramagnetic resonance (EPR) imaging with methoxycarbamyl-proxyl (MCP) as a redox-sensitive probe for studying oxidative stress in an early stage of pathology in a transgenic AD mouse model. Through assessing oxidative stress, mitochondrial function and cognitive behaviors of mAPP mice at the age of 8-9 months, we found that oxidative stress and mitochondrial dysfunction appeared in the early onset of AD. Increased ROS levels were associated with defects of mitochondrial and cognitive dysfunction. Notably, the in vivo EPR method offers a unique way of assessing tissue oxidative stress in living animals under noninvasive conditions, and thus holds a potential for early diagnosis and monitoring the progression of AD.
Keywords: Adenosine Triphosphate; Age of Onset; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition; Disease Models, Animal; Electron Spin Resonance Spectroscopy; Electron Transport Complex IV; Female; Humans; Male; Maze Learning; Mice, Transgenic; Mitochondria; Oxidative Stress; Reactive Oxygen Species; Spatial Memory

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia. - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschläger, Afra M; Riedl, Valentin; et al. (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory Disorders; Middle Aged; Nerve Net; Parietal Lobe; Temporal Lobe

Insulin Resistance is Associated with Increased Levels of Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Reduced Memory Function in At-Risk Healthy Middle-Aged Adults. - Hoscheidt, Siobhan M; Starks, Erika J; Oh, Jennifer M; Zetterberg, Henrik; Blennow, Kaj; Krause, Rachel A; Gleason, Carey E; Puglielli, Luigi; Atwood, Craig S; Carlsson, Cynthia M; Asthana, Sanjay; Johnson, Sterling C; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Type 2 diabetes is associated with an increased risk for Alzheimer's disease (AD). Regulation of normal insulin function may be important in reducing the prevalence of dementia due to AD, particularly in individuals who harbor genetic risk for or have a parental family history of AD. The relationship between insulin resistance (IR) and AD pathology remains poorly understood, particularly in midlife prior to the onset of clinical metabolic disease or cognitive decline. OBJECTIVE: We examined associations between IR as indexed by HOMA-IR, cerebrospinal fluid (CSF) biomarkers of AD pathology, and memory in middle-aged adults enriched for AD. We postulated that higher HOMA-IR and APOEɛ4 carriage would be associated with greater CSF AD pathology and poor memory performance. METHODS: Cognitively asymptomatic middle-aged adults (N = 70, mean age = 57.7 years) from the Wisconsin Alzheimer's Disease Research Center with a parental family history of dementia due to AD underwent lumbar puncture, blood draw, and neuropsychological testing. CSF AD biomarkers including soluble amyloid-β protein precursor β (sAβPPβ), amyloid-β42 (Aβ42), and phosphorylated tau (P-tau181) were examined with respect to HOMA-IR and APOEɛ4 status. Delayed memory performance was examined with respect to HOMA-IR, CSF AD biomarkers, and APOEɛ4 status. RESULTS: Higher HOMA-IR was associated with higher sAβPPβ and Aβ42 . APOEɛ4 carriers had significantly higher levels of sAβPPα, sAβPPβ, and P-tau181/Aβ42 compared to noncarriers. The concurrent presence of higher HOMA-IR and CSF AD pathology predicted worse delayed memory performance. CONCLUSION: Overall, the findings suggest that IR and APOEɛ4 are contributing factors to the development of AD pathology in midlife, and provide support for targeting insulin function as a potentially modifiable risk factor for AD.

Intranasal TAT-haFGF Improves Cognition and Amyloid-β Pathology in an AβPP/PS1 Mouse Model of Alzheimer's Disease. - Lou, Guofeng; Zhang, Qihao; Xiao, Fei; Xiang, Qi; Su, Zhijian; Huang, Yadong (J Alzheimers Dis, 2016)
Neurotoxic amyloid-β (Aβ) peptide causing cognitive function disabilities is one of the most characteristic pathological features in Alzheimer's disease (AD). A novel fusion protein, TAT-haFGF, was administrated to AβPP/PS1 transgenic mice by intravenous (IV) injection and intranasal (IN) delivery, respectively, for 5 weeks to compare the pharmacodynamics between the two routes of administration. Our results showed that IN administration of TAT-haFGF improved cognition and reduced Aβ plaques more significantly in AβPP/PS1 mice, when compared with IV injection. Our new findings suggest that TAT-haFGF might be a promising new therapy to attenuate AD pathological process.
Keywords: Administration, Intranasal; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition Disorders; Disease Models, Animal; Fibroblast Growth Factors; Gene Products, tat; Humans; Injections, Intraventricular; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Movement; Mutation; Peptide Fragments; Plaque, Amyloid; Presenilin-1

Intraneuronal Amylin Deposition, Peroxidative Membrane Injury and Increased IL-1β Synthesis in Brains of Alzheimer's Disease Patients with Type-2 Diabetes and in Diabetic HIP Rats. - Verma, Nirmal; Ly, Han; Liu, Miao; Chen, Jing; Zhu, Haining; Chow, Martin; Hersh, Louis B; Despa, Florin (J Alzheimers Dis, 2016)
Amylin is a hormone synthesized and co-secreted with insulin by pancreatic β-cells that crosses the blood-brain barrier and regulates satiety. Amylin from humans (but not rodents) has an increased propensity to aggregate into pancreatic islet amyloid deposits that contribute to β-cell mass depletion and development of type-2 diabetes by inducing oxidative stress and inflammation. Recent studies demonstrated that aggregated amylin also accumulates in brains of Alzheimer's disease (AD) patients, preponderantly those with type-2 diabetes. Here, we report that, in addition to amylin plaques and mixed amylin-Aβ deposits, brains of diabetic patients with AD show amylin immunoreactive deposits inside the neurons. Neuronal amylin formed adducts with 4-hydroxynonenal (4-HNE), a marker of peroxidative membrane injury, and increased synthesis of the proinflammatory cytokine interleukin (IL)-1β. These pathological changes were mirrored in rats expressing human amylin in pancreatic islets (HIP rats) and mice intravenously injected with aggregated human amylin, but not in hyperglycemic rats secreting wild-type non-amyloidogenic rat amylin. In cultured primary hippocampal rat neurons, aggregated amylin increased IL-1β synthesis via membrane destabilization and subsequent generation of 4-HNE. These effects were blocked by membrane stabilizers and lipid peroxidation inhibitors. Thus, elevated circulating levels of aggregated amylin negatively affect the neurons causing peroxidative membrane injury and aberrant inflammatory responses independent of other confounding factors of diabetes. The present results are consistent with the pathological role of aggregated amylin in the pancreas, demonstrate a novel contributing mechanism to neurodegeneration, and suggest a direct, potentially treatable link of type-2 diabetes with AD.

The Language Profile of Behavioral Variant Frontotemporal Dementia. - Hardy, Chris J D; Buckley, Aisling H; Downey, Laura E; Lehmann, Manja; Zimmerer, Vitor C; Varley, Rosemary A; Crutch, Sebastian J; Rohrer, Jonathan D; Warrington, Elizabeth K; Warren, Jason D (J Alzheimers Dis, 2016)
BACKGROUND: The language profile of behavioral variant frontotemporal dementia (bvFTD) remains to be fully defined. OBJECTIVE: We aimed to quantify the extent of language deficits in this patient group. METHODS: We assessed a cohort of patients with bvFTD (n = 24) in relation to patients with semantic variant primary progressive aphasia (svPPA; n = 14), nonfluent variant primary progressive aphasia (nfvPPA; n = 18), and healthy age-matched individuals (n = 24) cross-sectionally and longitudinally using a comprehensive battery of language and general neuropsychological tests. Neuroanatomical associations of language performance were assessed using voxel-based morphometry of patients' brain magnetic resonance images. RESULTS: Relative to healthy controls, and after accounting for nonverbal executive performance, patients with bvFTD showed deficits of noun and verb naming and single word comprehension, diminished spontaneous propositional speech, and deterioration in naming performance over time. Within the bvFTD group, patients with MAPT mutations had more severe impairments of noun naming and single word comprehension than patients with C9orf72 mutations. Overall the bvFTD group had less severe language deficits than patients with PPA, but showed a language profile that was qualitatively similar to svPPA. Neuroanatomical correlates of naming and word comprehension performance in bvFTD were identified predominantly in inferior frontal and antero-inferior temporal cortices within the dominant hemispheric language network. CONCLUSIONS: bvFTD is associated with a language profile including verbal semantic impairment that warrants further evaluation as a novel biomarker.
Keywords: Aged; Aphasia, Primary Progressive; Atrophy; Brain; Cognition; Comprehension; Female; Frontotemporal Dementia; Humans; Language; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia

Longitudinal Study of Impaired Intra- and Inter-Network Brain Connectivity in Subjects at High Risk for Alzheimer's Disease. - Zhan, Yafeng; Ma, Jianhua; Alexander-Bloch, Aaron F; Xu, Kaibin; Cui, Yue; Feng, Qianjin; Jiang, Tianzi; Liu, Yong (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is associated with abnormal resting-state network (RSN) architecture of the default mode network (DMN), the dorsal attention network (DAN), the executive control network (CON), the salience network (SAL), and the sensory-motor network (SMN). However, little is known about the disrupted intra- and inter-network architecture in mild cognitive impairment (MCI). Here, we employed a priori defined regions of interest to investigate the intra- and inter-network functional connectivity profiles of these RSNs in longitudinal participants, including normal controls (n = 23), participants with early MCI (n = 26), and participants with late MCI (n = 19). We found longitudinal alterations of functional connectivity within the DMN, where they were correlated with variation in cognitive ability. The SAL as well as the interaction between the DMN and the SAL were disrupted in MCI. Furthermore, our results demonstrate that longitudinal alterations of functional connectivity are more profound in earlier stages as opposed to later stages of the disease. The increased severity of cognitive impairment is associated with increasingly altered RSN connectivity patterns, suggesting that disruptions in functional connectivity may contribute to cognitive dysfunction and may represent a potential biomarker of impaired cognitive ability in MCI. Earlier prevention and treatment may help to delay disease progression to AD.

Lower Prevalence of Alzheimer's Disease among Tibetans: Association with Religious and Genetic Factors. - Huang, Fukai; Shang, Ying; Luo, Yuandai; Wu, Peng; Huang, Xue; Tan, Xiaohui; Lu, Xingyi; Zhen, Lifang; Hu, Xianda (J Alzheimers Dis, 2016)
BACKGROUND: The prevalence of dementia differs among racial groups, the highest prevalence being in Latin America (8.5%) compared to sub-Saharan African regions (2-4%). The most common type of dementia is Alzheimer's disease (AD). OBJECTIVE: To estimate the prevalence of AD in the Qinghai-Tibet plateau and to investigate the related factors. METHODS: This was a cross-sectional, multistage cluster sampling design survey. Data was collected from May 2014 to September 2014 from 4,060 Tibetan aged >60 years. Participants underwent clinical examinations and neuropsychological evaluations. MALDI-TOF was used to test the genotypes of CLU, TFAM, TP53INP1, IGHV1-67, CR1, ApoE, and BIN1. Logistic regression models were used to ascertain the associations with AD. RESULTS: The prevalence of AD among Tibetan individuals aged >60 years was 1.33% (95% CI: 0.98-1.69). The CLU haplotypes AA+GA (odds ratio (OR) = 4.483; 95% CI: 1.069-18.792) of rs2279590 was correlated with AD. The CLU haplotypes GG+GC (OR = 0.184; 95% CI: 0.038-0.888) of rs9331888 and kowtow (OR = 0.203; 95% CI 0.046-0.896) were negatively correlated with AD. CONCLUSION: A low prevalence of AD was found in Tibetans from the Qinghai-Tibet plateau. Multivariate analysis might suggest that regular "mind-body" religious meditative activities may be negatively associated with AD in this population, as well as the CLU genotype at rs9331888.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Clusterin; Cognition Disorders; Cross-Sectional Studies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Psychiatric Status Rating Scales; Religion; Risk Factors; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Tibet

M2 Macrophage Transplantation Ameliorates Cognitive Dysfunction in Amyloid-β-Treated Rats Through Regulation of Microglial Polarization. - Zhu, Dan; Yang, Nan; Liu, Yan-Yong; Zheng, Ji; Ji, Chao; Zuo, Ping-Ping (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most common neurodegenerative disorder in the elderly population. Neuroinflammation induced by amyloid-β (Aβ) aggregation is considered to be the critical factor underlying AD pathological mechanisms. Alternatively activated (M2) macrophages/microglia have been reported to have neuroprotective effects in neurodegenerative disease. In this study, we characterized the neuroprotective effects of M2 macrophage transplantation in AD model rats and investigated the underlying mechanisms. Intracerebroventricular injection of Aβ1 - 42 to rats was used to model AD and resulted in cognitive impairment, neuronal damage, and inflammatory changes in the brain microenvironment. We observed an increased interferon regulatory factor (IRF) 5/IRF4 ratio, resulting in greater production of classically activated (M1) versus M2 microglia. M2 macrophage transplantation attenuated inflammation in the brain, reversed Aβ1 - 42-induced changes in the IRF4-IRF5 ratio, drove endogenous microglial polarization toward the M2 phenotype, and ameliorated cognitive impairment. Nerve growth factor (NGF) treatment reduced the IRF5/IRF4 ratio and induced primary microglial polarization to the M2 phenotype in vitro; these effects were prevented by tyrosine Kinase Receptor A (TrkA) inhibition. M2 macrophage transplantation restored the balance of IRF4-IRF5 by affecting the expression of NGF and inflammatory cytokines in the brains of AD model rats. This drove microglial polarization to the M2 phenotype, promoted termination of neuroinflammation, and resulted in improved cognitive abilities.

Memory Binding Test Predicts Incident Amnestic Mild Cognitive Impairment. - Mowrey, Wenzhu B; Lipton, Richard B; Katz, Mindy J; Ramratan, Wendy S; Loewenstein, David A; Zimmerman, Molly E; Buschke, Herman (J Alzheimers Dis, 2016)
BACKGROUND: The Memory Binding Test (MBT), previously known as Memory Capacity Test, has demonstrated discriminative validity for distinguishing persons with amnestic mild cognitive impairment (aMCI) and dementia from cognitively normal elderly. OBJECTIVE: We aimed to assess the predictive validity of the MBT for incident aMCI. METHODS: In a longitudinal, community-based study of adults aged 70+, we administered the MBT to 246 cognitively normal elderly adults at baseline and followed them annually. Based on previous work, a subtle reduction in memory binding at baseline was defined by a Total Items in the Paired (TIP) condition score of ≤22 on the MBT. Cox proportional hazards models were used to assess the predictive validity of the MBT for incident aMCI accounting for the effects of covariates. The hazard ratio of incident aMCI was also assessed for different prediction time windows ranging from 4 to 7 years of follow-up, separately. RESULTS: Among 246 controls who were cognitively normal at baseline, 48 developed incident aMCI during follow-up. A baseline MBT reduction was associated with an increased risk for developing incident aMCI (hazard ratio (HR) = 2.44, 95% confidence interval: 1.30-4.56, p = 0.005). When varying the prediction window from 4-7 years, the MBT reduction remained significant for predicting incident aMCI (HR range: 2.33-3.12, p: 0.0007-0.04). CONCLUSION: Persons with poor performance on the MBT are at significantly greater risk for developing incident aMCI. High hazard ratios up to seven years of follow-up suggest that the MBT is sensitive to early disease.

Metabolic Syndrome and Mild Cognitive Impairment: A Case-Control Study among Elderly in a Shanghai Suburb. - Yao, Qian; Jiang, Guo-Xin; Zhou, Zhi-Ming; Chen, Jin-Mei; Cheng, Qi (J Alzheimers Dis, 2016)
BACKGROUND: Metabolic syndrome (MetS) maybe associated with mild cognitive impairment (MCI). OBJECTIVE: To investigate the relationship between MetS, with its individual or combined components, and MCI among elderly. METHODS: A case-control study was conducted among the elderly aged 65 years and over in a community located in the southwestern suburb of Shanghai, China. The Chinese version of the Mini-Mental Status Examination (C-MMSE) was used to screen subjects with MCI. Associations of MetS with its individual or combined components and MCI were analyzed using conditional regression analyses with or without adjustment for gender, education, current smoking, current drinking, and physical activities. RESULTS: There were 379 subjects with MCI and 379 gender- and age-matched healthy controls in the study. Compared with healthy controls in univariate analyses, subjects with MCI were more likely to have less time spent on physical activity, lower C-MMSE score, heavier weight, larger waistline and hipline, higher diastolic blood pressure, higher body mass index, higher abdominal obesity index, higher serum glycated hemoglobin, higher serum triglycerides, higher serum cholesterol, higher serum uric acid, and higher serum alanine aminotransferase. After multivariable adjustment, MetS was significantly associated with an increased risk of MCI (OR = 2.277; 95% CI: 1.086-4.773). Among MetS components, abdominal obesity (OR = 2.101; 95% CI: 1.224-3.608) and hypertension (OR = 2.075; 95% CI: 1.170-3.678) showed a significant association with MCI, respectively; while these two components were combined, the association was stronger (OR = 2.459; 95% CI: 1.360-4.447). CONCLUSION: MetS and its components, particularly abdominal obesity and hypertension, were found to be significantly associated with the risk of MCI.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Case-Control Studies; Chi-Square Distribution; China; Cities; Cognition Disorders; Community Health Planning; Female; Humans; Male; Mental Status Schedule; Metabolic Diseases; Risk Factors

Modulation of miR-19 in Aluminum-Induced Neural Cell Apoptosis. - Zhu, Mingming; Huang, Cong; Ma, Xiao; Wu, Rui; Zhu, Weiwei; Li, Xiaoting; Liang, Zhaofeng; Deng, Feifei; Zhu, Jianyun; Xie, Wei; Yang, Xue; Jiang, Ye; et al. (J Alzheimers Dis, 2016)
Neuronal cell death is an important feature of neurodegeneration. Aluminum is associated with neurodegenerative disorders, particularly Alzheimer's disease. However, the underlying mechanisms by which aluminum induces neuronal apoptosis remain to be elucidated. miR-19 is a key miRNA implicated in regulating cell survival process, while the role of miR-19 in Alzheimer's disease has not been investigated. In the present study, we showed that Aluminum maltolate (Al-malt), a lipophilic Al complex which is a common component of human diet with the ability to facilitate the entry of Al into the brain, induced apoptosis in human neuroblastoma SH-SY5Y cells, along with downregulation of miR-19a/miR-19b, upregulation of miR-19-targeted PTEN, and alterations of its downstream apoptosis related proteins including AKT, p53, Bax, and Bcl-2. miR-19 overexpression attenuated Al-malt-induced apoptosis as well as changes in the expression of apoptosis related proteins in SH-SY5Y cells. We further revealed that exposure of rats to Al-malt for 12 weeks at doses relevant to human exposure significantly elevated Al concentrations in serum and brain tissues. Al-malt dose-dependently induced apoptosis in rat brain, as evidenced by increased caspase activation and increased TUNEL staining. Consistent with in vitro results, Al-malt reduced miR-19 expression and altered the expression of apoptotic related proteins in rat brain. Taken together, our data suggest for the first time that miR-19 modulation is critically involved in Al-induced neural cell apoptosis. Findings from this study could provide new insight into the molecular mechanisms of Al-associated neurodegenerative pathogenesis.
Keywords: Aluminum; Animals; Apoptosis; Brain; Cell Line, Tumor; Dose-Response Relationship, Drug; Humans; Male; MicroRNAs; Neurons; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Rats, Sprague-Dawley; Tumor Suppressor Protein p53

Monitoring Blood-Brain Barrier Integrity Following Amyloid-β Immunotherapy Using Gadolinium-Enhanced MRI in a PDAPP Mouse Model. - Blockx, Ines; Einstein, Steve; Guns, Pieter-Jan; Van Audekerke, Johan; Guglielmetti, Caroline; Zago, Wagner; Roose, Dimitri; Verhoye, Marleen; Van der Linden, Annemie; Bard, Frederique (J Alzheimers Dis, 2016)
BACKGROUND: Amyloid-related imaging abnormalities (ARIA) have been reported with some anti-amyloid-β (Aβ) immunotherapy trials. They are detected with magnetic resonance imaging (MRI) and thought to represent transient accumulation of fluid/edema (ARIA-E) or microhemorrhages (ARIA-H). Although the clinical significance and pathophysiology are unknown, it has been proposed that anti-Aβimmunotherapy may affect blood-brain barrier (BBB) integrity. OBJECTIVE: To examine vascular integrity in aged (12-16 months) PDAPP and wild type mice (WT), we performed a series of longitudinal in vivo MRI studies. METHODS: Mice were treated on a weekly basis using anti-Aβimmunotherapy (3D6) and follow up was done longitudinally from 1-12 weeks after treatment. BBB-integrity was assessed using both visual assessment of T1-weighted scans and repeated T1 mapping in combination with gadolinium (Gd-DOTA). RESULTS: A subset of 3D6 treated PDAPP mice displayed numerous BBB disruptions, whereas WT and saline-treated PDAPP mice showed intact BBB integrity under the conditions tested. In addition, the contrast induced decrease in T1 value was observed in the meningeal and midline area. BBB disruption events occurred early during treatment (between 1 and 5 weeks), were transient, and resolved quickly. Finally, BBB-leakages associated with microhemorrhages were confirmed by Perls'Prussian blue histopathological analysis. CONCLUSION: Our preclinical findings support the hypothesis that 3D6 leads to transient leakage from amyloid-positive vessels. The current study has provided valuable insights on the time course of vascular alterations during immunization treatment and supports further research in relation to the nature of ARIA and the utility of in vivo repeated T1 MRI as a translational tool.

Morroniside-Induced PP2A Activation Antagonizes Tau Hyperphosphorylation in a Cellular Model of Neurodegeneration. - Yang, Cui-cui; Kuai, Xue-xian; Gao, Wen-bin; Yu, Jian-chun; Wang, Qi; Li, Lin; Zhang, Lan (J Alzheimers Dis, 2016)
BACKGROUND: An accumulation of hyperphosphorylated tau in the brain is a hallmark of Alzheimer's disease (AD). Deficits in protein phosphatase 2A (PP2A) are associated with tau hyperphosphorylation in AD. OBJECTIVE: To investigate the effects of morroniside (MOR), isolated from Cornus officinalis, on tau hyperphosphorylation and its underlying mechanisms related to PP2A. METHODS: SK-N-SH cells were pretreated with 50-200 μM MOR for 24 h followed by 20 nM okadaic acid (OA) for 6 h. PP2Ac siRNA was transfected into HEK293 cells to determine the direct interaction of MOR with PP2A. Western blotting was used to measure the expression of proteins and enzymes. PP2A activity was measured by molybdenum blue spectrophotometry. RESULTS: Pretreatment with MOR improved the cellular morphological damage and inhibited tau hyperphosphorylation in SK-N-SH cells induced by OA, a PP2A inhibitor. Moreover, MOR increased PP2A activity, concurrent with a decrease in the expression of demethylated PP2A at Leu309 and phosphorylated PP2A at Tyr307. MOR decreased protein phosphatase methylesterase 1 (PME-1) expression and the ratio of PME-1/leucine carboxyl methyltransferase 1 (LCMT-1). Furthermore, MOR treatment decreased the phosphorylation of Src at Tyr416, which regulates the phosphorylation of PP2A. MOR had no effect on PP2Ac expression and tau hyperphosphorylation in PP2Ac siRNA-transfected cells. CONCLUSION: MOR attenuated OA-induced tau hyperphosphorylation via PP2A activation, and its mechanism might be related to the regulation of PP2Ac post-translational modification and upstream enzymes such as Src and PME-1.
Keywords: Analysis of Variance; Cell Line; Enzyme Inhibitors; Gene Expression Regulation; Glycogen Synthase Kinase 3 beta; Glycosides; HEK293 Cells; Humans; Neuroblastoma; Okadaic Acid; Phosphorylation; Protein Phosphatase 2; RNA, Small Interfering; tau Proteins; Transfection; Tyrosine

Multimodal Classification of Mild Cognitive Impairment Based on Partial Least Squares. - Wang, Pingyue; Chen, Kewei; Yao, Li; Hu, Bin; Wu, Xia; Zhang, Jiacai; Ye, Qing; Guo, Xiaojuan (J Alzheimers Dis, 2016)
In recent years, increasing attention has been given to the identification of the conversion of mild cognitive impairment (MCI) to Alzheimer's disease (AD). Brain neuroimaging techniques have been widely used to support the classification or prediction of MCI. The present study combined magnetic resonance imaging (MRI), 18F-fluorodeoxyglucose PET (FDG-PET), and 18F-florbetapir PET (florbetapir-PET) to discriminate MCI converters (MCI-c, individuals with MCI who convert to AD) from MCI non-converters (MCI-nc, individuals with MCI who have not converted to AD in the follow-up period) based on the partial least squares (PLS) method. Two types of PLS models (informed PLS and agnostic PLS) were built based on 64 MCI-c and 65 MCI-nc from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database. The results showed that the three-modality informed PLS model achieved better classification accuracy of 81.40%, sensitivity of 79.69%, and specificity of 83.08% compared with the single-modality model, and the three-modality agnostic PLS model also achieved better classification compared with the two-modality model. Moreover, combining the three modalities with clinical test score (ADAS-cog), the agnostic PLS model (independent data: florbetapir-PET; dependent data: FDG-PET and MRI) achieved optimal accuracy of 86.05%, sensitivity of 81.25%, and specificity of 90.77%. In addition, the comparison of PLS, support vector machine (SVM), and random forest (RF) showed greater diagnostic power of PLS. These results suggested that our multimodal PLS model has the potential to discriminate MCI-c from the MCI-nc and may therefore be helpful in the early diagnosis of AD.

Netrin-1 Interrupts Amyloid-β Amplification, Increases sAβPPα in vitro and in vivo, and Improves Cognition in a Mouse Model of Alzheimer's Disease. - Spilman, Patricia R; Corset, Veronique; Gorostiza, Olivia; Poksay, Karen S; Galvan, Veronica; Zhang, Junli; Rao, Rammohan; Peters-Libeu, Clare; Vincelette, Jon; McGeehan, Andrew; Dvorak-Ewell, Melita; Beyer, Janine; et al. (J Alzheimers Dis, 2016)
Recent studies have shown that inoculation of susceptible mice with amyloid-β (Aβ) peptides accelerates Aβ deposition in the brain, supporting the idea that Aβ may be self-amplifying; however, the exact mechanism is not understood. Here we provide evidence that Aβ may self-amplify, in part, by inhibiting α-secretase ADAM10 (a disintegrin and metalloprotease) cleavage of full-length Aβ precursor protein (FL AβPP) and therefore allow greater β-secretase processing, and that Aβ itself is a substrate for ADAM10. Exposure of primary neuronal cultures from PDAβPP mice to exogenous rat Aβ1- 40 resulted in increased de novo human Aβ1-42 production and exposure of cells to Aβ decreased production of ADAM10 cleavage product soluble AβPPα (sAβPPα). In a cell-free assay, Aβ decreased ADAM10 cleavage of the chimeric substrate MBP-AβPPC125 and Aβ itself was apparently cleaved by the enzyme. The axonal guidance and trophic factor netrin-1, however, reduced the Aβ1- 40-induced Aβ1-42 increase, increased sAβPPα, and reversed the Aβ-induced sAβPPα decrease in vitro. In vivo, induction of netrin-1 expression in PDAβPPSwe/Ind transgenic mice resulted in reductions in both Aβ1-42 and Aβ1- 40, and ICV delivery of netrin-1 to PDAβPPSwe/Ind mice increased sAβPPα, decreased Aβ, and improved working memory. Finally, to support further study of netrin-1's potential as a therapeutic for Alzheimer's disease, pilot gene therapy studies were performed and a netrin mimetic peptide synthesized and tested that, like netrin, can increase sAβPPα and decrease Aβ1-42in vitro. Taken together, these data provide mechanistic insights into Aβ self-amplification and the ability of netrin-1 to disrupt it.

Neurodegeneration-Like Pathological and Behavioral Changes in an AAV9-Mediated p25 Overexpression Mouse Model. - Zhou, Xiao; Huang, Jianou; Pan, Suyue; Xu, Miaojing; He, Rongni; Ji, Zhong; Hu, Yafang (J Alzheimers Dis, 2016)
BACKGROUND: The transgenic mice models overexpressing human p25 contribute greatly to the in vivo neurotoxic mechanism of p25 in neurodegenerative diseases. However, it is time-consuming to manipulate existing transgenic mice models. OBJECTIVE: Here we aim to establish a novel mouse model of neurodegeneration by overexpressing p25 mediated by recombinant adeno-associated virus serotype 9 (rAAV9). METHODS: AAV9-GFP-p25 encoding GFP-fused p25 driven by synapsin promoter, and the control, AAV9-GFP, were delivered in mice by tail-vein injection. Assessments of p25 expression, neurodegenerative pathology, and behavioral changes were performed. RESULTS: GFP expression was detected by in vivo imaging as early as one week after virus injection. Notably, widespread expression of p25 was obviously found in cortex, hippocampus, and cerebellum in AAV9-GFP-p25 mice. Moreover, decreased hippocampus volumes in AAV9-GFP-p25 mice were detected by 7T MRI examination about one month after injection. Further, these AAV9-GFP-p25 mice exhibited progressive memory impairment from three-month to six-month after virus injection. At last, hyperphosphorylated tau, neurofibrillary tangles, activated astrocytes and microglia cells were elevated in these p25 mice at about six months after virus delivery. However, amyloid-β plaques, overt neuronal loss, and apoptosis in the hippocampus and cortex were not significantly induced by AAV9-mediated p25 overexpression. CONCLUSION: The AAV9-mediated p25 overexpression mouse model, which is a practical model exhibiting neurodegeneration-like pathological and behavioral changes, provides an easier and time-saving method to explore the functions of p25 in vivo, as well as an alternative tool for development of drugs against neurotoxic of p25.

Novel Selective Calpain 1 Inhibitors as Potential Therapeutics in Alzheimer's Disease. - Fà, Mauro; Zhang, Hong; Staniszewski, Agnieszka; Saeed, Faisal; Shen, Li W; Schiefer, Isaac T; Siklos, Marton I; Tapadar, Subhasish; Litosh, Vladislav A; Libien, Jenny; Petukhov, Pavel A; Teich, Andrew F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease, one of the most important brain pathologies associated with neurodegenerative processes, is related to overactivation of calpain-mediated proteolysis. Previous data showed a compelling efficacy of calpain inhibition against abnormal synaptic plasticity and memory produced by the excess of amyloid-β, a distinctive marker of the disease. Moreover, a beneficial effect of calpain inhibitors in Alzheimer's disease is predictable by the occurrence of calpain hyperactivation leading to impairment of memory-related pathways following abnormal calcium influxes that might ensue independently of amyloid-β elevation. However, molecules currently available as effective calpain inhibitors lack adequate selectivity. This work is aimed at characterizing the efficacy of a novel class of epoxide-based inhibitors, synthesized to display improved selectivity and potency towards calpain 1 compared to the prototype epoxide-based generic calpain inhibitor E64. Both functional and preliminary toxicological investigations proved the efficacy, potency, and safety of the novel and selective calpain inhibitors NYC438 and NYC488 as possible therapeutics against the disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cysteine Proteinase Inhibitors; Disease Models, Animal; Dose-Response Relationship, Drug; Fear; Glycoproteins; Hippocampus; Humans; In Vitro Techniques; Long-Term Potentiation; Maze Learning; Memory; Mice; Mice, Inbred ICR; Mice, Transgenic; Mutation; Patch-Clamp Techniques; Peptide Fragments; Presenilin-1; Spectrin

A Novel Splice-Acceptor Site Mutation in GRN (c.709-2 A>T) Causes Frontotemporal Dementia Spectrum in a Large Family from Southern Italy. - Sassi, Celeste; Capozzo, Rosa; Gibbs, Raphael; Crews, Cynthia; Zecca, Chiara; Arcuti, Simona; Copetti, Massimiliano; Barulli, Maria R; Brescia, Vincenzo; Singleton, Andrew B; Logroscino, Giancarlo (J Alzheimers Dis, 2016)
Heterozygous loss of function mutations in granulin represent a significant cause of frontotemporal lobar degeneration with ubiquitin and TDP-43 inclusions (FTLD-TDP). We report a novel GRN splice site mutation (c.709-2 A>T), segregating with frontotemporal dementia spectrum in a large family from southern Italy. The GRN c.709-2 A>T is predicted to result in the skipping of exon 8, leading to non-sense mediated mRNA decay. Moreover, the PGRN plasma levels in the GRN c.709-2 A>T carriers were significantly lower (24 ng/ml) compared to controls (142.7 ng/ml) or family members non-carriers (82.0 ng/ml) (p-value = 0.005, Kruskal Wallis), suggesting progranulin haploinsufficiency. We do not report any potential pathogenic GRN mutation in a follow-up cohort composed of 6 FTD families and 43 sporadic FTD cases, from the same geographic area. Our study suggests that GRN (c.709-2 A>T) is a novel and likely very rare cause of FTD in this Italian cohort. Finally, in line with previous studies, we show that GRN haploinsufficiency leads to a heterogeneous clinical picture, and plasma progranulin levels may be a reliable tool to identify GRN loss of function mutations. However, given that a) genetic and environmental factors, gender, and age may regulate PGRN plasma levels and b) plasma progranulin levels may not reflect PGRN levels in the central nervous system, we suggest that the measurement of progranulin in the plasma should always be coupled with genetic screening of GRN for mutations.

Partial Amelioration of Synaptic and Cognitive Deficits by Inhibiting Cofilin Dephosphorylation in an Animal Model of Alzheimer's Disease. - Deng, Yulei; Wei, Jing; Cheng, Jia; Zhong, Ping; Xiong, Zhe; Liu, Aiyi; Lin, Lin; Chen, Shengdi; Yan, Zhen (J Alzheimers Dis, 2016)
The loss of synaptic structure and function has been linked to the cognitive impairment of Alzheimer's disease (AD). Dysregulation of the actin cytoskeleton, which plays a key role in regulating the integrity of synapses and the transport of synaptic proteins, has been suggested to contribute to the pathology of AD. In this study, we found that glutamate receptor surface expression and synaptic function in frontal cortical neurons were significant diminished in a familial AD (FAD) model, which was correlated with the reduction of phosphorylated cofilin, a key protein regulating the dynamics of actin filaments. Injecting a cofilin dephosphorylation inhibitory peptide to FAD mice led to the partial rescue of the surface expression of AMPA and NMDA receptor subunits, as well as the partial restoration of AMPAR- and NMDAR-mediated synaptic currents. Moreover, the impaired working memory and novel object recognition memory in FAD mice were partially ameliorated by injections of the cofilin dephosphorylation inhibitory peptide. These results suggest that targeting the cofilin-actin signaling holds promise to mitigate the physiological and behavioral abnormality in AD.

Plasma Ceramides and Neuropsychiatric Symptoms of Alzheimer's Disease. - Xing, Yi; Tang, Yi; Zhao, Lina; Wang, Qi; Qin, Wei; Zhang, Jin-Lan; Jia, Jianping (J Alzheimers Dis, 2016)
BACKGROUND: Various evidence demonstrates the influences of ceramides on Alzheimer's disease (AD) pathogenesis. Furthermore, increased ceramides were also suggested to be related to cognitive decline. However, the association between ceramides and neuropsychiatric symptoms of AD remains unclear. OBJECTIVE: This study sought to investigate the association between plasma ceramide levels and multiple neuropsychiatric symptoms in AD. METHODS: A total of 98 patients and 92 cognitively normal controls participated in this study, including 56 with mild AD and 42 with moderate to severe AD. The Neuropsychiatric Inventory (NPI) was used to assess neuropsychiatric symptoms. Considering the influences of dementia severity on ceramide levels and neuropsychiatric symptoms, a subgroup analysis was conducted by dementia severity. RESULTS: Except for C24 : 0, all ceramide species were significantly higher in AD patients than in controls. After controlling for confounding factors, the C16 : 0 and C20 : 0 levels were positively associated with delusions, and the quartiles of C22 : 0 and C24 : 0 were positively associated with depression. In the subgroup analysis, association between ceramide species and delusions were only observed in mild AD, and the association between ceramides and depression were prominent in moderate to severe AD. In mild AD, after controlling for age, gender, anti-dementia medications, diabetes status, and ApoE ɛ4 status, the C16 : 0, C20 : 0, and quartiles of C24 : 1 were associated with delusions. In moderate to severe AD, depression was associated with C22 : 0 and C24 : 0. CONCLUSION: There were stage-specific associations between ceramides and neuropsychiatric symptoms of AD. The potential mechanisms deserve further investigation.

Prediction of Progressive Mild Cognitive Impairment by Multi-Modal Neuroimaging Biomarkers. - Xu, Lele; Wu, Xia; Li, Rui; Chen, Kewei; Long, Zhiying; Zhang, Jiacai; Guo, Xiaojuan; Yao, Li (J Alzheimers Dis, 2016)
For patients with mild cognitive impairment (MCI), the likelihood of progression to probable Alzheimer's disease (AD) is important not only for individual patient care, but also for the identification of participants in clinical trial, so as to provide early interventions. Biomarkers based on various neuroimaging modalities could offer complementary information regarding different aspects of disease progression. The current study adopted a weighted multi-modality sparse representation-based classification method to combine data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, from three imaging modalities: Volumetric magnetic resonance imaging (MRI), fluorodeoxyglucose (FDG) positron emission tomography (PET), and florbetapir PET. We included 117 normal controls (NC) and 110 MCI patients, 27 of whom progressed to AD within 36 months (pMCI), while the remaining 83 remained stable (sMCI) over the same time period. Modality-specific biomarkers were identified to distinguish MCI from NC and to predict pMCI among MCI. These included the hippocampus, amygdala, middle temporal and inferior temporal regions for MRI, the posterior cingulum, precentral, and postcentral regions for FDG-PET, and the hippocampus, amygdala, and putamen for florbetapir PET. Results indicated that FDG-PET may be a more effective modality in discriminating MCI from NC and in predicting pMCI than florbetapir PET and MRI. Combining modality-specific sensitive biomarkers from the three modalities boosted the discrimination accuracy of MCI from NC (76.7%) and the prediction accuracy of pMCI (82.5%) when compared with the best single-modality results (73.6% for MCI and 75.6% for pMCI with FDG-PET).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognitive Dysfunction; Disease Progression; Ethylene Glycols; Female; Fluorodeoxyglucose F18; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Predictive Value of Tests; Psychiatric Status Rating Scales; Sensitivity and Specificity

Preliminary Study of Plasma Exosomal Tau as a Potential Biomarker for Chronic Traumatic Encephalopathy. - Stern, Robert A; Tripodis, Yorghos; Baugh, Christine M; Fritts, Nathan G; Martin, Brett M; Chaisson, Christine; Cantu, Robert C; Joyce, James A; Shah, Sahil; Ikezu, Tsuneya; Zhang, Jing; Gercel-Taylor, Cicek; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Chronic traumatic encephalopathy (CTE) is a tauopathy associated with prior exposure to repetitive head impacts, such as those incurred through American football and other collision sports. Diagnosis is made through neuropathological examination. Many of the clinical features of CTE are common in the general population, with and without a history of head impact exposure, making clinical diagnosis difficult. As is now common in the diagnosis of other neurodegenerative disorders, such as Alzheimer's disease, there is a need for methods to diagnose CTE during life through objective biomarkers. OBJECTIVE: The aim of this study was to examine tau-positive exosomes in plasma as a potential CTE biomarker. METHODS: Subjects were 78 former National Football League (NFL) players and 16 controls. Extracellular vesicles were isolated from plasma. Fluorescent nanoparticle tracking analysis was used to determine the number of vesicles staining positive for tau. RESULTS: The NFL group had higher exosomal tau than the control group (p <  0.0001). Exosomal tau discriminated between the groups, with 82% sensitivity, 100% specificity, 100% positive predictive value, and 53% negative predictive value. Within the NFL group, higher exosomal tau was associated with worse performance on tests of memory (p = 0.0126) and psychomotor speed (p = 0.0093). CONCLUSION: These preliminary findings suggest that exosomal tau in plasma may be an accurate, noninvasive CTE biomarker.
Keywords: Adult; Aged; Analysis of Variance; Case-Control Studies; Chronic Traumatic Encephalopathy; Extracellular Vesicles; Humans; Male; Middle Aged; Plasma; tau Proteins

Prevalence and Risk Factor of Cognitive Impairment were Different between Urban and Rural Population: A Community-Based Study. - Tang, Hui-Dong; Zhou, Yi; Gao, Xiang; Liang, Liang; Hou, Miao-Miao; Qiao, Yuan; Ma, Jian-Fang; Chen, Sheng-Di (J Alzheimers Dis, 2016)
BACKGROUND: China is facing a continuously rising numbers of people with cognitive impairment (CI). OBJECTIVES: To investigate the prevalence and risk factors of CI among elderly people living in rural and urban communities. METHODS: We conducted a face-to-face survey of CI on 7,900 individuals aged 50 years or older meeting inclusion criteria in the Malu (rural community, n = 4,429) and Wuliqiao (urban community, n = 3,471) communities of Shanghai. The Mini-Mental State Examination (MMSE) was used to evaluate the cognitive function. Information on demographic features and potential risk factors for CI was collected during the interview. Multivariate logistic regression was performed to identify risk factors associated with CI. RESULTS: Based on the education modified MMSE score, we identified 329 CI cases in rural community and 227 in urban community. The prevalence of CI was 7.43% in rural population and 6.54% in urban population (p = 0.13). In the urban population, risk of having CI was associated with age (OR = 1.04; 95% CI: 1.01-1.08), lack of physical activities (OR = 2.25; 95% CI: 1.11-4.57), presence of diabetes mellitus (OR = 1.79; 95% CI: 1.04-3.07), and having three or more children (OR = 2.39; 95% CI: 1.27-4.50). In contrast, factors associated with rural populations included female gender (OR = 2.03; 95% CI: 1.08-3.82), age (OR = 1.06; 95% CI: 1.03-1.08), exposure to pesticides (OR = 4.68; 95% CI: 1.27-17.21), history of encephalitis or meningitis (OR = 6.02; 95% CI: 1.92-18.85) and head trauma (OR = 1.89; 95% CI: 1.10-3.24). CONCLUSIONS: Urban rural and populations showed different risk factors for CI, suggesting that different preventive strategies in these areas should be performed.
Keywords: Aged; Aged, 80 and over; China; Cognition Disorders; Female; Humans; Logistic Models; Male; Mental Status Schedule; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Rural Population; Urban Population

Puerarin Ameliorates D-Galactose Induced Enhanced Hippocampal Neurogenesis and Tau Hyperphosphorylation in Rat Brain. - Hong, Xiao-Ping; Chen, Tao; Yin, Ni-Na; Han, Yong-Ming; Yuan, Fang; Duan, Yan-Jun; Shen, Feng; Zhang, Yan-Hong; Chen, Ze-Bin (J Alzheimers Dis, 2016)
Enhanced neurogenesis has been reported in the hippocampus of patients with Alzheimer's disease (AD), the most common neurodegenerative disorder characterized with amyloid-β (Aβ) aggregation, tau hyperphosphorylation, and progressive neuronal loss. Previously we reported that tau phosphorylation played an essential role in adult hippocampal neurogenesis, and activation of glycogen synthase kinase (GSK-3), a crucial tau kinase, could induce increased hippocampal neurogenesis. In the present study, we found that treatment of D-galactose rats with Puerarin could significantly improve behavioral performance and ameliorate the enhanced neurogenesis and microtubule-associated protein tau hyperphosphorylation in the hippocampus of D-galactose rat brains. FGF-2/GSK-3 signaling pathway might be involved in the effects of Puerarin on hippocampal neurogenesis and tau hyperphosphorylation. Our finding provides primary in vivo evidence that Puerarin can attenuate AD-like enhanced hippocampal neurogenesis and tau hyperphosphorylation. Our finding also suggests Puerarin can be served as a treatment for age-related neurodegenerative disorders, such as AD.
Keywords: Animals; Cognition Disorders; Disease Models, Animal; Fibroblast Growth Factor 2; Galactose; Glycogen Synthase Kinase 3; Hippocampus; Isoflavones; Male; Maze Learning; Neurogenesis; Neurons; Neuroprotective Agents; Phosphorylation; Random Allocation; Rats, Sprague-Dawley; Signal Transduction; Spatial Memory; tau Proteins

Reduction of Blood Amyloid-β Oligomers in Alzheimer's Disease Transgenic Mice by c-Abl Kinase Inhibition. - Estrada, Lisbell D; Chamorro, David; Yañez, María José; Gonzalez, Marcelo; Leal, Nancy; von Bernhardi, Rommy; Dulcey, Andrés E; Marugan, Juan; Ferrer, Marc; Soto, Claudio; Zanlungo, Silvana; Inestrosa, Nibaldo C; et al. (J Alzheimers Dis, 2016)
One of the pathological hallmarks of Alzheimer's disease (AD) is the presence of amyloid plaques, which are deposits of misfolded and aggregated amyloid-beta peptide (Aβ). The role of the c-Abl tyrosine kinase in Aβ-mediated neurodegeneration has been previously reported. Here, we investigated the therapeutic potential of inhibiting c-Abl using imatinib. We developed a novel method, based on a technique used to detect prions (PMCA), to measure minute amounts of misfolded-Aβ in the blood of AD transgenic mice. We found that imatinib reduces Aβ-oligomers in plasma, which correlates with a reduction of AD brain features such as plaques and oligomers accumulation, neuroinflammation, and cognitive deficits. Cells exposed to imatinib and c-Abl KO mice display decreased levels of β-CTF fragments, suggesting that an altered processing of the amyloid-beta protein precursor is the most probable mechanism behind imatinib effects. Our findings support the role of c-Abl in Aβ accumulation and AD, and propose AD-PMCA as a new tool to evaluate AD progression and screening for drug candidates.

Reproductive history and risk of cognitive impairment in elderly women: a cross-sectional study in eastern China. - Li, Fu-Dong; He, Fan; Chen, Ting-Rui; Xiao, Yuan-Yuan; Lin, Shang-Tong; Shen, Wei; Wang, Xin-Yi; Zhai, Yu-Jia; Shang, Xiao-Peng; Lin, Jun-Fen (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies suggest that proxies of higher lifetime estrogen exposure are associated with better cognitive function in postmenopausal women, but this has not been found consistently. OBJECTIVE: To determine whether reproductive history, an important modifier of estrogen exposure across the lifetime, is associated with risk of cognitive impairment in postmenopausal women. METHODS: We analyzed the baseline data from Zhejiang Major Public Health Surveillance Program (ZPHS) including 4,796 postmenopausal women. Cognitive impairment was assessed through the application of Mini-Mental State Examination questionnaire. Logistic regression models, controlled for an extensive range of potential confounders, were generated to examine the associations between women's reproductive history and risk of cognitive impairment in their later life. RESULTS: The length of reproductive period was inversely associated with risk of cognitive impairment (p = 0.001). Odds ratio (OR) of cognitive impairment were 1.316 (95% CI 1.095∼1.582) for women with 5 or more times of full-term pregnancies, compared with those with 1∼4 times of full-term pregnancies. Women without incomplete pregnancy had a significant higher risk of cognitive impairment (OR = 1.194, 95% CI 1.000∼1.429), compared with the reference (1∼2 times of incomplete pregnancies). Oral contraceptive use (OR = 0.489, 95% CI 0.263∼0.910) and intrauterine device (IUD) use (OR = 0.684, 95% CI 0.575∼0.815) were associated with significantly reduced risk of cognitive impairment. CONCLUSION: Our results indicated that shorter reproductive period, higher number of full-term pregnancies and no incomplete pregnancy history were associated with an increased risk of cognitive impairment. In contrast, oral contraceptive and IUD use corresponded to reduced risk of cognitive impairment.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognition Disorders; Contraceptives, Oral; Cross-Sectional Studies; Estrogens; Female; Humans; Intrauterine Devices; Logistic Models; Middle Aged; Neuropsychological Tests; Odds Ratio; Postmenopause; Psychiatric Status Rating Scales; Reproductive History

The Role of Cerebrospinal Fluid Biomarkers in the Evolution of Diagnostic Criteria in Alzheimer's Disease: Shortcomings in Prodromal Diagnosis. - Szalárdy, Levente; Zádori, Dénes; Klivenyi, Peter; Vecsei, Laszlo (J Alzheimers Dis, 2016)
The available evidence indicates a high performance of core cerebrospinal fluid (CSF) biomarkers in differentiating between Alzheimer's disease (AD) and other dementias, and suggests that their characteristic alterations can be detected even at the prodromal stage of AD. On this basis, the ability of core CSF biomarkers to identify prodromal AD patients from pre-dementia of all causes can be postulated, a concept that is reflected in recent revisions of AD research criteria and a consensus statement. Following an overview on the role of biomarkers in the evolution of diagnostic criteria of AD in recent decades, this paper provides a critical review of the widely applied CSF biomarker study designs and evaluating approaches that address the ability of core CSF biomarkers to diagnose prodromal AD, with special focus on their potential limitations in terms of clinical interpretation and utility. The findings together raise the question of whether we are indeed able to establish a CSF biomarker-based diagnosis of AD at the prodromal stage.

Serum Uric Acid and Its Association with Longitudinal Cognitive Change Among Urban Adults. - Beydoun, May A; Canas, Jose-Atilio; Dore, Gregory A; Beydoun, Hind A; Rostant, Ola S; Fanelli-Kuczmarski, Marie T; Evans, Michele K; Zonderman, Alan B (J Alzheimers Dis, 2016)
Uric acid, a waste metabolite among humans, was linked to various cognitive outcomes. We describe sex and age-group specific associations of baseline serum uric acid (SUAbase) and significant change in SUA (ΔSUA: 1 versus 0 = decrease versus no change; 2 versus 0 = increase versus no change) with longitudinal annual rate of cognitive change among a large sample of urban adults. Data from the Healthy Aging in Neighborhoods of Diversity across the Life Span study, 2004-2009 (visit 1) and 2009-2013 (visit 2) were used. Of 3,720 adults selected at baseline (age range: 30-64 y), complete data were available for N = 1,487-1,602 with a mean repeat of 1.5-1.7 visits/participant. Cognitive test domains spanned attention, processing speed, learning/memory, executive function, visuo-spatial/visuo-construction ability, language/verbal, and global cognitive function. SUA was measured at both visits. Multiple mixed-effects regression analyses were conducted. In the total population, a higher SUAbase was associated with a faster annual rate of decline on a measure of visual memory/visuo-construction ability (the Benton Visual Retention Test) by γ= 0.07 with a standard error of 0.02, p < 0.001. Among older men, a significant increase in SUA was associated with slower decline on a test of attention/processing speed, namely Trailmaking test, Part A, measured in seconds to completion (γ= -6.91 ± 1.73, p < 0.001). In sum, a higher SUAbase was associated with faster cognitive decline over-time in a visual memory/visuo-construction ability test. ΔSUA had particular beneficial effects of an increasing ΔSUA on the domain of attention/processing speed among older men. More longitudinal studies are needed to examine cognitive domain-specific effects of over-time change in SUA within sex and age groups.

Shared Genetic Risk Factors for Late-Life Depression and Alzheimer's Disease. - Ye, Qing; Bai, Feng; Zhang, Zhijun (J Alzheimers Dis, 2016)
BACKGROUND: Considerable evidence has been reported for the comorbidity between late-life depression (LLD) and Alzheimer's disease (AD), both of which are very common in the general elderly population and represent a large burden on the health of the elderly. The pathophysiological mechanisms underlying the link between LLD and AD are poorly understood. Because both LLD and AD can be heritable and are influenced by multiple risk genes, shared genetic risk factors between LLD and AD may exist. OBJECTIVE: The objective is to review the existing evidence for genetic risk factors that are common to LLD and AD and to outline the biological substrates proposed to mediate this association. METHODS: A literature review was performed. RESULTS: Genetic polymorphisms of brain-derived neurotrophic factor, apolipoprotein E, interleukin 1-beta, and methylenetetrahydrofolate reductase have been demonstrated to confer increased risk to both LLD and AD by studies examining either LLD or AD patients. These results contribute to the understanding of pathophysiological mechanisms that are common to both of these disorders, including deficits in nerve growth factors, inflammatory changes, and dysregulation mechanisms involving lipoprotein and folate. Other conflicting results have also been reviewed, and few studies have investigated the effects of the described polymorphisms on both LLD and AD. CONCLUSION: The findings suggest that common genetic pathways may underlie LLD and AD comorbidity. Studies to evaluate the genetic relationship between LLD and AD may provide insights into the molecular mechanisms that trigger disease progression as the population ages.
Keywords: Age of Onset; Alzheimer Disease; Animals; Depressive Disorder; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors

Specific Triazine Herbicides Induce Amyloid-β42 Production. - Portelius, Erik; Durieu, Emilie; Bodin, Marion; Cam, Morgane; Pannee, Josef; Leuxe, Charlotte; Mabondzo, Aloϊse; Oumata, Nassima; Galons, Hervé; Lee, Jung Yeol; Chang, Young-Tae; Stϋber, Kathrin; et al. (J Alzheimers Dis, 2016)
Proteolytic cleavage of the amyloid-β protein precursor (AβPP) by secretases leads to extracellular release of amyloid-β (Aβ) peptides. Increased production of Aβ42 over Aβ40 and aggregation into oligomers and plaques constitute an Alzheimer's disease (AD) hallmark. Identifying products of the 'human chemical exposome' (HCE) able to induce Aβ42 production may be a key to understanding some of the initiating causes of AD and to generate non-genetic, chemically-induced AD animal models. A cell model was used to screen HCE libraries for Aβ42 inducers. Out of 3500+ compounds, six triazine herbicides were found that induced a β- and γ-secretases-dependent, 2-10 fold increase in the production of extracellular Aβ42 in various cell lines, primary neuronal cells, and neurons differentiated from human-induced pluripotent stem cells (iPSCs). Immunoprecipitation/mass spectrometry analyses show enhanced production of Aβ peptides cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and lower, a characteristic of AD. Neurons derived from iPSCs obtained from a familial AD (FAD) patient (AβPP K724N) produced more Aβ42 versus Aβ40 than neurons derived from healthy controls iPSCs (AβPP WT). Triazines enhanced Aβ42 production in both control and AD iPSCs-derived neurons. Triazines also shifted the cleavage pattern of alcadeinα, another γ-secretase substrate, suggesting a direct effect of triazines on γ-secretase activity. In conclusion, several widely used triazines enhance the production of toxic, aggregation prone Aβ42/Aβ43 amyloids, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in late-onset AD.

Staging Alzheimer's Disease Risk by Sequencing Brain Function and Structure, Cerebrospinal Fluid, and Cognition Biomarkers. - Chen, Guangyu; Shu, Hao; Chen, Gang; Ward, B Douglas; Antuono, Piero G; Zhang, Zhijun; Li, Shi-Jiang (J Alzheimers Dis, 2016)
This study aims to develop a composite biomarker that can accurately measure the sequential biological stages of Alzheimer's disease (AD) on an individual level. We selected 144 subjects from the Alzheimer's Disease Neuroimaging Initiative 2 datasets. Ten biomarkers, from brain function and structure, cerebrospinal fluid, and cognitive performance, were integrated using the event-based probabilistic model to estimate their optimal temporal sequence (Soptimal). We identified the numerical order of the Soptimal as the characterizing Alzheimer's disease risk events (CARE) index to measure disease stage. The results show that, in the Soptimal, hippocampal and posterior cingulate cortex network biomarkers occur first, followed by aberrant cerebrospinal fluid amyloid-β and p-tau levels, then cognitive deficit, and finally regional gray matter loss and fusiform network abnormality. The CARE index significantly correlates with disease severity and exhibits high reliability. Our findings demonstrate that use of the CARE index would advance AD stage measurement across the whole AD continuum and facilitate personalized treatment of AD.

Stratification by Genetic and Demographic Characteristics Improves Diagnostic Accuracy of Cerebrospinal Fluid Biomarkers in Rapidly Progressive Dementia. - Karch, André; Llorens, Franc; Schmitz, Matthias; Arora, Amandeep Singh; Zafar, Saima; Lange, Peter; Schmidt, Christian; Zerr, Inga (J Alzheimers Dis, 2016)
BACKGROUND: Cerebrospinal fluid (CSF) biomarkers are routinely used for the differential diagnosis of rapidly progressive dementia, but are also affected by patients' characteristics. OBJECTIVE: To assess if stratification by age, sex, and genetic risk factors improves the accuracy of cerebrospinal fluid (CSF) biomarkers in patients with rapidly progressive dementia. METHODS: 1,538 individuals with sporadic Creutzfeldt-Jakob disease (CJD), 173 with classic Alzheimer's disease (cAD), 37 with rapidly progressive Alzheimer's disease (rpAD), and 589 without signs of dementia were included in this retrospective diagnostic study. The effect of age, sex, PRNP codon 129, and APOE genotype on CSF levels of tau, p-tau, Aβ1-42, and Aβ1-40 values measured at time of diagnostic work-up was assessed. RESULTS: Tau was a better marker for the differentiation of CJD and rpAD in older (AUC:0.97; 95% CI:0.96-1.00) than in younger (AUC:0.91; 95% CI:0.87-0.94) patients as tau levels increased with age in CJD patients, but not in rpAD patients. PRNP codon 129 and APOE genotype had complex effects on biomarkers in all diseases, making stratification by genotype a powerful tool. In females (AUC:0.78; 95% CI:0.65-0.91) and patients older than 70 (AUC:0.78; 95% CI:0.62-0.93), tau was able to differentiate with moderate accuracy between cAD and rpAD patients. CONCLUSION: Implementation of stratum-specific reference ranges improves the diagnostic accuracy of CSF biomarkers for the differential diagnosis of rapidly progressive dementia. Diagnostic criteria developed for this setting have to take this into account.

Streptozotocin Induces Mild Cognitive Impairment at Appropriate Doses in Mice as Determined by Long-Term Potentiation and the Morris Water Maze. - Li, Dong; Huang, Yan; Cheng, Bin; Su, Jie; Zhou, Wen-Xia; Zhang, Yong-Xiang (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive neurodegenerative disease, and effective therapeutic drugs in the clinic are still lacking. Ideally, AD progression could be stopped at an early stage, such as at the mild cognitive impairment (MCI) stage. MCI refers to the clinical condition between normal aging and dementia. Patients with MCI experience memory loss but do not meet the criteria for the diagnosis of clinically probable AD. However, few MCI animal models have been established. Here, we used in vivo long-term potentiation (LTP) recording and the Morris water maze (MWM) to evaluate the effects of intracerebroventricular injection of streptozotocin (ICV-STZ) in mice. We found a relationship between cognitive behavior and LTP in vivo and determined the appropriate doses of STZ for a putative MCI animal model. Animals that received≥150μg of STZ exhibited cognitive impairment in the MWM test, and few changes in behavior tests were observed in animals receiving less than 150μg of STZ. In vivo LTP recordings revealed that the induction of LTP decreased significantly in STZ-treated animals, even at the lowest dose (25μg/mouse), in a dose-dependent manner. Pathology analysis revealed STZ-induced neuron loss in a dose-dependent manner, both in the cortex and in the hippocampus, as evidenced by a significantly decreased neuronal number in the cohort treated with 75μg of STZ/mouse. Our study indicated that a low dose (25μg/mouse) of STZ impaired neural plasticity; at a higher dose of 75μg/mouse STZ, further LTP deficits were noted along with induced neuronal loss in both the cortex and the hippocampus, which could be considered a possible MCI or pre-MCI animal model; and finally, at 150μg/mouse STZ, dementia was induced, feasibly indicating a state of AD.

Strong Impact of Chronic Cerebral Hypoperfusion on Neurovascular Unit, Cerebrovascular Remodeling, and Neurovascular Trophic Coupling in Alzheimer's Disease Model Mouse. - Shang, Jingwei; Yamashita, Toru; Zhai, Yun; Nakano, Yumiko; Morihara, Ryuta; Fukui, Yusuke; Hishikawa, Nozomi; Ohta, Yasuyuki; Abe, Koji (J Alzheimers Dis, 2016)
Although chronic cerebral hypoperfusion (CCH) may affect Alzheimer's disease (AD) pathogenesis, the mechanism remains elusive. In the present study, we investigated the role of CCH on an AD mouse model in neurovascular unit, cerebrovascular remodeling, and neurovascular trophic coupling. Moreover, examined protective effect of galantamine. Alzheimer's disease transgenic mice (APP23) were subjected to bilateral common carotid arteries stenosis with ameroid constrictors for slowly progressive cerebral hypoperfusion. CCH exacerbated neuronal loss and decrease of α7 subunit of nicotinic acetylcholine receptors (α7-nAChRs) expression in hippocampus and thalamus at 12 months. Meanwhile, CCH greatly induced advanced glycation end products expression, and blood-brain barrier leakage through observing IgG and MMP9 expressions. Furthermore, a significant number of dramatic enlarged cerebral vessels with remodeling, BDNF/TrkB decreased in neurovascular trophic coupling. The present study demonstrated that CCH strongly enhanced primary AD pathology including neurodegeneration, neurovascular unit disruption, cerebrovascular remodeling and neurovascular trophic coupling damage in AD mice, and that galantamine treatment greatly ameliorated such neuropathologic abnormalities.

STX, a Novel Membrane Estrogen Receptor Ligand, Protects Against Amyloid-β Toxicity. - Gray, Nora E; Zweig, Jonathan A; Kawamoto, Colleen; Quinn, Joseph F; Copenhaver, Philip F (J Alzheimers Dis, 2016)
Because STX is a selective ligand for membrane estrogen receptors, it may be able to confer the beneficial effects of estrogen without eliciting the deleterious side effects associated with activation of the nuclear estrogen receptors. This study evaluates the neuroprotective properties of STX in the context of amyloid-β (Aβ) exposure. MC65 and SH-SY5Y neuroblastoma cell lines, as well as primary hippocampal neurons from wild type (WT) and Tg2576 mice, were used to investigate the ability of STX to attenuate cell death, mitochondrial dysfunction, dendritic simplification, and synaptic loss induced by Aβ. STX prevented Aβ-induced cell death in both neuroblastoma cell lines; it also normalized the decrease in ATP and mitochondrial gene expression caused by Aβ in these cells. Notably, STX also increased ATP content and mitochondrial gene expression in control neuroblastoma cells (in the absence of Aβ). Likewise in primary neurons, STX increased ATP levels and mitochondrial gene expression in both genotypes. In addition, STX treatment enhanced dendritic arborization and spine densities in WT neurons and prevented the diminished outgrowth of dendrites caused by Aβ exposure in Tg2576 neurons. These data suggest that STX can act as an effective neuroprotective agent in the context of Aβ toxicity, improving mitochondrial function as well as dendritic growth and synaptic differentiation. In addition, since STX also improved these endpoints in the absence of Aβ, this compound may have broader therapeutic value beyond Alzheimer's disease.
Keywords: Acrylamides; Adenosine Triphosphate; Amyloid beta-Peptides; Animals; Cell Death; Cell Line, Tumor; Drug Evaluation, Preclinical; Estrogen Receptor Modulators; Genes, Mitochondrial; Hippocampus; Humans; Mice, Transgenic; Mitochondria; Neurons; Neuroprotective Agents

Subjective Memory Complaints in APOEɛ4 Carriers are Associated with High Amyloid-β Burden. - Zwan, Marissa D; Villemagne, Victor L; Doré, Vincent; Buckley, Rachel; Bourgeat, Pierrick; Veljanoski, Robyn; Salvado, Olivier; Williams, Rob; Margison, Laura; Rembach, Alan; Macaulay, S Lance; Martins, Ralph; et al. (J Alzheimers Dis, 2016)
BACKGROUND: APOEɛ4 genotype and aging have been identified as risk factors for Alzheimer's disease (AD). In addition, subjective memory complaints (SMC) might be a first clinical expression of the effect of AD pathology on cognitive functioning. OBJECTIVE: To assess whether APOEɛ4 genotype, age, SMC, and episodic memory are risk factors for high amyloid-β (Aβ) burden in cognitively normal elderly. METHODS: 307 cognitively normal participants (72.7 ± 6.8 years, 53% female, 55% SMC) from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study underwent amyloid PET and APOE genotyping. Logistic regression analyses were performed to determine the association of APOEɛ4 genotype, age, SMC, and episodic memory with Aβ pathology. RESULTS: Odds of high Aβ burden were greater at an older age (OR = 3.21; 95% CI = 1.68-6.14), when SMC were present (OR = 1.90; 95% CI = 1.03-3.48), and for APOEɛ4 carriers (OR = 7.49; 95% CI = 3.96-14.15), while episodic memory was not associated with odds of high Aβ burden. Stratified analyses showed that odds of SMC for high Aβ burden were increased in specifically APOEɛ4 carriers (OR = 4.58, 95% CI = 1.83-11.49) and younger participants (OR = 3.73, 95% CI = 1.39-10.01). CONCLUSION: Aging, APOEɛ4 genotype, and SMC were associated with high Aβ burden. SMC were especially indicative of high Aβ burden in younger participants and in APOEɛ4 carriers. These findings suggest that selection based on the presence of SMC, APOEɛ4 genotype and age may help identify healthy elderly participants with high Aβ burden eligible for secondary prevention trials.
Keywords: Aged; Aging; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Benzothiazoles; Brain; Cognition Disorders; Female; Genotyping Techniques; Heterozygote; Humans; Logistic Models; Male; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

Three-Dimensional Eigenbrain for the Detection of Subjects and Brain Regions Related with Alzheimer's Disease. - Zhang, Yudong; Wang, Shuihua; Phillips, Preetha; Yang, Jiquan; Yuan, Ti-Fei (J Alzheimers Dis, 2016)
BACKGROUND: Considering that Alzheimer's disease (AD) is untreatable, early diagnosis of AD from the healthy elderly controls (HC) is pivotal. However, computer-aided diagnosis (CAD) systems were not widely used due to its poor performance. OBJECTIVE: Inspired from the eigenface approach for face recognition problems, we proposed an eigenbrain to detect AD brains. Eigenface is only for 2D image processing and is not suitable for volumetric image processing since faces are usually obtained as 2D images. METHODS: We extended the eigenbrain to 3D. This 3D eigenbrain (3D-EB) inherits the fundamental strategies in either eigenface or 2D eigenbrain (2D-EB). All the 3D brains were transferred to a feature space, which encoded the variation among known 3D brain images. The feature space was named as the 3D-EB, and defined as eigenvectors on the set of 3D brains. We compared four different classifiers: feed-forward neural network, support vector machine (SVM) with linear kernel, polynomial (Pol) kernel, and radial basis function kernel. RESULTS: The 50x10-fold stratified cross validation experiments showed that the proposed 3D-EB is better than the 2D-EB. SVM with Pol kernel performed the best among all classifiers. Our "3D-EB + Pol-SVM" achieved an accuracy of 92.81% ± 1.99% , a sensitivity of 92.07% ± 2.48% , a specificity of 93.02% ± 2.22% , and a precision of 79.03% ± 2.37% . Based on the most important 3D-EB U1, we detected 34 brain regions related with AD. The results corresponded to recent literature. CONCLUSIONS: We validated the effectiveness of the proposed 3D-EB by detecting subjects and brain regions related to AD.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Brain; Datasets as Topic; Early Diagnosis; Female; Humans; Image Interpretation, Computer-Assisted; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Sensitivity and Specificity; Young Adult

Topographical Information-Based High-Order Functional Connectivity and Its Application in Abnormality Detection for Mild Cognitive Impairment. - Zhang, Han; Chen, Xiaobo; Shi, Feng; Li, Gang; Kim, Minjeong; Giannakopoulos, Panteleimon; Haller, Sven; Shen, Dinggang (J Alzheimers Dis, 2016)
Temporal synchronization-based functional connectivity (FC) has long been used by the neuroscience community. However, topographical FC information may provide additional information to characterize the advanced relationship between two brain regions. Accordingly, we proposed a novel method, namely high-order functional connectivity (HOFC), to capture this second-level relationship using inter-regional resemblance of the FC topographical profiles. Specifically, HOFC first calculates an FC profile for each brain region, notably between the given brain region and other brain regions. Based on these FC profiles, a second layer of correlations is computed between all pairs of brain regions (i.e., correlation's correlation). On this basis, we generated an HOFC network, where "high-order" network properties were computed. We found that HOFC was discordant with the traditional FC in several links, indicating additional information being revealed by the new metrics. We applied HOFC to identify biomarkers for early detection of Alzheimer's disease by comparing 77 mild cognitive impairment patients with 89 healthy individuals (control group). Sensitivity in detection of group difference was consistently improved by ∼25% using HOFC compared to using FC. An HOFC network analysis also provided complementary information to an FC network analysis. For example, HOFC between olfactory and orbitofrontal cortices was found significantly reduced in patients, besides extensive alterations in HOFC network properties. In conclusion, our results showed promise in using HOFC to comprehensively map the human brain connectome.

Transcriptional Analysis of Blood Lymphocytes and Skin Fibroblasts, Keratinocytes, and Endothelial Cells as a Potential Biomarker for Alzheimer's Disease. - Mukhamedyarov, Marat A; Rizvanov, Albert A; Yakupov, Eduard Z; Zefirov, Andrey L; Kiyasov, Andrey P; Reis, Helton J; Teixeira, Antônio L; Vieira, Luciene B; Lima, Luciana M; Salafutdinov, Ilnur I; Petukhova, Elena O; Khaiboullina, Svetlana F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a devastating and progressive form of dementia that is typically associated with a build-up of amyloid-β plaques and hyperphosphorylated and misfolded tau protein in the brain. Presently, there is no single test that confirms AD; therefore, a definitive diagnosis is only made after a comprehensive medical evaluation, which includes medical history, cognitive tests, and a neurological examination and/or brain imaging. Additionally, the protracted prodromal phase of the disease makes selection of control subjects for clinical trials challenging. In this study we have utilized a gene-expression array to screen blood and skin punch biopsy (fibroblasts, keratinocytes, and endothelial cells) for transcriptional differences that may lead to a greater understanding of AD as well as identify potential biomarkers. Our analysis identified 129 differentially expressed genes from blood of dementia cases when compared to healthy individuals, and four differentially expressed punch biopsy genes between AD subjects and controls. Additionally, we identified a set of genes in both tissue compartments that showed transcriptional variation in AD but were largely stable in controls. The translational products of these variable genes are involved in the maintenance of the Golgi structure, regulation of lipid metabolism, DNA repair, and chromatin remodeling. Our analysis potentially identifies specific genes in both tissue compartments that may ultimately lead to useful biomarkers and may provide new insight into the pathophysiology of AD.

The Utilization of Retinal Nerve Fiber Layer Thickness to Predict Cognitive Deterioration. - Shi, Zhongyong; Zhu, Yingbo; Wang, Meijuan; Wu, Yujie; Cao, Jing; Li, Chunbo; Xie, Zhongcong; Shen, Yuan (J Alzheimers Dis, 2016)
Our previous studies have shown that longitudinal reduction in retinal nerve fiber layer (RNFL) thickness is associated with cognitive deterioration. However, whether the combination of longitudinal reduction in RNFL thickness with baseline episodic memory performance can better predict cognitive deterioration remains unknown. Therefore, we set out to re-analyze the data obtained from our previous studies with 78 elderly adults (mean age 74.4 ± 3.83 years, 48.7% male) in the community over a 25-month period. The participants were categorized as either stable participants whose cognitive status did not change (n = 60) or converted participants whose cognitive status deteriorated (n = 18). A logistic regression analysis was applied to determine a conversion score for predicting the cognitive deterioration in the participants. We found that the area under the receiver operating characteristic curve (AUC) for the multivariable model was 0.854 (95% CI 0.762-0.947) using baseline story recall as a predictor, but the AUC increased to 0.915 (95% CI 0.849-0.981) with the addition of the longitudinal reduction of RNFL thickness in the inferior quadrant. The conversion score was significantly higher for the converted participants than the stable participants (0.59 ± 0.30 versus 0.12 ± 0.19, p <  0.001). Finally, the optimal cutoff value of the conversion score (0.134) was determined by the analysis of receiver operating characteristic curve, and this conversion score generated a sensitivity of 0.944 and a specificity of 0.767 in predicting the cognitive deterioration. These findings have established a system to perform a larger scale study to further test whether the longitudinal reduction in RNFL thickness could serve as a biomarker of Alzheimer's disease.
Keywords: Aged; Cognition Disorders; Female; Humans; Logistic Models; Longitudinal Studies; Male; Nerve Fibers; Neuropsychological Tests; Predictive Value of Tests; Retina; ROC Curve; Statistics, Nonparametric; Tomography, Optical Coherence

The Vanderbilt Memory & Aging Project: Study Design and Baseline Cohort Overview. - Jefferson, Angela L; Gifford, Katherine A; Acosta, Lealani Mae Y; Bell, Susan P; Donahue, Manus J; Davis, L Taylor; Gottlieb, JoAnn; Gupta, Deepak K; Hohman, Timothy J; Lane, Elizabeth M; Libon, David J; Mendes, Lisa A; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vascular health factors frequently co-occur with Alzheimer's disease (AD). A better understanding of how systemic vascular and cerebrovascular health intersects with clinical and pathological AD may inform prevention and treatment opportunities. OBJECTIVE: To establish the Vanderbilt Memory & Aging Project, a case-control longitudinal study investigating vascular health and brain aging, and describe baseline methodology and participant characteristics. METHODS: From September 2012 to November 2014, 335 participants age 60- 92 were enrolled, including 168 individuals with mild cognitive impairment (MCI, 73±8 years, 41% female) and 167 age-, sex-, and race-matched cognitively normal controls (NC, 72±7 years, 41% female). At baseline, participants completed a physical and frailty examination, fasting blood draw, neuropsychological assessment, echocardiogram, cardiac MRI, and brain MRI. A subset underwent 24-hour ambulatory blood pressure monitoring and lumbar puncture for cerebrospinal fluid (CSF) collection. RESULTS: As designed, participant groups were comparable for age (p = 0.31), sex (p = 0.95), and race (p = 0.65). MCI participants had greater Framingham Stroke Risk Profile scores (p = 0.008), systolic blood pressure values (p = 0.008), and history of left ventricular hypertrophy (p = 0.04) than NC participants. As expected, MCI participants performed worse on all neuropsychological measures (p-values < 0.001), were more likely to be APOEɛ4 carriers (p = 0.02), and had enhanced CSF biomarkers, including lower Aβ42 (p = 0.02), higher total tau (p = 0.004), and higher p-tau (p = 0.02) compared to NC participants. CONCLUSION: Diverse sources of baseline and longitudinal data will provide rich opportunities to investigate pathways linking vascular and cerebrovascular health, clinical and pathological AD, and neurodegeneration contributing to novel strategies to delay or prevent cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Pressure Monitoring, Ambulatory; Brain; Case-Control Studies; Cerebral Angiography; Cognitive Dysfunction; Echocardiography; Epidemiologic Research Design; Female; Follow-Up Studies; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Research Design

Amyloid-β and Tau Dynamics in Human Brain Interstitial Fluid in Patients with Suspected Normal Pressure Hydrocephalus. - Herukka, Sanna-Kaisa; Rummukainen, Jaana; Ihalainen, Jouni; von Und Zu Fraunberg, Mikael; Koivisto, Anne M; Nerg, Ossi; Puli, Lakshman K; Seppälä, Toni T; Zetterberg, Henrik; Pyykkö, Okko T; Helisalmi, Seppo; Tanila, Heikki; et al. (J Alzheimers Dis, 2015)
Background: Amyloid-β (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau181) in the cerebrospinal fluid (CSF) are the most promising biomarkers of Alzheimer's disease (AD). Still, little is known about the dynamics of these molecules in the living brain. In a transgenic mouse brain, soluble Aβ decreases with increasing age and advanced Aβ pathology as seen similarly in CSF. Objective: To assess the relationship between AD-related pathological changes in human brain tissue, ventricular and lumbar CSF, and brain interstitial fluid (ISF). Methods: Altogether 11 patients with suspected idiopathic normal pressure hydrocephalus underwent frontal cortical brain biopsy, 24-h intraventricular pressure monitoring, and a microdialysis procedure. AD-related biomarkers were analyzed from brain tissue, CSF, and ISF. Results: ISF T-tau levels decreased strongly within the first 12 h, then plateauing until the end of the experiment. Aβ1-42 and P-tau181 remained stable during the experiment (n = 3). T-tau and P-tau were higher in the ISF than in ventricular or lumbar CSF, while Aβ1-42 levels were within similar range in both CSF and ISF samples. ISF P-tau correlated with the ventricular CSF T-tau (r = 0.70, p = 0.017) and P-tau181 (r = 0.64, p = 0.034). Five patients with amyloid pathology in the brain biopsy tended to reveal lower ISF Aβ1-42 levels than those six without amyloid pathology. Conclusions: This is the first study to report ISF Aβ and tau levels in the human brain without significant brain injury. The set-up used enables sampling from the brain ISF for at least 24 h without causing adverse effects due to the microdialysis procedure to follow the dynamics of the key molecules in AD pathogenesis in the living brain at various stages of the disease.

Blood Protein Markers of Neocortical Amyloid-β Burden: A Candidate Study Using SOMAscan Technology. - Voyle, Nicola; Baker, David; Burnham, Samantha C; Covin, Antonia; Zhang, Zhanpan; Sangurdekar, Dipen P; Tan Hehir, Cristina A; Bazenet, Chantal; Lovestone, Simon; Kiddle, Steven; Dobson, Richard J B (J Alzheimers Dis, 2015)
BACKGROUND: Four previously reported studies have tested for association of blood proteins with neocortical amyloid-β burden (NAB). If shown to be robust, these proteins could have utility as a blood test for enrichment in clinical trials of Alzheimer's disease (AD) therapeutics. OBJECTIVE: This study aimed to investigate whether previously identified blood proteins also show evidence for association with NAB in serum samples from the Australian Imaging, Biomarker and Lifestyle Flagship Study of Ageing (AIBL). The study considers candidate proteins seen in cohorts other than AIBL and candidates previously discovered in the AIBL cohort. METHODS: Our study used the SOMAscan platform for protein quantification in blood serum. Linear and logistic regressions were used to model continuous NAB and dichotomized NAB respectively using single proteins as a predictor. Multiple protein models were built using stepwise regression techniques and support vectors machines. Age and APOE ε4 carriage were used as covariates for all analysis. RESULTS: Of the 41 proteins previously reported, 15 AIBL candidates and 20 non-AIBL candidates were available for testing. Of these candidates, pancreatic polypeptide (PPY) and IgM showed a significant association with NAB. Notably, IgM was found to associate with continuous NAB across cognitively normal control subjects. CONCLUSIONS: We have further demonstrated the association of PPY and IgM with NAB, despite technical differences between studies. There are several reasons for a lack of significance for the other candidates including platform differences and the use of serum rather than plasma samples. To investigate the possibility of technical differences causing lack of further replication, further studies are required.

Depression and Suicidal Ideation During Two Psychosocial Treatments in Older Adults with Major Depression and Dementia. - Kiosses, Dimitris N; Rosenberg, Paul B; McGovern, Amanda; Fonzetti, Pasquale; Zaydens, Hana; Alexopoulos, George S (J Alzheimers Dis, 2015)
BACKGROUND: Depression is prevalent in dementia and contributes to poor outcomes for patients and their families. Antidepressants have limited efficacy in older adults with major depression and dementia, and psychosocial interventions are under-investigated. OBJECTIVE: To examine the course, predictors and moderators of depression and suicidal ideation during 12 weeks of home-delivered Problem Adaptation Therapy (PATH) versus Supportive Therapy for Cognitively Impaired Older Adults (ST-CI) in 39 older adults with major depression and dementia. METHODS: Thirty-nine older adults with major depression, mild or moderate dementia, and disability participated in a randomized controlled trial that compared the efficacy of PATH versus ST-CI. Depression and suicidal ideation were assessed with Cornell Scale for Depression in Dementia Total Score and Suicide Item. RESULTS: PATH participants had significantly greater reduction in depression than ST-CI participants over 12 weeks of treatment. PATH participants with high social support had the greatest reduction in depression. Both treatments had comparable reduction in suicidal ideation. CONCLUSION: PATH is more effective in reducing depression in older adults with major depression and dementia compared to ST-CI. These results are clinically significant as antidepressants have limited efficacy in this population. Home-delivered psychosocial treatments may reduce suicidal ideation in this population.

Diabetes is Associated with Worse Executive Function in Both Eastern and Western Populations: Shanghai Aging Study and Mayo Clinic Study of Aging. - Zhao, Qianhua; Roberts, Rosebud O; Ding, Ding; Cha, Ruth; Guo, Qihao; Meng, Haijiao; Luo, Jianfeng; Machulda, Mary M; Shane Pankratz, V; Wang, Bei; Christianson, Teresa J H; Aakre, Jeremiah A; et al. (J Alzheimers Dis, 2015)
BACKGROUND AND OBJECTIVES: It remains unknown whether the association between diabetes mellitus (DM) and cognitive function differs in Eastern and Western populations. This study aimed to elucidate whether DM is associated with worse cognitive performance in both populations. METHODS: The Shanghai Aging Study (SAS) and the Mayo Clinic Study of Aging (MCSA) are two population-based studies with similar design and methodology in Shanghai, China and Rochester, MN, USA. Non-demented participants underwent cognitive testing, and DM was assessed from the medical record. Separate analyses were performed in SAS and MCSA regarding the association between DM and cognitive performance. RESULTS: A total of 3,348 Chinese participants in the SAS and 3,734 American subjects in the MCSA were included. Compared with MCSA subjects, SAS participants were younger, less educated, and had lower frequency of vascular disease, APOE ɛ4 carriers and obesity. Participants with DM (compared to non-DM participants) performed significantly worse on all the cognitive domains in both the SAS and MCSA. After adjustment for age, gender, education, and vascular covariates, DM was associated with worse performance in executive function (β=-0.15, p = 0.001 for SAS, and β=-0.10, p = 0.008 for MCSA) in the total sample and in the cognitively normal sub-sample. Furthermore, DM was associated with poor performance in visuospatial skills, language, and memory in the SAS, but not in the MCSA. CONCLUSIONS: Diabetes is associated with cognitive dysfunction and, in particular, exerts a negative impact on executive function regardless of race, age, and prevalence of vascular risk factors.

Human ApoE Isoforms Differentially Modulate Glucose and Amyloid Metabolic Pathways in Female Brain: Evidence of the Mechanism of Neuroprotection by ApoE2 and Implications for Alzheimer's Disease Prevention and Early Intervention. - Keeney, Jeriel Thomas-Richard; Ibrahimi, Shaher; Zhao, Liqin (J Alzheimers Dis, 2015)
Three major genetic isoforms of apolipoprotein E (ApoE), ApoE2, ApoE3, and ApoE4, exist in humans and lead to differences in susceptibility to Alzheimer's disease (AD). This study investigated the impact of human ApoE isoforms on brain metabolic pathways involved in glucose utilization and amyloid-β (Aβ) degradation, two major areas that are significantly perturbed in preclinical AD. Hippocampal RNA samples from middle-aged female mice with targeted human ApoE2, ApoE3, and ApoE4 gene replacement were comparatively analyzed with a qRT-PCR custom array for the expression of 85 genes involved in insulin/insulin-like growth factor (Igf) signaling. Consistent with its protective role against AD, ApoE2 brain exhibited the most metabolically robust profile among the three ApoE genotypes. When compared to ApoE2 brain, both ApoE3 and ApoE4 brains exhibited markedly reduced levels of Igf1, insulin receptor substrates (Irs), and facilitated glucose transporter 4 (Glut4), indicating reduced glucose uptake. Additionally, ApoE4 brain exhibited significantly decreased Pparg and insulin-degrading enzyme (Ide), indicating further compromised glucose metabolism and Aβ dysregulation associated with ApoE4. Protein analysis showed significantly decreased Igf1, Irs, and Glut4 in ApoE3 brain, and Igf1, Irs, Glut4, Pparg, and Ide in ApoE4 brain compared to ApoE2 brain. These data provide the first documented evidence that human ApoE isoforms differentially affect brain insulin/Igf signaling and downstream glucose and amyloid metabolic pathways, illustrating a potential mechanism for their differential risk in AD. A therapeutic strategy that enhances brain insulin/Igf1 signaling activity to a more robust ApoE2-like phenotype favoring both energy production and amyloid homeostasis holds promise for AD prevention and early intervention.

Identification of Novel Tau Interactions with Endoplasmic Reticulum Proteins in Alzheimer's Disease Brain. - Meier, Shelby; Bell, Michelle; Lyons, Danielle N; Ingram, Alexandria; Chen, Jing; Gensel, John C; Zhu, Haining; Nelson, Peter T; Abisambra, Jose F (J Alzheimers Dis, 2015)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is pathologically characterized by the formation of extracellular amyloid plaques and intraneuronal tau tangles. We recently identified that tau associates with proteins known to participate in endoplasmic reticulum (ER)-associated degradation (ERAD); consequently, ERAD becomes dysfunctional and causes neurotoxicity. We hypothesized that tau associates with other ER proteins, and that this association could also lead to cellular dysfunction in AD. Portions of human AD and non-demented age matched control brains were fractionated to obtain microsomes, from which tau was co-immunoprecipitated. Samples from both conditions containing tau and its associated proteins were analyzed by mass spectrometry. In total, we identified 91 ER proteins that co-immunoprecipitated with tau; 15.4% were common between AD and control brains, and 42.9% only in the AD samples. The remainder, 41.8% of the proteins, was only seen in the control brain samples. We identified a variety of previously unreported interactions between tau and ER proteins. These proteins participate in over sixteen functional categories, the most abundant being involved in RNA translation. We then determined that association of tau with these ER proteins was different between the AD and control samples. We found that tau associated equally with the ribosomal protein L28 but more robustly with the ribosomal protein P0. These data suggest that the differential association between tau and ER proteins in disease could reveal the pathogenic processes by which tau induces cellular dysfunction.

Reduced Benefit of Memory Elaboration in Older Adults with Subjective Memory Decline. - Pike, Kerryn E; Zeneli, Amina; Ong, Ben; Price, Sarah; Kinsella, Glynda J (J Alzheimers Dis, 2015)
BACKGROUND: Cognitive interventions for neurodegenerative diseases, such as Alzheimer's disease (AD), are best targeted at the preclinical stages, and subjective memory decline (SMD) without objective memory impairment on standard tests in older adults may represent a very early preclinical stage. Elaborated encoding effectively enhances memory performance for healthy older adults (HOAs), but has not been examined in people with SMD. OBJECTIVE: To examine elaborated encoding in people with SMD, compared with HOAs. METHODS: Participants were 32 HOAs and 22 people with SMD, defined using the Memory Complaint Questionnaire. Participants completed a verbal paired associate learning (PAL) task with delayed recall under elaborated and non-elaborated encoding conditions, as well as the California Verbal Learning Test-II. RESULTS: On the PAL learning trials, with age controlled, a significant interaction of group X encoding condition emerged, F(1, 51) =  6.47, MSE = 6.54, p = 0.014, ηp2 = 0.11. Simple main effects revealed no differences between groups in the non-elaborated condition, but in the elaborated condition HOAs recalled more pairs than SMD, although both groups benefited from elaboration. At delayed recall, HOA recalled more pairs than SMD, F(1, 51) =  4.59, p = 0.037, ηp2 = 0.08, and both groups benefited from elaboration, F(1, 52) =  19.25, p <  0.001, ηp2 = 0.27. CONCLUSION: People with SMD benefit from elaborated encoding, although not to the same extent as HOAs. This objective difference in complex learning and memory suggests neural changes in SMD that may represent preclinical AD. Elaborated encoding is a promising technique to help maintain memory and decrease anxiety in this at-risk population.

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

REST and stress resistance in ageing and Alzheimer's disease. - Lu, Tao; Aron, Liviu; Zullo, Joseph; Pan, Ying; Kim, Haeyoung; Chen, Yiwen; Yang, Tun-Hsiang; Kim, Hyun-Min; Drake, Derek; Liu, X Shirley; Bennett, David A; Colaiácovo, Monica P; et al. (Nature, 2014)
Human neurons are functional over an entire lifetime, yet the mechanisms that preserve function and protect against neurodegeneration during ageing are unknown. Here we show that induction of the repressor element 1-silencing transcription factor (REST; also known as neuron-restrictive silencer factor, NRSF) is a universal feature of normal ageing in human cortical and hippocampal neurons. REST is lost, however, in mild cognitive impairment and Alzheimer's disease. Chromatin immunoprecipitation with deep sequencing and expression analysis show that REST represses genes that promote cell death and Alzheimer's disease pathology, and induces the expression of stress response genes. Moreover, REST potently protects neurons from oxidative stress and amyloid β-protein toxicity, and conditional deletion of REST in the mouse brain leads to age-related neurodegeneration. A functional orthologue of REST, Caenorhabditis elegans SPR-4, also protects against oxidative stress and amyloid β-protein toxicity. During normal ageing, REST is induced in part by cell non-autonomous Wnt signalling. However, in Alzheimer's disease, frontotemporal dementia and dementia with Lewy bodies, REST is lost from the nucleus and appears in autophagosomes together with pathological misfolded proteins. Finally, REST levels during ageing are closely correlated with cognitive preservation and longevity. Thus, the activation state of REST may distinguish neuroprotection from neurodegeneration in the ageing brain.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Autophagy; Brain; Caenorhabditis elegans Proteins; Cell Death; Cell Nucleus; Chromatin Immunoprecipitation; Cognition; DNA-Binding Proteins; Down-Regulation; Frontotemporal Dementia; Gene Expression Regulation; Humans; Lewy Body Disease; Longevity; Mice; Mild Cognitive Impairment; Neurons; Neuroprotective Agents; Oxidative Stress; Phagosomes; Repressor Proteins; Transcription Factors; Up-Regulation; Wnt Signaling Pathway; Young Adult

A three-dimensional human neural cell culture model of Alzheimer's disease. - Choi, Se Hoon; Kim, Young Hye; Hebisch, Matthias; Sliwinski, Christopher; Lee, Seungkyu; D'Avanzo, Carla; Chen, Hechao; Hooli, Basavaraj; Asselin, Caroline; Muffat, Julien; Klee, Justin B; Zhang, Can; et al. (Nature, 2014)
Alzheimer's disease is the most common form of dementia, characterized by two pathological hallmarks: amyloid-β plaques and neurofibrillary tangles. The amyloid hypothesis of Alzheimer's disease posits that the excessive accumulation of amyloid-β peptide leads to neurofibrillary tangles composed of aggregated hyperphosphorylated tau. However, to date, no single disease model has serially linked these two pathological events using human neuronal cells. Mouse models with familial Alzheimer's disease (FAD) mutations exhibit amyloid-β-induced synaptic and memory deficits but they do not fully recapitulate other key pathological events of Alzheimer's disease, including distinct neurofibrillary tangle pathology. Human neurons derived from Alzheimer's disease patients have shown elevated levels of toxic amyloid-β species and phosphorylated tau but did not demonstrate amyloid-β plaques or neurofibrillary tangles. Here we report that FAD mutations in β-amyloid precursor protein and presenilin 1 are able to induce robust extracellular deposition of amyloid-β, including amyloid-β plaques, in a human neural stem-cell-derived three-dimensional (3D) culture system. More importantly, the 3D-differentiated neuronal cells expressing FAD mutations exhibited high levels of detergent-resistant, silver-positive aggregates of phosphorylated tau in the soma and neurites, as well as filamentous tau, as detected by immunoelectron microscopy. Inhibition of amyloid-β generation with β- or γ-secretase inhibitors not only decreased amyloid-β pathology, but also attenuated tauopathy. We also found that glycogen synthase kinase 3 (GSK3) regulated amyloid-β-mediated tau phosphorylation. We have successfully recapitulated amyloid-β and tau pathology in a single 3D human neural cell culture system. Our unique strategy for recapitulating Alzheimer's disease pathology in a 3D neural cell culture model should also serve to facilitate the development of more precise human neural cell models of other neurodegenerative disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Culture Techniques; Cell Differentiation; Drug Evaluation, Preclinical; Extracellular Space; Glycogen Synthase Kinase 3; Humans; Microtubule-Associated Proteins; Models, Biological; Neural Stem Cells; Neurites; Phosphorylation; Presenilin-1; Protein Aggregation, Pathological; Reproducibility of Results; tau Proteins

Young blood reverses age-related impairments in cognitive function and synaptic plasticity in mice. - Villeda, Saul A; Plambeck, Kristopher E; Middeldorp, Jinte; Castellano, Joseph M; Mosher, Kira I; Luo, Jian; Smith, Lucas K; Bieri, Gregor; Lin, Karin; Berdnik, Daniela; Wabl, Rafael; Udeochu, Joe; et al. (Nat Med, 2014)
As human lifespan increases, a greater fraction of the population is suffering from age-related cognitive impairments, making it important to elucidate a means to combat the effects of aging. Here we report that exposure of an aged animal to young blood can counteract and reverse pre-existing effects of brain aging at the molecular, structural, functional and cognitive level. Genome-wide microarray analysis of heterochronic parabionts--in which circulatory systems of young and aged animals are connected--identified synaptic plasticity-related transcriptional changes in the hippocampus of aged mice. Dendritic spine density of mature neurons increased and synaptic plasticity improved in the hippocampus of aged heterochronic parabionts. At the cognitive level, systemic administration of young blood plasma into aged mice improved age-related cognitive impairments in both contextual fear conditioning and spatial learning and memory. Structural and cognitive enhancements elicited by exposure to young blood are mediated, in part, by activation of the cyclic AMP response element binding protein (Creb) in the aged hippocampus. Our data indicate that exposure of aged mice to young blood late in life is capable of rejuvenating synaptic plasticity and improving cognitive function.
Keywords: Age Factors; Aging; Animals; Blood Transfusion; Blotting, Western; Cell Line; Cognition Disorders; Cyclic AMP Response Element-Binding Protein; DNA Primers; Hippocampus; Immunohistochemistry; Mice; Mice, Inbred C57BL; Microarray Analysis; Neuronal Plasticity; Parabiosis; Polymerase Chain Reaction

Integrated systems approach identifies genetic nodes and networks in late-onset Alzheimer's disease. - Zhang, Bin; Gaiteri, Chris; Bodea, Liviu-Gabriel; Wang, Zhi; McElwee, Joshua; Podtelezhnikov, Alexei A; Zhang, Chunsheng; Xie, Tao; Tran, Linh; Dobrin, Radu; Fluder, Eugene; Clurman, Bruce; et al. (Cell, 2013)
The genetics of complex disease produce alterations in the molecular interactions of cellular pathways whose collective effect may become clear through the organized structure of molecular networks. To characterize molecular systems associated with late-onset Alzheimer's disease (LOAD), we constructed gene-regulatory networks in 1,647 postmortem brain tissues from LOAD patients and nondemented subjects, and we demonstrate that LOAD reconfigures specific portions of the molecular interaction structure. Through an integrative network-based approach, we rank-ordered these network structures for relevance to LOAD pathology, highlighting an immune- and microglia-specific module that is dominated by genes involved in pathogen phagocytosis, contains TYROBP as a key regulator, and is upregulated in LOAD. Mouse microglia cells overexpressing intact or truncated TYROBP revealed expression changes that significantly overlapped the human brain TYROBP network. Thus the causal network structure is a useful predictor of response to gene perturbations and presents a framework to test models of disease mechanisms underlying LOAD.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Animals; Bayes Theorem; Brain; Gene Regulatory Networks; Humans; Membrane Proteins; Mice; Microglia

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Cerebrospinal fluid levels of β-amyloid 1-42, but not of tau, are fully changed already 5 to 10 years before the onset of Alzheimer dementia. - Buchhave, Peder; Minthon, Lennart; Zetterberg, Henrik; Wallin, Asa K; Blennow, Kaj; Hansson, Oskar (Arch Gen Psychiatry, 2012)
CONTEXT: Early detection of prodromal Alzheimer disease (AD) is important because new disease-modifying therapies are most likely to be effective when initiated during the early stages of disease. OBJECTIVES: To assess the ability of the cerebrospinal fluid (CSF) biomarkers total tau (T-tau), phosphorylated tau (P-tau), and β-amyloid 1-42 (Aβ42) to predict future development of AD dementia within 9.2 years in patients with mild cognitive impairment (MCI) and to compare CSF biomarkers between early and late converters to AD. DESIGN: A clinical study with a median follow-up of 9.2 years (range, 4.1-11.8 years). SETTING: Memory disorder clinic. Patients A total of 137 patients with MCI who underwent lumbar puncture at baseline. MAIN OUTCOME MEASURE Conversion to AD dementia. RESULTS: During follow-up, 72 patients (53.7%) developed AD and 21 (15.7%) progressed to other forms of dementia. At baseline, CSF Aβ42 levels were reduced and T-tau and P-tau levels were elevated in patients who converted to AD during follow-up compared with nonconverters (P < .001). Baseline CSF Aβ42 levels were equally reduced in patients with MCI who converted to AD within 0 to 5 years (early converters) compared with those who converted between 5 and 10 years (late converters). However, CSF T-tau and P-tau levels were significantly higher in early converters vs late converters. A baseline Aβ42:P-tau ratio predicted the development of AD within 9.2 years with a sensitivity of 88%, specificity of 90%, positive predictive value of 91%, and negative predictive value of 86%. CONCLUSIONS: Approximately 90% of patients with MCI and pathologic CSF biomarker levels at baseline develop AD within 9 to 10 years. Levels of Aβ42 are already fully decreased at least 5 to 10 years before conversion to AD dementia, whereas T-tau and P-tau seem to be later markers. These results provide direct support in humans for the hypothesis that altered Aβ metabolism precedes tau-related pathology and neuronal degeneration.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Follow-Up Studies; Humans; Male; Mild Cognitive Impairment; Peptide Fragments; Predictive Value of Tests; tau Proteins; Time Factors

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

Predicting regional neurodegeneration from the healthy brain functional connectome. - Zhou, Juan; Gennatas, Efstathios D; Kramer, Joel H; Miller, Bruce L; Seeley, William W (Neuron, 2012)
Neurodegenerative diseases target large-scale neural networks. Four competing mechanistic hypotheses have been proposed to explain network-based disease patterning: nodal stress, transneuronal spread, trophic failure, and shared vulnerability. Here, we used task-free fMRI to derive the healthy intrinsic connectivity patterns seeded by brain regions vulnerable to any of five distinct neurodegenerative diseases. These data enabled us to investigate how intrinsic connectivity in health predicts region-by-region vulnerability to disease. For each illness, specific regions emerged as critical network "epicenters" whose normal connectivity profiles most resembled the disease-associated atrophy pattern. Graph theoretical analyses in healthy subjects revealed that regions with higher total connectional flow and, more consistently, shorter functional paths to the epicenters, showed greater disease-related vulnerability. These findings best fit a transneuronal spread model of network-based vulnerability. Molecular pathological approaches may help clarify what makes each epicenter vulnerable to its targeting disease and how toxic protein species travel between networked brain structures.
Keywords: Aged; Atrophy; Brain; Brain Mapping; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Net; Neural Pathways; Neurodegenerative Diseases; Oxygen; Reference Values

Vascular risk factors promote conversion from mild cognitive impairment to Alzheimer disease. - Li, J; Wang, Y J; Zhang, M; Xu, Z Q; Gao, C Y; Fang, C Q; Yan, J C; Zhou, H D (Neurology, 2011)
OBJECTIVE: Growing evidence suggests that vascular risk factors (VRF) contribute to cognitive decline. The aim of this study was to investigate the impact of VRF on the conversion from mild cognitive impairment (MCI) to Alzheimer disease (AD) dementia. METHODS: A total of 837 subjects with MCI were enrolled at baseline and followed up annually for 5 years. The incidence of AD dementia was investigated. A mixed random effects regression model was used to analyze the association between VRF and the progression of MCI assessed with Mini-Mental State Examination and instrumental Activities of Daily Living. Cox proportional hazard models were used to identify the association between VRF and dementia conversion, and to examine whether treatment of VRF can prevent dementia conversion. RESULTS: At the end of the follow-up, 298 subjects converted to AD dementia, while 352 remained MCI. Subjects with VRF had a faster progression in cognition and function relative to subjects without. VRF including hypertension, diabetes, cerebrovascular diseases, and hypercholesterolemia increased the risk of dementia conversion. Those subjects with MCI in whom all VRF were treated had a lower risk of dementia than those who had some VRF treated. Treatment of individual VRF including hypertension, diabetes, and hypercholesterolemia was associated with the reduced risk of AD conversion. CONCLUSION: VRF increased the risk of incident AD dementia. Treatment of VRF was associated with a reduced risk of incident AD dementia. Although our findings are observational, they suggest active intervention for VRF might reduce progression in MCI to AD dementia.
Keywords: Aged; Alzheimer Disease; Cerebrovascular Disorders; Cognition Disorders; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptides; Regression Analysis; Residence Characteristics; Retrospective Studies; Risk Factors; Statistics, Nonparametric